Iron chelation by oral deferoxamine treatment decreased brain iron and iron signaling proteins. - Thorwald, Max A; Sta Maria, Naomi S; Chakhoyan, Ararat; O'Day, Peggy A; Jacobs, Russell E; Zlokovic, Berislav; Finch, Caleb E (J Alzheimers Dis, 2025)
BACKGROUND: Deferoxamine (DFO) and other iron chelators are clinically used for cancer and stroke. They may also be useful for Alzheimer's disease (AD) to diminish iron from microbleeds. DFO may also stimulate antioxidant membrane repair which is impaired during AD. DFO and other chelators do enter the brain despite some contrary reports. OBJECTIVE: Low dose, oral DFO was given in lab chow to wildtype (WT) C57BL/6 mice to evaluate potential impact on iron levels, iron-signaling and storage proteins, and amyloid-β protein precursor (AβPP) and processing enzymes. Young WT mice do not have microbleeds or disrupted blood-brain barrier of AD mice. METHODS: Iron was measured by MRI and chemically after two weeks of dietary DFO. Cerebral cortex was examined for changes in iron metabolism, antioxidant signaling, and AβPP processing by western blot. RESULTS: DFO decreased brain iron 18% ( < 0.01) estimated by R2 MRI and decreased seven major proteins that mediate iron metabolism by at least 25%. The iron storage proteins ferritin light and heavy chain decreased by at least 30%. AβPP and secretase enzymes also decreased by 30%. CONCLUSIONS: WT mice respond to DFO with decreased AβPP, amyloid processing enzymes, and antioxidant repair. Potential DFO treatment for early-stage AD by DFO should consider the benefits of lowered AβPP and secretase enzymes.

Leptin, adiponectin, body mass index, and incident cognitive impairment. - Thacker, Evan L; Karki, Reena; Gabor, Rachel; Blades, Natalie J; Sawyer, Russell P; Kouambo Beckodro, Cyrille N; Preece, Quinn; Prince, Samuel; Smith, McKay M; Gillett, Sarah R; Judd, Suzanne E; Kennedy, Richard E; et al. (J Alzheimers Dis, 2025)
BackgroundDisordered metabolism affects risk for cognitive decline, Alzheimer's disease, and other dementias, likely through pathways involving adipokines.ObjectiveAnalyze incident cognitive impairment in relation to leptin, adiponectin, body mass index, and other risk factors.MethodsNested case-control study within the Reasons for Geographic and Racial Differences in Stroke (REGARDS) cohort of 30,239 adults in the US. Cases with incident cognitive impairment (n = 489) scored >1.57 SD below demographically adjusted means on ≥2 of 3 cognitive tests: word list learning, word list delayed recall, and category fluency. Cognitively intact controls (n = 583) were randomly selected within demographic strata. Leptin and adiponectin were assayed in thawed blood that had been stored at baseline.ResultsIn participants with normal weight, lower leptin was associated with higher odds of cognitive impairment. Relative to leptin = 25 ng/mL, adjusted ORs were 1.5 (95% CI: 1.2, 1.9) at leptin = 15 ng/mL, 0.8 (0.8, 0.9) at leptin = 30 ng/mL, and 0.5 (0.4, 0.8) at leptin = 45 ng/mL. In participants with obesity, higher adiponectin was associated with higher odds of cognitive impairment. Relative to adiponectin = 25 ng/mL, adjusted ORs were 0.8 (95% CI: 0.7, 1.0) at adiponectin = 15 ng/mL, 1.1 (1.0, 1.2) at adiponectin = 30 ng/mL, and 1.3 (1.0, 1.7) at adiponectin = 45 ng/mL. Associations of adipokines with cognitive impairment varied across levels of other risk factors.ConclusionsAdipokines, in concert with body mass index, play complex roles in cognitive health, with many avenues open for further investigation.

Alzheimer DataLENS: An Open Data Analytics Portal for Alzheimer's Disease Research. - Noori, Ayush; Jayakumar, Rojashree; Moturi, Vaishnavi; Li, Zhaozhi; Liu, Rongxin; Serrano-Pozo, Alberto; Hyman, Bradley T; Das, Sudeshna (J Alzheimers Dis, 2024)
BACKGROUND: Recent Alzheimer's disease (AD) discoveries are increasingly based on studies from a variety of omics technologies on large cohorts. Currently, there is no easily accessible resource for neuroscientists to browse, query, and visualize these complex datasets in a harmonized manner. OBJECTIVE: Create an online portal of public omics datasets for AD research. METHODS: We developed Alzheimer DataLENS, a web-based portal, using the R Shiny platform to query and visualize publicly available transcriptomics and genetics studies of AD on human cohorts. To ensure consistent representation of AD findings, all datasets were processed through a uniform bioinformatics pipeline. RESULTS: Alzheimer DataLENS currently houses 2 single-nucleus RNA sequencing datasets, over 30 bulk RNA sequencing datasets from 19 brain regions and 3 cohorts, and 2 genome-wide association studies (GWAS). Available visualizations for single-nucleus data include bubble plots, heatmaps, and UMAP plots; for bulk expression data include box plots and heatmaps; for pathways include protein-protein interaction network plots; and for GWAS results include Manhattan plots. Alzheimer DataLENS also links to two other knowledge resources: the AD Progression Atlas and the Astrocyte Atlas. CONCLUSIONS: Alzheimer DataLENS is a valuable resource for investigators to quickly and systematically explore omics datasets and is freely accessible at https://alzdatalens.partners.org.
Keywords: Alzheimer Disease; Brain; Computational Biology; Genome-Wide Association Study; Humans; Internet

Association of Plasma Amyloid-β and Dementia Among Black and White Older Adults. - Jiang, Xiaqing; Bahorik, Amber L; Graff-Radford, Neill R; Yaffe, Kristine (J Alzheimers Dis, 2024)
BACKGROUND: Plasma amyloid-β (Aβ) has emerged as an important tool to detect risks of Alzheimer's disease and related dementias, although research in diverse populations is lacking. OBJECTIVE: We compared plasma Aβ 42/40 by race with dementia risk over 15 years among Black and White older adults. METHODS: In a prospective cohort of 997 dementia-free participants (mean age 74±2.9 years, 55% women, 54% Black), incident dementia was identified based on hospital records, medication, and neurocognitive test over 15 years. Plasma Aβ 42/40 was measured at Year 2 and categorized into low, medium, and high tertile. We used linear regression to estimate mean Aβ 42/40 by race and race-stratified Cox proportional hazards models to assess the association between Aβ 42/40 tertile and dementia risk. RESULTS: Black participants had a lower age-adjusted mean Aβ 42/40 compared to White participants, primarily among APOE ɛ4 non-carriers (Black: 0.176, White: 0.185, p = 0.035). Among Black participants, lower Aβ 42/40 was associated with increased dementia risk: 33% in low (hazard ratios [HR] = 1.77, 95% confidence interval 1.09-2.88) and 27% in medium tertile (HR = 1.67, 1.01-2.78) compared with 18% in high Aβ 42/40 tertile; Increased risks were attenuated among White participants: 21% in low (HR = 1.43, 0.81-2.53) and 23% in medium tertile (HR = 1.27, 0.68-2.36) compared with 15% in high Aβ 42/40 tertile. The interaction by race was not statistically significant. CONCLUSIONS: Among community-dwelling, non-demented older adults, especially APOE ɛ4 non-carriers, Black individuals had lower plasma Aβ 42/40 and demonstrated a higher dementia risk with low Aβ 42/40 compared with White individuals.

Association of Vitamin D Levels with Risk of Cognitive Impairment and Dementia: A Systematic Review and Meta-Analysis of Prospective Studies. - Zhang, Xiao-Xue; Wang, He-Ran; Hu, Ya-Zhuo; Sun, Hong-Mei; Feng, Yu-Xin; Jia, Jian-Jun (J Alzheimers Dis, 2024)
BACKGROUND: Emerging evidence suggests the potential relationship between vitamin D deficiency and risk of cognitive impairment or dementia. To what extent the excess risk of dementia conferred by vitamin D deficiency is less clear. OBJECTIVE: We summarized the current evidence from several aspects and further quantified these associations. METHODS: We collected relevant prospective cohort studies by searching PubMed, Embase and Cochrane up to July 2023. The pooled relative risks (RR) were evaluated by random-effects models. Dose-response analyses were conducted by the method of two-stage generalized least squares regression. RESULTS: Of 9,267 identified literatures, 23 were eligible for inclusion in the meta-analyses, among which 9 and 4 literatures were included in the dose-response analyses for the risk of dementia and Alzheimer's disease (AD). Vitamin D deficiency exhibited a 1.42 times risk for dementia (95% confidence interval (CI) = 1.21-1.65) and a 1.57-fold excess risk for AD (95% CI = 1.15-2.14). And vitamin D deficiency was associated with 34% elevated risk with cognitive impairment (95% CI = 1.19-1.52). Additionally, vitamin D was non-linearly related to the risk of dementia (pnonlinearity = 0.0000) and AD (pnonlinearity = 0.0042). The approximate 77.5-100 nmol/L 25-hydroxyvitamin D [25(OH)D] was optimal for reducing dementia risk. And the AD risk seemed to be decreased when the 25(OH)D level >40.1 nmol/L. CONCLUSIONS: Vitamin D deficiency was a risk factor for dementia, AD, and cognitive impairment. The nonlinear relationships may further provide the optimum dose of 25(OH)D for dementia prevention.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Dementia; Humans; Prospective Studies; Risk Factors; Vitamin D; Vitamin D Deficiency

Associations of Physical Activity Engagement with Cerebral Amyloid-β and Tau from Midlife. - Gonzales, Mitzi M; Kojis, Daniel; Spartano, Nicole L; Thibault, Emma G; DeCarli, Charles S; El Fakhri, Georges; Johnson, Keith A; Beiser, Alexa S; Seshadri, Sudha (J Alzheimers Dis, 2024)
BACKGROUND: Higher midlife physical activity engagement has been associated with lower dementia risk in late life. However, the underlying mechanisms contributing to the protective effect remain unclear. OBJECTIVE: The goal of the current study was to evaluate the associations of physical activity with cerebral amyloid-β (Aβ) and tau in a predominately middle-aged community-based cohort, as well as to explore whether the associations differ by sex or age. METHODS: Participants from the Framingham Heart Study underwent 11C-Pittsburgh Compound B amyloid and 18F-Flortaucipir tau positron emission tomography (PET) imaging. Total physical activity levels were evaluated by self-report using the Physical Activity Index (PAI). Cross-sectional associations between total PAI with regional Aβ and tau PET retention were evaluated using linear regression models adjusted for demographic and cardiovascular risk factors. Interactions with sex and age group were examined and stratified analyses were performed when significant. FDR-correction for multiple comparisons was applied. RESULTS: The sample included 354 participants (mean age 53±8 years, 51% female). Higher total PAI scores were associated with lower entorhinal cortex tau PET binding (β (SE) = -0.021(0.008), p = 0.049). There were significant interactions with sex. In men alone, total PAI inversely associated with entorhinal cortex (β (SE) = -0.035(0.009), p = 0.001), inferior temporal (β (SE) = -0.029(0.010), p = 0.012), and rhinal cortex tau(β (SE) = -0.033(0.010), p = 0.002). CONCLUSIONS: The results suggest that higher midlife physical activity engagement may confer resistance to tau pathology. However, the effects may vary based on sex, highlighting the importance of better understanding and tailoring lifestyle interventions to address sex disparities.

Bisecting N-Acetylglucosamine Correlates with Phospho-Tau181 in Subjective Cognitive Decline but not in Control Cases. - Egebäck Arulf, Sofia; Ziyue Zhou, Robin; Kirsebom, Bjørn-Eivind; Jejcic, Alenka; Fladby, Tormod; Winblad, Bengt; Tjernberg, Lars; Schedin-Weiss, Sophia (J Alzheimers Dis, 2024)
BACKGROUND: The N-glycan structure bisecting N-acetylglucosamine (bisecting GlcNAc) is present on several N-glycans that are elevated in Alzheimer's disease (AD), and previous studies have shown that bisecting GlcNAc levels correlate with total tau and phospho-tau181 in cerebrospinal fluid at early stages of AD. A recent population-based study showed that bisecting GlcNAc correlates with total tau also in blood and that this correlation could predict conversion to dementia. OBJECTIVE: In this study, we have further investigated how bisecting GlcNAc relates to total tau and phospho-tau 181 in cerebrospinal fluid samples from controls and cases with early cognitive deficits, stratified by amyloid/tau status and gender. METHODS: Relative levels of bisecting GlcNAc in cerebrospinal fluid were measured by an enzyme-linked lectin assay in individuals with subjective cognitive decline, mild cognitive impairment and controls from the Norwegian Dementia Disease Initiation cohort. RESULTS: As in our previous study, the correlation between bisecting GlcNAc and total tau or phospho-tau181 was particularly strong in the subjective cognitive decline group. The correlation was observed in amyloid negative and tau negative as well as amyloid positive and tau positive individuals, both in females and in males. Interestingly, among the amyloid negative and tau negative individuals, the correlation was observed in individuals with subjective cognitive decline but not in the controls. CONCLUSIONS: Thus, bisecting GlcNAc could be a biomarker for early cognitive decline.

Current Status and Challenges in Dementia Care in the Philippines: A Scoping Review. - Anlacan, Veeda Michelle M; Lanuza, Pamela Danielle T; Sanchez, Anna Anjelica R; Jamora, Roland Dominic G (J Alzheimers Dis, 2024)
BACKGROUND: Dementia prevalence is increasing in low- and middle-income countries such as the Philippines. OBJECTIVE: This study aimed to give an overview of dementia care in the Philippines and to identify gaps in terms of local epidemiology, research, financial coverage, diagnostics, pharmacotherapy, manpower, and caregiver support. METHODS: This scoping review was conducted using the Preferred Reporting Items for Systematic reviews and Meta-analysis guidelines extension for scoping reviews. Six international and two local databases, and government and non-government websites were searched. Data published in the English or Filipino language on dementia epidemiology, research, diagnostics, management, manpower, and training were extracted from the earliest indexed record until June 2022. RESULTS: The prevalence of dementia in the Philippines is high and research output on all aspects of dementia is low. Cost is a major barrier as health care coverage is limited, with reliance mainly on out-of-pocket payments, leading to challenges in the proper diagnosis and treatment of dementia. There is a low specialist-to-population ratio, with shortages beyond manpower and training. CONCLUSIONS: Gaps in dementia care include limited published local data, high healthcare costs, inadequate health financing, and limited manpower.
Keywords: Dementia; Health Care Costs; Health Services; Humans; Philippines; Prevalence

First Biodistribution Study of [68Ga]Ga-NOTA-Insulin Following Intranasal Administration in Adult Vervet Monkeys. - Solingapuram Sai, Kiran Kumar; Erichsen, Jennifer M; Gollapelli, Krishna K; Krizan, Ivan; Miller, Mack; Bansode, Avinash; Jorgensen, Mathew J; Register, Thomas; Cazzola, Charles; Gandhi, Reenal; Suman, Julie; Craft, Suzanne (J Alzheimers Dis, 2024)
BACKGROUND: Intranasal insulin (INI) is being explored as a treatment for Alzheimer's disease (AD). Improved memory, functional ability, and cerebrospinal fluid (CSF) AD biomarker profiles have been observed following INI administration. However, the method of intranasal delivery may significantly affect outcomes. OBJECTIVE: To show reliable delivery of insulin to the brain using the Aptar Cartridge Pump System (CPS) intranasal delivery system. METHODS: To visualize INI biodistribution, we developed a novel PET radiotracer, Gallium 68-radiolabeled (NOTA-conjugated) insulin, [68Ga]Ga-NOTA-insulin. We used the Aptar CPS to administer [68Ga]Ga-NOTA-insulin to anesthetized healthy adult vervet monkeys and measured brain regional activity and whole-body dosimetry following PET/CT scans. RESULTS: We observed brain penetration of [68Ga]Ga-NOTA-insulin following intranasal administration with the Aptar CPS. Radioactive uptake was seen in multiple regions, including the amygdala, putamen, hypothalamus, hippocampus, and choroid plexus. A safety profile and whole-body dosimetry were also established in a second cohort of vervets. Safety was confirmed: vitals remained stable, blood glucose levels were unchanged, and no organ was exposed to more than 2.5 mSv of radioactivity. Extrapolations from vervet organ distribution allowed for estimation of the [68Ga]Ga-NOTA-insulin absorbed dose in humans, and the maximum dose of [68Ga]Ga-NOTA-insulin that can be safely administered to humans was determined to be 185 MBq. CONCLUSIONS: The use of [68Ga]Ga-NOTA-insulin as a PET radiotracer is safe and effective for observing brain uptake in vervet monkeys. Further, the Aptar CPS successfully targets [68Ga]Ga-NOTA-insulin to the brain. The data will be essential in guiding future studies of intranasal [68Ga]Ga-NOTA-insulin administration in humans.
Keywords: Administration, Intranasal; Animals; Brain; Chlorocebus aethiops; Female; Gallium Radioisotopes; Heterocyclic Compounds; Heterocyclic Compounds, 1-Ring; Insulin; Male; Positron Emission Tomography Computed Tomography; Positron-Emission Tomography; Radiopharmaceuticals; Tissue Distribution

Impaired Skeletal Development by Disruption of Presenilin-1 in Pigs and Generation of Novel Pig Models for Alzheimer's Disease. - Uh, Kyungjun; Monarch, Kaylynn; Reese, Emily D; Rodriguez, Katherine; Yoon, Junchul; Spate, Lee D; Samuel, Melissa S; Koh, Sehwon; Chen, Paula R; Jarome, Timothy J; Allen, Timothy A; Prather, Randall S; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Presenilin 1 (PSEN1) is one of the genes linked to the prevalence of early onset Alzheimer's disease. In mice, inactivation of Psen1 leads to developmental defects, including vertebral malformation and neural development. However, little is known about the role of PSEN1 during the development in other species. OBJECTIVE: To investigate the role of PSEN1 in vertebral development and the pathogenic mechanism of neurodegeneration using a pig model. METHODS: CRISPR/Cas9 system was used to generate pigs with different mutations flanking exon 9 of PSEN1, including those with a deleted exon 9 (Δexon9). Vertebral malformations in PSEN1 mutant pigs were examined by X-ray, micro-CT and micro-MRI. Neuronal cells from the brains of PSEN1 mutant pigs were analyzed by immunoflourescence, followed by image analysis including morphometric evaluation via image J and 3D reconstruction. RESULTS: Pigs with a PSEN1 null mutation (Δexon9-12) died shortly after birth and had significant axial skeletal defects, whereas pigs carrying at least one Δexon9 allele developed normally and remained healthy. Effects of the null mutation on abnormal skeletal development were also observed in fetuses at day 40 of gestation. Abnormal distribution of astrocytes and microglia in the brain was detected in two PSEN1 mutant pigs examined compared to age-matched control pigs. The founder pigs were bred to establish and age PSEN1ΔE9/+ pigs to study their relevance to clinical Alzheimer's diseases. CONCLUSIONS: PSEN1 has a critical role for normal vertebral development and PSEN1 mutant pigs serves as novel resources to study Alzheimer's disease.

An Insertion Within SIRPβ1 Shows a Dual Effect Over Alzheimer's Disease Cognitive Decline Altering the Microglial Response. - García-Alberca, José María; de Rojas, Itziar; Sanchez-Mejias, Elisabeth; Garrido-Martín, Diego; Gonzalez-Palma, Laura; Jimenez, Sebastian; Pino-Angeles, Almudena; Cruz-Gamero, Jose Manuel; Mendoza, Silvia; Alarcón-Martín, Emilio; Muñoz-Castro, Clara; Real, Luis Miguel; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Microglial dysfunction plays a causative role in Alzheimer's disease (AD) pathogenesis. Here we focus on a germline insertion/deletion variant mapping SIRPβ1, a surface receptor that triggers amyloid-β(Aβ) phagocytosis via TYROBP. OBJECTIVE: To analyze the impact of this copy-number variant in SIRPβ1 expression and how it affects AD molecular etiology. METHODS: Copy-number variant proxy rs2209313 was evaluated in GERALD and GR@ACE longitudinal series. Hippocampal specimens of genotyped AD patients were also examined. SIRPβ1 isoform-specific phagocytosis assays were performed in HEK393T cells. RESULTS: The insertion alters the SIRPβ1 protein isoform landscape compromising its ability to bind oligomeric Aβ and its affinity for TYROBP. SIRPβ1 Dup/Dup patients with mild cognitive impairment show an increased cerebrospinal fluid t-Tau/Aβ ratio (p = 0.018) and a higher risk to develop AD (OR = 1.678, p = 0.018). MRIs showed that Dup/Dup patients exhibited a worse initial response to AD. At the moment of diagnosis, all patients showed equivalent Mini-Mental State Examination scores. However, AD patients with the duplication had less hippocampal degeneration (p < 0.001) and fewer white matter hyperintensities. In contrast, longitudinal studies indicate that patients bearing the duplication allele show a slower cognitive decline (p = 0.013). Transcriptional analysis also shows that the SIRPβ1 duplication allele correlates with higher TREM2 expression and an increased microglial activation. CONCLUSIONS: The SIRPβ1 internal duplication has opposite effects over MCI-to-Dementia conversion risk and AD progression, affecting microglial response to Aβ. Given the pharmacological approaches focused on the TREM2-TYROBP axis, we believe that SIRPβ1 structural variant might be considered as a potential modulator of this causative pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Humans; Microglia; Phagocytosis; Receptors, Cell Surface

Long Non-Coding RNA Profile in Genetic Symptomatic and Presymptomatic Frontotemporal Dementia: A GENFI Study. - Serpente, Maria; Fenoglio, Chiara; Arcaro, Marina; Carandini, Tiziana; Sacchi, Luca; Pintus, Manuela; Rotondo, Emanuela; Borracci, Vittoria; Ghezzi, Laura; Bouzigues, Arabella; Russell, Lucy L; Foster, Phoebe H; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Long non-coding RNAs (lncRNAs) play crucial roles in gene regulation and are implicated in neurodegenerative diseases, including frontotemporal dementia (FTD). However, their expression patterns and potential as biomarkers in genetic FTD involving Chromosome 9 Open Reading Frame (C9ORF72), Microtubule Associated Protein Tau (MAPT), and Progranulin (GRN) genes are not well understood. OBJECTIVE: This study aimed to profile the expression levels of lncRNAs in peripheral blood mononuclear cells collected within the GENetic Frontotemporal dementia Initiative (GENFI). METHODS: Fifty-three lncRNAs were analyzed with the OpenArray Custom panel, in 131 patients with mutations in C9ORF72, MAPT, and GRN, including 68 symptomatic mutation carriers (SMC) and 63 presymptomatic mutation carriers (PMC), compared with 40 non-carrier controls (NC). RESULTS: Thirty-eight lncRNAs were detectable; the relative expression of NEAT1 and NORAD was significantly higher in C9ORF72 SMC as compared with NC. GAS5 expression was instead significantly lower in the GRN group versus NC. MAPT carriers showed no significant deregulations. No significant differences were observed in PMC. Disease duration did not correlate with lncRNA expression. CONCLUSIONS: NEAT1 and NORAD are upregulated in C9ORF72 SMC and GAS5 levels are downregulated in GRN SMC, underlining lncRNAs' relevance in FTD and their potential for biomarker development. Further validation and mechanistic studies are crucial for clinical implications.

Mayo Normative Studies: Amyloid and Neurodegeneration Negative Normative Data for the Auditory Verbal Learning Test and Sex-Specific Sensitivity to Mild Cognitive Impairment/Dementia. - Stricker, Nikki H; Christianson, Teresa J; Pudumjee, Shehroo B; Polsinelli, Angelina J; Lundt, Emily S; Frank, Ryan D; Kremers, Walter K; Machulda, Mary M; Fields, Julie A; Jack, Clifford R; Knopman, David S; Graff-Radford, Jonathan; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Conventional normative samples include individuals with undetected Alzheimer's disease neuropathology, lowering test sensitivity for cognitive impairment. OBJECTIVE: We developed Mayo Normative Studies (MNS) norms limited to individuals without elevated amyloid or neurodegeneration (A-N-) for Rey's Auditory Verbal Learning Test (AVLT). We compared these MNS A-N- norms in female, male, and total samples to conventional MNS norms with varying levels of demographic adjustments. METHODS: The A-N- sample included 1,059 Mayo Clinic Study of Aging cognitively unimpaired (CU) participants living in Olmsted County, MN, who are predominantly non-Hispanic White. Using a regression-based approach correcting for age, sex, and education, we derived fully-adjusted T-score formulas for AVLT variables. We validated these A-N- norms in two independent samples of CU (n = 261) and mild cognitive impairment (MCI)/dementia participants (n = 392) > 55 years of age. RESULTS: Variability associated with age decreased by almost half in the A-N- norm sample relative to the conventional norm sample. Fully-adjusted MNS A-N- norms showed approximately 7- 9% higher sensitivity to MCI/dementia compared to fully-adjusted MNS conventional norms for trials 1- 5 total and sum of trials. Among women, sensitivity to MCI/dementia increased with each normative data refinement. In contrast, age-adjusted conventional MNS norms showed greatest sensitivity to MCI/dementia in men. CONCLUSIONS: A-N- norms show some benefits over conventional normative approaches to MCI/dementia sensitivity, especially for women. We recommend using these MNS A-N- norms alongside MNS conventional norms. Future work is needed to determine if normative samples that are not well characterized clinically show greater benefit from biomarker-refined approaches.

Mendelian Randomization of Blood Metabolites Suggests Circulating Glutamine Protects Against Late-Onset Alzheimer's Disease. - Ramadan, Ferris A; Arani, Gayatri; Jafri, Ayan; Thompson, Tingting; Bland, Victoria L; Renquist, Benjamin; Raichlen, David A; Alexander, Gene E; Klimentidis, Yann C (J Alzheimers Dis, 2024)
BACKGROUND: Late-onset Alzheimer's disease (LOAD) represents a growing health burden. Previous studies suggest that blood metabolite levels influence risk of LOAD. OBJECTIVE: We used a genetics-based study design which may overcome limitations of other epidemiological studies to assess the influence of metabolite levels on LOAD risk. METHODS: We applied Mendelian randomization (MR) to evaluate bi-directional causal effects using summary statistics from the largest genome-wide association studies (GWAS) of 249 blood metabolites (n = 115,082) and GWAS of LOAD (ncase = 21,982, ncontrol = 41,944). RESULTS: MR analysis of metabolites as exposures revealed a negative association of genetically-predicted glutamine levels with LOAD (Odds Ratio (OR) = 0.83, 95% CI = 0.73, 0.92) that was consistent in multiple sensitivity analyses. We also identified a positive association of genetically-predicted free cholesterol levels in small LDL (OR = 1.79, 95% CI = 1.36, 2.22) on LOAD. Using genetically-predicted LOAD as the exposure, we identified associations with phospholipids to total lipids ratio in large LDL (OR = 0.96, 95% CI = 0.94, 0.98), but not with glutamine, suggesting that the relationship between glutamine and LOAD is unidirectional. CONCLUSIONS: Our findings support previous evidence that higher circulating levels of glutamine may be a target for protection against LOAD.

Potential Impact of Slowing Disease Progression in Early Symptomatic Alzheimer's Disease on Patient Quality of Life, Caregiver Time, and Total Societal Costs: Estimates Based on Findings from GERAS-US Study. - Chandler, Julie M; Ye, Wenyu; Mi, Xiaojuan; Doty, Erin G; Johnston, Joseph A (J Alzheimers Dis, 2024)
BACKGROUND: Impact of Alzheimer's disease (AD) progression on patient health-related quality of life (HRQoL), caregiver time, and societal costs is not well characterized in early AD. OBJECTIVE: To assess the association of change in cognition with HRQoL, caregiver time, and societal costs over 36 months, and estimate the impact of slowing disease progression on these outcomes. METHODS: This post-hoc analysis included patients with amyloid-positive mild cognitive impairment (MCI) and mild AD dementia (MILD AD) from the 36-month GERAS-US study. Disease progression was assessed using the Mini-Mental State Examination score. Change in outcomes associated with slowing AD progression was estimated using coefficients from generalized linear models. RESULTS: At baseline, 300 patients had MCI and 317 had MILD AD. Observed natural progression over 36 months was associated with: 5.1 point decline in the Bath Assessment of Subjective Quality of Life in Dementia (BASQID) score (for HRQoL), increase in 1,050 hours of total caregiver time, and $8,504 total societal costs for MCI; 6.6 point decline in the BASQID score, increase in 1,929 hours of total caregiver time, and $12,795 total societal costs for MILD AD per person. Slowing AD progression by 30% could result in per person savings in HRQoL decline, total caregiver time, and total societal costs: for MCI: 1.5 points, 315 hours, and $2,638; for MILD AD: 2.0 points, 579 hours, and $3,974. CONCLUSIONS: Slowing AD progression over 36 months could slow decline in HRQoL and save caregiver time and societal cost in patients with MCI and MILD AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Caregivers; Cognitive Dysfunction; Cost of Illness; Disease Progression; Female; Humans; Male; Mental Status and Dementia Tests; Quality of Life; United States

Recent Advances in Drug Delivery Systems Targeting Insulin Signalling for the Treatment of Alzheimer's Disease. - Sachdeva, Punya; Narayanan, Kannan Badri; Sinha, Jitendra Kumar; Gupta, Saurabh; Ghosh, Shampa; Singh, Krishna Kumar; Bhaskar, Rakesh; Almutary, Abdulmajeed G; Zothantluanga, James H; Kotta, Kranthi Kumar; Nelson, Vinod Kumar; Paiva-Santos, Ana Cláudia; et al. (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) is a complex neurodegenerative disorder characterized by the accumulation of neurofibrillary tangles and amyloid-β plaques. Recent research has unveiled the pivotal role of insulin signaling dysfunction in the pathogenesis of AD. Insulin, once thought to be unrelated to brain function, has emerged as a crucial factor in neuronal survival, synaptic plasticity, and cognitive processes. Insulin and the downstream insulin signaling molecules are found mainly in the hippocampus and cortex. Some molecules responsible for dysfunction in insulin signaling are GSK-3β, Akt, PI3K, and IRS. Irregularities in insulin signaling or insulin resistance may arise from changes in the phosphorylation levels of key molecules, which can be influenced by both stimulation and inactivity. This, in turn, is believed to be a crucial factor contributing to the development of AD, which is characterized by oxidative stress, neuroinflammation, and other pathological hallmarks. Furthermore, this route is known to be indirectly influenced by Nrf2, NF-κB, and the caspases. This mini-review delves into the intricate relationship between insulin signaling and AD, exploring how disruptions in this pathway contribute to disease progression. Moreover, we examine recent advances in drug delivery systems designed to target insulin signaling for AD treatment. From oral insulin delivery to innovative nanoparticle approaches and intranasal administration, these strategies hold promise in mitigating the impact of insulin resistance on AD. This review consolidates current knowledge to shed light on the potential of these interventions as targeted therapeutic options for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Drug Delivery Systems; Glycogen Synthase Kinase 3 beta; Humans; Insulin; Insulin Resistance

Sex and Sleep Disruption as Contributing Factors in Alzheimer's Disease. - Johnson, Carrie E; Duncan, Marilyn J; Murphy, M Paul (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) affects more women than men, with women throughout the menopausal transition potentially being the most under researched and at-risk group. Sleep disruptions, which are an established risk factor for AD, increase in prevalence with normal aging and are exacerbated in women during menopause. Sex differences showing more disrupted sleep patterns and increased AD pathology in women and female animal models have been established in literature, with much emphasis placed on loss of circulating gonadal hormones with age. Interestingly, increases in gonadotropins such as follicle stimulating hormone are emerging to be a major contributor to AD pathogenesis and may also play a role in sleep disruption, perhaps in combination with other lesser studied hormones. Several sleep influencing regions of the brain appear to be affected early in AD progression and some may exhibit sexual dimorphisms that may contribute to increased sleep disruptions in women with age. Additionally, some of the most common sleep disorders, as well as multiple health conditions that impair sleep quality, are more prevalent and more severe in women. These conditions are often comorbid with AD and have bi-directional relationships that contribute synergistically to cognitive decline and neuropathology. The association during aging of increased sleep disruption and sleep disorders, dramatic hormonal changes during and after menopause, and increased AD pathology may be interacting and contributing factors that lead to the increased number of women living with AD.
Keywords: Alzheimer Disease; Animals; Cross-Sectional Studies; Female; Humans; Male; Multimorbidity; Sex Factors; Sleep; Sleep Wake Disorders

Socioeconomic Status and Dementia Risk Among Intensive Care Unit Survivors: Using National Health Insurance Cohort in Korea. - Park, Yu Shin; Joo, Hye Jin; Jang, Yun Seo; Jeon, Hajae; Park, Eun-Cheol; Shin, Jaeyong (J Alzheimers Dis, 2024)
BACKGROUND: In aging populations, more elderly patients are going to the intensive care unit (ICU) and surviving. However, the specific factors influencing the occurrence of post-intensive care syndrome in the elderly remain uncertain. OBJECTIVE: To investigate the association between socioeconomic status (SES) and risk of developing dementia within two years following critical care. METHODS: This study included participants from the Korean National Health Insurance Service Cohort Database who had not been diagnosed with dementia and had been hospitalized in the ICU from 2003 to 2019. Dementia was determined using specific diagnostic codes (G30, G31) and prescription of certain medications (rivastigmine, galantamine, memantine, or donepezil). SES was categorized into low (medical aid beneficiaries) and non-low (National Health Insurance) groups. Through a 1:3 propensity score matching based on sex, age, Charlson comorbidity index, and primary diagnosis, the study included 16,780 patients. We used Cox proportional hazard models to estimate adjusted hazard ratios (HR) of dementia. RESULTS: Patients with low SES were higher risk of developing dementia within 2 years after receiving critical care than those who were in non-low SES (HR: 1.23, 95% CI: 1.04-1.46). Specifically, patients with low SES and those in the high-income group exhibited the highest incidence rates of developing dementia within two years after receiving critical care, with rates of 3.61 (95% CI: 3.13-4.17) for low SES and 2.58 (95% CI: 2.20-3.03) for high income, respectively. CONCLUSIONS: After discharge from critical care, compared to the non-low SES group, the low SES group was associated with an increased risk of developing dementia.
Keywords: Aged; Dementia; Humans; Intensive Care Units; National Health Programs; Republic of Korea; Retrospective Studies; Social Class; Survivors

The Standardized Extract of Centella asiatica and Its Fractions Exert Antioxidative and Anti-Neuroinflammatory Effects on Microglial Cells and Regulate the Nrf2/HO-1 Signaling Pathway. - Hambali, Aqilah; Jusril, Nor Atiqah; Md Hashim, Nur Fariesha; Abd Manan, Nizar; Adam, Siti Khadijah; Mehat, Muhammad Zulfadli; Adenan, Mohd Ilham; Stanslas, Johnson; Abdul Hamid, Hafizah (J Alzheimers Dis, 2024)
BACKGROUND: Neuroinflammation and oxidative stress can aggravate the progression of Alzheimer's disease (AD). Centella asiatica has been traditionally consumed for memory and cognition. The triterpenes (asiaticoside, madecassoside, asiatic acid, madecassic acid) have been standardized in the ethanolic extract of Centella asiatica (SECA). The bioactivity of the triterpenes in different solvent polarities of SECA is still unknown. OBJECTIVE: In this study, the antioxidative and anti-neuroinflammatory effects of SECA and its fractions were explored on lipopolysaccharides (LPS)-induced microglial cells. METHODS: HPLC measured the four triterpenes in SECA and its fractions. SECA and its fractions were tested for cytotoxicity on microglial cells using MTT assay. NO, pro-inflammatory cytokines (TNF-α, IL-6, IL-1β), ROS, and MDA (lipid peroxidation) produced by LPS-induced microglial cells were measured by colorimetric assays and ELISA. Nrf2 and HO-1 protein expressions were measured using western blotting. RESULTS: The SECA and its fractions were non-toxic to BV2 microglial cells at tested concentrations. The levels of NO, TNF-α, IL-6, ROS, and lipid peroxidation in LPS-induced BV2 microglial cells were significantly reduced (p < 0.001) by SECA and its fractions. SECA and some of its fractions can activate the Nrf2/HO-1 signaling pathway by significantly enhancing (p < 0.05) the Nrf2 and HO-1 protein expressions. CONCLUSIONS: This study suggests that the inhibitory activity of SECA and its fractions on pro-inflammatory and oxidative stress events may be the result of the activation of antioxidant defense systems. The potential of SECA and its fractions in reducing neuroinflammation and oxidative stress can be further studied as a potential therapeutic strategy for AD.
Keywords: Animals; Anti-Inflammatory Agents; Antioxidants; Cell Line; Centella; Heme Oxygenase-1; Lipopolysaccharides; Membrane Proteins; Mice; Microglia; Neuroinflammatory Diseases; NF-E2-Related Factor 2; Oxidative Stress; Plant Extracts; Signal Transduction; Triterpenes

Symptomatic Clusters Related to Amyloid Positivity in Cognitively Unimpaired Individuals. - Sannemann, Lena; Bartels, Claudia; Brosseron, Frederic; Buerger, Katharina; Fliessbach, Klaus; Freiesleben, Silka Dawn; Frommann, Ingo; Glanz, Wenzel; Heneka, Michael T; Janowitz, Daniel; Kilimann, Ingo; Kleineidam, Luca; et al. (J Alzheimers Dis, 2024)
BACKGROUND: The NIA-AA Research Framework on Alzheimer's disease (AD) proposes a transitional stage (stage 2) characterized by subtle cognitive decline, subjective cognitive decline (SCD) and mild neurobehavioral symptoms (NPS). OBJECTIVE: To identify participant clusters based on stage 2 features and assess their association with amyloid positivity in cognitively unimpaired individuals. METHODS: We included baseline data of N = 338 cognitively unimpaired participants from the DELCODE cohort with data on cerebrospinal fluid biomarkers for AD. Classification into the AD continuum (i.e., amyloid positivity, A+) was based on Aβ42/40 status. Neuropsychological test data were used to assess subtle objective cognitive dysfunction (OBJ), the subjective cognitive decline interview (SCD-I) was used to detect SCD, and the Neuropsychiatric Inventory Questionnaire (NPI-Q) was used to assess NPS. A two-step cluster analysis was carried out and differences in AD biomarkers between clusters were analyzed. RESULTS: We identified three distinct participant clusters based on presented symptoms. The highest rate of A+ participants (47.6% ) was found in a cluster characterized by both OBJ and SCD. A cluster of participants that presented with SCD and NPS (A+:26.6% ) and a cluster of participants with overall few symptoms (A+:19.7% ) showed amyloid positivity in a range that was not higher than the expected A+ rate for the age group. Across the full sample, participants with a combination of SCD and OBJ in the memory domain showed a lower Aβ42/ptau181 ratio compared to those with neither SCD nor OBJ. CONCLUSIONS: The cluster characterized by participants with OBJ and concomitant SCD was enriched for amyloid pathology.

A 19-Year-Old Adolescent with Probable Alzheimer's Disease. - Jia, Jianping; Zhang, Yue; Shi, Yuqing; Yin, Xuping; Wang, Shiyuan; Li, Yan; Zhao, Tan; Liu, Wenying; Zhou, Aihong; Jia, Longfei (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) primarily affects older adults. In this report, we present the case of a 19-year-old male with gradual memory decline for 2 years and World Health Organization-University of California Los Angeles Auditory Verbal Learning Test (WHO-UCLA AVLT) results also showing memory impairment. Positron emission tomography-magnetic resonance imaging with 18F fluorodeoxyglucose revealed atrophy of the bilateral hippocampus and hypometabolism in the bilateral temporal lobe. Examination of the patient's cerebrospinal fluid showed an increased concentration of p-tau181 and a decreased amyloid-β 42/40 ratio. However, through whole-genome sequencing, no known gene mutations were identified. Considering the above, the patient was diagnosed with probable AD.
Keywords: Adolescent; Aged; Alzheimer Disease; Amyloid beta-Peptides; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Positron-Emission Tomography

Accumulation of pTau231 at the Postsynaptic Density in Early Alzheimer's Disease. - Lilek, Jaclyn; Ajroud, Kaouther; Feldman, Alexander Z; Krishnamachari, Sesha; Ghourchian, Shadi; Gefen, Tamar; Spencer, Callen L; Kawles, Allegra; Mao, Qinwen; Tranovich, Jessica F; Jack, Clifford R; Mesulam, M-Marsel; et al. (J Alzheimers Dis, 2023)

The Anti-Amyloid Monoclonal Antibody Lecanemab: 16 Cautionary Notes. - Kepp, Kasper P; Sensi, Stefano L; Johnsen, Kasper B; Barrio, Jorge R; Høilund-Carlsen, Poul F; Neve, Rachael L; Alavi, Abass; Herrup, Karl; Perry, George; Robakis, Nikolaos K; Vissel, Bryce; Espay, Alberto J (J Alzheimers Dis, 2023)
After the CLARITY-AD clinical trial results of lecanemab were interpreted as positive, and supporting the amyloid hypothesis, the drug received accelerated Food and Drug Administration approval. However, we argue that benefits of lecanemab treatment are uncertain and may yield net harm for some patients, and that the data do not support the amyloid hypothesis. We note potential biases from inclusion, unblinding, dropouts, and other issues. Given substantial adverse effects and subgroup heterogeneity, we conclude that lecanemab's efficacy is not clinically meaningful, consistent with numerous analyses suggesting that amyloid-β and its derivatives are not the main causative agents of Alzheimer's disease dementia.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloidogenic Proteins; Antibodies, Monoclonal; Humans; United States

Associations of Midlife Lifestyle and Health Factors with Long-Term Changes in Blood-Based Biomarkers of Alzheimer's Disease and Neurodegeneration. - Merten, Natascha; Pinto, A Alex; Paulsen, Adam J; Chen, Yanjun; Engelman, Corinne D; Hancock, Laura M; Johnson, Sterling C; Schubert, Carla R (J Alzheimers Dis, 2023)
BACKGROUND: Pathological biomarkers of Alzheimer's disease (AD) and other dementias can change decades before clinical symptoms. Lifestyle and health factors might be relevant modifiable risk factors for dementia. Many previous studies have been focusing on associations of lifestyle and health-related factors with clinical outcomes later in life. OBJECTIVE: We aimed to determine to what extent midlife factors of lifestyle, inflammation, vascular, and metabolic health were associated with long-term changes in blood-based biomarkers of AD (amyloid beta (Aβ)) and neurodegeneration (neurofilament light chain (NfL); total tau(TTau)). METHODS: In 1,529 Beaver Dam Offspring Study (BOSS) participants (mean age 49 years, standard deviation (SD) = 9;54% were women), we applied mixed-effects models with baseline risk factors as determinants and 10-year serum biomarker change as outcomes. RESULTS: We found that education and inflammatory markers were associated with levels and/or change over time across all three markers of AD and neurodegeneration in the blood. There were baseline associations of measures of cardiovascular health with lower Aβ42/Aβ40. TTau changed little over time and was higher in individuals with diabetes. Individuals with lower risk in a number of cardiovascular and metabolic risk factors, including diabetes, hypertension, and atherosclerosis had slower accumulation of neurodegeneration over time, as determined by NfL levels. CONCLUSION: Various lifestyle and health factors, including education and inflammation, were associated with longitudinal changes of neurodegenerative and AD biomarker levels in midlife. If confirmed, these findings could have important implications for developing early lifestyle and health interventions that could potentially slow processes of neurodegeneration and AD.

Associations of the Harvard Automated Phone Task and Alzheimer's Disease Pathology in Cognitively Normal Older Adults: Preliminary Findings. - Gonzalez, Christopher; Mimmack, Kayden J; Amariglio, Rebecca E; Becker, J Alex; Chhatwal, Jasmeer P; Fitzpatrick, Colleen D; Gatchel, Jennifer R; Johnson, Keith A; Katz, Zoe S; Kuppe, Madeline K; Locascio, Joseph J; Udeogu, Onyinye J; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Detecting clinically meaningful changes in instrumental activities of daily living (IADL) at the earliest stages of Alzheimer's disease (AD) is critical. OBJECTIVE: The objective of this exploratory study was to examine the cross-sectional relationship between a performance-based IADL test, the Harvard Automated Phone Task (APT), and cerebral tau and amyloid burden in cognitively normal (CN) older adults. METHODS: Seventy-seven CN participants underwent flortaucipir tau and Pittsburgh Compound B amyloid PET. IADL were assessed using the three Harvard APT tasks: prescription refill (APT-Script), health insurance company call (APT-PCP), and bank transaction (APT-Bank). Linear regression models were used to determine associations between each APT task and entorhinal cortex, inferior temporal, or precuneus tau with or without an interaction with amyloid. RESULTS: Significant associations were found between APT-Bank task rate and interaction between amyloid and entorhinal cortex tau, and APT-PCP task and interactions between amyloid and inferior temporal and precuneus tau. No significant associations were found between the APT tasks and tau or amyloid alone. CONCLUSION: Our preliminary findings suggest an association between a simulated real-life IADL test and interactions of amyloid and several regions of early tau accumulation in CN older adults. However, some analyses were underpowered due to the small number of participants with elevated amyloid, and findings should be interpreted with caution. Future studies will further explore these associations cross-sectionally and longitudinally in order to determine whether the Harvard APT can serve as a reliable IADL outcome measure for preclinical AD prevention trials and ultimately in the clinic setting.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Cognitive Dysfunction; Entorhinal Cortex; Humans; Positron-Emission Tomography; tau Proteins

Cerebrospinal Fluid Panel of Synaptic Proteins in Cerebral Amyloid Angiopathy and Alzheimer's Disease. - van den Berg, Emma; Nilsson, Johanna; Kersten, Iris; Brinkmalm, Gunnar; de Kort, Anna M; Klijn, Catharina J M; Schreuder, Floris H B M; Jäkel, Lieke; Gobom, Johan; Portelius, Erik; Zetterberg, Henrik; Brinkmalm, Ann; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) and cerebral amyloid angiopathy (CAA) share pathogenic pathways related to amyloid-β deposition. Whereas AD is known to affect synaptic function, such an association for CAA remains yet unknown. OBJECTIVE: We therefore aimed to investigate synaptic dysfunction in CAA. METHODS: Multiple reaction monitoring mass spectrometry was used to quantify cerebrospinal fluid (CSF) concentrations of 15 synaptic proteins in CAA and AD patients, and age- and sex-matched cognitively unimpaired controls. RESULTS: We included 25 patients with CAA, 49 patients with AD, and 25 controls. Only neuronal pentraxin-2 levels were decreased in the CSF of CAA patients compared with controls (p = 0.04). CSF concentrations of 12 other synaptic proteins were all increased in AD compared with CAA or controls (all p≤0.01) and were unchanged between CAA and controls. Synaptic protein concentrations in the subgroup of CAA patients positive for AD biomarkers (CAA/ATN+; n = 6) were similar to AD patients, while levels in CAA/ATN- (n = 19) were comparable with those in controls. A regression model including all synaptic proteins differentiated CAA from AD at high accuracy levels (area under the curve 0.987). CONCLUSION: In contrast to AD, synaptic CSF biomarkers were found to be largely unchanged in CAA. Moreover, concomitant AD pathology in CAA is associated with abnormal synaptic protein levels. Impaired synaptic function in AD was confirmed in this independent cohort. Our findings support an apparent differential involvement of synaptic dysfunction in CAA and AD and may reflect distinct pathological mechanisms.

Is Dementia Associated with COVID-19 Mortality? A Multicenter Retrospective Cohort Study Conducted in 50 Hospitals in Germany. - Kostev, Karel; Gessler, Nele; Wohlmuth, Peter; Arnold, Dirk; Bein, Berthold; Bohlken, Jens; Herrlinger, Klaus; Jacob, Louis; Koyanagi, Ai; Nowak, Lorenz; Smith, Lee; Wesseler, Claas; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Dementia has been identified as a major predictor of mortality associated with COVID-19. OBJECTIVE: The objective of this study was to investigate the association between dementia and mortality in COVID-19 inpatients in Germany across a longer interval during the pandemic. METHODS: This retrospective study was based on anonymized data from 50 hospitals in Germany and included patients with a confirmed COVID-19 diagnosis hospitalized between March 11, 2020 and July, 20, 2022. The main outcome of the study was the association of mortality during inpatient stays with dementia diagnosis, which was studied using multivariable logistic regression adjusted for age, sex, and comorbidities as well as univariate logistic regression for matched pairs. RESULTS: Of 28,311 patients diagnosed with COVID-19, 11.3% had a diagnosis of dementia. Prior to matching, 26.5% of dementia patients and 11.5% of non-dementia patients died; the difference decreased to 26.5% of dementia versus 21.7% of non-dementia patients within the matched pairs (n = 3,317). This corresponded to an increase in the risk of death associated with dementia (OR = 1.33; 95% CI: 1.16-1.46) in the univariate regression conducted for matched pairs. CONCLUSION: Although dementia was associated with COVID-19 mortality, the association was weaker than in previously published studies. Further studies are needed to better understand whether and how pre-existing neuropsychiatric conditions such as dementia may impact the course and outcome of COVID-19.
Keywords: COVID-19; COVID-19 Testing; Dementia; Germany; Hospitalization; Hospitals; Humans; Mortality; Retrospective Studies

Early Depressive Symptoms Predict Faster Dementia Progression in Autosomal-Dominant AD - Acosta-Baena, Natalia; Lopera-Gómez, Carlos M; Jaramillo-Elorza, Mario C; Velilla-Jiménez, Lina; Villegas-Lanau, Carlos Andrés; Sepúlveda-Falla, Diego; Arcos-Burgos, Mauricio; Lopera, Francisco (J Alzheimers Dis, 2023)
BACKGROUND: Depression is associated with Alzheimer's disease (AD). OBJECTIVE: To evaluate the association between depressive symptoms and age of onset of cognitive decline in autosomal dominant AD, and to determine possible factors associated to early depressive symptoms in this population. METHODS: We conducted a retrospective study to identify depressive symptoms among 190 presenilin 1 (PSEN1) E280A mutation carriers, subjected to comprehensive clinical evaluations in up to a 20-year longitudinal follow-up. We controlled for the following potential confounders: APOE, sex, hypothyroidism, education, marital status, residence, tobacco, alcohol, and drug abuse. RESULTS: PSEN1 E280A carriers with depressive symptoms before mild cognitive impairment (MCI) develop dementia faster than E280A carriers without depressive symptoms (Hazard Ratio, HR = 1.95; 95% CI, 1.15-3.31). Not having a stable partner accelerated the onset of MCI (HR = 1.60; 95 % CI, 1.03-2.47) and dementia (HR = 1.68; 95 % CI, 1.09-2.60). E280A carriers with controlled hypothyroidism had later age of onset of depressive symptoms (HR = 0.48; 95 % CI, 0.25-0.92), dementia (HR = 0.43; 95 % CI, 0.21-0.84), and death (HR = 0.35; 95 % CI, 0.13-0.95). APOEɛ2 significantly affected AD progression in all stages. APOE polymorphisms were not associate to depressive symptoms. Women had a higher frequency and developed earlier depressive symptoms than men throughout the illness (HR = 1.63; 95 % CI, 1.14-2.32). CONCLUSION: Depressive symptoms accelerated progress and faster cognitive decline of autosomal dominant AD. Not having a stable partner and factors associated with early depressive symptoms (e.g., in females and individuals with untreated hypothyroidism), could impact prognosis, burden, and costs.

The Effect of Exercise on Falls in People Living with Dementia: A Systematic Review. - Jehu, Deborah A; Davis, Jennifer C; Gill, Jessica; Oke, Olabamibo; Liu-Ambrose, Teresa (J Alzheimers Dis, 2023)
BACKGROUND: People living with dementia (PWD) are at a heightened risk for falls. However, the effects of exercise on falls in PWD are unclear. OBJECTIVE: To conduct a systematic review of randomized controlled trials (RCTs) examining the efficacy of exercise to reduce falls, recurrent falls, and injurious falls relative to usual care among PWD. METHODS: We included peer-reviewed RCTs evaluating any exercise mode on falls and related injuries among medically diagnosed PWD aged ≥55years (international prospective register of systematic reviews (PROSPERO) ID:CRD42021254637). We excluded studies that did not solely involve PWD and were not the primary publication examining falls. We searched the Cochrane Dementia and Cognitive Improvement Group's Specialized Register and grey literature on 08/19/2020 and 04/11/2022; topical categories included dementia, exercise, RCTs, and falls. We evaluated the risk of bias (ROB) using the Cochrane ROB Tool-2 and study quality using the Consolidated Standards of Reporting Trials. RESULTS: Twelve studies were included (n = 1,827; age = 81.3±7.0 years; female = 59.3%; Mini-Mental State Examination = 20.1±4.3 points; intervention duration = 27.8±18.5 weeks; adherence = 75.5±16.2%; attrition = 21.0±12.4%). Exercise reduced falls in two studies [Incidence Rate Ratio (IRR) range = 0.16 to 0.66; fall rate range: intervention = 1.35-3.76 falls/year, control = 3.07-12.21 falls/year]; all other studies (n = 10) reported null findings. Exercise did not reduce recurrent falls (n = 0/2) or injurious falls (n = 0/5). The RoB assessment ranged from some concerns (n = 9) to high RoB (n = 3); no studies were powered for falls. The quality of reporting was good (78.8±11.4%). CONCLUSION: There was insufficient evidence to suggest that exercise reduces falls, recurrent falls, or injurious falls among PWD. Well-designed studies powered for falls are needed.
Keywords: Dementia; Exercise; Female; Humans; Independent Living

Effect of Metabolic Syndrome Risk Factors on Processing Speed and Executive Function in Three Racialized Groups. - Bouges, Shenikqua; Fischer, Barbara; Norton, Derek L; Wyman, Mary F; Lambrou, Nickolas; Zuelsdorff, Megan; Van Hulle, Carol A; Ennis, Gilda E; James, Taryn T; Johnson, Adrienne L; Chin, Nathaniel; Carlsson, Cynthia M; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Metabolic syndrome (MetS) has been associated with increased risk for Alzheimer's disease and related dementias (ADRD). Understanding the association of MetS risk factors to processing speed and executive function in the pre-clinical stages of ADRD in under-represented groups would offer insight on potential mechanisms through which MetS associates with ADRD risk. OBJECTIVE: Examine association of MetS features and processing speed and executive function across three racial groups. METHODS: Cognitively unimpaired adults from the Wisconsin Alzheimer's Disease Research Center and the Wisconsin Registry for Alzheimer's Disease Prevention completed blood-draws and neuropsychological testing. Six cognitive outcomes were assessed in association to MetS risk factors: Trailmaking Tests A and B, Animal Fluency, Digit Symbol, and composite scores for Processing Speed and Executive Function. Linear mixed effect models were used to assess the relationship between MetS risk factor count and longitudinal cognitive performance across three racialized groups. RESULTS: Participant sample sizes varied by outcome analyzed (N = 714-1,088). African American and Native American groups exhibited higher rates of MetS than non-Hispanic Whites. MetS was associated with processing speed and executive function across all racialized groups. Three-way interaction by racialized group was limited to one cognitive outcome: Trailmaking Test A. CONCLUSION: Metabolic dysfunction incrementally affects cognitive trajectory, with generally similar associations across racial groups. Since racialized groups exhibit higher levels of both MetS and ADRD, MetS may represent a driving factor for increased ADRD risk experience by racialized group and an important and modifiable target through which to reduce risk of ADRD.

Effect of Pathway-Specific Polygenic Risk Scores for Alzheimer's Disease (AD) on Rate of Change in Cognitive Function and AD-Related Biomarkers Among Asymptomatic Individuals. - Xu, Yuexuan; Vasiljevic, Eva; Deming, Yuetiva K; Jonaitis, Erin M; Koscik, Rebecca L; Van Hulle, Carol A; Lu, Qiongshi; Carboni, Margherita; Kollmorgen, Gwendlyn; Wild, Norbert; Carlsson, Cynthia M; Johnson, Sterling C; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Genetic scores for late-onset Alzheimer's disease (LOAD) have been associated with preclinical cognitive decline and biomarker variations. Compared with an overall polygenic risk score (PRS), a pathway-specific PRS (p-PRS) may be more appropriate in predicting a specific biomarker or cognitive component underlying LOAD pathology earlier in the lifespan. OBJECTIVE: In this study, we leveraged longitudinal data from the Wisconsin Registry for Alzheimer's Prevention and explored changing patterns in cognition and biomarkers at various age points along six biological pathways. METHODS: PRS and p-PRSs with and without APOE were constructed separately based on the significant SNPs associated with LOAD in a recent genome-wide association study meta-analysis and compared to APOE alone. We used a linear mixed-effects model to assess the association between PRS/p-PRSs and cognitive trajectories among 1,175 individuals. We also applied the model to the outcomes of cerebrospinal fluid biomarkers in a subset. Replication analyses were performed in an independent sample. RESULTS: We found p-PRSs and the overall PRS can predict preclinical changes in cognition and biomarkers. The effects of PRS/p-PRSs on rate of change in cognition, amyloid-β, and tau outcomes are dependent on age and appear earlier in the lifespan when APOE is included in these risk scores compared to when APOE is excluded. CONCLUSION: In addition to APOE, the p-PRSs can predict age-dependent changes in amyloid-β, tau, and cognition. Once validated, they could be used to identify individuals with an elevated genetic risk of accumulating amyloid-β and tau, long before the onset of clinical symptoms.

Effects of a Physical Activity Program that Incorporates Exercises Targeting Balance, Strength, and Proprioception on Cognitive Functions and Physical Performance in Old Adults with Mild Cognitive Impairment. - Boulares, Ayoub; Fabre, Claudine; Cherni, Ala; Jdidi, Hela; Gaied Chortane, Sabri; Trompetto, Carlo; Puce, Luca; Bragazzi, Nicola Luigi (J Alzheimers Dis, 2023)
BACKGROUND: Aging often leads to cognitive function decline, sensory structure deterioration, and musculoskeletal system weakening. This impacts postural control during static and dynamic activities like walking, increasing the fall risk among the elderly. Older adults with mild cognitive impairment (MCI) face an elevated fall risk and cognitive decline, magnifying the public health concern. OBJECTIVE: This study aimed to explore solutions by investigating the effects of a multi-component physical activity program on cognitive and motor functions in MCI patients. METHODS: Twenty-three participants were enrolled in the study and assigned into two groups: an intervention group (n = 13; age = 85.7±5.5 years) and a control group (n = 9; age = 85±6.7 years). The study spanned two months, with participants engaging in three 60-minute weekly physical exercise sessions. The intervention focused on improving proprioception, muscle strength, and balance. RESULTS: Results demonstrated significant enhancements in physical performance, fall risk reduction, and balance (p < 0.05). Various tests, including the timed up and go test, Unipedal Stance test, Tinetti test, Short Physical Performance Battery, and 6-minute walking test, indicated these improvements. Cognitive function was evaluated with the Mini-Mental State Examination, revealing non-significant progress (p > 0.05). Predictive models for outcomes were developed using linear regression analysis during the follow-up stage. CONCLUSIONS: This study underscores the effectiveness of a multi-component physical activity program encompassing balance, proprioception, and muscle-strengthening exercises as a non-pharmaceutical approach in improving balance skills and playing a key role in mitigating the risk of falls among old adults with MCI.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Exercise; Exercise Therapy; Humans; Physical Functional Performance; Postural Balance; Proprioception; Time and Motion Studies

Effects of Brain Pathologies on Spatiotemporal Gait Parameters in Patients with Mild Cognitive Impairment. - Lindh-Rengifo, Magnus; Jonasson, Stina B; Ullén, Susann; Palmqvist, Sebastian; van Westen, Danielle; Stomrud, Erik; Mattsson-Carlgren, Niklas; Nilsson, Maria H; Hansson, Oskar (J Alzheimers Dis, 2023)
BACKGROUND: Impaired gait can precede dementia. The associations between gait parameters and brain pathologies are therefore of interest. OBJECTIVE: To explore how different brain pathologies (i.e., vascular and Alzheimer's) are associated with specific gait parameters from various gait components in persons with mild cognitive impairment (MCI), who have an increased risk of developing dementia. METHODS: This cross-sectional study included 96 patients with MCI (mean 72, ±7.5 years; 52% women). Gait was evaluated by using an electronic walkway, GAITRite®. Four gait parameters (step velocity variability; step length; step time; stance time asymmetry) were used as dependent variables in multivariable linear regression analyses. Independent variables included Alzheimer's disease pathologies (amyloid-β and tau) by using PET imaging and white matter hyperintensities (WMH) by using MRI. Covariates included age, sex, comorbidities (and intracranial volume in analyses that includedWMH). RESULTS: Increased tau-PET (Braak I-IV region of interest [ROI]) was associated with step velocity variability (standardized regression coefficient, β= 0.383, p < 0.001) and step length (β= 0.336, p < 0.001), which remained significant when using different Braak ROIs (I-II, III-IV, V-VI). The associations remained significant when adjusting for WMH (p < 0.001). When also controlling for gait speed, tau was no longer significantly (p = 0.168) associated with an increased step length. No significant associations between gait and Aβ-PET load or WMH were identified. CONCLUSIONS: The results indicate that one should pay specific attention to assess step velocity variability when targeting single task gait in patients with MCI. Future studies should address additional gait variability measures and dual tasking in larger cohorts.

Extracellular Tau Oligomers Damage the Axon Initial Segment. - Best, Merci N; Lim, Yunu; Ferenc, Nina N; Kim, Nayoung; Min, Lia; Wang, Dora Bigler; Sharifi, Kamyar; Wasserman, Anna E; McTavish, Sloane A; Siller, Karsten H; Jones, Marieke K; Jenkins, Paul M; et al. (J Alzheimers Dis, 2023)
BACKGROUND: In Alzheimer's disease (AD) brain, neuronal polarity and synaptic connectivity are compromised. A key structure for regulating polarity and functions of neurons is the axon initial segment (AIS), which segregates somatodendritic from axonal proteins and initiates action potentials. Toxic tau species, including extracellular oligomers (xcTauOs), spread tau pathology from neuron to neuron by a prion-like process, but few other cell biological effects of xcTauOs have been described. OBJECTIVE: Test the hypothesis that AIS structure is sensitive to xcTauOs. METHODS: Cultured wild type (WT) and tau knockout (KO) mouse cortical neurons were exposed to xcTauOs, and quantitative western blotting and immunofluorescence microscopy with anti-TRIM46 monitored effects on the AIS. The same methods were used to compare TRIM46 and two other resident AIS proteins in human hippocampal tissue obtained from AD and age-matched non-AD donors. RESULTS: Without affecting total TRIM46 levels, xcTauOs reduce the concentration of TRIM46 within the AIS and cause AIS shortening in cultured WT, but not TKO neurons. Lentiviral-driven tau expression in tau KO neurons rescues AIS length sensitivity to xcTauOs. In human AD hippocampus, the overall protein levels of multiple resident AIS proteins are unchanged compared to non-AD brain, but TRIM46 concentration within the AIS and AIS length are reduced in neurons containing neurofibrillary tangles. CONCLUSION: xcTauOs cause partial AIS damage in cultured neurons by a mechanism dependent on intracellular tau, thereby raising the possibility that the observed AIS reduction in AD neurons in vivo is caused by xcTauOs working in concert with endogenous neuronal tau.

The Impact of Routine Vaccinations on Alzheimer's Disease Risk in Persons 65 Years and Older: A Claims-Based Cohort Study using Propensity Score Matching. - Harris, Kristofer; Ling, Yaobin; Bukhbinder, Avram S; Chen, Luyao; Phelps, Kamal N; Cruz, Gabriela; Thomas, Jenna; Kim, Yejin; Jiang, Xiaoqian; Schulz, Paul E (J Alzheimers Dis, 2023)
BACKGROUND: Accumulating evidence suggests that adult vaccinations can reduce the risk of developing Alzheimer's disease (AD) and Alzheimer's disease related dementias. OBJECTIVE: To compare the risk for developing AD between adults with and without prior vaccination against tetanus and diphtheria, with or without pertussis (Tdap/Td); herpes zoster (HZ); or pneumococcus. METHODS: A retrospective cohort study was performed using Optum's de-identified Clinformatics® Data Mart Database. Included patients were free of dementia during a 2-year look-back period and were≥65 years old by the start of the 8-year follow-up period. We compared two similar cohorts identified using propensity score matching (PSM), one vaccinated and another unvaccinated, with Tdap/Td, HZ, or pneumococcal vaccines. We calculated the relative risk (RR) and absolute risk reduction (ARR) for developing AD. RESULTS: For the Tdap/Td vaccine, 7.2% (n = 8,370) vaccinated patients and 10.2% (n = 11,857) unvaccinated patients developed AD during follow-up; the RR was 0.70 (95% CI, 0.68-0.72) and ARR was 0.03 (95% CI, 0.02-0.03). For the HZ vaccine, 8.1% (n = 16,106) vaccinated patients and 10.7% (n = 21,273) unvaccinated patients developed AD during follow-up; the RR was 0.75 (95% CI, 0.73-0.76) and ARR was 0.02 (95% CI, 0.02-0.02). For the pneumococcal vaccine, 7.92% (n = 20,583) vaccinated patients and 10.9% (n = 28,558) unvaccinated patients developed AD during follow-up; the RR was 0.73 (95% CI, 0.71-0.74) and ARR was 0.02 (95% CI, 0.02-0.03). CONCLUSION: Several vaccinations, including Tdap/Td, HZ, and pneumococcal, are associated with a reduced risk for developing AD.

Impaired Early Insulin Response to Glucose Load Predicts Episodic Memory Decline: A 10-Year Population-Based Cohort Follow-Up of 45-74-Year-Old Men and Women. - Toppala, Sini; Ekblad, Laura L; Viitanen, Matti; Rinne, Juha O; Jula, Antti (J Alzheimers Dis, 2023)
BACKGROUND: Diabetes increases the risk for cognitive decline, but the mechanisms behind this association remain unknown. Impaired early insulin secretion in elderly men and insulin resistance, both of which are pathophysiological features of type 2 diabetes, have previously been linked to Alzheimer's disease. OBJECTIVE: To examine if the early insulin response to oral glucose load predicts cognitive performance after 10 years in men and women aged 45-74 years. METHODS: This study was based on a subpopulation of the Health 2000 Survey, a Finnish nationwide, population-based health examination study, and its follow-up, the Health 2011 Study. In total, 961 45-74-year-old individuals (mean age at baseline 55.6 years, 55.8% women) were examined. An oral glucose tolerance test was performed in 2001-2002, and early insulin response was defined as the ratio of the 30-min increment in insulin concentration to that of glucose concentration. Cognitive function was evaluated at baseline and follow-up with categorical verbal fluency, word-list learning, and word-list delayed recall. Statistical analyses were performed using multivariable linear models adjusted for age, sex, education, APOE&z.epsi;4 genotype, vascular risk factors including diabetes, and depressive symptoms. RESULTS: A lower early insulin response to glucose load predicted lower performance (β: 0.21, p = 0.03) and greater decline (β: 0.19, p = 0.03) in the word-list delayed recall test. Baseline early insulin response did not predict verbal fluency or word-list learning (all p-values≥0.13). CONCLUSION: Our results suggest that decreased early insulin secretion predicts episodic memory decline in middle-aged to elderly men and women.

Linking Air Pollution Exposure to Blood-Based Metabolic Features in a Community-Based Aging Cohort with and without Dementia. - Kalia, Vrinda; Kulick, Erin R; Vardarajan, Badri; Gu, Yian; Manly, Jennifer J; Elkind, Mitchell S V; Kaufman, Joel D; Jones, Dean P; Baccarelli, Andrea A; Mayeux, Richard; Kioumourtzoglou, Marianthi-Anna; Miller, Gary W (J Alzheimers Dis, 2023)
BACKGROUND: Long-term exposure to air pollution has been associated with changes in levels of metabolites measured in the peripheral blood. However, most research has been conducted in ethnically homogenous, young or middle-aged populations. OBJECTIVE: To study the relationship between the plasma metabolome and long-term exposure to three air pollutants: particulate matter (PM) less than 2.5μm in aerodynamic diameter (PM2.5), PM less than 10μm in aerodynamic diameter (PM10), and nitrogen dioxide (NO2) in an ethnically diverse, older population. METHODS: Plasma metabolomic profiles of 107 participants of the Washington Heights and Inwood Community Aging Project in New York City, collected from 1995-2015, including non-Hispanic white, Caribbean Hispanic, and non-Hispanic Black older adults were used. We estimated the association between each metabolic feature and predicted annual mean exposure to the air pollutants using three approaches: 1) A metabolome wide association study framework; 2) Feature selection using elastic net regression; and 3) A multivariate approach using partial-least squares discriminant analysis. RESULTS: 79 features associated with exposure to PM2.5 but none associated with PM10 or NO2. PM2.5 exposure was associated with altered amino acid metabolism, energy production, and oxidative stress response, pathways also associated with Alzheimer's disease. Three metabolites were associated with PM2.5 exposure through all three approaches: cysteinylglycine disulfide, a diglyceride, and a dicarboxylic acid. The relationship between several features and PM2.5 exposure was modified by diet and metabolic diseases. CONCLUSIONS: These relationships uncover the mechanisms through which PM2.5 exposure can lead to altered metabolic outcomes in an older population.
Keywords: Aged; Aging; Air Pollutants; Air Pollution; Dementia; Environmental Exposure; Humans; Nitrogen Dioxide; Particulate Matter

Longitudinal Effects of Herpesviruses on Multiple Cognitive Outcomes in Healthy Elderly Adults. - Weidung, Bodil; Josefsson, Maria; Lyttkens, Peter; Olsson, Jan; Elgh, Fredrik; Lind, Lars; Kilander, Lena; Lövheim, Hugo (J Alzheimers Dis, 2023)
BACKGROUND: Herpesviruses have been proposed to be involved in Alzheimer's disease development as potentially modifiable pathology triggers. OBJECTIVE: To investigate associations of serum antibodies for herpes simplex virus (HSV)-1 and cytomegalovirus (CMV) and anti-herpesvirus treatment with cognitive outcomes in relation to interactions with APOE ɛ4. METHODS: The study included 849 participants in the population-based Prospective Investigation of the Vasculature in Uppsala Seniors study. Cognitive performance at the ages of 75 and 80 years was assessed using the Mini-Mental State Examination (MMSE), trail-making test (TMT) A and B, and 7-minute screening test (7MS). RESULTS: Anti- HSV-1 IgG positivity was associated cross-sectionally with worse performance on the MMSE, TMT-A, TMT-B, 7MS, enhanced free recall, and verbal fluency tests (p = 0.016, p = 0.016, p <  0.001, p = 0.001, p = 0.033, and p <  0.001, respectively), but not orientation or clock drawing. Cognitive scores did not decline over time and longitudinal changes did not differ according to HSV-1 positivity. Anti- CMV IgG positivity was not associated cross-sectionally with cognition, but TMT-B scores declined more in anti- CMV IgG carriers. Anti- HSV-1 IgG interacted with APOE ɛ4 in association with worse TMT-A and better enhanced cued recall. Anti- HSV IgM interacted with APOE ɛ4 and anti-herpesvirus treatment in association with worse TMT-A and clock drawing, respectively. CONCLUSION: These findings indicate that HSV-1 is linked to poorer cognition in cognitively healthy elderly adults, including impairments in executive function, memory, and expressive language. Cognitive performance did not decline over time, nor was longitudinal decline associated with HSV-1.

Longitudinal White and Gray Matter Response to Precision Medicine-Guided Intervention for Alzheimer's Disease. - Chwa, Won Jong; Raji, Cyrus A; Toups, Kat; Hathaway, Ann; Gordon, Deborah; Chung, Henrianna; Boyd, Alan; Hill, Benjamin D; Hausman-Cohen, Sharon; Attarha, Mouna; Jarrett, Michael; Bredesen, Dale E (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a debilitating condition that is widely known to adversely affect gray matter (GM) and white matter (WM) tracts within the brain. Recently, precision medicine has shown promise in alleviating the clinical and gross morphological trajectories of patients with AD. However, regional morphological changes have not yet been adequately characterized. OBJECTIVE: Investigate regional morphological responses to a precision medicine-guided intervention with regards to white and gray matter in AD and mild cognitive impairment (MCI). METHODS: Clinical and neuroimaging data were compiled over a 9-month period from 25 individuals who were diagnosed with AD or MCI receiving individualized treatment plans. Structural T1-weighted MRI scans underwent segmentation and volumetric quantifications via Neuroreader. Longitudinal changes were calculated via annualized percent change of WM or GM ratios. RESULTS: Montreal Cognitive Assessment scores (p < 0.001) and various domains of the Computerized Neurocognitive Screening Vital Signs significantly improved from baseline to 9-month follow-up. There was regional variability in WM and GM atrophy or hypertrophy, but none of these observed changes were statistically significant after correction for multiple comparisons.
Keywords: Alzheimer Disease; Atrophy; Brain; Cognitive Dysfunction; Gray Matter; Humans; Magnetic Resonance Imaging; Precision Medicine; White Matter

Medial Temporal Lobe Atrophy in Predementia Alzheimer's Disease: A Longitudinal Multi-Site Study Comparing Staging and A/T/N in a Clinical Research Cohort. - Jarholm, Jonas Alexander; Bjørnerud, Atle; Dalaker, Turi Olene; Akhavi, Mehdi Sadat; Kirsebom, Bjørn Eivind; Pålhaugen, Lene; Nordengen, Kaja; Grøntvedt, Gøril Rolfseng; Nakling, Arne; Kalheim, Lisa F; Almdahl, Ina S; Tecelao, Sandra; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Atrophy of the medial temporal lobe (MTL) is a biological characteristic of Alzheimer's disease (AD) and can be measured by segmentation of magnetic resonance images (MRI). OBJECTIVE: To assess the clinical utility of automated volumetry in a cognitively well-defined and biomarker-classified multi-center longitudinal predementia cohort. METHODS: We used Automatic Segmentation of Hippocampal Subfields (ASHS) to determine MTL morphometry from MRI. We harmonized scanner effects using the recently developed longitudinal ComBat. Subjects were classified according to the A/T/N system, and as normal controls (NC), subjective cognitive decline (SCD), or mild cognitive impairment (MCI). Positive or negative values of A, T, and N were determined by cerebrospinal fluid measurements of the Aβ42/40 ratio, phosphorylated and total tau. From 406 included subjects, longitudinal data was available for 206 subjects by stage, and 212 subjects by A/T/N. RESULTS: Compared to A-/T-/N- at baseline, the entorhinal cortex, anterior and posterior hippocampus were smaller in A+/T+orN+. Compared to NC A- at baseline, these subregions were also smaller in MCI A+. Longitudinally, SCD A+ and MCI A+, and A+/T-/N- and A+/T+orN+, had significantly greater atrophy compared to controls in both anterior and posterior hippocampus. In the entorhinal and parahippocampal cortices, longitudinal atrophy was observed only in MCI A+ compared to NC A-, and in A+/T-/N- and A+/T+orN+ compared to A-/T-/N-. CONCLUSION: We found MTL neurodegeneration largely consistent with existing models, suggesting that harmonized MRI volumetry may be used under conditions that are common in clinical multi-center cohorts.
Keywords: Alzheimer Disease; Atrophy; Cognitive Dysfunction; Entorhinal Cortex; Hippocampus; Humans; Magnetic Resonance Imaging; Temporal Lobe

Mild Cognitive Impairment is Associated with Poorer Everyday Decision Making. - Fenton, Laura; Han, S Duke; DiGuiseppi, Carolyn G; Fowler, Nicole R; Hill, Linda; Johnson, Rachel L; Peterson, Ryan A; Knoepke, Christopher E; Matlock, Daniel D; Moran, Ryan; Karlawish, Jason; Betz, Marian E (J Alzheimers Dis, 2023)
BACKGROUND: Older adults are faced with many unique and highly consequential decisions such as those related to finances, healthcare, and everyday functioning (e.g., driving cessation). Given the significant impact of these decisions on independence, wellbeing, and safety, an understanding of how cognitive impairment may impact decision making in older age is important. OBJECTIVE: To examine the impact of mild cognitive impairment (MCI) on responses to a modified version of the Short Portable Assessment of Capacity for Everyday Decision making (SPACED). METHODS: Participants were community-dwelling, actively driving older adults (N = 301; M age = 77.1 years, SD = 5.1; 69.4% with a college degree or higher; 51.2% female; 95.3% White) enrolled in the Advancing Understanding of Transportation Options (AUTO) study. A generalized linear model adjusted for age, education, sex, randomization group, cognitive assessment method, and study site was used to examine the relationship between MCI status and decision making. RESULTS: MCI status was associated with poorer decision making; participants with MCI missed an average of 2.17 times more points on the SPACED than those without MCI (adjusted mean ratio: 2.17, 95% CI: 1.02, 4.61, p = 0.044). CONCLUSION: This finding supports the idea that older adults with MCI exhibit poorer decision-making abilities than cognitively normal older adults. It also suggests that older adults with MCI may exhibit poorer decision making across a wide range of decision contexts.
Keywords: Aged; Cognitive Dysfunction; Decision Making; Delivery of Health Care; Educational Status; Female; Humans; Independent Living; Male

Multi-Site Cross-Site Inter-Rater and Test-Retest Reliability and Construct Validity of the MarkVCID White Matter Hyperintensity Growth and Regression Protocol. - Bahrani, Ahmed A; Abner, Erin L; DeCarli, Charles S; Barber, Justin M; Sutton, Abigail C; Maillard, Pauline; Sandoval, Francisco; Arfanakis, Konstantinos; Yang, Yung-Chuan; Evia, Arnold M; Schneider, Julie A; Habes, Mohamad; et al. (J Alzheimers Dis, 2023)
BACKGROUND: White matter hyperintensities (WMH) that occur in the setting of vascular cognitive impairment and dementia (VCID) may be dynamic increasing or decreasing volumes or stable over time. Quantifying such changes may prove useful as a biomarker for clinical trials designed to address vascular cognitive-impairment and dementia and Alzheimer's Disease. OBJECTIVE: Conducting multi-site cross-site inter-rater and test-retest reliability of the MarkVCID white matter hyperintensity growth and regression protocol. METHODS: The NINDS-supported MarkVCID Consortium evaluated a neuroimaging biomarker developed to track WMH change. Test-retest and cross-site inter-rater reliability of the protocol were assessed. Cognitive test scores were analyzed in relation to WMH changes to explore its construct validity. RESULTS: ICC values for test-retest reliability of WMH growth and regression were 0.969 and 0.937 respectively, while for cross-site inter-rater ICC values for WMH growth and regression were 0.995 and 0.990 respectively. Word list long-delay free-recall was negatively associated with WMH growth (p < 0.028) but was not associated with WMH regression. CONCLUSIONS: The present data demonstrate robust ICC validity of a WMH growth/regression protocol over a one-year period as measured by cross-site inter-rater and test-retest reliability. These data suggest that this approach may serve an important role in clinical trials of disease-modifying agents for VCID that may preferentially affect WMH growth, stability, or regression.

Neural Stem Cells in the Treatment of Alzheimer's Disease: Current Status, Challenges, and Future Prospects. - Chen, Xiaokun; Jiang, Shenzhong; Wang, Renzhi; Bao, Xinjie; Li, Yongning (J Alzheimers Dis, 2023)
Alzheimer's disease (AD), a progressive dementia, is one of the world's most dangerous and debilitating diseases. Clinical trial results of amyloid-β (Aβ) and tau regulators based on the pretext of straightforward amyloid and tau immunotherapy were disappointing. There are currently no effective strategies for slowing the progression of AD. Further understanding of the mechanisms underlying AD and the development of novel therapeutic options are critical. Neurogenesis is impaired in AD, which contributes to memory deficits. Transplanted neural stem cells (NSCs) can regenerate degraded cholinergic neurons, and new neurons derived from NSCs can form synaptic connections with neighboring neurons. In theory, employing NSCs to replace and restore damaged cholinergic neurons and brain connections may offer new treatment options for AD. However there remain barriers to surmount before NSC-based therapy can be used clinically. The objective of this article is to describe recent advances in the treatment of AD models and clinical trials involving NSCs. In addition, we discuss the challenges and prospects associated with cell transplant therapy for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Cholinergic Neurons; Disease Models, Animal; Humans; Neural Stem Cells

Neuroinflammation: A Common Pathway in Alzheimer's Disease and Epilepsy. - Liew, Yee; Retinasamy, Thaarvena; Arulsamy, Alina; Ali, Idrish; Jones, Nigel C; O'Brien, Terence J; Shaikh, Mohd Farooq (J Alzheimers Dis, 2023)
BACKGROUND: Neuroinflammation is an innate immunological response of the central nervous system that may be induced by a brain insult and chronic neurodegenerative conditions. Recent research has shown that neuroinflammation may contribute to the initiation of Alzheimer's disease (AD) pathogenesis and associated epileptogenesis. OBJECTIVE: This systematic review aimed to investigate the available literature on the shared molecular mechanisms of neuroinflammation in AD and epilepsy. METHODS: The search included in this systematic review was obtained from 5 established databases. A total of 2,760 articles were screened according to inclusion criteria. Articles related to the modulation of the inflammatory biomarkers commonly associated with the progression of AD and epilepsy in all populations were included in this review. RESULTS: Only 7 articles met these criteria and were chosen for further analysis. Selected studies include both in vitro and in vivo research conducted on rodents. Several neuroinflammatory biomarkers were reported to be involved in the cross-talk between AD and epilepsy. CONCLUSION: Neuroinflammation was directly associated with the advancement of AD and epilepsy in populations compared to those with either AD or epilepsy. However, more studies focusing on common inflammatory biomarkers are required to develop standardized monitoring guidelines to prevent the manifestation of epilepsy and delay the progression of AD in patients.
Keywords: Alzheimer Disease; Biomarkers; Brain; Epilepsy; Humans; Neuroinflammatory Diseases

Neuropathology of Anti-Amyloid-β Immunotherapy: A Case Report. - Castellani, Rudolph J; Shanes, Elisheva; McCord, Matthew; Reish, Nicholas J; Flanagan, Margaret E; Mesulam, M-Marsel; Jamshidi, Pouya (J Alzheimers Dis, 2023)
Host responses to anti-amyloid-β (Aβ) antibody therapy are evident in neuroimaging changes and clinical symptoms in a subset of clinical trial subjects receiving such therapy. The pathological basis for the imaging changes and clinical symptoms is not known, nor is the precise mechanism of Aβ clearing. We report the autopsy findings in a 65-year-old woman who received three open label infusions of the experimental anti-Aβ drug lecanemab over about one month. Four days after the last infusion, she was treated with tissue plasminogen activator for acute stroke symptoms and died several days later with multifocal hemorrhage. Neuropathological examination demonstrated histiocytic vasculitis involving blood vessels with cerebral amyloid angiopathy. Fragmentation and phagocytosis of vascular Aβ were present throughout the cerebral cortex. Phagocytosis of parenchymal Aβ plaques was noted. Changes suggestive of Aβ and phosphorylated tau "clearing" were also noted. The findings overall suggest that anti-Aβ treatment stimulated a host response to Aβ, i.e., target engagement. The findings also provide evidence that amyloid-related imaging abnormalities might be indicative of an Aβ phagocytic syndrome within cerebral vasculature and parenchymal brain tissue in some cases.

Pathogenesis, Animal Models, and Drug Discovery of Alzheimer's Disease. - Xia, Zhao-Di; Ma, Ruo-Xin; Wen, Jin-Feng; Zhai, Yu-Fei; Wang, Yu-Qi; Wang, Feng-Yun; Liu, Dan; Zhao, Xiao-Long; Sun, Bao; Jia, Pu; Zheng, Xiao-Hui (J Alzheimers Dis, 2023)
Alzheimer's disease (AD), the most common cause of dementia, is a chronic neurodegenerative disease induced by multiple factors. The high incidence and the aging of the global population make it a growing global health concern with huge implications for individuals and society. The clinical manifestations are progressive cognitive dysfunction and lack of behavioral ability, which not only seriously affect the health and quality of life of the elderly, but also bring a heavy burden to the family and society. Unfortunately, almost all the drugs targeting the classical pathogenesis have not achieved satisfactory clinical effects in the past two decades. Therefore, the present review provides more novel ideas on the complex pathophysiological mechanisms of AD, including classical pathogenesis and a variety of possible pathogenesis that have been proposed in recent years. It will be helpful to find out the key target and the effect pathway of potential drugs and mechanisms for the prevention and treatment of AD. In addition, the common animal models in AD research are outlined and we examine their prospect for the future. Finally, Phase I, II, III, and IV randomized clinical trials or on the market of drugs for AD treatment were searched in online databases (Drug Bank Online 5.0, the U.S. National Library of Medicine, and Alzforum). Therefore, this review may also provide useful information in the research and development of new AD-based drugs.
Keywords: Alzheimer Disease; Animals; Drug Discovery; Models, Animal; Neurodegenerative Diseases; Quality of Life

Pathogenomic Signature and Aberrant Neurogenic Events in Experimental Cerebral Ischemic Stroke: A Neurotranscriptomic-Based Implication for Dementia. - Roshan, Syed Aasish; Elangovan, Gayathri; Gunaseelan, Dharani; Jayachandran, Swaminathan K; Kandasamy, Mahesh; Anusuyadevi, Muthuswamy (J Alzheimers Dis, 2023)
BACKGROUND: Cerebral ischemic stroke is caused due to neurovascular damage or thrombosis, leading to neuronal dysfunction, neuroinflammation, neurodegeneration, and regenerative failure responsible for neurological deficits and dementia. The valid therapeutic targets against cerebral stroke remain obscure. Thus, insight into neuropathomechanisms resulting from the aberrant expression of genes appears to be crucial. OBJECTIVE: In this study, we have elucidated how neurogenesis-related genes are altered in experimental stroke brains from the available transcriptome profiles in correlation with transcriptome profiles of human postmortem stroke brain tissues. METHODS: The transcriptome datasets available on the middle cerebral artery occlusion (MCAo) rat brains were obtained from the Gene Expression Omnibus, National Center for Biotechnology Information. Of the available datasets, 97 samples were subjected to the meta-analysis using the network analyst tool followed by Cytoscape-based enrichment mapping analysis. The key differentially expressed genes (DEGs) were validated and compared with transcriptome profiling of human stroke brains. RESULTS: Results revealed 939 genes are differently expressed in the brains of the MCAo rat model of stroke, in which 30 genes are key markers of neural stem cells, and regulators of neurogenic processes. Its convergence with DEGs from human stroke brains has revealed common targets. CONCLUSION: This study has established a panel of highly important DEGs to signify the potential therapeutic targets for neuroregenerative strategy against pathogenic events associated with cerebral stroke. The outcome of the findings can be translated to mitigate neuroregeneration failure seen in various neurological and metabolic disease manifestations with neurocognitive impairments.
Keywords: Animals; Brain; Dementia; Humans; Infarction, Middle Cerebral Artery; Ischemic Stroke; Neurogenesis; Rats; Stroke

Phonological and Semantic Fluency in Alzheimer's Disease: A Systematic Review and Meta-Analysis. - Olmos-Villaseñor, Rocio; Sepulveda-Silva, Consuelo; Julio-Ramos, Teresa; Fuentes-Lopez, Eduardo; Toloza-Ramirez, David; Santibañez, Rodrigo A; Copland, David A; Mendez-Orellana, Carolina (J Alzheimers Dis, 2023)
BACKGROUND: Semantic and Phonological fluency (SF and PF) are routinely evaluated in patients with Alzheimer's disease (AD). There are disagreements in the literature regarding which fluency task is more affected while developing AD. Most studies focus on SF assessment, given its connection with the temporoparietal amnesic system. PF is less reported, it is related to working memory, which is also impaired in probable and diagnosed AD. Differentiating between performance on these tasks might be informative in early AD diagnosis, providing an accurate linguistic profile. OBJECTIVE: Compare SF and PF performance in healthy volunteers, volunteers with probable AD, and patients with AD diagnosis, considering the heterogeneity of age, gender, and educational level variables. METHODS: A total of 8 studies were included for meta-analysis, reaching a sample size of 1,270 individuals (568 patients diagnosed with AD, 340 with probable AD diagnosis, and 362 healthy volunteers). RESULTS: The three groups consistently performed better on SF than PF. When progressing to a diagnosis of AD, we observed a significant difference in SF and PF performance across our 3 groups of interest (p = 0.04). The age variable explained a proportion of this difference in task performance across the groups, and as age increases, both tasks equally worsen. CONCLUSION: The performance of SF and PF might play a differential role in early AD diagnosis. These tasks rely on partially different neural bases of language processing. They are thus worth exploring independently in diagnosing normal aging and its transition to pathological stages, including probable and diagnosed AD.
Keywords: Alzheimer Disease; Humans; Linguistics; Neuropsychological Tests; Semantics; Verbal Behavior

The Potential Role of Selection Bias in the Association Between Coronary Atherosclerosis and Cognitive Impairment. - Yahagi-Estevam, Maristella; Farias-Itao, Daniela Souza; Leite, Renata Elaine Paraizo; Rodriguez, Roberta Diehl; Pasqualucci, Carlos Augusto; Nitrini, Ricardo; Jacob-Filho, Wilson; Power, Melinda C; Suemoto, Claudia Kimie (J Alzheimers Dis, 2023)
BACKGROUND: Coronary atherosclerosis assessed in vivo was associated with cognitive impairment; however, conflicting findings have been reported in autopsy samples. OBJECTIVE: Our aims were to assess the association between atherosclerotic stenosis in the coronary arteries and cognitive impairment and to investigate the possibility of selection bias in an autopsy study. METHODS: Coronary arteries were collected, and the largest luminal stenosis was measured. Sociodemographic, clinical, and cognitive information were reported by a reliable next-of-kin. The association was tested using logistic and linear regressions adjusted for sociodemographic and clinical variables. We restricted the sample to individuals that were born in 1935 or earlier and stratified the analysis by cause of death to investigate the role of selection bias. RESULTS: In 253 participants (mean age = 78.0±8.5 years old, 48% male), stenosis was not associated with cognitive impairment (OR = 0.85, 95% CI = 0.69; 1.06, p = 0.15). In individuals who were born before 1936 in the absence of cardiovascular disease as the cause of death, greater stenosis was associated with cognitive impairment (OR = 4.02, 95% CI = 1.39; 11.6, p = 0.01). On the other hand, this association was not present among those born in 1935 or earlier who died of cardiovascular diseases (OR = 0.83, 95% CI = 0.60; 1.16, p = 0.28). CONCLUSION: We found that higher coronary stenosis was associated with cognitive impairment only in individuals born in 1935 or earlier and who had not died from cardiovascular diseases. Selection bias may be an important issue when investigating risk factors for chronic degenerative diseases in older individuals using autopsy samples.

Precision Medicine Approach to Alzheimer's Disease: Rationale and Implications. - Bredesen, Dale E; Toups, Kat; Hathaway, Ann; Gordon, Deborah; Chung, Henrianna; Raji, Cyrus; Boyd, Alan; Hill, Benjamin D; Hausman-Cohen, Sharon; Attarha, Mouna; Chwa, Won Jong; Kurakin, Alexei; et al. (J Alzheimers Dis, 2023)
The neurodegenerative disease field has enjoyed extremely limited success in the development of effective therapeutics. One potential reason is the lack of disease models that yield accurate predictions and optimal therapeutic targets. Standard clinical trials have pre-determined a single treatment modality, which may be unrelated to the primary drivers of neurodegeneration. Recent proof-of-concept clinical trials using a precision medicine approach suggest a new model of Alzheimer's disease (AD) as a chronic innate encephalitis that creates a network insufficiency. Identifying and addressing the multiple potential contributors to cognitive decline for each patient may represent a more effective strategy. Here we review the rationale for a precision medicine approach in prevention and treatment of cognitive decline associated with AD. Results and implications from recent proof-of-concept clinical trials are presented. Randomized controlled trials, with much larger patient numbers, are likely to be significant to establishing precision medicine protocols as a standard of care for prevention and treatment of cognitive decline. Furthermore, combining this approach with the pharmaceutical approach offers the potential for enhanced outcomes. However, incorporating precision medicine approaches into everyday evaluation and care, as well as future clinical trials, would require fundamental changes in trial design, IRB considerations, funding considerations, laboratory evaluation, personalized treatment plans, treatment teams, and ultimately in reimbursement guidelines. Nonetheless, precision medicine approaches to AD, based on a novel model of AD pathophysiology, offer promise that has not been realized to date with monotherapeutic approaches.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Neurodegenerative Diseases; Precision Medicine

Resveratrol Mediated Regulation of Hippocampal Neuroregenerative Plasticity via SIRT1 Pathway in Synergy with Wnt Signaling: Neurotherapeutic Implications to Mitigate Memory Loss in Alzheimer's Disease. - Surya, Kumar; Manickam, Nivethitha; Jayachandran, Kesavan Swaminathan; Kandasamy, Mahesh; Anusuyadevi, Muthuswamy (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is a major form of dementia. Abnormal amyloidogenic event-mediated degeneration of cholinergic neurons in the cognitive centers of the brain has been attributed to neuropathological sequelae and behavioral deficits in AD. Besides, impaired adult neurogenesis in the hippocampus has experimentally been realized as an underlying cause of dementia regardless of neurodegeneration. Therefore, nourishing the neurogenic process in the hippocampus has been considered an effective therapeutic strategy to mitigate memory loss. In the physiological state, the Wnt pathway has been identified as a potent mitogenic generator in the hippocampal stem cell niche. However, downstream components of Wnt signaling have been noticed to be downregulated in AD brains. Resveratrol (RSV) is a potent Sirtuin1 (SIRT1) enhancer that facilitates neuroprotection and promotes neurogenesis in the hippocampus of the adult brain. While SIRT1 is an important positive regulator of Wnt signaling, ample reports indicate that RSV treatment strongly mediates the fate determination of stem cells through Wnt signaling. However, the possible therapeutic roles of RSV-mediated SIRT1 enhancement on the regulation of hippocampal neurogenesis and reversal of memory loss through the Wnt signaling pathway have not been addressed yet. Taken together, this review describes RSV-mediated effects on the regulation of hippocampal neurogenesis via the activation of SIRT1 in synergy with the Wnt signaling. Further, the article emphasizes a hypothesis that RSV treatment can provoke the activation of quiescent neural stem cells and prime their neurogenic capacity in the hippocampus via Wnt signaling in AD.
Keywords: Alzheimer Disease; Amnesia; Hippocampus; Humans; Neurogenesis; Resveratrol; Sirtuin 1; Wnt Signaling Pathway

Safety, Feasibility, and Potential Clinical Efficacy of 40 Hz Invisible Spectral Flicker versus Placebo in Patients with Mild-to-Moderate Alzheimer's Disease: A Randomized, Placebo-Controlled, Double-Blinded, Pilot Study. - Agger, Mikkel Pejstrup; Danielsen, Else Rubæk; Carstensen, Marcus Schultz; Nguyen, N Mai; Horning, Maibritt; Henney, Mark Alexander; Jensen, Christopher Boe Ravn; Baandrup, Anders Ohlhues; Kjær, Troels Wesenberg; Madsen, Kristoffer Hougaard; Miskowiak, Kamilla; Petersen, Paul Michael; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Recent studies suggested induction of 40 Hz neural activity as a potential treatment for Alzheimer's disease (AD). However, prolonged exposure to flickering light raises adherence and safety concerns, encouraging investigation of tolerable light stimulation protocols. OBJECTIVE: To investigate the safety, feasibility, and exploratory measures of efficacy. METHODS: This two-stage randomized placebo-controlled double-blinded clinical trial, recruited first cognitive healthy participants (n = 3/2 active/placebo), and subsequently patients with mild-to-moderate AD (n = 5/6, active/placebo). Participants were randomized 1:1 to receive either active intervention with 40 Hz Invisible Spectral Flicker (ISF) or placebo intervention with color and intensity matched non-flickering white light. RESULTS: Few and mild adverse events were observed. Adherence was above 86.1% of intended treatment days, with participants remaining in front of the device for >51.3 min (60 max) and directed gaze >34.9 min. Secondary outcomes of cognition indicate a tendency towards improvement in the active group compared to placebo (mean: -2.6/1.5, SD: 6.58/6.53, active/placebo) at week 6. Changes in hippocampal and ventricular volume also showed no tendency of improvement in the active group at week 6 compared to placebo. At week 12, a potential delayed effect of the intervention was seen on the volume of the hippocampus in the active group compared to placebo (mean: 0.34/-2.03, SD: 3.26/1.18, active/placebo), and the ventricular volume active group (mean: -0.36/2.50, SD: 1.89/2.05, active/placebo), compared to placebo. CONCLUSION: Treatment with 40 Hz ISF offers no significant safety or adherence concerns. Potential impact on secondary outcomes must be tested in larger scale clinical trials.
Keywords: Alzheimer Disease; Cognition; Double-Blind Method; Feasibility Studies; Humans; Pilot Projects; Treatment Outcome

Superior Global Cognition in Oldest-Old Is Associated with Resistance to Neurodegenerative Pathologies: Results from The 90+ Study. - Biswas, Roshni; Kawas, Claudia; Montine, Thomas J; Bukhari, Syed A; Jiang, Luohua; Corrada, Maria M (J Alzheimers Dis, 2023)
BACKGROUND: Some oldest-old individuals can maintain superior cognition despite advanced age. Little is known about the neuropathological changes in the brains of oldest-old superior cognitive performers. OBJECTIVE: Our objective was to examine the associations between Alzheimer's disease (AD) and non-AD neuropathologic features in relation to superior cognitive performance in oldest-old individuals. METHODS: We analyzed brain autopsy data from 102 participants with normal cognition from The 90+ Study. Superior global cognitive performers (SGCP) were defined as having Mini-Mental State Examination (MMSE) score ≥28 in the last visit 12 to 2 months before death. To examine the associations between individual and multiple comorbid neuropathologic features with SGCP status we used multiple logistic regression models adjusting for age, sex, and education. RESULTS: Alzheimer's disease neuropathological change (ADNC) and low levels of vascular pathologic change were not associated with superior cognition. In contrast, participants with limbic (OR = 8.37; 95% CI: 1.48-47.44) and neocortical (OR = 10.80;95% CI: 1.03-113.82) Lewy body disease (LBD), or with hippocampal sclerosis (HS) (OR = 5.28; 95% CI: 1.10-25.47) were more likely to be non-SGCP. High total burden of multiple comorbid neuropathologic features was associated with a lower likelihood of being SGCP. CONCLUSION: Oldest-old superior cognitive performers were resilient to ADNC and low levels of vascular pathologic change and were resistant to non-AD neurodegenerative changes and multiple comorbid neuropathologic features. Understanding the factors underlying the ability of superior cognitive performers to resist these changes might provide useful insights on maintenance of superior cognition despite advanced age.

Validation of a Multivariate Prediction Model of the Clinical Progression of Alzheimer's Disease in a Community-Dwelling Multiethnic Cohort. - Stallard, Eric; Kociolek, Anton; Jin, Zhezhen; Ryu, Hyunnam; Lee, Seonjoo; Cosentino, Stephanie; Zhu, Carolyn; Gu, Yian; Fernandez, Kayri; Hernandez, Michelle; Kinosian, Bruce; Stern, Yaakov (J Alzheimers Dis, 2023)
BACKGROUND: The major aims of the three Predictors Studies have been to further our understanding of Alzheimer's disease (AD) progression sufficiently to predict the length of time from disease onset to major disease outcomes in individual patients with AD. OBJECTIVES: To validate a longitudinal Grade of Membership (L-GoM) prediction algorithm developed using clinic-based, mainly white patients from the Predictors 2 Study in a statistically representative community-based sample of Hispanic (N = 211) and non-Hispanic (N = 62) older adults (with 60 males and 213 females) from the Predictors 3 Study and extend the algorithm to mild cognitive impairment (MCI). METHODS: The L-GoM model was applied to data collected at the initial Predictors 3 visit for 150 subjects with AD and 123 with MCI. Participants were followed annually for up to seven years. Observed rates of survival and need for full-time care (FTC) were compared to those predicted by the algorithm. RESULTS: Initial MCI/AD severity in Predictors 3 was substantially higher than among clinic-based AD patients enrolled at the specialized Alzheimer's centers in Predictors 2. The observed survival and need for FTC followed the L-GoM model trajectories in individuals with MCI or AD, except for N = 32 subjects who were initially diagnosed with AD but reverted to a non-AD diagnosis on follow-up. CONCLUSION: These findings indicate that the L-GoM model is applicable to community-dwelling, multiethnic older adults with AD. They extend the use of the model to the prediction of outcomes for MCI. They also justify release of our L-GoM calculator at this time.

Association Between Plasma Biomarkers of Amyloid, Tau, and Neurodegeneration with Cerebral Microbleeds. - McCarter, Stuart J; Lesnick, Timothy G; Lowe, Val J; Rabinstein, Alejandro A; Przybelski, Scott A; Algeciras-Schimnich, Alicia; Ramanan, Vijay K; Jack, Clifford R; Petersen, Ronald C; Knopman, David S; Boeve, Bradley F; Kantarci, Kejal; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Cerebral microbleeds (CMBs) are a common vascular pathology associated with future intracerebral hemorrhage. Plasma biomarkers of amyloid, tau, and neurodegeneration may provide a screening avenue to identify those with CMBs, but evidence is conflicting. OBJECTIVE: To determine the association between plasma biomarkers (Aβ40, Aβ42, t-tau, p-tau181, p-tau217, neurofilament light chain (NfL)) and CMBs in a population-based study of aging and whether these biomarkers predict higher signal on Aβ-PET imaging in patients with multiple CMBs. METHODS: 712 participants from the Mayo Clinic Study of Aging with T2 * GRE MRI and plasma biomarkers were included. Biomarkers were analyzed utilizing Simoa (Aβ40, Aβ42, t-tau, NfL) or Meso Scale Discovery (p-tau181, p-tau217) platforms. Cross-sectional associations between CMBs, plasma biomarkers and Aβ-PET were evaluated using hurdle models and multivariable regression models. RESULTS: Among the 188 (26%) individuals with≥1 CMB, a lower plasma Aβ42/Aβ40 ratio was associated with more CMBs after adjusting for covariables (IRR 568.5 95% CI 2.8-116,127). No other biomarkers were associated with risk or number CMBs. In 81 individuals with≥2 CMBs, higher plasma t-tau, p-tau181, and p-tau217 all were associated with higher Aβ-PET signal, with plasma p-tau217 having the strongest predictive value (r2 0.603, AIC -53.0). CONCLUSION: Lower plasma Aβ42/Aβ40 ratio and higher plasma p-tau217 were associated with brain amyloidosis in individuals with CMBs from the general population. Our results suggest that in individuals with multiple CMBs and/or lobar intracranial hemorrhage that a lower plasma Aβ42/Aβ40 ratio or elevated p-tau217 may indicate underlying cerebral amyloid angiopathy.

Association Between Serum Vitamins and the Risk of Alzheimer's Disease in Chinese Population. - Liu, Xi-Xi; Wu, Peng-Fei; Liu, Ying-Zi; Jiang, Ya-Ling; Wan, Mei-Dan; Xiao, Xue-Wen; Yang, Qi-Jie; Jiao, Bin; Liao, Xin-Xin; Wang, Jun-Ling; Liu, Shao-Hui; Zhang, Xuewei; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Alzheimer's disease (AD) is a chronic and fatal neurodegenerative disease; accumulating evidence suggests that vitamin deficiency is associated with the risk of AD. However, studies attempting to elucidate the relationship between vitamins and AD varied widely. OBJECTIVE: This study aimed to investigate the relationship between serum vitamin levels and AD in a cohort of the Chinese population. METHODS: A total of 368 AD patients and 574 healthy controls were recruited in this study; serum vitamin A, B1, B6, B9, B12, C, D, and E were measured in all participants. RESULTS: Compared with the controls, vitamin B2, B9, B12, D, and E were significantly reduced in AD patients. Lower levels of vitamin B2, B9, B12, D, and E were associated with the risk of AD. After adjusting for age and gender, low levels of vitamin B2, B9, and B12 were still related to the risk of AD. In addition, a negative correlation was determined between vitamin E concentration and Activity of Daily Living Scale score while no significant association was found between serum vitamins and age at onset, disease duration, Mini-Mental State Examination, and Neuropsychiatric Inventory Questionnaire score. CONCLUSION: We conclude that lower vitamin B2, B9, B12, D, and E might be associated with the risk of AD, especially vitamin B2, B9, and B12. And lower vitamin E might be related to severe ability impairment of daily activities.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Case-Control Studies; China; Female; Folic Acid; Humans; Logistic Models; Male; Mental Status and Dementia Tests; Middle Aged; Riboflavin; Risk; Vitamin B 12; Vitamin D; Vitamin E

Association of Alzheimer's Disease with COVID-19 Susceptibility and Severe Complications: A Nationwide Cohort Study. - Chung, Seok Jong; Chang, Yoonkyung; Jeon, Jimin; Shin, Jae Il; Song, Tae-Jin; Kim, Jinkwon (J Alzheimers Dis, 2022)
BACKGROUND: Identification of patients at high susceptibility and high risk of developing serious complications related to coronavirus disease 2019 (COVID-19) infection is clinically important in the face of the COVID-19 pandemic. OBJECTIVE: To investigate whether patients with Alzheimer's disease (AD) are more susceptible to COVID-19 infection and whether they have a higher risk of developing serious complications. METHODS: We retrospectively reviewed the Korean nationwide population-based COVID-19 dataset for participants who underwent real-time reverse transcription polymerase chain reaction assays for COVID-19 between January 1 and June 4, 2020. A 1 : 3 ratio propensity score matching and binary logistic regression analysis were performed to investigate the association between AD and the susceptibility or severe complications (i.e., mechanical ventilation, intensive care unit admission, or death) of COVID-19. RESULTS: Among 195,643 study participants, 5,725 participants had AD and 7,334 participants were diagnosed with COVID-19. The prevalence of participants testing positive for COVID-19 did not differ according to the presence of AD (p = 0.234). Meanwhile, AD was associated with an increased risk of severe COVID-19 complications (OR 2.25 [95% CI 1.54-3.28]). Secondary outcome analyses showed that AD patients had an increased risk for mortality (OR 3.09 [95% CI 2.00-4.78]) but were less likely to receive mechanical ventilation (OR 0.42 [95% CI 0.20-0.87]). CONCLUSION: AD was not associated with increased susceptibility to COVID-19 infection, but was associated with severe COVID-19 complications, especially with mortality. Early diagnosis and active intervention are necessary for patients with AD suspected COVID-19 infection.
Keywords: Alzheimer Disease; Cohort Studies; COVID-19; Humans; Pandemics; Retrospective Studies; SARS-CoV-2

Association of Carotid Intima Media Thickening with Future Brain Region Specific Amyloid-β Burden. - Baradaran, Hediyeh; Peloso, Gina M; Polak, Joseph F; Killiany, Ronald J; Ghosh, Saptaparni; DeCarli, Charles S; Thibault, Emma G; Sperling, Reisa A; Johnson, Keith A; Beiser, Alexa; Romero, Jose R; Seshadri, Sudha (J Alzheimers Dis, 2022)
BACKGROUND: Carotid atherosclerosis is associated with cognitive impairment and dementia, though there is limited evidence of a direct link between carotid disease and amyloid-β (Aβ) burden. OBJECTIVE: We studied the association of baseline and progressive carotid intima media thickness (CIMT) with Aβ on 11C-Pittsburgh Compound B (PiB) to determine if those with carotid atherosclerosis would have higher Aβ burden. METHODS: We studied 47 participants from the Framingham Offspring cohort with carotid ultrasounds measuring CIMT at their 6th clinic examination (aged 49.5±5.7 years) and an average of 9.6 years later, and PiB imaging measuring Aβ on average 22.1 years post baseline. We used multivariate linear regression analyses to relate baseline, follow-up, mean, and progression of internal carotid artery (ICA) and common carotid artery (CCA) CIMT to Aβ in brain regions associated with Alzheimer's disease (AD) and related dementias (ADRD), adjusting for age, sex, and other vascular risk factors. RESULTS: Participants with higher mean ICA IMT had more Aβ in the precuneus (beta±standard error [β±SE]: 0.466±0.171 mm, p = 0.01) and the frontal, lateral, and retrosplenial regions (β±SE: 0.392±0.164 mm, p = 0.022) after adjusting for age, sex, vascular risk factors, and medication use. We did not find an association between any CCA IMT measures and Aβ or progression of ICA or CCA IMT and Aβ. CONCLUSION: Carotid atherosclerosis, as measured by ICA IMT, is associated with increased Aβ burden later in life. These findings support a link between vascular disease and AD/ADRD pathophysiology.

Association of Cholinergic Basal Forebrain Volume and Functional Connectivity with Markers of Inflammatory Response in the Alzheimer's Disease Spectrum. - Teipel, Stefan J; Dyrba, Martin; Ballarini, Tommaso; Brosseron, Frederic; Bruno, Davide; Buerger, Katharina; Cosma, Nicoleta-Carmen; Dechent, Peter; Dobisch, Laura; Düzel, Emrah; Ewers, Michael; Fliessbach, Klaus; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Inflammation has been described as a key pathogenic event in Alzheimer's disease (AD), downstream of amyloid and tau pathology. Preclinical and clinical data suggest that the cholinergic basal forebrain may moderate inflammatory response to different pathologies. OBJECTIVE: To study the association of cholinergic basal forebrain volume and functional connectivity with measures of neuroinflammation in people from the AD spectrum. METHODS: We studied 261 cases from the DELCODE cohort, including people with subjective cognitive decline, mild cognitive impairment, AD dementia, first degree relatives, and healthy controls. Using Bayesian ANCOVA, we tested associations of MRI indices of cholinergic basal forebrain volume and functional connectivity with cerebrospinal fluid (CSF) levels of sTREM2 as a marker of microglia activation, and serum levels of complement C3. Using Bayesian elastic net regression, we determined associations between basal forebrain measures and a large inflammation marker panel from CSF and serum. RESULTS: We found anecdotal to moderate evidence in favor of the absence of an effect of basal forebrain volume and functional connectivity on CSF sTREM2 and serum C3 levels both in Aβ42/ptau-positive and negative cases. Bayesian elastic net regression identified several CSF and serum markers of inflammation that were associated with basal forebrain volume and functional connectivity. The effect sizes were moderate to small. CONCLUSION: Our data-driven analyses generate the hypothesis that cholinergic basal forebrain may be involved in the neuroinflammation response to Aβ42 and phospho-tau pathology in people from the AD spectrum. This hypothesis needs to be tested in independent samples.
Keywords: Aged; Alzheimer Disease; Basal Forebrain; Biomarkers; Cholinergic Agents; Cognitive Dysfunction; Cohort Studies; Female; Humans; Inflammation; Magnetic Resonance Imaging; Male

Associations Between Brainstem Volume and Alzheimer's Disease Pathology in Middle-Aged Individuals of the Framingham Heart Study. - Jacobs, Heidi I L; O'Donnell, Adrienne; Satizabal, Claudia L; Lois, Cristina; Kojis, Daniel; Hanseeuw, Bernard J; Thibault, Emma; Sanchez, Justin S; Buckley, Rachel F; Yang, Qiong; DeCarli, Charles; Killiany, Ron; et al. (J Alzheimers Dis, 2022)
The brainstem is among the first regions to accumulate Alzheimer's disease (AD)-related hyperphosphorylated tau pathology during aging. We aimed to examine associations between brainstem volume and neocortical amyloid-β or tau pathology in 271 middle-aged clinically normal individuals of the Framingham Heart Study who underwent MRI and PET imaging. Lower volume of the medulla, pons, or midbrain was associated with greater neocortical amyloid burden. No associations were detected between brainstem volumes and tau deposition. Our results support the hypothesis that lower brainstem volumes are associated with initial AD-related processes and may signal preclinical AD pathology.

Bifidobacterium breve MCC1274 Supplementation Increased the Plasma Levels of Metabolites with Potential Anti-Oxidative Activity in APP Knock-In Mice. - Ohno, Kazuya; Abdelhamid, Mona; Zhou, Chunyu; Jung, Cha-Gyun; Michikawa, Makoto (J Alzheimers Dis, 2022)
BACKGROUND: We previously reported the effects of a probiotic strain, Bifidobacterium breve MCC1274, in improving cognitive function in preclinical and clinical studies. Recently, we demonstrated that supplementation of this strain led to decreased amyloid-β production, attenuated microglial activation, and suppressed inflammation reaction in the brain of APP knock-in (AppNL - G - F) mice. OBJECTIVE: In this study, we investigated the plasma metabolites to reveal the mechanism of action of this probiotic strain in this Alzheimer's disease (AD)-like model. METHODS: Three-month-old mice were orally supplemented with B. breve MCC1274 or saline for four months and their plasma metabolites were comprehensively analyzed using CE-FTMS and LC-TOFMS. RESULTS: Principal component analysis showed a significant difference in the plasma metabolites between the probiotic and control groups (PERMANOVA, p = 0.03). The levels of soy isoflavones (e.g., genistein) and indole derivatives of tryptophan (e.g., 5-methoxyindoleacetic acid), metabolites with potent anti-oxidative activities were significantly increased in the probiotic group. Moreover, there were increased levels of glutathione-related metabolites (e.g., glutathione (GSSG)_divalent, ophthalmic acid) and TCA cycle-related metabolites (e.g., 2-Oxoglutaric acid, succinic acid levels) in the probiotic group. Similar alternations were observed in the wild-type mice by the probiotic supplementation. CONCLUSION: These results suggest that the supplementation of B. breve MCC1274 enhanced the bioavailability of potential anti-oxidative metabolites from the gut and addressed critical gaps in our understanding of the gut-brain axis underlying the mechanisms of the probiotic action of this strain in the improvement of cognitive function.

Cancer and Vascular Comorbidity Effects on Dementia Risk and Neuropathology in the Oldest-Old. - Lachner, Christian; Day, Gregory S; Camsari, Gamze Balci; Kouri, Naomi; Ertekin-Taner, Nilufer; Boeve, Bradley F; Labuzan, Sydney A; Lucas, John A; Thompson, E Aubrey; Siddiqui, Habeeba; Crook, Julia E; Cabrera-Rodriguez, Janisse N; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Dementia, vascular disease, and cancer increase with age, enabling complex comorbid interactions. Understanding vascular and cancer contributions to dementia risk and neuropathology in oldest-old may improve risk modification and outcomes. OBJECTIVE: Investigate vascular and cancer contributions to dementia and neuropathology in oldest-old. METHODS: Longitudinal clinicopathologic study of prospectively followed Mayo Clinic participants dying≥95 years-old who underwent autopsy. Participants were stratified by dementia status and compared according to demographics, vascular risk factors, cancer, and neuropathology. RESULTS: Participants (n = 161; 83% female; 99% non-Hispanic whites)≥95 years (95-106 years-old) with/without dementia did not differ based on demographics. APOE ɛ2 frequency was higher in no dementia (20/72 [28%]) versus dementia (11/88 [12%]; p = 0.03), but APOE ɛ4 frequency did not differ. Coronary artery disease was more frequent in no dementia (31/72 [43%]) versus dementia (23/89 [26%]; p = 0.03) associated with 56% lower dementia odds (odds ratio [OR] = 0.44 [confidence interval (CI) = 0.19-0.98]; p = 0.04) and fewer neuritic/diffuse plaques. Diabetes had an 8-fold increase in dementia odds (OR = 8.42 [CI = 1.39-163]; p = 0.02). Diabetes associated with higher cerebrovascular disease (Dickson score; p = 0.05). Cancer associated with 63% lower dementia odds (OR = 0.37 [CI = 0.17-0.78]; p <  0.01) and lower Braak stage (p = 0.01). CONCLUSION: Cancer exposure in the oldest-old was associated with lower odds of dementia and tangle pathology, whereas history of coronary artery disease was associated with lower odds of dementia and amyloid-β plaque pathology. History of diabetes mellitus was associated with increased odds of dementia and cerebrovascular disease pathology. Cancer-related mechanisms and vascular risk factor reduction strategies may alter dementia risk and neuropathology in oldest-old.

Cerebrospinal Fluid Sphingomyelins in Alzheimer's Disease, Neurodegeneration, and Neuroinflammation. - Morrow, Autumn; Panyard, Daniel J; Deming, Yuetiva K; Jonaitis, Erin; Dong, Ruocheng; Vasiljevic, Eva; Betthauser, Tobey J; Kollmorgen, Gwendlyn; Suridjan, Ivonne; Bayfield, Anna; Van Hulle, Carol A; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Sphingomyelin (SM) levels have been associated with Alzheimer's disease (AD), but the association direction has been inconsistent and research on cerebrospinal fluid (CSF) SMs has been limited by sample size, breadth of SMs examined, and diversity of biomarkers available. OBJECTIVE: Here, we seek to build on our understanding of the role of SM metabolites in AD by studying a broad range of CSF SMs and biomarkers of AD, neurodegeneration, and neuroinflammation. METHODS: Leveraging two longitudinal AD cohorts with metabolome-wide CSF metabolomics data (n = 502), we analyzed the relationship between the levels of 12 CSF SMs, and AD diagnosis and biomarkers of pathology, neurodegeneration, and neuroinflammation using logistic, linear, and linear mixed effects models. RESULTS: No SMs were significantly associated with AD diagnosis, mild cognitive impairment, or amyloid biomarkers. Phosphorylated tau, neurofilament light, α-synuclein, neurogranin, soluble triggering receptor expressed on myeloid cells 2, and chitinase-3-like-protein 1 were each significantly, positively associated with at least 5 of the SMs. CONCLUSION: The associations between SMs and biomarkers of neurodegeneration and neuroinflammation, but not biomarkers of amyloid or diagnosis of AD, point to SMs as potential biomarkers for neurodegeneration and neuroinflammation that may not be AD-specific.

Characterization of Mild Cognitive Impairment and Dementia among Community-Dwelling Mexican Americans and Non-Hispanic Whites. - O'Bryant, Sid E; Petersen, Melissa; Hall, James; Johnson, Leigh A; Barber, Robert; Phillips, Nicole; Braskie, Meredith N; Yaffe, Kristine; Rissman, Robert; Toga, Arthur (J Alzheimers Dis, 2022)
BACKGROUND: Despite tremendous advancements in the field, our understanding of mild cognitive impairment (MCI) and Alzheimer's disease (AD) among Mexican Americans remains limited. OBJECTIVE: The aim of this study was to characterize MCI and dementia among Mexican Americans and non-Hispanic whites. METHODS: Baseline data were analyzed from n = 1,705 (n = 890 Mexican American; n = 815 non-Hispanic white) participants enrolled in the Health and Aging Brain Study-Health Disparities (HABS-HD). RESULTS: Among Mexican Americans, age (OR = 1.07), depression (OR = 1.09), and MRI-based neurodegeneration (OR = 0.01) were associated with dementia, but none of these factors were associated with MCI. Among non-Hispanic whites, male gender (OR = 0.33), neighborhood deprivation (OR = 1.34), depression (OR = 1.09), and MRI-based neurodegeneration (OR = 0.03) were associated with MCI, while depression (OR = 1.09) and APOEɛ4 genotype (OR = 4.38) were associated with dementia. CONCLUSION: Findings from this study revealed that the demographic, clinical, sociocultural and biomarker characteristics of MCI and dementia are different among Mexican Americans as compared to non-Hispanic whites.

Clinical Utility of Cerebrospinal Fluid Aβ42 and Tau Measures in Diagnosing Mild Cognitive Impairment in Early Onset Dementia. - Hosseini, Akram A; Brown, Thomas; Mannino, Luca; Gran, Bruno; Junaid, Kehinde; Mukaetova-Ladinska, Elizabeta B (J Alzheimers Dis, 2022)
BACKGROUND: The differentiation of a preclinical or prodromal Alzheimer's disease (AD) is challenging particularly in patients with early onset Alzheimer's or related dementias (EOARD). We report our experience on diagnostic lumbar puncture to diagnose EOARD at a tertiary neurocognitive referral center in Nottingham, England from March 2018 to October 2020. OBJECTIVE: To assess amyloid-β42 (Aβ42), total tau, and Thr181-phosphorylated tau (p-tau) measurements in the cerebrospinal fluid (CSF) in patients with mild cognitive impairment (MCI) and in relation to their follow-up cognitive performance. METHODS: Thirty participants aged 32-68 years old (mean 59 years; 57% female) were included. Clinical diagnosis was based on clinical presentation, neurocognitive profile, neuroradiological features (MRI, FDG-PET CT) and CSF Aβ42, total tau, and p-tau measurements. RESULTS: Patients with MCI who progressed to AD (prodromal AD) had significantly higher CSF total (797.63 pg/ml) and p-tau (82.31 pg/ml), and lower Aβ42 levels (398.94 pg/ml) in comparison to their counterparts with stable MCI (total tau 303.67 pg/ml, p-tau 43.56 pg/ml, Aβ42 873.44 pg/ml) (p <  0.01 for CSF total and p-tau measures and p <  0.0001 for CSF Aβ42 measures). None of the CSF biomarkers correlated with any of the cognitive performance measures. Principal component analysis confirmed that the clinical diagnosis of MCI secondary to AD, namely prodromal AD (as per NIA-AA criteria) in younger adults, was associated with decreased CSF Aβ42. CONCLUSION: In early onset AD, low levels of CSF Aβ42 appear to be more sensitive than total and p-tau measures in differentiating AD MCI from other forms of dementia. Further work on larger samples of EOARD in clinical practice will address the cost effectiveness of making an earlier diagnosis.

Cognitive Function Associated with Gut Microbial Abundance in Sucrose and S-Adenosyl-L-Methionine (SAMe) Metabolic Pathways. - Jeong, Sohyun; Huang, Li-Kai; Tsai, Ming-Ju; Liao, Yi-Tyng; Lin, Yow-Sien; Hu, Chaur-Jong; Hsu, Yi-Hsiang (J Alzheimers Dis, 2022)
BACKGROUND: Differential abundance of gut microbiota has found to be associated with Alzheimer's disease (AD). However, the relative abundance of gut microbiota between dementia and mild cognitive impairment (MCI) in AD is not well studied. OBJECTIVE: We attempted to identify differentially enriched gut microbes and their metabolic pathways in AD patients with dementia comparing to AD patients with MCI. METHODS: Fecal samples were collected at Shuang Ho Hospital, Taipei Medical University, Taiwan and analyzed by whole metagenomic sequencing technique. For normal controls without AD (NC), 16S rRNA sequencing was obtained from the Taiwan Microbiome Database. A total of 48 AD (38 dementia and 10 MCI defined by cognitive function scores) and 50 NC were included. Microbiome alpha and beta diversities were estimated. Differentially enriched microbes were identified with HAllA, MaAsLin, DESeq2, and LEfSe statistical modeling approaches. RESULTS: We found significantly increased abundance of Firmicutes but decreased abundance of Bacteroidetes at phylum level in AD compared to NC. In AD patients, cognitive function scores were negatively associated with abundance of Blautia hydrogenotrophica (Firmicutes), Anaerotruncus colihominis (Firmicutes), and Gordonibacter pamelaeae (Actinobacteria). In addition, microbial abundance in the sucrose and S-Adenosyl-L-methionine (SAMe) metabolic pathways was more enriched in AD with MCI than AD with dementia and significantly associated with higher cognitive function scores. CONCLUSION: Gut microbe community diversity was similar in AD patients regardless of MCI or dementia status. However, differential analyses probed in lower-level taxa and metabolic pathways suggested that specific gut microbes in Firmicutes and Actinobacteria might involve in cognitive decline.
Keywords: Alzheimer Disease; Cognition; Cognitive Dysfunction; Gastrointestinal Microbiome; Humans; Metabolic Networks and Pathways; RNA, Ribosomal, 16S; S-Adenosylmethionine; Sucrose

The Correlation of Tau Levels with Blood Monocyte Count in Patients with Alzheimer's Disease. - Sun, Hao-Lun; Zhou, Fa-Ying; Chen, Dong-Wan; Tan, Cheng-Rong; Zeng, Gui-Hua; Liu, Yu-Hui; Wang, Jun; Bu, Xian-Le; Wang, Yan-Jiang; Li, Hui-Yun; Jin, Wang-Sheng (J Alzheimers Dis, 2022)
BACKGROUND: Recent studies have shown that monocytes can phagocytize the tau protein, which may ameliorate tau-type pathology in Alzheimer's disease (AD). However, there are few clinical studies on the relationship between monocytes and tau-type pathology in AD patients. OBJECTIVE: We aimed to explore changes in peripheral monocytes and their association with tau protein in AD patients. METHODS: A total of 127 clinically diagnosed AD patients and 100 age- and sex-matched cognitively normal controls were recruited for analysis of the correlation of plasma tau levels with the blood monocyte count. Cerebrospinal fluid (CSF) samples from 46 AD patients and 88 controls were further collected to analyze the correlation of CSF tau and amyloid-β (Aβ) levels with the blood monocyte count. 105 clinically diagnosed mild cognitive impairment (MCI) patients and 149 age- and sex-matched cognitively normal controls were recruited from another cohort for verification. RESULTS: Compared to normal controls, AD patients showed a significant reduction in the blood monocyte count. In addition, the monocyte count of AD patients was negatively correlated with CSF t-tau and p-tau levels but not with plasma tau levels. In normal people, monocyte count lack correlation with tau levels both in plasma and CSF. Monocyte count were not correlated with CSF Aβ levels in either group but were negatively correlated with CSF tau/Aβ42 levels in the AD group. We had further verified the correlations of monocyte count with CSF tau levels in another cohort. CONCLUSION: This study suggests that monocytes may play an important role in the clearance of tau protein in the brain.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Cohort Studies; Female; Humans; Male; Monocytes; tau Proteins

Dementia Research on Facebook and Twitter: Current Practice and Challenges. - Hrincu, Viorica; An, Zijian; Joseph, Kenneth; Jiang, Yu Fei; Robillard, Julie M (J Alzheimers Dis, 2022)
BACKGROUND: Social media is a powerful tool for engaging diverse audiences in dementia research. However, there is little data summarizing current content exchange in this context. OBJECTIVE: To inform ethical dementia research engagement on social media, we characterized current practices by analyzing public social media posts. METHODS: We retrieved Facebook (2-year period, N = 7,896) and Twitter (1-year period, N = 9,323) posts containing dementia research-related keywords using manual and machine learning-based search strategies. We performed qualitative and quantitative content and sentiment analyses on random samples (10%) of the posts. RESULTS: Top Facebook users were advocacy (45%) and health organizations (25%). On Twitter, academics/researchers were the largest user group. Prevention was the most frequently coded theme (Facebook 30%; Twitter 26%), followed by treatment (Facebook 15%; Twitter 18%). Diagnostics had the highest Facebook engagement. Sharing knowledge was the primary form of content exchange (Facebook 63%; Twitter 80%). Most shared journal articles were peer-reviewed and open access. Emotional tone was overall more positive on Facebook. Justice was a prominent ethics topic regarding inequalities related to identity and intersecting modes of marginalization in dementia research. CONCLUSION: The findings indicate the importance of social media as an engagement tool of current topics in health research and reveal areas of potential for increased engagement. These data can inform consensus-based best practices for ethical social media application in dementia research.
Keywords: Dementia; Humans; Social Media

Demonstration of Clinical Meaningfulness of the Integrated Alzheimer's Disease Rating Scale (iADRS): Association Between Change in iADRS Scores and Patient and Caregiver Health Outcomes. - Wessels, Alette M; Belger, Mark; Johnston, Joseph A; Yu, Youying; Rentz, Dorene M; Dowsett, Sherie A; Chandler, Julie (J Alzheimers Dis, 2022)
BACKGROUND: The integrated Alzheimer's Disease Rating Scale (iADRS) is a validated cognitive/functional composite that effectively captures cognitive and functional decline over a broad spectrum of disease. The clinical meaningfulness of change on iADRS can be supported by establishing an association with changes on important health outcome measures. OBJECTIVE: To evaluate the relationship between change on the iADRS and changes in health outcomes in individuals with mild cognitive impairment (MCI) due to Alzheimer's disease (AD), or mild or moderate AD dementia using placebo data from four AD clinical trials and data from one AD observational study. METHODS: Analysis of covariate (ANCOVA) models were used to estimate the relationship between 18-month change on the iADRS and changes on health outcome measures (related to cost, quality of life, and caregiver burden). The regression coefficients for the iADRS were used to compute impact of natural disease progression and disease-modifying treatment on health outcomes. Additional ANCOVAs were conducted to understand whether cognition and/or function was the underlying explanation of any association between iADRS and health outcome change. RESULTS: Across datasets and disease stages, a worsening on the iADRS was significantly associated with increased societal costs, caregiver burden (time and distress) and worsening in measures of patient quality of life. CONCLUSION: Decline on the iADRS was associated with worsening in health outcome measures. These findings suggest that the iADRS can be used in clinical trials as a proxy measure of clinically meaningful outcomes of AD progression.
Keywords: Alzheimer Disease; Caregivers; Clinical Trials as Topic; Cognitive Dysfunction; Humans; Observational Studies as Topic; Outcome Assessment, Health Care; Quality of Life

Evaluation of the Accuracy of Cognitive Screening Tests in Detecting Dementia Associated with Alzheimer's Disease: A Hierarchical Bayesian Latent Class Meta-Analysis. - Wang, Xiaonan; Li, Fengjie; Gao, Qi; Jiang, Zhen; Abudusaimaiti, Xiayidanmu; Yao, Jiangyue; Zhu, Huiping (J Alzheimers Dis, 2022)
BACKGROUND: Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE) are neuropsychological tests commonly used by physicians for screening cognitive dysfunction of Alzheimer's disease (AD). Due to different imperfect reference standards, the performance of MoCA and MMSE do not reach consensus. It is necessary to evaluate the consistence and differentiation of MoCA and MMSE in the absence of a gold standard for AD. OBJECTIVE: We aimed to assess the accuracy of MoCA and MMSE in screening AD without a gold standard reference test. METHODS: Studies were identified from PubMed, Web of Science, CNKI, Chinese Wanfang Database, China Science and Technology Journal Database, and Cochrane Library. Our search was limited to studies published in English and Chinese before August 2021. A hierarchical Bayesian latent class model was performed in meta-analysis when the gold standard was absent. RESULTS: A total of 67 studies comprising 5,554 individuals evaluated for MoCA and 76,862 for MMSE were included in this meta-analysis. The pooled sensitivity was 0.934 (95% CI 0.905 to 0.954) for MoCA and 0.883 (95% CI 0.859 to 0.903) for MMSE, while the pooled specificity was 0.899 (95% CI 0.859 to 0.928) for MoCA and 0.903 (95% CI 0.879 to 0.923) for MMSE. MoCA was useful to rule out dementia associated with AD with lower negative likelihood ratio (LR-) (0.074, 95% CI 0.051 to 0.108). MoCA showed better performance with higher diagnostic odds ratio (DOR) (124.903, 95% CI 67.459 to 231.260). CONCLUSION: MoCA had better performance than MMSE in screening dementia associated with AD from patients with mild cognitive impairment or healthy controls.
Keywords: Alzheimer Disease; Bayes Theorem; Cognition; Cognitive Dysfunction; Humans; Mental Status and Dementia Tests; Neuropsychological Tests

Evoked Cortical Depolarizations Before and After the Amyloid Plaque Accumulation: Voltage Imaging Study. - Zhu, Mei Hong; Jogdand, Aditi H; Jang, Jinyoung; Nagella, Sai C; Das, Brati; Milosevic, Milena M; Yan, Riqiang; Antic, Srdjan D (J Alzheimers Dis, 2022)
BACKGROUND: In Alzheimer's disease (AD), synaptic dysfunction is thought to occur many years before the onset of cognitive decline. OBJECTIVE: Detecting synaptic dysfunctions at the earliest stage of AD would be desirable in both clinic and research settings. METHODS: Population voltage imaging allows monitoring of synaptic depolarizations, to which calcium imaging is relatively blind. We developed an AD mouse model (APPswe/PS1dE9 background) expressing a genetically-encoded voltage indicator (GEVI) in the neocortex. GEVI was restricted to the excitatory pyramidal neurons (unlike the voltage-sensitive dyes). RESULTS: Expression of GEVI did not disrupt AD model formation of amyloid plaques. GEVI expression was stable in both AD model mice and Control (healthy) littermates (CTRL) over 247 days postnatal. Brain slices were stimulated in layer 2/3. From the evoked voltage waveforms, we extracted several parameters for comparison AD versus CTRL. Some parameters (e.g., temporal summation, refractoriness, and peak latency) were weak predictors, while other parameters (e.g., signal amplitude, attenuation with distance, and duration (half-width) of the evoked transients) were stronger predictors of the AD condition. Around postnatal age 150 days (P150) and especially at P200, synaptically-evoked voltage signals in brain slices were weaker in the AD groups versus the age- and sex-matched CTRL groups, suggesting an AD-mediated synaptic weakening that coincides with the accumulation of plaques. However, at the youngest ages examined, P40 and P80, the AD groups showed differentially stronger signals, suggesting "hyperexcitability" prior to the formation of plaques. CONCLUSION: Our results indicate bidirectional alterations in cortical physiology in AD model mice; occurring both prior (P40-80), and after (P150-200) the amyloid deposition.

It's Groundhog Day! What Can the History of Science Say About the Crisis in Alzheimer's Disease Research? - Jacobs, Noortje; Theunissen, Bert (J Alzheimers Dis, 2022)
For years now, Alzheimer's disease (AD) research has been stuck in a Groundhog-Day scenario: an endless time loop with no breakthrough in sight. Disagreement about the validity of the field's dominant approach, based on the Amyloid Cascade Hypothesis, has led to a seemingly unresolvable trench war between proponents and critics. Our paper evaluates the recent scientific literature on AD from a historical and philosophical perspective. We show that AD research is a classic example of the boundary work at play in a field in crisis: both parties deploy historical and philosophical references to illustrate what counts as good and bad science, as proper scientific method and appropriate scientific conduct. We also show that boundary work has proved unable to point a way out of the deadlock and argue that the science system's tools for establishing scientific quality, such as peer review and the grant system, are unlikely to resolve the crisis. Rather, they consolidate the dominant model's position even more. In conclusion, we suggest that some kind of reverse boundary-work is needed that reopens the discussion on the nature of AD, an issue that has never been settled scientifically. Drawing on historical and philosophical work, we make clear that the definition of AD as a biomedical disease for which a cure can be found has consequences, not only for funding opportunities, but also for patients and their lives. A reconsideration of the desirability of these consequences may lead to different choices with respect to research priorities and patient care.
Keywords: Alzheimer Disease; Amyloid; Humans

Medial Temporal Atrophy in Posterior Cortical Atrophy and Its Relationship to the Cingulate Island Sign. - Josephs, Kennedy A; Pham, Nha Trang Thu; Graff-Radford, Jonathan; Machulda, Mary M; Lowe, Val J; Whitwell, Jennifer L (J Alzheimers Dis, 2022)
BACKGROUND: It has been hypothesized that medial temporal sparing may be related to preserved posterior cingulate metabolism and the cingulate island sign (CIS) on [18F]fluorodeoxyglucose (FDG) PET in posterior cortical atrophy (PCA). OBJECTIVE: To assess the severity of medial temporal atrophy in PCA and determine whether the presence of a CIS is related to medial temporal sparing. METHODS: Fifty-five PCA patients underwent MRI and FDG-PET. The degree and symmetry of medial temporal atrophy on MRI was visually assessed using a five-point scale for both hemispheres. Visual assessments of FDG-PET coded the presence/absence of a CIS and whether the CIS was symmetric or asymmetric. Hippocampal volumes and a quantitative CIS were also measured. RESULTS: Medial temporal atrophy was most commonly mild or moderate, was symmetric in 55% of patients, and when asymmetric was most commonly worse on the right (76%). Older age and worse memory performance were associated with greater medial temporal atrophy. The CIS was observed in 44% of the PCA patients and was asymmetric in 50% of these. The patients with a CIS showed greater medial temporal asymmetry, but did not show lower medial temporal atrophy scores, compared to those without a CIS. Hippocampal volumes were not associated with quantitative CIS. CONCLUSION: Mild medial temporal atrophy is a common finding in PCA and is associated with memory impairment. However, medial temporal sparing was not related to the presence of a CIS in PCA.
Keywords: Alzheimer Disease; Atrophy; Fluorodeoxyglucose F18; Humans; Lewy Body Disease; Magnetic Resonance Imaging; Positron-Emission Tomography

Metabolic Factors Are Related to Brain Amyloid Among Mexican Americans: A HABS-HD Study. - O'Bryant, Sid E; Petersen, Melissa; Hall, James; Johnson, Leigh (J Alzheimers Dis, 2022)
BACKGROUND: Despite the tremendous amount of research on Alzheimer's disease (AD) biomarkers, very little data is available regarding the fundamental biomarkers of AD among Mexican Americans. OBJECTIVE: Here we sought to examine the link between metabolic markers and brain amyloid among Mexican Americans as compared to non-Hispanic whites from the Health & Aging Brain Study -Health Disparities (HABS-HD) cohort. METHODS: PET amyloid (florbetaben) data was analyzed from 34 Mexican American and 22 non-Hispanic white participants. RESULTS: Glucagon (t = 3.84, p <  0.001) and insulin (t = -2.56, p = 0.02) were both significantly related to global SUVR levels among Mexican Americans. Glucagon and insulin were both related to most ROIs. No metabolic markers were significantly related to brain amyloid levels among non-Hispanic whites. CONCLUSION: Metabolic markers are related to brain amyloid burden among Mexican Americans. Given the increased risk for diabetes, additional research is needed to determine the impact of diabetes on core AD biomarkers among this underserved population.

Non-Alcoholic Fatty Liver Disease, Liver Fibrosis, and Regional Amyloid-β and Tau Pathology in Middle-Aged Adults: The Framingham Study. - Weinstein, Galit; O'Donnell, Adrienne; Davis-Plourde, Kendra; Zelber-Sagi, Shira; Ghosh, Saptaparni; DeCarli, Charles S; Thibault, Emma G; Sperling, Reisa A; Johnson, Keith A; Beiser, Alexa S; Seshadri, Sudha (J Alzheimers Dis, 2022)
BACKGROUND: Liver steatosis and fibrosis are emerging as risk factors for multiple extrahepatic health conditions; however, their relationship with Alzheimer's disease pathology is unclear. OBJECTIVE: To examine whether non-alcoholic fatty liver disease (NAFLD) and FIB-4, a non-invasive index of advanced fibrosis, are associated with brain amyloid-β (Aβ) and tau pathology. METHODS: The study sample included Framingham Study participants from the Offspring and Third generation cohorts who attended exams 9 (2011-2014) and 2 (2008-2011), respectively. Participants underwent 11C-Pittsburgh Compound-B amyloid and 18F-Flortaucipir tau positron emission tomography (PET) imaging and abdomen computed tomography, or had information on all components of the FIB-4 index. Linear regression models were used to assess the relationship of NAFLD and FIB-4 with regional tau and Aβ, adjusting for potential confounders and multiple comparisons. RESULTS: Of the subsample with NAFLD information (N = 169; mean age 52±9 y; 57% males), 57 (34%) had NAFLD. Of the subsample with information on liver fibrosis (N = 177; mean age 50±10 y; 51% males), 34 (19%) had advanced fibrosis (FIB-4 >  1.3). Prevalent NAFLD was not associated with Aβ or tau PET. However, FIB-4 index was significantly associated with increased rhinal tau (β= 1.03±0.33, p = 0.002). Among individuals with prevalent NAFLD, FIB-4 was related to inferior temporal, parahippocampal gyrus, entorhinal and rhinal tau (β= 2.01±0.47, p <  0.001; β= 1.60±0.53, p = 0.007, and β= 1.59±0.47, p = 0.003 and β= 1.60±0.42, p = 0.001, respectively) and to Aβ deposition overall and in the inferior temporal and parahippocampal regions (β= 1.93±0.47, p <  0.001; β= 1.59±0.38, p <  0.001, and β= 1.52±0.54, p = 0.008, respectively). CONCLUSION: This study suggests a possible association between liver fibrosis and early Alzheimer's disease pathology, independently of cardio-metabolic risk factors.

Passive Immunotherapy Targeting Tau Oligomeric Strains Reverses Tauopathy Phenotypes in Aged Human-Tau Mice in a Mouse Model-Specific Manner. - Bittar, Alice; Al-Lahham, Rabab; Bhatt, Nemil; Moore, Kenya; Montalbano, Mauro; Jerez, Cynthia; Fung, Leiana; McAllen, Salome; Ellsworth, Anna; Kayed, Rakez (J Alzheimers Dis, 2022)
BACKGROUND: Tau oligomers are one of the most toxic species, displaying prion-like strains which have different conformations resulting in different tauopathies. Passive immunotherapy targeting different tau species is a promising therapeutic approach. Age is one of the greatest risk factors; however, most immunotherapy studies are done in young to middle-aged mice tauopathy models, which is not representative of the many clinical trials done with older humans with established tauopathies. OBJECTIVE: We utilized two different clones of tau oligomer monoclonal antibodies (TOMAs) in aged Htau and JNPL3 mouse models to investigate the potential of passive immunotherapy. METHODS: Aged mice received a single intravenous injection of 120 μg/animal of either TOMA1, TOMA3 clones or a non-specific IgG. Their cognitive functions were assessed one-week post-injection using Y-maze and novel object recognition tests. Brain tissues were analyzed using biochemical and immunological assays. RESULTS: TOMA 1 and 3 rescues cognitive phenotypes in aged animals in a mouse model-specific manner, indicative by a reduction in tau oligomers levels. The TOMAs were shown to have strong reactivity with different tau oligomeric species in the different mouse models in vitro and ex vivo. CONCLUSION: This is the first study testing tau passive immunotherapy in aged animals and supports our previous reports on of the role of oligomeric tau in disease progression further validating the potential of TOMAs to rescue the late-stage disease pathology and phenotype. Moreover, this study suggests that multiple tau oligomeric strains exist in aged animals; therefore, it is of great importance to further characterize these strains.

Pelargonidin and Berry Intake Association with Alzheimer's Disease Neuropathology: A Community-Based Study. - Agarwal, Puja; Holland, Thomas M; James, Bryan D; Cherian, Laurel J; Aggarwal, Neelum T; Leurgans, Sue E; Bennett, David A; Schneider, Julie A (J Alzheimers Dis, 2022)
BACKGROUND: An anthocyanidin, pelargonidin, primarily found in berries, has antioxidant and anti-inflammatory properties, and is associated with better cognition and reduced Alzheimer's dementia risk. OBJECTIVE: This study investigated if pelargonidin or berry intake is associated with Alzheimer's disease (AD) neuropathology in human brains. METHODS: The study was conducted among 575 deceased participants (age at death = 91.3±6.1 years; 70% females) of the Rush Memory and Aging Project, with dietary data (assessed using a food frequency questionnaire) and neuropathological evaluations. Calorie-adjusted pelargonidin intake was modeled in quartiles and berry intake as continuous (servings/week). Mean amyloid-beta load and phosphorylated tau neuronal neurofibrillary tangle density across multiple cortical regions were assessed using immunohistochemistry. Global AD pathology burden, a quantitative summary score of neurofibrillary tangles, and diffuse and neuritic plaques using Bielschowsky silver stains in multiple brain regions, was also assessed. RESULTS: In a linear regression model adjusted for age at death, sex, education, APOE ɛ4 status, vitamin E, and vitamin C, participants in the highest quartile of pelargonidin intake when compared to those in the lowest quartile, had less amyloid-β load (β (SE) = -0.293 (0.14), p = 0.038), and fewer phosphorylated tau tangles (β (SE) = -0.310, p = 0.051). Among APOE ɛ4 non-carriers, higher strawberry (β (SE) = -0.227 (0.11), p = 0.037) and pelargonidin (Q4 versus Q1: β (SE) = -0.401 (0.16), p = 0.011; p trend = 0.010) intake was associated with less phosphorylated tau tangles, no association was observed in APOE ɛ4 carriers. Berry intake was not associated with AD pathology. However, excluding participants with dementia or mild cognitive impairment at baseline, strawberry (p = 0.004) and pelargonidin (ptrend = 0.007) intake were associated with fewer phosphorylated tau tangles. CONCLUSION: Higher intake of pelargonidin, a bioactive present in strawberries, is associated with less AD neuropathology, primarily phosphorylated tau tangles.

Plasma Cholesterol Levels as Potential Nutritional Biomarkers for Lewy Body Dementia. - Dou, Yuchao; Liu, Shuai; Li, Yuqing; Wu, Hao; Chen, Hui; Ji, Yong (J Alzheimers Dis, 2022)
BACKGROUND: The relationship between cholesterol level and the risk of developing Alzheimer's disease has been well established, but the relationship between cholesterol level and Lewy body dementia (LBD) is still not well known. OBJECTIVE: The aim of this case-control study was to explore the association between blood cholesterol levels and LBD in Chinese older adults. METHODS: A total of 65 patients with LBD and 110 older adult controls were enrolled during the study period. The levels of triglyceride, total cholesterol, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and fasting glucose were measured separately. The associations between LBD, blood cholesterol levels, and fasting glucose levels were assessed using multiple binary logistic regression analyses adjusted for multiple covariates. RESULTS: Increased plasma LDL-C levels and lower HDL-C levels were independently associated with the risk of LBD in models adjusted for age, sex, education, alcohol use status, smoking status, and vascular disorders. Higher fasting glucose levels may be associated with the risk of LBD. CONCLUSION: The results of this study suggest that elevated levels of LDL-C and reduced levels of HDL-C were associated with LBD development and therefore are potential nutritional risk factors for LBD. Adjusting diet and individualized and effective cholesterol-lowering therapy in high-risk adults may aid in the prevention or management of LBD.

Polygenic Scores of Alzheimer's Disease Risk Genes Add Only Modestly to APOE in Explaining Variation in Amyloid PET Burden. - Ramanan, Vijay K; Heckman, Michael G; Przybelski, Scott A; Lesnick, Timothy G; Lowe, Val J; Graff-Radford, Jonathan; Mielke, M; Jack, Clifford R; Knopman, David S; Petersen, Ronald C; Ross, Owen A; Vemuri, Prashanthi (J Alzheimers Dis, 2022)
BACKGROUND: Brain accumulation of amyloid-β is a hallmark event in Alzheimer's disease (AD) whose underlying mechanisms are incompletely understood. Case-control genome-wide association studies have implicated numerous genetic variants in risk of clinically diagnosed AD dementia. OBJECTIVE: To test for associations between case-control AD risk variants and amyloid PET burden in older adults, and to assess whether a polygenic measure encompassing these factors would account for a large proportion of the unexplained variance in amyloid PET levels in the wider population. METHODS: We analyzed data from the Mayo Clinic Study of Aging (MCSA) and the Alzheimer's Disease Neuroimaging Initiative (ADNI). Global cortical amyloid PET burden was the primary outcome. The 38 gene variants from Wightman et al. (2021) were analyzed as predictors, with PRSice-2 used to assess the collective phenotypic variance explained. RESULTS: Known AD risk variants in APOE, PICALM, CR1, and CLU were associated with amyloid PET levels. In aggregate, the AD risk variants were strongly associated with amyloid PET levels in the MCSA (p = 1.51×10-50) and ADNI (p = 3.21×10-64). However, in both cohorts the non-APOE variants uniquely contributed only modestly (MCSA = 2.1%, ADNI = 4.4%) to explaining variation in amyloid PET levels. CONCLUSION: Additional case-control AD risk variants added only modestly to APOE in accounting for individual variation in amyloid PET burden, results which were consistent across independent cohorts with distinct recruitment strategies and subject characteristics. Our findings suggest that advancing precision medicine for dementia may require integration of strategies complementing case-control approaches, including biomarker-specific genetic associations, gene-by-environment interactions, and markers of disease progression and heterogeneity.

Precision Medicine Approach to Alzheimer's Disease: Successful Pilot Project. - Toups, Kat; Hathaway, Ann; Gordon, Deborah; Chung, Henrianna; Raji, Cyrus; Boyd, Alan; Hill, Benjamin D; Hausman-Cohen, Sharon; Attarha, Mouna; Chwa, Won Jong; Jarrett, Michael; Bredesen, Dale E (J Alzheimers Dis, 2022)
BACKGROUND: Effective therapeutics for Alzheimer's disease are needed. However, previous clinical trials have pre-determined a single treatment modality, such as a drug candidate or therapeutic procedure, which may be unrelated to the primary drivers of the neurodegenerative process. Therefore, increasing data set size to include the potential contributors to cognitive decline for each patient, and addressing the identified potential contributors, may represent a more effective strategy. OBJECTIVE: To determine whether a precision medicine approach to Alzheimer's disease and mild cognitive impairment is effective enough in a proof-of-concept trial to warrant a larger, randomized, controlled clinical trial. METHODS: Twenty-five patients with dementia or mild cognitive impairment, with Montreal Cognitive Assessment (MoCA) scores of 19 or higher, were evaluated for markers of inflammation, chronic infection, dysbiosis, insulin resistance, protein glycation, vascular disease, nocturnal hypoxemia, hormone insufficiency or dysregulation, nutrient deficiency, toxin or toxicant exposure, and other biochemical parameters associated with cognitive decline. Brain magnetic resonance imaging with volumetrics was performed at baseline and study conclusion. Patients were treated for nine months with a personalized, precision medicine protocol, and cognition was assessed at t = 0, 3, 6, and 9 months. RESULTS: All outcome measures revealed improvement: statistically significant improvement in MoCA scores, CNS Vital Signs Neurocognitive Index, and Alzheimer's Questionnaire Change score were documented. No serious adverse events were recorded. MRI volumetrics also improved. CONCLUSION: Based on the cognitive improvements observed in this study, a larger, randomized, controlled trial of the precision medicine therapeutic approach described herein is warranted.

Probiotic Bifidobacterium breve Prevents Memory Impairment Through the Reduction of Both Amyloid-β Production and Microglia Activation in APP Knock-In Mouse. - Abdelhamid, Mona; Zhou, Chunyu; Ohno, Kazuya; Kuhara, Tetsuya; Taslima, Ferdous; Abdullah, Mohammad; Jung, Cha-Gyun; Michikawa, Makoto (J Alzheimers Dis, 2022)
BACKGROUND: Probiotic supplementation reestablishes microbiome diversity and improves brain function in Alzheimer's disease (AD); their molecular mechanisms, however, have not yet been fully illustrated. OBJECTIVE: We investigated the effects of orally supplemented Bifidobacterium breve MCC1274 on cognitive function and AD-like pathologies in AppNL-G-F mice. METHODS: Three-month-old AppNL-G-F mice were orally supplemented with B. breve MCC1274 for four months. The short-term memory function was evaluated using a novel object recognition test. Amyloid plaques, amyloid-β (Aβ) levels, Aβ fibril, amyloid-β protein precursor and its processing enzymes, its metabolic products, glial activity, and cell proliferation in the subgranular zone of the dentate gyrus were evaluated by immunohistochemistry, Aβ ELISA, western blotting, and immunofluorescence staining. The mRNA expression levels of pro- and anti-inflammatory cytokines were determined by qRT-PCR analysis. RESULTS: We found that the oral B. breve MCC1 274 supplementation prevented memory impairment in AppNL-G-F mice and decreased hippocampal Aβ levels through the enhancement of the a-disintegrin and metalloproteinase 10 (ADAM10) level. Moreover, administration of the probiotic activated the ERK/HIF-1α signaling pathway responsible for increasing the ADAM10 level and also attenuated microglial activation, which in turn led to reduction in the mRNA expression levels of pro-inflammatory cytokines in the brain. In addition, B. breve MCC1274 supplementation increased the level of synaptic proteins in the hippocampus. CONCLUSION: Our findings support the possibility that oral B. breve MCC1274 supplementation might be used as a potential preventive therapy for AD progression.
Keywords: Amyloid beta-Peptides; Animals; Bifidobacterium breve; Brain; Disease Models, Animal; Hippocampus; Memory Disorders; Mice; Mice, Transgenic; Microglia; Probiotics

Progression from Subjective Cognitive Decline to Mild Cognitive Impairment or Dementia: The Role of Baseline Cognitive Performance. - Jester, Dylan J; Vyhnálek, Martin; Andel, Ross; Marková, Hana; Nikolai, Tomas; Laczó, Jan; Matuskova, Veronika; Cechova, Katerina; Sheardova, Katerina; Hort, Jakub (J Alzheimers Dis, 2022)
BACKGROUND: Older adults with subjective cognitive decline (SCD) are at an increased risk of progression to mild cognitive impairment (MCI) or dementia. However, few have examined the specific cognitive tests that are associated with progression. OBJECTIVE: This study examined performance on 18 neuropsychological tests among participants with SCD who later progressed to MCI or dementia. METHODS: We included 131 participants from the Czech Brain Aging Study that had SCD at baseline. They completed a comprehensive neuropsychological battery including cognitive tests from the Uniform Data Set 2.0 enriched by the verbal memory test Rey Auditory Verbal Learning Test (RAVLT) and Rey-Osterrieth Complex Figure Test (ROCFT). RESULTS: Fifty-five participants progressed: 53% to non-amnestic MCI (naMCI), 44% to amnestic MCI (aMCI), and 4% to dementia. Scoring one SD below the mean at baseline on the RAVLT 1 and RAVLT 1-5 was associated with 133% (RAVLT 1; HR: 2.33 [1.50, 3.62]) and 122% (RAVLT 1-5; HR: 2.22 [1.55, 3.16]) greater risk of progression to MCI or dementia over 3.84 years on average. Worse performance on the RAVLT 5, RAVLT 1-5, RAVLT 30, and ROCFT-Recall was associated with progression to aMCI whereas worse performance on the RAVLT 1, TMT B, and Boston Naming Test was associated with progression to naMCI. CONCLUSION: At baseline, lower verbal memory performance was most strongly associated with progression to aMCI whereas lower executive or language performance was most strongly associated with progression to naMCI.

Proteomic Profiles of Neurodegeneration Among Mexican Americans and Non-Hispanic Whites in the HABS-HD Study. - O'Bryant, Sid E; Zhang, Fan; Petersen, Melissa; Hall, James R; Johnson, Leigh A; Yaffe, Kristine; Braskie, Meredith; Vig, Rocky; Toga, Arthur W; Rissman, Robert A (J Alzheimers Dis, 2022)
BACKGROUND: Hispanics are expected to experience the largest increase in Alzheimer's disease (AD) and AD related dementias over the next several decades. However, few studies have examined biomarkers of AD among Mexican Americans, the largest segment of the U.S. Hispanic population. OBJECTIVE: We sought to examine proteomic profiles of an MRI-based marker of neurodegeneration from the AT(N) framework among a multi-ethnic, community-dwelling cohort. METHODS: Community-dwelling Mexican Americans and non-Hispanic white adults and elders were recruited. All participants underwent comprehensive assessments including an interview, functional exam, clinical labs, informant interview, neuropsychological testing, and 3T MRI of the brain. A neurodegeneration MRI meta-ROI biomarker for the AT(N) framework was calculated. RESULTS: Data was examined from n = 1,291 participants. Proteomic profiles were highly accurate for detecting neurodegeneration (i.e., N+) among both Mexican Americans (AUC = 1.0) and non-Hispanic whites (AUC = 0.98). The proteomic profile of N + was different between ethnic groups. Further analyses revealed that the proteomic profiles of N + varied by diagnostic status (control, MCI, dementia) and ethnicity (Mexican American versus non-Hispanic whites) though diagnostic accuracy was high for all classifications. CONCLUSION: A proteomic profile of neurodegeneration has tremendous value and point towards novel diagnostic and intervention opportunities. The current findings demonstrate that the underlying biological factors associated with neurodegeneration are different between Mexican Americans versus non-Hispanic whites as well as at different levels of disease progression.

Rheumatoid Arthritis, Cognitive Impairment, and Neuroimaging Biomarkers: Results from the Mayo Clinic Study of Aging. - Vassilaki, Maria; Crowson, Cynthia S; Davis Iii, John M; Duong, Stephanie Q; Jones, David T; Nguyen, Aivi; Mielke, Michelle M; Vemuri, Prashanthi; Myasoedova, Elena (J Alzheimers Dis, 2022)
BACKGROUND: Observational studies suggested that dementia risk in patients with rheumatoid arthritis (RA) is higher than in the general population. OBJECTIVE: To examine the associations of RA with cognitive decline and dementia, and neuroimaging biomarkers of aging, Alzheimer's disease, and vascular pathology in adult participants in the Mayo Clinic Study of Aging (MCSA). METHODS: Participants with RA were matched 1:3 on age, sex, education, and baseline cognitive diagnosis to participants without RA. RA cases with MRI were also matched with non-cases with available MRI. All available imaging studies (i.e., amyloid and FDG PET, sMRI, and FLAIR) were included. The study included 104 participants with RA and 312 without RA (mean age (standard deviation, SD) 75.0 (10.4) years, 33% male and average follow-up (SD) 4.2 (3.8) years). RESULTS: Groups were similar in cognitive decline and risk of incident dementia. Among participants with neuroimaging, participants with RA (n = 33) and without RA (n = 98) had similar amyloid burden and neurodegeneration measures, including regions sensitive to aging and dementia, but greater mean white matter hyperintensity volume relative to the total intracranial volume (mean (SD)% : 1.12 (0.57)% versus 0.76 (0.69)% of TIV, p = 0.01), and had higher mean (SD) number of cortical infarctions (0.24 (0.44) versus 0.05 (0.33), p = 0.02). CONCLUSION: Although cognitive decline and dementia risk were similar in participants with and without RA, participants with RA had more abnormal cerebrovascular pathology on neuroimaging. Future studies should examine the mechanisms underlying these changes and potential implications for prognostication and prevention of cognitive decline in RA.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidosis; Arthritis, Rheumatoid; Biomarkers; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Neuroimaging; Positron-Emission Tomography

Risk of Alzheimer's Disease Following Influenza Vaccination: A Claims-Based Cohort Study Using Propensity Score Matching. - Bukhbinder, Avram S; Ling, Yaobin; Hasan, Omar; Jiang, Xiaoqian; Kim, Yejin; Phelps, Kamal N; Schmandt, Rosemarie E; Amran, Albert; Coburn, Ryan; Ramesh, Srivathsan; Xiao, Qian; Schulz, Paul E (J Alzheimers Dis, 2022)
BACKGROUND: Prior studies have found a reduced risk of dementia of any etiology following influenza vaccination in selected populations, including veterans and patients with serious chronic health conditions. However, the effect of influenza vaccination on Alzheimer's disease (AD) risk in a general cohort of older US adults has not been characterized. OBJECTIVE: To compare the risk of incident AD between patients with and without prior influenza vaccination in a large US claims database. METHODS: Deidentified claims data spanning September 1, 2009 through August 31, 2019 were used. Eligible patients were free of dementia during the 6-year look-back period and≥65 years old by the start of follow-up. Propensity-score matching (PSM) was used to create flu-vaccinated and flu-unvaccinated cohorts with similar baseline demographics, medication usage, and comorbidities. Relative risk (RR) and absolute risk reduction (ARR) were estimated to assess the effect of influenza vaccination on AD risk during the 4-year follow-up. RESULTS: From the unmatched sample of eligible patients (n = 2,356,479), PSM produced a sample of 935,887 flu-vaccinated-unvaccinated matched pairs. The matched sample was 73.7 (SD, 8.7) years of age and 56.9% female, with median follow-up of 46 (IQR, 29-48) months; 5.1% (n = 47,889) of the flu-vaccinated patients and 8.5% (n = 79,630) of the flu-unvaccinated patients developed AD during follow-up. The RR was 0.60 (95% CI, 0.59-0.61) and ARR was 0.034 (95% CI, 0.033-0.035), corresponding to a number needed to treat of 29.4. CONCLUSION: This study demonstrates that influenza vaccination is associated with reduced AD risk in a nationwide sample of US adults aged 65 and older.
Keywords: Adult; Aged; Alzheimer Disease; Chronic Disease; Cohort Studies; Female; Humans; Influenza, Human; Male; Middle Aged; Propensity Score; Vaccination

Small RNA Sequencing in the Tg4-42 Mouse Model Suggests the Involvement of snoRNAs in the Etiology of Alzheimer's Disease. - Lio, Chit Tong; Kacprowski, Tim; Klaedtke, Maik; Jensen, Lars R; Bouter, Yvonne; Bayer, Thomas A; Kuss, Andreas W (J Alzheimers Dis, 2022)
BACKGROUND: The Tg4-42 mouse model for sporadic Alzheimer's disease (AD) has unique features, as the neuronal expression of wild type N-truncated Aβ4-42 induces an AD-typical neurological phenotype in the absence of plaques. It is one of the few models developing neuron death in the CA1 region of the hippocampus. As such, it could serve as a powerful tool for preclinical drug testing and identification of the underlying molecular pathways that drive the pathology of AD. OBJECTIVE: The aim of this study was to use a differential co-expression analysis approach for analyzing a small RNA sequencing dataset from a well-established murine model in order to identify potentially new players in the etiology of AD. METHODS: To investigate small nucleolar RNAs in the hippocampus of Tg4-42 mice, we used RNA-Seq data from this particular tissue and, instead of analyzing the data at single gene level, employed differential co-expression analysis, which takes the comparison to gene pair level and thus affords a new angle to the interpretation of these data. RESULTS: We identified two clusters of differentially correlated small RNAs, including Snord55, Snord57, Snord49a, Snord12, Snord38a, Snord99, Snord87, Mir1981, Mir106b, Mir30d, Mir598, and Mir99b. Interestingly, some of them have been reported to be functionally relevant in AD pathogenesis, as AD biomarkers, regulating tau phosphorylation, TGF-β receptor function or Aβ metabolism. CONCLUSION: The majority of snoRNAs for which our results suggest a potential role in the etiology of AD were so far not conspicuously implicated in the context of AD pathogenesis and could thus point towards interesting new avenues of research in this field.

Is Acculturation Associated with the Cognitive Performance of Older Hispanics? - Alam, Rifat B; Singleton, Chelsea R; Aguiñaga, Susan; Chodzko-Zajko, Wojtek; Jahan, Nilufer A; Oke, Adeyosola; Schwingel, Andiara (J Alzheimers Dis, 2021)
BACKGROUND: Hispanics in the United Statues are disproportionately affected by Alzheimer's disease and related dementias. Little is known about the impact of acculturation on cognitive performance. OBJECTIVE: This study examined the association between acculturation and cognitive performance among older Hispanics. METHODS: We analyzed cross-sectional data of 616 Hispanic participants in the National Health and Nutrition Examination Survey (NHANES) 2011-2014 [average age = 67.15 years, %Female = 51.46, %less than high-school graduate = 52.60]. Cognitive performance was measured by two neuropsychological tests: Animal Fluency Test (AFT) and Digit Symbol Substitution Test (DSST). We used two single-item proxy measures to quantify acculturation: nativity status (non-US-born residing <  15 years in the US (low acculturation), non-US-born residing ≥15 years in the US, and US-born (high acculturation)); and language acculturation (only/mostly Spanish (low acculturation), Spanish and English, only/mostly English (high acculturation)). We used adjusted linear regression to evaluate associations between acculturation and cognitive performance. RESULTS: Results indicated poorer cognitive performance among the low-acculturated groups for both nativity and linguistic measures. Participants who were non-US-born living ≥15 years (p = 0.02) and speaking only/mostly Spanish or Spanish and English (p = 0.01 and 0.006 respectively) had significantly lower AFT scores compared to US-born and only/mostly English-speaking groups. Participants who were non-US-born living <  15 years (p <  0.0001) or non-US-born living ≥15 years (p <  0.0001) and speaking only/mostly Spanish (p = 0.0008) scored lower on the DSST than the US-born and only/mostly English-speaking participants. CONCLUSION: In summary, low acculturation is associated with poorer cognitive performance among older Hispanics. Acculturation might be an important attribute to help understand cognitive decline and dementias among Hispanics.

The Association of Essential Metals with APOE Genotype in Alzheimer's Disease. - Babić Leko, Mirjana; Jurasović, Jasna; Nikolac Perković, Matea; Španić, Ena; Sekovanić, Ankica; Orct, Tatjana; Lukinović Škudar, Vesna; Bačić Baronica, Koraljka; Kiđemet-Piskač, Spomenka; Vogrinc, Željka; Pivac, Nela; Borovečki, Fran; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The major confirmed genetic risk factor for late-onset, sporadic Alzheimer's disease (AD) is variant ɛ4 of apolipoprotein E gene (APOE). It is proposed that ApoE, a protein involved in transport of cholesterol to neurons can cause neurodegeneration in AD through interaction with metals. Previous studies mostly associated copper, iron, zinc, and calcium with ApoE4-mediated toxicity. OBJECTIVE: To test the association of essential metals with APOE genotype. METHODS: We compared plasma and cerebrospinal fluid (CSF) levels of copper, zinc, iron, sodium, magnesium, calcium, cobalt, molybdenum, manganese, boron, and chromium, and CSF ferritin levels among AD, mild cognitive impairment (MCI) patients, and healthy controls (HC) with different APOE genotype. RESULTS: Sodium, copper, and magnesium levels were increased in carriers of ɛ4 allele. Additionally, the increase in sodium, calcium and cobalt plasma levels was observed in carriers of ɛ4/ɛx genotype. The decrease in boron plasma levels was observed in carriers of ɛ4 allele and ɛ4/ɛ4 genotype. Additionally, CSF zinc levels as well as plasma sodium levels were increased in AD patients compared to HC. CONCLUSION: These results indicate that the molecular underpinnings of association of essential metals and metalloids with APOE should be further tested and clarified in vivo and in vitro.

Association of Malnutrition with Functional and Cognitive Trajectories in People Living with Dementia: A Five-Year Follow-Up Study. - Borda, Miguel Germán; Ayala Copete, Ana María; Tovar-Rios, Diego Alejandro; Jaramillo-Jimenez, Alberto; Giil, Lasse Melvær; Soennesyn, Hogne; Gómez-Arteaga, Camilo; Venegas-Sanabria, Luis Carlos; Kristiansen, Ida; Chavarro-Carvajal, Diego Andrés; Caicedo, Sandra; Cano-Gutierrez, Carlos Alberto; et al. (J Alzheimers Dis, 2021)
BACKGROUND: In dementia, functional status depends on multiple factors in addition to cognition. Nutritional status is a potentially modifiable factor related to homeostasis and proper functioning of body systems and may contribute to cognitive and functional decline. OBJECTIVE: This paper aims to analyze the association of malnutrition with the course of cognitive and functional decline in people living with dementia. METHODS: This is an analysis of a longitudinal cohort study, the Dementia Study of Western Norway. Data of 202 patients diagnosed with mild dementia were analyzed; Alzheimer's disease (AD) (n = 103), Lewy body dementia (LBD) (n = 74), and other dementias (OD) (n = 25). Cognition was assessed with the Mini-Mental State Examination and functional decline through the activities of daily living included in the Rapid Disability Rating Scale. The Global Leadership Initiative on Malnutrition Index was used to determine nutritional status. Associations of nutritional status with cognitive and functional decline were evaluated through adjusted linear mixed models. RESULTS: At baseline, the prevalence of general malnutrition was 28.7%; 17.32% were classified as moderate malnutrition and 11.38% as severe malnutrition (there were no significant differences between AD and LBD). Malnutrition at diagnosis and over follow-up was a significant predictor of functional-decline, but not of cognitive decline. CONCLUSION: According to our results malnutrition was associated with faster functional loss but, not cognitive decline in older adults with dementia. A more comprehensive dementia approach including nutritional assessments could improve prognosis.

Association of Midlife Depressive Symptoms with Regional Amyloid-β and Tau in the Framingham Heart Study. - Gonzales, Mitzi M; Samra, Jasmeet; O'Donnell, Adrienne; Mackin, R Scott; Salinas, Joel; Jacob, Mini; Satizabal, Claudia L; Aparicio, Hugo J; Thibault, Emma G; Sanchez, Justin S; Finney, Rebecca; Rubinstein, Zoe B; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Depressive symptoms predict increased risk for dementia decades before the emergence of cognitive symptoms. Studies in older adults provide preliminary evidence for an association between depressive symptoms and amyloid-β (Aβ) and tau accumulation. It is unknown if similar alterations are observed in midlife when preventive strategies may be most effective. OBJECTIVE: The study aim was to evaluate the association between depressive symptoms and cerebral Aβ and tau in a predominately middle-aged cohort with examination of the apolipoprotein (APOE) ɛ4 allele as a moderator. METHODS: Participants included 201 adults (mean age 53±8 years) who underwent 11C-Pittsburgh Compound B amyloid and 18F-Flortaucipir tau positron emission tomography (PET) imaging. Depressive symptoms were evaluated with the Center for Epidemiological Studies Depression Scale (CES-D) at the time of PET imaging, as well as eight years prior. Associations between depressive symptoms at both timepoints, as well as depression (CES-D≥16), with regional Aβ and tau PET retention were evaluated with linear regression adjusting for age and sex. Interactions with the APOE ɛ4 allele were explored. RESULTS: Depressive symptoms and depression were not associated with PET outcomes in the overall sample. However, among APOE ɛ4 allele carriers, there was a significant cross-sectional association between depressive symptoms and increased tau PET uptake in the entorhinal cortex (β= 0.446, SE = 0.155, p = 0.006) and amygdala (β= 0.350, SE = 0.133, p = 0.012). CONCLUSION: Although longitudinal studies are necessary, the results suggest that APOE ɛ4 carriers with depressive symptoms may present with higher susceptibility to early tau accumulation in regions integral to affective regulation and memory consolidation.

B Vitamins Prevent Iron-Associated Brain Atrophy and Domain-Specific Effects of Iron, Copper, Aluminum, and Silicon on Cognition in Mild Cognitive Impairment. - Jakubowski, Hieronim; Zioła-Frankowska, Anetta; Frankowski, Marcin; Perła-Kaján, Joanna; Refsum, Helga; de Jager, Celeste A; Smith, A David (J Alzheimers Dis, 2021)

Blood-Based ATN Biomarkers of Alzheimer's Disease: A Meta-Analysis. - Koychev, Ivan; Jansen, Katrin; Dette, Alina; Shi, Liu; Holling, Heinz (J Alzheimers Dis, 2021)
BACKGROUND: The Amyloid Tau Neurodegeneration (ATN) framework was proposed to define the biological state underpinning Alzheimer's disease (AD). Blood-based biomarkers offer a scalable alternative to the costly and invasive currently available biomarkers. OBJECTIVE: In this meta-analysis we sought to assess the diagnostic performance of plasma amyloid (Aβ40, Aβ42, Aβ42/40 ratio), tangle (p-tau181), and neurodegeneration (total tau [t-tau], neurofilament light [NfL]) biomarkers. METHODS: Electronic databases were screened for studies reporting biomarker concentrations for AD and control cohorts. Biomarker performance was examined by random-effect meta-analyses based on the ratio between biomarker concentrations in patients and controls. RESULTS: 83 studies published between 1996 and 2020 were included in the analyses. Aβ42/40 ratio as well as Aβ42 discriminated AD patients from controls when using novel platforms such as immunomagnetic reduction (IMR). We found significant differences in ptau-181 concentration for studies based on single molecule array (Simoa), but not for studies based on IMR or ELISA. T-tau was significantly different between AD patients and control in IMR and Simoa but not in ELISA-based studies. In contrast, NfL differentiated between groups across platforms. Exosome studies showed strong separation between patients and controls for Aβ42, t-tau, and p-tau181. CONCLUSION: Currently available assays for sampling plasma ATN biomarkers appear to differentiate between AD patients and controls. Novel assay methodologies have given the field a significant boost for testing these biomarkers, such as IMR for Aβ, Simoa for p-tau181. Enriching samples through extracellular vesicles shows promise but requires further validation.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Humans; Neurodegenerative Diseases; Neurofibrillary Tangles; Neurofilament Proteins; Peptide Fragments; Phosphorylation; Plaque, Amyloid; tau Proteins

Body Mass Index and Mild Cognitive Impairment Among Middle-Aged and Older Adults from Low- and Middle-Income Countries. - Smith, Lee; Shin, Jae Il; Oh, Hans; Carmichael, Christina; Jacob, Louis; Stefanac, Sinisa; Lindsay, Rosie K; Soysal, Pinar; Veronese, Nicola; Tully, Mark A; Butler, Laurie; Barnett, Yvonne; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The effect of weight modification on future dementia risk is currently a subject of debate and may be modified by age. OBJECTIVE: The aim of the present study was to investigate the association between body mass index (BMI) status with mild cognitive impairment (MCI) (a preclinical stage of dementia) in middle-aged and older adults residing in six low- and middle-income countries using nationally representative data. METHODS: Cross-sectional data from the Study on Global Ageing and Adult Health (SAGE) were analyzed. MCI was defined using the National Institute on Aging-Alzheimer's Association criteria. BMI (kg/m2) was based on measured weight and height and categorized as: underweight (<18.5), normal (18.5-24.9), overweight (25.0-29.9), and obese (≥30.0). Multivariable logistic regression analysis and meta-analysis were conducted to assess associations. RESULTS: Data on 32,715 individuals aged ≥50 years with preservation in functional abilities were analyzed [mean (SD) age 62.1 (15.6) years; 51.7% females]. Among those aged 50-64 years, compared to normal weight, underweight (OR = 1.44; 95% CI = 1.14-1.81), overweight (OR = 1.17; 95% CI = 1.002-1.37), and obesity (OR = 1.46; 95% CI = 1.09-1.94) were all significantly associated with higher odds for MCI. In those aged ≥65 years, underweight (OR = 0.71; 95% CI = 0.54-0.95) and overweight (OR = 0.72; 95% CI = 0.55-0.94) were associated with significantly lower odds for MCI, while obesity was not significantly associated with MCI. CONCLUSION: The results of the study suggest that the association between BMI and MCI is likely moderated by age. Future longitudinal studies are required to confirm or refute the present findings before recommendations for policy and practice can be made.

Cannabidiol Ameliorates Cognitive Function via Regulation of IL-33 and TREM2 Upregulation in a Murine Model of Alzheimer's Disease. - Khodadadi, Hesam; Salles, Évila Lopes; Jarrahi, Abbas; Costigliola, Vincenzo; Khan, M B; Yu, Jack C; Morgan, John C; Hess, David C; Vaibhav, Kumar; Dhandapani, Krishnan M; Baban, Babak (J Alzheimers Dis, 2021)
There is a dire need for due innovative therapeutic modalities to improve outcomes of AD patients. In this study, we tested whether cannabidiol (CBD) improves outcomes in a translational model of familial AD and to investigate if CBD regulates interleukin (IL)-33 and triggering receptor expressed on myeloid cells 2 (TREM2), which are associated with improved cognitive function. CBD was administered to 5xFAD mice, which recapitulate early onset, familial AD. Behavioral tests and immunoassays were used to evaluate cognitive and motor outcomes. Our findings suggest that CBD treatment enhanced IL-33 and TREM2 expression, ameliorated the symptoms of AD, and retarded cognitive decline.
Keywords: Alzheimer Disease; Animals; Cannabidiol; Cognition; Disease Models, Animal; Humans; Interleukin-33; Male; Membrane Glycoproteins; Mice; Mice, Transgenic; Receptors, Immunologic; Up-Regulation

Cerebrospinal Fluid Sulfatide Levels Lack Diagnostic Utility in the Subcortical Small Vessel Type of Dementia. - Svensson, Johan; Blomqvist, Maria; Kettunen, Petronella; Eckerström, Carl; Henricsson, Marcus; Jonsson, Michael; Bjerke, Maria; Månsson, Jan-Eric; Wallin, Anders (J Alzheimers Dis, 2021)
BACKGROUND: Sulfatides (STs) in cerebrospinal fluid (CSF), as well as magnetic resonance imaging (MRI)-detected white matter hyperintensities (WMHs), may reflect demyelination. Here, we investigated the diagnostic utility of CSF ST levels in the subcortical small vessel type of dementia (SSVD), which is characterized by the presence of brain WMHs. OBJECTIVE: To study the diagnostic utility of CSF ST levels in SSVD. METHODS: This was a mono-center, cross-sectional study of SSVD (n = 16), Alzheimer's disease (n = 40), mixed dementia (n = 27), and healthy controls (n = 33). Totally, 20 ST species were measured in CSF by liquid chromatography-mass spectrometry (LC-MS/MS). RESULTS: CSF total ST levels, as well as CSF levels of hydroxylated and nonhydroxylated ST species, did not differ across the study groups. In contrast, CSF neurofilament light chain (NFL) levels separated the patient groups from the controls. CSF total ST level correlated with CSF/serum albumin ratio in the total study population (r = 0.64, p <  0.001) and in all individual study groups. Furthermore, CSF total ST level correlated positively with MRI-estimated WMH volume in the total study population (r = 0.30, p <  0.05), but it did not correlate with CSF NFL level. CONCLUSION: Although there was some relation between CSF total ST level and WMH volume, CSF ST levels were unaltered in all dementia groups compared to the controls. This suggests that CSF total ST level is a poor biomarker of demyelination in SSVD. Further studies are needed to investigate the mechanisms underlying the marked correlation between CSF total ST level and CSF/serum albumin ratio.

Cognitive Effects of the BET Protein Inhibitor Apabetalone: A Prespecified Montreal Cognitive Assessment Analysis Nested in the BETonMACE Randomized Controlled Trial. - Cummings, Jeffrey; Schwartz, Gregory G; Nicholls, Stephen J; Khan, Aziz; Halliday, Chris; Toth, Peter P; Sweeney, Michael; Johansson, Jan O; Wong, Norman C W; Kulikowski, Ewelina; Kalantar-Zadeh, Kamyar; Lebioda, Kenneth; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Epigenetic changes may contribute importantly to cognitive decline in late life including Alzheimer's disease (AD) and vascular dementia (VaD). Bromodomain and extra-terminal (BET) proteins are epigenetic "readers" that may distort normal gene expression and contribute to chronic disorders. OBJECTIVE: To assess the effects of apabetalone, a small molecule BET protein inhibitor, on cognitive performance of patients 70 years or older participating in a randomized trial of patients at high risk for major cardiovascular events (MACE). METHODS: The Montreal Cognitive Assessment (MoCA) was performed on all patients 70 years or older at the time of randomization. 464 participants were randomized to apabetalone or placebo in the cognition sub-study. In a prespecified analysis, participants were assigned to one of three groups: MoCA score≥26 (normal performance), MoCA score 25-22 (mild cognitive impairment), and MoCA score≤21 (dementia). Exposure to apabetalone was equivalent in the treatment groups in each MoCA-defined group. RESULTS: Apabetalone was associated with an increased total MoCA score in participants with baseline MoCA score of≤21 (p = 0.02). There was no significant difference in change from baseline in the treatment groups with higher MoCA scores. In the cognition study, more patients randomized to apabetalone discontinued study drug for adverse effects (11.3% versus 7.9%). CONCLUSION: In this randomized controlled study, apabetalone was associated with improved cognition as measured by MoCA scores in those with baseline scores of 21 or less. BET protein inhibitors warrant further investigation for late life cognitive disorders.
Keywords: Aged; Cardiovascular Diseases; Cognitive Dysfunction; Epigenesis, Genetic; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Quinazolinones

A Cost-Consequence Analysis of Different Screening Procedures in Alzheimer's Disease: Results from the MOPEAD Project. - Wimo, Anders; Belger, Mark; Bon, Jaka; Jessen, Frank; Dumas, Annette; Kramberger, Milica G; Jamilis, Laura; Johansson, Gunilla; Rodrigo Salas, Adrián; Rodríguez Gómez, Octavio; Sannemann, Lena; Stoekenbroek, Malou; et al. (J Alzheimers Dis, 2021)
BACKGROUND: For care planning and support, under-detection and late diagnosis of Alzheimer's disease (AD) is a great challenge. Models of Patient-Engagement for Alzheimer's Disease (MOPEAD) is an EU-funded project aiming at testing different strategies to improve this situation. OBJECTIVE: To make a cost-consequence analysis of MOPEAD. METHODS: Four screening strategies were tested in five countries (Germany, the Netherlands, Slovenia, Spain, and Sweden): 1) a web-approach; 2) Open-House initiative; 3) in primary care; and 4) by diabetes specialists. Persons-at-risk of AD in all strategies were offered referral to a hospital-based specialist. The primary health-economic outcome was the cost per true-positive case (TP) of AD from the screened population. RESULTS: Of 2,847 screened persons, 1,121 screened positive (39%), 402 were evaluated at memory clinics (14%), and 236 got an AD diagnosis (8%). The cost per TP of those screened was 3,115€ with the web-approach, 2,722€ with the Open-House, 1,530€ in primary care, and 1,190€ by diabetes specialists. Sensitivity analyses that more likely reflect the real-world situation confirmed the results. The number-needed-to-screen was 30 with the web-approach, 8 with the Open-House and primary care, and 6 with the diabetes specialists.There were country differences in terms of screening rates, referrals to memory clinics, staff-types involved, and costs per TP. CONCLUSION: In primary care and by the diabetes specialist, the costs per TP/screened population were lowest, but the capacity of such settings to identify cases with AD-risk must be discussed. Hence new diagnostic strategies such as web-solutions and Open-House initiatives may be valuable after modifications.

Current and Future Prevalence Estimates of Mild Cognitive Impairment, Dementia, and Its Subtypes in a Population-Based Sample of People 70 Years and Older in Norway: The HUNT Study. - GjØra, Linda; Strand, Bjørn Heine; Bergh, Sverre; Borza, Tom; Brækhus, Anne; Engedal, Knut; Johannessen, Aud; Kvello-Alme, Marte; Krokstad, Steinar; Livingston, Gill; Matthews, Fiona E; Myrstad, Christian; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Having accurate, up-to-date information on the epidemiology of mild cognitive impairment (MCI) and dementia is imperative. OBJECTIVE: To determine the prevalence of MCI and dementia in Norway using data from a large population-based study. METHODS: All people 70 + years of age, n = 19,403, in the fourth wave of the Trøndelag Health Study (HUNT4) were invited to participate in the study HUNT4 70 + . Trained health personnel assessed participants using cognitive tests at a field station, at homes, or at their nursing home. Interviewers also completed a structured carer questionnaire in regard to participants suspected of having dementia. Clinical experts made diagnoses according to DSM-5 criteria. We calculated prevalence weighing the data to ensure population representativeness. RESULTS: A total of 9,930 (51.2%) of the possible 19,403 people participated, and 9,663 of these had sufficient information for analysis. Standardized prevalence of dementia and MCI was 14.6% (95% confidence interval (CI) 13.9-15.4) and 35.3% (95% CI 34.3-36.4), respectively. Dementia was more prevalent in women and MCI more prevalent in men. The most prevalent dementia subtype was Alzheimer's disease (57%). By adding data collected from a study of persons < 70 years in the same region, we estimate that there are 101,118 persons with dementia in Norway in 2020, and this is projected to increase to 236,789 and 380,134 in 2050 and 2100, respectively. CONCLUSION: We found a higher prevalence of dementia and MCI than most previous studies. The present prevalence and future projections are vital for preparing for future challenges to the healthcare system and the entire society.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Dementia; Female; Forecasting; Humans; Male; Mental Status and Dementia Tests; Neuropsychological Tests; Norway; Prevalence; Sex Factors; Surveys and Questionnaires

Dementia and Parkinson's Disease: Risk Factors for 30-Day Mortality in Nursing Home Residents with COVID-19. - Rutten, Jeanine J S; van Kooten, Janine; van Loon, Anouk M; van Buul, Laura W; Joling, Karlijn J; Smalbrugge, Martin; Hertogh, Cees M P M (J Alzheimers Dis, 2021)
BACKGROUND: The COVID-19 pandemic has led to high mortality rates in nursing homes (NHs) in Europe. For adequate risk management and good prognostications, it is essential to identify mortality risk factors. OBJECTIVE: This study aimed to determine whether previously identified risk factors for 30-day mortality in Dutch NH residents with COVID-19 are unique to COVID-19. METHODS: In this cohort study, we included 1,294 NH residents with COVID-19 (cases) and 17,999 NH residents without COVID-19 (controls, from the pre-COVID-19 period). We used descriptive statistics and Cox proportional hazard models to compare mortality rates in residents with and without COVID-19, categorized by risk factors. RESULTS: Cases had a more than 18 times higher hazard of death within 30 days compared to controls (HR 18, 95%CI: 16-20). For residents with COVID-19, being male, having dementia, and having Parkinson's disease (PD) were all associated with a higher 30-day mortality (HR 1.8 versus 1.3 versus 1.7). Being male was also associated with a higher mortality (HR 1.7) in the control group, whereas having dementia and PD were not. COVID-19 symptomatology was very similar for residents with and without dementia or PD, except for delirium and malaise which was more frequent in residents with dementia. CONCLUSION: Dementia and PD were significant additional risk factors for mortality in Dutch NH residents with COVID-19, whereas male gender was not unique to residents with COVID-19. The frailty of PD and dementia in NH residents with COVID-19 are relevant to consider in prognostication, communication, and care planning with residents and their families.

Depression and Dementia: The Role of Cortisol and Vascular Brain Lesions. AGES-Reykjavik Study. - Gerritsen, Lotte; Twait, Emma L; Jonsson, Palmi V; Gudnason, Vilmundur; Launer, Lenore J; Geerlings, Mirjam I (J Alzheimers Dis, 2021)
BACKGROUND: Late-life depression (LLD) is related to an increased risk of developing dementia; however, the biological mechanisms explaining this relationship remain unclear. OBJECTIVE: To determine whether the relationship between LLD and dementia can be best explained by the glucocorticoid cascade or vascular hypothesis. METHODS: Data are from 4,354 persons (mean age 76±5 years) without dementia at baseline from the AGES-Reykjavik Study. LLD was assessed with the MINI diagnostic interview (current and remitted major depressive disorder [MDD]) and the Geriatric Depression Scale-15. Morning and evening salivary cortisol were collected (glucocorticoid cascade hypothesis). White matter hyperintensities (WMH; vascular hypothesis) volume was assessed using 1.5T brain MRI. Using Cox proportional hazard models, we estimated the associations of LLD, cortisol levels, and WMH volume with incident all-cause dementia, AD, and non-AD dementia. RESULTS: During 8.8±3.2 years of follow-up, 843 persons developed dementia, including 397 with AD. Current MDD was associated with an increased risk of developing all-cause dementia (HR = 2.17; 95% CI 1.66-2.67), with risks similar for AD and non-AD, while remitted MDD was not (HR = 1.02; 95% CI 0.55-1.49). Depressive symptoms were also associated with increased risk of dementia, in particular non-AD dementias. Higher levels of evening cortisol increased risk of dementia, but this was independent of MDD. WMH partially explained the relation between current MDD and dementia risk but remained increased (HR = 1.71; 95% CI 1.34-2.08). CONCLUSION: The current study highlights the importance of LLD in developing dementia. However, neither the glucocorticoid cascade nor the vascular hypotheses fully explained the relation between depression and dementia.

Effects of Peroral Omega-3 Fatty Acid Supplementation on Cerebrospinal Fluid Biomarkers in Patients with Alzheimer's Disease: A Randomized Controlled Trial-The OmegAD Study. - Tofiq, Avin; Zetterberg, Henrik; Blennow, Kaj; Basun, Hans; Cederholm, Tommy; Eriksdotter, Maria; Faxen-Irving, Gerd; Hjorth, Erik; Jernerén, Fredrik; Schultzberg, Marianne; Wahlund, Lars-Olof; Palmblad, Jan; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Studies have suggested a connection between a decrease in the levels of polyunsaturated fatty acids (PUFAs) and Alzheimer's disease (AD). We aimed to assess the effect of supplementation with omega-3 fatty acids (n-3 FAs) on biomarkers analyzed in the cerebrospinal fluid (CSF) of patients diagnosed with AD. OBJECTIVE: To investigate the effects of daily supplementation with 2.3 g of PUFAs in AD patients on the biomarkers in CSF described below. We also explored the possible correlation between these biomarkers and the performance in the cognitive test Mini-Mental State Examination (MMSE). METHODS: Thirty-three patients diagnosed with AD were randomized to either treatment with a daily intake of 2.3 g of n-3 FAs (n  =  18) or placebo (n  =  15). CSF samples were collected at baseline and after six months of treatment, and the following biomarkers were analyzed: Aβ 38, Aβ 40, Aβ 42, t-tau, p-tau, neurofilament light (NfL), chitinase-3-like protein 1 (YKL-40), acetylcholinesterase (AChE), butyrylcholinesterase (BuChE), soluble IL-1 receptor type II (sIL-1RII), and IL-6. RESULTS: There were no significant differences between the groups concerning the level of the different biomarkers in the CSF at baseline. Within the treatment group, there was a small but significant increase in both YKL-40 (p = 0.04) and NfL (p = 0.03), while the other CSF biomarkers remained stable. CONCLUSION: Supplementation with n-3 FAs had a statistically significant effect on NfL and YKL-40, resulting in an increase of both biomarkers, indicating a possible increase of inflammatory response and axonal damage. This increase in biomarkers did not correlate with MMSE score.

Elevated Norepinephrine Metabolism Gauges Alzheimer's Disease-Related Pathology and Memory Decline. - Riphagen, Joost M; van Egroo, Maxime; Jacobs, Heidi I L (J Alzheimers Dis, 2021)
The noradrenergic (NE) locus coeruleus (LC) is vulnerable to hyperphosphorylated tau, and dysregulated NE-metabolism is linked to greater tau and disease progression. We investigated whether elevated NE-metabolism alone predicts memory decline or whether concomitant presence of tau and amyloid-β is required. Among 114 memory clinic participants, time trends (max. six years) showed dose-response declines in learning across groups with elevated NE-metabolite 3-methoxy-4-hydroxyphenylethyleneglycol (MHPG) with no, one, or two Alzheimer's disease biomarkers; and no decline in the low MHPG group. Elevated MHPG is required and sufficient to detect learning declines, supporting a pathophysiologic model including the LC-NE system contributing to initial Alzheimer's disease-related processes.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Cohort Studies; Disease Progression; Female; Humans; Learning; Locus Coeruleus; Male; Memory Disorders; Methoxyhydroxyphenylglycol; Middle Aged; Neuropsychological Tests; Norepinephrine; Predictive Value of Tests; tau Proteins

Gut Microbiota Changes and Their Correlation with Cognitive and Neuropsychiatric Symptoms in Alzheimer's Disease. - Zhou, Yunzhe; Wang, Yan; Quan, Meina; Zhao, Huiying; Jia, Jianping (J Alzheimers Dis, 2021)
BACKGROUND: Gut microbiota can influence human brain function and behavior. Recent studies showed that gut microbiota might play an important role in the pathogenesis of Alzheimer's disease (AD). OBJECTIVE: To investigate the composition of gut microbiota in AD patients and their association with cognitive function and neuropsychiatric symptoms (NPS). METHODS: The fecal samples from 60 AD patients (30 with NPS and 30 without NPS) and 32 healthy control subjects (HC) were collected and analyzed by 16S ribosomal RNA sequencing. The functional variations of gut microbiota were predicted using Phylogenetic Investigation of Communities by Reconstruction of Unobserved States. The correlation between different bacterial taxa and cognitive (Mini-Mental State Examination (MMSE), Clinical Dementia Rating (CDR)), and NPS measures were analyzed. RESULTS: The fecal microbial composition of AD patients was quite distinct from HC. Bifidobacterium, Sphingomonas, Lactobacillus, and Blautia were enriched, while Odoribacter, Anaerobacterium, and Papillibacter were reduced. AD patients with NPS showed decreased Chitinophagaceae, Taibaiella, and Anaerobacterium compared with those without NPS. Functional pathways were different between AD and HC, and between AD patients with and without NPS. Correlation analysis showed that Sphingomonas correlated negatively with MMSE; Anaerobacterium and Papillibacter correlated positively with MMSE and negatively with CDR. Cytophagia, Rhodospirillaceae, and Cellvibrio correlated positively with NPS, while Chitinophagaceae, Taibaiella, and Anaerobacterium correlated negatively with NPS. CONCLUSION: AD patients have gut microbiota alterations related to cognition, and differential taxa between AD patients with and without NPS associated differently with NPS domains, which helps further understand the pathogenesis of AD and explore potential therapeutic targets.

Hippocampal Functional Connectivity and Memory Performance After Exercise Intervention in Older Adults with Mild Cognitive Impairment. - Won, Junyeon; Callow, Daniel D; S Pena, Gabriel; Jordan, Leslie S; Arnold-Nedimala, Naomi A; Nielson, Kristy A; Smith, J Carson (J Alzheimers Dis, 2021)
BACKGROUND: Exercise training (ET) has neuroprotective effects in the hippocampus, a key brain region for memory that is vulnerable to age-related dysfunction. OBJECTIVE: We investigated the effects of ET on functional connectivity (FC) of the hippocampus in older adults with mild cognitive impairment (MCI) and a cognitively normal (CN) control group. We also assessed whether the ET-induced changes in hippocampal FC (Δhippocampal-FC) are associated with changes in memory task performance (Δmemory performance). METHODS: 32 older adults (77.0±7.6 years; 16 MCI and 16 CN) participated in the present study. Cardiorespiratory fitness tests, memory tasks (Rey Auditory Verbal Learning Test (RAVLT) and Logical Memory Test (LM)), and resting-state fMRI were administered before and after a 12-week walking ET intervention. We utilized a seed-based correlation analysis using the bilateral anterior and posterior hippocampi as priori seed regions of interest. The associations of residualized ET-induced Δhippocampal-FC and Δmemory performance were assessed using linear regression. RESULTS: There were significant improvements in RAVLT Trial 1 and LM test performance after ET across participants. At baseline, MCI, compared to CN, demonstrated significantly lower posterior hippocampal FC. ET was associated with increased hippocampal FC across groups. Greater ET-related anterior and posterior hippocampal FC with right posterior cingulate were associated with improved LM recognition performance in MCI participants. CONCLUSION: Our findings indicate that hippocampal FC is significantly increased following 12-weeks of ET in older adults and, moreover, suggest that increased hippocampal FC may reflect neural network plasticity associated with ET-related improvements in memory performance in individuals diagnosed with MCI.

How Do Persons with Young and Late Onset Dementia Die? - Roβmeier, Carola; Hartmann, Julia; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Schneider-Schelte, Helga; Jox, Ralf J; Dinkel, Andreas; Diehl-Schmid, Janine (J Alzheimers Dis, 2021)
BACKGROUND: End of life symptoms and symptom management as well as the quality of dying (QoD) of persons with advanced dementia (PWAD) have not yet been systematically studied in Germany. OBJECTIVE: 1) To investigate symptoms, treatment and care at the end of life, advance care planning, and circumstances of death of recently deceased PWAD; 2) To determine whether there are differences between young and late onset dementia (YOD and LOD). METHODS: The study was performed in the context of the project EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of Young-onset and Late-Onset dementia in Germany). Closest relatives of recently deceased patients with advanced YOD (N = 46) and LOD (N = 54) living at home or in long term care were interviewed. RESULTS: Circumstances of death, symptoms, and treatment appeared to be similar between YOD and LOD, except that persons with LOD had significantly more somatic comorbidities and were admitted to hospital in the last three months of life more often than persons with LOD. At end of life, 60% of PWAD appeared to be "at peace". Difficulty swallowing, gurgling, shortness of breath, and discomfort were observed most frequently. Large interindividual differences in suffering and QoD were present. Determinants of QoD were not identified. CONCLUSION: Our findings suggest that low QoD was caused by inadequate recognition and/or insufficient treatment of burdensome physical and emotional symptoms. PWADs' needs should be assessed regularly, and strategies focusing on treatment and implementing support for both the patient and caregiver must be established.
Keywords: Advance Care Planning; Age of Onset; Aged; Aged, 80 and over; Caregivers; Dementia; Female; Humans; Long-Term Care; Male; Palliative Care; Quality of Life

Impact of 40 Hz Transcranial Alternating Current Stimulation on Cerebral Tau Burden in Patients with Alzheimer's Disease: A Case Series. - Dhaynaut, Maeva; Sprugnoli, Giulia; Cappon, Davide; Macone, Joanna; Sanchez, Justin S; Normandin, Marc; Guehl, Nicolas; Koch, Giacomo; Paciorek, Rachel; Connor, Ann; Press, Daniel; Johnson, Keith; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is characterized by diffuse amyloid-β (Aβ) and phosphorylated Tau (p-Tau) aggregates as well as neuroinflammation. Exogenously-induced 40 Hz gamma oscillations have been showing to reduce Aβ and p-Tau deposition presumably via microglia activation in AD mouse models. OBJECTIVE: We aimed to translate preclinical data on gamma-induction in AD patients by means of transcranial alternating current stimulation (tACS). METHODS: Four participants with mild-to-moderate AD received 1 h of daily 40 Hz (gamma) tACS for 4 weeks (Monday to Friday) targeting the bitemporal lobes (20 h treatment duration). Participant underwent Aβ, p-Tau, and microglia PET imaging with [11C]-PiB, [18F]-FTP, and [11C]-PBR28 respectively, before and after the intervention along with electrophysiological assessment. RESULTS: No adverse events were reported, and an increase in gamma spectral power on EEG was observed after the treatment. [18F]-FTP PET revealed a significant decrease over 2% of p-Tau burden in 3/4 patients following the tACS treatment, primarily involving the temporal lobe regions targeted by tACS and especially mesial regions (e.g., entorhinal cortex). The amount of intracerebral Aβ as measured by [11C]-PiB was not significantly influenced by tACS, whereas 1/4 reported a significant decrease of microglia activation as measured by [11C]-PBR28. CONCLUSION: tACS seems to represent a safe and feasible option for gamma induction in AD patients, with preliminary evidence of a possible effect on protein clearance partially mimicking what is observed in animal models. Longer interventions and placebo control conditions are needed to fully evaluate the potential for tACS to slow disease progression.

Impacts of Iron Metabolism Dysregulation on Alzheimer's Disease. - Jouini, Najla; Saied, Zakaria; Ben Sassi, Samia; Nebli, Fatma; Messaoud, Taieb; Hentati, Faycel; Belal, Samir (J Alzheimers Dis, 2021)
BACKGROUND: Iron plays an important role in maintaining cell survival, with normal iron trafficking known to be regulated by the ceruloplasmin-transferrin (Cp-Tf) antioxidant system. Disruption to this system is thought to be detrimental to normal brain function. OBJECTIVE: To determine whether an imbalance of iron and the proteins involved in its metabolism (ceruloplasmin and transferrin) are linked to Alzheimer's disease (AD) and to the expression of amyloid-beta (Aβ) peptide 1-42 (Aβ 1-42), which is a major species of Aβ, and the most toxic. METHODS: We evaluated the concentrations of iron, calcium, magnesium, and Aβ 1-42 in the cerebrospinal fluid (CSF) of patients with AD and cognitively normal controls. Correlations between the components of the Cp-Tf antioxidant system in plasma were studied to determine the role of peripheral blood in the onset and/or development of AD. We used commercial ELISA immunoassays to measure Aβ 1-42, immunoturbidimetry to quantify ceruloplasmin and transferrin, and colorimetry to quantify iron, calcium, and magnesium. RESULTS: We found that the AD group had lower CSF concentrations of Aβ 1-42 (p <  0.001) and calcium (p <  0.001), but a higher CSF concentration of iron (p <  0.001). Significantly lower plasma concentrations of ceruloplasmin (p = 0.003), transferrin (mean, p <  0.001), and iron (p <  0.001) were observed in the AD group than in cognitively normal adults. Moreover, we found a strong interdependence between most of these components. CONCLUSION: Iron dyshomeostasis has a crucial role in the onset of AD and/or its development. Correcting metal misdistribution is an appealing therapeutic strategy for AD.

Improving the Diagnosis of the Frontal Variant of Alzheimer's Disease with the DAPHNE Scale. - Lehingue, Elsa; Gueniat, Julien; Jourdaa, Sandra; Hardouin, Jean BenoÎt; Pallardy, Amandine; Courtemanche, Hélène; Rocher, Laetitia; Etcharry-Bouyx, Frédérique; Auriacombe, Sophie; Mollion, Hélène; Formaglio, Maıté; Rouaud, Olivier; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The frontal variant of Alzheimer's disease (fAD) is poorly understood and poorly defined. The diagnosis remains challenging. The main differential diagnosis is the behavioral variant of frontotemporal degeneration (bvFTD). For fAD, there is some dissociation between the clinical frontal presentation and imaging and neuropathological studies, which do not always find a specific involvement of the frontal lobes. DAPHNE is a behavioral scale, which demonstrated excellent performance to distinguish between bvFTD and AD. OBJECTIVE: The aim of the present study was to assess the reliability of this new tool to improve the clinical diagnosis of fAD. METHODS: Twenty fAD patients and their caregivers were prospectively included and were compared with 36 bvFTD and 22 AD patients. RESULTS: The three main behavioral disorders in the fAD patients were apathy, loss of empathy, and disinhibition. Three disorders were discriminant because they were less frequent and less severe in the fAD patients than in the bvFTD patients, namely hyperorality, neglect, and perseverations. This specific pattern of behavioral disorders was corroborated by SPECT or 18FDG PET-CT scan that showed that patients with fAD could have a medial frontal hypoperfusion, whereas in bvFTD patients the orbitofrontal cortex was the main involved region, with more diffuse hypoperfusion. CONCLUSION: We demonstrated that DAPHNE had good sensitivity and good specificity to discriminate between the three groups and in particular between fAD and bvFTD patients. DAPHNE is a quick tool that could help clinicians in memory clinics not only to differentiate bvFTD from typical AD but also from fAD.
Keywords: Aged; Alzheimer Disease; Cohort Studies; Diagnosis, Differential; Female; Frontal Lobe; Frontotemporal Dementia; Humans; Male; Middle Aged; Neuropsychological Tests

Lipidomic Network of Mild Cognitive Impairment from the Mayo Clinic Study of Aging. - Wang, Xuewei; Bui, Hai; Vemuri, Prashanthi; Graff-Radford, Jonathan; Jack, Clifford R; Petersen, Ronald C; Mielke, Michelle M (J Alzheimers Dis, 2021)
BACKGROUND: Lipid alterations contribute to Alzheimer's disease (AD) pathogenesis. Lipidomics studies could help systematically characterize such alterations and identify potential biomarkers. OBJECTIVE: To identify lipids associated with mild cognitive impairment and amyloid-β deposition, and to examine lipid correlation patterns within phenotype groupsMethods:Eighty plasma lipids were measured using mass spectrometry for 1,255 non-demented participants enrolled in the Mayo Clinic Study of Aging. Individual lipids associated with mild cognitive impairment (MCI) were first identified. Correlation network analysis was then performed to identify lipid species with stable correlations across conditions. Finally, differential correlation network analysis was used to determine lipids with altered correlations between phenotype groups, specifically cognitively unimpaired versus MCI, and with elevated brain amyloid versus without. RESULTS: Seven lipids were associated with MCI after adjustment for age, sex, and APOE4. Lipid correlation network analysis revealed that lipids from a few species correlated well with each other, demonstrated by subnetworks of these lipids. 177 lipid pairs differently correlated between cognitively unimpaired and MCI patients, whereas 337 pairs of lipids exhibited altered correlation between patients with and without elevated brain amyloid. In particular, 51 lipid pairs showed correlation alterations by both cognitive status and brain amyloid. Interestingly, the lipids central to the network of these 51 lipid pairs were not significantly associated with either MCI or amyloid, suggesting network-based approaches could provide biological insights complementary to traditional association analyses. CONCLUSION: Our attempt to characterize the alterations of lipids at network-level provides additional insights beyond individual lipids, as shown by differential correlations in our study.

Longitudinally Increasing Elevated Asymmetric Flortaucipir Binding in a Cognitively Unimpaired Amyloid-Negative Older Individual. - Schwarz, Christopher G; Knopman, David S; Ramanan, Vijay K; Lowe, Val J; Wiste, Heather J; Cogswell, Petrice M; Utianski, Rene L; Senjem, Matthew L; Gunter, Jeffrey R; Vemuri, Prashanthi; Petersen, Ronald C; Jack, Clifford R (J Alzheimers Dis, 2021)
We present the case of a cognitively unimpaired 77-year-old man with elevated, asymmetric, and longitudinally increasing Flortaucipir tau PET despite normal (visually negative) amyloid PET. His atypical tau PET signal persisted and globally increased in a follow-up scan five years later. Across eight years of observations, temporoparietal atrophy was observed consistent with tau PET patterns, but he retained the cognitively unimpaired classification. Altogether, his atypical tau PET signal is not explained by any known risk factors or alternative pathologies, and other imaging findings were not remarkable. He remains enrolled for further observation.

Memory-Related Frontal Brainwaves Predict Transition to Mild Cognitive Impairment in Healthy Older Individuals Five Years Before Diagnosis. - Jiang, Yang; Li, Juan; Schmitt, Frederick A; Jicha, Gregory A; Munro, Nancy B; Zhao, Xiaopeng; Smith, Charles D; Kryscio, Richard J; Abner, Erin L (J Alzheimers Dis, 2021)
BACKGROUND: Early prognosis of high-risk older adults for amnestic mild cognitive impairment (aMCI), using noninvasive and sensitive neuromarkers, is key for early prevention of Alzheimer's disease. We have developed individualized measures in electrophysiological brain signals during working memory that distinguish patients with aMCI from age-matched cognitively intact older individuals. OBJECTIVE: Here we test longitudinally the prognosis of the baseline neuromarkers for aMCI risk. We hypothesized that the older individuals diagnosed with incident aMCI already have aMCI-like brain signatures years before diagnosis. METHODS: Electroencephalogram (EEG) and memory performance were recorded during a working memory task at baseline. The individualized baseline neuromarkers, annual cognitive status, and longitudinal changes in memory recall scores up to 10 years were analyzed. RESULTS: Seven of the 19 cognitively normal older adults were diagnosed with incident aMCI for a median 5.2 years later. The seven converters' frontal brainwaves were statistically identical to those patients with diagnosed aMCI (n = 14) at baseline. Importantly, the converters' baseline memory-related brainwaves (reduced mean frontal responses to memory targets) were significantly different from those who remained normal. Furthermore, differentiation pattern of left frontal memory-related responses (targets versus nontargets) was associated with an increased risk hazard of aMCI (HR = 1.47, 95% CI 1.03, 2.08). CONCLUSION: The memory-related neuromarkers detect MCI-like brain signatures about five years before diagnosis. The individualized frontal neuromarkers index increased MCI risk at baseline. These noninvasive neuromarkers during our Bluegrass memory task have great potential to be used repeatedly for individualized prognosis of MCI risk and progression before clinical diagnosis.
Keywords: Aged; Brain Waves; Cognition; Cognitive Dysfunction; Electroencephalography; Female; Humans; Longitudinal Studies; Male; Memory, Short-Term; Neuropsychological Tests; Prodromal Symptoms

Metabolites Associated with Early Cognitive Changes Implicated in Alzheimer's Disease. - Darst, Burcu F; Huo, Zhiguang; Jonaitis, Erin M; Koscik, Rebecca L; Clark, Lindsay R; Lu, Qiongshi; Kremen, William S; Franz, Carol E; Rana, Brinda; Lyons, Michael J; Hogan, Kirk J; Zhao, Jinying; et al. (J Alzheimers Dis, 2021)

MIND Diet, Common Brain Pathologies, and Cognition in Community-Dwelling Older Adults. - Dhana, Klodian; James, Bryan D; Agarwal, Puja; Aggarwal, Neelum T; Cherian, Laurel J; Leurgans, Sue E; Barnes, Lisa L; Bennett, David A; Schneider, Julie A (J Alzheimers Dis, 2021)
BACKGROUND: MIND diet, a hybrid of the Mediterranean diet and the Dietary Approaches to Stop Hypertension diet, is associated with a slower cognitive decline and lower risk of Alzheimer's disease (AD) dementia in older adults. OBJECTIVE: We aim to examine whether the association of the MIND diet with cognition is independent of common brain pathologies. METHODS: Utilizing data from the Rush Memory and Aging Project (MAP), a longitudinal clinical-pathologic study, we studied 569 decedents with valid dietary data, cognitive testing proximate to death, and complete autopsy data at the time of these analyses. A series of regression analyses were used to examine associations of the MIND diet, dementia-related brain pathologies, and global cognition proximate to death adjusting for age, sex, education, APOEɛ4, late-life cognitive activities, and total energy intake. RESULTS: A higher MIND diet score was associated with better global cognitive functioning proximate to death (β= 0.119, SE = 0.040, p = 0.003), and neither the strength nor the significance of association changed substantially when AD pathology and other brain pathologies were included in the model. The β-estimate after controlling for global AD pathology was 0.111 (SE = 0.037, p = 0.003). The MIND diet-cognition relationship remained significant when we restricted our analysis to individuals without mild cognitive impairment at the baseline (β= 0.121, SE = 0.042, p = 0.005) or in people diagnosed with postmortem diagnosis of AD based on NIA-Reagan consensus recommendations (β= 0.114, SE = 0.050, p = 0.023). CONCLUSION: MIND diet is associated with better cognitive functioning independently of common brain pathology, suggesting that the MIND diet may contribute to cognitive resilience in the elderly.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid; Autopsy; Brain; Chicago; Cognition; Diet, Mediterranean; Female; Humans; Independent Living; Longitudinal Studies; Male; Neuropsychological Tests; Surveys and Questionnaires

Modifiable Barriers for Recruitment and Retention of Older Adults Participants from Underrepresented Minorities in Alzheimer's Disease Research. - Indorewalla, Khushnoo K; O'Connor, Maureen K; Budson, Andrew E; Guess DiTerlizzi, Christina; Jackson, Jonathan (J Alzheimers Dis, 2021)
Clinical Alzheimer's disease (AD) trials currently face a critical shortfall of thousands of eligible participants, which inflates the duration and cost of the clinical study as well as threatens the scientific merit of promising clinical interventions. This recruitment crisis is further compounded by the fact that underrepresented and marginalized populations-particularly those identifying as a racial or ethnic minority, those with low socioeconomic status, or living in rural areas-have been historically underrepresented in ongoing AD clinical trials despite overwhelming evidence that such populations are at increased risk for developing dementia. As a result of various recruitment barriers, current AD clinical studies frequently reflect a decreasingly representative segment of the US population, which threatens the overall generalizability of these findings. The current narrative review provides an updated examination and critique of common recruitment barriers and potential solutions, as well as a discussion of theoretical approaches that may address barriers disproportionately experienced by underrepresented communities. AD clinical researchers are encouraged to take purposive action aimed at increasing diversity of enrolled AD clinical trial cohorts by actively identifying and quantifying barriers to research participation-especially recruitment barriers and health disparities that disproportionately prevent underrepresented and marginalized populations from participating in research. Furthermore, researchers are encouraged to closely track which individuals who express interest in AD research ultimately enroll in research studies to examine whether AD research participation is appropriately representative of the intended population for whom these new and novel AD interventions are being designed.
Keywords: Alzheimer Disease; Clinical Trials as Topic; Humans; Minority Groups; Patient Selection

Paraoxonase 1, B Vitamins Supplementation, and Mild Cognitive Impairment. - Perła-Kaján, Joanna; Włoczkowska, Olga; Zioła-Frankowska, Anetta; Frankowski, Marcin; David Smith, A; de Jager, Celeste A; Refsum, Helga; Jakubowski, Hieronim (J Alzheimers Dis, 2021)
BACKGROUND: Identification of modifiable risk factors that affect cognitive decline is important for the development of preventive and treatment strategies. Status of paraoxonase 1 (PON1), a high-density lipoprotein-associated enzyme, may play a role in the development of neurological diseases, including Alzheimer's disease. OBJECTIVE: We tested a hypothesis that PON1 status predicts cognition in individuals with mild cognitive impairment (MCI). METHODS: Individuals with MCI (n = 196, 76.8-years-old, 60% women) participating in a randomized, double-blind placebo-controlled trial (VITACOG) were assigned to receive a daily dose of folic acid (0.8 mg), vitamin B12 (0.5 mg) and B6 (20 mg) (n = 95) or placebo (n = 101) for 2 years. Cognition was analyzed by neuropsychological tests. Brain atrophy was quantified in a subset of participants (n = 168) by MRI. PON1 status, including PON1 Q192R genotype, was determined by quantifying enzymatic activity of PON1 using paraoxon and phenyl acetate as substrates. RESULTS: In the placebo group, baseline phenylacetate hydrolase (PhAcase) activity of PON1 (but not paraoxonase activity or PON1 Q192R genotype) was significantly associated with global cognition (Mini-Mental State Examination, MMSE; Telephone Inventory for Cognitive Status-modified, TICS-m), verbal episodic memory (Hopkins Verbal Learning Test-revised: Total Recall, HVLT-TR; Delayed Recall, HVLT-DR), and attention/processing speed (Trail Making A and Symbol Digits Modalities Test, SDMT) at the end of study. In addition to PhAcase, baseline iron and triglycerides predicted MMSE, baseline fatty acids predicted SDMT, baseline anti-N-Hcy-protein autoantibodies predicted TICS-m, SDMT, Trail Making A, while BDNF V66M genotype predicted HVLT-TR and HVLT-DR scores at the end of study. B-vitamins abrogated associations of PON1 and other variables with cognition. CONCLUSION: PON1 is a new factor associated with impaired cognition that can be ameliorated by B-vitamins in individuals with MCI.

Periodontal Disease and Risk of Dementia in Medicare Patients with Hepatitis C Virus. - Malone, Joseph; Jung, Jeah; Tran, Linh; Zhao, Chen (J Alzheimers Dis, 2021)
BACKGROUND: Periodontal disease and hepatitis C virus (HCV) represent chronic infectious states that are common in elderly adults. Both conditions have independently been associated with an increased risk for dementia. Chronic infections are thought to lead to neurodegenerative changes in the central nervous system possibly by promoting a proinflammatory state. This is consistent with growing literature on the etiological role of infections in dementia. Few studies have previously evaluated the association of periodontal disease with dementia in HCV patients. OBJECTIVE: To examine whether periodontal disease increases the risk of developing Alzheimer's disease and related dementias (ADRD) among HCV patients in Medicare claims data. METHODS: We used Medicare claims data for HCV patients to assess the incidence rate of ADRD with and without exposure to periodontal disease between 2014 and 2017. Cox multivariate regression was used to estimate the association between periodontal disease and development of ADRD, controlling for age, gender, race, ZIP-level income and education, and medical comorbidities. RESULTS: Of 439,760 HCV patients, the incidence rate of ADRD was higher in patients with periodontal diseases compared to those without (10.84% versus 9.26%, p <  0.001), and those with periodontal disease developed ADRD earlier compared to those without periodontal disease (13.99 versus 21.60 months, p <  0.001). The hazard of developing ADRD was 1.35 times higher in those with periodontal disease (95% CI, 1.30 to 1.40, p <  0.001) after adjusting for all covariates, including age. CONCLUSION: Periodontal disease increased the risk of developing ADRD among HCV patients in a national Medicare claims dataset.

Plasma Total-Tau and Neurofilament Light Chain as Diagnostic Biomarkers of Alzheimer's Disease Dementia and Mild Cognitive Impairment in Adults with Down Syndrome. - Petersen, Melissa E; Rafii, Michael S; Zhang, Fan; Hall, James; Julovich, David; Ances, Beau M; Schupf, Nicole; Krinsky-McHale, Sharon J; Mapstone, Mark; Silverman, Wayne; Lott, Ira; Klunk, William; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The need for diagnostic biomarkers of cognitive decline is particularly important among aging adults with Down syndrome (DS). Growing empirical support has identified the utility of plasma derived biomarkers among neurotypical adults with mild cognitive impairment (MCI) and Alzheimer's disease (AD); however, the application of such biomarkers has been limited among the DS population. OBJECTIVE: This study aimed to investigate the cross-sectional diagnostic performance of plasma neurofilament light chain (Nf-L) and total-tau, individually and in combination among a cohort of DS adults. METHODS: Plasma samples were analyzed from n = 305 (n = 225 cognitively stable (CS); n = 44 MCI-DS; n = 36 DS-AD) participants enrolled in the Alzheimer's Biomarker Consortium -Down Syndrome. RESULTS: In distinguishing DS-AD participants from CS, Nf-L alone produced an AUC of 90%, total-tau alone reached 74%, and combined reached an AUC of 86%. When age and gender were included, AUC increased to 93%. Higher values of Nf-L, total-tau, and age were all shown to be associated with increased risk for DS-AD. When distinguishing MCI-DS participants from CS, Nf-L alone produced an AUC of 65%, while total-tau alone reached 56%. A combined model with Nf-L, total-tau, age, and gender produced an AUC of 87%. Both higher values in age and total-tau were found to increase risk for MCI-DS; Nf-L levels were not associated with increased risk for MCI-DS. CONCLUSION: Advanced assay techniques make total-tau and particularly Nf-L useful biomarkers of both AD pathology and clinical status in DS and have the potential to serve as outcome measures in clinical trials for future disease-modifying drugs.

Porphyromonas Gingivalis Infection Induces Synaptic Failure via Increased IL-1β Production in Leptomeningeal Cells. - Huang, Wanyi; Zeng, Fan; Gu, Yebo; Jiang, Muzhou; Zhang, Xinwen; Yan, Xu; Kadowaki, Tomoko; Mizutani, Shinsuke; Kashiwazaki, Haruhiko; Ni, Junjun; Wu, Zhou (J Alzheimers Dis, 2021)
BACKGROUND: Studies have reported that synaptic failure occurs before the Alzheimer's disease (AD) onset. The systemic Porphyromonas gingivalis (P. gingivalis) infection is involved in memory decline. We previously showed that leptomeningeal cells, covering the brain, activate glial cells by releasing IL-1β in response to systemic inflammation. OBJECTIVE: In the present study, we focused on the impact of leptomeningeal cells on neurons during systemic P. gingivalis infection. METHODS: The responses of leptomeningeal cells and cortical neurons to systemic P. gingivalis infection were examined in 15-month-old mice. The mechanism of IL-1β production by P. gingivalis infected leptomeningeal cells was examined, and primary cortical neurons were treated with P. gingivalis infected leptomeningeal cells condition medium (Pg LCM). RESULTS: Systemic P. gingivalis infection increased the expression of IL-1β in leptomeninges and reduced the synaptophysin (SYP) expression in leptomeninges proximity cortex in mice. Leptomeningeal cells phagocytosed P. gingivalis resulting in lysosomal rupture and Cathepsin B (CatB) leakage. Leaked CatB mediated NLRP3 inflammasome activation inducing IL-1β secretion in leptomeningeal cells. Pg LCM decreased the expression of synaptic molecules, including SYP, which was inhibited by an IL-1 receptor antagonist pre-treatment. CONCLUSION: These observations demonstrate that P. gingivalis infection is involved in synaptic failure by inducing CatB/NLRP3 inflammasome-mediated IL-1β production in leptomeningeal cells. The periodontal bacteria-induced synaptic damage may accelerate the onset and cognitive decline of AD.

Proton Stimulation Targeting Plaque Magnetite Reduces Amyloid-β Plaque and Iron Redox Toxicity and Improves Memory in an Alzheimer's Disease Mouse Model. - Seo, Seung-Jun; Chang, Won-Seok; Jeon, Jae-Geun; Choi, Younshick; Kim, EunHo; Kim, Jong-Ki (J Alzheimers Dis, 2021)
BACKGROUND: The coexistence of magnetite within protein aggregates in the brain is a typical pathologic feature of Alzheimer's disease (AD), and the formation of amyloid-β (Aβ) plaques induces critical impairment of cognitive function. OBJECTIVE: This study aimed to investigate the therapeutic effect of proton stimulation (PS) targeting plaque magnetite in the transgenic AD mouse brain. METHODS: A proton transmission beam was applied to the whole mouse brain at a single entrance dose of 2 or 4 Gy to test the effect of disruption of magnetite-containing Aβ plaques by electron emission from magnetite. The reduction in Aβ plaque burden and the cognitive function of the PS-treated mouse group were assayed by histochemical analysis and memory tests, respectively. Aβ-magnetite and Aβ fibrils were treated with PS to investigate the breakdown of the amyloid protein matrix. RESULTS: Single PS induced a 48-87%reduction in both the amyloid plaque burden and ferrous-containing magnetite level in the early-onset AD mouse brain while saving normal tissue. The overall Aβ plaque burden (68-82%) and (94-97%) hippocampal magnetite levels were reduced in late onset AD mice that showed improvements in cognitive function after PS compared with untreated AD mice (p <  0.001). Analysis of amyloid fibrils after exposure to a single 2 or 4 Gy proton transmission beam demonstrated that the protein matrix was broken down only in magnetite-associated Aβ fibrils. CONCLUSION: Single PS targeting plaque magnetite effectively decreases the amyloid plaque burden and the ferrous-containing magnetite level, and this effect is useful for memory recovery.

Quality of Life in Advanced Dementia with Late Onset, Young Onset, and Very Young Onset. - Hartmann, Julia; Roßmeier, Carola; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Slawik, Till; Fleischhaker, Mareike; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Haller, Bernhard; Schneider-Schelte, Helga; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Advanced stages of dementia are characterized by severe cognitive and physical impairment. It has not yet been investigated whether persons with young onset dementia (YOD) and late onset dementia (LOD) differ in advanced disease stages. OBJECTIVES: To compare quality of life (QoL) between persons with advanced YOD and LOD; to explore the determinants of QoL; to investigate whether YOD and LOD differ with regard to symptoms and care. METHODS: The study was performed in the context of EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of YOD and LOD in Germany). Persons with advanced dementia (PWAD) were assessed and caregivers were interviewed. QoL was measured with the proxy rating Quality of Life in Late Stage Dementia (QUALID) scale. RESULTS: 93 persons with YOD and 98 with LOD were included. No significant differences in QoL were detected. Determinants of QoL were similar in YOD and LOD. Behavioral and psychological symptoms of dementia (BPSD), suffering and other distressing symptoms were associated with a lower QoL. In YOD but not in LOD antipsychotic treatment was associated with low QoL. The group of persons who were younger than 65 years at the time of the study visit experienced significantly more distressing symptoms than older PWAD. CONCLUSION: Overall, persons with advanced YOD do not appear to be disadvantaged compared to old and oldest PWAD. Special attention, however, must be paid to the group of the very young persons who seem to be particularly vulnerable.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Antipsychotic Agents; Behavioral Symptoms; Caregivers; Dementia; Disease Progression; Female; Germany; Home Care Services; Humans; Individuality; Male; Middle Aged; Pain; Palliative Care; Psychotropic Drugs; Quality of Life

Race-Related Association between APOE Genotype and Alzheimer's Disease: A Systematic Review and Meta-Analysis. - Qin, Wei; Li, Wenwen; Wang, Qi; Gong, Min; Li, Tingting; Shi, Yuqing; Song, Yang; Li, Ying; Li, Fangyu; Jia, Jianping (J Alzheimers Dis, 2021)
BACKGROUND: The global race-dependent association of Alzheimer's disease (AD) and apolipoprotein E (APOE) genotype is not well understood. Transethnic analysis of APOE could clarify the role of genetics in AD risk across populations. OBJECTIVE: This study aims to determine how race and APOE genotype affect the risks for AD. METHODS: We performed a systematic search of PubMed, Embase, Web of Science, and the Cochrane Library since 1993 to Aug 25, 2020. A total of 10,395 reports were identified, and 133 were eligible for analysis with data on 77,402 participants. Studies contained AD clinical diagnostic and APOE genotype data. Homogeneous data sets were pooled in case-control analyses. Odds ratios and 95% confidence intervals for developing AD were calculated for populations of different races and APOE genotypes. RESULTS: The proportion of APOE genotypes and alleles differed between populations of different races. Results showed that APOEɛ4 was a risk factor for AD, whereas APOEɛ2 protected against it. The effects of APOEɛ4 and ɛ2 on AD risk were distinct in various races, and they were substantially attenuated among Black people. Sub-group analysis found a higher frequency of APOEɛ4/ɛ4 and lower frequency of APOEɛ3/ɛ3 among early-onset AD than late-onset AD in a combined group and different races. CONCLUSION: Our meta-analysis suggests that the association of APOE genotypes and AD differ among races. These results enhance our understanding of APOE-related risk for AD across race backgrounds and provide new insights into precision medicine for AD.
Keywords: Alleles; Alzheimer Disease; Apolipoprotein E2; Apolipoprotein E4; Apolipoproteins E; Genotype; Humans; Racial Groups

Reliability of Telephone and Videoconference Methods of Cognitive Assessment in Older Adults with and without Dementia. - Hunter, Matthew B; Jenkins, Natalie; Dolan, Clare; Pullen, Hannah; Ritchie, Craig; Muniz-Terrera, Graciela (J Alzheimers Dis, 2021)
BACKGROUND: Telephone and videoconference administration of cognitive tests introduce additional sources of variance compared to in-person testing. Reviews of test-retest reliability have included mixed neurocognitive and psychiatric populations with limited consideration of methodological and statistical contributions. OBJECTIVE: We reviewed reliability estimates from comparison studies of older adults with and without dementia, considering test-retest analyses and study methods. METHODS: Medline, Embase, PsycINFO, and Web of Science were systematically searched from 1 January 2000 to 9 June 2020 for original articles comparing telephone or videoconference administered cognitive instruments to in-person administration in older adults with and without dementia or mild cognitive impairment. RESULTS: Of 4,125 articles, 23 were included: 11 telephone (N = 2 dementia cohorts) and 12 videoconference (N = 4 dementia cohorts). Telephone administered subtest scores trended in the same direction as in-person with comparable means. Person-level data were scarce. Data on dementia was only available for MMSE, with resulting subtle modality bias. MMSE, SMMSE, Letter Fluency, and HVLT-R in healthy to mild-moderate Alzheimer's disease were particularly reliable for videoconference administration. Other tests show promise but require more observations and comprehensive analyses. Most studies used high-speed stable videoconferencing hardware resulting in a lack of ecological validity for home administration. CONCLUSION: Remote administration is often consistent with in-person administration but variable and limited at the person/test level. Improved statistical design and inclusion of dementia related cohorts in telephone studies is recommended. Reliability evidence is stronger for videoconferencing but with limited applicability to home administration and severe dementia. Improved reporting of administrative procedures is recommended.
Keywords: Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Dementia; Geriatric Assessment; Humans; Neuropsychological Tests; Remote Consultation; Reproducibility of Results; Telephone; Videoconferencing

Synaptic Molecular and Neurophysiological Markers Are Independent Predictors of Progression in Alzheimer's Disease. - Smailovic, Una; Kåreholt, Ingemar; Koenig, Thomas; Ashton, Nicholas J; Winblad, Bengt; Höglund, Kina; Nilsson, Per; Zetterberg, Henrik; Blennow, Kaj; Jelic, Vesna (J Alzheimers Dis, 2021)
BACKGROUND: Cerebrospinal fluid (CSF) neurogranin and quantitative electroencephalography (qEEG) are potential molecular and functional markers of synaptic pathology in Alzheimer's disease (AD). Synaptic markers have emerged as candidate prognostic indicators of AD since synaptic degeneration was shown to be an early event and the best correlate of cognitive deficits in patients along the disease continuum. OBJECTIVE: The present study investigated the association between CSF neurogranin and qEEG measures as well as their potential to predict clinical deterioration in mild cognitive impairment (MCI) patients. METHODS: Patients diagnosed with MCI (n = 99) underwent CSF conventional AD biomarkers and neurogranin analysis and resting-state EEG recordings. The study population was further stratified into stable (n = 41) and progressive MCI (n = 31), based on the progression to AD dementia during two years follow-up. qEEG analysis included computation of global field power and global field synchronization in four conventional frequency bands. RESULTS: CSF neurogranin levels were associated with theta power and synchronization in the progressive MCI group. CSF neurogranin and qEEG measures were significant predictors of progression to AD dementia, independent of baseline amyloid status in MCI patients. A combination of CSF neurogranin with global EEG power in theta and global EEG synchronization in beta band exhibited the highest classification accuracy as compared to either of these markers alone. CONCLUSION: qEEG and CSF neurogranin are independent predictors of progression to AD dementia in MCI patients. Molecular and neurophysiological synaptic markers may have additive value in a multimodal diagnostic and prognostic approach to dementia.

TAR DNA-Binding Protein 43 Is Associated with Rate of Memory and Functional and Global Cognitive Decline in the Decade Prior to Death. - Buciuc, Marina; Tosakulwong, Nirubol; Machulda, Mary M; Whitwell, Jennifer L; Weigand, Stephen D; Murray, Melissa E; Ross Reichard, R; Parisi, Joseph E; Dickson, Dennis W; Boeve, Bradley F; Knopman, David S; Petersen, Ronald C; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Transactive response DNA-binding protein of 43 kDa (TDP-43) is associated with memory impairment and overall cognitive decline. It is unclear how TDP-43 contributes to the rate of clinical decline. OBJECTIVE: To determine whether cross-sectional and longitudinal cognitive and functional decline are associated with anatomical distribution of TDP-43 in the brain. METHODS: Longitudinal clinical-neuropathologic autopsy cohort study of 385 initially cognitively normal/mildly impaired older adults prospectively followed until death. We investigated how TDP-43, amyloid-β (Aβ), tau neurofibrillary tangles (NFT), Lewy body disease (LBD), age, sex, and genetics are associated with clinical scores and rates of their longitudinal decline. RESULTS: Of 385 participants, 260 (68%) had no TDP-43, 32 (8%) TDP-43 limited to amygdala, and 93 (24%) TDP-43 in the hippocampus and beyond. Higher TDP-43 and Braak NFT stages independently were associated with faster decline in global cognition, functional performance measured by Clinical Dementia Rating scale, and naming and episodic memory, whereas older age was associated with slower rate of cognitive, psychiatric, and functional decline. Cross-sectionally the following associations were found: higher TDP-43 and Braak NFT - worse performance; higher Aβ burden - worse global cognition, more behavioral changes, the latter also with higher LBD; older age - worse naming, lower frequency of behavioral changes; female sex - more impaired naming and better preserved episodic memory. There were no genetic associations. CONCLUSION: The association of TDP-43 distribution with decline in cognitive and functional performance suggests that TDP-43 is playing a role in the clinical progression to dementia. Further characterization of clinical features associated with TDP-43 can facilitate establishment of antemortem diagnosis.

Time Trends of Cerebrospinal Fluid Biomarkers of Neurodegeneration in Idiopathic Normal Pressure Hydrocephalus. - Lukkarinen, Heikki; Tesseur, Ina; Pemberton, Darrel; van der Ark, Peter; Timmers, Maarten; Slemmon, Randy; Janssens, Luc; Streffer, Johannes; Van Nueten, Luc; Bottelbergs, Astrid; Rauramaa, Tuomas; Koivisto, Anne M; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Longitudinal changes in cerebrospinal fluid (CSF) biomarkers are seldom studied. Furthermore, data on biomarker gradient between lumbar (L-) and ventricular (V-) compartments seems to be discordant. OBJECTIVE: To examine alteration of CSF biomarkers reflecting Alzheimer's disease (AD)-related amyloid-β (Aβ) aggregation, tau pathology, neurodegeneration, and early synaptic degeneration by CSF shunt surgery in idiopathic normal pressure hydrocephalus (iNPH) in relation to AD-related changes in brain biopsy. In addition, biomarker levels in L- and V-CSF were compared. METHODS: L-CSF was collected prior to shunt placement and, together with V-CSF, 3-73 months after surgery. Thereafter, additional CSF sampling took place at 3, 6, and 18 months after the baseline sample from 26 iNPH patients with confirmed Aβ plaques in frontal cortical brain biopsy and 13 iNPH patients without Aβ pathology. CSF Amyloid-β42 (Aβ42), total tau (T-tau), phosphorylated tau (P-tau181), neurofilament light (NFL), and neurogranin (NRGN) were analyzed with customized ELISAs. RESULTS: All biomarkers but Aβ42 increased notably by 140-810% in L-CSF after CSF diversion and then stabilized. Aβ42 instead showed divergent longitudinal decrease between Aβ-positive and -negative patients in L-CSF, and thereafter increase in Aβ-negative iNPH patients in both L- and V-CSF. All five biomarkers correlated highly between V-CSF and L-CSF (Aβ42 R = 0.87, T-tau R = 0.83, P-tau R = 0.92, NFL R = 0.94, NRGN R = 0.9; all p <  0.0001) but were systematically lower in V-CSF (Aβ42 14 %, T-tau 22%, P-tau 20%, NFL 32%, NRGN 19%). With APOE genotype-grouping, only Aβ42 showed higher concentration in non-carriers of allele ɛ4. CONCLUSION: Longitudinal follow up shows that after an initial post-surgery increase, T-tau, P-tau, and NRGN are stable in iNPH patients regardless of brain biopsy Aβ pathology, while NFL normalized toward its pre-shunt levels. Aβ42 as biomarker seems to be the least affected by the surgical procedure or shunt and may be the best predictor of AD risk in iNPH patients. All biomarker concentrations were lower in V- than L-CSF yet showing strong correlations.

Animal Models of Alzheimer's Disease Should Be Controlled for Roseolovirus. - Denner, Joachim; Tanzi, Rudolph; Jacobson, Steve (J Alzheimers Dis, 2020)
Animal models to study Alzheimer's disease (AD) pathogenesis are under development. Since herpesviruses have been postulated to be capable of triggering the pathogenic process, AD animal models (mouse, pig, and non-human primates) should be controlled for the presence of these viruses. Only virus-free models allow studying the genetic factors and the effect of adding viruses. Roseoloviruses such as human herpesvirus 6 and the related viruses in the animals are the main topic of this commentary.

Circulating Vitamin D Levels and Alzheimer's Disease: A Mendelian Randomization Study in the IGAP and UK Biobank. - Wang, Longcai; Qiao, Yanchun; Zhang, Haihua; Zhang, Yan; Hua, Jiao; Jin, Shuilin; Liu, Guiyou (J Alzheimers Dis, 2020)
Observational studies strongly supported the association of low levels of circulating 25-hydroxyvitamin D (25OHD) and cognitive impairment or dementia in aging populations. However, randomized controlled trials have not shown clear evidence that vitamin D supplementation could improve cognitive outcomes. In fact, some studies reported the association between vitamin D and cognitive impairment based on individuals aged 60 years and over. However, it is still unclear that whether vitamin D levels are causally associated with Alzheimer's disease (AD) risk in individuals aged 60 years and over. Here, we performed a Mendelian randomization (MR) study to investigate the causal association between vitamin D levels and AD using a large-scale vitamin D genome-wide association study (GWAS) dataset and two large-scale AD GWAS datasets from the IGAP and UK Biobank with individuals aged 60 years and over. Our results showed that genetically increased 25OHD levels were significantly associated with reduced AD risk in individuals aged 60 years and over. Hence, our findings in combination with previous literature indicate that maintaining adequate vitamin D status in older people especially aged 60 years and over, may contribute to slow down cognitive decline and forestall AD. Long-term randomized controlled trials are required to test whether vitamin D supplementation may prevent AD in older people especially those aged 60 years and may be recommended as preventive agents.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biological Specimen Banks; Cognition Disorders; Databases, Factual; Female; Genome-Wide Association Study; Humans; Hydroxycholecalciferols; Male; Mendelian Randomization Analysis; Middle Aged; Nutritional Status; United Kingdom; Vitamin D; Vitamin D Deficiency

Combining Select Blood-Based Biomarkers with Neuropsychological Assessment to Detect Mild Cognitive Impairment among Mexican Americans. - Petersen, Melissa; Hall, James; Parsons, Thomas; Johnson, Leigh; O'Bryant, Sid (J Alzheimers Dis, 2020)
BACKGROUND: Recent work has supported use of blood-based biomarkers in detection of amnestic mild cognitive impairment (MCI). Inclusion of neuropsychological measures has shown promise in enhancing utility of biomarkers to detect disease. OBJECTIVE: The present study sought to develop cognitive-biomarker profiles for detection of MCI. METHODS: Data were analyzed on 463 participants (normal control n = 378; MCI n = 85) from HABLE. Random forest analyses determined proteomic profile of MCI. Separate linear regression analyses determined variance accounted for by select biomarkers per neuropsychological measure. When neuropsychological measure with the least shared variance was identified, it was then combined with select biomarkers to create a biomarker-cognitive profile. RESULTS: The biomarker-cognitive profile was 90% accurate in detecting MCI. Among amnestic MCI cases, the detection accuracy of the biomarker-cognitive profile was 92% and increased to 94% with demographic variables. CONCLUSION: The biomarker-cognitive profile for MCI was highly accurate in its detection with use of only five biomarkers.

Concentration-Dependent Activity of Hydromethylthionine on Clinical Decline and Brain Atrophy in a Randomized Controlled Trial in Behavioral Variant Frontotemporal Dementia. - Shiells, Helen; Schelter, Bjoern O; Bentham, Peter; Baddeley, Thomas C; Rubino, Christopher M; Ganesan, Harish; Hammel, Jeffrey; Vuksanovic, Vesna; Staff, Roger T; Murray, Alison D; Bracoud, Luc; Wischik, Damon J; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Hydromethylthionine is a potent inhibitor of pathological aggregation of tau and TDP-43 proteins. OBJECTIVE: To compare hydromethylthionine treatment effects at two doses and to determine how drug exposure is related to treatment response in bvFTD. METHODS: We undertook a 52-week Phase III study in 220 bvFTD patients randomized to compare hydromethylthionine at 200 mg/day and 8 mg/day (intended as a control). The principal outcomes were change on the Addenbrookes Cognitive Examination - Revised (ACE-R), the Functional Activities Questionnaire (FAQ), and whole brain volume. Secondary outcomes included Modified Clinical Global Impression of Change (Modified-CGIC). A population pharmacokinetic exposure-response analysis was undertaken in 175 of the patients with available blood samples and outcome data using a discriminatory plasma assay for the parent drug. RESULTS: There were no significant differences between the two doses as randomized. There were steep concentration-response relationships for plasma levels in the range 0.3-0.6 ng/ml at the 8 mg/day dose on clinical and MRI outcomes. There were significant exposure-dependent differences at 8 mg/day for FAQ, Modified-CGIC, and whole brain atrophy comparing patients with plasma levels greater than 0.346 ng/ml with having minimal drug exposure. The exposure-response is biphasic with worse outcomes at the high concentrations produced by 200 mg/day. CONCLUSIONS: Hydromethylthionine has a similar concentration-response profile for effects on clinical decline and brain atrophy at the 8 mg/day dose in bvFTD as recently reported in AD. Treatment responses in bvFTD are predicted to be maximal at doses in the range 20-60 mg/day. A confirmatory placebo-controlled trial is now planned.

COVID-19: Review of a 21st Century Pandemic from Etiology to Neuro-psychiatric Implications. - Yamamoto, Vicky; Bolanos, Joe F; Fiallos, John; Strand, Susanne E; Morris, Kevin; Shahrokhinia, Sanam; Cushing, Tim R; Hopp, Lawrence; Tiwari, Ambooj; Hariri, Robert; Sokolov, Rick; Wheeler, Christopher; et al. (J Alzheimers Dis, 2020)
COVID-19 is a severe infectious disease that has claimed >150,000 lives and infected millions in the United States thus far, especially the elderly population. Emerging evidence has shown the virus to cause hemorrhagic and immunologic responses, which impact all organs, including lungs, kidneys, and the brain, as well as extremities. SARS-CoV-2 also affects patients', families', and society's mental health at large. There is growing evidence of re-infection in some patients. The goal of this paper is to provide a comprehensive review of SARS-CoV-2-induced disease, its mechanism of infection, diagnostics, therapeutics, and treatment strategies, while also focusing on less attended aspects by previous studies, including nutritional support, psychological, and rehabilitation of the pandemic and its management. We performed a systematic review of >1,000 articles and included 425 references from online databases, including, PubMed, Google Scholar, and California Baptist University's library. COVID-19 patients go through acute respiratory distress syndrome, cytokine storm, acute hypercoagulable state, and autonomic dysfunction, which must be managed by a multidisciplinary team including nursing, nutrition, and rehabilitation. The elderly population and those who are suffering from Alzheimer's disease and dementia related illnesses seem to be at the higher risk. There are 28 vaccines under development, and new treatment strategies/protocols are being investigated. The future management for COVID-19 should include B-cell and T-cell immunotherapy in combination with emerging prophylaxis. The mental health and illness aspect of COVID-19 are among the most important side effects of this pandemic which requires a national plan for prevention, diagnosis and treatment.
Keywords: Coronavirus Infections; COVID-19; Humans; Immunotherapy; Mental Health; Nutritional Support; Pandemics; Pneumonia, Viral

Dickkopf-1 Overexpression in vitro Nominates Candidate Blood Biomarkers Relating to Alzheimer's Disease Pathology. - Shi, Liu; Winchester, Laura M; Liu, Benjamine Y; Killick, Richard; Ribe, Elena M; Westwood, Sarah; Baird, Alison L; Buckley, Noel J; Hong, Shengjun; Dobricic, Valerija; Kilpert, Fabian; Franke, Andre; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Previous studies suggest that Dickkopf-1 (DKK1), an inhibitor of Wnt signaling, plays a role in amyloid-induced toxicity and hence Alzheimer's disease (AD). However, the effect of DKK1 expression on protein expression, and whether such proteins are altered in disease, is unknown. OBJECTIVE: We aim to test whether DKK1 induced protein signature obtained in vitro were associated with markers of AD pathology as used in the amyloid/tau/neurodegeneration (ATN) framework as well as with clinical outcomes. METHODS: We first overexpressed DKK1 in HEK293A cells and quantified 1,128 proteins in cell lysates using aptamer capture arrays (SomaScan) to obtain a protein signature induced by DKK1. We then used the same assay to measure the DKK1-signature proteins in human plasma in two large cohorts, EMIF (n = 785) and ANM (n = 677). RESULTS: We identified a 100-protein signature induced by DKK1 in vitro. Subsets of proteins, along with age and apolipoprotein E ɛ4 genotype distinguished amyloid pathology (A + T-N-, A+T+N-, A+T-N+, and A+T+N+) from no AD pathology (A-T-N-) with an area under the curve of 0.72, 0.81, 0.88, and 0.85, respectively. Furthermore, we found that some signature proteins (e.g., Complement C3 and albumin) were associated with cognitive score and AD diagnosis in both cohorts. CONCLUSIONS: Our results add further evidence for a role of DKK regulation of Wnt signaling in AD and suggest that DKK1 induced signature proteins obtained in vitro could reflect theATNframework as well as predict disease severity and progression in vivo.

Examining Cognitive Decline Across Black and White Participants in the Harvard Aging Brain Study. - Amariglio, Rebecca E; Buckley, Rachel F; Rabin, Jennifer S; Papp, Kathryn V; Quiroz, Yakeel T; Mormino, Elizabeth C; Sparks, Kathryn P; Johnson, Keith A; Rentz, Dorene M; Sperling, Reisa A (J Alzheimers Dis, 2020)
BACKGROUND: Black Americans are approximately twice as likely to develop dementia as compared to White Americans and the magnitude of this disparity is often attributed to a variety of factors that include psychosocial and vascular risk factors. However, less is known about the potential contribution of Alzheimer's disease pathological differences. OBJECTIVE: To examine potential differences incross-sectional and longitudinal cognitive performance in black and white participants who were clinically normal at baseline. METHODS: 296 participants (48 African-American/black participants) underwent MRI and amyloid PET at baseline. Linear mixed models were used to examine the main effects of race, years of education, reading ability, Framingham Heart Study cardiovascular risk score (FHS-CVD), white matter hyperintensities (WMH), and amyloid (Aβ) burden on the Preclinical Alzheimer Cognitive Composite-5 (PACC5). RESULTS: Lower levels of educationalattainment and reading ability were found for blacks compared to whites. By contrast, no differences in FHS-CVD, WMH, or Aβ were found by racial group. Baseline differences in PACC5 score were attenuated after adjusting for educationalfactors, vascular factors, and Aβ, but remained lower for blacks compared to whites (β= -0.24, p = 0.014). Further, blacks demonstrated a faster rate of PACC5 decline longitudinally compared to whites (β  = -0.055, p = 0.025) after adjusting for covariates. CONCLUSION: Accounting for educationalfactors, vascular factors, and Aβ burden diminished, but did not eliminate, racial differences in PACC5 performance longitudinally. Understanding potential differences in longitudinal cognitive outcomes by race may be important for upcoming secondary prevention trials.

The Impact of Amyloid-β or Tau on Cognitive Change in the Presence of Severe Cerebrovascular Disease. - Jang, Hyemin; Kim, Hee Jin; Sim Choe, Yeong; Kim, Soo-Jong; Park, Seongbeom; Kim, Yeshin; Woon Kim, Ko; Hyoung Lyoo, Chul; Cho, Hanna; Hoon Ryu, Young; Choi, Jae Yong; DeCarli, Charles; et al. (J Alzheimers Dis, 2020)
BACKGROUND: As Alzheimer's disease (AD) and cerebral small vessel disease (CSVD) commonly coexist, the interaction between two has been of the considerable interest. OBJECTIVE: We determined whether the association of Aβ and tau with cognitive decline differs by the presence of significant CSVD. METHODS: We included 60 subcortical vascular cognitive impairment (SVCI) from Samsung Medical Center and 82 Alzheimer's disease-related cognitive impairment (ADCI) from ADNI, who underwent Aβ (florbetaben or florbetapir) and tau (flortaucipir, FTP) PET imaging. They were retrospectively assessed for 5.0±3.9 and 5.6±1.9 years with Clinical Dementia Rating-sum of boxes (CDR-SB)/Mini-Mental State Examination (MMSE). Mixed effects models were used to investigate the interaction between Aβ/tau and group on CDR-SB/MMSE changes. RESULTS: The frequency of Aβ positivity (45% versus 54.9%, p = 0.556) and mean global FTP SUVR (1.17±0.21 versus 1.16±0.17, p = 0.702) were not different between the two groups. We found a significant interaction effect of Aβ positivity and SVCI group on CDR-SB increase/MMSE decrease (p = 0.013/p <  0.001) change, and a significant interaction effect of global FTP uptake and SVCI group on CDR-SB increase/MMSE decrease (p <  0.001 and p = 0.030) change. Finally, the interaction effects of regional tau and group were prominent in the Braak III/IV (p = 0.001) and V/VI (p = 0.003) not in Braak I/II region (p = 0.398). CONCLUSION: The association between Aβ/tau and cognitive decline is stronger in SVCI than in ADCI. Therefore, our findings suggested that Aβ positivity or tau burden (particularly in the Braak III/IV or V/VI regions) and CSVD might synergistically affect cognitive decline.

In Vivo Validation of a Small Molecule Inhibitor of Tau Self-Association in htau Mice. - Davidowitz, Eliot J; Krishnamurthy, Pavan K; Lopez, Patricia; Jimenez, Heidy; Adrien, Leslie; Davies, Peter; Moe, James G (J Alzheimers Dis, 2020)
Tau oligomers have been shown to transmit tau pathology from diseased neurons to healthy neurons through seeding, tau misfolding, and aggregation that is thought to play an influential role in the progression of Alzheimer's disease (AD) and related tauopathies. To develop a small molecule therapeutic for AD and related tauopathies, we have developed in vitro and cellular assays to select molecules inhibiting the first step in tau aggregation, the self-association of tau into oligomers. In vivo validation studies of an optimized lead compound were independently performed in the htau mouse model of tauopathy that expresses the human isoforms of tau without inherited tauopathy mutations that are irrelevant to AD. Treated mice did not show any adverse events related to the compound. The lead compound significantly reduced the level of self-associated tau and total and phosphorylated insoluble tau aggregates. The dose response was linear with respect to levels of compound in the brain. A confirmatory study was performed with male htau mice that gave consistent results. The results validated our screening approach by showing that targeting tau self-association can inhibit the entire tau aggregation pathway by using the selected and optimized lead compound whose activity translated from in vitro and cellular assays to an in vivo model of tau aggregation.

Metabolic Changes Detected by 18F-FDG PET in the Preclinical Stage of Familial Creutzfeldt-Jakob Disease. - Lu, Hui; Jing, Donglai; Chen, Yaojing; Cui, Chunlei; Gao, Ran; Wang, Lin; Liang, Zhigang; Chen, Kewei; Wu, Liyong (J Alzheimers Dis, 2020)
BACKGROUND: Pathologic processes in Creutzfeldt-Jakob disease (CJD) are not fully understood. Familial CJD (fCJD) gives opportunities to discover pathologic changes in the preclinical stage. OBJECTIVE: To investigate cerebral glucose metabolism in the preclinical stage via 18F-fluorodeoxyglucose positron emission tomography (18F-FDG PET) in fCJD. METHODS: Seven asymptomatic carriers of G114V mutation and six family members without PRNP mutation from the same fCJD kindred were included, and were followed for 2 years. Ten symptomatic CJD patients were also recruited. All subjects underwent standardized clinical examinations and 18F-FDG PET scans. Results were compared in three groups: baseline carriers against non-carriers (baseline analysis), changes after 2 years in carriers (follow-up analysis), and differences between symptomatic CJD patients and healthy controls (CJD patients analysis). RESULTS: No carriers developed any neurological symptoms during 2-year follow-up. Baseline analysis: carriers demonstrates decreased metabolism (p < 0.001) in left and right postcentral, left fusiform, left superior temporal, left lingual, left superior parietal, and left Heschl gyrus. Follow-up analysis shows metabolic decline (p < 0.001) in right inferior temporal, left supra-marginal and left postcentral lobe, and increased metabolism (p < 0.001) in left fusiform, left angular, left thalamus, left Heschl's, right Rolandic operculum, and left superior parietal gyrus. CJD patients demonstrates decreased metabolism in right inferior triangularis frontal gyrus, right middle occipital gyrus, right putamen, right thalamus, and right middle temporal gyrus. CONCLUSION: Hypo-metabolism of parietal and temporal lobe can be detected by 18F-FDG PET in the preclinical stage of CJD. Subcortical area might compensate in the preclinical stage and decompensate in the symptomatic stage.

Metabolic Profiles Help Discriminate Mild Cognitive Impairment from Dementia Stage in Alzheimer's Disease. - Jääskeläinen, Olli; Hall, Anette; Tiainen, Mika; van Gils, Mark; Lötjönen, Jyrki; Kangas, Antti J; Helisalmi, Seppo; Pikkarainen, Maria; Hallikainen, Merja; Koivisto, Anne; Hartikainen, Päivi; Hiltunen, Mikko; et al. (J Alzheimers Dis, 2020)
Accurate differentiation between neurodegenerative diseases is developing quickly and has reached an effective level in disease recognition. However, there has been less focus on effectively distinguishing the prodromal state from later dementia stages due to a lack of suitable biomarkers. We utilized the Disease State Index (DSI) machine learning classifier to see how well quantified metabolomics data compares to clinically used cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD). The metabolic profiles were quantified for 498 serum and CSF samples using proton nuclear magnetic resonance spectroscopy. The patient cohorts in this study were dementia (with a clinical AD diagnosis) (N = 359), mild cognitive impairment (MCI) (N = 96), and control patients with subjective memory complaints (N = 43). DSI classification was conducted for MCI (N = 51) and dementia (N = 214) patients with low CSF amyloid-β levels indicating AD pathology and controls without such amyloid pathology (N = 36). We saw that the conventional CSF markers of AD were better at classifying controls from both dementia and MCI patients. However, quantified metabolic subclasses were more effective in classifying MCI from dementia. Our results show the consistent effectiveness of traditional CSF biomarkers in AD diagnostics. However, these markers are relatively ineffective in differentiating between MCI and the dementia stage, where the quantified metabolomics data provided significant benefit.

Multi-Target Effects of the Cannabinoid CP55940 on Familial Alzheimer's Disease PSEN1 E280A Cholinergic-Like Neurons: Role of CB1 Receptor. - Soto-Mercado, Viviana; Mendivil-Perez, Miguel; Jimenez-Del-Rio, Marlene; Velez-Pardo, Carlos (J Alzheimers Dis, 2020)
BACKGROUND: Alzheimer's disease (AD) is characterized by structural damage, death, and functional disruption of cholinergic neurons (ChNs) as a result of intracellular amyloid-β (Aβ) aggregation, extracellular neuritic plaques, and hyperphosphorylation of protein tau (p-Tau) overtime. OBJECTIVE: To evaluate the effect of the synthetic cannabinoid CP55940 (CP) on PSEN1 E280A cholinergic-like nerve cells (PSEN1 ChLNs)-a natural model of familial AD. METHODS: Wild type (WT) and PSEN1 ChLNs were exposed to CP (1μM) only or in the presence of the CB1 and CB2 receptors (CB1Rs, CB2Rs) inverse agonist SR141716 (1μM) and SR144528 (1μM) respectively, for 24 h. Untreated or treated neurons were assessed for biochemical and functional analysis. RESULTS: CP in the presence of both inverse agonists (hereafter SR) almost completely inhibits the aggregation of intracellular sAβPPβf and p-Tau, increases ΔΨm, decreases oxidation of DJ-1Cys106-SH residue, and blocks the activation of c-Jun, p53, PUMA, and caspase-3 independently of CB1Rs signaling in mutant ChLNs. CP also inhibits the generation of reactive oxygen species partially dependent on CB1Rs. Although CP reduced extracellular Aβ 42, it was unable to reverse the Ca2 + influx dysregulation as a response to acetylcholine stimuli in mutant ChLNs. Exposure to anti-Aβ antibody 6E10 (1:300) in the absence or presence of SR plus CP completely recovered transient [Ca2 +]i signal as a response to acetylcholine in mutant ChLNs. CONCLUSION: Taken together our findings suggest that the combination of cannabinoids, CB1Rs inverse agonists, and anti-Aβ antibodies might be a promising therapeutic approach for the treatment of familial AD.

Older Patients with Alzheimer's Disease-Related Cortical Atrophy Who Develop Post-Operative Delirium May Be at Increased Risk of Long-Term Cognitive Decline After Surgery. - Racine, Annie M; Touroutoglou, Alexandra; Abrantes, Tatiana; Wong, Bonnie; Fong, Tamara G; Cavallari, Michele; Travison, Thomas G; Gou, Yun; Marcantonio, Edward R; Alsop, David C; Jones, Richard N; Inouye, Sharon K; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Older surgical patients with Alzheimer's disease (AD) dementia and delirium are at increased risk for accelerated long-term cognitive decline. OBJECTIVE: Investigate associations between a probabilistic marker of preclinical AD, delirium, and long-term cognitive decline. METHODS: The Successful Aging after Elective Surgery cohort includes older adults (≥70 years) without dementia who underwent elective surgery. 140 patients underwent preoperative magnetic resonance imaging and had≥6 months cognitive follow-up. Cortical thickness was measured in 'AD-Signature' regions. Delirium was evaluated each postoperative day by the Confusion Assessment Method. Cognitive performance was assessed using a detailed neuropsychological battery at baseline; months 1, 2, and 6; and every 6 months thereafter until 36 months. Using either a General Cognitive Performance composite (GCP) or individual test scores as outcomes, we performed linear mixed effects models to examine main effects of AD-signature atrophy and the interaction of AD-signature atrophy and delirium on slopes of cognitive change from post-operative months 2-36. RESULTS: Reduced baseline AD-signature cortical thickness was associated with greater 36-month cognitive decline in GCP (standardized beta coefficient, β = -0.030, 95% confidence interval [-0.060, -0.001]). Patients who developed delirium who also had thinner AD signature cortex showed greater decline on a verbal learning test (β = -0.100 [-0.192, -0.007]). CONCLUSION: Patients with the greatest baseline AD-related cortical atrophy who develop delirium after elective surgery appear to experience the greatest long-term cognitive decline. Thus, atrophy suggestive of preclinical AD and the development of delirium may be high-risk indicators for long-term cognitive decline following surgery.

Plasma High Density Lipoprotein Small Subclass is Reduced in Alzheimer's Disease Patients and Correlates with Cognitive Performance. - Pedrini, Steve; Hone, Eugene; Gupta, Veer B; James, Ian; Teimouri, Elham; Bush, Ashley I; Rowe, Christopher C; Villemagne, Victor L; Ames, David; Masters, Colin L; Rainey-Smith, Stephanie; Verdile, Giuseppe; et al. (J Alzheimers Dis, 2020)
BACKGROUND: The link between cholesterol and Alzheimer's disease (AD) has received much attention, as evidence suggests high levels of cholesterol might be an AD risk factor. The carriage of cholesterol and lipids through the body is mediated via lipoproteins, some of which, particularly apolipoprotein E (ApoE), are intimately linked with AD. In humans, high density lipoprotein (HDL) is regarded as a "good" lipid complex due to its ability to enable clearance of excess cholesterol via 'cholesterol reverse transport', although its activities in the pathogenesis of AD are poorly understood. There are several subclasses of HDL; these range from the newly formed small HDL, to much larger HDL. OBJECTIVE: We examined the major subclasses of HDL in healthy controls, mild cognitively impaired, and AD patients who were not taking statins to determine whether there were HDL profile differences between the groups, and whether HDL subclass levels correlated with plasma amyloid-β (Aβ) levels or brain Aβ deposition. METHODS: Samples from AIBL cohort were used in this study. HDL subclass levels were assessed by Lipoprint while Aβ1-42 levels were assessed by ELISA. Brain Aβ deposition was assessed by PET scan. Statistical analysis was performed using parametric and non-parametric tests. RESULTS: We found that small HDL subclass is reduced in AD patients and it correlates with cognitive performance while plasma Aβ concentrations do not correlate with lipid profile or HDL subfraction levels. CONCLUSION: Our data indicate that AD patients exhibit altered plasma HDL profile and that HDL subclasses correlate with cognitive performances.

Potentially Pathogenic Calcium Oxalate Dihydrate and Titanium Dioxide Crystals in the Alzheimer's Disease Entorhinal Cortex. - Heller, Adam; Coffman, Sheryl S; Jarvis, Karalee (J Alzheimers Dis, 2020)
Knowing that Alzheimer's disease (AD) nucleates in the entorhinal cortex (EC), samples of 12 EC specimens were probed for crystals by a protocol detecting fewer than 1/5000th of those present. Of the 61 crystals found, 31 were expected and 30 were novel. Twenty-one crystals of iron oxides and 10 atherosclerosis-associated calcium pyrophosphate dihydrate crystals were expected and found. The 30 unexpected crystals were NLRP3-inflammasome activating calcium oxalate dihydrate (12) and titanium dioxide (18). Their unusual distribution raises the possibility that some were of AD origination sites.

Validation of Plasma Proteomic Biomarkers Relating to Brain Amyloid Burden in the EMIF-Alzheimer's Disease Multimodal Biomarker Discovery Cohort. - Westwood, Sarah; Baird, Alison L; Anand, Sneha N; Nevado-Holgado, Alejo J; Kormilitzin, Andrey; Shi, Liu; Hye, Abdul; Ashton, Nicholas J; Morgan, Angharad R; Bos, Isabelle; Vos, Stephanie J B; Baker, Susan; et al. (J Alzheimers Dis, 2020)
We have previously investigated, discovered, and replicated plasma protein biomarkers for use to triage potential trials participants for PET or cerebrospinal fluid measures of Alzheimer's disease (AD) pathology. This study sought to undertake validation of these candidate plasma biomarkers in a large, multi-center sample collection. Targeted plasma analyses of 34 proteins with prior evidence for prediction of in vivo pathology were conducted in up to 1,000 samples from cognitively healthy elderly individuals, people with mild cognitive impairment, and in patients with AD-type dementia, selected from the EMIF-AD catalogue. Proteins were measured using Luminex xMAP, ELISA, and Meso Scale Discovery assays. Seven proteins replicated in their ability to predict in vivo amyloid pathology. These proteins form a biomarker panel that, along with age, could significantly discriminate between individuals with high and low amyloid pathology with an area under the curve of 0.74. The performance of this biomarker panel remained consistent when tested in apolipoprotein E ɛ4 non-carrier individuals only. This blood-based panel is biologically relevant, measurable using practical immunocapture arrays, and could significantly reduce the cost incurred to clinical trials through screen failure.

Adverse Vascular Risk Relates to Cerebrospinal Fluid Biomarker Evidence of Axonal Injury in the Presence of Alzheimer's Disease Pathology. - Osborn, Katie E; Alverio, Jonathan M; Dumitrescu, Logan; Pechman, Kimberly R; Gifford, Katherine A; Hohman, Timothy J; Blennow, Kaj; Zetterberg, Henrik; Jefferson, Angela L (J Alzheimers Dis, 2019)
BACKGROUND: Vascular risk factors promote cerebral small vessel disease and neuropathological changes, particularly in white matter where large-caliber axons are located. How Alzheimer's disease pathology influences the brain's vulnerability in this regard is not well understood. OBJECTIVE: Systemic vascular risk was assessed in relation to cerebrospinal fluid concentrations of neurofilament light, a biomarker of large-caliber axonal injury, evaluating for interactions by clinical and protein markers of Alzheimer's disease. METHODS: Among Alzheimer's Disease Neuroimaging Initiative participants with normal cognition (n = 117), mild cognitive impairment (n = 190), and Alzheimer's disease (n = 95), linear regression related vascular risk (as measured by the modified Framingham Stroke Risk Profile) to neurofilament light, adjusting for age, sex, education, and cognitive diagnosis. Interactions were assessed by cognitive diagnosis, and by cerebrospinal fluid markers of Aβ42, hyperphosphorylated tau, and total tau. RESULTS: Vascular risk and neurofilament light were not related in the main effect model (p = 0.08). However, interactions emerged for total tau (p = 0.01) and hyperphosphorylated tau (p = 0.002) reflecting vascular risk becoming more associated with cerebrospinal fluid neurofilament light in the context of greater concentrations of tau biomarkers. An interaction also emerged for the Alzheimer's disease biomarker profiles (p = 0.046) where in comparison to the referent 'normal' biomarker group, individuals with abnormal levels of both Aβ42 and total tau showed stronger associations between vascular risk and neurofilament light. CONCLUSION: Older adults may be more vulnerable to axonal injury in response to higher vascular risk burdens in the context of concomitant Alzheimer's disease pathology.

Amyloidogenic Nanoplaques in Blood Serum of Patients with Alzheimer's Disease Revealed by Time-Resolved Thioflavin T Fluorescence Intensity Fluctuation Analysis. - Tiiman, Ann; Jelic, Vesna; Jarvet, Jüri; Järemo, Petter; Bogdanovic, Nenad; Rigler, Rudolf; Terenius, Lars; Gräslund, Astrid; Vukojević, Vladana (J Alzheimers Dis, 2019)
BACKGROUND: Biomarkers are central to current research on molecular mechanisms underlying Alzheimer's disease (AD). Their further development is of paramount importance for understanding pathophysiological processes that eventually lead to disease onset. Biomarkers are also crucial for early disease detection, before clinical manifestation, and for development of new disease modifying therapies. OBJECTIVE: The overall aim of this work is to develop a minimally invasive method for fast, ultra-sensitive and cost-effective detection of structurally modified peptide/protein self-assemblies in the peripheral blood and in other biological fluids. Specifically, we focus here on using this method to detect structured amyloidogenic oligomeric aggregates in the blood serum of apparently healthy individuals and patients in early AD stage, and measure their concentration and size. METHODS: Time-resolved detection of Thioflavin T (ThT) fluorescence intensity fluctuations in a sub-femtoliter observation volume element was used to identify in blood serum ThT-active structured amyloidogenic oligomeric aggregates, hereafter called nanoplaques, and measure with single-particle sensitivity their concentration and size. RESULTS: The concentration and size of structured amyloidogenic nanoplaques are significantly higher in the blood serum of individuals diagnosed with AD than in control subjects. CONCLUSION: A new method with the ultimate, single-particle sensitivity was successfully developed. The proposed approach neither relies on the use of immune-based probes, nor on the use of radiotracers, signal-amplification or protein separation techniques, and provides a minimally invasive test for fast and cost-effective early determination of structurally modified peptides/proteins in the peripheral blood, as shown here, but also in other biological fluids.

Association of Cognitive Function with Amyloid-β and Tau Proteins in the Vitreous Humor. - Wright, Lauren M; Stein, Thor D; Jun, Gyungah; Chung, Jaeyoon; McConnell, Kate; Fiorello, Marissa; Siegel, Nicole; Ness, Steven; Xia, Weiming; Turner, Kelley L; Subramanian, Manju L (J Alzheimers Dis, 2019)
BACKGROUND: The eye may serve as source for diagnostic testing for early detection of Alzheimer's disease (AD). Examination of amyloid-β (Aβ) and tau protein content in human vitreous and its correlation to neuro-cognition may improve ocular-based AD detection methods. OBJECTIVE: To evaluate levels of Aβ and tau protein in human vitreous humor and investigate the clinical predictive role of these proteins as early diagnostic markers of AD. METHODS: A prospective, single-center, multi-surgeon cohort study. Vitreous humor samples from 80 eyes were measured quantitatively for Aβ40-42, pTau, and tTau. Linear regression was used to test associations between AD biomarker levels, Mini-Mental State Exam (MMSE), and serum apolipoprotein E (APOE) allele status, with adjustment for age, sex, and education level of patients. RESULTS: Lower MMSE scores were significantly associated with lower levels of vitreous Aβ40 (p = 0.015), Aβ42 (p = 0.0066), and tTau (p = 0.0085), and these biomarkers were not associated with any pre-existing eye conditions. Presence of the ɛ4 allele and the ɛ2 allele approached significance with reduced Aβ40 level (p = 0.053) and increased p-Tau level (p = 0.056), respectively. CONCLUSION: Patients with poor cognitive function have significantly lower vitreous humor levels of AD-related biomarkers Aβ40, Aβ42, and tTau. These biomarkers do not correlate with underlying eye conditions, suggesting their specificity in association with cognitive change. This is the first study to our knowledge to correlate cognition with AD-related proteins in the vitreous humor. Results suggest ocular proteins may have a role for early dementia detection in individuals at risk for AD.

Choroid Plexus Acts as Gatekeeper for TREM2, Abnormal Accumulation of ApoE, and Fibrillary Tau in Alzheimer's Disease and in Down Syndrome Dementia. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Vuono, Romina; Bickerton, Anastasia; Jones, Elizabeth; Fincham, Robert; Allinson, Kieren; Holland, Anthony; Zaman, Shahid H (J Alzheimers Dis, 2019)
BACKGROUND: Genetic factors that influence Alzheimer's disease (AD) risk include mutations in TREM2 and allelic variants of Apolipoprotein E, influencing AD pathology in the general population and in Down syndrome (DS). Evidence shows that dysfunction of the choroid plexus may compromise the blood-cerebrospinal fluid (CSF) barrier, altering secretary, transport and immune function that can affect AD pathology. OBJECTIVE: To investigate the genotype and phenotype of DS individuals in relation to choroid plexus damage and blood-CSF barrier leakage to identify markers that could facilitate early diagnosis of AD in DS. METHODS: To assess allele frequency and haplotype associations ApoE, Tau, TREM2, and HLA-DR were analyzed by SNP analysis in DS participants (n = 47) and controls (n = 50). The corresponding plasma protein levels were measured by ELISA. Postmortem brains from DS, AD, and age-matched controls were analyzed by immunohistochemistry. RESULTS: Haplotype analysis showed that individuals with Tau H1/H1 and ApoEɛ4 genotypes were more prevalent among DS participants with an earlier diagnosis of dementia (17%) compared to H1/H2 haplotypes (6%). Plasma TREM2 levels decreased whereas phospho-tau levels increased with age in DS. In AD and DS brain, insoluble tau and ApoE were found to accumulate in the choroid plexus. CONCLUSION: Accumulation of tau and ApoE in the choroid plexus may increase the oligomerization rate of Aβ42 and impair tau trafficking, leading to AD pathology. We have identified a high-risk haplotype: ApoEɛ4, Tau/H1, and TREM2/T, that manifests age-related changes potentially opening a window for treatment many years prior to the manifestation of the AD dementia.

Clinico-Neuropathological Findings in the Oldest Old from the Georgia Centenarian Study. - Tanprasertsuk, Jirayu; Johnson, Elizabeth J; Johnson, Mary Ann; Poon, Leonard W; Nelson, Peter T; Davey, Adam; Martin, Peter; Barbey, Aron K; Barger, Kathryn; Wang, Xiang-Dong; Scott, Tammy M (J Alzheimers Dis, 2019)
BACKGROUND: Centenarian studies are important sources for understanding of factors that contribute to longevity and healthy aging. Clinico-neuropathological finding is a key in identifying pathology and factors contributing to age-related cognitive decline and dementia in the oldest old. OBJECTIVE: To characterize the cross-sectional relationship between neuropathologies and measures of premortem cognitive performance in centenarians. METHODS: Data were acquired from 49 centenarians (≥98 years) from the Georgia Centenarian Study. Cognitive assessment from the time point closest to mortality was used ( RESULTS: Wide ranges of AD-type neuropathological changes were observed in both non-demented and demented subjects. Neocortical NFT and Braak staging were related to clinical dementia rating. Neocortical NFT and NP, Braak and NIARI staging, cerebral and ventricular atrophy, HS, CAA, and TDP-43 proteinopathy were differentially associated with poor performance in multiple cognitive domains and activities of daily living. CONCLUSION: AD-type pathology was associated with severe dementia and poor cognition but was not the only variable that explained cognitive impairment, indicating the complexity and heterogeneity of pathophysiology of dementia in the oldest old.

A Comparison of Partial Volume Correction Techniques for Measuring Change in Serial Amyloid PET SUVR. - Schwarz, Christopher G; Gunter, Jeffrey L; Lowe, Val J; Weigand, Stephen; Vemuri, Prashanthi; Senjem, Matthew L; Petersen, Ronald C; Knopman, David S; Jack, Clifford R (J Alzheimers Dis, 2019)
Longitudinal PET studies in aging and Alzheimer's disease populations rely on accurate and precise measurements of change over time from serial PET scans. Various methods for partial volume correction (PVC) are commonly applied to such studies, but existing comparisons and validations of these PVC methods have focused on cross-sectional measurements. Rate of change measurements inherently have smaller magnitudes than cross-sectional measurements, so levels of noise amplification due to PVC must be smaller, and it is necessary to re-evaluate methods in this context. Here we compare the relative precision in longitudinal measurements from serial amyloid PET scans when using geometric transfer matrix (GTM) PVC versus the traditional two-compartment (Meltzer-style), three-compartment (Müller-Gärtner-style), and no-PVC approaches. We used two independent implementations of standardized uptake value ratio (SUVR) measurement and PVC (one in-house pipeline based on SPM12 and ANTs, and one using FreeSurfer 6.0). For each approach, we also tested longitudinal-specific variants. Overall, we found that measurements using GTM PVC had significantly worse relative precision (unexplained within-subject variability ≈4-8%) than those using two-compartment, three-compartment, or no PVC (≈2-4%). Longitudinally-stabilized approaches did not improve these properties. This data suggests that GTM PVC methods may be less suitable than traditional approaches when measuring within-person change over time in longitudinal amyloid PET.

Ethical Issues in the Treatment of Late-Stage Alzheimer's Disease. - Watt, Andrew D; Jenkins, Nicole L; McColl, Gawain; Collins, Steven; Desmond, Patricia M (J Alzheimers Dis, 2019)
There is hope that the continuing efforts of researchers will yield a disease-modifying drug for Alzheimer's disease. Such a drug is likely to be capable of halting, or significantly slowing, the underlying pathological processes driving cognitive decline; however, it is unlikely to be capable of restoring brain function already lost through the pathological process. A therapy capable of halting Alzheimer's disease, while not providing restoration of function, may prompt serious ethical questions. For example, is there a stage in the disease process when it becomes too late for therapeutic intervention to commence? And who bears the responsibility of making such a decision? Conversations regarding the ethics of treating neurodegenerative conditions with non-restorative drugs have been largely absent within both clinical and research communities. Such discussions are urgently required to ensure that patients' rights and well-being are protected when such therapeutic options become available.

Genome-Wide Methylation of Mild Cognitive Impairment in Mexican Americans Highlights Genes Involved in Synaptic Transport, Alzheimer's Disease-Precursor Phenotypes, and Metabolic Morbidities. - Pathak, Gita A; Silzer, Talisa K; Sun, Jie; Zhou, Zhengyang; Daniel, Ann A; Johnson, Leigh; O'Bryant, Sid; Phillips, Nicole R; Barber, Robert C (J Alzheimers Dis, 2019)
The Mexican American population is among the fastest growing aging population and has a younger onset of cognitive decline. This group is also heavily burdened with metabolic conditions such as hypertension, diabetes, and obesity. Unfortunately, limited research has been conducted in this group. Understanding methylation alterations, which are influenced by both genetic and lifestyle factors, is key to identifying and addressing the root cause for mild cognitive impairment, a clinical precursor for dementia. We conducted an epigenome-wide association study on a community-based Mexican American population using the Illumina EPIC array. Following rigorous quality control measures, we identified 10 CpG sites to be differentially methylated between normal controls and individuals with mild cognitive impairment annotated to PKIB, KLHL29, SEPT9, OR2C3, CPLX3, BCL2L2-PABPN1, and CCNY. We found four regions to be differentially methylated in TMEM232, SLC17A8, ALOX12, and SEPT8. Functional gene-set analysis identified four gene-sets, RIN3, SPEG, CTSG, and UBE2L3, as significant. The gene ontology and pathway analyses point to neuronal cell death, metabolic dysfunction, and inflammatory processes. We found 1,450 processes to be enriched using empirical Bayes gene-set enrichment. In conclusion, the functional overlap of differentially methylated genes associated with cognitive impairment in Mexican Americans implies cross-talk between metabolically-instigated systemic inflammation and disruption of synaptic vesicular transport.

Geographical Variation in the Diagnostic Rate and Quality of Dementia Diagnoses. - Zakarias, Johanne Købstrup; Jensen-Dahm, Christina; Nørgaard, Ane; Roos, Peter; Gasse, Christiane; Phung, Thien Kieu Thi; Waldemar, Gunhild (J Alzheimers Dis, 2019)
BACKGROUND: Early and accurate diagnosis of dementia opens the door to appropriate treatment, support, and counseling. Despite availability of evidence-based guidelines for diagnostic evaluation of dementia, the diagnostic rate in people with dementia is low and the quality of dementia diagnoses is unknown. OBJECTIVE: The overall aim of this register-based study was to analyze the quality of diagnostic evaluation of dementia by assessing nationwide geographical variations in a range of indicators. METHODS: A register-based cross-sectional study of the entire Danish population aged 65 years or older in 2015 was conducted. The surrogate indicators for diagnostic quality included 1) prevalence rates of dementia diagnoses, 2) incidence rates of dementia diagnoses, 3) age at first diagnosis of dementia, 4) medical specialty responsible for diagnosis, 5) diagnostic rate of dementia subtypes, and 6) use of anti-dementia medication. The indicators were compared across the five Danish regions. RESULTS: The national prevalence and incidence of registered dementia diagnoses was 3.0% and 0.5%, respectively. The proportion of patients diagnosed at a dementia specialist department ranged from 60.9% to 90.5% across the five regions, subtype specific diagnosis ranged from 45.3% to 75.5%, and use of anti-dementia medication ranged from 29.2% to 58.3%. CONCLUSION: The observed geographical variations in dementia diagnoses and treatment indicate inequality in the access to appropriate diagnostic evaluation and care for patients with dementia. Our findings call for more awareness of the benefits of timely diagnosis and for improvement in the quality of diagnostic evaluation of dementia.

Herpes Simplex Virus, APOEɛ4, and Cognitive Decline in Old Age: Results from the Betula Cohort Study. - Lövheim, Hugo; Norman, Tove; Weidung, Bodil; Olsson, Jan; Josefsson, Maria; Adolfsson, Rolf; Nyberg, Lars; Elgh, Fredrik (J Alzheimers Dis, 2019)
BACKGROUND: Herpes simplex virus (HSV) has been suggested to play a role in Alzheimer's disease (AD) development. OBJECTIVE: The aim of the present study was to investigate the early AD-related symptom episodic memory decline in relation to HSV and carriage of allele 4 of the apolipoprotein E gene (APOEɛ4) in a large population-based cohort with a long follow-up time. METHODS: The study included 3,413 persons, with longitudinal data available for 1,293 persons with a mean follow-up time of 11.6 years. The associations between HSV carriage, APOEɛ4 carriage, and episodic memory was investigated at baseline, as well as in longitudinal analyses where individuals with and without HSV antibodies (HSV1/2 non-specific) were matched and episodic memory decline compared. RESULTS: Cross-sectional analyses revealed an age-dependent association of HSV carriage with lower episodic memory function, particularly among APOEɛ4 carriers (p = 0.008). Longitudinal analyses showed an increased risk of episodic memory decline in HSV carriers (≥65 years: p < 0.001, all ages: non-significant), and a significant interaction between HSV and APOEɛ4 for episodic memory decline (p < 0.001). CONCLUSION: In this large population-based cohort study, both cross-sectional and longitudinal results support an association between HSV carriage and declining episodic memory function, especially among APOEɛ4 carriers. The results strengthen the hypothesis that HSV is associated with AD development.

Inferring the Molecular Mechanisms of Noncoding Alzheimer's Disease-Associated Genetic Variants. - Amlie-Wolf, Alexandre; Tang, Mitchell; Way, Jessica; Dombroski, Beth; Jiang, Ming; Vrettos, Nicholas; Chou, Yi-Fan; Zhao, Yi; Kuzma, Amanda; Mlynarski, Elisabeth E; Leung, Yuk Yee; Brown, Christopher D; et al. (J Alzheimers Dis, 2019)
Most of the loci identified by genome-wide association studies (GWAS) for late-onset Alzheimer's disease (LOAD) are in strong linkage disequilibrium (LD) with nearby variants all of which could be the actual functional variants, often in non-protein-coding regions and implicating underlying gene regulatory mechanisms. We set out to characterize the causal variants, regulatory mechanisms, tissue contexts, and target genes underlying these associations. We applied our INFERNO algorithm to the top 19 non-APOE loci from the IGAP GWAS study. INFERNO annotated all LD-expanded variants at each locus with tissue-specific regulatory activity. Bayesian co-localization analysis of summary statistics and eQTL data was performed to identify tissue-specific target genes. INFERNO identified enhancer dysregulation in all 19 tag regions analyzed, significant enrichments of enhancer overlaps in the immune-related blood category, and co-localized eQTL signals overlapping enhancers from the matching tissue class in ten regions (ABCA7, BIN1, CASS4, CD2AP, CD33, CELF1, CLU, EPHA1, FERMT2, ZCWPW1). In several cases, we identified dysregulation of long noncoding RNA (lncRNA) transcripts and applied the lncRNA target identification algorithm from INFERNO to characterize their downstream biological effects. We also validated the allele-specific effects of several variants on enhancer function using luciferase expression assays. By integrating functional genomics with GWAS signals, our analysis yielded insights into the regulatory mechanisms, tissue contexts, genes, and biological processes affected by noncoding genetic variation associated with LOAD risk.

Lipopolysaccharide Induced Opening of the Blood Brain Barrier on Aging 5XFAD Mouse Model. - Barton, Shawn M; Janve, Vaibhav A; McClure, Richard; Anderson, Adam; Matsubara, Joanne A; Gore, John C; Pham, Wellington (J Alzheimers Dis, 2019)
The development of neurotherapeutics for many neurodegenerative diseases has largely been hindered by limited pharmacologic penetration across the blood-brain barrier (BBB). Previous attempts to target and clear amyloid-β (Aβ) plaques, a key mediator of neurodegenerative changes in Alzheimer's disease (AD), have had limited clinical success due to low bioavailability in the brain because of the BBB. Here we test the effects of inducing an inflammatory response to disrupt the BBB in the 5XFAD transgenic mouse model of AD. Lipopolysaccharide (LPS), a bacterial endotoxin recognized by the innate immune system, was injected at varying doses. 24 hours later, mice were injected with either thioflavin S, a fluorescent Aβ-binding small molecule or 30 nm superparamagnetic iron oxide (SPIO) nanoparticles, both of which are unable to penetrate the BBB under normal physiologic conditions. Our results showed that when pretreated with 3.0 mg/kg LPS, thioflavin S can be found in the brain bound to Aβ plaques in aged 5XFAD transgenic mice. Following the same LPS pretreatment, SPIO nanoparticles could also be found in the brain. However, when done on wild type or young 5XFAD mice, limited SPIO was detected. Our results suggest that the BBB in aged 5XFAD mouse model is susceptible to increased permeability mediated by LPS, allowing for improved delivery of the small molecule thioflavin S to target Aβ plaques and SPIO nanoparticles, which are significantly larger than antibodies used in clinical trials for immunotherapy of AD. Although this approach demonstrated efficacy for improved delivery to the brain, LPS treatment resulted in significant weight loss even at low doses, resulting from the induced inflammatory response. These findings suggest inducing inflammation can improve delivery of small and large materials to the brain for improved therapeutic or diagnostic efficacy. However, this approach must be balanced with the risks of systemic inflammation.

Maintain Your Brain: Protocol of a 3-Year Randomized Controlled Trial of a Personalized Multi-Modal Digital Health Intervention to Prevent Cognitive Decline Among Community Dwelling 55 to 77 Year Olds. - Heffernan, Megan; Andrews, Gavin; Fiatarone Singh, Maria A; Valenzuela, Michael; Anstey, Kaarin J; Maeder, Anthony J; McNeil, John; Jorm, Louisa; Lautenschlager, Nicola T; Sachdev, Perminder S; Ginige, Jeewani A; Hobbs, Megan J; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Maintain Your Brain (MYB) is a randomized controlled trial of an online multi-modal lifestyle intervention targeting modifiable dementia risk factors with its primary aim being to reduce cognitive decline in an older age cohort. METHODS: MYB aims to recruit 8,500 non-demented community dwelling 55 to 77 year olds from the Sax Institute's 45 and Up Study in New South Wales, Australia. Participants will be screened for risk factors related to four modules that comprise the MYB intervention: physical activity, nutrition, mental health, and cognitive training. Targeting risk factors will enable interventions to be personalized so that participants receive the most appropriate modules. MYB will run for three years and up to four modules will be delivered sequentially each quarter during year one. Upon completing a module, participants will continue to receive less frequent booster activities for their eligible modules (except for the mental health module) until the end of the trial. DISCUSSION: MYB will be the largest internet-based trial to attempt to prevent cognitive decline and potentially dementia. If successful, MYB will provide a model for not just effective intervention among older adults, but an intervention that is scalable for broad use.

Midlife Insulin Resistance as a Predictor for Late-Life Cognitive Function and Cerebrovascular Lesions. - Toppala, Sini; Ekblad, Laura L; Lötjönen, Jyrki; Helin, Semi; Hurme, Saija; Johansson, Jarkko; Jula, Antti; Karrasch, Mira; Koikkalainen, Juha; Laine, Hanna; Parkkola, Riitta; Viitanen, Matti; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Type 2 diabetes (T2DM) increases the risk for Alzheimer's disease (AD) but not for AD neuropathology. The association between T2DM and AD is assumed to be mediated through vascular mechanisms. However, insulin resistance (IR), the hallmark of T2DM, has been shown to associate with AD neuropathology and cognitive decline. OBJECTIVE: To evaluate if midlife IR predicts late-life cognitive performance and cerebrovascular lesions (white matter hyperintensities and total vascular burden), and whether cerebrovascular lesions and brain amyloid load are associated with cognitive functioning. METHODS: This exposure-to-control follow-up study examined 60 volunteers without dementia (mean age 70.9 years) with neurocognitive testing, brain 3T-MRI and amyloid-PET imaging. The volunteers were recruited from the Finnish Health 2000 survey (n = 6062) to attend follow-up examinations in 2014-2016 according to their insulin sensitivity in 2000 and their APOE genotype. The exposure group (n = 30) had IR in 2000 and the 30 controls had normal insulin sensitivity. There were 15 APOEɛ4 carriers per group. Statistical analyses were performed with multivariable linear models. RESULTS: At follow-up the IR+group performed worse on executive functions (p = 0.02) and processing speed (p = 0.007) than the IR- group. The groups did not differ in cerebrovascular lesions. No associations were found between cerebrovascular lesions and neurocognitive test scores. Brain amyloid deposition associated with slower processing speed. CONCLUSION: Midlife IR predicted poorer executive functions and slower processing speed, but not cerebrovascular lesions. Brain amyloid deposition was associated with slower processing speed. The association between midlife IR and late-life cognition might not be mediated through cerebrovascular lesions measured here.

Neurodegenerative Disease-Related Proteins within the Epidermal Layer of the Human Skin. - Akerman, S Can; Hossain, Shireen; Shobo, Adeola; Zhong, Yifei; Jourdain, Roland; Hancock, Mark A; George, Kelly; Breton, Lionel; Multhaup, Gerhard (J Alzheimers Dis, 2019)
There is increasing evidence suggesting that amyloidogenic proteins might form deposits in non-neuronal tissues in neurodegenerative disorders such as Alzheimer's or Parkinson's diseases. However, the detection of these aggregation-prone proteins within the human skin has been controversial. Using immunohistochemistry (IHC) and mass spectrometry tissue imaging (MALDI-MSI), fresh frozen human skin samples were analyzed for the expression and localization of neurodegenerative disease-related proteins. While α-synuclein was detected throughout the epidermal layer of the auricular samples (IHC and MALDI-MSI), tau and Aβ34 were also localized to the epidermal layer (IHC). In addition to Aβ peptides of varying length (e.g., Aβ40, Aβ42, Aβ34), we also were able to detect inflammatory markers within the same sample sets (e.g., thymosin β-4, psoriasin). While previous literature has described α-synuclein in the nucleus of neurons (e.g., Parkinson's disease), our current detection of α-synuclein in the nucleus of skin cells is novel. Imaging of α-synuclein or tau revealed that their presence was similar between the young and old samples in our present study. Future work may reveal differences relevant for diagnosis between these proteins at the molecular level (e.g., age-dependent post-translational modifications). Our novel detection of Aβ34 in human skin suggests that, just like in the brain, it may represent a stable intermediate of the Aβ40 and Aβ42 degradation pathway.

NP03, a Microdose Lithium Formulation, Blunts Early Amyloid Post-Plaque Neuropathology in McGill-R-Thy1-APP Alzheimer-Like Transgenic Rats. - Wilson, Edward N; Do Carmo, Sonia; Welikovitch, Lindsay A; Hall, Hélène; Aguilar, Lisi Flores; Foret, Morgan K; Iulita, M Florencia; Jia, Dan Tong; Marks, Adam R; Allard, Simon; Emmerson, Joshua T; Ducatenzeiler, Adriana; et al. (J Alzheimers Dis, 2019)
Epidemiological, preclinical, and clinical studies have suggested a role for microdose lithium in reducing Alzheimer's disease (AD) risk by modulating key mechanisms associated with AD pathology. The novel microdose lithium formulation, NP03, has disease-modifying effects in the McGill-R-Thy1-APP transgenic rat model of AD-like amyloidosis at pre-plaque stages, before frank amyloid-β (Aβ) plaque deposition, during which Aβ is primarily intraneuronal. Here, we are interested in determining whether the positive effects of microdose lithium extend into early Aβ post-plaque stages. We administered NP03 (40μg Li/kg; 1 ml/kg body weight) to McGill-R-Thy1-APP transgenic rats for 12 weeks spanning the transition phase from plaque-free to plaque-bearing. The effect of NP03 on remote working memory was assessed using the novel object recognition task. Levels of human Aβ38, Aβ40, and Aβ42 as well as levels of pro-inflammatory mediators were measured in brain-extracts and plasma using electrochemiluminescent assays. Mature Aβ plaques were visualized with a thioflavin-S staining. Vesicular acetylcholine transporter (VAChT) bouton density and levels of chemokine (C-X-C motif) ligand 1 (CXCL1), interleukin-6 (IL-6), and 4-hydroxynonenal (4-HNE) were probed using quantitative immunohistochemistry. During the early Aβ post-plaque stage, we find that NP03 rescues functional deficits in object recognition, reduces loss of cholinergic boutons in the hippocampus, reduces levels of soluble and insoluble cortical Aβ42 and reduces hippocampal Aβ plaque number. In addition, NP03 reduces markers of neuroinflammation and cellular oxidative stress. Together these results indicate that microdose lithium NP03 is effective at later stages of amyloid pathology, after appearance of Aβ plaques.

Transcriptome Changes in the Alzheimer's Disease Middle Temporal Gyrus: Importance of RNA Metabolism and Mitochondria-Associated Membrane Genes. - Piras, Ignazio S; Krate, Jonida; Delvaux, Elaine; Nolz, Jennifer; Mastroeni, Diego F; Persico, Antonio M; Jepsen, Wayne M; Beach, Thomas G; Huentelman, Matthew J; Coleman, Paul D (J Alzheimers Dis, 2019)
We used Illumina Human HT-12 v4 arrays to compare RNA expression of middle temporal gyrus (MTG; BA21) in Alzheimer's disease (AD = 97) and non-demented controls (ND = 98). A total of 938 transcripts were highly differentially expressed (adj p < 0.01; log2 FC ≥ |0.500|, with 411 overexpressed and 527 underexpressed in AD. Our results correlated with expression profiling in neurons from AD and ND obtained by laser capture microscopy in MTG from an independent dataset (log2 FC correlation: r = 0.504; p = 2.2e-16). Additionally, selected effects were validated by qPCR. ANOVA analysis yielded no difference between genders in response to AD, but some gender specific genes were detected (e.g., IL8 and AGRN in males, and HSPH1 and GRM1 in females). Several transcripts were associated with Braak staging (e.g., AEBP1 and DNALI1), antemortem MMSE (e.g., AEBP1 and GFAP), and tangle density (e.g., RNU1G2, and DNALI1). At the pathway level, we detected enrichment of synaptic vesicle processes and GABAergic transmission genes. Finally, applying the Weighted Correlation Network Analysis, we identified four expression modules enriched for neuronal and synaptic genes, mitochondria-associated membrane, chemical stimulus and olfactory receptor and non-coding RNA metabolism genes. Our results represent an extensive description of MTG mRNA profiling in a large sample of AD and ND. These data provide a list of genes associated with AD, and correlated to neurofibrillary tangles density. In addition, these data emphasize the importance of mitochondrial membranes and transcripts related to olfactory receptors in AD.

An UNC5C Allele Predicts Cognitive Decline and Hippocampal Atrophy in Clinically Normal Older Adults. - Yang, Hyun-Sik; Chhatwal, Jasmeer P; Xu, Jishu; White, Charles C; Hanseeuw, Bernard; Rabin, Jennifer S; Papp, Kathryn V; Buckley, Rachel F; Schultz, Aaron P; Properzi, Michael J; Gatchel, Jennifer R; Amariglio, Rebecca E; et al. (J Alzheimers Dis, 2019)
BACKGROUND: The UNC5C rs3846455G allele has been linked to poor cognitive resilience against age-related neuropathologies, but this association remains to be replicated, and the allele's effect on hippocampal neurodegeneration needs to be examined. OBJECTIVE: To further validate the association between rs3846455G and faster cognitive decline, especially among cognitively normal older adults, and to assess whether rs3846455G predicts accelerated hippocampal volume loss in older adults. METHODS: We assessed participants in the Harvard Aging Brain Study (HABS), a longitudinal cohort study of older adults who were clinically normal at baseline. To avoid bias from population admixture, analyses were limited to participants of European descent with longitudinal neuroimaging data (n = 174). Linear mixed effect models were used to examine the effect of rs3846455G on longitudinal change of the Preclinical Alzheimer Cognitive Composite (PACC) and MRI-measured bilateral hippocampal volume, adjusting for baseline amyloid-β (Aβ) measured by the cortical Pittsburgh Compound B PET distributed volume ratio. We also tested whether hippocampal atrophy mediates the association between rs3846455G and greater PACC decline through a mediation analysis. RESULTS: rs3846455G was associated with greater PACC decline (β= -0.087/year, 95% CI -0.169 to -0.005, p = 0.039) after controlling for baseline Aβ. Further, rs3846455G predicted accelerated hippocampal atrophy after controlling for baseline Aβ (β= -57.3 mm3/year, 95% CI -102.8 to -11.9, p = 0.014). The association between rs3846455G and greater PACC decline was partially mediated by accelerated hippocampal atrophy (mediated effect (relative scale) = -0.014, 95% CI -0.032 to -6.0×10-4, p = 0.039). CONCLUSION: UNC5C rs3846455G predicts greater cognitive decline and accelerated hippocampal atrophy in clinically normal older adults.

Vascular Burden Score Impacts Cognition Independent of Amyloid PET and MRI Measures of Alzheimer's Disease and Vascular Brain Injury. - DeCarli, Charles; Villeneuve, Sylvia; Maillard, Pauline; Harvey, Danielle; Singh, Baljeet; Carmichael, Owen; Fletcher, Evan; Olichney, John; Farias, Sarah; Jagust, William; Reed, Bruce; Mungas, Dan (J Alzheimers Dis, 2019)
BACKGROUND/OBJECTIVE: To determine the impact of vascular burden on rates of decline in episodic memory and executive function. We hypothesize that greater vascular burden will have an additive negative impact on cognition after accounting for baseline cognitive impairment, positron emission tomography (PET) amyloid burden, and magnetic resonance imaging (MRI) measures. METHODS: Individuals were followed an average of 5 years with serial cognitive assessments. Predictor variables include vascular burden score (VBS), quantitative brain MRI assessment, and amyloid imaging. Subjects consisted of 65 individuals, 53% of whom were male, aged 73.2±7.2 years on average with an average of 15.5±3.3 years of educational achievement. RESULTS: Baseline cognitive impairment was significantly associated poorer episodic memory (p < 0.0001), smaller hippocampal volume (p < 0.0001), smaller brain volume (p = 0.0026), and greater global Pittsburg Imaging Compound B (PiB) index (p = 0.0008). Greater amyloid burden was associated with greater decline in episodic memory over time (β= -0.20±0.07, p < 0.005). VBS was significantly associated with the level of executive function performance (β= -0.14±0.05, p < 0.005) and there was a significant negative interaction between VBS, cognitive impairment, and PiB index (β= -0.065±0.03, p = 0.03). CONCLUSIONS: Our results find a significant influence of VBS independent of standard MRI measures and cerebral amyloid burden on executive function. In addition, VBS reduced the amount of cerebral amyloid burden needed to result in cognitive impairment. We conclude that the systemic effects of vascular disease as reflected by the VBS independently influence cognitive ability.

11C-CFT-PET in Presymptomatic FTDP-17: A Potential Biomarker Predicting Onset. - Wu, Liyong; Liu, Jia; Feng, Xueyan; Dong, Jing; Qin, Wei; Liu, Yang; Wang, Jingjuan; Lu, Jie; Chen, Kewei; Wang, Yuping; Jia, Jianping (J Alzheimers Dis, 2018)
Frontotemporal dementia with parkinsonism-linked to chromosome 17 (FTDP-17) is a rare autosomal dominant neurodegenerative disorder. Most patients with FTDP-17 carry the mutation in the microtubule-associated protein tau (MAPT) gene. Striatum is predominantly and early affected in FTDP-17. Five family members (two symptomatic patients and three presymptomatic mutation carriers) from a Chinese pedigree of FTDP-17 with N279K mutation in MAPT were enrolled. Parkinsonism was the initial symptom for symptomatic patients. 2b-carbomethoxy-3b-(4-trimethylstannylphenyl) tropane (11C-CFT) uptake was obviously affected in the putamen of two presymptomatic mutation carriers. Presymptomatic case 3, whose 11C-CFT uptake in the right putamen was normal at baseline, was still free of parkinsonism during follow-up. In conclusion, 11C-CFT-positron emission tomography could be a potential biomarker for the presymptomatic stage of FTDP-17 to predict the disease onset.
Keywords: Adult; Biomarkers; Brain; Carbon Radioisotopes; Female; Frontotemporal Dementia; Heterozygote; Humans; Male; Middle Aged; Mutation; Parkinsonian Disorders; Pedigree; Positron-Emission Tomography; tau Proteins

18F-Flortaucipir Binding in Choroid Plexus: Related to Race and Hippocampus Signal. - Lee, Christopher M; Jacobs, Heidi I L; Marquié, Marta; Becker, John A; Andrea, Nicolas V; Jin, David S; Schultz, Aaron P; Frosch, Matthew P; Gómez-Isla, Teresa; Sperling, Reisa A; Johnson, Keith A (J Alzheimers Dis, 2018)
BACKGROUND: On target 18F-Flortaucipir (FTP) binding of Alzheimer's disease tau aggregates and off-target binding of melanocytes have been demonstrated with autoradiography. OBJECTIVE: We aimed to investigate the hypothesis that if binding in choroid plexus (CP) is due to melanocytes, the signal would be elevated in Black/African American (B/AA) compared to White (W) participants. In addition, we examined whether CP signal affects measurements in adjacent regions, and whether correcting for spill-in effects has an influence on associations between hippocampus (HC) FTP and amyloid or cognition. METHODS: FTP race differences in 147 Harvard Aging Brain Study participants (23 B/AA, 124W) were examined in CP, HC, HC covaried for CP, amygdala, inferior temporal gyrus, entorhinal cortex, and fusiform regions. Associations between CP FTP and other regions-of-interest (ROIs) were probed to assess spill-in effects. A statistical regression approach to attenuate CP spill-in was tested by relating adjusted HC SUVR residuals and unadjusted HC SUVR to race, cognition and amyloid. All analyses were covaried for age, sex, education and amyloid deposition, and Bonferroni-corrected for multiple comparisons. RESULTS: B/AA individuals had elevated CP and HC SUVR (p < 0.007), whereas other ROI SUVR and HC SUVR covaried for CP SUVR did not show race differences (p > 0.05). CP SUVR was associated with HC SUVR (p < 10-14), but with no other ROI SUVR (p > 0.05). When adjusting HC SUVR for CP SUVR, no race differences in residual HC SUVR were detected, and relationships with amyloid and memory became apparent. CONCLUSION: Melanocyte FTP binding may account partially for high CP signal. This off-target binding affects mainly HC FTP measurements, which should be interpreted with caution.

Acute Stroke Care in Dementia: A Cohort Study from the Swedish Dementia and Stroke Registries. - Zupanic, Eva; Kåreholt, Ingemar; Norrving, Bo; Secnik, Juraj; von Euler, Mia; Winblad, Bengt; Religa, Dorota; Kramberger, Milica Gregoric; Johnell, Kristina; Eriksdotter, Maria; Garcia-Ptacek, Sara (J Alzheimers Dis, 2018)
BACKGROUND: Previous studies have shown that patients with dementia receive less testing and treatment for stroke. OBJECTIVES: Our aim was to investigate hospital management of acute ischemic stroke in patients with and without dementia. METHODS: Retrospective analysis of prospectively collected data 2010-2014 from the Swedish national dementia registry (SveDem) and the Swedish national stroke registry (Riksstroke). Patients with dementia who suffered an acute ischemic stroke (AIS) (n = 1,356) were compared with matched non-dementia AIS patients (n = 6,755). Outcomes included length of stay in a stroke unit, total length of hospitalization, and utilization of diagnostic tests and assessments. RESULTS: The median age at stroke onset was 83 years. While patients with dementia were equally likely to be directly admitted to a stroke unit as their non-dementia counterparts, their stroke unit and total hospitalization length were shorter (10.5 versus 11.2 days and 11.6 versus 13.5, respectively, p < 0.001). Dementia patients were less likely to receive carotid ultrasound (OR 0.36, 95% CI [0.30-0.42]) or undergo assessments by the interdisciplinary team members (physiotherapists, speech therapists, occupational therapists; p < 0.05 for all adjusted models). However, a similar proportion of patients received CT imaging (97.4% versus 98.6%, p = 0.001) and a swallowing assessment (90.7% versus 91.8%, p = 0.218). CONCLUSIONS: Patients with dementia who suffer an ischemic stroke have equal access to direct stroke unit care compared to non-dementia patients; however, on average, their stay in a stroke unit and total hospitalization are shorter. Dementia patients are also less likely to receive specific diagnostic tests and assessments by the interdisciplinary stroke team.

The Added Value of Diffusion-Weighted MRI-Derived Structural Connectome in Evaluating Mild Cognitive Impairment: A Multi-Cohort Validation1. - Wang, Qi; Guo, Lei; Thompson, Paul M; Jack, Clifford R; Dodge, Hiroko; Zhan, Liang; Zhou, Jiayu (J Alzheimers Dis, 2018)
T1-weighted MRI has been extensively used to extract imaging biomarkers and build classification models for differentiating Alzheimer's disease (AD) patients from healthy controls, but only recently have brain connectome networks derived from diffusion-weighted MRI been used to model AD progression and various stages of disease such as mild cognitive impairment (MCI). MCI, as a possible prodromal stage of AD, has gained intense interest recently, since it may be used to assess risk factors for AD. Little work has been done to combine information from both white matter and gray matter, and it is unknown how much classification power the diffusion-weighted MRI-derived structural connectome could provide beyond information available from T1-weighted MRI. In this paper, we focused on investigating whether diffusion-weighted MRI-derived structural connectome can improve differentiating healthy controls subjects from those with MCI. Specifically, we proposed a novel feature-ranking method to build classification models using the most highly ranked feature variables to classify MCI with healthy controls. We verified our method on two independent cohorts including the second stage of Alzheimer's Disease Neuroimaging Initiative (ADNI2) database and the National Alzheimer's Coordinating Center (NACC) database. Our results indicated that 1) diffusion-weighted MRI-derived structural connectome can complement T1-weighted MRI in the classification task; 2) the feature-rank method is effective because of the identified consistent T1-weighted MRI and network feature variables on ADNI2 and NACC. Furthermore, by comparing the top-ranked feature variables from ADNI2, NACC, and combined dataset, we concluded that cross-validation using independent cohorts is necessary and highly recommended.

Albuminuria and Microalbuminuria as Predictors of Cognitive Performance in a General Population: An 11-Year Follow-Up Study. - Ekblad, Laura L; Toppala, Sini; Johansson, Jouni K; Koskinen, Seppo; Sundvall, Jouko; Rinne, Juha O; Puukka, Pauli; Viitanen, Matti; Jula, Antti (J Alzheimers Dis, 2018)
Microalbuminuria, defined as urine albumin-to-creatinine ratio (UACR)>3.0 mg/mmol and ≤ 30 mg/mmol, is an early marker of endothelial damage of the renal glomeruli. Recent research suggests an association among microalbuminuria, albuminuria (UACR > 3.0 mg/mmol), and cognitive impairment. Previous studies on microalbuminuria, albuminuria, and cognition in the middle-aged have not provided repeated cognitive testing at different time-points. We hypothesized that albuminuria (micro- plus macroalbuminuria) and microalbuminuria would predict cognitive decline independently of previously reported risk factors for cognitive decline, including cardiovascular risk factors. In addition, we hypothesized that UACR levels even below the cut-off for microalbuminuria might be associated with cognitive functioning. These hypotheses were tested in the Finnish nationwide, population-based Health 2000 Survey (n = 5,921, mean age 52.6, 55.0% women), and its follow-up, Health 2011 (n = 3,687, mean age at baseline 49.3, 55.6% women). Linear regression analysis was used to determine the associations between measures of albuminuria and cognitive performance. Cognitive functions were assessed with verbal fluency, word-list learning, word-list delayed recall (at baseline and at follow-up), and with simple and visual choice reaction time tests (at baseline only). Here, we show that micro- plus macroalbuminuria associated with poorer word-list learning and a slower reaction time at baseline, with poorer word-list learning at follow-up, and with a steeper decline in word-list learning during 11 years after multivariate adjustments. Also, higher continuous UACR consistently associated with poorer verbal fluency at levels below microalbuminuria. These results suggest that UACR might have value in evaluating the risk for cognitive decline.
Keywords: Adult; Aged; Albuminuria; Cognition; Cognitive Dysfunction; Creatinine; Cross-Sectional Studies; Female; Finland; Follow-Up Studies; Humans; Kidney; Linear Models; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Risk Factors

Alterations in the Plasma Levels of Specific Choline Phospholipids in Alzheimer's Disease Mimic Accelerated Aging. - Dorninger, Fabian; Moser, Ann B; Kou, Jianqiu; Wiesinger, Christoph; Forss-Petter, Sonja; Gleiss, Andreas; Hinterberger, Margareta; Jungwirth, Susanne; Fischer, Peter; Berger, Johannes (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common neurodegenerative disease and of continuously rising prevalence. The identification of easy-to-measure biomarkers capable to assist in the prediction and early diagnosis of AD is currently a main research goal. Lipid metabolites in peripheral blood of human patients have recently gained major attention in this respect. Here, we analyzed plasma of 174 participants (not demented at baseline; mean age: 75.70±0.44 years) of the Vienna Transdanube Aging (VITA) study, a longitudinal, population-based birth cohort study, at baseline and after 90 months or at diagnosis of probable AD. We determined the levels of specific choline phospholipids, some of which have been suggested as potential biomarkers for the prediction of AD. Our results show that during normal aging the levels of lysophosphatidylcholine, choline plasmalogen, and lyso-platelet activating factor increase significantly. Notably, we observed similar but more pronounced changes in the group that developed probable AD. Thus, our results imply that, in terms of choline-containing plasma phospholipids, the conversion to AD mimics an accelerated aging process. We conclude that age, even in the comparatively short time frame between 75 and 82.5 years, is a crucial factor in the quest for plasma lipid biomarkers for AD that must be carefully considered in future studies and trials.

Alterations of Effective Connectivity Patterns in Mild Cognitive Impairment: An MEG Study. - Gómez, Carlos; Juan-Cruz, Celia; Poza, Jesús; Ruiz-Gómez, Saúl J; Gomez-Pilar, Javier; Núñez, Pablo; García, María; Fernández, Alberto; Hornero, Roberto (J Alzheimers Dis, 2018)
Neuroimaging techniques have demonstrated over the years their ability to characterize the brain abnormalities associated with different neurodegenerative diseases. Among all these techniques, magnetoencephalography (MEG) stands out by its high temporal resolution and noninvasiveness. The aim of the present study is to explore the coupling patterns of resting-state MEG activity in subjects with mild cognitive impairment (MCI). To achieve this goal, five minutes of spontaneous MEG activity were acquired with a 148-channel whole-head magnetometer from 18 MCI patients and 26 healthy controls. Inter-channel relationships were investigated by means of two complementary coupling measures: coherence and Granger causality. Coherence is a classical method of functional connectivity, while Granger causality quantifies effective (or causal) connectivity. Both measures were calculated in the five conventional frequency bands: delta (δ, 1-4 Hz), theta (θ, 4-8 Hz), alpha (α, 8-13 Hz), beta (β, 13-30 Hz), and gamma (γ, 30-45 Hz). Our results showed that connectivity values were lower for MCI patients than for controls in all frequency bands. However, only Granger causality revealed statistically significant differences between groups (p-values < 0.05, FDR corrected Mann-Whitney U-test), mainly in the beta band. Our results support the role of MCI as a disconnection syndrome, which elicits early alterations in effective connectivity patterns. These findings can be helpful to identify the neural substrates involved in prodromal stages of dementia.

Altered Expression of Urea Cycle Enzymes in Amyloid-β Protein Precursor Overexpressing PC12 Cells and in Sporadic Alzheimer's Disease Brain. - Jęśko, Henryk; Lukiw, Walter J; Wilkaniec, Anna; Cieślik, Magdalena; Gąssowska-Dobrowolska, Magdalena; Murawska, Emilia; Hilgier, Wojciech; Adamczyk, Agata (J Alzheimers Dis, 2018)
Urea cycle enzymes may play important yet poorly characterized roles in Alzheimer's disease (AD). Our previous results showed that amyloid-β (Aβ) affects urea cycle enzymes in rat pheochromocytoma (PC12) cells. The aim of the present study was to investigate the changes in arginases, other urea cycle enzymes, and nitric oxide synthases (NOSs) in PC12 cells transfected with AβPP bearing the double 'Swedish' mutation (APPsw, K670M/N671L) and in postmortem sporadic AD brain hippocampus; the mutation intensifies Aβ production and strongly associates with AD neuropathology. mRNA expression was analyzed using real-time PCR in cell cultures and DNA microarrays in hippocampal CA1 area of human AD brains. Arginase activity was measured spectrophotometrically, and arginine, ornithine, and citrulline levels by high-performance liquid chromatography. Our data demonstrated that the expression and activity of arginases (Arg1 and Arg2), as well as the expression of argininosuccinate synthase (Ass) were significantly reduced in APPsw cells compared to control. However, argininosuccinate lyase (Asl) was upregulated in APPsw cells. Real-time PCR analysis revealed significant elevation of neuronal nitric oxide synthase (Nnos) mRNA in APPsw cells, without changes in the endothelial Enos, whereas inducible Inos was undetectable. The changes were found to follow closely those observed in the human hippocampal CA1 region of sporadic AD brains. The changes in enzyme expression were accompanied in APPsw cells by significantly elevated citrulline, ornithine, and arginine. Our findings demonstrate that AβPP/Aβ alters arginine metabolism and induces a shift of cellular homeostasis that may support the oxidative/nitrosative stress observed in AD.

Alzheimer-Like Pattern of Hypometabolism Emerges with Elevated Amyloid-β Burden in Down Syndrome. - Lao, Patrick J; Handen, Ben L; Betthauser, Tobey J; Mihaila, Iulia; Hartley, Sigan L; Cohen, Annie D; Tudorascu, Dana L; Bulova, Peter D; Lopresti, Brian J; Tumuluru, Rameshwari V; Murali, Dhanabalan; Mathis, Chester A; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The Down syndrome (DS) population is genetically predisposed to amyloid-β protein precursor overproduction and Alzheimer's disease (AD). OBJECTIVE: The temporal ordering and spatial association between amyloid-β, glucose metabolism, and gray matter (GM) volume in the DS population can provide insight into those associations in the more common sporadic AD. METHODS: Twenty-four adults (13 male, 11 female; 39±7 years) with DS underwent [11C]PiB, [18F]FDG, and volumetric MRI scans. Voxel-wise associations between PiB SUVR, FDG SUVR, and GM volume were investigated, with and without individual adjustments for variables of interest. RESULTS: Positive associations of PiB and age were widespread throughout the neocortex and striatum. Negative associations of FDG and age (frontal, parietal, and temporal cortex) and of GM volume and age (frontal and insular cortex) were observed. PiB and FDG were negatively associated in parietal cortex, after adjustment for GM volume. CONCLUSIONS: In adults with DS, early amyloid-β accumulation in the striatum is divergent from sporadic AD; however, despite the early striatal amyloid-β, glucose hypometabolism was confined to the typical AD-associated regions, which occurs similarly in autosomal dominant AD. Importantly, the glucose hypometabolism was not explained solely by increased partial volume effect due to GM volume reductions.
Keywords: Adult; Alzheimer Disease; Amyloid beta-Peptides; Down Syndrome; Female; Fluorodeoxyglucose F18; Gray Matter; Humans; Linear Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Positron-Emission Tomography; Radiopharmaceuticals; United States

Alzheimer's Disease Biomarkers Have Distinct Associations with Specific Hippocampal Subfield Volumes. - Müller-Ehrenberg, Lisa; Riphagen, Joost M; Verhey, Frans R J; Sack, Alexander T; Jacobs, Heidi I L (J Alzheimers Dis, 2018)
Measures of amyloid-β (Aβ) and phosphorylated tau (p-tau) concentrations in cerebrospinal fluid are extensively used for diagnostic and research purposes in Alzheimer's disease (AD) as correlates of cortical thinning and cognitive outcomes. The present study investigated the relationship of Aβ and p-tau with hippocampal subfield volumes Cornu Ammonis (CA) 1-4, dentate gyrus (DG), and subiculum. Subfields were segmented from T1-weighted images from the ADNI-population using FreeSurfer v6. Linear and polynomial regression models revealed distinct associations of Aβ and p-tau with subfield volumes. Aβ had a quadratic relationship with all hippocampal subfield volumes and the inflection point was higher than the validated cut-off for Aβ. For p-tau the relationships were linear, except for CA3, in which it was quadratic. For the CA1 and CA3, these quadratic relationships with Aβ were only observed when p-tau was low. Amyloid and p-tau contributed equally to the explained variance in CA4 and DG volume. Subicular volume was best explained by Aβ alone. These biomarker relationships with hippocampal subfield volumes seem to mirror the hippocampal-specific topography of Aβ and tau reported in neuropathological staging models. In addition, using continuous values of Aβ reveals positive patterns with imaging markers for individuals around the positivity threshold that would be masked when using dichotomized biomarker groups, which can be important for early detection and accurate inclusion of potential participants at risk for AD in clinical trials.

Alzheimer's Disease rs11767557 Variant Regulates EPHA1 Gene Expression Specifically in Human Whole Blood. - Liu, Guiyou; Zhang, Yan; Wang, Longcai; Xu, Jianyong; Chen, Xiaoyun; Bao, Yunjuan; Hu, Yang; Jin, Shuilin; Tian, Rui; Bai, Weiyang; Zhou, Wenyang; Wang, Tao; et al. (J Alzheimers Dis, 2018)
Large-scale genome-wide association studies have reported EPHA1 rs11767557 variant to be associated with Alzheimer's disease (AD) risk in the European population. However, it is still unclear how this variant functionally contributes to the underlying disease pathogenesis. The rs11767557 variant is located approximately 3 kb upstream of EPHA1 gene. We think that rs11767557 may modify the expression of nearby genes such as EPHA1 and further cause AD risk. Until now, the potential association between rs11767557 and the expression of nearby genes has not been reported in previous studies. Here, we evaluate the potential expression association between rs11767557 and EPHA1 using multiple large-scale eQTLs datasets in human brain tissues and the whole blood. The results show that rs11767557 variant could significantly regulate EPHA1 gene expression specifically in human whole blood. These findings may further provide important supplementary information about the regulating mechanisms of rs11767557 variant in AD risk.
Keywords: Alzheimer Disease; Case-Control Studies; China; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Receptor, EphA1; Risk Assessment

Amyloid-β25-35 Upregulates Endogenous Neuroprotectant Neuroglobin via NFκB Activation in vitro. - Liu, Ning; Yu, Zhanyang; Xun, Yu; Shu, Pan; Yue, Yiwei; Yuan, Shishan; Jiang, Yinghua; Huang, Zixuan; Yang, Xiaoping; Feng, Xing; Xiang, Shuanglin; Wang, Xiaoying (J Alzheimers Dis, 2018)
Neuroglobin (Ngb) has been reported to be increased in early and moderately advanced Alzheimer's disease (AD) stages but declined in the severe stage. However, its regulatory mechanisms and pathophysiological roles in the disease remain to be defined. In this study, we found that Ngb expression was significantly upregulated by low dose Aβ25-35, the neurotoxic fragment of Aβ1 - 40 and Aβ1 - 42, but was not further increased by a higher dose of Aβ25-35. Mutation analysis and supershift assay demonstrated that transcription factor Nuclear Factor κB (NFκB), κB2 and κB3 sites located in mouse Ngb promoter region were involved in dynamic regulation of Ngb expression in response to different doses of Aβ25-35 stimulation. In addition, we found that suppression of endogenous Ngb expression exacerbated Aβ25-35-induced neuronal cell death and mitochondrial dysfunction. Our results indicate that endogenous Ngb expression may be upregulated by low dose Aβ25-35, which is responsible for protecting against Aβ25-35-mediated neurotoxicity. These experimental findings suggest that upregulation of endogenous Ngb expression might be an effective intervention approach for AD.

Analyses of Clinical Features and Investigations on Potential Mechanisms in Patients with Alzheimer's Disease and Olfactory Dysfunction. - Zuo, Li-Jun; Guo, Peng; Liu, Li; Yu, Shu-Yang; Lian, Teng-Hong; Yu, Qiu-Jin; Hu, Yang; Jin, Zhao; Wang, Rui-Dan; Piao, Ying-Shan; Li, Li-Xia; Wang, Ya-Jie; et al. (J Alzheimers Dis, 2018)
BACKGROUND: OD is common in patients with Alzheimer's disease (AD). However, the relationship between OD and clinical symptoms and the potential mechanisms of OD in AD patients are still unknown. OBJECTIVE: To explore the relationship between OD and clinical symptoms and the potential mechanisms of OD in AD patients. METHODS: We evaluated OD using the Hyposmia Rating Scale (HRS), classified patients into AD with OD (AD-OD) and AD with no OD (AD-NOD) groups, and detected the levels of free radicals and inflammatory factors, including hydroxyl radical (•OH), hydrogen peroxide (H2O2), nitric oxide, interleukin-1β, interleukin-6, tumor necrosis factor-α, and prostaglandin E2 in serum from AD patients. RESULTS: It was shown that the scores of the Mini-Mental State Examination, Animal Fluency Test, Boston Naming Test (BNT), and Auditory Verbal Learning Test-delayed recall were all significantly lower and the score of overall activity of daily living (ADL) and instrumental ADL were significantly higher in AD-OD group than those in AD-NOD group. Compared with AD-NOD group, •OH level in serum was prominently elevated, and H2O2 level was dramatically declined in AD-OD group. In the correlation analysis, HRS score was significantly and positively correlated with the score of BNT, and negatively correlated with •OH level in serum. CONCLUSIONS: AD-OD patients suffered from severe cognitive impairment in the domain of language. Oxidative stress might be correlated with AD-OD featured by the drastically increased •OH level in serum.

Antemortem-Postmortem Correlation of Florbetapir (18F) PET Amyloid Imaging with Quantitative Biochemical Measures of Aβ42 but not Aβ40. - Beach, Thomas G; Maarouf, Chera L; Intorcia, Anthony; Sue, Lucia I; Serrano, Geidy E; Lu, Ming; Joshi, Abhinay; Pontecorvo, Michael J; Roher, Alex E (J Alzheimers Dis, 2018)
Amyloid imaging demonstrates the in vivo presence of amyloid-β (Aβ) deposits in the aging human brain but it is still unknown which structural forms and modifications of Aβ are detected. In Alzheimer's disease, most amyloid deposits are predominantly composed of Aβ ending at amino acid residues Val40 or Ala42. It has been reported that Aβ40 is largely restricted to neuritic plaques while Aβ42 may be deposited in amyloid plaques of all types, and is often the sole component of diffuse plaques. The distinction is important as it is mainly the neuritic plaques that correlate with cognitive impairment while diffuse plaques may be the initial type of Aβ deposited. Whether PET amyloid ligands such as florbetapir-18F (Amyvid) are partially or wholly selective for brain deposits of Aβ40 or Aβ42 is currently unknown. We compared antemortem florbetapir PET cortical/cerebellar signal intensity (SUVr) of 55 subjects with postmortem biochemical (ELISA) measurements employing specific antibodies against Aβ40 and Aβ42. Spearman's univariable correlations were significant for both Aβ40 and Aβ42, but were much stronger for Aβ42. Multiple linear regression showed significance only for Aβ42. These results suggest that florbetapir binds only weakly, if at all, to Aβ40. This may be in part due to the higher likelihood for Aβ42 to be present in a β-pleated sheet tertiary structure, or to differences between Aβ40 and Aβ42 in β-pleated sheet tertiary or quaternary structure.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Amyloidosis; Aniline Compounds; Autopsy; Brain; Ethylene Glycols; Humans; Linear Models; Peptide Fragments; Plaque, Amyloid; Positron-Emission Tomography

Anticholinergic Burden and Risk of Stroke and Death in People with Different Types of Dementia. - Tan, Edwin C K; Eriksdotter, Maria; Garcia-Ptacek, Sara; Fastbom, Johan; Johnell, Kristina (J Alzheimers Dis, 2018)
BACKGROUND: Anticholinergic burden is associated with poorer cognitive and functional outcomes in people with dementia. However, the impact of anticholinergics on significant adverse outcomes such as stroke has not been studied previously. OBJECTIVE: To investigate the association between total anticholinergic cognitive burden (ACB) and risk of stroke and death in people with different dementia subtypes. METHODS: This was a cohort study of 39,107 people with dementia and no prior history of stroke registered in the Swedish Dementia Registry (SveDem) from 2008-2014. Data were extracted from the Swedish Prescribed Drug Register, the Swedish National Patient Register, and the Swedish Total Population Register. Competing risk regression models were used to compute hazard ratios (HRs) and 95% confidence intervals (CIs) for the association between time-varying ACB score and risk of stroke and all-cause mortality. RESULTS: During a mean follow-up period of 2.31 (standard deviation 1.66) years, 11,224 (28.7%) individuals had a stroke or died. Compared with non-users of anticholinergic medications, ACB score of 1 (HR 1.09, 95% CI 1.04-1.14) and ACB score of ≥2 (HR 1.20, 95% CI 1.14-1.26) increased the risk of developing the composite outcome of stroke and death. When stratifying by dementia disorder, the association remained significant in Alzheimer's disease, mixed dementia, and vascular dementia. CONCLUSIONS: The use of anticholinergic medicines may be associated with an increased risk of stroke and death in people with dementia. A dose-response relationship was observed. Careful consideration should be made when prescribing medications with anticholinergic properties to people with dementia.

Assessing Mild Behavioral Impairment with the Mild Behavioral Impairment-Checklist in People with Mild Cognitive Impairment. - Mallo, Sabela C; Ismail, Zahinoor; Pereiro, Arturo X; Facal, David; Lojo-Seoane, Cristina; Campos-Magdaleno, María; Juncos-Rabadán, Onésimo (J Alzheimers Dis, 2018)
BACKGROUND: Neuropsychiatric symptoms (NPS) are non-cognitive, behavioral, or psychiatric symptoms, common in mild cognitive impairment (MCI) and associated with a higher risk of dementia. Mild behavioral impairment (MBI) is a validated diagnostic entity, that describes the emergence of later life NPS in pre-dementia states. The Mild Behavioral Impairment Checklist (MBI-C) is the first measure developed to assess MBI. OBJECTIVE: To estimate the prevalence of MBI in people with MCI and to study the score distribution, sensitivity, specificity, diagnostic utility of the MBI-C, and its correlations with neuropsychological tests. METHODS: One hundred eleven MCI participants were evaluated with the Questionnaire for Subjective Memory Complaints (QSMC), Mini-Mental State Examination, Cambridge Cognitive Assessment-Revised, Neuropsychiatric Inventory-Questionnaire (NPI-Q), Geriatric Depression Scale-15 items (GDS-15), Lawton and Brody Index, and the MBI-C, which was administered by phone to participants' informants. Descriptive, logistic regression, ROC curve, and bivariate correlations analyses were performed. RESULTS: MBI diagnosis prevalence was 14.2%. The total MBI-C score differentiated people with MBI at a cutoff-point of 6.5, optimizing sensitivity and specificity. MBI-C total score correlated positively with NPI-Q, QSMC, GDS-15, and Lawton and Brody Index. CONCLUSION: The total MBI-C score, obtained by phone administration, is sensitive for detecting MBI in people with MCI. The MBI-C scores indicated that MCI participants had subtle NPS that were correlated to their subjective memory complaints reported by informants, depressive symptoms, and negatively with Instrumental Activities of Daily Living. Further research should be done to clarify the predictive role of NPS in MCI for incident dementia.

Assessing Working Memory in Mild Cognitive Impairment with Serial Order Recall. - Emrani, Sheina; Libon, David J; Lamar, Melissa; Price, Catherine C; Jefferson, Angela L; Gifford, Katherine A; Hohman, Timothy J; Nation, Daniel A; Delano-Wood, Lisa; Jak, Amy; Bangen, Katherine J; Bondi, Mark W; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Working memory (WM) is often assessed with serial order tests such as repeating digits backward. In prior dementia research using the Backward Digit Span Test (BDT), only aggregate test performance was examined. OBJECTIVE: The current research tallied primacy/recency effects, out-of-sequence transposition errors, perseverations, and omissions to assess WM deficits in patients with mild cognitive impairment (MCI). METHODS: Memory clinic patients (n = 66) were classified into three groups: single domain amnestic MCI (aMCI), combined mixed domain/dysexecutive MCI (mixed/dys MCI), and non-MCI where patients did not meet criteria for MCI. Serial order/WM ability was assessed by asking participants to repeat 7 trials of five digits backwards. Serial order position accuracy, transposition errors, perseverations, and omission errors were tallied. RESULTS: A 3 (group)×5 (serial position) repeated measures ANOVA yielded a significant group×trial interaction. Follow-up analyses found attenuation of the recency effect for mixed/dys MCI patients. Mixed/dys MCI patients scored lower than non-MCI patients for serial position 3 (p < 0.003) serial position 4 (p < 0.002); and lower than both group for serial position 5 (recency; p < 0.002). Mixed/dys MCI patients also produced more transposition errors than both groups (p < 0.010); and more omissions (p < 0.020), and perseverations errors (p < 0.018) than non-MCI patients. CONCLUSIONS: The attenuation of a recency effect using serial order parameters obtained from the BDT may provide a useful operational definition as well as additional diagnostic information regarding working memory deficits in MCI.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Executive Function; Female; Humans; Male; Memory Disorders; Memory, Short-Term; Mental Recall; Neuropsychological Tests; Regression Analysis; Serial Learning

Association Between the Use of Antihyperglycemic Drugs and Dementia Risk: A Case-Control Study. - Bohlken, Jens; Jacob, Louis; Kostev, Karel (J Alzheimers Dis, 2018)
BACKGROUND: There is a conflicting literature on the association between the use of antihyperglycemic drugs and dementia risk. OBJECTIVE: The goal of this case-control study was to analyze the association between the use of antihyperglycemic drugs and dementia risk in patients followed in general practices in Germany. METHODS: This study included patients with type 2 diabetes mellitus who had received a first dementia diagnosis in 972 general practices in Germany between January 2013 and December 2017 (index date). Controls without dementia were matched (1:1) to cases by age, gender, index year, and physician. Two multivariate regression models were used to study the association between the use of antihyperglycemic drugs and dementia risk. Model 1 included all antihyperglycemic drugs prescribed to patients regardless of the prescription duration, whereas Model 2 only included the longest therapy prescribed to each patient. RESULTS: There were 8,276 diabetes patients with dementia and 8,276 diabetes patients without dementia included in this study. In Model 1, glitazones were associated with a decreased dementia risk (odds ratio [OR] = 0.80), whereas insulin was associated with an increased risk of developing the condition (OR = 1.34). In Model 2, metformin, prescribed as monotherapy (OR = 0.71) or as dual therapy with sulfonylureas (OR = 0.90), was associated with a decrease in the likelihood of subsequently being diagnosed with dementia. By contrast, the combination of basal insulin and bolus insulin (OR = 1.47) and premix insulin (OR = 1.33) were risk factors for dementia. CONCLUSION: Metformin and glitazones were negatively associated with dementia, while insulin was positively associated with dementia.

The Association of Mid- and Late-Life Systemic Inflammation with Brain Amyloid Deposition: The ARIC-PET Study. - Walker, Keenan A; Windham, B Gwen; Brown, Charles H; Knopman, David S; Jack, Clifford R; Mosley, Thomas H; Selvin, Elizabeth; Wong, Dean F; Hughes, Timothy M; Zhou, Yun; Gross, Alden L; Gottesman, Rebecca F (J Alzheimers Dis, 2018)
BACKGROUND: Although inflammation has been implicated in the pathogenesis of Alzheimer's disease, the effects of systemic inflammation on brain amyloid deposition remain unclear. OBJECTIVE: We examined the association of midlife and late-life systemic inflammation with late-life brain amyloid levels in a community sample of non-demented older adults from the Atherosclerosis Risk in Communities (ARIC) - PET Study. METHODS: 339 non-demented participants (age: 75 [SD 5]) were recruited from the ARIC Study to undergo florbetapir PET (amyloid) imaging. Blood levels of high sensitivity C-reactive protein (CRP), a marker of systemic inflammation, were measured 22 years (Visit 2), 16 years (Visit 4), and up to 2 years before PET imaging (Visit 5). Elevated brain amyloid deposition (standardized uptake value ratio >1.2) was the primary outcome. RESULTS: Our primary analyses found no association of midlife and late-life CRP with late-life brain amyloid levels. However, in secondary stratified analyses, we found that higher midlife (Visit 2) CRP was associated with elevated amyloid among males (OR 1.65, 95% CI: 1.13-2.42), and among white (OR 1.33, 95% CI: 1.02-1.75), but not African American, participants (p-interactions<0.05). Among male participants, those who maintained high CRP levels (≥3 mg/L) throughout mid- and late-life were most likely to have elevated brain amyloid (OR, 8.81; 95% CI: 1.23, 62.91). CONCLUSIONS: Although our primary analysis does not support an association between systemic inflammation and brain amyloid deposition, we found evidence for sex- and race-dependent associations. However, findings from subgroup analyses should be interpreted with caution.

Atherosclerosis, Hypertension, and Diabetes in Alzheimer's Disease, Vascular Dementia, and Mixed Dementia: Prevalence and Presentation. - Javanshiri, Keivan; Waldö, Maria Landqvist; Friberg, Niklas; Sjövall, Fredrik; Wickerström, Karin; Haglund, Mattias; Englund, Elisabet (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is the most prevalent cause of dementia with vascular dementia (VaD) being second alongside with mixed AD and VaD, according to some. For some time, it has been proposed that cardiovascular disease (CaVD), hypertension, and diabetes mellitus (DM), which are known risk factors for VaD, also are associated with and contribute to the development of AD. OBJECTIVE: The aim of this study was to investigate the prevalence of these proposed general risk factors, and to document presence of CaVD as evidenced from clinical records or from autopsy findings, further to correlate these with the diagnoses AD, VaD and mixed AD-VaD (MD), respectively. METHODS: Autopsy reports at the Clinical Department of Pathology in Lund from 1992-2017 were analyzed. All cases with a complete autopsy report and a neuropathologically diagnosed dementia disorder (AD, VaD, or MD) were selected on the condition of a clinical diagnosis of dementia. Clinical data were retrieved through medical records and the Swedish National Diabetes Register (NDR). A total of 268 subjects were included. RESULTS: In AD, there was less CaVD as significantly less organ/tissue findings (p < 0.05), significantly less hypertension (p < 0.001), and likewise significantly less DM (p = 0.0014) than in VaD, with the MD group results being set between these two in all aspects studied. CONCLUSION: AD and VaD exhibit such different profiles of organ and vascular damage as well as of hypertension and DM that they clearly point toward different pathogenic origin with low likelihood of shared risk factors.

Blood Inflammatory Mediators and Cognitive Decline in Alzheimer's Disease: A Two Years Longitudinal Study. - Julian, Adrien; Rioux-Bilan, Agnès; Ragot, Stéphanie; Krolak-Salmon, Pierre; Berrut, Gilles; Dantoine, Thierry; Hommet, Caroline; Hanon, Olivier; Page, Guylène; Paccalin, Marc (J Alzheimers Dis, 2018)
Peripheral inflammatory processes are involved in Alzheimer's disease (AD). We aimed to determine whether plasma inflammatory mediator levels at diagnosis are associated with cognitive decline through a 2-year follow-up in AD patients. Patients (n = 109, mean age 79.44 (6.82) years) were included at diagnosis with MMSE scores between 16 and 25, with C-reactive protein <10 mg/L, and without any acute or chronic inflammation status. Plasma IL-1β, IL-6, TNF-α, and CCL5 were measured using Luminex X-MAP technology at baseline, and after one year and two years of follow-up. The mean values of IL-1β, IL-6, TNF-α, and CCL5 at diagnosis were 0.3, 1.94, 6.57, and 69,615.81 pg/mL, respectively. Mean cognitive decline in MMSE was 3.35 points. No correlation between plasmatic value of IL-1β, IL-6, TNF-α, or CCL5 at diagnosis and cognitive decline during the two years of follow-up was found. Cognitive decline in AD does not appear to be predictable by the tested inflammatory mediators.

Calpain I Activation Causes GLUT3 Proteolysis and Downregulation of O-GlcNAcylation in Alzheimer's Disease Brain. - Gu, Jianlan; Jin, Nana; Ma, Denglei; Chu, Dandan; Iqbal, Khalid; Gong, Cheng-Xin; Liu, Fei (J Alzheimers Dis, 2018)
Impairment of cerebral glucose uptake/metabolism in individuals with Alzheimer's disease (AD) is believed to lead to downregulation of protein O-GlcNAcylation, which contributes to tau pathogenesis through tau hyperphosphorylation. Level of glucose transporter 3 (GLUT3), a neuronal specific glucose transporter, is decreased in AD brain, which may contribute to impaired brain glucose uptake/metabolism. However, what causes the reduction of GLUT3 in AD brain is not fully understood. Here, we report 1) that decrease of GLUT3 is associated with the reduction of protein O-GlcNAcylation in AD brain, 2) that GLUT3 level is negatively correlated with calpain I activation in human brain, 3) that calpain I proteolyzes GLUT3 at the N-terminus in vitro, and 4) that activation of calpain I is negatively correlated with protein O-GlcNAcylation in AD brain. Furthermore, we found that overexpression of GLUT3 enhances protein O-GlcNAcylation in N2a cells. Overexpression of calpain I suppresses protein O-GlcNAcylation in these cells. These findings suggest a novel mechanism by which calpain I overactivation leads to GLUT3 degradation and the consequent down-regulation of protein O-GlcNAcylation in AD brain.

Cerebrospinal Fluid and Plasma Levels of Inflammation Differentially Relate to CNS Markers of Alzheimer's Disease Pathology and Neuronal Damage. - Bettcher, Brianne M; Johnson, Sterling C; Fitch, Ryan; Casaletto, Kaitlin B; Heffernan, Kate S; Asthana, Sanjay; Zetterberg, Henrik; Blennow, Kaj; Carlsson, Cynthia M; Neuhaus, John; Bendlin, Barbara B; Kramer, Joel H (J Alzheimers Dis, 2018)
Inflammatory markers have been shown to predict neurocognitive outcomes in aging adults; however, the degree to which peripheral markers mirror the central nervous system remains unknown. We investigated the association between plasma and cerebrospinal fluid (CSF) markers of inflammation, and explored whether these markers independently predict CSF indicators of Alzheimer's disease (AD) pathology or neuronal damage. Plasma and CSF samples were analyzed for inflammatory markers in a cohort of asymptomatic older adults (n = 173). CSF samples were analyzed for markers of AD pathology (Aβ42, phosphorylated tau [p-tau], sAβPPβ) or neuronal damage (total tau; neurofilament light chain) (n = 147). Separate linear models for each analyte were conducted with CSF and plasma levels entered simultaneously as predictors and markers of AD pathology or neuronal damage as outcome measures. Strong associations were noted between CSF and plasma MIP-1β levels, and modest associations were observed for remaining analytes. With respect to AD pathology, higher levels of plasma and CSF IL-8, CSF MIP-1β, and CSF IP-10 were associated with higher levels of p-tau. Higher levels of CSF IL-8 were associated with higher levels of CSF Aβ42. Higher CSF sAβPPβ levels were associated with higher plasma markers only (IL-8; MCP-1). In terms of neuronal injury, higher levels of plasma and CSF IL-8, CSF IP-10, and CSF MIP-1β were associated with higher levels of CSF total tau. Exploratory analyses indicated that CSF Aβ42 modifies the relationship between plasma inflammatory levels and CSF tau levels. Results suggest that both plasma and CSF inflammatory markers independently relay integral information about AD pathology and neuronal damage.

Characteristics of Cognitively Normal Mexican-Americans with Cognitive Complaints. - Hall, James R; Wiechmann, April; Johnson, Leigh A; Edwards, Melissa; O'Bryant, Sid E (J Alzheimers Dis, 2018)
BACKGROUND: Subjective cognitive complaints in cognitively normal adults have been linked to later cognitive decline and dementia. Research on the characteristics of this group has been conducted on a variety of clinical and community-based populations. The current study focuses on the rapidly expanding population of Mexican-American elders. OBJECTIVE: The objective of the study is the determination of characteristics of cognitively normal Mexican-Americans with cognitive complaints. METHODS: Data on 319 cognitively normal participants in a large-scale community-based study of elderly Mexican-Americans (HABLE) were analyzed comparing those with cognitive complaints with those without on clinical characteristics, affective status, neuropsychological functioning, and proteomic markers. RESULTS: Those expressing concern about cognitive decline scored lower on the MMSE, were more likely to have significantly more affective symptoms, higher levels of diabetic markers, poorer performance on attention and executive functioning, and a different pattern of inflammatory markers. CONCLUSION: Although longitudinal research is needed to determine the impact of these differences on later cognition, possible targets for early intervention with Mexican-Americans were identified.
Keywords: Aged; Biomarkers; Cognition; Cognitive Dysfunction; Executive Function; Female; Humans; Male; Mexican Americans; Middle Aged; Neuropsychological Tests; Risk Factors; Texas

Chronic Traumatic Encephalopathy and Neurodegeneration in Contact Sports and American Football. - Zuckerman, Scott L; Brett, Benjamin L; Jeckell, Aaron; Yengo-Kahn, Aaron M; Solomon, Gary S (J Alzheimers Dis, 2018)
Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease characterized by the presence of abnormally phosphorylated tau protein in the depths of one or more cortical sulci. Controversy over the risk of CTE and neurologic disorders later in life among contact sport athletes has taken hold in the public spotlight, most notably in American football. Players, parents, coaches, and legislators have taken action based on the commonly held notion that contact sports invariably lead to neurodegenerative disorders. However, to fully understand the science behind this assumed association, a critical appraisal of the evidence is warranted. With regards to CTE in sports, the objectives of the current report are to: 1) describe the history of CTE, 2) review current CTE definitions, 3) critically evaluate the empiric data, divided into all contact sports and exclusively American football, and 4) summarize notable themes for future research.

Circulating Progenitor Cells Correlate with Memory, Posterior Cortical Thickness, and Hippocampal Perfusion. - Nation, Daniel A; Tan, Alick; Dutt, Shubir; McIntosh, Elissa C; Yew, Belinda; Ho, Jean K; Blanken, Anna E; Jang, Jung Yun; Rodgers, Kathleen E; Gaubert, Aimée (J Alzheimers Dis, 2018)
BACKGROUND: Bone marrow-derived progenitor cells survey the vasculature and home to sites of tissue injury where they can promote repair and regeneration. It has been hypothesized that these cells may play a protective role neurodegenerative and vascular cognitive impairment. OBJECTIVE: To evaluate progenitor cell levels in older adults with and without mild cognitive impairment (MCI), and to relate circulating levels to memory, brain volume, white matter lesion volume, and cerebral perfusion. METHOD: Thirty-two older adults, free of stroke and cardiovascular disease, were recruited from the community and evaluated for diagnosis of MCI versus cognitively normal (CN). Participants underwent brain MRI and blood samples were taken to quantify progenitor reserve using flow cytometry (CD34+, CD34+CD133+, and CD34+CD133+CD309+ cells). RESULTS: Participants with MCI (n = 10) exhibited depletion of all CPC markers relative to those who were CN (n = 22), after controlling for age, sex, and education. Post-hoc age, sex, and education matched comparisons (n = 10 MCI, n = 10 CN) also revealed the same pattern of results. Depletion of CD34+ cells correlated with memory performance, left posterior cortical thickness, and bilateral hippocampal perfusion. Participants exhibited low levels of vascular risk and white matter lesion burden that did not correlate with progenitor levels. CONCLUSIONS: Circulating progenitor cells are associated with cognitive impairment, memory, cortical atrophy, and hippocampal perfusion. We hypothesize that progenitor depletion contributes to, or is triggered by, cognitive decline and cortical atrophy. Further study of progenitor cell depletion in older adults may benefit efforts to prevent or delay dementia.
Keywords: Aged; Aged, 80 and over; Antigens, CD; Apolipoproteins E; Cerebral Cortex; Cognitive Dysfunction; Female; Flow Cytometry; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Perfusion; Stem Cells; White Matter

Cognitive Variability Predicts Incident Alzheimer's Disease and Mild Cognitive Impairment Comparable to a Cerebrospinal Fluid Biomarker. - Gleason, Carey E; Norton, Derek; Anderson, Eric D; Wahoske, Michelle; Washington, Danielle T; Umucu, Emre; Koscik, Rebecca L; Dowling, N Maritza; Johnson, Sterling C; Carlsson, Cynthia M; Asthana, Sanjay (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) biomarkers are emerging as critically important for disease detection and monitoring. Most biomarkers are obtained through invasive, resource-intense procedures. A cognitive marker, intra-individual cognitive variability (IICV) may provide an alternative or adjunct marker of disease risk for individuals unable or disinclined to undergo lumbar puncture. OBJECTIVE: To contrast risk of incident AD and mild cognitive impairment (MCI) associated with IICV to risk associated with well-established biomarkers: cerebrospinal fluid (CSF) phosphorylated tau protein (p-tau181) and amyloid-β 42 (Aβ42) peptide. METHODS: Dispersion in cognitive performance, IICV, was estimated with a published algorithm, and included Trail Making Test A and B, Rey Auditory Verbal Learning Test (RAVLT), and the American National Adult Reading Test (ANART). CSF biomarkers were expressed as a ratio: p-tau181/Aβ42, wherein high values signified pathognomonic profiles. Logistic regression models included longitudinal data from 349 Alzheimer's Disease Neuroimaging Initiative (ADNI) participants who completed lumbar puncture. All subjects were cognitively healthy (n = 105) or diagnosed with MCI (n = 244) at baseline. We examined odds of conversion associated with baseline elevations in IICV and/or ratio of CSF p-tau181/Aβ42. RESULTS: When included in models alone or in combination with CSF p-tau181/Aβ42, one standard IICV unit higher was associated with an estimated odds ratio for incident AD or MCI of 2.81 (95% CI: 1.83-4.33) in the most inclusive sample, and an odds ratio of 3.41 (95% CI: 2.03-5.73) when restricted to participants with MCI. Iterative analyses suggested that IICV independently improved model fit even when individual index components were included in comparative models. CONCLUSIONS: These analyses provide preliminary support for IICV as a marker of incident AD and MCI. This easily-disseminated, non-invasive marker compared favorably to well-established CSF biomarkers.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Incidence; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Statistics, Nonparametric; tau Proteins

Correlates of Subjective Cognitive Decline in Lesbian, Gay, Bisexual, and Transgender Older Adults. - Flatt, Jason D; Johnson, Julene K; Karpiak, Stephen E; Seidel, Liz; Larson, Britta; Brennan-Ing, Mark (J Alzheimers Dis, 2018)
BACKGROUND: Little is known about subjective cognitive decline (SCD) in lesbian, gay, bisexual, and transgender (LGBT) older adults. OBJECTIVES: To examine SCD and its association with dementia risk factors, other physical and psychosocial health factors in LGBT older adults. METHODS: A cross-sectional study of SCD was conducted with LGBT older adults, aged 50 and older (n = 210). SCD was categorized based on endorsement of memory problems and one other cognitive domain. Hierarchical logistic regression examined the associations between demographic factors, dementia risk factors, other health and psychosocial factors, and SCD. RESULTS: Nearly 25% of LGBT older adults were classified as having SCD. LGBT older adults who were people of color (OR = 2.5; 95% CI = 1.1- 7.8), depressed (OR = 2.9; 95% CI = 1.3- 6.9), or reported having functional impairment (OR = 2.6; 95% CI = 1.1- 6.5) were significantly more likely to be classified as having SCD (Nagelkerke pseudo R2 = 0.27). CONCLUSION: Depression and functional impairment should be considered when screening LGBT older adults for cognitive impairment and dementia. Future research on the cognitive impairment and dementia risk in LGBT older adults is needed.

Crosstalk between Peripheral Small Vessel Properties and Anxious-like Profiles: Sex, Genotype, and Interaction Effects in Mice with Normal Aging and 3×Tg-AD mice at Advanced Stages of Disease. - Jiménez-Altayó, Francesc; Sánchez-Ventura, Judith; Vila, Elisabet; Giménez-Llort, Lydia (J Alzheimers Dis, 2018)
Cardiovascular disease resulting from oxidative stress and inflammation can exacerbate Alzheimer's disease. This brief report provides the first evidence of compromised small peripheral mesenteric resistance artery (MRA) properties in 15-month-old 3xTg-AD mice. Females showed worse physiologically relevant MRA structural (increased passive external and internal diameters, cross sectional area) and functional (increased active internal diameters) alterations suggesting sex-dependent dysfunctions. At both physiological and high intraluminal pressures, vascular alterations correlated with the anxious-like behavioral profile, in a sex-dependent manner. Finally, the results unveil a crosstalk between peripheral small vessel properties and behavior in both 3xTg-AD mice and age-matched counterparts with normal aging.

Decreased Prefrontal Activation during Matrix Reasoning in Predementia Progranulin Mutation Carriers. - Alexander, Courtney; Zeithamova, Dagmar; Hsiung, Ging-Yuek R; Mackenzie, Ian R; Jacova, Claudia (J Alzheimers Dis, 2018)
We tested the potential of task-based functional neuroimaging as a biomarker of emerging prefrontal brain changes in progranulin (GRN) mutations carriers. Five GRN mutation carriers free of frontotemporal dementia (FTD) and 11 non-carriers from families with FTD-GRN underwent functional MRI while solving matrix-reasoning problems. Mutation carriers displayed slower responses for more difficult problems and lower lateral prefrontal activation across all problems. Overall task-evoked posterior ventrolateral prefrontal activation predicted mutation status with 100% sensitivity and 91% specificity. Volumetric differences did not account for activation differences. Prefrontal activation may have utility as a biomarker in GRN mutation.
Keywords: Adult; Biomarkers; Female; Frontotemporal Dementia; Functional Neuroimaging; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Prefrontal Cortex; Progranulins

Delirium Severity Post-Surgery and its Relationship with Long-Term Cognitive Decline in a Cohort of Patients without Dementia. - Vasunilashorn, Sarinnapha M; Fong, Tamara G; Albuquerque, Asha; Marcantonio, Edward R; Schmitt, Eva M; Tommet, Douglas; Gou, Yun; Travison, Thomas G; Jones, Richard N; Inouye, Sharon K (J Alzheimers Dis, 2018)
BACKGROUND: Delirium has been associated with more rapid cognitive decline. However, it is unknown whether increased delirium severity is associated with a higher rate of long-term cognitive decline. OBJECTIVE: To evaluate delirium severity and the presence and rate of cognitive decline over 36 months following surgery. METHODS: We examined patients from the Successful Aging after Elective Surgery Study, who were age ≥70 years undergoing major elective surgery (N = 560). Delirium severity was determined by the peak Confusion Assessment Method-Severity (CAM-S) score for each patient's hospitalization and grouped based on the sample distribution: scores of 0-2, 3-7, and 8-19. A neuropsychological composite, General Cognitive Performance (GCP), and proxy-reported Informant Questionnaire for Cognitive Decline (IQCODE) were used to examine cognitive outcomes following surgery at 0, 1, and 2 months, and then every 6 months for up to 3 years. RESULTS: No significant cognitive decline was observed for patients with peak CAM-S scores 0-2 (-0.17 GCP units/year, 95% confidence interval [CI] -0.35, 0.01). GCP scores decreased significantly in the group with peak CAM-S scores 3-7 (-0.30 GCP units/year, 95% CI -0.51, -0.09), and decreased almost three times faster in the highest delirium severity group (peak CAM-S scores 8-19; -0.82 GCP units/year, 95% CI -1.28, -0.37). A similar association was found for delirium severity and the proportion of patients who developed IQCODE impairment over time. CONCLUSION: Patients with the highest delirium severity experienced the greatest rate of cognitive decline, which exceeds the rate previously observed for patients with dementia, on serial neuropsychological testing administered over 3 years, with a dose-response relationship between delirium severity and long-term cognitive decline.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Delirium; Elective Surgical Procedures; Female; Humans; Male; Neuropsychological Tests; Postoperative Complications; Severity of Illness Index

Designing an Internet-Based Multidomain Intervention for the Prevention of Cardiovascular Disease and Cognitive Impairment in Older Adults: The HATICE Trial. - Barbera, Mariagnese; Mangialasche, Francesca; Jongstra, Susan; Guillemont, Juliette; Ngandu, Tiia; Beishuizen, Cathrien; Coley, Nicola; Brayne, Carol; Andrieu, Sandrine; Richard, Edo; Soininen, Hilkka; Kivipelto, Miia (J Alzheimers Dis, 2018)
BACKGROUND: Many dementia and cardiovascular disease (CVD) cases in older adults are attributable to modifiable vascular and lifestyle-related risk factors, providing opportunities for prevention. In the Healthy Aging Through Internet Counselling in the Elderly (HATICE) randomized controlled trial, an internet-based multidomain intervention is being tested to improve the cardiovascular risk (CVR) profile of older adults. OBJECTIVE: To design a multidomain intervention to improve CVR, based on the guidelines for CVR management, and administered through a coach-supported, interactive, platform to over 2500 community-dwellers aged 65+ in three European countries. METHODS: A comparative analysis of national and European guidelines for primary and secondary CVD prevention was performed. Results were used to define the content of the intervention. RESULTS: The intervention design focused on promoting awareness and self-management of hypertension, dyslipidemia, diabetes mellitus, and overweight, and supporting smoking cessation, physical activity, and healthy diet. Overall, available guidelines lacked specific recommendations for CVR management in older adults. The comparative analysis of the guidelines showed general consistency for lifestyle-related recommendations. Key differences, identified mostly in methods used to assess the overall CVR, did not hamper the intervention design. Minor country-specific adaptations were implemented to maximize the intervention feasibility in each country. CONCLUSION: Despite differences in CVR management within the countries considered, it was possible to design and implement the HATICE multidomain intervention. The study can help define preventative strategies for dementia and CVD that are applicable internationally.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cognitive Dysfunction; Counseling; Europe; Exercise; Female; Healthy Aging; Humans; Internet; Life Style; Male; Practice Guidelines as Topic; Risk Factors; Telemedicine

Diagnostic Value of Diffusion Tensor Imaging and Positron Emission Tomography in Early Stages of Frontotemporal Dementia. - Krämer, Julia; Lueg, Gero; Schiffler, Patrick; Vrachimis, Alexis; Weckesser, Matthias; Wenning, Christian; Pawlowski, Matthias; Johnen, Andreas; Teuber, Anja; Wersching, Heike; Meuth, Sven G; Duning, Thomas (J Alzheimers Dis, 2018)
BACKGROUND: Due to suboptimal sensitivity and specificity of structural and molecular neuroimaging tools, the diagnosis of behavioral variant frontotemporal dementia (bvFTD) remains challenging. OBJECTIVE: Investigation of the sensitivity of diffusion tensor imaging (DTI) and fluorodeoxyglucose positron emission tomography (FDG-PET) to detect cerebral alterations in early stages of bvFTD despite inconspicuous conventional MRI. METHODS: Thirty patients with early stages of bvFTD underwent a detailed neuropsychological examination, cerebral 3T MRI with DTI analysis, and FDG-PET. After 12 months of follow-up, all patients finally fulfilled the diagnosis of bvFTD. Individual FDG-PET data analyses showed that 20 patients exhibited a "typical" pattern for bvFTD with bifrontal and/or temporal hypometabolism (bvFTD/PET+), and that 10 patients showed a "non-typical"/normal pattern (bvFTD/PET-). DTI data were compared with 42 healthy controls in an individual and voxel-based group analysis. To examine the clinical relevance of the findings, associations between pathologically altered voxels of DTI or FDG-PET results and behavioral symptoms were estimated by linear regression analyses. RESULTS: DTI voxel-based group analyses revealed microstructural degeneration in bifrontal and bitemporal areas in bvFTD/PET+ and bvFTD/PET- groups. However, when comparing the sensitivity of individual DTI data analysis with FDG-PET, DTI appeared to be less sensitive. Neuropsychological symptoms were considerably related to neurodegeneration within frontotemporal areas identified by DTI and FDG-PET. CONCLUSION: DTI seems to be an interesting tool for detection of functionally relevant neurodegenerative alterations in early stages of bvFTD, even in bvFTD/PET- patients. However, at a single subject level, it seems to be less sensitive than FDG-PET. Thus, improvement of individual DTI analysis is necessary.

Differences Between Women and Men in Incidence Rates of Dementia and Alzheimer's Disease. - Beam, Christopher R; Kaneshiro, Cody; Jang, Jung Yun; Reynolds, Chandra A; Pedersen, Nancy L; Gatz, Margaret (J Alzheimers Dis, 2018)
In the following brief report, we examined gender differences in incidence rates of any dementia, Alzheimer's disease (AD) alone, and non-Alzheimer's dementia alone in 16,926 women and men in the Swedish Twin Registry aged 65+. Dementia diagnoses were based on clinical workup and national health registry linkage. Incidence rates of any dementia and AD were greater in women than men, with any dementia rates diverging after age 85 and AD rates diverging around 80. This pattern is consistent with women's survival to older ages compared to men. These findings are similar to incidence rates reported in other Swedish samples.

Diffuse Amyloid-β Plaques, Neurofibrillary Tangles, and the Impact of APOE in Elderly Persons' Brains Lacking Neuritic Amyloid Plaques. - Abner, Erin L; Neltner, Janna H; Jicha, Gregory A; Patel, Ela; Anderson, Sonya L; Wilcock, Donna M; Van Eldik, Linda J; Nelson, Peter T (J Alzheimers Dis, 2018)
Data from a large autopsy series were analyzed to address questions pertinent to primary age-related tauopathy (PART) and Alzheimer's disease (AD): what factors are associated with increased severity of neurofibrillary degeneration in brains that lack neuritic amyloid plaques?; is there an association between Apolipoprotein E (APOE) alleles and PART pathologic severity independent of amyloid-β (Aβ) deposits?; and, how do the stains used to detect plaques and tangles impact the experimental results? Neuropathologic data were evaluated from elderly research volunteers whose brain autopsies were performed at University of Kentucky Alzheimer's Disease Center (UK-ADC; N = 145 subjects). All of the included subjects' brains lacked neuritic amyloid plaques according to the CERAD diagnostic criteria and the average final MMSE score before death was 26.8±4.6 stdev. The study incorporated evaluation of tissue with both silver histochemical stains and immunohistochemical stains to compare results; the immunohistochemical stains (Aβ and phospho-tau) were scanned and quantified using digital pathologic methods. Immunohistochemical stains provided important advantages over histochemical stains due to sensitivity and detectability via digital methods. When AD-type pathology was in its presumed earliest phases, neocortical parenchymal Aβ deposits were associated with increased medial temporal lobe neurofibrillary tangles. The observation supports the NIA-AA consensus recommendation for neuropathologic diagnoses, because even these "diffuse" Aβ deposits signal that AD pathobiologic mechanisms are occurring. Further, the data were most compatible with the hypothesis that the APOEɛ4 allele exerts its effect(s) via driving Aβ deposition, i.e., an "upstream" influence, rather than being associated directly with Aβ- independent PART pathology.

Diosgenin Attenuates Lipopolysaccharide-Induced Parkinson's Disease by Inhibiting the TLR/NF-κB Pathway. - Li, Bingyu; Xu, Pengli; Wu, Shuyan; Jiang, Zhixian; Huang, Zhijian; Li, Qian; Chen, Danhong (J Alzheimers Dis, 2018)
BACKGROUND: Parkinson's disease (PD) is a neurodegenerative disease characterized by loss of dopaminergic neurons in the substantia nigra. Diosgenin is a natural steroid saponin which was shown to play a beneficial role in Alzheimer's disease. OBJECTIVE: This study sought to investigate the potential effect of diosgenin on a rat model of PD. METHODS: Sprague Dawley rats were subjected to intra-striatal injection of lipopolysaccharide (LPS) and treated with diosgenin. Stepping, Whisker, and Cylinder tests were carried out to determine the motor function, and the expression of tyrosine hydroxylase was detected by immunohistochemistry. The levels of multiple proinflammatory cytokines, oxidative stress related factors and proteins involved in Toll-like receptor (TLR)/nuclear factor kappa B (NF-κB) pathway were measured. The synergistic effect of environment enrichment on diosgenin was also investigated. RESULTS: Intra-striatal injection of LPS caused motor deficits in rats, induced inflammatory response and oxidative stress response, and activated the TLR/NF-κB pathway both in vivo and in vitro. Diosgenin could attenuate the LPS-induced alterations. Enriched environment enhanced the effect of diosgenin to ameliorate the LPS-induced motor deficits in rats and decreased the protein levels of TLR2, TLR4, and nuclear NF-κB in diosgenin treated PD rats. CONCLUSION: Diosgenin had a beneficial effect in LPS-induced rat PD models, by suppressing the TLR/NF-κB signaling pathway. Environmental enrichment could play a synergistic effect with diosgenin, by enhancing the inhibitory effect of diosgenin on the TLR/ NF-κB signaling pathway.

Distinct White Matter Changes Associated with Cerebrospinal Fluid Amyloid-β1-42 and Hypertension. - Al-Janabi, Omar M; Brown, Christopher A; Bahrani, Ahmed A; Abner, Erin L; Barber, Justin M; Gold, Brian T; Goldstein, Larry B; Murphy, Ronan R; Nelson, Peter T; Johnson, Nathan F; Shaw, Leslie M; Smith, Charles D; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) pathology and hypertension (HTN) are risk factors for development of white matter (WM) alterations and might be independently associated with these alterations in older adults. OBJECTIVE: To evaluate the independent and synergistic effects of HTN and AD pathology on WM alterations. METHODS: Clinical measures of cerebrovascular disease risk were collected from 62 participants in University of Kentucky Alzheimer's Disease Center studies who also had cerebrospinal fluid (CSF) sampling and MRI brain scans. CSF Aβ1-42 levels were measured as a marker of AD, and fluid-attenuated inversion recovery imaging and diffusion tensor imaging were obtained to assess WM macro- and microstructural properties. Linear regression analyses were used to assess the relationships among WM alterations, cerebrovascular disease risk, and AD pathology. Voxelwise analyses were performed to examine spatial patterns of WM alteration associated with each pathology. RESULTS: HTN and CSF Aβ1-42 levels were each associated with white matter hyperintensities (WMH). Also, CSF Aβ1-42 levels were associated with alterations in normal appearing white matter fractional anisotropy (NAWM-FA), whereas HTN was marginally associated with alterations in NAWM-FA. Linear regression analyses demonstrated significant main effects of HTN and CSF Aβ1-42 on WMH volume, but no significant HTN×CSF Aβ1-42 interaction. Furthermore, voxelwise analyses showed unique patterns of WM alteration associated with hypertension and CSF Aβ1-42. CONCLUSION: Associations of HTN and lower CSF Aβ1-42 with WM alteration were statistically and spatially distinct, suggesting independent rather than synergistic effects. Considering such spatial distributions may improve diagnostic accuracy to address each underlying pathology.

The Distribution of Urinary Alzheimer-Associated Neuronal Thread Protein and Its Association with Common Chronic Diseases in the General Population. - Jin, He; Guan, Shaochen; Wang, Rong; Fang, Xianghua; Liu, Hongjun; Wu, Yanchuan; Zhang, Yanlei; Liu, Chunxiao (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer-associated neuronal thread protein (AD7c-NTP) has been found to be a biomarker for Alzheimer's disease (AD). OBJECTIVE: The aim of the present study was to investigate the distribution of Alzheimer-associated neuronal thread protein and its relationship to common chronic diseases in the general population. METHODS: Urine samples of 1,805 participants were collected from four districts (Xi Cheng, Fang Shan, Tong Zhou, and Yan Qing) in Beijing. The assessment in this study included a questionnaire that captured participants' demographic information, use of medication and histories of disease, neurological examinations, psychometric evaluations, physical and clinical examinations, and laboratory tests. RESULTS: Urine AD7c-NTP level was increased among the population over 60 years old and females exhibited higher levels than males. These results controlled for other demographic factors such as education levels, employment status, body mass index and current residence. The urine AD7c-NTP levels exhibited no association with non-neurological diseases (0.3346±0.4482 ng/ml), such as hypertension (0.3445±0.4187), stroke (0.3652±0.4010), diabetes (0.3319±0.4371), dyslipidemia (0.3440±0.4314), renal insufficiency (0.3223±0.3909), cancer (0.5055±1.0006), chronic lung disease (0.2911±0.2852), chronic liver disease (0.5579±0.6726), severe depression symptoms (0.5186±0.7040), and mild depression symptoms (0.3669±0.3811). CONCLUSIONS: Cut-off values for urine AD7c-NTP levels for different age groups and genders should be established. AD7c-NTP levels proved relatively stable in the body and were not impacted by demographic factors or common chronic diseases.

DNA Hypomethylation in Blood Links B3GALT4 and ZADH2 to Alzheimer's Disease. - Madrid, Andy; Hogan, Kirk J; Papale, Ligia A; Clark, Lindsay R; Asthana, Sanjay; Johnson, Sterling C; Alisch, Reid S (J Alzheimers Dis, 2018)
Differentially methylated positions (DMPs) between persons with and without late-onset Alzheimer's disease (LOAD) were observed at 477 of 769,190 loci in a plurality of genes. Of these, 17 were shared with DMPs identified using clinical LOAD markers analyzed independently as continuous variables comprising Rey Auditory Verbal Learning Test scores, cerebrospinal fluid total tau (t-tau) and phosphorylated tau 181 (p-tau181) levels, and t-tau/Aβ1-42 (Aβ42), p-tau181/Aβ42, and Aβ42/Aβ1-40 (Aβ40) ratios. In patients with LOAD, 12 of the shared 17 DMPs were hypomethylated in B3GALT4 (Beta-1,3-galatcosyltransferase 4) (EC 2.4.1.62), and 5 were hypomethylated in ZADH2 (Prostaglandin reductase 3) (EC 1.3.1.48).

Dual Time-Point [18F]Florbetaben PET Delivers Dual Biomarker Information in Mild Cognitive Impairment and Alzheimer's Disease. - Florek, Lisa; Tiepolt, Solveig; Schroeter, Matthias L; Berrouschot, Jörg; Saur, Dorothee; Hesse, Swen; Jochimsen, Thies; Luthardt, Julia; Sattler, Bernhard; Patt, Marianne; Hoffmann, Karl-Titus; Villringer, Arno; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Current research diagnostic criteria for Alzheimer's disease (AD) and mild cognitive impairment (MCI) due to AD include biomarkers to supplement clinical testing. Recently, we demonstrated that dual time-point [18F]FBB PET is able to deliver both blood flow and amyloid-β (Aβ) load surrogates. OBJECTIVE: The aim of this study was to investigate whether these surrogates can be utilized as AD biomarkers. METHODS: 112 subjects (41 with MCI, 50 with probable/possible AD, 21 with other dementias) underwent dual time-point [18F]FBB PET. Data were visually and relative quantitatively (Herholz scores for the early and composite SUVRs for the late PET data) analyzed. RESULTS: In the early images AD-typical patterns were present in 42% /27% /33% of probable/possible AD/MCI/other dementia cases. In late [18F]FBB PET, 42% /29% /38% of probable/possible AD/ MCI/other dementia cases were Aβ-positive. 17% of the MCIs were categorized as "MCI due to AD-high likelihood", 44% of the probable ADs as "probable AD with high evidence of AD pathophysiological process" and 28% of the possible ADs as "possible AD with evidence of AD pathophysiological process". 27% of all subjects showed a positive diagnostic and progression biomarker. Herholz scores were lower (0.85±0.05 versus 0.88±0.04, p = 0.015) for probable/possible AD versus MCI. Composite late phase SUVRs were significantly higher (1.65±0.23 versus 1.15±0.17, p < 0.005) in Aβ-positive versus Aβ-negative patients. Herholz and MMSE scores were positively correlated (R = 0.30 p = 0.006). CONCLUSION: Dual time-point [18F]FBB PET provides dual biomarker information which enables to categorize MCI and AD dementia patients according to established diagnostic criteria. Thus, dual time-point [18F]FBB PET has great potential to supplement diagnostic dementia workups.

Early Emotional Attention is Impacted in Alzheimer's Disease: An Eye-Tracking Study. - Bourgin, Jessica; Guyader, Nathalie; Chauvin, Alan; Juphard, Alexandra; Sauvée, Mathilde; Moreaud, Olivier; Silvert, Laetitia; Hot, Pascal (J Alzheimers Dis, 2018)
Emotional deficits have been repetitively reported in Alzheimer's disease (AD) without clearly identifying how emotional processing is impaired in this pathology. This paper describes an investigation of early emotional processing, as measured by the effects of emotional visual stimuli on a saccadic task involving both pro (PS) and anti (AS) saccades. Sixteen patients with AD and 25 age-matched healthy controls were eye-tracked while they had to quickly move their gaze toward a positive, negative, or neutral image presented on a computer screen (in the PS condition) or away from the image (in the AS condition). The age-matched controls made more AS mistakes for negative stimuli than for other stimuli, and triggered PSs toward negative stimuli more quickly than toward other stimuli. In contrast, patients with AD showed no difference with regard to the emotional category in any of the tasks. The present study is the first to highlight a lack of early emotional attention in patients with AD. These results should be taken into account in the care provided to patients with AD, since this early impairment might seriously degrade their overall emotional functioning.

Early Impairments of Hippocampal Neurogenesis in 5xFAD Mouse Model of Alzheimer's Disease Are Associated with Altered Expression of SOXB Transcription Factors. - Zaletel, Ivan; Schwirtlich, Marija; Perović, Milka; Jovanović, Mirna; Stevanović, Milena; Kanazir, Selma; Puškaš, Nela (J Alzheimers Dis, 2018)
Dysregulation of neurogenesis in the subgranular zone (SGZ) of the hippocampal dentate gyrus has been related to cognitive deficits and memory loss in neurodegenerative diseases, such as Alzheimer's disease (AD). Members of the B group of SOX transcription factors play critical roles in regulating neurogenesis in the embryonic and adult nervous system, including maintaining the multipotency, renewal, and cell fate decision of neural stem/progenitor cells. The aim of the present study was to evaluate the expression patterns of selected SOXB proteins in the SGZ, of 8-week-old male and female 5xFAD mice, which represent a transgenic model of AD with a severe and very early development of amyloid pathology. Immunohistochemical analysis showed a significant decrease in the number of cells expressing SOX1, SOX2, and SOX21 transcription factors within the SGZ of 5xFAD mice in comparison to their non-transgenic counterparts which coincidences with reduced number of doublecortin immunoreactive immature neurons found in Tg males. Despite observed changes in expressional pattern of examined SOXB proteins, the proliferative capacity evaluated by the number of Ki-67 immunoreactive cells remained unaffected in transgenic mice of both genders. Based on our results, we suggest that SOXB proteins might be considered as new biomarkers for the detection of early impairments in adult neurogenesis in different animal models or/and new targets in human regenerative medicine.

EEG Theta Power Is an Early Marker of Cognitive Decline in Dementia due to Alzheimer's Disease. - Musaeus, Christian Sandøe; Engedal, Knut; Høgh, Peter; Jelic, Vesna; Mørup, Morten; Naik, Mala; Oeksengaard, Anne-Rita; Snaedal, Jon; Wahlund, Lars-Olof; Waldemar, Gunhild; Andersen, Birgitte Bo (J Alzheimers Dis, 2018)
BACKGROUND: Quantitative EEG (qEEG) power could potentially be used as a diagnostic tool for Alzheimer's disease (AD) and may further our understanding of the pathophysiology. However, the early qEEG power changes of AD are not well understood. OBJECTIVE: To investigate the early changes in qEEG power and the possible correlation with memory function and cerebrospinal fluid biomarkers. In addition, whether qEEG power could discriminate between AD, mild cognitive impairment (MCI), and older healthy controls (HC) at the individual level. METHODS: Standard EEGs from 138 HC, 117 MCI, and 117 AD patients were included from six Nordic memory clinics. All EEGs were recorded consecutively before the diagnosis and were not used for the consensus diagnosis. Absolute and relative power was calculated for both eyes closed and open condition. RESULTS: At group level using relative power, we found significant increases globally in the theta band and decreases in high frequency power in the temporal regions for eyes closed for AD and, to a lesser extent, for MCI compared to HC. Relative theta power was significantly correlated with multiple neuropsychological measures and had the largest correlation coefficient with total tau. At the individual level, the classification rate for AD and HC was 72.9% for relative power with eyes closed. CONCLUSION: Our findings suggest that the increase in relative theta power may be the first change in patients with dementia due to AD. At the individual level, we found a moderate classification rate for AD and HC when using EEGs alone.

The Effect of Chronic Cerebral Hypoperfusion on Amyloid-β Metabolism in a Transgenic Mouse Model of Alzheimer's Disease (PS1V97L). - Yang, Heyun; Hou, Tingting; Wang, Wei; Luo, Yumin; Yan, Feng; Jia, Jianping (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) and cerebrovascular disease often coexist. However, it is difficult to determine how chronic cerebral hypoperfusion affects the metabolism of amyloid-β peptides (Aβ) in a living patient with AD. Thus, we developed an animal model of this condition, using transgenic mice (PS1V97L) and right common carotid artery ligation to create chronic cerebral hypoperfusion. The metabolic processes associated with amyloid-β peptide (Aβ) were observed and evaluated in this PS1V97L plus hypoperfusion model. Compared with control mice, the model revealed significantly upregulated expression of Aβ (including Aβ oligomers), with decreased α-secretase activity and expression and increased β-secretase activity and expression. Furthermore, the model revealed increased mRNA and protein expression of the receptor for advanced glycation end products (RAGE) and decreased mRNA and protein expression of low-density lipoprotein receptor-related protein 1 (LRP-1); both these are Aβ transporters. Moreover, the model revealed decreased activity and expression of neprilysin, which is a peripheral Aβ degrading enzyme. These findings suggest that hypoperfusion may magnify the effect of AD on Aβ metabolism by aggravating its abnormal production, transport, and clearance.

Effect of Cilostazol on Incident Dementia in Elderly Men and Women with Ischemic Heart Disease. - Kim, Mi-Young; Noh, Yoojin; Son, Sang Joon; Shin, Sooyoung; Paik, Hee-Young; Lee, Sukhyang; Jung, Yi-Sook (J Alzheimers Dis, 2018)
BACKGROUND: Ischemic heart disease (IHD) is associated with cognitive decline and may contribute to an increased risk of dementia. OBJECTIVE: The goal of the present study was to investigate whether cilostazol use is associated with a lower risk of incident dementia in Asian patients with IHD, and whether these effects differed based on sex. METHODS: This retrospective cohort study was performed using the Korean National Insurance Claim Data of the Health Insurance Review and Assessment Service; the duration of the study was from January 1, 2007 to December 31, 2015. The study group comprised 66,225 patients with IHD, aged >65 years, who had received cilostazol. Age- and sex-matched IHD patients without cilostazol exposure were selected as the control group. The risk of dementia was compared between the cilostazol and control groups. RESULTS: Compared to the control group, total cilostazol users had a marginally significant lower risk of incident dementia. After stratification by sex, the reducing effect of cilostazol on incident dementia was significant in female participants, but not in male participants. Female patients who had cilostazol for over 2 years showed a clinically meaningful preventive effect (HR, 0.85; 95% CI, 0.82-0.88). CONCLUSIONS: This study suggested that cilostazol treatment may reduce the risk of incident dementia in Korean patients with IHD. Its beneficial effect was remarkably significant in female patients who received cilostazol for over a 2-year period.

Effect of Physical Activity on the Progression of Alzheimer's Disease: The Clinical Research Center for Dementia of South Korea Study. - Minn, Yang-Ki; Choi, Seong Hye; Suh, Young Ju; Jeong, Jee Hyang; Kim, Eun-Joo; Kim, Jong Hun; Park, Kyung Won; Park, Moon Ho; Youn, Young Chul; Yoon, Bora; Choi, Seok-Jin; Oh, Youn Kyung; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is a lack of research on the effects of physical activity (PA) on the progression of Alzheimer's disease (AD). OBJECTIVES: We investigated whether PA is associated with progression of dementia and mortality in AD. METHODS: In the present study, 934 patients with mild-to-moderate AD were included. PA was evaluated using a questionnaire written by the caregiver. The outcome measures were the Clinical Dementia Rating-Sum of Boxes (CDR-SB), Seoul-Instrumental Activities of Daily Living (S-IADL), Caregiver-Administered Neuropsychiatric Inventory (CGA-NPI), a global composite score of neuropsychological subtests, and mortality. They were evaluated annually and received a maximum of three follow-up examinations. RESULTS: Between-group differences compared with the no PA group in the change of CDR-SB scores were -0.431 (95% CI = -0.824∼-0.039; p = 0.031) for the moderate PA group (150-750 minutes per week of moderate intensity PA), and -1.148 (-1.656∼-0.639; p < 0.001) for the high PA group (>750 minutes per week). As PA increased, there was a significant trend to slow the rate of increase in the CDR-SB, S-IADL, and CGA-NPI scores. The patients with ≥150 minutes per week for each of non-recreational and recreational PAs had a lower risk of mortality compared to those with <150 minutes per week for each of the PAs (hazard ratio 0.22, 95% CI = 0.05∼0.88; p = 0.033). CONCLUSION: More PA is associated with slower progression of dementia severity, functional decline, and abnormal behavior, and with a lower risk of mortality in AD.

Effectiveness of Anti-Dementia Drugs in Extremely Severe Alzheimer's Disease: A 12-Week, Multicenter, Randomized, Single-Blind Study. - Hong, Yun Jeong; Choi, Seong Hye; Jeong, Jee Hyang; Park, Kyung Won; Na, Hae Ri (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: There is insufficient evidence to guide decisions concerning how long anti-dementia drug (ADD) regimens should be maintained in severe Alzheimer's disease (AD). We investigated whether patients with extremely severe AD who were already receiving donepezil or memantine benefited from continuing treatment. METHODS: In this randomized and rater-blinded trial, 65 AD patients with a Mini-Mental State Examination score from 0 to 5 and a score of 6c or worse on Functional Assessment Staging were randomly assigned to an ADD-continuation group (N = 30) or an ADD-discontinuation group (N = 35). The current use of donepezil or memantine was maintained for 12 weeks in the ADD-continuation group and was discontinued after baseline in the ADD-discontinuation group. Efficacy measures were obtained at baseline and 12 weeks. The primary efficacy variable was the change from baseline to the end of the study in Baylor Profound Mental State Examination (BPMSE) scores. RESULTS: The change in the BPMSE from baseline to the end of the study in the ADD-continuation group (a 0.4-point improvement) was not equivalent to that in the ADD-discontinuation group (a 0.5-point decline), as determined by two one-sided tests of equivalence. Study withdrawals due to adverse events (11.4% versus 6.7%) were more frequent in the ADD-discontinuation group than in the ADD-continuation group. CONCLUSION: Continued treatment with donepezil or memantine seems unequal and might be superior to withdrawal of the drugs in terms of the effects on global cognition in patients with extremely severe AD. Current Controlled Trials number: KCT0000874 (CRIS).

The Effectiveness of Psychosocial and Behavioral Interventions for Informal Dementia Caregivers: Meta-Analyses and Meta-Regressions. - Jütten, Linda Helena; Mark, Ruth Elaine; Wicherts, Jelte Michiel; Sitskoorn, Margriet Maria (J Alzheimers Dis, 2018)
BACKGROUND: Many psychosocial and behavioral interventions have been developed for informal dementia caregivers. Because existing meta-analyses only focused on a limited number of interventions and outcomes, how effective these interventions are overall and which interventions components are associated with larger effects has yet to be explored. OBJECTIVE: To provide a comprehensive meta-analysis of the effectiveness of psychosocial and behavioral interventions on burden, depression, anxiety, quality of life, stress, and sense of competence in informal dementia caregivers. In addition, we examined if interventions which utilized more sessions and/or were delivered personally (face-to-face) had larger effect sizes. In exploratory meta-regressions, we examined seven additional moderators. METHODS: The protocol was registered with PROSPERO, number CRD42017062555. We systematically searched the literature to identify controlled trials assessing the effect of psychosocial and behavioral interventions on the six outcome measures, for informal dementia caregivers. We performed six random effects meta-analyses, to assess the pooled effect sizes of the interventions. In addition, we performed separate meta-regressions, for each outcome, for each moderator. RESULTS: The sample consisted of 60 studies. For all outcomes except anxiety, the pooled effects were small and in favor of the intervention group. No moderator was found to systematically predict these effects. There were no indications for publication bias or selection bias based on significance. CONCLUSION: Overall, the interventions yield significant (small) effects, independent of intervention characteristics. Future research should explore options to enhance the effectiveness of interventions aimed at assisting informal caregivers.

The Effects and Meanings of Receiving a Diagnosis of Mild Cognitive Impairment or Alzheimer's Disease When One Lives Alone. - Portacolone, Elena; Johnson, Julene K; Covinsky, Kenneth E; Halpern, Jodi; Rubinstein, Robert L (J Alzheimers Dis, 2018)
BACKGROUND: One third of older adults with cognitive impairment live alone and are at high risk for poor health outcomes. Little is known about how older adults who live alone experience the process of receiving a diagnosis of mild cognitive impairment (MCI) or Alzheimer's disease (AD). OBJECTIVE: The aim of this study was to understand the effects and meanings of receiving a diagnosis of MCI or AD on the lived experience of older adults living alone. METHODS: This is a qualitative study of adults age 65 and over living alone with cognitive impairment. Participants' lived experiences were elicited through ethnographic interviews and participant observation in their homes. Using a qualitative content analysis approach, interview transcripts and fieldnotes were analyzed to identify codes and themes. RESULTS: Twenty-nine older adults and 6 members of their social circles completed 114 ethnographic interviews. Core themes included: relief, distress, ambiguous recollections, and not knowing what to do. Participants sometimes felt uplifted and relieved by the diagnostic process. Some participants did not mention having received a diagnosis or had only partial recollections about it. Participants reported that, as time passed, they did not know what to do with regard to the treatment of their condition. Sometimes they also did not know how to prepare for a likely worsening of their condition, which they would experience while living alone. CONCLUSION: Findings suggest the need for more tailored care and follow-up as soon as MCI or AD is diagnosed in persons living alone.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Emotions; Female; Health Services; Humans; Interviews as Topic; Male; Residence Characteristics; Single Person

The Effects of Music Therapy on Cognition, Psychiatric Symptoms, and Activities of Daily Living in Patients with Alzheimer's Disease. - Lyu, Jihui; Zhang, Jingnan; Mu, Haiyan; Li, Wenjie; Champ, Mei; Xiong, Qian; Gao, Tian; Xie, Lijuan; Jin, Weiye; Yang, Wan; Cui, Mengnan; Gao, Maolong; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is the most common type of dementia, affecting millions of older people worldwide. However, pharmacological therapies have not achieved desirable clinical efficacy in the past decades. Non-pharmacological therapies have been receiving increased attention to treat dementia in recent years. OBJECTIVE: This study explores the effects of music therapy on cognitive function and mental wellbeing of patients with AD. METHODS: A total number of 298 AD patients with mild, moderate, or severe dementia participated in the study. The participants with each grade of severity were randomly divided into three groups, which were a singing group, a lyric reading group, and a control group. These three groups received different interventions for three months. All participants underwent a series of tests on cognitive functions, neuropsychological symptoms, and activities of daily living at baseline, three months, and six months. RESULTS: The analysis shows that music therapy is more effective for improving verbal fluency and for alleviating the psychiatric symptoms and caregiver distress than lyrics reading in patients with AD. Stratified analysis shows that music therapy is effective for enhancing memory and language ability in patients with mild AD and reducing the psychiatric symptoms and caregiver distress in patients with moderate or severe AD. However, no significant effect was found for activities of daily living in patients with mild, moderate, or severe AD. CONCLUSION: This study suggests that music therapy is effective in enhancing cognitive function and mental wellbeing and can be recommended as an alternative approach to manage AD associated symptoms.

Elevation of Plasma Amyloid-β Level is More Significant in Early Stage of Cognitive Impairment: A Population-Based Cross-Sectional Study. - Wang, Jin; Qiao, Fan; Shang, Suhang; Li, Pei; Chen, Chen; Dang, Liangjun; Jiang, Yu; Huo, Kang; Deng, Meiying; Wang, Jingyi; Qu, Qiumin (J Alzheimers Dis, 2018)
BACKGROUND: Aggregation and deposition of amyloid-β (Aβ) in the brain is the main pathological change of Alzheimer's disease (AD). Decreased Aβ42 in the cerebrospinal fluid has been confirmed as a biomarker of AD; however, the relationship between plasma Aβ and cognitive impairment is currently unclear. OBJECTIVE: The aim was to explore the relationship between plasma Aβ and cognitive impairment in a cross-sectional study. METHODS: A total of 1,314 subjects (age above 40) from a village in the suburbs of Xi'an, China were enrolled between October 8, 2014 and March 30, 2015. A validated Chinese version of the Mini-Mental State Examination and neuropsychological battery were used to assess cognition. Levels of plasma Aβ42 and Aβ40 were tested using commercial enzyme-linked immunosorbent assay. Relationship of plasma Aβ and cognitive impairment was analyzed using logistic regression analysis. RESULTS: Of the enrolled subjects, 1,180 (89.80%) had normal cognition, 85 (6.47%) had possible cognitive impairment and 49 (3.73%) had probable cognitive impairment. Logistic regression analysis showed that the Aβ42/Aβ40 ratio (OR = 4.042, 95% CI: 1.248-11.098, p = 0.012) and plasma Aβ42 (OR = 1.036, 95% CI: 1.003-1.071, p = 0.031) was higher in the possible cognitive impairment than that in the normal cognition group. Furthermore, the plasma Aβ42/Aβ40 ratio was higher in the possible cognitive impairment group than that in the probable cognitive impairment group (OR = 0.029, 95% CI: 0.002-0.450, p = 0.011). CONCLUSIONS: Levels of plasma Aβ42 and Aβ42/Aβ40 ratio were elevated in patients with possible cognitive impairment, indicating that plasma Aβ42 and Aβ42/Aβ40 ratio increases may be more pronounced in early stage of cognitive impairment.

Episodic Memory and Learning Dysfunction Over an 18-Month Period in Preclinical and Prodromal Alzheimer's Disease. - Baker, Jenalle E; Lim, Yen Ying; Jaeger, Judith; Ames, David; Lautenschlager, Nicola T; Robertson, Joanne; Pietrzak, Robert H; Snyder, Peter J; Villemagne, Victor L; Rowe, Christopher C; Masters, Colin L; Maruff, Paul (J Alzheimers Dis, 2018)
Recent meta-analyses suggest that episodic memory impairment associated with preclinical Alzheimer's disease (AD) equates to 0.15-0.24 standard deviations below that of cognitively healthy older adults. The current study aimed to characterize impairments in verbal acquisition and recall detectable at a single assessment, and investigate how verbal learning and episodic memory deteriorates in preclinical AD. A verbal list-learning task, the International Shopping List Test (ISLT), was administered multiple times over an 18-month period, to three groups of participants: amyloid-beta negative healthy older adults (Aβ- CN; n = 50); Aβ+ positive healthy older adults (preclinical AD; n = 25); and Aβ+ positive individuals diagnosed with mild cognitive impairment (prodromal AD; n = 22). At baseline, there was no significant difference between the preclinical AD and control groups rate of acquisition, or total and delayed recall, however all indices were impaired in prodromal AD. Performance on ISLT total score improved in the control group over the 18-month period, but showed a moderate magnitude decline in the preclinical AD group (Cohen's d = - 0.63, [- 1.12, - 0.14]) and the prodromal AD group (Cohen's d = - 0.36, [- 0.94, 0.22]). No significant impairment in acquisition associated with preclinical AD was seen at baseline. Individuals with preclinical AD showed a significantly different performance on the ISLT total score over an 18-month period, compared to those without abnormal Aβ. Individuals with prodromal AD showed substantial impairment on the ISLT at baseline and declined to a greater extent over time.

The Ethyl Acetate Extract of Leaves of Ugni molinae Turcz. Improves Neuropathological Hallmarks of Alzheimer's Disease in Female APPswe/PS1dE9 Mice Fed with a High Fat Diet. - Jara-Moreno, Daniela; Castro-Torres, Rubn D; Ettcheto, Miren; Auladell, Carme; Kogan, Marcelo J; Folch, Jaume; Verdaguer, Ester; Cano, Amanda; Busquets, Oriol; Delporte, Carla; Camins, Antoni (J Alzheimers Dis, 2018)
The most common type of dementia is Alzheimer's disease (AD), a progressive neurodegenerative disease characterized by impairment in cognitive performance in aged individuals. Currently, there is no effective pharmacological treatment that cures the disease due to the lack of knowledge on the actual mechanisms involved in its pathogenesis. In the last decades, the amyloidogenic hypothesis has been the most studied theory trying to explain the origin of AD, yet it does not address all the concerns relating to its development. In the present study, a possible new preclinical treatment of AD was evaluated using the ethyl acetate extract (EAE) of leaves of Ugni molinae Turcz. (synonym Myrtus ugni Molina Family Myrtacea). The effects were assessed on female transgenic mice from a preclinical model of familial AD (APPswe/PS1dE9) combined with a high fat diet. This preclinical model was selected due to the already available experimental and observational data proving the relationship between obesity, gender, metabolic stress, and cognitive dysfunction; related to characteristics of sporadic AD. According to chemical analyses, EAE would contain polyphenols such as tannins, flavonoid derivatives, and phenolic acids, as well as pentacyclic triterpenoids that exhibit neuroprotective, anti-inflammatory, and antioxidant effects. In addition, the treatment evidenced its capacity to prevent deterioration of memory capacity and reduction of progression speed of AD neuropathology.

Evaluation of Ocular Perfusion in Alzheimer's Disease Using Optical Coherence Tomography Angiography. - Lahme, Larissa; Esser, Eliane Luisa; Mihailovic, Natasa; Schubert, Friederike; Lauermann, Jost; Johnen, Andreas; Eter, Nicole; Duning, Thomas; Alnawaiseh, Maged (J Alzheimers Dis, 2018)
BACKGROUND: There is increasing evidence for the involvement of cerebrovascular factors in Alzheimer's disease (AD). OBJECTIVE: To evaluate retinal and optic nerve head perfusion in patients with AD using optical coherence tomography angiography (OCTA), and to analyze the correlations of quantitative OCTA metrics with AD pathology and vascular cerebral lesions in AD patients. METHODS: 36 eyes of 36 patients with AD (study group) and 38 eyes of 38 healthy subjects (control group) were prospectively included in this study. OCTA was performed using RTVue XR Avanti with AngioVue. In addition, patients underwent a detailed ophthalmological and neurological examination including Mini-Mental State Examination, cerebral magnetic resonance imaging, and amyloid-β (Aβ) and tau levels in the cerebrospinal fluid (CSF). RESULTS: The flow density in the superficial retinal OCT angiogram of the macula in the study group was significantly lower compared to the control group (p = 0.001). There was a significant correlation between the flow density in the superficial retinal OCT angiogram of the macula, as measured using OCTA, and the Fazekas scale (Spearman's correlation coefficient = -0.520; p = 0.003). There was no significant correlation between the Aβ or tau levels in the CSF and the flow density data. CONCLUSION: Patients with AD showed a reduced flow density in the radial peripapillary capillaries layer and in the superficial retinal OCT angiogram when compared with healthy controls. The reduced retinal flow density measured using OCTA is not specifically associated with AD pathology but is associated with the vascular cerebral lesions in AD.

A 'Framingham-like' Algorithm for Predicting 4-Year Risk of Progression to Amnestic Mild Cognitive Impairment or Alzheimer's Disease Using Multidomain Information. - Steenland, Kyle; Zhao, Liping; John, Samantha E; Goldstein, Felicia C; Levey, Allan; Alvaro, Alonso (J Alzheimers Dis, 2018)
BACKGROUND: There are no agreed-upon variables for predicting progression from unimpaired cognition to amnestic mild cognitive impairment (aMCI), or from aMCI to Alzheimer's disease (AD). OBJECTIVE: Use ADNI data to develop a 'Framingham-like' prediction model for a 4-year period. METHODS: We developed models using the strongest baseline predictors from six domains (demographics, neuroimaging, CSF biomarkers, genetics, cognitive tests, and functional ability). We chose the best predictor from each domain, which was dichotomized into more versus less harmful. RESULTS: There were 224 unimpaired individuals and 424 aMCI subjects with baseline data on all predictors, of whom 37 (17% ) and 150 (35% ) converted to aMCI and AD, respectively, during 4 years of follow-up. For the unimpaired, CSF tau/Aβ ratio, hippocampal volume, and a memory score predicted progression. For those aMCI at baseline, the same predictors plus APOE4 status and functional ability predicted progression. Demographics and family history were not important predictors for progression for either group. The fit statistic was good for the unimpaired-aMCI model (C-statistic 0.80) and very good for the aMCI-AD model (C-statistic 0.91). Among the unimpaired, those with no harmful risk factors had a 4-year predicted 2% risk of progression, while those with the most harmful risk factors had a predicted 35% risk. The aMCI subjects with no harmful risk factors had a predicted 1% risk of progression those with all six harmful risk factors had a predicted 90% risk. CONCLUSION: Our parsimonious model accurately predicted progression from unimpaired to aMCI with three variables, and from aMCI to AD with five variables.

Gamma Band Neural Stimulation in Humans and the Promise of a New Modality to Prevent and Treat Alzheimer's Disease. - McDermott, Barry; Porter, Emily; Hughes, Diarmaid; McGinley, Brian; Lang, Mark; O'Halloran, Martin; Jones, Marggie (J Alzheimers Dis, 2018)
Existing treatments for Alzheimer's disease (AD) have questionable efficacy with a need for research into new and more effective therapies to both treat and possibly prevent the condition. This review examines a novel therapeutic modality that shows promise for treating AD based on modulating neuronal activity in the gamma frequency band through external brain stimulation. The gamma frequency band is roughly defined as being between 30 Hz-100 Hz, with the 40 Hz point being of particular significance. The epidemiology, diagnostics, existing pathological models, and related current treatment targets are initially briefly reviewed. Next, the concept of external simulation triggering brain activity in the gamma band with potential demonstration of benefit in AD is introduced with reference to a recent important study using a mouse model of the disease. The review then presents a selection of relevant studies that describe the neurophysiology involved in brain stimulation by external sources, followed by studies involving application of the modality to clinical scenarios. A table summarizing the results of clinical studies applied to AD patients is also reported and may aid future development of the modality. The use of a therapy based on modulation of gamma neuronal activity represents a novel non-invasive, non-pharmacological approach to AD. Although use in clinical scenarios is still a relatively recent area of research, the technique shows good signs of efficacy and may represent an important option for treating AD in the future.

The GWAS Risk Genes for Depression May Be Actively Involved in Alzheimer's Disease. - Ni, Hua; Xu, Min; Zhan, Gui-Lai; Fan, Yu; Zhou, Hejiang; Jiang, Hong-Yan; Lu, Wei-Hong; Tan, Liwen; Zhang, Deng-Feng; Yao, Yong-Gang; Zhang, Chen (J Alzheimers Dis, 2018)
Depression is one of the most frequent psychiatric symptoms observed in people during the development of Alzheimer's disease (AD). We hypothesized that genetic factors conferring risk of depression might affect AD development. In this study, we screened 31 genes, which were located in 19 risk loci for major depressive disorder (MDD) identified by two recent large genome-wide association studies (GWAS), in AD patients at the genomic and transcriptomic levels. Association analysis of common variants was performed by using summary statistics of the International Genomics of Alzheimer's Project (IGAP), and association analysis of rare variants was conducted by sequencing the entire coding region of the 31 MDD risk genes in 107 Han Chinese patients with early-onset and/or familial AD. We also quantified the mRNA expression alterations of these MDD risk genes in brain tissues of AD patients and AD mouse models, followed by protein-protein interaction network prediction to show their potential effects in AD pathways. We found that common and rare variants of L3MBTL2 were significantly associated with AD. mRNA expression levels of 18 MDD risk genes, in particular SORCS3 and OAT, were differentially expressed in AD brain tissues. 13 MDD risk genes were predicted to physically interact with core AD genes. The involvement of HACE1, NEGR1, and SLC6A15 in AD was supported by convergent lines of evidence. Taken together, our results showed that MDD risk genes might play an active role in AD pathology and supported the notion that depression might be the "common cold" of psychiatry.

Healthy versus Entorhinal Cortical Atrophy Identification in Asymptomatic APOE4 Carriers at Risk for Alzheimer's Disease. - Konishi, Kyoko; Joober, Ridha; Poirier, Judes; MacDonald, Kathleen; Chakravarty, Mallar; Patel, Raihaan; Breitner, John; Bohbot, Véronique D (J Alzheimers Dis, 2018)
Early detection of Alzheimer's disease (AD) has been challenging as current biomarkers are invasive and costly. Strong predictors of future AD diagnosis include lower volume of the hippocampus and entorhinal cortex, as well as the ɛ4 allele of the Apolipoprotein E gene (APOE) gene. Therefore, studying functions that are critically mediated by the hippocampus and entorhinal cortex, such as spatial memory, in APOE ɛ4 allele carriers, may be key to the identification of individuals at risk of AD, prior to the manifestation of cognitive impairments. Using a virtual navigation task developed in-house, specifically designed to assess spatial versus non-spatial strategies, the current study is the first to differentiate functional and structural differences within APOE ɛ4 allele carriers. APOE ɛ4 allele carriers that predominantly use non-spatial strategies have decreased fMRI activity in the hippocampus and increased atrophy in the hippocampus, entorhinal cortex, and fimbria compared to APOE ɛ4 allele carriers who use spatial strategies. In contrast, APOE ɛ4 allele carriers who use spatial strategies have grey matter levels comparable to non-APOE ɛ4 allele carriers. Furthermore, in a leave-one-out analysis, grey matter in the entorhinal cortex could predict navigational strategy with 92% accuracy.
Keywords: Aged; Alleles; Alzheimer Disease; Apolipoprotein E4; Atrophy; Case-Control Studies; Entorhinal Cortex; Female; Heterozygote; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Risk Factors; Spatial Memory

Honokiol Alleviates Cognitive Deficits of Alzheimer's Disease (PS1V97L) Transgenic Mice by Activating Mitochondrial SIRT3. - Li, Haitao; Jia, Jianping; Wang, Wei; Hou, Tingting; Tian, Yuanruhua; Wu, Qiaoqi; Xu, Lingzhi; Wei, Yiping; Wang, Xiu (J Alzheimers Dis, 2018)
Accumulating evidence has demonstrated that mitochondrial dysfunction is a prominent early event in the progression of Alzheimer's disease (AD). Whether protecting mitochondrial function can reduce amyloid-β oligomer (AβO)-induced neurotoxicity in PS1V97L transgenic mice remains unknown. In this study, we examined the possible protective effects of honokiol (HKL) on mitochondrial dysfunction induced by AβOs in neurons, and cognitive function in AD PS1V97Ltransgenic mice. We determined that HKL increased mitochondrial sirtuin 3 (SIRT3) expression levels and activity, which in turn markedly improved ATP production and weakened mitochondrial reactive oxygen species production. We demonstrated that the enhanced energy metabolism and attenuated oxidative stress of HKL restores AβO-mediated mitochondrial dysfunction in vitro and in vivo. Consequently, memory deficits in the PS1V97L transgenic mice were rescued by HKL in the early stages. These results suggest that HKL has therapeutic potential for delaying the onset of AD symptoms by alleviating mitochondrial impairment and increasing hyperactivation of SIRT3 in the pathogenesis of preclinical AD.

Hospitalization after Oral Antibiotic Initiation in Finnish Community Dwellers with and without Alzheimer's Disease: Retrospective Register-Based Cohort Study. - Järvinen, Heli; Taipale, Heidi; Koponen, Marjaana; Tanskanen, Antti; Tiihonen, Jari; Tolppanen, Anna-Maija; Hartikainen, Sirpa (J Alzheimers Dis, 2018)
BACKGROUND: Persons with Alzheimer's disease (AD) are frequently hospitalized from infection-related causes. There are no previous studies investigating hospitalization associated with antibiotic initiation in persons with AD. OBJECTIVE: To investigate the frequency and risk of hospitalization associated with oral antibiotic initiation among community dwellers with and without AD. METHODS: We performed a retrospective register-based study utilizing register-based Medication Use and Alzheimer's disease (MEDALZ) cohort. It includes all community dwellers diagnosed with AD during 2005-2011 in Finland and their matched comparison persons without AD. Antibiotic use was initiated by 34,785 persons with and 36,428 without AD. Drug use data were collected from Prescription Register and comorbidities from Special Reimbursement and Hospital Care Registers. Infection diagnoses were collected from the Hospital Care Register. Factors associated with hospitalization were estimated utilizing logistic regression models. RESULTS: Risk of hospitalization following antibiotic initiation was higher among antibiotic initiators with AD than without AD (adjusted odds ratio, aOR, 1.37, 95% Cl 1.28-1.46).Strongest association with hospitalization was found for oral glucocorticoid use, aOR 1.41 (1.25-1.59); epilepsy, aOR 1.33 (1.10-1.63); and active cancer, aOR 1.30 (1.14-1.49). Among initiators of cephalexin, pivmecillinam, amoxicillin/amoxicillin, and enzyme inhibitor and doxycycline, persons with AD were more frequently hospitalized than persons without AD. A quarter of hospitalized antibiotic initiators had infection diagnosis in their hospital care records. CONCLUSIONS: Persons with AD initiating an antibiotic had a higher risk for hospitalization than antibiotic initiators without AD. Further research is needed to determine whether infection-related hospitalization could be reduced.

Humanin Exerts Neuroprotection During Cardiac Ischemia-Reperfusion Injury. - Kumfu, Sirinart; Charununtakorn, Savitree T; Jaiwongkam, Thidarat; Chattipakorn, Nipon; Chattipakorn, Siriporn C (J Alzheimers Dis, 2018)
Cardiac ischemia-reperfusion (I/R) injury has been shown to impair brain function. Humanin analogue (HNG) given prior to cardiac ischemia has been shown to attenuate both heart and brain mitochondrial dysfunction caused by cardiac I/R injury. In a clinical setting, patients received medical treatment for acute myocardial infarction either during or after the onset of myocardial ischemia; thus, in this study, we tested the hypothesis that the administration of HNG during cardiac I/R injury has therapeutic potential for brain protection. Thirty-six male Wistar rats were divided into two groups: a cardiac I/R group (n = 30), and a sham group (n = 6). The I/R rats were then divided into five subgroups to receive: 1) vehicle; 2) HNG (84 μg/kg); 3) HNG (168 μg/kg); 4) HNG (252 μg/kg) intravenously administered during the cardiac-ischemia; and 5) HNG at 252 μg/kg given at the onset of reperfusion. At the end of treatment, brains were removed for determination of blood-brain barrier (BBB) breakdown, oxidative stress, brain mitochondrial function, brain mitochondrial dynamics, p-tau, amyloid-β (Aβ) and apoptosis. HNG at a dose of 168 and 252 μg/kg administered during ischemia, and 252 μg/kg given at the onset of reperfusion effectively attenuated the brain mitochondrial dysfunction, tau hyperphosphorylation and Aβ accumulation, and apoptosis, without reducing BBB breakdown, brain oxidative stress, or mitochondrial dynamic, caused by cardiac I/R injury. In conclusion, humanin exerted neuroprotection during induced cardiac I/R injury via improvement in brain mitochondrial function, and the reduction of Alzheimer's disease pathology and apoptosis.
Keywords: Animals; Apoptosis; Blood-Brain Barrier; Brain; Intracellular Signaling Peptides and Proteins; Male; Microscopy, Electron; Mitochondria; Myocardial Reperfusion Injury; Neurons; Neuroprotection; Neuroprotective Agents; Oxidative Stress; Rats; Rats, Wistar; Signal Transduction

Hypoxia-Induced Signaling Activation in Neurodegenerative Diseases: Targets for New Therapeutic Strategies. - Jha, Niraj Kumar; Jha, Saurabh Kumar; Sharma, Renu; Kumar, Dhiraj; Ambasta, Rashmi K; Kumar, Pravir (J Alzheimers Dis, 2018)
For the maintenance of cellular homeostasis and energy metabolism, an uninterrupted supply of oxygen (O2) is routinely required in the brain. However, under the impaired level of O2 (hypoxia) or reduced blood flow (ischemia), the tissues are not sufficiently oxygenated, which triggers disruption of cellular homeostasis in the brain. Hypoxia is known to have a notable effect on controlling the expression of proteins involved in a broad range of biological processes varying from energy metabolism, erythropoiesis, angiogenesis, neurogenesis to mitochondrial trafficking and autophagy, thus facilitating neuronal cells to endure in deprived O2. On the contrary, hypoxia to the brain is a major source of morbidity and mortality in humans culminating in cognitive impairment, gradual muscle weakness, loss of motor activity, speech deficit, and paralysis as well as other pathological consequences. Further, hypoxia resulting in reduced O2 deliveries to brain tissues is supposed to cause neurodegeneration in both in vivo and in vitro models. Similarly, chronic exposure to hypoxia has also been reportedly involved in defective vessel formation. Such vascular abnormalities lead to altered blood flow, reduced nutrient delivery, and entry of otherwise restricted infiltrates, thereby limiting O2 availability to the brain and causing neurological disabilities. Moreover, the precise mechanistic role played by hypoxia in mediating key processes of the brain and alternatively, in triggering pathological signals associated with neurodegeneration remains mysterious. Therefore, this review elucidates the intricate role played by hypoxia in modulating crucial processes of the brain and their severity in neuronal damage. Additionally, the involvement of numerous pharmacological approaches to compensate hypoxia-induced neuronal damage has also been addressed, which may be considered as a potential therapeutic approach in hypoxia-mediated neurodegeneration.

The Impact of APOE ɛ4 in Alzheimer's Disease Differs According to Age. - Kim, Jaeho; Park, Seongbeom; Yoo, Heejin; Jang, Hyemin; Kim, Yeshin; Kim, Ko Woon; Jang, Young Kyoung; Lee, Jin San; Kim, Sung Tae; Kim, Seonwoo; Lee, Jong Min; Ki, Chang-Seok; et al. (J Alzheimers Dis, 2018)
We evaluated how the impact of apolipoprotein E4 (APOE4) differs according to age in Alzheimer's disease (AD) patients. We recruited 846 AD patients and 815 cognitively normal controls and categorized into three groups with respect to their age (<65, 65-74, and ≥75 years). We evaluated the risk of AD in APOE4 carriers and compared cortical thickness and cognitive function according to APOE4 status in each age group. At the point of this study, in young (<65 years) AD, APOE4 noncarriers had the most severe frontal and perisylvian atrophy, while in old (≥75 years) AD, APOE4 carriers had the most severe medial temporal atrophy. In AD under 75 years, APOE4 noncarriers and heterozygotes showed worse performance in language, visuospatial, and frontal function compared to homozygotes, while, in old (≥75 years) AD, APOE4 homozygotes showed worse performance in memory compared to noncarriers. As the detrimental effects of APOE4 seen in older AD patients were not found in younger AD patients, we suggest that some unrevealed factors are associated with cortical atrophy and non-amnestic cognitive dysfunction in young AD with APOE4 noncarriers.
Keywords: Age Factors; Aged; Alzheimer Disease; Apolipoprotein E4; Atrophy; Brain; Case-Control Studies; Cognition; Female; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Memory; Middle Aged; Republic of Korea

Impact of Mild Cognitive Impairment on Mortality and Cause of Death in the Elderly. - Bae, Jong Bin; Han, Ji Won; Kwak, Kyung Phil; Kim, Bong Jo; Kim, Shin Gyeom; Kim, Jeong Lan; Kim, Tae Hui; Ryu, Seung-Ho; Moon, Seok Woo; Park, Joon Hyuk; Youn, Jong Chul; Lee, Dong Young; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Mild cognitive impairment (MCI) is a cognitive state that lies on the continuum between normal aging and dementia, and the prevalence of MCI is higher than dementia. However, the risk for mortality of people with MCI has been far less studied than that of people with dementia, and the population attributable risk percent (PAR%) of death attributable to MCI has not been estimated yet. OBJECTIVE: To investigate the impact of MCI on mortality and the cause of death in the elderly, and to estimate the PAR% of deaths attributable to MCI. METHODS: Data came from 7,315 elderly subjects aged ≥60 years without dementia from two cohort studies with diagnostic assessments of MCI at baseline. Deaths among participants were confirmed through the nationwide mortality database of Statistics Korea. RESULTS: MCI increased the risk of mortality in a multivariate Cox proportional model adjusting for age, sex, education, smoking, alcohol drinking, chronic illness, depression, vascular components, and cohort (hazard ratio = 1.59, 95% confidence interval 1.30, 1.94). PAR% of death attributable to MCI was 10.7% for age 65-74 years, 16.0% for age 75-84 years, and 24.2% for age ≥85 years. In the elderly with MCI, mortality risks from cerebrovascular disease, respiratory disease, and external causes were higher than in the cognitively normal elderly. CONCLUSIONS: Our results suggest that the mortality risk of MCI in Asian countries may be comparable to that in Western countries, and MCI can contribute to the death of the elderly as much as dementia.

Impact of Osteoporosis on the Risk of Dementia in Almost 60,000 Patients Followed in General Practices in Germany. - Kostev, Karel; Hadji, Peyman; Jacob, Louis (J Alzheimers Dis, 2018)
BACKGROUND: There has been in recent decades a growing interest in the relationship between osteoporosis and cognitive decline. OBJECTIVE: The goal of this study was to analyze the impact of osteoporosis on the risk of dementia in patients followed for up to 20 years in general practices in Germany. METHODS: This study included patients who received an initial diagnosis of osteoporosis and were followed by 1,215 general practitioners in Germany between January 1993 and December 2012 (index date). Controls were matched (1:1) to osteoporosis patients using propensity scores based on age, gender, index year, comorbidities, and co-therapies. Kaplan-Meier curves were performed to study the development of dementia separately in men and women with or without osteoporosis within 20 years of the index date. Cox proportional regression models were used to estimate the relationship between osteoporosis and dementia in men and women. RESULTS: The present study included 29,983 cases and 29,983 controls. After 20 years of follow-up, 20.5% of women with osteoporosis and 16.4% of controls had been diagnosed with dementia (log-rank p-value <0.001). At the end of the follow-up period, dementia was found in 22.0% of men previously diagnosed with osteoporosis and 14.9% of men without this chronic condition (log-rank p-value <0.001). Osteoporosis was associated with a 1.2-fold increase in the risk of being diagnosed with dementia in women and a 1.3-fold increase in the risk of being diagnosed with dementia in men. CONCLUSIONS: There was a positive association between osteoporosis and dementia in patients followed in general practices in Germany.

Impact of Untimely Access to Formal Care on Costs and Quality of Life in Community Dwelling People with Dementia. - Janssen, Niels; Handels, Ron L; Sköldunger, Anders; Woods, Bob; Jelley, Hannah; Edwards, Rhiannon Tudor; Orrell, Martin; Selbæk, Geir; Røsvik, Janne; Gonçalves-Pereira, Manuel; Marques, Maria J; Zanetti, Orazio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Access to formal care is not always timely and a better understanding on the impact of untimely access is needed. OBJECTIVE: To examine, from a societal perspective, the impact of untimely access to formal care in terms of total costs and quality of life over one year in community dwelling people with dementia. METHODS: Within the Actifcare study, needs, resource use, and quality of life were observed for one year in a cohort of 451 community dwelling people with dementia in 8 European countries. Untimely access to care was operationalized as having at least one unmet need for care identified by the Camberwell Assessment of Need for the Elderly (CANE) instrument. Two regression models were built for both total costs and quality of life measured by the EQ-5D-5L, one using sum of unmet needs and one using a predefined selection of need items. RESULTS: Unmet needs were not associated with higher total costs but they were associated with a lower quality of life of people with dementia. Of all CANE items, only an unmet need for "company" was significantly related to lower total costs. CONCLUSION: Total costs did not seem to differ between participants with unmet and met needs. Only few associations between specific unmet needs and costs and quality of life were found. Furthermore, quality of life of people with dementia decreases when multiple unmet needs are experienced, indicating that assessing and meeting needs is important to improve quality of life.

In Vivo Visualization of Tau Accumulation, Microglial Activation, and Brain Atrophy in a Mouse Model of Tauopathy rTg4510. - Ishikawa, Ai; Tokunaga, Masaki; Maeda, Jun; Minamihisamatsu, Takeharu; Shimojo, Masafumi; Takuwa, Hiroyuki; Ono, Maiko; Ni, Ruiqing; Hirano, Shigeki; Kuwabara, Satoshi; Ji, Bin; Zhang, Ming-Rong; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Tau imaging using PET is a promising tool for the diagnosis and evaluation of tau-related neurodegenerative disorders, but the relationship among PET-detectable tau, neuroinflammation, and neurodegeneration is not yet fully understood. OBJECTIVE: We aimed to elucidate sequential changes in tau accumulation, neuroinflammation, and brain atrophy by PET and MRI in a tauopathy mouse model. METHODS: rTg4510 transgenic (tg) mice expressing P301L mutated tau and non-tg mice were examined with brain MRI and PET imaging (analyzed numbers: tg = 17, non-tg = 13; age 2.5∼14 months). As PET probes, [11C]PBB3 (Pyridinyl-Butadienyl-Benzothiazole 3) and [11C]AC-5216 were used to visualize tau pathology and 18-kDa translocator protein (TSPO) neuroinflammation. Tau pathology and microglia activation were subsequently analyzed by histochemistry. RESULTS: PET studies revealed age-dependent increases in [11C]PBB3 and [11C]AC-5216 signals, which were correlated with age-dependent volume reduction in the forebrain on MRI. However, the increase in [11C]PBB3 signals reached a plateau at age 7 months, and therefore its significant correlation with [11C]AC-5216 disappeared after age 7 months. In contrast, [11C]AC-5216 showed a strong correlation with both age and volume reduction until age 14 months. Histochemical analyses confirmed the relevance of pathological tau accumulation and elevated TSPO immunoreactivity in putative microglia. CONCLUSION: Our results showed that tau accumulation is associated with neuroinflammation and brain atrophy in a tauopathy mouse model. The time-course of the [11C]PBB3- and TSPO-PET finding suggests that tau deposition triggers progressive neuroinflammation, and the sequential changes can be evaluated in vivo in mouse brains.
Keywords: Animals; Atrophy; Benzothiazoles; Brain; Disease Models, Animal; Female; Magnetic Resonance Imaging; Male; Mice; Mice, Transgenic; Microglia; Positron-Emission Tomography; Receptors, GABA; tau Proteins; Tauopathies

Increased Risk of Dementia in Subjective Cognitive Decline if CT Brain Changes are Present. - Sacuiu, Simona; Eckerström, Marie; Johansson, Lena; Kern, Silke; Sigström, Robert; Xinxin, Guo; Östling, Svante; Skoog, Ingmar (J Alzheimers Dis, 2018)
BACKGROUND: Subjective cognitive decline (SCD) has low predictive value for incident dementia. OBJECTIVES: We examined whether CT detectable brain changes add predictive value to SCD in a population sample with high scores on the Mini-Mental State Examination. METHODS: Subjective reports of memory and executive function were gathered in a non-demented population sample ≥70 years (n = 921). CT-brain was performed at baseline (n = 626). Brain atrophy, infarcts, and white matter lesions (WMLs) were classified using visual ratings. Dementia incidence was evaluated periodically during 12 years. RESULTS: The prevalence of SCD was 32.5% among individuals without dementia. During follow-up, 151 individuals (16.4%) developed dementia. The risk of dementia was increased in SCD, and increased further with WMLs and cortical atrophy present. However, the positive predictive values for incident dementia were low, 25% in SCD and 41% in SCD with WMLs and cortical atrophy. CONCLUSION: Our observations add clinical value to the use of SCD and CT to select relevant populations for interventions against dementia, but more stringent screening methods are necessary to reach individuals at risk.

The Influence of Polypharmacy on the Initiation of Anti-Dementia Therapy in Germany. - Bohlken, Jens; Jacob, Louis; van den Bussche, Hendrik; Kostev, Karel (J Alzheimers Dis, 2018)
The goal of the present retrospective study was to focus on the potential influence of polypharmacy on the initiation of antidementia therapy in patients diagnosed with dementia in general practices in Germany. The current study sample included patients diagnosed with dementia in 1,217 general practices in Germany between 2014 and 2016 (index date). The primary outcome measure was the rate of prescription of anti-dementia drugs within one year following the index date. The explanatory variable was the number of different drugs prescribed at baseline per patient. Independent variables included age, sex, and type of dementia. Logistic regression analyses were conducted to study the impact of the number of different drugs prescribed at baseline per participant on the odds of receiving anti-dementia therapy (in all patients and in patients diagnosed with Alzheimer's disease). The study included 21,888 patients with all-cause dementia. Mean age was 80.2 years (SD = 7.3 years) and 61.4% of the study population were women. Individuals receiving six drugs or more at baseline were significantly less likely to be prescribed anti-dementia treatment when compared to those without any drug at baseline (6- 9 drugs: odds ratio [OR] = 0.75;≥10 drugs: OR = 0.58). In the subgroup of patients with Alzheimer's disease, the odds of being prescribed anti-dementia therapy were lower in individuals with four drugs or more, compared to patients who had not been prescribed any drugs at baseline (4- 5 drugs: OR = 0.60; 6- 9 drugs: OR = 0.49;≥10 drugs: OR = 0.36). There is a negative association between polypharmacy and antidementia therapy initiation in general practices in Germany.

Interaction between Cytomegalovirus and Herpes Simplex Virus Type 1 Associated with the Risk of Alzheimer's Disease Development. - Lövheim, Hugo; Olsson, Jan; Weidung, Bodil; Johansson, Anders; Eriksson, Sture; Hallmans, Göran; Elgh, Fredrik (J Alzheimers Dis, 2018)
BACKGROUND: Several environmental factors, including infectious agents, have been suggested to cause Alzheimer's disease (AD). Cytomegalovirus (CMV) has been associated with AD in several recent studies. OBJECTIVE: To investigate whether carriage of CMV, alone or in combination with Herpes simplex virus (HSV), increased the risk of developing AD. METHODS: Plasma samples from 360 AD cases (75.3% women, mean age 61.2 years), taken an average of 9.6 years before AD diagnosis, and 360 age-, sex-, cohort-, and sampling date matched dementia-free controls were analyzed to detect anti-CMV (immunoglobulin [Ig] G and IgM), group-specific anti-HSV (IgG and IgM), and specific anti-HSV1 and HSV2 IgG antibodies by enzyme-linked immunosorbent assays. AD cases and dementia-free controls were compared using conditional logistic regression analyses. RESULTS: The presence of anti-CMV IgG antibodies did not increase the risk of AD (odds ratio [OR], 0.857; p = 0.497). Among AD cases, an association between CMV and HSV1 carriage was detected (OR 7.145, p < 0.001); in a conditional logistic regression model, the interaction between CMV and HSV1 was associated with AD development (OR 5.662; p = 0.007). CONCLUSION: The present findings do not support a direct relationship between CMV infection and the development of AD; however, an interaction between CMV and HSV1 was found to be associated significantly with AD development. These findings suggest that CMV infection facilitates the development of HSV1-associated AD, possibly via its effects on the immune system.
Keywords: Aged; Alzheimer Disease; Antibodies, Viral; Case-Control Studies; Cytomegalovirus; Cytomegalovirus Infections; Enzyme-Linked Immunosorbent Assay; Female; Herpes Simplex; Herpesvirus 1, Human; Humans; Immunoglobulin G; Immunoglobulin M; Logistic Models; Male; Middle Aged

Lentivirus-Mediated HDAC3 Inhibition Attenuates Oxidative Stress in APPswe/PS1dE9 Mice. - Yu, Linjie; Liu, Yi; Jin, Yuexinzi; Cao, Xiang; Chen, Jian; Jin, Jiali; Gu, Yue; Bao, Xinyu; Ren, Zhuoying; Xu, Yun; Zhu, Xiaolei (J Alzheimers Dis, 2018)
Amyloid-β (Aβ) induces a burst of oxidative stress and plays a critical role in the pathogenesis of Alzheimer's disease (AD). Our previous results have shown that histone deacetylase 3 (HDAC3) inhibition ameliorates spatial memory deficits and decreases the Aβ burden in the brains of 9-month-old APPswe/PS1dE9 (APP/PS1) mice. In this study, we investigated the role of HDAC3 inhibition in oxidative stress in vivo and in vitro models of AD. HDAC3 was detected mainly in the neurons, and HDAC3 inhibition significantly decreased reactive oxygen species generation and improved primary cortical neuron viability. In addition, HDAC3 inhibition attenuated spatial memory dysfunction in 6-month-old APP/PS1 mice, and decreased the apoptotic rate in the hippocampi as demonstrated by TUNEL staining. HDAC3 inhibition also reduced markers of lipid peroxidation, protein oxidation, and DNA/RNA oxidation in the hippocampi of APP/PS1 mice. Moreover, HDAC3 inhibition inactivated the c-Abl/MST1/YAP signaling pathway in the hippocampi of APP/PS1 mice. In conclusion, our data show that HDAC3 inhibition can attenuate spatial memory deficits and inhibit oxidative stress in APP/PS1 mice; these results indicate a potential strategy for AD treatment.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Hippocampus; Histone Deacetylases; Lentivirus; Male; Maze Learning; Mice; Mice, Inbred C57BL; Mice, Transgenic; Neurons; Oxidative Stress; Plaque, Amyloid; Primary Cell Culture; Reactive Oxygen Species; Spatial Memory; tau Proteins

The Level of Plasma Amyloid-β40 Is Correlated with Peripheral Transport Proteins in Cognitively Normal Adults: A Population-Based Cross-Sectional Study. - Gao, Ling; Jiang, Yu; Wei, Shan; Shang, Suhang; Li, Pei; Chen, Chen; Dang, Liangjun; Wang, Jin; Huo, Kang; Deng, Meiying; Wang, Jingyi; Zhang, Rong; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Transport proteins, soluble low-density lipoprotein receptor-related protein-1 (sLRP1), and soluble receptor of advanced glycation end products (sRAGE), play an important role in the clearance of plasma amyloid-β (Aβ). However, their relationship is not clear. OBJECTIVE: The aim was to explore the relationship between plasma levels of sLRP1, sRAGE, and Aβ in a cross-sectional study. METHODS: A total of 1,185 cognitively normal participants (age above 40) from a village in the suburbs of Xi'an, China were enrolled from October 8, 2014 to March 30, 2015. Plasma Aβ40, Aβ42, sLRP1, and sRAGE were tested using a commercial ELISA. Apolipoprotein E (APOE) genotyping was conducted using PCR and sequencing. The relationship between plasma levels of sLRP1, sRAGE, and Aβ was analyzed using Pearson's correlation analysis and multiple linear regression. RESULTS: In the total population, Log sLRP1 and Log sRAGE were positively correlated with plasma Aβ40 (r= 0.103, p < 0.001; r= 0.064, p = 0.027, respectively), but neither were associated with plasma Aβ42. After multivariable adjustment in the regression model, Log sLRP1 and Log sRAGE were still positively related with plasma Aβ40 (β= 2.969, p < 0.001; β= 1.936, p = 0.017, respectively) but not Aβ42. Furthermore, the positive correlations between transport proteins and plasma Aβ40 remained significant only in APOEɛ4 non-carriers after Pearson's analysis and multiple regression analysis after stratification by gene status. CONCLUSION: The concentrations of plasma sLRP1 and sRAGE had a significant impact on the level of plasma Aβ40 in cognitively normal adults, especially in APOEɛ4 non-carriers. However, the mechanism by which the transport proteins are involved in peripheral Aβ clearance and the relationship between transporters and amyloid burden in the brain needs further validation.

A Longitudinal Study of Total and Phosphorylated α-Synuclein with Other Biomarkers in Cerebrospinal Fluid of Alzheimer's Disease and Mild Cognitive Impairment. - Wang, Hua; Stewart, Tessandra; Toledo, Jon B; Ginghina, Carmen; Tang, Lu; Atik, Anzari; Aro, Patrick; Shaw, Leslie M; Trojanowski, John Q; Galasko, Douglas R; Edland, Steven; Jensen, Poul H; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) features a dynamic sequence of amyloid deposition, neurodegeneration, and cognitive impairment. A significant fraction of AD brains also displays Lewy body pathology, suggesting that addition of classically Parkinson's disease-related proteins to the AD biomarker panel may be of value. To determine whether addition of cerebrospinal fluid (CSF) total α-synuclein and its form phosphorylated at S129 (pS129) to the AD biomarker panel [Amyloid-β1-42 (Aβ42), tau, and phosphorylated tau (p-tau181)] improves its performance, we examined CSF samples collected longitudinally up to 7 years as part of the Alzheimer's Disease Neuroimaging Initiative. From 87 AD, 177 mild cognitive impairment (MCI), and 104 age-matched healthy controls, 792 baseline and longitudinal CSF samples were tested for total α-synuclein, pS129, Aβ42, tau, and p-tau181. pS129, but not total α-synuclein, was weakly associated with diagnosis at baseline when t-tau/Aβ42 was included in the statistical model (β= 0.0026, p = 0.041, 95% CI [(0.0001)-(0.005)]). CSF α-synuclein predicted Alzheimer's Disease Assessment Scale-Cognitive (β= -0.59, p = 0.0015, 95% CI [(-0.96)-(-0.23)]), memory (β= 0.4, p = 0.00025, 95% CI [(0.16)-(0.59)]), and executive (0.62,<0.0001, 95% CI [(0.31)-(0.93)]) function composite scores, and progression from MCI to AD (β= 0.019, p = 0.0011, 95% CI [(0.002)-(0.20)]). pS129 was associated with executive function (β= -2.55, p = 0.0085, 95% CI [(-4.45)-(-0.66)]). Lower values in the mismatch between α-synuclein and p-tau181 predicted faster cognitive decline (β= 0.64, p = 0.0012, 95% CI [(0.48)-(0.84)]). Longitudinal biomarker changes did not differ between groups, and may not reflect AD progression. The α-synuclein-p-tau181-Mismatch could better predict longitudinal cognitive changes than classical AD markers alone, and its pathological correlates should be investigated further.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Executive Function; Female; Humans; Linear Models; Longitudinal Studies; Male; Memory Disorders; Multivariate Analysis; Neuropsychological Tests; Phosphorylation; tau Proteins

Mediterranean Diet, Its Components, and Amyloid Imaging Biomarkers. - Vassilaki, Maria; Aakre, Jeremiah A; Syrjanen, Jeremy A; Mielke, Michelle M; Geda, Yonas E; Kremers, Walter K; Machulda, Mary M; Alhurani, Rabe E; Staubo, Sara C; Knopman, David S; Petersen, Ronald C; Lowe, Val J; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is accumulating evidence suggesting that diet may play a role in preventing or delaying cognitive decline and dementia, but the underlying biological mechanisms are not well understood. OBJECTIVES: To examine the cross-sectional associations of the Mediterranean diet (MeDi) and its components with 11C-PiB-PET scan measures of amyloid-β (Aβ) deposition. METHODS: The study consisted of 278 Mayo Clinic Study of Aging participants 70+ years old, who were cognitively unimpaired (CU) at the time of completion of the Food Frequency Questionnaire (FFQ) and when they underwent PET imaging. Adherence to the MeDi was assessed by computing the MeDi score for each participant. All scans were performed after the FFQ completion; median [IQR] time between FFQ and Aβ PET was 3.5 (1.4) years. Z-scores were created for component, macro- and micronutrients measured. Linear and logistic regression models were adjusted for age, sex, education, apolipoprotein E (APOE) ɛ4 allele carrier status, time interval between the FFQ completion and PET scan, and total energy intake. RESULTS: Participants' median age at FFQ was 77.7 years (55.8% men; 26.6% with an APOE ɛ4 allele). Higher MeDi score (linear regression slope (beta):-0.035, p = 0.012; per standard deviation increase), vegetable intake (beta:-0.043, p = 0.002), intake of vitamin A (beta:-0.041, p = 0.003) or β-carotene (beta: -0.039, p = 0.005) from food sources and moderate alcohol consumption (beta: -0.074, p = 0.03) were associated with lower 11C-PiB standardized uptake value ratio. CONCLUSION: Findings are consistent with previous studies suggesting that higher adherence to a MeDi pattern and higher vegetable consumption are associated with better neuroimaging biomarker profile. Prospective studies are needed to validate current findings.

Melatonin in Synaptic Impairments of Alzheimer's Disease. - Shi, Yan; Fang, Ying-Yan; Wei, Yu-Ping; Jiang, Qian; Zeng, Peng; Tang, Na; Lu, Youming; Tian, Qing (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) underlies dementia for millions of people worldwide with no effective treatment. The dementia of AD is thought stem from the impairments of the synapses because of their critical roles in cognition. Melatonin is a neurohormone mainly released by the pineal gland in a circadian manner and it regulates brain functions in various manners. It is reported that both the melatonin deficit and synaptic impairments are present in the very early stage of AD and strongly contribute to the progress of AD. In the mammalian brains, the effects of melatonin are mainly relayed by two of its receptors, melatonin receptor type 1a (MT1) and 1b (MT2). To have a clear idea on the roles of melatonin in synaptic impairments of AD, this review discussed the actions of melatonin and its receptors in the stabilization of synapses, modulation of long-term potentiation, as well as their contributions in the transmissions of glutamatergic, GABAergic and dopaminergic synapses, which are the three main types of synapses relevant to the synaptic strength. The synaptic protective roles of melatonin in AD treatment were also summarized. Regarding its protective roles against amyloid-β neurotoxicity, tau hyperphosphorylation, oxygenation, inflammation as well as synaptic dysfunctions, melatonin may be an ideal therapeutic agent against AD at early stage.

Mesenchymal Stem Cell-Derived Extracellular Vesicles Suppresses iNOS Expression and Ameliorates Neural Impairment in Alzheimer's Disease Mice. - Wang, Shan-Shan; Jia, Jianjun; Wang, Zhenfu (J Alzheimers Dis, 2018)
BACKGROUND: Mesenchymal stem cells (MSCs)-derived extracellular vesicles (EVs) have been reported to exhibit therapeutic effects in various animal models of neurological diseases, such as stroke and hypoxic-ischemic brain injury. OBJECTIVE: The present study investigated the potential beneficial effect of MSC-derived EVs in an animal model of Alzheimer's disease (AD). METHODS: APP/PS1 mice and their non-transgenic littermates (WT) received intracerebroventricle injection of MSC-derived EVs once per two days for two weeks. Then novel object recognition and water maze tasks were carried out to measure the cognitive behaviors. Electrophysiological tests were carried out to measure hippocampal synaptic plasticity. Inducible nitric oxide synthase (iNOS) mRNA and protein levels were measured by qRT-PCR and western blotting in primary cultured neurons treated with amyloid-β peptide (Aβ) or prepared from APP/PS1 mice. RESULTS: Treatment with MSC-derived EVs alleviates exogenous Aβ-induced iNOS mRNA and protein expression. In cultured primary neurons prepared from APP/PS1 pups, iNOS mRNA and protein levels were significantly reduced when treated with MSC-derived EVs. MSC-derived EVs improved cognitive behavior, rescued impairment of CA1 synaptic transmission, and long-term potentiation in APP/PS1 mice. CONCLUSION: MSC-derived EVs possessed beneficial effects in a mouse model of AD, probably by suppressing Aβ induced iNOS expression.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Cells, Cultured; Disease Models, Animal; Extracellular Vesicles; Humans; Male; Mesenchymal Stem Cells; Mice; Mice, Transgenic; Neuronal Plasticity; Neurons; Nitric Oxide Synthase Type II; Synaptic Transmission

The Montreal Cognitive Assessment: Normative Data from a German-Speaking Cohort and Comparison with International Normative Samples. - Thomann, Alessandra E; Goettel, Nicolai; Monsch, Raphael J; Berres, Manfred; Jahn, Thomas; Steiner, Luzius A; Monsch, Andreas U (J Alzheimers Dis, 2018)
BACKGROUND: The Montreal Cognitive Assessment (MoCA) is used to evaluate multiple cognitive domains in elderly individuals. However, it is influenced by demographic characteristics that have yet to be adequately considered. OBJECTIVE: The aim of our study was to investigate the effects of age, education, and sex on the MoCA total score and to provide demographically adjusted normative values for a German-speaking population. METHODS: Subjects were recruited from a registry of healthy volunteers. Cognitive health was defined using the Mini-Mental State Examination (score ≥27/30 points) and the Consortium to Establish a Registry for Alzheimer's Disease-Neuropsychological Assessment Battery (total score ≥85.9 points). Participants were assessed with the German version of the MoCA. Normative values were developed based on regression analysis. Covariates were chosen using the Predicted Residual Sums of Squares approach. RESULTS: The final sample consisted of 283 participants (155 women, 128 men; mean (SD) age = 73.8 (5.2) years; education = 13.6 (2.9) years). Thirty-one percent of participants scored below the original cut-off (<26/30 points). The MoCA total score was best predicted by a regression model with age, education, and sex as covariates. Older age, lower education, and male sex were associated with a lower MoCA total score (p < 0.001). CONCLUSION: We developed a formula to provide demographically adjusted standard scores for the MoCA in a German-speaking population. A comparison with other MoCA normative studies revealed considerable differences with respect to selection of volunteers and methods used to establish normative data.

Multicenter Resting State Functional Connectivity in Prodromal and Dementia Stages of Alzheimer's Disease. - Teipel, Stefan J; Metzger, Coraline D; Brosseron, Frederic; Buerger, Katharina; Brueggen, Katharina; Catak, Cihan; Diesing, Dominik; Dobisch, Laura; Fliebach, Klaus; Franke, Christiana; Heneka, Michael T; Kilimann, Ingo; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alterations of intrinsic networks from resting state fMRI (rs-fMRI) have been suggested as functional biomarkers of Alzheimer's disease (AD). OBJECTIVE: To determine the diagnostic accuracy of multicenter rs-fMRI for prodromal and preclinical stages of AD. METHODS: We determined rs-fMRI functional connectivity based on Pearson's correlation coefficients and amplitude of low-frequency fluctuation in people with subjective cognitive decline, people with mild cognitive impairment, and people with AD dementia compared with healthy controls. We used data of 247 participants of the prospective DELCODE study, a longitudinal multicenter observational study, imposing a unified fMRI acquisition protocol across sites. We determined cross-validated discrimination accuracy based on penalized logistic regression to account for multicollinearity of predictors. RESULTS: Resting state functional connectivity reached significant cross-validated group discrimination only for the comparison of AD dementia cases with healthy controls, but not for the other diagnostic groups. AD dementia cases showed alterations in a large range of intrinsic resting state networks, including the default mode and salience networks, but also executive and language networks. When groups were stratified according to their CSF amyloid status that was available in a subset of cases, diagnostic accuracy was increased for amyloid positive mild cognitive impairment cases compared with amyloid negative controls, but still inferior to the accuracy of hippocampus volume. CONCLUSION: Even when following a strictly harmonized data acquisition protocol and rigorous scan quality control, widely used connectivity measures of multicenter rs-fMRI do not reach levels of diagnostic accuracy sufficient for a useful biomarker in prodromal stages of AD.

Multiple System Atrophy: An Oligodendroglioneural Synucleinopathy1. - Jellinger, Kurt A (J Alzheimers Dis, 2018)
Multiple system atrophy (MSA) is an orphan, fatal, adult-onset neurodegenerative disorder of uncertain etiology that is clinically characterized by various combinations of parkinsonism, cerebellar, autonomic, and motor dysfunction. MSA is an α-synucleinopathy with specific glioneuronal degeneration involving striatonigral, olivopontocerebellar, and autonomic nervous systems but also other parts of the central and peripheral nervous systems. The major clinical variants correlate with the morphologic phenotypes of striatonigral degeneration (MSA-P) and olivopontocerebellar atrophy (MSA-C). While our knowledge of the molecular pathogenesis of this devastating disease is still incomplete, updated consensus criteria and combined fluid and imaging biomarkers have increased its diagnostic accuracy. The neuropathologic hallmark of this unique proteinopathy is the deposition of aberrant α-synuclein in both glia (mainly oligodendroglia) and neurons forming glial and neuronal cytoplasmic inclusions that cause cell dysfunction and demise. In addition, there is widespread demyelination, the pathogenesis of which is not fully understood. The pathogenesis of MSA is characterized by propagation of misfolded α-synuclein from neurons to oligodendroglia and cell-to-cell spreading in a "prion-like" manner, oxidative stress, proteasomal and mitochondrial dysfunction, dysregulation of myelin lipids, decreased neurotrophic factors, neuroinflammation, and energy failure. The combination of these mechanisms finally results in a system-specific pattern of neurodegeneration and a multisystem involvement that are specific for MSA. Despite several pharmacological approaches in MSA models, addressing these pathogenic mechanisms, no effective neuroprotective nor disease-modifying therapeutic strategies are currently available. Multidisciplinary research to elucidate the genetic and molecular background of the deleterious cycle of noxious processes, to develop reliable biomarkers and targets for effective treatment of this hitherto incurable disorder is urgently needed.

Multivariate Approach for Alzheimer's Disease Detection Using Stationary Wavelet Entropy and Predator-Prey Particle Swarm Optimization. - Zhang, Yudong; Wang, Shuihua; Sui, Yuxiu; Yang, Ming; Liu, Bin; Cheng, Hong; Sun, Junding; Jia, Wenjuan; Phillips, Preetha; Górriz, Juan Manuel (J Alzheimers Dis, 2018)
BACKGROUND: The number of patients with Alzheimer's disease is increasing rapidly every year. Scholars often use computer vision and machine learning methods to develop an automatic diagnosis system. OBJECTIVE: In this study, we developed a novel machine learning system that can make diagnoses automatically from brain magnetic resonance images. METHODS: First, the brain imaging was processed, including skull stripping and spatial normalization. Second, one axial slice was selected from the volumetric image, and stationary wavelet entropy (SWE) was done to extract the texture features. Third, a single-hidden-layer neural network was used as the classifier. Finally, a predator-prey particle swarm optimization was proposed to train the weights and biases of the classifier. RESULTS: Our method used 4-level decomposition and yielded 13 SWE features. The classification yielded an overall accuracy of 92.73±1.03%, a sensitivity of 92.69±1.29%, and a specificity of 92.78±1.51%. The area under the curve is 0.95±0.02. Additionally, this method only cost 0.88 s to identify a subject in online stage, after its volumetric image is preprocessed. CONCLUSION: In terms of classification performance, our method performs better than 10 state-of-the-art approaches and the performance of human observers. Therefore, this proposed method is effective in the detection of Alzheimer's disease.

Neuropathologic Correlates of Psychiatric Symptoms in Alzheimer's Disease. - Ehrenberg, Alexander J; Suemoto, Claudia K; França Resende, Elisa de Paula; Petersen, Cathrine; Leite, Renata Elaine Paraizo; Rodriguez, Roberta Diehl; Ferretti-Rebustini, Renata Eloah de Lucena; You, Michelle; Oh, Jun; Nitrini, Ricardo; Pasqualucci, Carlos Augusto; Jacob-Filho, Wilson; et al. (J Alzheimers Dis, 2018)
Clarifying the relationships between neuropsychiatric symptoms and Alzheimer's disease (AD)-related pathology may open avenues for effective treatments. Here, we investigate the odds of developing neuropsychiatric symptoms across increasing burdens of neurofibrillary tangle and amyloid-β pathology. Participants who passed away between 2004 and 2014 underwent comprehensive neuropathologic evaluation at the Biobank for Aging Studies from the Faculty of Medicine at the University of São Paulo. Postmortem interviews with reliable informants were used to collect information regarding neuropsychiatric and cognitive status. Of 1,092 cases collected, those with any non-Alzheimer pathology were excluded, bringing the cohort to 455 cases. Braak staging was used to evaluate neurofibrillary tangle burden, and the CERAD neuropathology score was used to evaluate amyloid-β burden. The 12-item neuropsychiatric inventory was used to evaluate neuropsychiatric symptoms and CDR-SOB score was used to evaluate dementia status. In Braak I/II, significantly increased odds were detected for agitation, anxiety, appetite changes, depression, and sleep disturbances, compared to controls. Increased odds of agitation continue into Braak III/IV. Braak V/VI is associated with higher odds for delusions. No increased odds for neuropsychiatric symptoms were found to correlate with amyloid-β pathology. Increased odds of neuropsychiatric symptoms are associated with early neurofibrillary tangle pathology, suggesting that subcortical neurofibrillary tangle accumulation with minimal cortical pathology is sufficient to impact quality of life and that neuropsychiatric symptoms are a manifestation of AD biological processes.

Neuropsychiatric Symptoms Complicating the Diagnosis of Alzheimer's Disease: A Case Report. - Eikelboom, Willem S; van Rooij, Jeroen G J; van den Berg, Esther; Coesmans, Michiel; Jiskoot, Lize C; Singleton, Ellen; Ossenkoppele, Rik; van Swieten, John C; Seelaar, Harro; Papma, Janne M (J Alzheimers Dis, 2018)
Neuropsychiatric symptoms (NPS) are increasingly recognized as a core element of Alzheimer's disease (AD); however, clinicians still consider AD primarily as a cognitive disorder. We describe a case in which the underrecognition of NPS as part of AD resulted in substantial delay of an AD diagnosis, a wrong psychiatric diagnosis, and the organization of inappropriate care. The aim of this paper is to acknowledge NPS as an (early) manifestation of AD and to suggest features that may point toward underlying AD in older adults with late-life behavioral changes.

A Nomogram for Predicting Amyloid PET Positivity in Amnestic Mild Cognitive Impairment. - Kim, Si Eun; Woo, Sookyoung; Kim, Seon Woo; Chin, Juhee; Kim, Hee Jin; Lee, Byung In; Park, Jinse; Park, Kyung Won; Kang, Do-Young; Noh, Young; Ye, Byoung Seok; Yoo, Han Soo; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Most clinical trials focus on amyloid-β positive (Aβ+) amnestic mild cognitive impairment (aMCI), but screening failures are high because only a half of patients with aMCI are positive on Aβ PET. Therefore, it becomes necessary for clinicians to predict which patients will have Aβ biomarker. OBJECTIVE: We aimed to compare clinical factors, neuropsychological (NP) profiles, and apolipoprotein E (APOE) genotype between Aβ+ aMCI and Aβ-aMCI and to develop a clinically useful prediction model of Aβ positivity on PET (PET-Aβ+) in aMCI using a nomogram. METHODS: We recruited 523 aMCI patients who underwent Aβ PET imaging in a nation-wide multicenter cohort. The results of NP measures were divided into following subgroups: 1) Stage (Early and Late-stage), 2) Modality (Visual, Verbal, and Both), 3) Recognition failure, and 4) Multiplicity (Single and Multiple). A nomogram for PET-Aβ+ in aMCI patients was constructed using a logistic regression model. RESULTS: PET-Aβ+ had significant associations with NP profiles for several items, including high Clinical Dementia Rating Scale Sum of Boxes score (OR 1.47, p = 0.013) and impaired memory modality (impaired both visual and verbal memories compared with visual only, OR 3.25, p = 0.001). Also, presence of APOEɛ4 (OR 4.14, p < 0.001) was associated with PET-Aβ+. These predictors were applied to develop the nomogram, which showed good prediction performance (C-statistics = 0.79). Its prediction performances were 0.77/0.74 in internal/external validation. CONCLUSIONS: The nomogram consisting of NP profiles, especially memory domain, and APOEɛ4 genotype may provide a useful predictive model of PET-Aβ+ in patients with aMCI.

Observational Study of Clinical and Functional Progression Based on Initial Brain MRI Characteristics in Patients with Alzheimer's Disease. - Choi, Hojin; Yang, YoungSoon; Han, Hyun Jeong; Jeong, Jee Hyang; Park, Mee Young; Kim, Yong Bum; Jo, Kwang Deog; Choi, Jin-Yong; Kang, Kyung-Hun; Kang, Heeyoung; Kwon, Do-Young; Yoo, Bong-Goo; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Magnetic resonance imaging (MRI) is a useful tool to predict the diagnosis and progression of Alzheimer's disease (AD), especially for primary physicians. However, the correlation between baseline MRI findings and AD progression has not been fully established. OBJECTIVE: To investigate the correlation between hippocampal atrophy (HA) and white matter hyperintensities (WMH) on initial brain MRI images and the degree of cognitive decline and functional changes over 1 year. METHODS: In this prospective, 12-month observational study, dementia outpatients were recruited from 29 centers across South Korea. Baseline assessments of HA and WMH on baseline brain MRI were derived as well as cognitive function, dementia severity, activities of daily living, and acetylcholinesterase inhibitor (AChEI) use. Follow-up assessments were conducted at 6 and 12 months. RESULTS: Among 899 enrolled dementia patients, 748 were diagnosed with AD of whom 654 (87%) were taking AChEIs. Baseline WMH showed significant correlations with age, current alcohol consumption, and Clinical Dementia Rating score; baseline HA was correlated with age, family history, physical exercise, and the results of cognitive assessments. Among the AChEI group, changes in the Korean version of the Instrumental Activities of Daily Living (K-IADL) were correlated with the severity of HA on baseline brain MRI, but not with the baseline severity of WMH. In the no AChEI group, changes in K-IADL were correlated with the severity of WMH and HA at baseline. CONCLUSION: Baseline MRI findings could be a useful tool for predicting future clinical outcomes by primary physicians, especially in relation to patients' functional status.

Odor Identification Ability Predicts PET Amyloid Status and Memory Decline in Older Adults. - Kreisl, William Charles; Jin, Peng; Lee, Seonjoo; Dayan, Ezra R; Vallabhajosula, Shankar; Pelton, Gregory; Luchsinger, Jose A; Pradhaban, Gnanavalli; Devanand, D P (J Alzheimers Dis, 2018)
BACKGROUND: Odor identification deficits occur in Alzheimer's disease (AD), as measured by the 40-item University of Pennsylvania Smell Identification Test (UPSIT). OBJECTIVE: To determine if UPSIT scores predict amyloid-β (Aβ) status, determined by 11C-Pittsburgh Compound B PET. We also compared UPSIT scores to Aβ status in predicting future memory decline. METHODS: Subjects were recruited into a longitudinal clinical prediction study. We analyzed data from those who had UPSIT, cognitive testing, PIB PET, and at least 12 months' clinical follow-up. Forty-six amnestic mild cognitive impairment patients and 25 cognitively normal controls were included. Amyloid-positivity was defined as composite PIB standardized uptake value ratio >1.5. Logistic regression and Receiver Operating Characteristic Curve analyses tested the predictive utility of impaired olfaction (defined as UPSIT score <35) and amyloid-positivity for memory decline. RESULTS: High UPSIT scores predicted absence of amyloidosis on PET, with negative predictive value of 100%. Positive predictive value of low UPSIT scores on positive Aβ status was only 41%. Both low UPSIT score (OR = 4.301, 95% CI = 1.248, 14.821, p = 0.021) and positive PET scan (OR = 20.898, 95% CI = 2.222, 196.581, p = 0.008) predicted memory decline. CONCLUSION: Individuals with high UPSIT scores are less likely to have cerebral amyloidosis or experience memory decline. Therefore, UPSIT has potential as a screening tool to determine utility of Aβ PET in clinical practice or enrollment in clinical trials. Low UPSIT score is a non-specific marker of neurodegeneration that could indicate further workup in patients with memory complaints.

Olfactory Function is Associated with Cognitive Performance: Results of the Heinz Nixdorf Recall Study. - Tebrügge, Sarah; Winkler, Angela; Gerards, Diana; Weimar, Christian; Moebus, Susanne; Jöckel, Karl-Heinz; Erbel, Raimund; Jokisch, Martha (J Alzheimers Dis, 2018)
BACKGROUND: There is strong evidence for an association of olfactory dysfunction and neurodegenerative diseases. Studies on the association of olfaction and cognition in the general population are rare. OBJECTIVE: To evaluate gender- and age-specific associations of olfactory function and cognitive performance in a well characterized population-based study sample. METHODS: At the third examination of the Heinz Nixdorf Recall study (n = 3,087), 2,640 participants (48% men; 68.2±7.2 years) underwent Sniffin' Sticks Screening Test measuring olfactory function on a scale of 0-12 points. Olfactory function was rated as anosmic, hyposmic, or normosmic (≤6, 7-10 or ≥11 points, respectively). All participants performed eight validated cognitive subtests. Age- (55-64 years, 65-74 years, 75-86 years) and gender-stratified multivariate analysis of covariance was used to evaluate group differences in cognitive performance. RESULTS: Women showed better olfactory function than men (p < 0.001). For middle-aged participants, olfactory groups differed in almost all cognitive subtests. The analyses revealed no gender effects, although associations were slightly greater for women than for men. Anosmics showed the worst cognitive performance and normosmics showed the best cognitive performance. In the young- and old-aged groups, a quantitative association was found for anosmics in all subtests and for normosmics and hyposmics in almost all subtests. CONCLUSION: This is the first study reporting on age-specific associations of olfactory function and cognitive performance in the general population. The association found in middle-aged participants (65-74 years) may serve as a marker to improve identification of persons at high risk for cognitive decline and dementia.

Pathologically Confirmed Alzheimer's Disease in APOE ɛ2 Homozygotes is Rare but Does Occur. - Stipho, Faissal; Jackson, Robert; Sabbagh, Marwan N (J Alzheimers Dis, 2018)
BACKGROUND: Homozygous APOEɛ4 status is a well-known risk factor in the development of Alzheimer's disease (AD). However, other genotypes of APOE have not yet been found to have equal clinical significance. There is a paucity of reports regarding clinically or pathologically described AD in APOEɛ2 homozygotes compared to the other alleles. OBJECTIVE: To notify clinicians that patients with homozygous APOEɛ2 are also at risk of developing AD based on results from the largest prospectively gathered registry of brain samples to date. METHODS: We queried the National Alzheimer's Coordinating Center (NACC) database for autopsy-confirmed AD cases. Of the Uniform Data Set (UDS) participants who are deceased, 5,779 were diagnosed with dementia at their last UDS visit prior to death, and autopsy data is available for 3,518. RESULTS: Of the brains in the NACC database with pathologically confirmed dementia, seven were found to be homozygous for APOEɛ2, which represents only 0.2% of the autopsy-confirmed sample. Furthermore, pathology-confirmed AD represents 29% (2/7) of the APOEɛ2/ɛ2 patients diagnosed with dementia. CONCLUSIONS: Although rare, autopsy-confirmed AD can be present in APOEɛ2/ɛ2 carriers.

Patterns of Neuropsychological Dysfunction and Cortical Volume Changes in Logopenic Aphasia. - Owens, Tyler E; Machulda, Mary M; Duffy, Joseph R; Strand, Edythe A; Clark, Heather M; Boland, Sarah; Martin, Peter R; Lowe, Val J; Jack, Clifford R; Whitwell, Jennifer L; Josephs, Keith A (J Alzheimers Dis, 2018)
BACKGROUND: Neuropsychological assessment can add essential information to the characterization of individuals presenting with the logopenic variant of primary progressive aphasia (lvPPA). OBJECTIVE: This study examined the neuropsychological characteristics of lvPPA patients. We also examined differences in regional and whole brain atrophy based on neuropsychological profiles. METHODS: We conducted a hierarchical cluster analysis on memory, executive functioning, and visuospatial neuropsychological test data for 56 individuals with lvPPA. We then compared resultant clusters to left middle temporal, inferior parietal, and superior parietal regions-of-interest using multivariate analysis of covariance. We also performed voxel-level analyses. RESULTS: We identified three clusters characterized as lvPPA with no neurocognitive impairment (n = 5), lvPPA with mild neurocognitive deficits (n = 23), and lvPPA with marked cognitive deficits (n = 28). WAB-AQ was associated with left middle temporal volume. Superior parietal volumes were smaller for the lvPPA group with marked cognitive symptoms compared to the less severe groups. Voxel-level analyses showed greater atrophy in temporal, parietal, lateral occipital, and frontal regions, left worse than right. Age, disease duration, gender, WAB-AQ, and PiB-PET did not account for differences between groups. CONCLUSIONS: LvPPA patients without cognitive deficits in other domains were relatively uncommon while 50% of our sample exhibited pronounced neurocognitive deficits outside the language domain. Pronounced cognitive deficits in lvPPA are associated with widespread atrophy, left worse than right. Our study underscores the importance of examining neuropsychological function in addition to language in patients with lvPPA.

Periodontal Pathogens and Associated Intrathecal Antibodies in Early Stages of Alzheimer's Disease. - Laugisch, Oliver; Johnen, Andreas; Maldonado, Alejandra; Ehmke, Benjamin; Bürgin, Walter; Olsen, Ingar; Potempa, Jan; Sculean, Anton; Duning, Thomas; Eick, Sigrun (J Alzheimers Dis, 2018)
BACKGROUND: Recent studies suggest a link between periodontitis and Alzheimer's disease (AD). OBJECTIVE: Verification of the presence of periodontal pathogens and the intrathecal generation of pathogen-specific antibodies in 20 patients with AD and 20 with other forms of dementia (DEM-noAD). METHODS: Clinical periodontal indices were recorded. Cerebrospinal fluid (CSF) was analyzed for total tau protein (T-tau) and amyloid-β (Aβ1-42). In serum and CSF, antibody levels against Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Treponema species were quantified. The presence of selected bacteria and inflammatory biomarkers were determined in periodontium, serum, and CSF. RESULTS: In line with diagnoses, CSF-levels of Aβ1-42 were significantly lower in AD than DEM-noAD patients. Periodontal destruction and inflammation were omnipresent with no difference between groups. P. gingivalis, T. forsythia, and Treponema species were detected in more than 50% of subgingival biofilm samples, but neither in serum nor in the CSF. Elevated levels of anti-pathogen antibodies in CSF of 16 patients (7 AD; 9 DEM-noAD) compared to serum highlight a possibility of the intrathecal immune response to pathogens. There was no significant difference in antibodies levels against selected bacteria in CSF and serum between groups. Multivariate regression analysis and general linear models revealed an association of the T-tau level in AD group with both serum levels of anti-P. gingivalis antibodies and MCP-1/CCL-2. CONCLUSION: Periodontal pathogens may enter the brain and stimulate a local immune response. However, in patients with dementia at the age up to 70 years, periodontal pathogens do not act as a trigger for developing AD.

Pink1 Regulates Tyrosine Hydroxylase Expression and Dopamine Synthesis. - Lu, Lingling; Jia, Huanzhen; Gao, Ge; Duan, Chunli; Ren, Jing; Li, Yi; Yang, Hui (J Alzheimers Dis, 2018)
PTEN induced putative kinase 1 (PINK1), also known as PARK6, is causally linked to familial Parkinsonism, and heterozygous loss of PINK1 is a risk factor for sporadic Parkinson's disease. However, little is known about its physiological function. Its deficiency was shown to decrease dopamine without significant loss of dopaminergic neurons. We investigated the mechanistic basis for this observation in the present study using dopaminergic MN9D cells. We found that PINK1 knockdown resulted in dopamine content to decrease with suppressed tyrosine hydroxylase expression in cells. Conversely, PINK1 overexpression increased tyrosine hydroxylase protein level. We also found that PINK1 deficiency blocked the nuclear translocation and activity of nuclear receptor-related 1, a transcription factor regulating tyrosine hydroxylase gene expression. These data suggest that PINK1 regulates tyrosine hydroxylase gene expression and dopamine content by modulating the transcriptional activity of nuclear receptor-related 1. Taken together, our results reveal a novel function of PINK1 in dopamine homeostasis.

Polypharmacy and Potentially Inappropriate Medication in People with Dementia: A Nationwide Study. - Kristensen, Rachel Underlien; Nørgaard, Ane; Jensen-Dahm, Christina; Gasse, Christiane; Wimberley, Theresa; Waldemar, Gunhild (J Alzheimers Dis, 2018)
BACKGROUND: Polypharmacy (use of ≥5 different medications) and potentially inappropriate medication (PIM) are well-known risk factors for numerous negative health outcomes. However, the use of polypharmacy and PIM in people with dementia is not well-described. OBJECTIVE: To examine the prevalence of polypharmacy and PIM in older people with and without dementia in a nationwide population. METHODS: Cross-sectional study of the Danish population aged ≥65 in 2014 (n = 1,032,120) based on register data, including information on diagnoses and dispensed prescriptions. Polypharmacy and PIM use among people with (n = 35,476) and without dementia (n = 994,231) were compared, stratified by living situation and adjusted for age, sex, and comorbidity. The red-yellow-green list from the Danish Institute for Rational Pharmacotherapy and the German PRISCUS list were used to define PIM. RESULTS: People with dementia were more frequently exposed to polypharmacy (dementia: 62.6% versus no-dementia: 35.1%, p < 0.001) and likewise PIM (red-yellow-green: 45.0% versus 29.7%, p < 0.001; PRISCUS: 24.4% versus 13.2%, p < 0.001). After adjustments for age, sex, and comorbidity, the likelihood of polypharmacy and PIM was higher for community-dwelling people with dementia than without dementia (odds ratio (OR); [95% confidence interval (CI)] polypharmacy: 1.50 [1.45-1.55]; red-yellow-green: 1.27 [1.23-1.31]; PRISCUS: 1.25 [1.20-1.30]). In contrast, dementia slightly decreased the odds of polypharmacy and PIM in nursing home residents. CONCLUSION: Use of polypharmacy and PIM were widespread in the older population and more so in people with dementia. This could have negative implications for patient-safety and demonstrates the need for interventions to improve drug therapy in people with dementia.

Potential of Low Dose Leuco-Methylthioninium Bis(Hydromethanesulphonate) (LMTM) Monotherapy for Treatment of Mild Alzheimer's Disease: Cohort Analysis as Modified Primary Outcome in a Phase III Clinical Trial. - Wilcock, Gordon K; Gauthier, Serge; Frisoni, Giovanni B; Jia, Jianping; Hardlund, Jiri H; Moebius, Hans J; Bentham, Peter; Kook, Karin A; Schelter, Bjoern O; Wischik, Damon J; Davis, Charles S; Staff, Roger T; et al. (J Alzheimers Dis, 2018)
BACKGROUND: LMTM is being developed as a treatment for AD based on inhibition of tau aggregation. OBJECTIVES: To examine the efficacy of LMTM as monotherapy in non-randomized cohort analyses as modified primary outcomes in an 18-month Phase III trial in mild AD. METHODS: Mild AD patients (n = 800) were randomly assigned to 100 mg twice a day or 4 mg twice a day. Prior to unblinding, the Statistical Analysis Plan was revised to compare the 100 mg twice a day as monotherapy subgroup (n = 79) versus 4 mg twice a day as randomized (n = 396), and 4 mg twice a day as monotherapy (n = 76) versus 4 mg twice a day as add-on therapy (n = 297), with strong control of family-wise type I error. RESULTS: The revised analyses were statistically significant at the required threshold of p < 0.025 in both comparisons for change in ADAS-cog, ADCS-ADL, MRI atrophy, and glucose uptake. The brain atrophy rate was initially typical of mild AD in both add-on and monotherapy groups, but after 9 months of treatment, the rate in monotherapy patients declined significantly to that reported for normal elderly controls. Differences in severity or diagnosis at baseline between monotherapy and add-on patients did not account for significant differences in favor of monotherapy. CONCLUSIONS: The results are consistent with earlier studies in supporting the hypothesis that LMTM might be effective as monotherapy and that 4 mg twice a day may serve as well as higher doses. A further suitably randomized trial is required to test this hypothesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antipsychotic Agents; Cohort Studies; Double-Blind Method; Female; Humans; International Cooperation; Male; Mental Status and Dementia Tests; Methylene Blue; Middle Aged; Treatment Outcome

A Precision Medicine Model for Targeted NSAID Therapy in Alzheimer's Disease. - O'Bryant, Sid E; Zhang, Fan; Johnson, Leigh A; Hall, James; Edwards, Melissa; Grammas, Paula; Oh, Esther; Lyketsos, Constantine G; Rissman, Robert A (J Alzheimers Dis, 2018)
BACKGROUND: To date, the therapeutic paradigm for Alzheimer's disease (AD) has focused on a single intervention for all patients. However, a large literature in oncology supports the therapeutic benefits of a precision medicine approach to therapy. Here we test a precision-medicine approach to AD therapy. OBJECTIVE: To determine if a baseline, blood-based proteomic companion diagnostic predicts response to NSAID therapy. METHODS: Proteomic assays of plasma from a multicenter, randomized, double-blind, placebo-controlled, parallel group trial, with 1-year exposure to rofecoxib (25 mg once daily), naproxen (220 mg twice-daily) or placebo. RESULTS: 474 participants with mild-to-moderate AD were screened with 351 enrolled into the trial. Using support vector machine (SVM) analyses, 89% of the subjects randomized to either NSAID treatment arms were correctly classified using a general NSAID companion diagnostic. Drug-specific companion diagnostics yielded 98% theragnostic accuracy in the rofecoxib arm and 97% accuracy in the naproxen arm. CONCLUSION: Inflammatory-based companion diagnostics have significant potential to identify select patients with AD who have a high likelihood of responding to NSAID therapy. This work provides empirical support for a precision medicine model approach to treating AD.

Predicting and Tracking Short Term Disease Progression in Amnestic Mild Cognitive Impairment Patients with Prodromal Alzheimer's Disease: Structural Brain Biomarkers. - Marizzoni, Moira; Ferrari, Clarissa; Jovicich, Jorge; Albani, Diego; Babiloni, Claudio; Cavaliere, Libera; Didic, Mira; Forloni, Gianluigi; Galluzzi, Samantha; Hoffmann, Karl-Titus; Molinuevo, José Luis; Nobili, Flavio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Early Alzheimer's disease (AD) detection using cerebrospinal fluid (CSF) biomarkers has been recommended as enrichment strategy for trials involving mild cognitive impairment (MCI) patients. OBJECTIVE: To model a prodromal AD trial for identifying MRI structural biomarkers to improve subject selection and to be used as surrogate outcomes of disease progression. METHODS: APOE ɛ4 specific CSF Aβ42/P-tau cut-offs were used to identify MCI with prodromal AD (Aβ42/P-tau positive) in the WP5-PharmaCog (E-ADNI) cohort. Linear mixed models were performed 1) with baseline structural biomarker, time, and biomarker×time interaction as factors to predict longitudinal changes in ADAS-cog13, 2) with Aβ42/P-tau status, time, and Aβ42/P-tau status×time interaction as factors to explain the longitudinal changes in MRI measures, and 3) to compute sample size estimation for a trial implemented with the selected biomarkers. RESULTS: Only baseline lateral ventricle volume was able to identify a subgroup of prodromal AD patients who declined faster (interaction, p = 0.003). Lateral ventricle volume and medial temporal lobe measures were the biomarkers most sensitive to disease progression (interaction, p≤0.042). Enrichment through ventricular volume reduced the sample size that a clinical trial would require from 13 to 76%, depending on structural outcome variable. The biomarker needing the lowest sample size was the hippocampal subfield GC-ML-DG (granule cells of molecular layer of the dentate gyrus) (n = 82 per arm to demonstrate a 20% atrophy reduction). CONCLUSION: MRI structural biomarkers can enrich prodromal AD with fast progressors and significantly decrease group size in clinical trials of disease modifying drugs.

Proteomic Profiling of Mouse Brains Exposed to Blast-Induced Mild Traumatic Brain Injury Reveals Changes in Axonal Proteins and Phosphorylated Tau. - Chen, Mei; Song, Hailong; Cui, Jiankun; Johnson, Catherine E; Hubler, Graham K; DePalma, Ralph G; Gu, Zezong; Xia, Weiming (J Alzheimers Dis, 2018)
Alzheimer's disease (AD), the most prevalent form of dementia, is characterized by two pathological hallmarks: Tau-containing neurofibrillary tangles and amyloid-β protein (Aβ)-containing neuritic plaques. The goal of this study is to understand mild traumatic brain injury (mTBI)-related brain proteomic changes and tau-related biochemical adaptations that may contribute to AD-like neurodegeneration. We found that both phosphorylated tau (p-tau) and the ratio of p-tau/tau were significantly increased in brains of mice collected at 3 and 24 h after exposure to 82-kPa low-intensity open-field blast. Neurological deficits were observed in animals at 24 h and 7 days after the blast using Simple Neuroassessment of Asymmetric imPairment (SNAP) test, and axon/dendrite degeneration was revealed at 7 days by silver staining. Liquid chromatography-mass spectrometry (LC-MS/MS) was used to analyze brain tissue labeled with isobaric mass tags for relative protein quantification. The results from the proteomics and bioinformatic analysis illustrated the alterations of axonal and synaptic proteins in related pathways, including but not being limited to substantia nigra development, cortical cytoskeleton organization, and synaptic vesicle exocytosis, suggesting a potential axonal damage caused by blast-induced mTBI. Among altered proteins found in brains suffering blast, microtubule-associated protein 1B, stathmin, neurofilaments, actin binding proteins, myelin basic protein, calcium/calmodulin-dependent protein kinase, and synaptotagmin I were representative ones involved in altered pathways elicited by mTBI. Therefore, TBI induces elevated phospho-tau, a pathological feature found in brains of AD, and altered a number of neurophysiological processes, supporting the notion that blast-induced mTBI as a risk factor contributes to AD pathogenesis. LC/MS-based profiling has presented candidate target/pathways that could be explored for future therapeutic development.

Psychological and Mnemonic Benefits of Nostalgia for People with Dementia. - Ismail, Sanda; Christopher, Gary; Dodd, Emily; Wildschut, Tim; Sedikides, Constantine; Ingram, Tom A; Jones, Roy W; Noonan, Krist A; Tingley, Danielle; Cheston, Richard (J Alzheimers Dis, 2018)
BACKGROUND: Studies with non-clinical populations show that nostalgia increases psychological resources, such as self-esteem and social connectedness. OBJECTIVES: Our objectives were to find out if the benefits of nostalgia in non-clinical populations generalize to people with dementia and if nostalgia facilitates recall of dementia-related information. METHODS: All three experiments recruited participants with mild or moderate levels of dementia. Experiment 1 tested whether nostalgia (compared to control) enhances psychological resources among 27 participants. Experiment 2 used music to induce nostalgia (compared to control) in 29 participants. Experiment 3 compared recall for self-referent dementia statements among 50 participants randomized to either a nostalgia or control condition. Findings across experiments were synthesized with integrative data analysis. RESULTS: Nostalgia (compared to control) significantly increased self-reported social connectedness, meaning in life, self-continuity, optimism, self-esteem, and positive (but not negative) affect (Experiments 1-3). Compared to controls, nostalgic participants also recalled significantly more self-referent dementia-related information (Experiment 3). CONCLUSION: This series of experiments extends social psychological research with non-clinical populations into dementia care, providing evidence that nostalgia significantly enhances psychological resources. The finding that nostalgia increased recall of self-referent statements about dementia suggests that this emotion lends participants the fortitude to face the threat posed by their illness. The finding has potentially important clinical implications both for the development of reminiscence therapy and for facilitating adjustment to a diagnosis of dementia.

Quality of Life, Care Resource Use, and Costs of Dementia in 8 European Countries in a Cross-Sectional Cohort of the Actifcare Study. - Handels, Ron L H; Sköldunger, Anders; Bieber, Anja; Edwards, Rhiannon Tudor; Gonçalves-Pereira, Manuel; Hopper, Louise; Irving, Kate; Jelley, Hannah; Kerpershoek, Liselot; Marques, Maria J; Meyer, Gabriele; Michelet, Mona; et al. (J Alzheimers Dis, 2018)
BACKGROUND: With 10.5 million people with dementia in Europe and $301 billion associated costs, governments face challenges organizing access to care. OBJECTIVE: To examine the costs related to formal and informal care use and quality of life for people with dementia in eight European countries, and explore the association with unmet needs. METHODS: Cross-sectional data from 451 persons with dementia and their informal caregivers of the Actifcare cohort study were obtained. Formal and informal care use was multiplied by country specific unit prices of services. Needs were measured using the CANE and health-related quality of life (HRQOL) of the person with dementia (both self- and proxy-rated) and informal caregiver's quality of life using EQ-5D-5L, ICECAP-O, DEMQOL-U, and CarerQol utility scores. The association between costs and country, European region, and unmet needs was assessed using multi-level linear regression. RESULTS: Self-rated EQ-5D-5L utility score was higher than proxy-rated (0.84 and 0.71, respectively). Informal caregivers' utility score was 0.84. Across eight countries annual mean costs of formal and informal care were approximately € 17,000. Unmet needs were not associated with annual costs of care, nor with proxy-rated HRQOL, but were associated with self-rated HRQOL. CONCLUSION: We found varying relationships between unmet needs and quality of life, and no association between unmet needs and care costs, although the results were sensitive to various factors. Future research should further investigate the relation between unmet needs, quality of life and costs to generate a better understanding of the effects of (un)timely access to care.

Quantifying the Diagnostic Pathway for Patients with Cognitive Impairment: Real-World Data from Seven European and North American Countries. - Ritchie, Craig W; Black, Christopher M; Khandker, Rezaul K; Wood, Robert; Jones, Eddie; Hu, Xiaohan; Ambegaonkar, Baishali M (J Alzheimers Dis, 2018)
To ensure that patients with dementia and their caregivers receive appropriate treatment and support, early diagnosis is essential but remains challenging. Real-world data from a multi-national, cross-sectional survey of physicians and their patients were analyzed to quantify the diagnostic pathway for dementia, including a focus on severity of patients' cognitive impairment (CI) at the time of symptom onset, referral and subsequent diagnosis. Data were collected for 7,620 patients with CI. Most patients saw a healthcare professional within 1 year of first symptoms and received a diagnosis within 3-7 months of initial consultation. However, only 20% of patients received a diagnosis before their disease progressed beyond the prodromal stage and 23.5% already had moderate CI at diagnosis. These findings show that the goal of identifying and diagnosing CI at the earliest stages of disease is, for many patients, not achieved. Efforts toward public awareness and proactive, earlier detection and intervention, must be maintained-indeed where possible invigorated.

Quantitative Genetics Validates Previous Genetic Variants and Identifies Novel Genetic Players Influencing Alzheimer's Disease Cerebrospinal Fluid Biomarkers. - Ramos de Matos, Mafalda; Ferreira, Catarina; Herukka, Sanna-Kaisa; Soininen, Hilkka; Janeiro, André; Santana, Isabel; Baldeiras, Ines; Almeida, Maria Rosário; Lleo, Alberto; Dols-Icardo, Oriol; Alcolea, Daniel; Benussi, Luisa; et al. (J Alzheimers Dis, 2018)
Cerebrospinal fluid (CSF) biomarkers have been extensively investigated in the Alzheimer's disease (AD) field, and are now being applied in clinical practice. CSF amyloid-beta (Aβ1-42), total tau (t-tau), and phosphorylated tau (p-tau) reflect disease pathology, and may be used as quantitative traits for genetic analyses, fostering the identification of new genetic factors and the proposal of novel biological pathways of the disease. In patients, the concentration of CSF Aβ1-42 is decreased due to the accumulation of Aβ1-42 in amyloid plaques in the brain, while t-tau and p-tau levels are increased, indicating the extent of neuronal damage. To better understand the biological mechanisms underlying the regulation of AD biomarkers, and its relation to AD, we examined the association between 36 selected single nucleotide polymorphisms (SNPs) and AD biomarkers Aβ1-42, t-tau, and p-tau in CSF in a cohort of 672 samples (571 AD patients and 101 controls) collected within 10 European consortium centers.Our results highlighted five genes, APOE, LOC100129500, PVRL2, SNAR-I, and TOMM40, previously described as main players in the regulation of CSF biomarkers levels, further reinforcing a role for these in AD pathogenesis. Three new AD susceptibility loci, INPP5D, CD2AP, and CASS4, showed specific association with CSF tau biomarkers. The identification of genes that specifically influence tau biomarkers point out to mechanisms, independent of amyloid processing, but in turn related to tau biology that may open new venues to be explored for AD treatment.

Quantitative Susceptibility Mapping of Amyloid-β Aggregates in Alzheimer's Disease with 7T MR. - Tiepolt, Solveig; Schäfer, Andreas; Rullmann, Michael; Roggenhofer, Elisabeth; Gertz, Hermann-Josef; Schroeter, Matthias L; Patt, Marianne; Bazin, Pierre-Louis; Jochimsen, Thies H; Turner, Robert; Sabri, Osama; Barthel, Henryk (J Alzheimers Dis, 2018)
BACKGROUND: PET imaging is an established technique to detect cerebral amyloid-β (Aβ) plaques in vivo. Some preclinical and postmortem data report an accumulation of redox-active iron near Aβ plaques. Quantitative susceptibility mapping (QSM) at high-field MRI enables iron deposits to be depicted with high spatial resolution. OBJECTIVE: Aim of this study was to examine whether iron and Aβ plaque accumulation is related and thus, whether 7T MRI might be an additive diagnostic tool to Aβ PET imaging. METHODS: Postmortem human Alzheimer's disease (AD) and healthy control (HC) frontal gray matter (GM) was imaged with 7T MRI which resulted in T1 maps and QSM. Aβ plaque load was determined by histopathology. In vivo, 10 Aβ PET-positive AD patients (74.1±6.0a) and 10 Aβ PET-negative HCs (67.1±4.4a) underwent 7T MR examination and QSM maps were analyzed. Severity of cognitive deficits was determined by MMSE. RESULTS: Postmortem, the susceptibility of Aβ plaque-containing GM were higher than those of Aβ plaque-free GM (0.011±0.002 versus - 0.008±0.003 ppm, p < 0.001). In vivo, only the bilateral globus pallidus showed significantly higher susceptibility in AD patients compared to HCs (right: 0.277±0.018 versus - 0.009±0.009 ppm; left: 0.293±0.014 versus - 0.007±0.012 ppm, p < 0.0001). The pallidal QSM values were negatively correlated with those of the MMSE (r = - 0.69, p = 0.001). CONCLUSION: The postmortem study revealed significant susceptibility differences between the Aβ plaque-containing and Aβ plaque-free GM, whereas in vivo only the QSM values of the globus pallidus differed significantly between AD and HC group. The pallidal QSM values correlated with the severity of cognitive deficits. These findings encourage efforts to optimize the 7T-QSM methodology.

Real-World, Multinational, Retrospective Observational Survey of the ADAS-Cog and Associations with Healthcare Resource Utilization in Patients with Alzheimer's Disease. - Ritchie, Craig W; Khandker, Rezaul K; Pike, James; Black, Christopher M; Jones, Eddie; Ambegaonkar, Baishali M (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is one of the most costly conditions, both economically and regarding patient disability and dependency. The huge costs coupled with the predicted increase in prevalence worldwide are likely to challenge healthcare systems in the future. The classic version of the Alzheimer's Disease Assessment Scale-Cognition subscale (ADAS-Cog) is generally seen as the current gold standard primary outcome measure of cognitive symptom progression in dementia clinical trials. OBJECTIVE: This study evaluated the relationship between ADAS-Cog scores as a measure of clinical progression and the healthcare resource utilization (HCRU)-measured burden of cognitive impairment in patients with mild cognitive impairment, AD, or suspected AD in the real world. METHODS: A retrospective observational survey of physicians and their consulting patients with multiple ADAS-Cog scores. Regression models were constructed for HCRU variables (e.g., consultations, hospitalizations, caregiving requirements) with ADAS-Cog rate of change, baseline ADAS-Cog, and their interaction included as exposure variables. RESULTS: 651 patient records were completed by 154 physicians. Approximately 70% of patients had mild to moderate dementia. In 56.7% of patients, clinical progression was maintained/stable from baseline. Mean change in ADAS-Cog (adjusted to 12 months) was 2.8 points and change scores increased with increasing dementia severity. Most HCRU variables increased significantly (p < 0.05; joint test) with increasing ADAS-Cog scores (indexing clinical deterioration). CONCLUSION: The results suggest that further understanding the relationship between HCRU and ADAS-Cog changes in real-world clinical practice could potentially provide a baseline upon which the success of disease-modifying, as well as newer symptomatic, dementia therapies can be judged.

Reduced Cerebrovascular Reserve Capacity as a Biomarker of Microangiopathy in Alzheimer's Disease and Mild Cognitive Impairment. - Urbanova, Barbora Soukupova; Schwabova, Jaroslava Paulasova; Magerova, Hana; Jansky, Petr; Marková, Hana; Vyhnálek, Martin; Laczó, Jan; Hort, Jakub; Tomek, Ales (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral microangiopathy in Alzheimer's disease (AD) causes chronic hypoperfusion and probably accelerates neurodegenerative changes. OBJECTIVE: We hypothesize microvascular impairment could be present already in mild cognitive impairment (MCI) and can be revealed using transcranial color-coded sonography (TCCS) and the breath-holding maneuver. METHODS: Three groups of subjects (AD in the stage of dementia, MCI, and cognitively normal controls) with detailed neuropsychological testing and low cerebrovascular burden (no history of stroke, no intra- or extracranial artery stenoses, and no severe vascular lesions on brain MRI), underwent a TCCS assessment of peak systolic (PSV), mean flow (MFV), and end diastolic velocities (EDV) and resistance and pulsatility indices (RI, PI) in large intracranial vessels bilaterally. Cerebrovascular reserve capacity was assessed using the breath-holding index (BHI) in middle cerebral artery (MCA) bilaterally. The ultrasound parameters were compared between the groups, correlated with neuropsychological tests, and compared between amnestic and non-amnestic MCI subtypes. RESULTS: Fourteen AD (3 males, 67.9±11.1 years, MMSE 18.0±4.6), 24 MCI (13 males, 71.9±7.3 years, MMSE 28.0±1.6), and 24 risk factor-matched controls (14 males, 67.8±6.4 years, MMSE 29.1±1.2) were enrolled. Significant differences were found between AD and controls in MFV, EDV, RI, PI in right MCA after breath holding, in PSV, MFV, EDV in left MCA after breath holding, and in BHI on the left side. The left BHI correlated positively with verbal memory test. CONCLUSION: Results show decreased cerebrovascular reserve capacity in AD as a sign of impaired cerebral hemodynamic status without severe underlying atherosclerosis. This can be identified using TCCS and BHI.

Regional Distribution, Asymmetry, and Clinical Correlates of Tau Uptake on [18F]AV-1451 PET in Atypical Alzheimer's Disease. - Tetzloff, Katerina A; Graff-Radford, Jonathan; Martin, Peter R; Tosakulwong, Nirubol; Machulda, Mary M; Duffy, Joseph R; Clark, Heather M; Senjem, Matthew L; Schwarz, Christopher G; Spychalla, Anthony J; Drubach, Daniel A; Jack, Clifford R; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Despite common pathology, Alzheimer's disease (AD) can have multiple clinical presentations which pathological studies suggest result from differences in the regional distribution of tau pathology. Positron emission tomography (PET) ligands are now available that can detect tau proteins in vivo and hence can be used to investigate the biological mechanisms underlying atypical AD. OBJECTIVE: To assess regional patterns of tau uptake on PET imaging in two atypical AD variants, posterior cortical atrophy (PCA) and logopenic progressive aphasia (lvPPA). METHODS: Eighteen PCA and 19 lvPPA subjects that showed amyloid-β deposition on PET underwent tau-PET imaging with [18F]AV-1451. Group comparisons of tau uptake in PCA and lvPPA were performed using voxel-level and regional-level analyses. We also assessed the degree of lobar tau asymmetry and correlated regional tau uptake to age and performance on clinical evaluations. RESULTS: Both syndromes showed diffuse tau uptake throughout all cortical regions, although PCA showed greater uptake in occipital regions compared to lvPPA, and lvPPA showed greater uptake in left frontal and temporal regions compared to PCA. While lvPPA showed predominant left-asymmetric tau deposition, PCA was more bilateral. Younger subjects showed greater tau uptake bilaterally in frontal and parietal lobes than older subjects, and sentence repetition, Boston naming test, simultanagnosia, and visuoperceptual function showed specific regional tau correlates. CONCLUSION: Tau deposition is closely related to clinical presentation in atypical AD with age playing a role in determining the degree of cortical tau deposition.

The Relevance of Iron in the Pathogenesis of Multiple System Atrophy: A Viewpoint. - Kaindlstorfer, Christine; Jellinger, Kurt A; Eschlböck, Sabine; Stefanova, Nadia; Weiss, Günter; Wenning, Gregor K (J Alzheimers Dis, 2018)
Iron is essential for cellular development and maintenance of multiple physiological processes in the central nervous system. The disturbance of its homeostasis leads to abnormal iron deposition in the brain and causes neurotoxicity via generation of free radicals and oxidative stress. Iron toxicity has been established in the pathogenesis of Parkinson's disease; however, its contribution to multiple system atrophy (MSA) remains elusive. MSA is characterized by cytoplasmic inclusions of misfolded α-synuclein (α-SYN) in oligodendrocytes referred to as glial cytoplasmic inclusions (GCIs). Remarkably, the oligodendrocytes possess high amounts of iron, which together with GCI pathology make a contribution toward MSA pathogenesis likely. Consistent with this observation, the GCI density is associated with neurodegeneration in central autonomic networks as well as olivopontocerebellar and striatonigral pathways. Iron converts native α-SYN into a β-sheet conformation and promotes its aggregation either directly or via increasing levels of oxidative stress. Interestingly, α-SYN possesses ferrireductase activity and α-SYN expression underlies iron mediated translational control via RNA stem loop structures. Despite a correlation between progressive putaminal atrophy and iron accumulation as well as clinical decline, it remains unclear whether pathologic iron accumulation in MSA is a secondary event in the cascade of neuronal degeneration rather than a primary cause. This review summarizes the current knowledge of iron in MSA and gives evidence for perturbed iron homeostasis as a potential pathogenic factor in MSA-associated neurodegeneration.
Keywords: alpha-Synuclein; Brain; Humans; Inclusion Bodies; Iron; Magnetic Resonance Imaging; Multiple System Atrophy; Oligodendroglia; Parkinsonian Disorders

A Review of the Familial Alzheimer's Disease Locus PRESENILIN 2 and Its Relationship to PRESENILIN 1. - Jiang, Haowei; Jayadev, Suman; Lardelli, Michael; Newman, Morgan (J Alzheimers Dis, 2018)
PRESENILIN 1 (PSEN1) and PRESENILIN 2 (PSEN2) genes are loci for mutations causing familial Alzheimer's disease (fAD). However, the function of these genes and how they contribute to fAD pathogenesis has not been fully determined. This review provides a summary of the overlapping and independent functions of the PRESENILINS with a focus on the lesser studied PSEN2. As a core component of the γ-secretase complex, the PSEN2 protein is involved in many γ-secretase-related physiological activities, including innate immunity, Notch signaling, autophagy, and mitochondrial function. These physiological activities have all been associated with AD progression, indicating that PSEN2 plays a particular role in AD pathogenesis.

Role of the Glyoxalase System in Alzheimer's Disease. - Jiang, Lianying; Wang, Jiafeng; Wang, Zhigang; Huang, Wenhui; Yang, Yixia; Cai, Zhiyou; Li, Keshen (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is an insidious and progressive neurodegenerative disease. The main pathological features of AD are the formation of amyloid-β deposits in the anterior cerebral cortex and hippocampus as well as the formation of intracellular neurofibrillary tangles. Thus far, accumulating evidence shows that glycation is closely related to AD. As a final product resulting from the crosslinking of a reducing sugar or other reactive carbonyls and a protein, the advanced glycation end products have been found to be associated with the formation of amyloid-β and neurofibrillary tangles in AD. As a saccharification inhibitor, the glyoxalase system and its substrate methylglyoxal (MG) were certified to be associated with AD onset and development. As an active substance of AGEs, MG could cause direct or indirect damage to nerve cells and tissues. MG is converted to D-lactic acid after decomposition by the glyoxalase system. Under normal circumstances, MG metabolism is in a dynamic equilibrium, whereas MG accumulates in cells in the case of aging or pathological states. Studies have shown that increasing glyoxalase activity and reducing the MG level can inhibit the generation of oxidative stress and AGEs, thereby alleviating the symptoms and signs of AD to some extent. This paper focuses on the relevant mechanisms of action of the glyoxalase system and MG in the pathogenesis of AD, as well as the potential of inhibiting the production of advanced glycation end products in the treatment of AD.

S-[18F]THK-5117-PET and [11C]PIB-PET Imaging in Idiopathic Normal Pressure Hydrocephalus in Relation to Confirmed Amyloid-β Plaques and Tau in Brain Biopsies. - Leinonen, Ville; Rauramaa, Tuomas; Johansson, Jarkko; Bottelbergs, Astrid; Tesseur, Ina; van der Ark, Peter; Pemberton, Darrel; Koivisto, Anne M; Jääskeläinen, Juha E; Hiltunen, Mikko; Herukka, Sanna-Kaisa; Blennow, Kaj; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Detection of pathological tau aggregates could facilitate clinical diagnosis of Alzheimer's disease (AD) and monitor drug effects in clinical trials. S-[18F]THK-5117 could be a potential tracer to detect pathological tau deposits in brain. However, no previous study have correlated S-[18F]THK-5117 uptake in PET with brain biopsy verified tau pathology in vivo. OBJECTIVE: Here we aim to evaluate the association between cerebrospinal fluid (CSF) AD biomarkers, S-[18F]THK-5117, and [11C]PIB PET against tau and amyloid lesions in brain biopsy. METHODS: Fourteen patients with idiopathic normal pressure hydrocephalus (iNPH) with previous shunt surgery including right frontal cortical brain biopsy and CSF Aβ1 - 42, total tau, and P-tau181 measures, underwent brain MRI, [11C]PIB PET, and S-[18F]THK-5117 PET imaging. RESULTS: Seven patients had amyloid-β (Aβ, 4G8) plaques, two both Aβ and phosphorylated tau (Pτ, AT8) and one only Pτ in biopsy. As expected, increased brain biopsy Aβ was well associated with higher [11C]PIB uptake in PET. However, S-[18F]THK-5117 uptake did not show any statistically significant correlation with either brain biopsy Pτ or CSF P-tau181 or total tau. CONCLUSIONS: S-[18F]THK-5117 lacked clear association with neuropathologically verified tau pathology in brain biopsy probably, at least partially, due to off-target binding. Further studies with larger samples of patients with different tau tracers are urgently needed. The detection of simultaneous Aβ and tau pathology in iNPH is important since that may indicate poorer and especially shorter response for CSF shunt surgery compared with no pathology.

Sex-Related Reserve Hypothesis in Alzheimer's Disease: Changes in Cortical Thickness with a Five-Year Longitudinal Follow-Up. - Lee, Juyoun; Cho, Hanna; Jeon, Seun; Kim, Hee Jin; Kim, Yeo Jin; Lee, Jeongmin; Kim, Sung Tae; Lee, Jong-Min; Chin, Juhee; Lockhart, Samuel N; Lee, Ae Young; Na, Duk L; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Sex effects on the progression of Alzheimer's disease (AD) have received less attention than other demographic factors, including onset age and education. OBJECTIVE: The aim of this study was to investigate whether sex affected cortical thinning in the disease progression of AD. METHODS: We prospectively recruited 36 patients with early-stage AD and 14 people with normal cognition. All subjects were assessed with magnetic resonance imaging at baseline, Year 1, Year 3, and Year 5. We performed cortical thickness analyses using surface-based morphometry on magnetic resonance imaging. RESULTS: Women with AD showed more rapid cortical thinning in the left dorsolateral frontal cortex, left superior temporal gyrus, bilateral temporo-parietal association cortices, bilateral anterior cingulate gyri, bilateral medial frontal cortices, and bilateral occipital cortices over 5 years than men with AD, even though there was no difference in cortical thickness at baseline. In contrast, there were no regions of significantly more rapid atrophy in men with AD. CONCLUSIONS: Our findings suggest that women deteriorate faster than men in the progression of AD.

SIRT1 Deacetylates SC35 and Suppresses Its Function in Tau Exon 10 Inclusion. - Yin, Xiaomin; Jiang, Xiaosu; Wang, Jia; Qian, Shuo; Liu, Fei; Qian, Wei (J Alzheimers Dis, 2018)
Approximately equal amounts of 3R-tau and 4R-tau resulting from alternative splicing of tau exon 10 is necessary to maintain normal brain function. Dysregulation of alternative splicing of tau exon 10 and the imbalance of 3R-tau/4R-tau have been seen in inherited and sporadic tauopathies. Splicing factor SC35 (also name as SRSF2) plays an important role in promoting tau exon 10 inclusion. SC35 is post-translationally modified by phosphorylation and acetylation, but the role of acetylation in SC35-medicated tau exon 10 inclusion is unknown. Sirtuin type 1 (SIRT1) is an enzyme that deacetylates proteins and associates with age-related disease such as Alzheimer's disease. In the present study, we determined the role of SIRT1 in SC35 acetylation and in the alternative splicing of tau exon 10. We found that SIRT1 interacts with and deacetylates SC35, and inhibits SC35-promoted tau exon 10 inclusion. Substituting K52 residue of SC35 by arginine impairs the role of SC35 in tau exon 10 inclusion. These results suggest that SIRT1 may serve as a therapeutic target for tauopathy by regulating SC35-mediated tau exon 10 splicing.
Keywords: Alternative Splicing; Alzheimer Disease; Exons; HEK293 Cells; HeLa Cells; Humans; Phosphorylation; Ribonucleoproteins; Serine-Arginine Splicing Factors; Sirtuin 1; tau Proteins; Tauopathies

Some Methodological Characteristics of Alzheimer-Associated Urine Neuronal Thread Protein Detected by Enzyme-Linked Immunosorbent Assay. - Jin, He; Wang, Rong; Liu, Zhaohui; Jia, Qiang; Wu, Yanchuan; Zhao, Zhiwei; Wang, Yulan; Zhang, Xu (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer-associated neuronal thread protein (AD7c-NTP) has been found to be a candidate biomarker of Alzheimer's disease (AD). OBJECTIVE: To investigate the effects of urine collected time, different preservatives addition, and storage condition on the measurement of urine AD7c-NTP by enzyme-linked immunosorbent assay (ELISA). METHODS: Three hundred urine samples were collected from 20 participants at three time points on five consecutive days. These samples were immediately placed at 4°C and detected within 2 h. The single spot samples of the first day morning were split into eleven duplicate aliquots (a-k) of 1 ml each, (a) without any preservative (untreated), (b) containing boric acid (2 g/L), (c) containing NaHCO3 (5 g/L), (a-c) were detected at six different time points. For the other eight preservative-free samples, (d-g) were stored at -20°C and (h-k) were stored at -70°C, respectively, detected at different time points. All of the results were compared with the baseline urine. RESULTS: The urine AD7c-NTP levels at different time points behaved stably (p > 0.05). Urine samples without any preservative increased over time, and compared with the NaHCO3 addition group, boric acid addition group behaved stably. Samples stored at -20°C and -70°C led to an obviously false positive. CONCLUSIONS: AD7c-NTP can be tested using random urine instead of the first morning urine. If the specimen cannot be tested in time, boric acid appears to be an acceptable preservative with storage at 4°C, freezing is not recommended.

Stabilized Low-n Amyloid-β Oligomers Induce Robust Novel Object Recognition Deficits Associated with Inflammatory, Synaptic, and GABAergic Dysfunction in the Rat. - Watremez, William; Jackson, Joshua; Almari, Bushra; McLean, Samantha L; Grayson, Ben; Neill, Joanna C; Fischer, Nicolas; Allouche, Ahmad; Koziel, Violette; Pillot, Thierry; Harte, Michael K (J Alzheimers Dis, 2018)
BACKGROUND: With current treatments for Alzheimer's disease (AD) only providing temporary symptomatic benefits, disease modifying drugs are urgently required. This approach relies on improved understanding of the early pathophysiology of AD. A new hypothesis has emerged, in which early memory loss is considered a synapse failure caused by soluble amyloid-β oligomers (Aβo). These small soluble Aβo, which precede the formation of larger fibrillar assemblies, may be the main cause of early AD pathologies. OBJECTIVE: The aim of the current study was to investigate the effect of acute administration of stabilized low-n amyloid-β1-42 oligomers (Aβo1-42) on cognitive, inflammatory, synaptic, and neuronal markers in the rat. METHODS: Female and male Lister Hooded rats received acute intracerebroventricular (ICV) administration of either vehicle or 5 nmol of Aβo1-42 (10μL). Cognition was assessed in the novel object recognition (NOR) paradigm at different time points. Levels of inflammatory (IL-1β, IL-6, TNF-α), synaptic (PSD-95, SNAP-25), and neuronal (n-acetylaspartate, parvalbumin-positive cells) markers were investigated in different brain regions (prefrontal and frontal cortex, striatum, dorsal and ventral hippocampus). RESULTS: Acute ICV administration of Aβo1-42 induced robust and enduring NOR deficits. These deficits were reversed by acute administration of donepezil and rolipram but not risperidone. Postmortem analysis revealed an increase in inflammatory markers, a decrease in synaptic markers and parvalbumin containing interneurons in the frontal cortex, with no evidence of widespread neuronal loss. CONCLUSION: Taken together the results suggest that acute administration of soluble low-n Aβo may be a useful model to study the early mechanisms involved in AD and provide us with a platform for testing novel therapeutic approaches that target the early underlying synaptic pathology.

Statins and Brain Health: Alzheimer's Disease and Cerebrovascular Disease Biomarkers in Older Adults. - Ramanan, Vijay K; Przybelski, Scott A; Graff-Radford, Jonathan; Castillo, Anna M; Lowe, Val J; Mielke, Michelle M; Roberts, Rosebud O; Reid, Robert I; Knopman, David S; Jack, Clifford R; Petersen, Ronald C; Vemuri, Prashanthi (J Alzheimers Dis, 2018)
BACKGROUND: Statins have been proposed to reduce the risk of Alzheimer's disease (AD). OBJECTIVE: Assess whether long-term statin use was associated with neuroimaging biomarkers of aging and dementia. METHODS: Methods: We analyzed neuroimaging biomarkers in 1,160 individuals aged 65+ from the Mayo Clinic Study of Aging, a population-based prospective longitudinal study of cognitive aging. RESULTS: Statin-treated (5+ years of therapy) individuals had greater burden of mid-and late-life cardiovascular disease (p < 0.001) than statin-untreated (≤3 months) individuals. Lower fractional anisotropy in the genu of the corpus callosum, an early marker of cerebrovascular disease, was associated with long-term statin exposure (p < 0.035). No significant associations were identified between long-term statin exposure and cerebral amyloid or tau burden, AD pattern neurodegeneration, or white matter hyperintensity burden. CONCLUSIONS: Long-term statin therapy was not associated with differences in AD biomarkers. Individuals with long-term statin exposure had worse white matter integrity in the genu of the corpus callosum, consistent with the coexistence of higher cerebrovascular risk factor burden in this group.

Stereological Investigation of the Effects of Treadmill Running Exercise on the Hippocampal Neurons in Middle-Aged APP/PS1 Transgenic Mice. - Chao, Fenglei; Jiang, Lin; Zhang, Yi; Zhou, Chunni; Zhang, Lei; Tang, Jing; Liang, Xin; Qi, Yingqiang; Zhu, Yanqing; Ma, Jing; Tang, Yong (J Alzheimers Dis, 2018)
The risk of cognitive decline during Alzheimer's disease (AD) can be reduced if physical activity is maintained; however, the specific neural events underlying this beneficial effect are still uncertain. To quantitatively investigate the neural events underlying the effect of running exercise on middle-aged AD subjects, 12-month-old male APP/PS1 mice were randomly assigned to a control group or running group, and age-matched non-transgenic littermates were used as a wild-type group. AD running group mice were subjected to a treadmill running protocol (regular and moderate intensity) for four months. Spatial learning and memory abilities were assessed using the Morris water maze. Hippocampal amyloid plaques were observed using Thioflavin S staining and immunohistochemistry. Hippocampal volume, number of neurons, and number of newborn cells (BrdU+ cells) in the hippocampus were estimated using stereological techniques, and newborn neurons were observed using double-labelling immunofluorescence. Marked neuronal loss in both the CA1 field and dentate gyrus (DG) and deficits in both the neurogenesis and survival of new neurons in the DG of middle-aged APP/PS1 mice were observed. Running exercise could improve the spatial learning and memory abilities, reduce amyloid plaques in the hippocampi, delay neuronal loss, induce neurogenesis, and promote the survival of newborn neurons in the DG of middle-aged APP/PS1 mice. Exercise-induced protection of neurons and adult neurogenesis within the DG might be part of the important structural basis of the improved spatial learning and memory abilities observed in AD mice.

Subtle Cognitive Impairment and Alzheimer's Disease-Type Pathological Changes in Cerebrospinal Fluid are Common Among Neurologically Healthy Subjects. - Haapalinna, Fanni; Kokki, Merja; Jääskeläinen, Olli; Hallikainen, Merja; Helisalmi, Seppo; Koivisto, Anne; Kokki, Hannu; Paajanen, Teemu; Penttinen, Janne; Pikkarainen, Maria; Rautiainen, Minna; Soininen, Hilkka; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The neuropathology of Alzheimer's disease (AD) has previously been shown to be rather common among the elderly. OBJECTIVE: The aim of this study was to inspect the associations between cerebrospinal fluid (CSF) AD biomarker concentrations, age, the APOEɛ4 allele, cardiovascular diseases, diabetes, and cognitive performance in a cohort of a neurologically healthy population. METHODS: This study included 93 subjects (42 men, mean age 67 years) without previous neurological symptoms or subjective cognitive complaints. Their cognition was assessed, and CSF biomarkers and APOEɛ4 status were analyzed. RESULTS: Of the studied subjects, 8.6% (n = 8) had a pathological CSF AD biomarker profile. An increase in age correlated positively with CSF tau pathology and negatively with global cognitive performance. CONCLUSION: AD-type pathological changes in CSF and subtle cognitive impairment are common within a population with no previous memory complaints. Age was the main risk factor for the changes.

Sulforaphane Inhibits the Generation of Amyloid-β Oligomer and Promotes Spatial Learning and Memory in Alzheimer's Disease (PS1V97L) Transgenic Mice. - Hou, Ting-Ting; Yang, He-Yun; Wang, Wei; Wu, Qiao-Qi; Tian, Yuan-Ruhua; Jia, Jian-Ping (J Alzheimers Dis, 2018)
Abnormal amyloid-β (Aβ) aggregates are a striking feature of Alzheimer's disease (AD), and Aβ oligomers have been proven to be crucial in the pathology of AD. Any intervention targeting the generation or aggregation of Aβ can be expected to be useful in AD treatment. Oxidative stress and inflammation are common pathological changes in AD that are involved in the generation and aggregation of Aβ. In the present study, 6-month-old PS1V97L transgenic (Tg) mice were treated with sulforaphane, an antioxidant, for 4 months, and this treatment significantly inhibited the generation and aggregation of Aβ. Sulforaphane also alleviated several downstream pathological changes that including tau hyperphosphorylation, oxidative stress, and neuroinflammation. Most importantly, the cognition of the sulforaphane-treated PS1V97L Tg mice remained normal compared to that of wild-type mice at 10 months of age, when dementia typically emerges in PS1V97L Tg mice. Pretreating cultured cortical neurons with sulforaphane also protected against neuronal injury caused by Aβ oligomers in vitro. These findings suggest that sulforaphane may be a potential compound that can inhibit Aβ oligomer production in AD.

Targeting Insulin for Alzheimer's Disease: Mechanisms, Status and Potential Directions. - Lee, Jung Hyun; Jahrling, Jordan B; Denner, Larry; Dineley, Kelly T (J Alzheimers Dis, 2018)
Insulin resistance can occur when the body is unable to respond to insulin even in excess. In the brain, insulin manages glucose metabolism in regions such as the hippocampus and plays a key role in directly regulating ERK, a kinase required for the type of memory compromised in early Alzheimer's disease (AD). Human imaging studies show that brain glucose utilization declines with age and is notably impaired in subjects with early AD. Likewise, animal models of AD or insulin resistance, or both, demonstrate that dysfunctional insulin signaling and insulin resistance in the brain have reciprocity with neuroinflammation and aberrant accumulation of amyloid-β (Aβ), pathological hallmarks in AD. As such, the association between brain insulin activity and AD has led to clinical trials testing the efficacy of insulin and insulin-sensitizing drugs to intervene in AD. Based on recent inquiries to ClinicalTrials.gov, we evaluated thirty-three clinical studies related to AD and insulin. The search filtered for interventional clinical trials to test FDA-approved drugs or substances that impinge upon the insulin signaling pathway. Insulin, metformin, and thiazolidinediones were the three main interventions assessed. Overall, these strategies are expected to negate the effects of brain insulin resistance by targeting insulin signaling pathways involved in neuroinflammation, metabolic homeostasis, synaptic functional and structural integrity. The goal of this review is to provide an update on insulin and ERK signaling in relation to memory, its decline in early AD, and provide an overview of clinical trials related to insulin for early AD intervention.

Tau Protein Dysfunction after Brain Ischemia. - Pluta, Ryszard; Ułamek-Kozioł, Marzena; Januszewski, Sławomir; Czuczwar, Stanisław J (J Alzheimers Dis, 2018)
Brain ischemia comprises blood-brain barrier, glial, and neuronal cells. The blood-brain barrier controls permeability of different substances and the composition of the neuronal cells 'milieu', which is required for their physiological functioning. Recent evidence indicates that brain ischemia itself and ischemic blood-brain barrier dysfunction is associated with the accumulation of neurotoxic molecules within brain tissue, e.g., different parts of amyloid-β protein precursor and changed pathologically tau protein. All these changes due to ischemia can initiate and progress neurodegeneration of the Alzheimer's disease-type. This review presents brain ischemia and ischemic blood-brain barrier as a trigger for tau protein alterations. Thus, we hypothesize that the changes in pattern of phosphorylation of tau protein are critical to microtubule function especially in neurons, and contribute to the neurodegeneration following brain ischemia-reperfusion episodes with Alzheimer's disease phenotype.

TDP-43 and Alzheimer's Disease Pathologic Subtype in Non-Amnestic Alzheimer's Disease Dementia. - Sahoo, Aradhana; Bejanin, Alexandre; Murray, Melissa E; Tosakulwong, Nirubol; Weigand, Stephen D; Serie, Amanda M; Senjem, Matthew L; Machulda, Mary M; Parisi, Joseph E; Boeve, Bradley F; Knopman, David S; Petersen, Ronald C; et al. (J Alzheimers Dis, 2018)
BACKGROUND: TDP-43 has been shown to be strongly associated with memory loss, smaller hippocampal volumes, and faster rates of hippocampal atrophy in Alzheimer's disease (AD) patients with an amnestic presentation. Whether TDP-43 has any clinical or anatomical associations in AD patients with non-amnestic phenotype is unknown. OBJECTIVE: To determine whether TDP-43 plays a significant role in the clinic-anatomic features of non-amnestic AD. METHODS: All cases with pathologically confirmed intermediate-high probability AD from 1996-2012 were identified and retrospectively sub-classified into amnestic versus non-amnestic dementia at the time of presentation. Neurofibrillary tangle counts were performed in those with a non-amnestic presentation using thioflavin-S microscopy in the hippocampus and three neocortical regions, and all cases were subtyped into hippocampal-sparing, limbic-predominant, and typical AD pathology. TDP-43 immunoreactivity was used to assess for the presence of TDP-43. Statistical analyses helped determine whether pathologic subtype or TDP-43 was more strongly associated with clinico-imaging features. RESULTS: Out of 172 pathologically confirmed AD cases, 36 (19%) were classified as non-amnestic. Twenty-five of these 36 (69%) had typical pathology, 0 limbic-predominant pathology, and 11 (31%) hippocampal-sparing pathology. Eleven (44%) of the 25 cases with typical pathology were TDP-43+. Of the 11 cases with hippocampal-sparing pathology, 4 (36%) were TDP-43+. There were no differences in demographic, clinical, or neuroimaging features in those with TDP-43 versus those without except for older age at onset (p = 0.02) and age at death (p = 0.02) in those with TDP-43. AD pathological subtype accounted for slightly more of the variances in the neocortex than TDP-43. CONCLUSION: In non-amnestic AD, we find little evidence that clinical or anatomical features of the disease are related to TDP-43.

A Three-Factor Structure of Cognitive Functioning Among Unimpaired Carriers and Non-Carriers of Autosomal-Dominant Alzheimer's Disease. - Guzmán-Vélez, Edmarie; Jaimes, Sehily; Aguirre-Acevedo, Daniel C; Norton, Daniel J; Papp, Kathryn V; Amariglio, Rebecca; Rentz, Dorene; Baena, Ana; Henao, Eliana; Tirado, Victoria; Munoz, Claudia; Giraldo, Margarita; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is a need to find cognitive markers that can help identify individuals at risk for Alzheimer's disease (AD), and that can be used to reliably measure cognitive decline. OBJECTIVE: We tested whether a theoretically driven three-factor structure would characterize cognitive functioning in individuals who are genetically-determined to develop AD due to a mutation in Presenilin-1 (PSEN1) gene. We also examined whether these factors could distinguish cognitively unimpaired PSEN1 mutation carriers from age-matched non-carrier family members. METHODS: 1,395 cognitively unimpaired members of a Colombian kindred with the PSEN1 E280A mutation were included in the study. A confirmatory factor analysis examined the fit of the three-factor model comprising episodic memory (MMSE memory recall, CERAD-COL Word list recall, and Constructional praxis recall), executive function (Phonemic fluency and WCST perseverative errors), and psychomotor processing speed (TMT-A and WAIS-III Digit Symbol). RESULTS: The three-factor model provided an excellent fit for all participants (p = 0.24; RMSEA = 0.01). Further, the episodic memory (p = 0.0004, d = 0.25) and executive functioning (p = 0.001, d = 0.18) factors distinguished cognitively unimpaired carriers from non-carriers. The episodic memory factor provided the earliest indication of preclinical cognitive decline at 35 years of age, nine years before individuals' estimated age of clinical onset. CONCLUSIONS: The three theoretically derived cognitive factors provide a reliable measure of cognition and may be useful for the early detection of AD, as well as for measuring disease progression. However, longitudinal studies are needed to confirm that these factors can be used to track the progression of cognitive decline in preclinical AD.

Total MRI Small Vessel Disease Burden Correlates with Cognitive Performance, Cortical Atrophy, and Network Measures in a Memory Clinic Population. - Banerjee, Gargi; Jang, Hyemin; Kim, Hee Jin; Kim, Sung Tae; Kim, Jae Seung; Lee, Jae Hong; Im, Kiho; Kwon, Hunki; Lee, Jong Min; Na, Duk L; Seo, Sang Won; Werring, David John (J Alzheimers Dis, 2018)
BACKGROUND: Recent evidence suggests that combining individual imaging markers of cerebral small vessel disease (SVD) may more accurately reflect its overall burden and better correlate with clinical measures. OBJECTIVE: We wished to establish the clinical relevance of the total SVD score in a memory clinic population by investigating the association with SVD score and cognitive performance, cortical atrophy, and structural network measures, after adjusting for amyloid-β burden. METHODS: We included 243 patients with amnestic mild cognitive impairment (MCI), Alzheimer's disease dementia, subcortical vascular MCI, or subcortical vascular dementia. All underwent MR and [11C] PiB-PET scanning and had standardized cognitive testing. Multiple linear regression was used to evaluate the relationships between SVD score and cognition, cortical thickness, and structural network measures. Path analyses were performed to evaluate whether network disruption mediates the effects of SVD score on cortical thickness and cognition. RESULTS: Total SVD score was associated with the performance of frontal (β - 4.31, SE 2.09, p = 0.040) and visuospatial (β - 0.95, SE 0.44, p = 0.032) tasks, and with reduced cortical thickness in widespread brain regions. Total SVD score was negatively correlated with nodal efficiency, as well as changes in brain network organization, with evidence of reduced integration and increasing segregation. Path analyses showed that the associations between SVD score and frontal and visuospatial scores were partially mediated by decreases in their corresponding nodal efficiency and cortical thickness. CONCLUSION: Total SVD burden has clinical relevance in a memory clinic population and correlates with cognition, and cortical atrophy, as well as structural network disruption.

Trajectories of Physiological Brain Aging and Related Factors in People Aged from 20 to over-80. - Lee, Jin San; Kim, Seonwoo; Yoo, Heejin; Park, Seongbeom; Jang, Young Kyoung; Kim, Hee Jin; Kim, Ko Woon; Kim, Yeshin; Jang, Hyemin; Park, Key-Chung; Yaffe, Kristine; Yang, Jin-Ju; et al. (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: In this study, we investigated a long-term trajectory of brain aging (from the 20 s to over-80) in cognitively normal (CN) individuals. We further determined whether differences in sex, education years, and apolipoprotein E ε 4 status affect age-related cortical thinning. METHODS: A total of 2,944 CN individuals who underwent high-resolution (3.0-Tesla) magnetic resonance imaging were included in this study. Cortical thickness was measured using a surface-based method. Multiple linear regression analyses were performed to evaluate age-related cortical thinning and related factors. RESULTS: Compared to those in their 20 s/30 s, participants in their 40 s showed thinning primarily in the medial and lateral frontal and inferior parietal regions, and cortical thinning occurred across most of the cortices with increasing age. Notably, the precuneus, inferior temporal and lateral occipital regions were relatively spared until later in life. Male and lower education years were associated with greater cortical thinning with distinct regional specificity. CONCLUSION: Our findings provide an important clue to understanding the mechanism of age-related cognitive decline and new strategies for preventing the acceleration of pathological brain aging.

Treatment of Atrial Fibrillation in Patients with Dementia: A Cohort Study from the Swedish Dementia Registry. - Subic, Ana; Cermakova, Pavla; Religa, Dorota; Han, Shuang; von Euler, Mia; Kåreholt, Ingemar; Johnell, Kristina; Fastbom, Johan; Bognandi, Liselia; Winblad, Bengt; Kramberger, Milica G; Eriksdotter, Maria; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Patients with dementia might have higher risk for hemorrhagic complications with anticoagulant therapy prescribed for atrial fibrillation (AF). OBJECTIVE: This study assesses the risks and benefits of warfarin, antiplatelets, and no treatment in patients with dementia and AF. METHODS: Of 49,792 patients registered in the Swedish Dementia Registry 2007-2014, 8,096 (16%) had a previous diagnosis of AF. Cox proportional hazards models were used to calculate the risk for ischemic stroke (IS), nontraumatic intracranial hemorrhage, any-cause hemorrhage, and death. RESULTS: Out of the 8,096 dementia patients with AF, 2,143 (26%) received warfarin treatment, 2,975 (37%) antiplatelet treatment, and 2,978 (37%) had no antithrombotic treatment at the time of dementia diagnosis. Patients on warfarin had fewer IS than those without treatment (5.2% versus 8.7%; p < 0.001) with no differences compared to antiplatelets. In adjusted analyses, warfarin was associated with a lower risk for IS (HR 0.76, CI 0.59-0.98), while antiplatelets were associated with increased risk (HR 1.25, CI 1.01-1.54) compared to no treatment. For any-cause hemorrhage, there was a higher risk with warfarin (HR 1.28, CI 1.03-1.59) compared to antiplatelets. Warfarin and antiplatelets were associated with a lower risk for death compared to no treatment. CONCLUSIONS: Warfarin treatment in Swedish patients with dementia is associated with lower risk of IS and mortality, and a small increase in any-cause hemorrhage. This study supports the use of warfarin in appropriate cases in patients with dementia. The low percentage of patients on warfarin treatment indicates that further gains in stroke prevention are possible.
Keywords: Aged; Aged, 80 and over; Anticoagulants; Atrial Fibrillation; Dementia; Female; Hemorrhage; Humans; Longitudinal Studies; Male; Registries; Risk Factors; Stroke; Survival Analysis; Sweden; Warfarin

The Use of Mobile Games to Assess Cognitive Function of Elderly with and without Cognitive Impairment. - Bonnechère, Bruno; Van Vooren, Mélissa; Bier, Jean-Christophe; De Breucker, Sandra; Van Hove, Olivier; Van Sint Jan, Serge; Feipel, Véronique; Jansen, Bart (J Alzheimers Dis, 2018)
BACKGROUND: In the past few years numerous mobile games have been developed to train the brain. There is a lack of information about the relation between the scores obtained in these games and the cognitive abilities of the patients. OBJECTIVE: The aim of this study was to determine whether or not mobile games can be used to assess cognitive abilities of elderly. METHODS: Twenty healthy young adults, 29 old patients with cognitive impairments (Mini-Mental State Exam (MMSE) [20- 24]) and 27-aged controls participated in this study. Scores obtained in 7 mobile games were correlated with MMSE and the Addenbrooke's Cognitive Evaluation revised (ACE-R). RESULTS: Statistically significant differences were found for all games between patients with cognitive impairments and the aged controls. Correlations between the average scores of the games and the MMSE and ACE-R are significant (R = 0.72 [p < 0.001] and R = 0.81 [p < 0.001], respectively). CONCLUSION: Scores of cognitive mobile games could be used as an alternative to MMSE and ACE-R to evaluate cognitive function of aged people with and without cognitive impairment at least when MMSE is higher than 20/30.

Validation of the Delayed Matching-to-Sample Task 48 (DMS48) in Elderly Chinese. - Feng, Xueyan; Zhou, Aihong; Liu, Zhixin; Li, Fangyu; Wei, Cuibai; Zhang, Guili; Jia, Jianping (J Alzheimers Dis, 2018)
BACKGROUND: Delayed Matching-to-Sample Task 48 (DMS48), a brief tool measuring visual recognition memory, is valid to identify the early stage of Alzheimer's disease (AD) in Caucasians. However, little data is available in Chinese. OBJECTIVE: To develop norms and optimal cutoff points for the DMS48 in Chinese elders. METHODS: A cross-sectional study was conducted in seven memory clinics from five cities across China. DMS48 was applied to 369 Chinese aged 50 or older (138 cognitively normal [CN], 112 mild cognitive impairment due to AD (MCI-A), and 119 mild AD dementia). The demographic factors which influence DMS48 scores were investigated and the norms were established considering those factors. Receiver operating characteristic (ROC) analysis was used to determine the optimal cutoff points. RESULTS: Age was shown to influence DMS48 scores (r = -0.36, p < 0.05), and we presented the age-stratified normative data for the DMS48. The optimal cutoff point is 42/43 for identifying cognitive impairment (MCI-A and AD dementia) against CN (sensitivity 97.80% and specificity 89.13%) and MCI-A against CN (sensitivity 86.60% and specificity 94.20%). A cutoff of 39/40 obtained good sensitivity (100.00%) and specificity (94.90%) in discriminating AD dementia from CN. The age-stratified optimal cutoff points for identifying MCI-A were 43/44 for individuals aged 50 to 59 years old, 42/43 for 60 to 69 years old, 41/42 for 70 to 79 years old, and 40/41 for 80 or older, respectively (sensitivity 84.80% and specificity 95.70%). CONCLUSION: This study proved that DMS48 is of good validation in screening MCI-A in elderly Chinese.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; China; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Linear Models; Male; Memory Disorders; Middle Aged; Neuropsychological Tests; ROC Curve; Sensitivity and Specificity; Severity of Illness Index

Vascular Effects on Depressive Symptoms in Cognitive Impairment. - Kim, Yeshin; Jang, Hyemin; Kim, Seung Joo; Cho, Soo Hyun; Kim, Si Eun; Kim, Sung Tae; Kim, Hee Jin; Moon, Seung Hwan; Ewers, Michael; Im, Kiho; Kwon, Hunki; Na, Duk L; et al. (J Alzheimers Dis, 2018)
Late life depression is related to pathologic burdens, such as cerebral small vascular disease (CSVD) and amyloid, which are associated with brain network changes and cortical thinning. To examine the associations of various CSVD imaging markers, amyloid, and network changes with depression in cognitively impaired patients, we prospectively recruited 228 cognitively impaired patients having various degrees of amyloid and CSVD who underwent diffuse tensor image and PiB PET. Greater CSVD burden was associated with greater Geriatric Depression Scale (GDS) (white matter hyperintensities, WMH: p = 0.025, lacunes: p < 0.001) but not with amyloid (p = 0.095), and cortical thinning (p = 0.630) was not associated with greater GDS. The changes in white matter networks were related to GDS with decreasing integration (global efficiency: p < 0.001) and increasing segregation (clustering coefficient: p = 0.009). The network changes mediated the relationships of WMH and lacunes with GDS. Our findings provide insight to better understand how CSVD burdens contribute to depression in cognitively impaired patients having varying degrees of amyloid and vascular burdens.

Visualization of Focal Thinning of the Ganglion Cell-Inner Plexiform Layer in Patients with Mild Cognitive Impairment and Alzheimer's Disease. - Shao, Yi; Jiang, Hong; Wei, Yantao; Shi, Yingying; Shi, Ce; Wright, Clinton B; Sun, Xiaoyan; Vanner, Elizabeth A; Rodriguez, Anny D; Lam, Byron L; Rundek, Tatjana; Baumel, Barry S; et al. (J Alzheimers Dis, 2018)
BACKGROUND: A detailed analysis of the tomographic thickness of intraretinal layers may provide more information on neurodegeneration in patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD). OBJECTIVE: The goal was to analyze tomographic thickness patterns of intraretinal layers in patients with AD andMCI. METHOD: Forty-nine patients (25 AD and 24 MCI) and 21 cognitively normal (CN) controls were imaged using ultra-high-resolution optical coherence tomography to obtain volumetric data centered on the fovea. The segmented intraretinal layers were retinal nerve fiber layer (RNFL), ganglion cell- inner plexiform layer (GCIPL), inner nuclear layer (INL), outer nuclear layer (ONL), outer plexiform layer (OPL), and retinal photoreceptor (PR), in addition to the total retinal thickness(TRT). RESULTS: The thickness differences were negative (thinning) mainly in TRT, RNFL, and GCIPL in both AD and MCI groups in comparison to CN, while the thickness differences were positive (thickening) mainly in ONL and PR in AD. GCIPL of AD and MCI was thinner in superior, nasal superior, and temporal superior quadrants, compared to CN (p < 0.05). GCIPL of the inner superior, inner nasal superior, inner temporal superior, and outer nasal superior sectors was significantly thinner in AD than CN (p < 0.05). GCIPL of the outer superior, inner temporal superior, outer nasal, and temporal superior sectors was significantly thinner in MCI than CN (p < 0.05). CONCLUSION: Focal thinning of the GCIPL was visualized and quantified by detailed partitions in AD and MCI, which provides specific information about neurodegeneration in MCI and AD.

What Factors Predict Family Caregivers' Attendance at Dementia Cafés? - Jones, Susan May; Killett, Anne; Mioshi, Eneida (J Alzheimers Dis, 2018)
BACKGROUND: Dementia Cafés are community support groups which provide post-diagnostic support for families affected by dementia. However, little is known about the characteristics of caregivers who attend Cafés. OBJECTIVES: To describe the demographic and psychosocial characteristics of caregivers who attend Dementia Cafés, and to identify which of those factors may influence the likelihood of family caregivers attending Dementia Cafés. METHODS: A cross-sectional study on caregivers (n = 80; July 2016- July 2017). Resilience (Brief Resilient Coping Scale), Subjective Wellbeing (Personal Wellbeing Index), and Social Support (MOS-Social Support Survey) were measured. Café attendees and non-attendees were compared in regards to demographic characteristics (Chi-Square tests), resilience, subjective wellbeing and social support (independent t-tests). Bivariate and multivariate regression analyses were run to detect associations between predictor variables and café attendance. RESULTS: Caregivers who attended Cafés reported higher resilience (OR: 1.26; 95% CI 1.10-1.45; p = 0.001) and subjective wellbeing (OR: 1.63; 95% CI 1.24-2.142; p = 0.001); no significant difference in social support was detected. Female caregivers were more likely to attend a Café (OR: 3.23; 95% CI 1.14-9.10; p = 0.03). However, only higher subjective wellbeing (OR: 1.63; 95% CI 1.10-24.2; p = 0.02) and fewer years formal education (OR: 4.99; 95% CI 1.12-21.36; p = 0.03) predicted attendance at a café. CONCLUSION: Dementia Cafés may bring about benefits in resilience and subjective wellbeing, or may be best suited to those with higher resilience and wellbeing. Cafes are not being accessed by all caregiver groups. Alternative models of post-diagnostic support should be considered to increase equity of care.

When Art Meets Gardens: Does It Enhance the Benefits? The Nancy Hypothesis of Care for Persons with Alzheimer's Disease. - Jonveaux, Thérèse Rivasseau; Fescharek, Reinhard (J Alzheimers Dis, 2018)
The creation of healing gardens for persons with Alzheimer's disease and related diseases (ADRD) offers vast potential. They can play a role in the scaffolding of cognitive disorders, emotional stress, sensory processing, sense of harmony, and appeasement. These effects are achieved through a distributed interplay of psychological functions with the immediate environment and local culture on the one hand, and dialogue on the other. The garden, a natural canvas created by man, shares with art the ability to foster an esthetic sense for which the perception can be measured by functional neurological imaging exploration. Art represents a mediator for the collaborative realization of distributed psychological functions between different individuals. Based on the hypothesis of an optimization of the therapeutic potential of a garden by a design adapted to the neuro-psycho-social and cultural specificities of its users combined with the thoughtful introduction of an artistic dimension, the "art, memory and life" healing garden was created at the University Hospital of Nancy as a prototype for persons with ADRD. The design concept was based on two hypotheses that we formulate herein, discuss their theoretical foundation, and suggest enhanced design for therapeutic gardens based upon our experience.
Keywords: Alzheimer Disease; Art Therapy; Cognition; Cognitive Behavioral Therapy; France; Gardening; Humans

18F-AV-1451 PET Imaging in Three Patients with Probable Cerebral Amyloid Angiopathy. - Kim, Hee Jin; Cho, Hanna; Werring, David J; Jang, Young Kyoung; Kim, Yeo Jin; Lee, Jin San; Lee, Juyoun; Jun, Soomin; Park, Seongbeom; Ryu, Young Hoon; Choi, Jae Yong; Cho, Young Seok; et al. (J Alzheimers Dis, 2017)
Cerebrovascular deposition of amyloid-β, known as cerebral amyloid angiopathy (CAA), is associated with MRI findings of lobar hemorrhage, cerebral microbleeds, and cortical superficial siderosis. Although pathological studies suggest that tau may co-localize with vascular amyloid, this has not yet been investigated in CAA in vivo. Three patients with probable CAA underwent 11C-Pittsburgh Compound B (PiB) PET or 18F-florbetaben PET to evaluate amyloid burden, and 18F-AV-1451 PET to evaluate paired helical filament tau burden. Regions that had cerebral microbleeds or cortical superficial siderosis largely overlapped with those showing increased 18F-AV-1451. Our preliminary study raised the possibility that lobar cerebral microbleeds, and cortical superficial siderosis, which are characteristic markers of vascular amyloid, may be associated with local production of paired helical filament tau.
Keywords: Aged; Aged, 80 and over; Aniline Compounds; Brain; Carbolines; Cerebral Amyloid Angiopathy; Female; Humans; Image Processing, Computer-Assisted; Male; Positron-Emission Tomography; Thiazoles

The 2002 NIMH Provisional Diagnostic Criteria for Depression of Alzheimer's Disease (PDC-dAD): Gauging their Validity over a Decade Later. - Sepehry, Amir A; Lee, Philip E; Hsiung, Ging-Yuek R; Beattie, B Lynn; Feldman, Howard H; Jacova, Claudia (J Alzheimers Dis, 2017)
Presented herein is evidence for criterion, content, and convergent/discriminant validity of the NIMH-Provisional Diagnostic Criteria for depression of Alzheimer's Disease (PDC-dAD) that were formulated to address depression in Alzheimer's disease (AD). Using meta-analytic and systematic review methods, we examined criterion validity evidence in epidemiological and clinical studies comparing the PDC-dAD to Diagnostic and Statistical Manual of Mental Disorders fourth edition (DSM-IV), and International Classification of Disease (ICD 9) depression diagnostic criteria. We estimated prevalence of depression by PDC, DSM, and ICD with an omnibus event rate effect-size. We also examined diagnostic agreement between PDC and DSM. To gauge content validity, we reviewed rates of symptom endorsement for each diagnostic approach. Finally, we examined the PDC's relationship with assessment scales (global cognition, neuropsychiatric, and depression definition) for convergent validity evidence. The aggregate evidence supports the validity of the PDC-dAD. Our findings suggest that depression in AD differs from other depressive disorders including Major Depressive Disorder (MDD) in that dAD is more prevalent, with generally a milder presentation and with unique features not captured by the DSM. Although the PDC are the current standard for diagnosis of depression in AD, we identified the need for their further optimization based on predictive validity evidence.

Acceleration of Amyloidosis by Inflammation in the Amyloid-Beta Marmoset Monkey Model of Alzheimer's Disease. - Philippens, Ingrid H; Ormel, Paul R; Baarends, Guus; Johansson, Maja; Remarque, Ed J; Doverskog, Magnus (J Alzheimers Dis, 2017)
BACKGROUND: The immune system is increasingly mentioned as a potential target for Alzheimer's disease (AD) treatment. OBJECTIVE: In the present pilot study, the effect of (neuro)inflammation on amyloidopathy was investigated in the marmoset monkey, which has potential as an AD animal model due to its natural cerebral amyloidosis similar to humans. METHODS: Six adult/aged marmosets (Callithrix jacchus) were intracranial injected with amyloid-beta (Aβ) fibrils at three cortical locations in the right hemisphere. Additionally, in half of the monkeys, lipopolysaccharide (LPS) was co-injected with the Aβ fibrils and injected in the other hemisphere without Aβ fibrils. The other three monkeys received phosphate buffered saline instead of LPS, as a control for the inflammatory state. The effect of inflammation on amyloidopathy was also investigated in an additional monkey that suffered from chronic inflammatory wasting syndrome. Mirror histology sections were analyzed to assess amyloidopathy and immune reaction, and peripheral blood for AD biomarker expression. RESULTS: All LPS-injected monkeys showed an early AD immune blood cell expression profile on CD95 and CD45RA. Two out of three monkeys injected with Aβ and LPS and the additional monkey, suffering from chronic inflammation, developed plaques. None of the controls, injected with Aβ only, developed any plaques. CONCLUSION: This study shows the importance of immune modulation on the susceptibility for amyloidosis, a hallmark of AD, which offers new perspectives for disease modifying approaches in AD.

Aerosol Delivery of Curcumin Reduced Amyloid-β Deposition and Improved Cognitive Performance in a Transgenic Model of Alzheimer's Disease. - McClure, Richard; Ong, Henry; Janve, Vaibhab; Barton, Shawn; Zhu, Meiying; Li, Bo; Dawes, Mary; Jerome, W Gray; Anderson, Adam; Massion, Pierre; Gore, John C; Pham, Wellington (J Alzheimers Dis, 2017)
We report a novel approach for the delivery of curcumin to the brain via inhalation of the aerosol for the potential treatment of Alzheimer's disease. The percentage of plaque fraction in the subiculum and hippocampus reduced significantly when young 5XFAD mice were treated with inhalable curcumin over an extended period of time compared to age-matched nontreated counterparts. Further, treated animals demonstrated remarkably improved overall cognitive function, no registered systemic or pulmonary toxicity associated with inhalable curcumin observed during the course of this work.

Alzheimer's Disease Biomarkers and Future Decline in Cognitive Normal Older Adults. - Dumurgier, Julien; Hanseeuw, Bernard J; Hatling, Frances B; Judge, Kelly A; Schultz, Aaron P; Chhatwal, Jasmeer P; Blacker, Deborah; Sperling, Reisa A; Johnson, Keith A; Hyman, Bradley T; Gómez-Isla, Teresa (J Alzheimers Dis, 2017)
BACKGROUND: Identifying older adults at risk of cognitive decline represents a challenge as Alzheimer's disease (AD) modifying therapies move toward preclinical stages. OBJECTIVE: To investigate the relationship between AD biomarkers and subsequent change in cognition in a cohort of cognitively intact older adults. METHODS: 84 cognitively normal subjects (mean age 72.0 years, 59% women) were recruited through the Massachusetts Alzheimer's Disease Research Center and the Harvard Aging Brain Study and followed over 3 years. Measurements of amyloid-β 1-42 (Aβ42), total Tau (t-Tau), and Tau phosphorylated at threonine 181 (p-Tau181) in the cerebrospinal fluid (CSF) at study entry were available in all cases. Baseline brain MRI, FDG-PET, and PiB-PET data were available in the majority of participants. Relationship between baseline AD biomarkers and longitudinal change in cognition was assessed using Cox proportional hazard regression and linear mixed models. RESULTS: 14% participants increased their global Clinical Dementia Rating (CDR) score from 0 to 0.5 during follow-up. A CDR score increase was associated with higher baseline CSF t-Tau and p-Tau181, higher global cortical PiB retention, and lower hippocampal volume. The combination of high CSF t-Tau and low Aβ42 or low hippocampal volume was more strongly related to cognitive outcome than each single biomarker. Higher CSF t-Tau was the only biomarker associated with subsequent decline in MMSE score. CONCLUSIONS: Baseline CSF t-Tau and p-Tau181, in vivo amyloid load, and hippocampal volume were all independently associated with future decline in cognition. The discriminatory ability of these biomarkers to predict risk of cognitive decline, however, was only modest.

Alzheimer's Disease Histological and Behavioral Manifestations in Transgenic Mice Correlate with Specific Gut Microbiome State. - Shen, Liang; Liu, Lu; Ji, Hong-Fang (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a neurodegenerative brain disease and is the most common form of dementia. In recent years, many studies indicated the association of gut microbiota changes with metabolic diseases. However, the gut microbiota of AD has not been investigated. The present study aims to compare the gut microbiota in APP/PS1 transgenic mice of AD and C57/Bl6 wild-type (WT) mice by pyrosequencing the V3 and V4 regions of the bacterial 16S ribosomal RNA genes. The 3-, 6-, and 8-month-old APP/PS1 and WT mice were used to explore the effects of age on the gut microbiota. First, the results indicated that impaired spatial learning and memory appeared in 6-month-old APP/PS1 mice and was further aggravated in the 8-month-old group, which was consistent with immunohistochemical studies of amyloid plaque. Second, AD histological and behavioral manifestations in the APP/PS1 mice were found to be correlated with a specific gut microbiome state. Third, the microbiota diversity of APP/PS1 mice decreased with increased age. Fourth, further inspection showed that the abundance of Helicobacteraceae and Desulfovibrionaceae at the family level and Odoribacter and Helicobacter at the genus level increased significantly in APP/PS1 mice than in WT mice, while Prevotella abundance in WT mice was significantly higher than in APP/PS1 mice. More human studies are warranted to explore the potential of gut microbiota as diagnostic biomarkers or therapeutic target for AD.

Alzheimer's Disease-Related Polymorphisms in Shunt-Responsive Idiopathic Normal Pressure Hydrocephalus. - Huovinen, Joel; Helisalmi, Seppo; Paananen, Jussi; Laiterä, Tiina; Kojoukhova, Maria; Sutela, Anna; Vanninen, Ritva; Laitinen, Marjo; Rauramaa, Tuomas; Koivisto, Anne M; Remes, Anne M; Soininen, Hilkka; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Idiopathic normal pressure hydrocephalus (iNPH) is a late onset, surgically treated progressive brain disease caused by impaired cerebrospinal fluid dynamics and subsequent ventriculomegaly. Comorbid Alzheimer's disease (AD) seems to be frequent in iNPH. OBJECTIVE: We aim to evaluate the role of AD-related polymorphisms in iNPH. METHODS: Overall 188 shunt-operated iNPH patients and 688 controls without diagnosed neurodegenerative disease were included into analysis. Twenty-three single-nucleotide polymorphisms (SNPs FRMD4A [rs7081208_A, rs2446581_A, rs17314229_T], CR1, BIN, CD2AP, CLU, MS4A6A, MS4A4E, PICALM, ABCA7, CD33, INPP5D, HLA_DRB5, EPHA1, PTK2B, CELF1, SORL1, FERMT2, SLC24A, DSG2, CASS4, and NME8) adjusted to APOE were analyzed between groups by using binary logistic regression analysis. Neuroradiological characteristics and AD-related changes in the right frontal cortical brain biopsies were available for further analysis. RESULTS: Logistic regression analysis adjusted to age, gender, and other SNPs indicated allelic variation of NME8 between iNPH patients and non-demented controls (p = 0.014). The allelic variation of NME8 was not related to the neuropathological changes in the brain biopsies of iNPH patients. However, periventricular white matter changes (p = 0.017) were more frequent in the iNPH patients with the AA-genotype, an identified risk factor of AD. CONCLUSIONS: Our findings increase the evidence that iNPH is characterized by genetic and pathophysiological mechanisms independent from AD. Considering that NME8 plays a role in the ciliary function and displays SNP-related diversity in white matter changes, the mechanisms of NME8 in iNPH and other neurodegenerative processes are worth further study.

Amyloid-Related Imaging Abnormalities in an Aged Squirrel Monkey with Cerebral Amyloid Angiopathy. - Heuer, Eric; Jacobs, Jessica; Du, Rebecca; Wang, Silun; Keifer, Orion P; Cintron, Amarallys F; Dooyema, Jeromy; Meng, Yuguang; Zhang, Xiaodong; Walker, Lary C (J Alzheimers Dis, 2017)
Amyloid-related imaging abnormalities (ARIA) in magnetic resonance imaging scans have emerged as indicators of potentially serious side effects in clinical trials of therapeutics for Alzheimer's disease. These anomalies include an edematous type (ARIA-E) that appears as hyperintense (bright) regions by T2-weighted MRI, and a type characterized by the deposition of hemosiderin (ARIA-H) that elicits a hypointense signal, especially in T2* susceptibility weighted images. ARIA in general has been linked to the presence of amyloid-β (Aβ)-type cerebral amyloid angiopathy, an accumulation of misfolded Aβ protein in the vascular wall that impairs the integrity of brain blood vessels. However, the pathobiology of ARIA remains poorly understood, in part due to the absence of an animal model of the disorder that would enable a contemporaneous analysis of tissue integrity in the affected region. Here we describe both ARIA-E and ARIA-H in an aged squirrel monkey (Saimiri sciureus), a nonhuman primate model of naturally occurring cerebral amyloid angiopathy. Histopathologic examination of the anomalous region revealed reactive astrocytosis and microgliosis, infiltration of systemic inflammatory/immune cells, damage to axons and myelin, and hemosiderin deposition. The disruption of axons in particular suggests that ARIA-E could have functional consequences for affected regions. The squirrel monkey model can be useful for studying the pathogenesis and long-term effects of ARIA, and for testing the safety and efficacy of emerging therapies for Alzheimer's disease.

The Anti-Amyloid-β and Neuroprotective Properties of a Novel Tricyclic Pyrone Molecule. - Maezawa, Izumi; Zou, Bende; Di Lucente, Jacopo; Cao, William S; Pascual, Conrado; Weerasekara, Sahani; Zhang, Man; Xie, Xinmin Simon; Hua, Duy H; Jin, Lee-Way (J Alzheimers Dis, 2017)
There is an urgent unmet need for new therapeutics for Alzheimer's disease (AD), the most common cause of dementia in the elderly. Therapeutic approaches targeting amyloid-β (Aβ) and its downstream toxicities have become major strategies in AD drug development. We have taken a rational design approach and synthesized a class of tricyclic pyrone (TP) compounds that show anti-Aβ and other neuroprotective actions. The in vivo efficacy of a lead TP named CP2 to ameliorate AD-like pathologies has been shown in mouse models. Here we report the selection and initial characterization of a new lead TP70, which exhibited an anti-Aβ therapeutic index even higher than CP2. Moreover, TP70 was able to reduce oxidative stress, inhibit acyl-coenzyme A:cholesterol acyltransferase (ACAT), and upregulate the expression of ATP-binding cassette subfamily A, member 1 (ABCA1), actions considered neuroprotective in AD. TP70 further showed excellent pharmacokinetic properties, including brain penetration and oral availability. When administered to 5xFAD mice via intraperitoneal or oral route, TP70 enhanced the overall solubility and decreased the level of cerebral Aβ, including both fibrillary and soluble Aβ species. Interestingly, TP70 enhanced N-methyl-D-aspartate (NMDA) receptor-mediated excitatory post-synaptic potential (EPSP) in the hippocampal CA1 area, increased the magnitude of NMDA-dependent hippocampal long-term potentiation (LTP), a cellular model of learning and memory, and prevented the Aβ oligomer-impaired LTP. Significantly, a single dose of TP70 administered to aged 5xFAD mice was effective in mitigating the impaired LTP induction, recorded at 24 h after administration. Our results support a potential of TP70 in clinical development for AD in view of its synergistic neuroprotective actions, ability to positively modulate NMDA receptor-mediated hippocampal plasticity, and favorable pharmacokinetic properties in rodents.

Apolipoprotein A1 in Cerebrospinal Fluid and Plasma and Progression to Alzheimer's Disease in Non-Demented Elderly. - Slot, Rosalinde E R; Van Harten, Argonde C; Kester, Maartje I; Jongbloed, Wesley; Bouwman, Femke H; Teunissen, Charlotte E; Scheltens, Philip; Veerhuis, Robert; van der Flier, Wiesje M (J Alzheimers Dis, 2017)
BACKGROUND: HDL-cholesterol transporter Apolipoprotein A1 (ApoA1) holds neuroprotective properties, such as inhibition of amyloid-β aggregation. Low plasma ApoA1 concentrations are associated with Alzheimer's disease (AD). Little is known about ApoA1 levels in the pre-dementia stages of AD. OBJECTIVE: To investigate associations between cerebrospinal fluid (CSF) and plasma ApoA1 levels and clinical progression toward AD in non-demented elderly. METHODS: From the Amsterdam Dementia Cohort, we included 429 non-demented elderly with subjective cognitive decline (SCD; n = 206, 61±9 years, Mini-Mental State Exam (MMSE) 28±2) and mild cognitive impairment (MCI; n = 223, 67±8 years, MMSE 27±2), with a mean follow-up of 2.5±1.6 years. We used Cox proportional hazard models to investigate relations between CSF and plasma ApoA1 concentrations and clinical progression, defined as progression to MCI or AD for SCD, and progression to AD for MCI. Analyses were adjusted for age, gender, MMSE, and plasma cholesterol levels. Analyses were stratified for diagnosis and APOEɛ4 carriership. RESULTS: 117 patients (27%) showed clinical progression. One standard deviation increase of CSF ApoA1 was associated with a 30% increased risk of clinical progression (hazard ratio (HR) (95% CI)  = 1.3(1.0-1.6)). The effect appeared to be attributable to the APOEɛ4 carriers with SCD (HR 3.3(1.0-10.9)). Lower plasma ApoA1 levels were associated with an increased risk of clinical progression in APOEɛ4 carriers with SCD (HR 5.0(1.3-18.9)). CONCLUSION: Higher CSF and lower plasma ApoA1 levels were associated with an increased risk of clinical progression in APOEɛ4 carriers with SCD; suggesting that ApoA1 may be involved in the earliest stages of AD.

An Arabic Version of the Cognitive Subscale of the Alzheimer's Disease Assessment Scale (ADAS-Cog): Reliability, Validity, and Normative Data. - Ben Jemaa, Sonia; Attia Romdhane, Neila; Bahri-Mrabet, Amel; Jendli, Adel; Le Gall, Didier; Bellaj, Tarek (J Alzheimers Dis, 2017)
The Alzheimer's Disease Assessment Scale's cognitive subscale (ADAS-Cog) is the most widely used instrument for screening cognitive dysfunction in Alzheimer's disease. The aim of the present study was to develop an Arabic version of this scale (A-ADAS-Cog), examine its psychometric properties (reliability and validity), and provide normative data. The A-ADAS-Cog), an Arabic version of the Mini-Mental State Examination (A-MMSE), and a Standardized Clinical Dementia Rating Scale (CDR) were administered to three Tunisian groups: 124 normal controls (NC), 33 patients with non-Alzheimer dementia (N-AD), and 25 patients with Alzheimer's disease (AD). The A-ADAS-Cog scores were significantly affected by age and education. A correction table was constructed to control these effects. The results showed that the A-ADAS-Cog has good internal consistency and reliability (α= 0.82 for AD). The test-retest reliability of the A-ADAS-Cog was stable over time (r = 0.97). An evaluation of the construct validity of the A-ADAS-Cog using principal component analysis led to a solution with three factors (memory, language and praxis), which explained 72% of the variance. The concurrent validity of the A-ADAS-Cog was established using the A-MMSE score (r = -0.86), CDR Sum of Boxes score (CDR-SB; r = 0.87), and global CDR score (CDR-Global; r = 0.74). Finally, the A-ADAS-Cog has an excellent discriminating power in the diagnosis of AD (ROC area = 0.92). A cut-off score of 10 (sensitivity = 84% and specificity = 91%) is indicated for the screening of the AD. Overall, the results indicated that the A-ADAS-Cog is psychometrically reliable and valid and provides promising results for screening of dementia in Arabic speaking patients.

Association between Anti-Dementia Treatment Persistence and Daily Dosage of the First Prescription: A Retrospective Analysis in Neuropsychiatric Practices in Germany. - Bohlken, Jens; Jacob, Louis; Kostev, Karel (J Alzheimers Dis, 2017)
BACKGROUND: High adherence and persistence are important for the efficacy of anti-dementia treatments. OBJECTIVE: The goal of this study was to analyze the association between anti-dementia treatment persistence and daily dosage of the first prescription in patients treated in neuropsychiatric practices in Germany. METHODS: This study included patients aged 60 years or over who were diagnosed with Alzheimer's disease and received anti-dementia prescriptions (galantamine, donepezil, memantine, and rivastigmine) for the first time between 2005 and 2014. The main outcome measure was the treatment persistence rate within 12 months after the index date as a function of the first dose. Cox proportional hazards regression models were used to estimate the relation between persistence and daily dosages after adjusting for age, gender, and residence in nursing homes. RESULTS: In this study, 2,442, 5,669, 4,416, 642, and 2,334 patients received galantamine, donepezil, memantine, oral rivastigmine, and patch rivastigmine, respectively. After 12 months of follow-up, continuation rates were similar for individuals using different doses of galantamine, donepezil, oral rivastigmine, and patch rivastigmine, but were significantly different for those taking memantine. Patients using 20 mg of memantine were less likely to discontinue their treatment than patients using 10 mg (HR = 0.88, 95% CI: 0.80-0.96). There was no significant association between daily dosages and persistence for the other drugs (HRs ranging from 0.86 to 1.15). CONCLUSIONS: There was no significant association between treatment persistence and daily dosages in patients with Alzheimer's disease in Germany who were treated with galantamine, donepezil, or rivastigmine.

Association of Cancer History with Alzheimer's Disease Dementia and Neuropathology. - Yarchoan, Mark; James, Bryan D; Shah, Raj C; Arvanitakis, Zoe; Wilson, Robert S; Schneider, Julie; Bennett, David A; Arnold, Steven E (J Alzheimers Dis, 2017)
BACKGROUND: Cancer and Alzheimer's disease (AD) are common diseases of aging and share many risk factors. Surprisingly, however, epidemiologic data from several recent independent cohort studies suggest that there may be an inverse association between these diseases. OBJECTIVE: To determine the relationship between history of cancer and odds of dementia proximate to death and neuropathological indices of AD. METHODS: Using data from two separate clinical-pathologic cohort studies of aging and AD, the Religious Orders Study (ROS) and the Rush Memory and Aging Project (MAP), we compared odds of AD dementia proximate to death among participants with and without a history of cancer. We then examined the relation of history of cancer with measures of AD pathology at autopsy, i.e., paired helical filament tau (PHFtau) neurofibrillary tangles and amyloid-β load. RESULTS: Participants reporting a history of cancer had significantly lower odds of AD (OR 0.70 [0.55-0.89], p = 0.0040) proximate to death as compared to participants reporting no prior history of cancer. The results remained significant after adjusting for multiple risk factors including age, sex, race, education, and presence of an APOEɛ4 allele. At autopsy, participants with a history of cancer had significantly fewer PHFtau tangles (p < 0.001) than participants without a history of cancer, but similar levels of amyloid-β. CONCLUSIONS: Cancer survivors have reduced odds of developing AD and a lower burden of neurofibrillary tangle deposition.

Association of Kidney Function Biomarkers with Brain MRI Findings: The BRINK Study. - Vemuri, Prashanthi; Knopman, David S; Jack, Clifford R; Lundt, Emily S; Weigand, Stephen D; Zuk, Samantha M; Thostenson, Kaely B; Reid, Robert I; Kantarci, Kejal; Slinin, Yelena; Lakshminarayan, Kamakshi; Davey, Cynthia S; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Chronic kidney disease (CKD) studies have reported variable prevalence of brain pathologies, in part due to low inclusion of participants with moderate to severe CKD. OBJECTIVE: To measure the association between kidney function biomarkers and brain MRI findings in CKD. METHODS: In the BRINK (BRain IN Kidney Disease) study, MRI was used to measure gray matter volumes, cerebrovascular pathologies (white matter hyperintensity (WMH), infarctions, microhemorrhages), and microstructural changes using diffusion tensor imaging (DTI). We performed regression analyses with estimated glomerular filtration rate (eGFR) and urine albumin to creatinine ratio (UACR) as primary predictors, and joint models that included both predictors, adjusted for vascular risk factors. RESULTS: We obtained 240 baseline MRI scans (150 CKD with eGFR <45 in ml/min/1.73 m2; 16 mild CKD: eGFR 45-59; 74 controls: eGFR≥60). Lower eGFR was associated with greater WMH burden, increased odds of cortical infarctions, and worsening diffusion changes throughout the brain. In eGFR models adjusted for UACR, only cortical infarction associations persisted. However, after adjusting for eGFR, higher UACR provided additional information related to temporal lobe atrophy, increased WMH, and whole brain microstructural changes as measured by increased DTI mean diffusivity. CONCLUSIONS: Biomarkers of kidney disease (eGFR and UACR) were associated with MRI brain changes, even after accounting for vascular risk factors. UACR adds unique additional information to eGFR regarding brain structural and diffusion biomarkers. There was a greater impact of kidney function biomarkers on cerebrovascular pathologies and microstructural brain changes, suggesting that cerebrovascular etiology may be the primary driver of cognitive impairment in CKD.

Cerebrospinal Fluid Aβ42/Aβ40 as a Means to Limiting Tube- and Storage-Dependent Pre-Analytical Variability in Clinical Setting. - Gervaise-Henry, Christelle; Watfa, Gasshan; Albuisson, Eliane; Kolodziej, Allan; Dousset, Brigitte; Olivier, Jean-Luc; Jonveaux, Thérèse Rivasseau; Malaplate-Armand, Catherine (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) cerebrospinal fluid (CSF) biomarkers have recently been included in the criteria for AD diagnosis. Unfortunately, their wider use in routine and interpretation require more standardization, particularly for the pre-analytical steps. In particular, amyloid-β (Aβ)42 peptide measurement is strongly influenced by the type of collection tube and by repeated freeze/thaw cycles. OBJECTIVE: The objectives of this study were to compare, in clinical setting, the impact of collection tubes and the repetition of freeze/thaw cycles on Aβ42 and Aβ40 concentrations and consequently determine if the Aβ42/Aβ40 ratio could resolve the diagnosis difficulties related to these pre-analytical parameters. METHODS: CSF from 35 patients was collected in different polypropylene (PP) and stored at - 80°C after sampling. For CSF collected in the reference tube, three successive freeze-thaw cycles were done. Aβ42 and Aβ40 concentrations were determined in each condition in order to calculate the Aβ42/Aβ40 ratio. RESULTS: Our results showed that CSF Aβ42 and Aβ40 values were significantly different according to the type of collection tube and the number of freeze/thaw cycles. Although the calculation of the Aβ42/Aβ40 ratio eliminated the effect of PP tube-dependent variation, this was not the case for freeze-thaw cycle-associated variation. CONCLUSION: The use of Aβ42/Aβ40 ratio rather than Aβ42 alone could contribute toward pre-analytical standardization, thus allowing the general use of CSF AD biomarkers in routine practice.

Cerebrospinal Fluid Biomarkers and Clinical Progression in Patients with Subjective Cognitive Decline and Mild Cognitive Impairment. - Wolfsgruber, Steffen; Polcher, Alexandra; Koppara, Alexander; Kleineidam, Luca; Frölich, Lutz; Peters, Oliver; Hüll, Michael; Rüther, Eckart; Wiltfang, Jens; Maier, Wolfgang; Kornhuber, Johannes; Lewczuk, Piotr; et al. (J Alzheimers Dis, 2017)
BACKGROUND: There is very limited data on the prevalence of abnormal cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD) and their predictive value for clinical progression in memory clinic patients with subjective cognitive decline (SCD). OBJECTIVE: To assess the frequency of abnormal CSF biomarkers of AD and their predictive value for clinical progression in memory clinic patients with SCD in comparison to patients with mild cognitive impairment (MCI) from the same cohort. METHODS: We analyzed prospective data from memory clinic patients of the German Competence Network Dementia cohort with a baseline diagnosis of SCD (n = 82) or MCI (n = 134), distinguished by actuarial neuropsychological MCI criteria ("Jak-Bondi criteria"). Risk of clinical progression during 3-year follow-up was evaluated with Cox-Proportional-Hazard models. RESULTS: Prevalence of abnormal values in CSF markers of tau-mediated neurodegeneration (67.8% versus 46.3%) but not of amyloid deposition (40.3% versus 35.4%) was significantly higher in MCI compared to SCD. The rate of incident AD dementia (26.1% versus 12.2%) was also significantly higher in MCI. In SCD, additional 22% progressed to MCI during follow-up. Combined amyloid/tau abnormality was the strongest predictor of clinical progression in both groups. CONCLUSION: High prevalence of biomarker abnormality and clinical progression, together with the predictive value of CSF biomarkers, in memory clinic patients with SCD support the validity and usefulness of this condition as a "pre-MCI" at risk stage of AD.

Challenges and Considerations Related to Studying Dementia in Blacks/African Americans. - Ighodaro, Eseosa T; Nelson, Peter T; Kukull, Walter A; Schmitt, Frederick A; Abner, Erin L; Caban-Holt, Allison; Bardach, Shoshana H; Hord, Derrick C; Glover, Crystal M; Jicha, Gregory A; Van Eldik, Linda J; Byrd, Alexander X; et al. (J Alzheimers Dis, 2017)
Blacks/African Americans have been reported to be ∼2-4 times more likely to develop clinical Alzheimer's disease (AD) compared to Whites. Unfortunately, study design challenges (e.g., recruitment bias), racism, mistrust of healthcare providers and biomedical researchers, confounders related to socioeconomic status, and other sources of bias are often ignored when interpreting differences in human subjects categorized by race. Failure to account for these factors can lead to misinterpretation of results, reification of race as biology, discrimination, and missed or delayed diagnoses. Here we provide a selected historical background, discuss challenges, present opportunities, and suggest considerations for studying health outcomes among racial/ethnic groups. We encourage neuroscientists to consider shifting away from using biologic determination to interpret data, and work instead toward a paradigm of incorporating both biological and socio-environmental factors known to affect health outcomes with the goal of understanding and improving dementia treatments for Blacks/African Americans and other underserved populations.

Chronic Neurodegenerative Illnesses and Epilepsy in Danish Adventists and Baptists: A Nationwide Cohort Study. - Thygesen, Lau Caspar; Gimsing, Louise NØrreslet; Bautz, Andrea; Hvidt, Niels Christian; Johansen, Christoffer (J Alzheimers Dis, 2017)
BACKGROUND: Limited knowledge of the influence of lifestyle risk factors and religious living on chronic neurological diseases exist. Seventh-day Adventists (SDA) do not consume tobacco, alcohol, or pork, and many adhere to lacto-ovo-vegetarian diet, and Baptists discourage excessive use of alcohol and tobacco. OBJECTIVE: We investigated whether the incidence of four common chronic neurological illnesses: dementia, Alzheimer's disease, Parkinson's disease, and epilepsy in a large cohort of Danish Adventists and Baptists was different compared to the general Danish population. Three of the illnesses are neurodegenerative, whereas epilepsy can occur at any age. METHODS: We compared hospital admission rates for some major neurological diseases among members of the Danish Religious Societies Health Study comprising 6,532 SDA and 3,720 Baptists with the general Danish population. Standardized incidence rates (SIR) stratified by sex, age, and calendar time were calculated. RESULTS: SIR of dementia or Alzheimer's disease was significantly decreased for members of both communities (SDA, 0.78; 95% CI, 0.67-#x2013;0.90 and Baptists, 0.59; 0.47-#x2013;0.73). The SIRs of Parkinson's disease and epilepsy were not significantly different compared to the general population. CONCLUSIONS: We observe reduced incidence for dementia or Alzheimer's disease in a large cohort of members of two religious communities characterized by lifestyle recommendations. More studies are needed to disentangle the interaction between such lifestyle and other components of the religious belief system.

Chronotropic Response and Cognitive Function in a Cohort at Risk for Alzheimer's Disease. - Law, Lena L; Schultz, Stephanie A; Boots, Elizabeth A; Einerson, Jean A; Dougherty, Ryan J; Oh, Jennifer M; Korcarz, Claudia E; Edwards, Dorothy F; Koscik, Rebecca L; Dowling, N Maritza; Gallagher, Catherine L; Bendlin, Barbara B; et al. (J Alzheimers Dis, 2017)
The objective of this study was to examine the association of chronotropic response (CR) and heart rate (HR) recovery- two indices of cardiovascular function within the context of a graded exercise test- with cognitive performance in a cognitively healthy, late-middle-aged cohort at risk for Alzheimer's disease (AD). Ninety participants (age = 63.52±5.86 years; 65.6% female) from the Wisconsin Registry for Alzheimer's Prevention participated in this study. They underwent graded exercise testing and a comprehensive neuropsychological assessment that assessed the following four cognitive domains: Immediate Memory, Verbal & Learning Memory, Working Memory, and Speed & Flexibility. Regression analyses, adjusted for age, sex, and education, were used to examine the association between CR, HR recovery, and cognition. We found significant associations between CR and cognitive performance in the domains of Immediate Memory, Verbal Learning & Memory, and Speed & Flexibility. In contrast, HR recovery was not significantly associated with cognitive function. The association between CR and cognition persisted even after controlling for HR recovery. Together, these findings indicatethat, in a cognitively normal, late-middle-aged cohort, CR is a stronger correlate of cognitive performance than HR recovery. Overall, this study reinforces the idea that cardiovascular health plays an important role in cognitive function, specifically in a cohort at risk for AD; and that interventions that promote vascular health may be a viable pathway to preventing or slowing cognitive decline due to AD.

Classification of Alzheimer's Disease and Prediction of Mild Cognitive Impairment Conversion Using Histogram-Based Analysis of Patient-Specific Anatomical Brain Connectivity Networks. - Beheshti, Iman; Maikusa, Norihide; Daneshmand, Morteza; Matsuda, Hiroshi; Demirel, Hasan; Anbarjafari, Gholamreza (J Alzheimers Dis, 2017)
In this study, we investigated the early detection of Alzheimer's disease (AD) and mild cognitive impairment (MCI) conversion to AD through individual structural connectivity networks using structural magnetic resonance imaging (sMRI) data. In the proposed method, the cortical morphometry of individual gray matter images were used to construct structural connectivity networks. A statistical feature generation approach based on histogram-based feature generation procedure was proposed to represent a statistical-pattern of connectivity networks from a high-dimensional space into low-dimensional feature vectors. The proposed method was evaluated on numerous samples including 61 healthy controls (HC), 42 stable-MCI (sMCI), 45 progressive-MCI (pMCI), and 83 AD subjects at the baseline from the J-ADNI data-set using support vector machine classifier. The proposed method yielded a classification accuracy of 84.17%, 70.38%, and 61.05% in identifying AD/HC, MCIs/HCs, and sMCI/pMCI, respectively. The experimental results show that the proposed method performed in a comparable way to alternative methods using MRI data.

The Correlation between Inflammatory Biomarkers and Polygenic Risk Score in Alzheimer's Disease. - Morgan, Angharad R; Touchard, Samuel; O'Hagan, Caroline; Sims, Rebecca; Majounie, Elisa; Escott-Price, Valentina; Jones, Lesley; Williams, Julie; Morgan, B Paul (J Alzheimers Dis, 2017)
Plasma biomarkers to aid the early diagnosis of Alzheimer's disease (AD) or to monitor disease progression have long been sought and continue to be widely studied. Biomarkers that correlate with AD polygenic risk score, a measure of the polygenic architecture of the disease and highly predictive of AD status, would be excellent candidates. Therefore, we undertook a preliminary study to assess the association of plasma inflammatory biomarkers with an overall AD polygenic risk score as well as with an inflammation-specific AD polygenic risk score in a sample set of 93 AD cases. We measured five complement biomarkers [complement receptor 1 (CR1), clusterin, complement component 9 (C9), C1 inhibitor (C1inh), terminal complement complex (TCC)] and the benchmark inflammatory marker C-reactive protein (CRP). Plasma clusterin level showed an association with overall AD polygenic risk score, while clusterin, C1inh, and CRP levels each displayed some association with the inflammatory-specific AD polygenic risk score. The results suggest that elevated plasma levels of inflammatory biomarkers, including complement proteins, associate with polygenic risk scores in AD, further strengthening the link between genetic and biomarker disease predictors and indicating a potential role for these markers in disease prediction and patient stratification in AD.

Cortical Thickness and Depressive Symptoms in Cognitively Normal Individuals: The Mayo Clinic Study of Aging. - Pink, Anna; Przybelski, Scott A; Krell-Roesch, Janina; Stokin, Gorazd B; Roberts, Rosebud O; Mielke, Michelle M; Knopman, David S; Jack, Clifford R; Petersen, Ronald C; Geda, Yonas E (J Alzheimers Dis, 2017)
Altered cortical thickness has been observed in aging and various neurodegenerative disorders. Furthermore, reduced hippocampal volume has been reported in late-life depression. Even mild depressive symptoms are common in the elderly. However, little is known about the structural MRI measures of depressive symptoms in normal cognitive aging. Thus we sought to examine the association between depressive symptoms with cortical thickness and hippocampal volume as measured by brain MRI among community-dwelling participants. We conducted a cross-sectional study derived from the ongoing population-based Mayo Clinic Study of Aging, involving cognitively normal participants (N = 1,507) aged≥70 years. We observed that depressive symptoms were associated with lower global cortical thickness and lower thickness in specific prefrontal and temporal cortical regions, labeled by FreeSurfer software, version 5.3. As expected, the strength of correlation was very small, given that participants were community-dwelling with only mild depressive symptoms. We did not observe associations between hippocampal volume and depressive symptoms. These findings may provide insight into the structural correlates of mild depressive symptoms in elderly participants.

Decreased Expression of hsa-miR-4274 in Cerebrospinal Fluid of Normal Pressure Hydrocephalus Mimics with Parkinsonian Syndromes. - Jurjević, Ivana; Miyajima, Masakazu; Ogino, Ikuko; Akiba, Chihiro; Nakajima, Madoka; Kondo, Akihide; Kikkawa, Mika; Kanai, Mitsuyasu; Hattori, Nobutaka; Arai, Hajime (J Alzheimers Dis, 2017)
BACKGROUND: Patients presenting with the classical idiopathic normal pressure hydrocephalus (iNPH) triad often show additional parkinsonian spectrum signs. Accurate differential diagnosis strongly influences the long-term outcome of cerebrospinal fluid (CSF) shunting. OBJECTIVE: The aim of this study was to find potential CSF microRNA (miRNA) biomarkers for NPH mimics with parkinsonian syndromes that can reliably distinguish them from iNPH patients. METHODS: Two cohorts of 81 patients (cohort 1, n = 55; cohort 2, n = 26) with possible iNPH who were treated in two centers between January 2011 and May 2014 were studied. In both cohorts, CSF samples were obtained from patients clinically diagnosed with iNPH (n = 21 and n = 10, respectively), possible iNPH with parkinsonian spectrum (PS) (n = 18, n = 10, respectively), possible iNPH with Alzheimer's disease (AD) (n = 16), and non-affected elderly individuals (NC) (n = 6). A three-step qRT-PCR analysis of the CSF samples was performed to detect miRNAs that were differentially expressed in the groups. RESULTS: The expression of hsa-miR-4274 in CSF was decreased in both cohorts of PS group patients (cohort 1: p < 0.0001, cohort 2: p < 0.0001), and was able to distinguish PS from iNPH with high accuracy (area under the curve = 0.908). The CSF concentration of hsa-miR-4274 also correlated with the specific binding ratio of ioflupane (123I) dopamine transporter scan (r = -0.494, p = 0.044). By contrast, the level of hsa-miR-4274 was significantly increased in the PS group after CSF diversion. CONCLUSION: Levels of CSF hsa-miR-4274 can differentiate PS from patients with iNPH, AD, and NC. This may be clinically useful for diagnostic purposes and predicting shunt treatment responses.

Deficit in Central Auditory Processing as a Biomarker of Pre-Clinical Alzheimer's Disease. - Tuwaig, Miranda; Savard, Mélissa; Jutras, Benoît; Poirier, Judes; Collins, D Louis; Rosa-Neto, Pedro; Fontaine, David; Breitner, John C S (J Alzheimers Dis, 2017)
Prevention of dementia due to Alzheimer's disease (d/AD) requires interventions that slow the disease process prior to symptom onset. To develop such interventions, one needs metrics that assess pre-symptomatic disease progression. Familiar measures of progression include cerebrospinal fluid (CSF) biochemical and imaging analyses, as well as cognitive testing. Changes in the latter can sometimes be difficult to distinguish from effects of "normal" aging. A different approach involves testing of "central auditory processing" (CAP), which enables comprehension of auditory stimuli amidst a distracting background (e.g., conversation in a noisy bar or restaurant). Such comprehension is often impaired in d/AD. Similarly, effortful or diminished auditory comprehension is sometimes reported by cognitively healthy elders, raising the possibility that CAP deficit may be a marker of pre-symptomatic AD. In 187 cognitively and physically healthy members of the aging, AD family history-positive PREVENT-AD cohort, we therefore evaluated whether CAP deficits were associated with known markers of AD neurodegeneration. Such markers included CSF tau concentrations and magnetic resonance imaging volumetric and cortical thickness measures in key AD-related regions. Adjusting for age, sex, education, pure-tone hearing, and APOEɛ4 status, we observed a persistent relationship between CAP scores and CSF tau levels, entorhinal and hippocampal cortex volumes, cortical thickness, and deficits in cognition (Repeatable Battery for Assessment of Neuropsychological Status total score, and several of its index scales). These cross-sectional observations suggest that CAP may serve as a novel metric for pre-symptomatic AD pathogenesis. They are therefore being followed up longitudinally with larger samples.

Dementia and Pressure Ulcers: Is There a Close Pathophysiological Interrelation? - Jaul, Efraim; Meiron, Oded (J Alzheimers Dis, 2017)
The current theoretical investigation aimed to explore common pathophysiological mechanisms underlying dementia and pressure ulcers (PU). Along with the increased longevity, especially in frail elderly patients, there is a higher rate of functional and cognitive impairment with dementia coinciding with immobility, which results in a higher rate of PU. Understanding common etiological paths resulting in pressure ulcers and dementia is likely to produce new treatment strategies that could lead to the prevention of comorbid complications. Data collected from elderly dementia patients indicate a deterioration of several neurophysiological subsystems associated with motor, sensory, autonomic, cognitive, or behavioral pathways, supporting a "close pathophysiological interrelation" perspective linking PU with dementia progression. Overall, the authors' theoretical systemic-model of disease progression and PU comorbidity proposes that increased clinician awareness to PU in mild to moderate dementia may suppress the accelerated development of PU, resulting in less patient suffering, reduced long-term care hospitalization, and hopefully PU prevention.

Depressive Symptoms and Tau Accumulation in the Inferior Temporal Lobe and Entorhinal Cortex in Cognitively Normal Older Adults: A Pilot Study. - Gatchel, Jennifer R; Donovan, Nancy J; Locascio, Joseph J; Schultz, Aaron P; Becker, J Alex; Chhatwal, Jasmeer; Papp, Kathryn V; Amariglio, Rebecca E; Rentz, Dorene M; Blacker, Deborah; Sperling, Reisa A; Johnson, Keith A; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Depressive symptoms are common in older adults and associated with increased morbidity and cognitive decline. These symptoms occur during preclinical and prodromal stages of Alzheimer's disease (AD), but their relationship to tau, one of the main AD proteinopathies, is poorly understood. OBJECTIVE: The objective of this study was to investigate the cross-sectional association between depressive symptoms and cerebral tau [18F T807 (also known as 18F-AV-1451) tau positron emission tomography (PET) imaging] in cognitively normal (CN) older adults. METHODS: We measured depressive symptoms using the Geriatric Depression Scale (GDS), and in vivo cerebral tau using T807 PET in 111 CN older adults. We employed general linear regression models to evaluate the relationship of GDS score regressed on entorhinal cortex (EC) or inferior temporal (IT) tau in separate backward elimination models. Other predictors included age, sex, and in secondary analyses, amyloid (Pittsburgh Compound B PET). RESULTS: Higher GDS was significantly associated with greater IT tau (partial r = 0.188, p = 0.050) and marginally associated with greater EC tau (partial r = 0.183, p = 0.055). In additional analyses including both linear and quadratic age terms, we found a significant U-shaped relation of GDS to age (p = 0.001). CONCLUSIONS: Results suggest that IT and EC tau are modestly associated with depressive symptoms in CN older adults. Findings suggest a link between depressive symptoms and tau-mediated neurodegeneration in a region vulnerable in AD. Future longitudinal studies examining the association of more severe depressive symptoms and cerebral tau accumulation are needed to substantiate this finding and to guide prevention and treatment in AD.

Depressive Symptoms are Associated with Progression to Dementia in Patients with Amyloid-Positive Mild Cognitive Impairment. - Moon, Byungseung; Kim, Seongheon; Park, Young Ho; Lim, Jae-Sung; Youn, Young Chul; Kim, SangYun; Jang, Jae-Won (J Alzheimers Dis, 2017)
BACKGROUND: Depressive symptoms are prevalent in patients with mild cognitive impairment (MCI) and are considered to be a risk factor for progression to dementia. OBJECTIVE: The purpose of this study was to evaluate whether depressive symptoms in MCI promote disease progression in a manner related to amyloid status, and to determine the relationship between depressive symptoms and longitudinal cerebral structural changes. METHODS: Baseline data for 336 patients with MCI (75 with depression and 261 without) from the Alzheimer's Disease Neuroimaging Initiative study were analyzed. All participants underwent comprehensive cognitive testing, volumetric magnetic resonance imaging (MRI), and [18F]AV45 positron emission tomography amyloid imaging. Depressive symptoms were measured using the Neuropsychiatric Inventory Questionnaire. A voxel-based morphometric analysis using volumetric brain MRI data was used to compare longitudinal structural changes related to depressive symptoms. RESULTS: The conversion rate to dementia was different between patients with and without depression in amyloid-positive MCI (40.8% versus 19.7%, respectively; p = 0.006). Patients who were amyloid-positive at baseline also exhibited a greater degree of 2-year cognitive decline. Depression in amyloid-positive MCI was associated with longitudinal cortical atrophy in the left cingulate gyrus. CONCLUSION: Our study indicates that the presence of depressive symptoms in patients with amyloid-positive MCI is associated with higher progression to dementia and longitudinal cortical atrophy.

Detecting At-Risk Alzheimer's Disease Cases. - Fladby, Tormod; Pålhaugen, Lene; Selnes, Per; Waterloo, Knut; Bråthen, Geir; Hessen, Erik; Almdahl, Ina Selseth; Arntzen, Kjell-Arne; Auning, Eirik; Eliassen, Carl Fredrik; Espenes, Ragna; Grambaite, Ramune; et al. (J Alzheimers Dis, 2017)
While APOEɛ4 is the major genetic risk factor for Alzheimer's disease (AD), amyloid dysmetabolism is an initial or early event predicting clinical disease and is an important focus for secondary intervention trials. To improve identification of cases with increased AD risk, we evaluated recruitment procedures using pathological CSF concentrations of Aβ42 (pAβ) and APOEɛ4 as risk markers in a multi-center study in Norway. In total, 490 subjects aged 40-80 y were included after response to advertisements and media coverage or memory clinics referrals. Controls (n = 164) were classified as normal controls without first-degree relatives with dementia (NC), normal controls with first-degree relatives with dementia (NCFD), or controls scoring below norms on cognitive screening. Patients (n = 301) were classified as subjective cognitive decline or mild cognitive impairment. Subjects underwent a clinical and cognitive examination and MRI according to standardized protocols. Core biomarkers in CSF from 411 and APOE genotype from 445 subjects were obtained. Cases (both self-referrals (n = 180) and memory clinics referrals (n = 87)) had increased fractions of pAβ and APOEɛ4 frequency compared to NC. Also, NCFD had higher APOEɛ4 frequencies without increased fraction of pAβ compared to NC, and cases recruited from memory clinics had higher fractions of pAβ and APOEɛ4 frequency than self-referred. This study shows that memory clinic referrals are pAβ enriched, whereas self-referred and NCFD cases more frequently are pAβ negative but at risk (APOEɛ4 positive), suitable for primary intervention.

Development of Nasal Lipid Nanocarriers Containing Curcumin for Brain Targeting. - Vaz, Gustavo Richter; Hädrich, Gabriela; Bidone, Juliana; Rodrigues, Jamile Lima; Falkembach, Mariana Corrêa; Putaux, Jean-Luc; Hort, Mariana Appel; Monserrat, José Maria; Varela Junior, Antônio Sergio; Teixeira, Helder Ferreira; Muccillo-Baisch, Ana Luiza; Horn, Ana Paula; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Curcumin (CUR) has properties that can be useful for the treatment of Alzheimer's disease. Such properties are the inhibition of amyloid-β-protein (Aβ) aggregation, Aβ-induced inflammation, and activities of β-secretase and acetylcholinesterase. However, previous studies have revealed that CUR exhibited low bioavailability and difficulties in reaching the brain. OBJECTIVE: To overcome such drawbacks, this study aims at developing nasal lipid nanocarriers loaded with CUR to effectively target the brain. METHODS: The lipid nanocarriers (NE) were prepared using the hot solvent diffusion associated with the phase inversion temperature methods. Physico-chemical and morphological characterizations and in vitro drug release of the nanocarriers were carried out. The CUR permeation/retention was analyzed in Franz-type diffusion cell using porcine nasal mucosa. Confocal laser scan and histopathological studies were also performed. RESULTS: The results showed that the NE sizes ranged between 18 nm and 44 nm with negative zeta potential. The CUR content ranged from 0.24 to 1.50 mg/mL with an encapsulation efficiency of 99%. The profiles of CUR release indicated a biphasic kinetics. CUR-NE permeation across the porcine nasal mucosa was higher when compared to free CUR. These results have also been validated through an analysis on a confocal microscopy. In addition, no toxicity on the nasal mucosa has been observed in a histopathological analysis. CONCLUSION: These results suggest that it is possible to develop NEs with a high content of CUR and small particle size. Such an encapsulation increases the potential of CUR permeation across the porcine nasal mucosa.

The Diagnostic and Prognostic Value of Neuropsychological Assessment in Memory Clinic Patients. - Jansen, Willemijn J; Handels, Ron L H; Visser, Pieter Jelle; Aalten, Pauline; Bouwman, Femke; Claassen, Jurgen; van Domburg, Peter; Hoff, Erik; Hoogmoed, Jan; Leentjens, Albert F G; Rikkert, Marcel Olde; Oleksik, Ania M; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Neuropsychological testing has long been embedded in daily clinical practice at memory clinics but the added value of a complete neuropsychological assessment (NPA) to standard clinical evaluation is unknown. OBJECTIVE: To evaluate the added diagnostic and prognostic value of NPA to clinical evaluation only in memory clinic patients. METHODS: In 221 memory clinic patients of a prospective cohort study, clinical experts diagnosed clinical syndrome (subjective cognitive impairment (SCI), mild cognitive impairment (MCI), or dementia) and etiology (Alzheimer's disease (AD) or no AD), and provided a prognosis of disease course (decline or no decline) before and after results of NPA were made available. The reference standard was a panel consensus based on all clinical information at baseline and up to 2 follow-up assessments. RESULTS: With NPA data available, clinicians changed their initial syndromal diagnosis in 22% of patients, and the etiological diagnosis as well as the prognosis in 15%. This led to an increase in correctly classified cases of 18% for syndromal diagnosis, 5% for etiological diagnosis, and 1% for prognosis. NPA data resulted in the largest improvement in patients initially classified as SCI (syndrome: 93.3% (n = 14) correctly reclassified, etiology: net reclassification improvement [NRI] = 0.61, prognosis: NRI = 0.13) or MCI (syndrome: 89.3% (n = 23) correctly reclassified, etiology: NRI = 0.17, prognosis: NRI = 0.14), while there was no improvement in patients with dementia (syndrome: 100% (n = 1) correctly reclassified, etiology: NRI = -0.05, prognosis: NRI = -0.06). Overall, inclusion of NPA in the diagnostic process increased confidence in all diagnoses with 6-7%. CONCLUSION: Administration of a complete NPA after standard clinical evaluation has added value for diagnosing cognitive syndrome and its underlying etiology in patients regarded as non-demented based on the first clinical impression.

Dickkopf 3 (Dkk3) Improves Amyloid-β Pathology, Cognitive Dysfunction, and Cerebral Glucose Metabolism in a Transgenic Mouse Model of Alzheimer's Disease. - Zhang, Li; Sun, Caixian; Jin, Yaxi; Gao, Kai; Shi, Xudong; Qiu, Wenying; Ma, Chao; Zhang, Lianfeng (J Alzheimers Dis, 2017)
Dysfunctional Wnt signaling is associated with Alzheimer's disease (AD), and activation of the Wnt signaling pathway inhibits AD development. Dickkopf 3 (Dkk3) is a modulator of the Wnt signaling pathway and is physiologically expressed in the brain. The role of Dkk3 in the pathogenesis of AD has not been evaluated. In the present study, we determined that Dkk3 expression was significantly decreased in brain tissue from AD patients and the AD transgenic mouse model APPswe/PS1dE9 (AD mice). Transgenic mice with brain tissue-specific Dkk3 expression were generated or crossed with AD mice to study the effects of Dkk3 on AD. In AD mice, transgenic expression of Dkk3 improved abnormalities in learning, memory, and locomotor activity, reduced the accumulation of amyloid-β, and ameliorated glucose uptake deficits. Furthermore, we determined that Dkk3 downregulated GSK-3β, a central negative regulator in canonical Wnt signaling, and upregulated PKCβ1, a factor implicated in noncanonical Wnt signaling. This indicates that increased activation of GSK-3β and the inhibition of PKCβ1 in AD patients may be responsible for the dysfunctional Wnt signaling in AD. In summary, our data suggest that Dkk3 is an agonist of Wnt signaling, and the ability of transgenic expression of Dkk3 to compensate for the decrease in Dkk3 expression in AD mice, reverse dysfunctional Wnt signaling, and partially inhibit the pathological development of AD suggests that Dkk3 could serve as a therapeutic target for the treatment of AD.

Dietary Lycopene Supplementation Improves Cognitive Performances in Tau Transgenic Mice Expressing P301L Mutation via Inhibiting Oxidative Stress and Tau Hyperphosphorylation. - Yu, Lixia; Wang, Weiguang; Pang, Wei; Xiao, Zhonghai; Jiang, Yugang; Hong, Yan (J Alzheimers Dis, 2017)
BACKGROUND: Oxidative stress is implicated in the pathogenesis of Alzheimer's disease (AD) and other tauopathies and participates in their development by promoting hyperphosphorylation of microtubule-associated protein tau. Lycopene, as an effective antioxidant, combined with vitamin E seemed to be additive against oxidative stress. OBJECTIVE: The present study was undertaken to examine whether lycopene or lycopene/vitamin E could exert protective effects on memory deficit and oxidative stress in tau transgenic mice expressing P301L mutation. MATERIALS AND METHODS: P301L transgenic mice were assigned to three groups: P301L group (P301L), P301L+lycopene (Lyc), and P301L+lycopene/vitamin E (Lyc+VE). Age-matched C57BL/6J mice as wild type controls (Con) were used in the present study. Spatial memory was assessed by radial arm while passive memories were evaluated by step-down and step-through tests. Levels of tau phosphorylation were detected by western blot. Oxidative stress biomarkers were measured in the serum using biochemical assay kits. RESULTS: Compared with the control group, P301L mice displayed significant spatial and passive memory impairments, elevated malondialdehyde (MDA) levels and decreased glutathione peroxidase (GSH-Px) activities in serum, and increased tau phosphorylation at Thr231/Ser235, Ser262, and Ser396 in brain. Supplementations of lycopene or lycopene/vitamin E could significantly ameliorate the memory deficits, observably decreased MDA concentrations and increased GSH-Px activities, and markedly attenuated tau hyperphosphorylation at multiple AD-related sites. CONCLUSIONS: Our findings indicated that the combination of lycopene and vitamin E antioxidants acted in a synergistic fashion to bring significant effects against oxidative stress in tauopathies.

Discriminative Properties of Hippocampal Hypoperfusion in Marijuana Users Compared to Healthy Controls: Implications for Marijuana Administration in Alzheimer's Dementia. - Amen, Daniel G; Darmal, Borhan; Raji, Cyrus A; Bao, Weining; Jorandby, Lantie; Meysami, Somayeh; Raghavendra, Cauligi S (J Alzheimers Dis, 2017)
BACKGROUND: Few studies have evaluated the impact of marijuana use on regional cerebral blood flow. OBJECTIVE: To determine whether perfusion in specific brain regions on functional neuroimaging, including those affected by Alzheimer's disease pathology, are abnormal in marijuana users compared to controls. METHOD: Persons with a diagnosis of cannabis use disorder by DSM-IV and DSM-V criteria (n = 982) were compared to controls (n = 92) with perfusion neuroimaging with SPECT at rest and at a concentration task. Perfusion estimates were quantified using a standard atlas. Cerebral perfusion differences were calculated using one-way ANOVA. Diagnostic separation was determined with discriminant analysis of all subjects. Feature selection with a minimum redundancy maximum relevancy (mRMR) identified predictive regions in a subset of marijuana users (n = 436) with reduced psychiatric co-morbidities. RESULTS: Marijuana users showed lower cerebral perfusion on average (p < 0.05). Discriminant analysis distinguished marijuana users from controls with correct classification of 96% and leave one out cross-validation of 92%. With concentration SPECT regions, there was correct classification of 95% with a leave-one-out cross validation of 90%. AUC analysis for concentration SPECT regions showed 95% accuracy, 90% sensitivity, and 83% specificity. The mRMR analysis showed right hippocampal hypoperfusion on concentration SPECT imaging was the most predictive in separating marijuana subjects from controls. CONCLUSION: Multiple brain regions show low perfusion on SPECT in marijuana users. The most predictive region distinguishing marijuana users from healthy controls, the hippocampus, is a key target of Alzheimer's disease pathology. This study raises the possibility of deleterious brain effects of marijuana use.

DNA Methylation and Tag SNPs of the BDNF Gene in Conversion of Amnestic Mild Cognitive Impairment into Alzheimer's Disease: A Cross-Sectional Cohort Study. - Xie, Bing; Liu, Zanchao; Liu, Wenxuan; Jiang, Lei; Zhang, Rui; Cui, Dongsheng; Zhang, Qingfu; Xu, Shunjiang (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a complex multifactorial disease influenced by both genetic and epigenetic factors. This study was aimed to evaluate the interaction between brain-derived neurotrophic factor (BDNF) promoter methylation status and tag single nucleotide polymorphisms (tag SNPs) on amnestic mild cognitive impairment (aMCI) and its conversion to AD. A total of 506 aMCI patients and 728 cognitive normal controls were included in the cross-sectional analysis. Patients (n = 458) from aMCI cohort were selected in the 5-year longitudinal study and classified into two groups: aMCI-stable group (n = 330) and AD-conversion group (n = 128). BDNF promoter methylation was detected by bisulfite-PCR amplification and pyrosequencing. Seven tag SNPs were genotyped by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS). Elevation of BDNF promoter methylation status was associated with aMCI and AD conversion. The higher methylation levels at CpG5 site showed significant main interactive effects between group and time (F = 8.827, p = 0.005). Genetic analysis revealed rs2030324 and rs6265 were associated with aMCI and rs6265 was associated with AD conversion. The interaction between DNA methylation of CpG5 and AA genotype of rs6265 had a risk role in the development of aMCI (p = 0.019, OR = 1.233, 95% CI: 1.117-1.303) and its progression to AD (p = 0.003, OR = 1.399, 95% CI: 1.198-1.477). The interactions between DNA methylation (CpG5) of the BDNF gene promoter and the tag SNP (rs6265) play important roles in the etiology of aMCI and its conversion to AD.

Dynamics of the Complement, Cytokine, and Chemokine Systems in the Regulation of Synaptic Function and Dysfunction Relevant to Alzheimer's Disease. - Jiang, Shanya; Bhaskar, Kiran (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common form of dementia affecting nearly 45 million people worldwide. However, the etiology of AD is still unclear. Accumulations of amyloid-β plaques and tau tangles, neuroinflammation, and synaptic and neuronal loss are the major neuropathological hallmarks of AD, with synaptic loss being the strongest correlating factor with memory and cognitive impairment in AD. Many of these pathological hallmarks influence each other during the onset and progression of the disease. Recent genetic evidence suggests the possibility of a causal link between altered immune pathways and synaptic dysfunction in AD. Emerging studies also suggest that immune system-mediated synaptic pruning could initiate early-stage pathogenesis of AD. This comprehensive review is toward understanding the crosstalk of neuron-microglia-astrocyte and dynamics of complement, cytokine, and chemokine systems in the regulation of synaptic function and dysfunction relevant to AD. We start with summarizing several immune pathways, involving complements, MHC-I and CX3CL1, which mediate synaptic elimination during development and in AD. We then will discuss the potential of targeting these molecules as therapeutic interventions or as biomarkers for AD.

Effects of Alzheimer's Disease-Associated Risk Loci on Amyloid-β Accumulation in the Brain of Idiopathic Normal Pressure Hydrocephalus Patients. - Laiterä, Tiina; Paananen, Jussi; Helisalmi, Seppo; Sarajärvi, Timo; Huovinen, Joel; Laitinen, Marjo; Rauramaa, Tuomas; Alafuzoff, Irina; Remes, Anne M; Soininen, Hilkka; Haapasalo, Annakaisa; Jääskeläinen, Juha E; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Idiopathic normal pressure hydrocephalus (iNPH) is a dementing condition featuring characteristic symptoms, ventriculomegaly, and normal or slightly elevated cerebrospinal fluid pressure. In Alzheimer's disease (AD) patients, diffuse aggregates of amyloid-β (Aβ) and neurofibrillary hyperphosphorylated tau are detected in the neocortex of the brain, while similar accumulation of Aβ is also detected in iNPH. Recent genome-wide association studies have identified several novel risk loci for AD, potentially affecting Aβ-related cellular processes. Apart from the apolipoprotein E ɛ4 allele (APOE4), the risk effect of single loci is low, emphasizing the importance of the polygenic risk score approach when assessing the combined effects. OBJECTIVE: To study the effects of AD-associated individual and polygenic risk score of single nucleotide polymorphisms (SNPs) on the accumulation of Aβ in the brain samples of iNPH patients. METHODS: A sample set of frontal cortex biopsies from 188 iNPH patients were divided into two groups according to the Aβ pathology. After the genotyping of the AD-associated risk loci, polygenic risk score was calculated for each iNPH patient and subsequently analyzed in relation to Aβ deposition. RESULTS: Apart from the APOE4, none of the SNPs revealed a statistically significant effect on the accumulation of Aβ in iNPH. Also, the non-APOE4 polygenic risk score did not associate with Aβ deposition. CONCLUSION: Novel AD-associated risk genes have no significant effect on Aβ accumulation in the brain of iNPH patients. However, APOE4 affects the Aβ deposition in the brain of iNPH and AD patients in a similar manner.

Effects of Regular and Long-Acting Insulin on Cognition and Alzheimer's Disease Biomarkers: A Pilot Clinical Trial. - Craft, Suzanne; Claxton, Amy; Baker, Laura D; Hanson, Angela J; Cholerton, Brenna; Trittschuh, Emily H; Dahl, Deborah; Caulder, Erin; Neth, Bryan; Montine, Thomas J; Jung, Youngkyoo; Maldjian, Joseph; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Long acting insulin detemir administered intranasally for three weeks enhanced memory for adults with Alzheimer's disease dementia (AD) or amnestic mild cognitive impairment (MCI). The investigation of longer-term administration is necessary to determine whether benefits persist, whether they are similar to benefits provided by regular insulin, and whether either form of insulin therapy affects AD biomarkers. OBJECTIVE: The present study aimed to determine whether four months of treatment with intranasal insulin detemir or regular insulin improves cognition, daily functioning, and AD biomarkers for adults with MCI or AD. METHODS: This randomized, double-blind, placebo-controlled trial included an intent-to-treat sample consisting of 36 adults diagnosed with MCI or mild to moderate AD. Participants received placebo (n = 12), 40 IU of insulin detemir (n = 12), or 40 IU of regular insulin (n = 12) daily for four months, administered with a nasal delivery device. A cognitive battery was administered at baseline and after two and four months of treatment. MRI was administered for all participants and lumbar puncture for a subset (n = 20) at baseline and four months. The primary outcome was change from baseline to four months on a memory composite (sum of Z scores for delayed list and story recall). Secondary outcomes included: global cognition (Alzheimer's Disease Assessment Scale-Cognition), daily functioning (Dementia Severity Rating Scale), MRI volume changes in AD-related regions of interest, and cerebrospinal fluid AD markers. RESULTS: The regular insulin treated group had better memory after two and four months compared with placebo (p < 0.03). No significant effects were observed for the detemir-assigned group compared with the placebo group, or for daily functioning for either group. Regular insulin treatment was associated with preserved volume on MRI. Regular insulin treatment was also associated with reduction in the tau-P181/Aβ42 ratio. CONCLUSION: Future research is warranted to examine the mechanistic basis of treatment differences, and to further assess the efficacy and safety of intranasal insulin.

Efficacy and Safety of Donepezil in Chinese Patients with Severe Alzheimer's Disease: A Randomized Controlled Trial. - Jia, Jianping; Wei, Cuibai; Jia, Longfei; Tang, Yi; Liang, Junhua; Zhou, Aihong; Li, Fangyu; Shi, Lu; Doody, Rachelle S (J Alzheimers Dis, 2017)
BACKGROUND: Donepezil has been used worldwide for the treatment of severe Alzheimer's disease (AD). Whether it is also appropriate for severe AD in Chinese patients remains unknown. OBJECTIVE: To determine whether donepezil is effective and tolerable for Chinese patients with severe AD. METHODS: The present study was a 24-week, multicenter, double-blind, randomized, placebo-controlled, parallel-group study conducted at 38 investigational hospitals in China. Patients with severe AD were enrolled in this trial. Patients were randomly assigned in a 1:1 ratio to receive either donepezil or placebo (5 mg for 6 weeks and10 mg for the remaining 18 weeks). The efficacy for donepezil were evaluated by the SIB, the Clinician's Interview-Based Impression of Change-Plus caregiver input (CIBIC-plus) and the MMSE. Safety parameters were monitored throughout. RESULTS: A total of 313 patients included the donepezil (n = 157) and the placebo groups (n = 156). Donepezil group improved more in SIB scores (least squares [LS] mean difference: 4.8, 95% CI 1.56 to 8.08, p = 0.004) and CIBIC-plus scores (drug-placebo difference: -0.4, 95% CI -0.66 to 0.03, p = 0.04) than placebo groups at Week 24. The MMSE scores between drug and placebo groups did not differ significantly. Twenty-nine patients with serious adverse events (SAEs) were reported in donepezil (n = 11) and placebo groups (n = 18) (p = 0.08). Most SAEs were not considered drug-related. CONCLUSION: Donepezil for 24 weeks was more effective than placebo and showed good safety and tolerability in Chinese patients with severe AD. This study supports utility of the drug in severe stages of AD in the Chinese population.

Elevated Epstein-Barr Virus Antibody Level is Associated with Cognitive Decline in the Korean Elderly. - Shim, Sung-Mi; Cheon, Hyo-Soon; Jo, Chulman; Koh, Young Ho; Song, Jihyun; Jeon, Jae-Pil (J Alzheimers Dis, 2017)
Chronic viral infection is implicated in cognitive decline and Alzheimer's disease (AD). Our goal was to identify biomarkers for the development of amnestic mild cognitive impairment (aMCI) from cognitively normal state. To accomplish this, we analyzed plasma IgG levels against Epstein-Barr virus (EBV) and herpes simplex virus 1 (HSV-1) in study subjects with incident aMCI (Converter) and normal cognitive function (NC Control) who did or did not convert from cognitively normal state to aMCI during the 2-year follow-up period, respectively. The Converter group exhibited elevated levels of anti-EBV IgG antibodies in the post-follow-up phase (aMCI state) compared to the pre-follow-up phase (cognitively normal state), but not the NC Control group. In contrast, the total IgG level was not significantly changed over the follow-up period. Moreover, elevated anti-EBV IgG levels were significantly associated with CDR scales and total CERAD scores in the Converter group. These results suggest that EBV infection or its related host immune response is linked to cognitive decline. Thus, an EBV antibody level may be used as a potential biomarker for assessing the risk of aMCI development, implying a role for chronic EBV infection in AD pathogenesis.

Elevation of Peripheral BDNF Promoter Methylation Predicts Conversion from Amnestic Mild Cognitive Impairment to Alzheimer's Disease: A 5-Year Longitudinal Study. - Xie, Bing; Xu, Yao; Liu, Zanchao; Liu, Wenxuan; Jiang, Lei; Zhang, Rui; Cui, Dongsheng; Zhang, Qingfu; Xu, Shunjiang (J Alzheimers Dis, 2017)
Epigenetic aberrations have been identified as biomarkers to predict the risk of Alzheimer's disease (AD). This study aimed to evaluate whether altered DNA methylation status of BDNF promoter could be used as potential epigenetic biomarkers for predicting the progression from amnestic mild cognitive impairment (aMCI) to AD. A total of 506 aMCI patients and 728 cognitively normal controls were recruited in the cross-sectional analyses. Patients (n = 458) from aMCI cohort were classified into two groups after 5-year follow-up: aMCI-stable group (n = 330) and AD-conversion group (n = 128). DNA methylation of BDNF promoter was detected by bisulfite-PCR amplification and pyrosequencing. The DNA methylation levels of CpG1 and CpG2 in promoter I and CpG5 and CpG6 in promoter IV of BDNF gene were significantly higher in the aMCI group than in the control group at baseline and also were increased in the conversion group compared with the non-conversion group at 5-year follow up time point. CpG5 in BDNF promoter IV had the highest AUC of 0.910 (95% CI: 0.817-0.983, p < 0.05). Kaplan-Meier analysis showed a significant AD conversion propensity for aMCI patients with high methylation levels of CpG5 (HR = 1.96, 95% CI: 1.07-2.98, p < 0.001). Multivariate Cox regression analysis revealed elevated methylation status of CpG5 was a significant independent predictor for AD conversion (HR = 3.51, p = 0.013). These results suggest that elevation of peripheral BDNF promoter methylation might be used as potential epigenetic biomarkers for predicting the conversion from aMCI to AD.

Evaluation of the Reliability, Validity, and Predictive Validity of the Subscales of the Perceived Stress Scale in Older Adults. - Jiang, Julie M; Seng, Elizabeth K; Zimmerman, Molly E; Sliwinski, Martin; Kim, Mimi; Lipton, Richard B (J Alzheimers Dis, 2017)
BACKGROUND: The Perceived Stress Scale (PSS) is made up of two subscales but is typically used as a single summary measure. However, research has shown that the two subscales may have differential properties in older adults. OBJECTIVE: To evaluate the internal consistency, test-retest reliability, and the concurrent and predictive validity for development of amnestic mild cognitive impairment (aMCI) of the positively-worded (PSS-PW) and negatively-worded (PSS-NW) subscale scores of the PSS in older adults. METHODS: We recruited community residing older adults free of dementia from the Einstein Aging Study. Reliability of the PSS-PW and PSS-NW was assessed using Cronbach's alpha for internal consistency and intraclass correlation for one year test-retest reliability. Concurrent validity was evaluated by examining the relationship between the PSS subscales and depression, anxiety, neuroticism, and positive and negative affect. Predictive validity was assessed using multivariate Cox regression analyses to examine the relationship between baseline PSS-PW and PSS-NW score and subsequent onset of aMCI. RESULTS: Both PSS-PW and PSS-NW showed adequate internal consistency and retest reliabilities. Both the PSS-PW and PSS-NW were associated with depression, neuroticism, and negative affect. The PSS-NW was uniquely associated with anxiety while the PSS-PW was uniquely associated with positive affect. Only the PSS-PW was associated with a statistically significant increased risk of incident aMCI (HR = 1.27; 95% CI: 1.06-1.51 for every 5-point increase in PSS-PW). CONCLUSIONS: Evaluating the separate effects of the two PSS subscales may reveal more information than simply using a single summation score. Future research should investigate the PSS-PW and PSS-NW as separate subscales.

Face-Name Associative Recognition Deficits in Subjective Cognitive Decline and Mild Cognitive Impairment. - Polcher, Alexandra; Frommann, Ingo; Koppara, Alexander; Wolfsgruber, Steffen; Jessen, Frank; Wagner, Michael (J Alzheimers Dis, 2017)
BACKGROUND: There is a need for more sensitive neuropsychological tests to detect subtle cognitive deficits emerging in the preclinical stage of Alzheimer's disease (AD). Associative memory is a cognitive function supported by the hippocampus and affected early in the process of AD. OBJECTIVE: We developed a short computerized face-name associative recognition test (FNART) and tested whether it would detect memory impairment in memory clinic patients with mild cognitive impairment (MCI) and subjective cognitive decline (SCD). METHODS: We recruited 61 elderly patients with either SCD (n = 32) or MCI (n = 29) and 28 healthy controls (HC) and compared performance on FNART, self-reported cognitive deterioration in different domains (ECog-39), and, in a reduced sample (n = 46), performance on the visual Paired Associates Learning of the CANTAB battery. RESULTS: A significant effect of group on FNART test performance in the total sample was found (p < 0.001). Planned contrasts indicated a significantly lower associative memory performance in the SCD (p = 0.001, d = 0.82) and MCI group (p < 0.001, d = 1.54), as compared to HCs, respectively. The CANTAB-PAL discriminated only between HC and MCI, possibly because of reduced statistical power. Adjusted for depression, performance on FNART was significantly related to ECog-39 Memory in SCD patients (p = 0.024) but not in MCI patients. CONCLUSIONS: Associative memory is substantially impaired in memory clinic patients with SCD and correlates specifically with memory complaints at this putative preclinical stage of AD. Further studies will need to examine the predictive validity of the FNART in SCD patients with regard to longitudinal (i.e., conversion to MCI/AD) and biomarker outcomes.

Frequency-Dependent Changes in the Amplitude of Low-Frequency Fluctuations in Mild Cognitive Impairment with Mild Depression. - Li, Yuxia; Jing, Bin; Liu, Han; Li, Yifan; Gao, Xuan; Li, Yongqiu; Mu, Bin; Yu, Haikuo; Cheng, Jinbo; Barker, Peter B; Wang, Hongxing; Han, Ying (J Alzheimers Dis, 2017)
BACKGROUND: Depression is a potential marker of preclinical Alzheimer's disease (AD). However, little is known about the abnormal characteristics revealed by resting-state functional magnetic resonance imaging (rs-fMRI) in mild cognitive impairment (MCI) subjects with depressive symptoms (MCI-d). OBJECTIVE: The study was to examine whether abnormalities in amplitudes of low-frequency oscillation occurred in MCI-d and tried to find the possible spectrum showed higher recognition ability to the diagnosis by utilizing functional MRI (fMRI). METHODS: The amplitude of low-frequency fluctuation (ALFF) and fractional ALFF (fALFF) within full frequency (0.01-0.1 Hz), slow-5 (0.01-0.027 Hz), and slow-4 (0.027-0.073 Hz) were computed using resting-state fMRI data of 27 MCI without depressive symptoms, 19 MCI-d, and 32 well-matched healthy controls (HC). Analysis of covariance was performed on ALFF and fALFF among MCI, MCI-d, and HC groups. RESULTS: Several brain regions showed significant differences in ALFF and fALFF within full frequency, slow-5, and slow-4 bands among three groups. Importantly, receiver operating characteristic analysis revealed that the ALFF values in the full frequency band in the left parahippocampal gyrus and the left precuneus, Slow 5 value in ALFF in the left inferior frontal gyrus, and Slow 4 value in ALFF in the left precuneus could effectively differentiate MCI-d from MCI patients. CONCLUSION: In this study, we found that several changes in special brain regions are associated with MCI and MCI-d patients. And the differences depend on the studied frequency bands of rs-fMRI data. The affective network and the default-mode network might be damaged simultaneously in MCI-d patients.

Functional Disintegration of the Default Mode Network in Prodromal Alzheimer's Disease. - Dillen, Kim N H; Jacobs, Heidi I L; Kukolja, Juraj; Richter, Nils; von Reutern, Boris; Onur, Özgür A; Langen, Karl-Josef; Fink, Gereon R (J Alzheimers Dis, 2017)
Neurodegenerative brain changes can affect the functional connectivity strength between nodes of the default-mode network (DMN), which may underlie changes in cognitive performance. It remains unclear how the functional connectivity strength of DMN nodes differs from healthy to pathological aging and whether these changes are cognitively relevant. We used resting-state functional magnetic resonance imaging to investigate the functional connectivity strength across five DMN nodes in 25 healthy controls (HC), 28 subjective cognitive decline (SCD) participants, and 25 prodromal Alzheimer's disease (AD) patients. After identifying the ventral medial prefrontal cortex (vmPFC), posterior cingulate cortex (PCC), retrosplenial cortex (RSC), inferior parietal lobule, and the hippocampus we investigated the functional strength between DMN nodes using temporal network modeling. Functional coupling of the vmPFC and PCC in prodromal AD patients was disrupted. This vmPFC-PCC coupling correlated positively with memory performance in prodromal AD. Furthermore, the hippocampus de-coupled from posterior DMN nodes in SCD and prodromal AD patients. There was no coupling between the hippocampus and the anterior DMN. Additional mediation analyses indicated that the RSC enables communication between the hippocampus and DMN regions in HC but none of the other two groups. These results suggest an anterior-posterior disconnection and a hippocampal de-coupling from posterior DMN nodes with disease progression. Hippocampal de-coupling already occurring in SCD may provide valuable information for the development of a functional biomarker.

Genetic Risk as a Marker of Amyloid-β and Tau Burden in Cerebrospinal Fluid. - Voyle, Nicola; Patel, Hamel; Folarin, Amos; Newhouse, Stephen; Johnston, Caroline; Visser, Pieter Jelle; Dobson, Richard J B; Kiddle, Steven J (J Alzheimers Dis, 2017)
BACKGROUND: The search for a biomarker of Alzheimer's disease (AD) pathology (amyloid-β (Aβ) and tau) is ongoing, with the best markers currently being measurements of Aβ and tau in cerebrospinal fluid (CSF) and via positron emission tomography (PET) scanning. These methods are relatively invasive, costly, and often have high screening failure rates. Consequently, research is aiming to elucidate blood biomarkers of Aβ and tau. OBJECTIVE: This study aims to investigate a case/control polygenic risk score (PGRS) as a marker of tau and investigate blood markers of a combined Aβ and tau outcome for the first time. A sub-study also considers plasma tau as markers of Aβ and tau pathology in CSF. METHODS: We used data from the EDAR*, DESCRIPA**, and Alzheimer's Disease Neuroimaging Initiative (ADNI) cohorts in a logistic regression analysis to investigate blood markers of Aβ and tau in CSF. In particular, we investigated the extent to which a case/control PGRS is predictive of CSF tau, CSF amyloid, and a combined amyloid and tau outcome. The predictive ability of models was compared to that of age, gender, and APOE genotype ('basic model'). RESULTS: In EDAR and DESCRIPA test data, inclusion of a case/control PGRS was no more predictive of Aβ, and a combined Aβ and tau endpoint than the basic models (accuracies of 66.0%, and 73.3% respectively). The tau model saw a small increase in accuracy compared to basic models (59.6%). ADNI 2 test data also showed a slight increase in accuracy for the Aβ model when compared to the basic models (61.4%). CONCLUSION: We see some evidence that a case/control PGRS is marginally more predictive of Aβ and tau pathology than the basic models. The search for predictive factors of Aβ and tau pathologies, above and beyond demographic information, is still ongoing. Better understanding of AD risk alleles, development of more sensitive assays, and studies of larger sample size are three avenues that may provide such factors. However, the clinical utility of possible predictors of brain Aβ and tau pathologies must also be investigated.*'Beta amyloid oligomers in the early diagnosis of AD and as marker for treatment response'**'Development of screening guidelines and criteria for pre-dementia Alzheimer's disease'.

The Gut Microbiota and Alzheimer's Disease. - Jiang, Chunmei; Li, Guangning; Huang, Pengru; Liu, Zhou; Zhao, Bin (J Alzheimers Dis, 2017)
The gut microbiota comprises a complex community of microorganism species that resides in our gastrointestinal ecosystem and whose alterations influence not only various gut disorders but also central nervous system disorders such as Alzheimer's disease (AD). AD, the most common form of dementia, is a neurodegenerative disorder associated with impaired cognition and cerebral accumulation of amyloid-β peptides (Aβ). Most notably, the microbiota-gut-brain axis is a bidirectional communication system that is not fully understood, but includes neural, immune, endocrine, and metabolic pathways. Studies in germ-free animals and in animals exposed to pathogenic microbial infections, antibiotics, probiotics, or fecal microbiota transplantation suggest a role for the gut microbiota in host cognition or AD-related pathogenesis. The increased permeability of the gut and blood-brain barrier induced by microbiota dysbiosis may mediate or affect AD pathogenesis and other neurodegenerative disorders, especially those associated with aging. In addition, bacteria populating the gut microbiota can secrete large amounts of amyloids and lipopolysaccharides, which might contribute to the modulation of signaling pathways and the production of proinflammatory cytokines associated with the pathogenesis of AD. Moreover, imbalances in the gut microbiota can induce inflammation that is associated with the pathogenesis of obesity, type 2 diabetes mellitus, and AD. The purpose of this review is to summarize and discuss the current findings that may elucidate the role of the gut microbiota in the development of AD. Understanding the underlying mechanisms may provide new insights into novel therapeutic strategies for AD.

Higher Peripheral TREM2 mRNA Levels Relate to Cognitive Deficits and Hippocampal Atrophy in Alzheimer's Disease and Amnestic Mild Cognitive Impairment. - Tan, Yi Jayne; Ng, Adeline S L; Vipin, Ashwati; Lim, Joseph K W; Chander, Russell J; Ji, Fang; Qiu, Yingwei; Ting, Simon K S; Hameed, Shahul; Lee, Tih-Shih; Zeng, Li; Kandiah, Nagaendran; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Variants in triggering receptor expressed on myeloid cells 2 (TREM2) are associated with increased Alzheimer's disease (AD) risk. Recent studies have reported inconsistent peripheral TREM2 mRNA expression levels and relationship with cognitive scores in AD and mild cognitive impairment (MCI). Additionally, no study has examined the association of peripheral TREM2 levels with neuroimaging measures in AD and MCI. OBJECTIVE: To determine peripheral TREM2 mRNA levels in AD, amnestic MCI (aMCI) and healthy controls, and the association with cognitive performance and brain structural changes. METHODS: We measured peripheral TREM2 mRNA levels in 80 AD, 30 aMCI, and 86 healthy controls using real time polymerase chain reaction. TREM2 levels were correlated with various cognitive performance and brain volumes, correcting for APOE4 status. RESULTS: TREM2 mRNA levels were significantly higher in AD compared to controls and aMCI. Levels did not differ between aMCI and controls. Corrected for APOE4, higher TREM2 levels correlated with lower Mini-Mental State Examination, Montreal Cognitive Assessment (MoCA) and episodic memory scores, and lower total grey matter and right hippocampal volumes. Whole-brain voxel-based morphometry analysis found negative association between TREM2 mRNA levels and grey matter volumes in temporal, parietal and frontal regions. AD subjects with MoCA scores ≤20 had higher TREM2 levels correlating with smaller total grey matter, left hippocampal and right hippocampal volumes. CONCLUSION: Peripheral TREM2 mRNA levels are higher in AD and are associated with AD-related cognitive deficits and hippocampal atrophy. Our findings suggest that TREM2 may be a potential non-invasive peripheral biomarker for AD diagnosis.

Histogram-Based Feature Extraction from Individual Gray Matter Similarity-Matrix for Alzheimer's Disease Classification. - Beheshti, Iman; Maikusa, Norihide; Matsuda, Hiroshi; Demirel, Hasan; Anbarjafari, Gholamreza (J Alzheimers Dis, 2017)
Automatic computer-aided diagnosis (CAD) systems have been widely used in classification of patients who suffer from Alzheimer's disease (AD). This paper presents an automatic CAD system based on histogram feature extraction from single-subject gray matter similarity-matrix for classifying the AD patients from healthy controls (HC) using structural magnetic resonance imaging (MRI) data. The proposed CAD system is composed of five stages. In the first stage, segmentation is employed to perform pre-processing on the MRI images, and segment into gray matter, white matter, and cerebrospinal fluid using the voxel-based morphometric toolbox procedure. In the second stage, gray matter MRI scans are used to construct similarity-matrices. In the third stage, a novel statistical feature-generation process is proposed, utilizing the histogram of the individual similarity-matrix to represent statistical patterns of the respective similarity-matrices of different size and order into fixed-size feature-vectors. In the fourth stage, we propose to combine MRI measures with a neuropsychological test, the Functional Assessment Questionnaire (FAQ), to improve the classification accuracy. Finally, the classification is performed using a support vector machine and evaluated with the 10-fold cross-validation strategy. We evaluated the proposed method on 99 AD and 102 HC subjects from the J-ADNI. The proposed CAD system yields an 84.07% classification accuracy using MRI measures and 97.01% for combining MRI measures with FAQ scores, respectively. The experimental results indicate that the performance of the proposed system is competitive with respect to state-of-the-art techniques reported in the literature.

Histopathology and Florbetaben PET in Patients Incorrectly Diagnosed with Alzheimer's Disease. - Sabbagh, Marwan N; Schäuble, Barbara; Anand, Keshav; Richards, Danielle; Murayama, Shigeo; Akatsu, Hiroyasu; Takao, Masaki; Rowe, Christopher C; Masters, Colin L; Barthel, Henryk; Gertz, Hermann-Josef; Peters, Oliver; et al. (J Alzheimers Dis, 2017)
Of 57 individuals diagnosed with Alzheimer's disease (AD) in a phase III study, 13 (23%) had amyloid-β (Aβ) levels on postmortem histopathology that did not explain the dementia. Based on postmortem histopathology, a wide range of different non-AD conditions was identified, including frontotemporal dementia, hippocampal sclerosis, and dementia with Lewy bodies. Of the histopathologically Aβ negative scored cases ante-mortem Florbetaben PET scans were classified as negative for Aβ in 11 patients based on visual analysis and in all 12 quantifiable cases based on composite standardized uptake value ratios. Thus, florbetaben PET can assist physicians in the differential diagnosis of neurodegenerative disorders by reliably excluding Aβ pathology.

How Different are Quality of Life Ratings for People with Dementia Reported by Their Family Caregivers from Those Reported by the Patients Themselves? - Jacob, Louis; Han, Ji Won; Kim, Tae Hui; Park, Joon Hyuk; Lee, Seok Bum; Lee, Jung Jae; Ryu, Seung-Ho; Kim, Shin-Kyeom; Yoon, Jong Chul; Jhoo, Jin Hyeong; Kim, Jeong Lan; Kwak, Kyung Phil; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Measurements of patient quality of life (QoL) play a major role in the management of dementia. OBJECTIVE: We investigated the self-proxy discrepancy of QoL ratings in the elderly and the impact of dementia severity on the discrepancy. METHODS: QoL of 718 patients with dementia and 651 non-demented elderly were rated by themselves and their caregivers (CG) using the Quality of Life-Alzheimer's Disease (QoL-AD). The impact of the rater on the total and item scores of QoL-AD was analyzed using repeated measures ANOVA and differential response patterns between self and proxy were analyzed using differential item functioning (DIF) analysis. RESULTS: Self-rated scores were higher than CG-rated scores in all diagnostic groups. The interaction between rater and diagnostic group was significant in total QoL-AD score and 5 item scores ('memory', 'marriage', 'chores around the house', 'do things for fun', and 'life as a whole'). The strength of the DIF increased with advancing dementia in these items. CONCLUSION: Self-proxy rating discrepancy of QoL was influenced by the presence and severity of dementia only in five items.

Impaired Center-Surround Suppression in Patients with Alzheimer's Disease. - Zhuang, Xianbo; Chen, Yanxiu; Zhuang, Xianpeng; Xing, Tao; Chen, Tuanzhi; Jiang, Guisheng; Yang, Xiafeng (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is often associated with declined visual processing abilities. Here we tested whether the functions of center-surround suppression- a hallmark property in the visual system- are altered by AD. To this end, we recruited three groups of participants (AD, elderly, and young) in a motion direction discrimination task, in which we measured the temporal duration threshold of a  drifting Gabor with varying stimulus sizes. We first replicated the phenomena of center-surround suppression that the required duration for discriminating a high contrast grating decreases with increasing stimulus size. We then showed that the magnitudes of suppression varied among the three groups. There was progressive reduction of suppression in the elderly and AD groups compared with the young group. Interestingly, we found that the levels of suppression can predict the severity of dementia in the AD group. Our results suggest that AD is associated with impaired center-surround functions in the visual motion processing pathway.

In vivo Patterns of Tau Pathology, Amyloid-β Burden, and Neuronal Dysfunction in Clinical Variants of Alzheimer's Disease. - Dronse, Julian; Fliessbach, Klaus; Bischof, Gérard N; von Reutern, Boris; Faber, Jennifer; Hammes, Jochen; Kuhnert, Georg; Neumaier, Bernd; Onur, Oezguer A; Kukolja, Juraj; van Eimeren, Thilo; Jessen, Frank; et al. (J Alzheimers Dis, 2017)
The clinical heterogeneity of Alzheimer's disease is not reflected in the rather diffuse cortical deposition of amyloid-β. We assessed the relationship between clinical symptoms, in vivo tau pathology, amyloid distribution, and hypometabolism in variants of Alzheimer's disease using novel multimodal PET imaging techniques. Tau pathology was primarily observed in brain regions related to clinical symptoms and overlapped with areas of hypometabolism. In contrast, amyloid-β deposition was diffusely distributed over the entire cortex. Tau PET imaging may thus serve as a valuable biomarker for the localization of neuronal injury in vivo and may help to validate atypical subtypes of Alzheimer's disease.

Increased Serum miR-206 Level Predicts Conversion from Amnestic Mild Cognitive Impairment to Alzheimer's Disease: A 5-Year Follow-up Study. - Xie, Bing; Liu, Zanchao; Jiang, Lei; Liu, Wei; Song, Mei; Zhang, Qingfu; Zhang, Rui; Cui, Dongsheng; Wang, Xueyi; Xu, Shunjiang (J Alzheimers Dis, 2017)
Evidence suggests that individuals with amnestic mild cognitive impairment (aMCI) tend to progress to probable Alzheimer's disease (AD) with aging. This study was performed to examine whether circulating miRNAs could be potential predictors for the progression of aMCI to AD. A total of 458 patients with aMCI were included in this study, and the clinical data were collected at two time points: the baseline and the follow-up assessment. These aMCI patients were classified into two groups after 5 years: aMCI-stable group (n = 330) and AD-conversion group (n = 128). The expression of miR-206 and miR-132 and the levels of BDNF and SIRT1 in serum were detected using a quantitative real-time RT-PCR (qPCR) and the ELISA method, respectively. Kaplan-Meier method (Log-rank test) was used for univariate survival analysis. Cox proportional hazard model was used to estimate the prognostic value of miRNAs in conversion from aMCI to AD. At the baseline, serum levels of miR-206 in aMCI-AD group were significantly elevated compared to aMCI-aMCI group and the same trend was found at 5-year follow-up time point as well. There were no significant differences in serum levels of miR-132 between the conversion and non-conversion group at both time points. Kaplan-Meier analysis showed significant correlation between AD conversion and higher serum levels of miR-206 for aMCI patients (HR = 3.60, 95% CI: 2.51- 5.36, p < 0.001). Multivariate Cox regression analysis revealed that serum miR-206 and its target BDNF were significant independent predictors for AD conversion (HR = 4.22, p < 0.001). These results suggested that increased serum miR-206 level might be a potential predictor of conversion from aMCI to AD.

Initial Heart Rate Reactivity to Socioemotional Pictures in Early-Onset Alzheimer's Disease. - Joshi, Aditi; Jimenez, Elvira; Mendez, Mario F (J Alzheimers Dis, 2017)
Patients with Alzheimer's disease (AD) often have generalized anxiety, particularly in early-onset AD (EOAD) or the first stages of their disease. This increased anxiety could be associated with decreased sensorimotor gating with increased attention to significant stimuli from AD pathology in the entorhinal cortex. We investigated whether widening initial attention to socioemotional stimuli was association with anxiety among 16 patients with first stage EOAD compared to 19 normal controls (NCs). The participants underwent assessment of their initial heart rate deceleration ("orienting response"; OR), a measure of attentional refocusing, to pictures (International Affective Picture Stimuli) varying in pleasant-unpleasant valence and social-nonsocial content. The results showed group differences; the EOAD patients had significantly larger ORs than the NCs across conditions, with larger ORs in each valence and social condition. In addition, the EOAD patients, but not the NCs, showed ORs to normally less threatening stimuli, particularly pleasant, but also less significantly, social stimuli. On the Neuropsychiatric Inventory, the ORs among the EOAD patients significantly correlated with anxiety scores. Together, these findings suggest that anxiety in mild EOAD may be associated with widening attentional refocusing to socioemotional stimuli, possibly reflecting decreased sensorimotor gating in the entorhinal cortex. This finding could be a potential biomarker for the first stages of AD.

Insula and Inferior Frontal Gyrus' Activities Protect Memory Performance Against Alzheimer's Disease Pathology in Old Age. - Lin, Feng; Ren, Ping; Lo, Raymond Y; Chapman, Benjamin P; Jacobs, Alanna; Baran, Timothy M; Porsteinsson, Anton P; Foxe, John J (J Alzheimers Dis, 2017)
Apolipoprotein E (APOE) ɛ4 carriers and patients with amnestic mild cognitive impairment (MCI) have high risk of developing Alzheimer's disease (AD). The Scaffolding Theory of Aging and Cognition proposes that recruitment of additional frontal brain regions can protect cognition against aging. This thesis has yet to be fully tested in older adults at high risk for AD. In the present study, 75 older participants (mean age: 74 years) were included. Applying a voxel-wise approach, fractional amplitude of low-frequency fluctuations (fALFF) in resting-state functional neuroimaging data were analyzed as a function of APOEɛ4 status (carrier versus noncarrier) and clinical status (healthy control [HC] versus MCI) using a 2×2 analysis of covariance (ANCOVA). Measures of cognition and cerebrospinal fluid levels of amyloid- β were also obtained. Three frontal regions were identified with significant interaction effects using ANCOVA (corrected p < 0.01): left-insula, left-inferior frontal gyrus (IFG), and right-precentral gyrus. The HC/APOEɛ4 carrier group had significantly higher fALFF in all three regions than other groups. In the entire sample, for two regions (left insula and left IFG), a significant positive relationship between amyloid-β and memory was only observed among individuals with low fALFF. Our results suggest higher activity in frontal regions may explain being cognitively normal among a subgroup of APOEɛ4 carriers and protect against the negative impact of AD-associated pathology on memory. This is an observation with potential implications for AD therapeutics.

Intracranial Arterial 4D Flow in Individuals with Mild Cognitive Impairment is Associated with Cognitive Performance and Amyloid Positivity. - Berman, Sara E; Clark, Lindsay R; Rivera-Rivera, Leonardo A; Norton, Derek; Racine, Annie M; Rowley, Howard A; Bendlin, Barbara B; Blennow, Kaj; Zetterberg, Henrik; Carlsson, Cynthia M; Asthana, Sanjay; Turski, Patrick; et al. (J Alzheimers Dis, 2017)
It is becoming increasingly recognized that cerebrovascular disease is a contributing factor in the pathogenesis of Alzheimer's disease (AD). A unique 4D-Flow magnetic resonance imaging (MRI) technique, phase contrast vastly undersampled isotropic projection imaging (PC VIPR), enables examination of angiographic and quantitative metrics of blood flow in the arteries of the Circle of Willis within a single MRI acquisition. Thirty-eight participants with mild cognitive impairment (MCI) underwent a comprehensive neuroimaging protocol (including 4D-Flow imaging) and a standard neuropsychological battery. A subset of participants (n = 22) also underwent lumbar puncture and had cerebrospinal fluid (CSF) assayed for AD biomarkers. Cut-offs for biomarker positivity in CSF resulting from a receiver operating characteristic curve analysis of AD cases and controls from the larger Wisconsin Alzheimer's Disease Research Center cohort were used to classify MCI participants as biomarker positive or negative on amyloid-β (Aβ42), total-tau and total-tau/Aβ42 ratio. Internal carotid artery (ICA) and middle cerebral artery (MCA) mean flow were associated with executive functioning performance, with lower mean flow corresponding to worse performance. MCI participants who were biomarker positive for Aβ42 had lower ICA mean flow than did those who were Aβ42 negative. In sum, mean ICA and MCA arterial flow was associated with cognitive performance in participants with MCI and lower flow in the ICA was associated with amyloid positivity. This provides further evidence for vascular health as a contributing factor in the etiopathogenesis of AD, and could represent a point to intervene in the disease process.

Investigation on the Role of BDNF in the Benefits of Blueberry Extracts for the Improvement of Learning and Memory in Alzheimer's Disease Mouse Model. - Tan, Long; Yang, Hongpeng; Pang, Wei; Li, Haiqiang; Liu, Wei; Sun, Shoudan; Song, Nan; Zhang, Wanqi; Jiang, Yugang (J Alzheimers Dis, 2017)
BACKGROUND: Blueberry (BB) can provide a wide range of antioxidant benefits for AD. There is evidence that BB extracts could improve brain functions. However, the details are still unknown. OBJECTIVE: In the present study, we aimed to investigate the possible mechanism involved in the improvement of learning and memory capacity from BB extracts in AD. METHODS: APP/PS1 transgenic mice were fed BB extracts for 16 weeks. The capacity of learning and memory was assessed by Morris water maze (MWM) test, and long-term potentiation (LTP) was determined to evaluate hippocampal neuronal plasticity at the end of administration. Pathological changes in the brain were observed, and the expressions of brain-derived neurotrophic factor (BDNF) and extracellular signal-related kinase (ERK1/2) were determined to explore the mechanism of BB extract-induced benefits. RESULTS: AD mice exhibited more difficulties to learn and remember the exact position of the platform in the MWM test. The data showed that AD mice lacked effective learning in the platform search. In contrast, AD mice exhibited better performance both in the training phase and probe test of MWM after the BB treatment. Moreover, LTP was enhanced and the neuron loss was alleviated with BB treatment, while we did not find any obvious effect on the elimination of amyloid-β. In the AD mice, the expression of ERK1/2 was significantly increased (p < 0.05), while the level of BDNF was decreased (p < 0.05). CONCLUSIONS: BB treatment was beneficial for the improvement of learning and memory of AD, and these effects might be related to the regulation of BDNF.

Iron Concentration in Deep Gray Matter Structures is Associated with Worse Visual Memory Performance in Healthy Young Adults. - Darnai, Gergely; Nagy, Szilvia Anett; Horváth, Réka; Ács, Péter; Perlaki, Gábor; Orsi, Gergely; Kovács, Norbert; Altbäcker, Anna; Plózer, Enikő; Tényi, Dalma; Weintraut, Rita; Schwarcz, Attila; et al. (J Alzheimers Dis, 2017)
Abnormally high deposition of iron can contribute to neurodegenerative disorders with cognitive impairment. Since previous studies investigating cognition-brain iron accumulation relationships focused on elderly people, our aim was to explore the association between iron concentration in subcortical nuclei and two types of memory performances in a healthy young population. Gender difference was found only in the globus pallidus. Our results showed that iron load characterized by R2* value on the MRI in the caudate and putamen was related to visual memory, while verbal memory was unrelated to iron concentration.

Left Frontal Hub Connectivity during Memory Performance Supports Reserve in Aging and Mild Cognitive Impairment. - Franzmeier, Nicolai; Hartmann, Julia C; Taylor, Alexander N W; Araque Caballero, Miguel Á; Simon-Vermot, Lee; Buerger, Katharina; Kambeitz-Ilankovic, Lana M; Ertl-Wagner, Birgit; Mueller, Claudia; Catak, Cihan; Janowitz, Daniel; Stahl, Robert; et al. (J Alzheimers Dis, 2017)
Reserve in aging and Alzheimer's disease (AD) is defined as maintaining cognition at a relatively high level in the presence of neurodegeneration, an ability often associated with higher education among other life factors. Recent evidence suggests that higher resting-state functional connectivity within the frontoparietal control network, specifically the left frontal cortex (LFC) hub, contributes to higher reserve. Following up these previous resting-state fMRI findings, we probed memory-task related functional connectivity of the LFC hub as a neural substrate of reserve. In elderly controls (CN, n = 37) and patients with mild cognitive impairment (MCI, n = 17), we assessed global connectivity of the LFC hub during successful face-name association learning, using generalized psychophysiological interaction analyses. Reserve was quantified as residualized memory performance, accounted for gender and proxies of neurodegeneration (age, hippocampus atrophy, and APOE genotype). We found that greater education was associated with higher LFC-connectivity in both CN and MCI during successful memory. Furthermore, higher LFC-connectivity predicted higher residualized memory (i.e., reserve). These results suggest that higher LFC-connectivity contributes to reserve in both healthy and pathological aging.

Left Ventricular Hypertrophy and Cognitive Decline in Old Age. - Mahinrad, Simin; Vriend, Annelotte E; Jukema, J Wouter; van Heemst, Diana; Sattar, Naveed; Blauw, Gerard Jan; Macfarlane, Peter W; Clark, Elaine N; de Craen, Anton J M; Sabayan, Behnam (J Alzheimers Dis, 2017)
BACKGROUND: Patients with advanced heart failure run a greater risk of dementia. Whether early cardiac structural changes also associate with cognitive decline is yet to be determined. OBJECTIVE: We tested whether left ventricular hypertrophy (LVH) derived from electrocardiogram associates with cognitive decline in older subjects at risk of cardiovascular disease. METHODS: We included 4,233 participants (mean age 75.2 years, 47.8% male) from PROSPER (PROspective Study of Pravastatin in the Elderly at Risk). LVH was assessed from baseline electrocardiograms by measuring the Sokolow-Lyon index. Higher levels of Sokolow-Lyon index indicate higher degrees of LVH. Cognitive domains involving selective attention, processing speed, and immediate and delayed memory were measured at baseline and repeated during a mean follow-up of 3.2 years. RESULTS: At baseline, LVH was not associated with worse cognitive function. During follow-up, participants with higher levels of LVH had a steeper decline in cognitive function including in selective attention (p = 0.009), processing speed (p = 0.010), immediate memory (p < 0.001), and delayed memory (p = 0.002). These associations were independent of cardiovascular risk factors, co-morbidities, and medications. CONCLUSION: LVH assessed by electrocardiogram associates with steeper decline in cognitive function of older subjects independent of cardiovascular risk factors and co-morbidities. This study provides further evidence on the link between subclinical cardiac structural changes and cognitive decline in older subjects.

Living Alone with Alzheimer's Disease: Data from SveDem, the Swedish Dementia Registry. - Cermakova, Pavla; Nelson, Maja; Secnik, Juraj; Garcia-Ptacek, Sara; Johnell, Kristina; Fastbom, Johan; Kilander, Lena; Winblad, Bengt; Eriksdotter, Maria; Religa, Dorota (J Alzheimers Dis, 2017)
BACKGROUND: Many people with Alzheimer's disease (AD) live alone in their own homes. There is a lack of knowledge about whether these individuals receive the same quality of diagnostics and treatment for AD as patients who are cohabiting. OBJECTIVES: To investigate the diagnostic work-up and treatment of community-dwelling AD patients who live alone. METHODS: We performed a cross-sectional cohort study based on data from the Swedish Dementia Registry (SveDem). We studied patients diagnosed with AD between 2007 and 2015 (n = 26,163). Information about drugs and comorbidities was acquired from the Swedish Prescribed Drug Register and the Swedish Patient Register. RESULTS: 11,878 (46%) patients lived alone, primarily older women. After adjusting for confounders, living alone was inversely associated with receiving computed tomography (OR 0.90; 95% CI 0.82-0.99), magnetic resonance imaging (OR 0.91; 95% CI 0.83-0.99), and lumbar puncture (OR 0.86; 95% CI 0.80-0.92). Living alone was also negatively associated with the use of cholinesterase inhibitors (OR 0.81; 95% CI 0.76; 0.87), memantine (OR 0.77; 95% CI 0.72; 0.83), and cardiovascular medication (OR 0.92; 0.86; 0.99). On the other hand, living alone was positively associated with the use of antidepressants (OR 1.15; 95% CI 1.08; 1.22), antipsychotics (OR 1.41; 95% CI 1.25; 1.58), and hypnotics and sedatives (OR 1.09; 95% CI 1.02; 1.17). CONCLUSIONS: Solitary living AD patients do not receive the same extent of care as those who are cohabiting.

A Longitudinal Study on Resting State Functional Connectivity in Behavioral Variant Frontotemporal Dementia and Alzheimer's Disease. - Hafkemeijer, Anne; Möller, Christiane; Dopper, Elise G P; Jiskoot, Lize C; van den Berg-Huysmans, Annette A; van Swieten, John C; van der Flier, Wiesje M; Vrenken, Hugo; Pijnenburg, Yolande A L; Barkhof, Frederik; Scheltens, Philip; van der Grond, Jeroen; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: Alzheimer's disease (AD) and behavioral variant frontotemporal dementia (bvFTD) are the most common types of early-onset dementia. We applied longitudinal resting state functional magnetic resonance imaging (fMRI) to delineate functional brain connections relevant for disease progression and diagnostic accuracy. METHODS: We used two-center resting state fMRI data of 20 AD patients (65.1±8.0 years), 12 bvFTD patients (64.7±5.4 years), and 22 control subjects (63.8±5.0 years) at baseline and 1.8-year follow-up. We used whole-network and voxel-based network-to-region analyses to study group differences in functional connectivity at baseline and follow-up, and longitudinal changes in connectivity within and between groups. RESULTS: At baseline, connectivity between paracingulate gyrus and executive control network, between cuneal cortex and medial visual network, and between paracingulate gyrus and salience network was higher in AD compared with controls. These differences were also present after 1.8 years. At follow-up, connectivity between angular gyrus and right frontoparietal network, and between paracingulate gyrus and default mode network was lower in bvFTD compared with controls, and lower compared with AD between anterior cingulate gyrus and executive control network, and between lateral occipital cortex and medial visual network. Over time, connectivity decreased in AD between precuneus and right frontoparietal network and in bvFTD between inferior frontal gyrus and left frontoparietal network. Longitudinal changes in connectivity between supramarginal gyrus and right frontoparietal network differ between both patient groups and controls. CONCLUSION: We found disease-specific brain regions with longitudinal connectivity changes. This suggests the potential of longitudinal resting state fMRI to delineate regions relevant for disease progression and for diagnostic accuracy, although no group differences in longitudinal changes in the direct comparison of AD and bvFTD were found.

Low Arousal Positive Emotional Stimuli Attenuate Aberrant Working Memory Processing in Persons with Mild Cognitive Impairment. - Broster, Lucas S; Jenkins, Shonna L; Holmes, Sarah D; Jicha, Gregory A; Jiang, Yang (J Alzheimers Dis, 2017)
Emotional enhancement effects on memory have been reported to mitigate the pathophysiology of Alzheimer's disease (AD). However, relative to their manifestation in persons without pathologic aging, these effects may be reduced in magnitude or even deleterious, especially in tasks that more closely model ecologic memory performance. Based upon a synthesis of such reports, we hypothesized that in persons with AD low arousal positive stimuli would evoke relatively intact emotional enhancement effects, but that high arousal negative stimuli would evoke disordered emotional enhancement effects. To assess this, participants with and without mild cognitive impairment (MCI) presumed to be due to AD performed an emotionally-valenced short-term memory task while encephalography was recorded. Results indicated that for persons with MCI, high arousal negative stimuli led to working memory processing patterns previously associated with MCI presumed due to AD and dementia of the Alzheimer-type. In contrast, low arousal positive stimuli evoked a processing pattern similar to MCI participants' unaffected spouses. Our current findings suggest that low arousal positive stimuli attenuate working memory deficits of MCI due to AD.

Memory Correlates of Alzheimer's Disease Cerebrospinal Fluid Markers: A Longitudinal Cohort Study. - Reijs, Babette L R; Ramakers, Inez H G B; Köhler, Sebastian; Teunissen, Charlotte E; Koel-Simmelink, Marleen; Nathan, Pradeep J; Tsolaki, Magda; Wahlund, Lars-Olof; Waldemar, Gunhild; Hausner, Lucrezia; Vandenberghe, Rik; Johannsen, Peter; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Performance on episodic, semantic, and working memory tests is impaired in Alzheimer's disease (AD)-type dementia, but it is unclear which type of memory test is most strongly associated with early AD biomarkers in cerebrospinal fluid (CSF), and most useful for monitoring disease progression. OBJECTIVE: To examine the association between amyloid-β 1-42 (Aβ42) and tau in CSF with performance on different memory domains at baseline, and how these CSF markers are related with memory decline. METHODS: We included 263 individuals with normal cognition, mild cognitive impairment, AD-type dementia, and non-AD dementia from the European EDAR study. Assessment included CSF Aβ42 and t-tau analyses with INNO-BIA AlzBio3 Luminex assay, the CERAD wordlist learning and delayed recall, animal fluency test, and the CANTAB Paired Associates Learning (PAL) and Spatial Working Memory tasks. Follow-up assessments were performed within 3 years after baseline. RESULTS: At baseline, decreased CSF Aβ42 correlated most strongly with the PAL total errors adjusted and the wordlist delayed recall and increased CSF t-tau with the wordlist delayed recall. Over time, decreased CSF Aβ42 was associated with decline on the wordlist learning, whereas increased CSF t-tau were associated with decline in scores on the wordlist learning, wordlist delayed recall, and animal fluency. Associations were independent of baseline diagnosis. CONCLUSION: Tests assessing episodic verbal and visuospatial memory are most useful for detection of AD pathology. Tests for episodic verbal memory and semantic memory are most useful for tracking memory decline.

A Metal-Free Method for Producing MRI Contrast at Amyloid-β. - Hilt, Silvia; Tang, Tang; Walton, Jeffrey H; Budamagunta, Madhu; Maezawa, Izumi; Kálai, Tamás; Hideg, Kálmán; Singh, Vikrant; Wulff, Heike; Gong, Qizhi; Jin, Lee-Way; Louie, Angelique; et al. (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is characterized by depositions of the amyloid-β (Aβ) peptide in the brain. The disease process develops over decades, with substantial neurological loss occurring before a clinical diagnosis of dementia can be rendered. It is therefore imperative to develop methods that permit early detection and monitoring of disease progression. In addition, the multifactorial pathogenesis of AD has identified several potential avenues for AD intervention. Thus, evaluation of therapeutic candidates over lengthy trial periods also demands a practical, noninvasive method for measuring Aβ in the brain. Magnetic resonance imaging (MRI) is the obvious choice for such measurements, but contrast enhancement for Aβ has only been achieved using Gd(III)-based agents. There is great interest in gadolinium-free methods to image the brain. In this study, we provide the first demonstration that a nitroxide-based small-molecule produces MRI contrast in brain specimens with elevated levels of Aβ. The molecule is comprised of a  fluorene (a molecule with high affinity for Aβ) and a nitroxide spin label (a paramagnetic MRI contrast species). Labeling of brain specimens with the spin-labeled fluorene produces negative contrast in samples from AD model mice whereas no negative contrast is seen in specimens harvested from wild-type mice. Injection of spin-labeled fluorene into live mice resulted in good brain penetration, with the compound able to generate contrast 24-h post injection. These results provide a proof of concept method that can be used for early, noninvasive, gadolinium-free detection of amyloid plaques by MRI.

A Mitochondrial Biomarker-Based Study of S-Equol in Alzheimer's Disease Subjects: Results of a Single-Arm, Pilot Trial. - Wilkins, Heather M; Mahnken, Jonathan D; Welch, Paul; Bothwell, Rebecca; Koppel, Scott; Jackson, Richard L; Burns, Jeffrey M; Swerdlow, Russell H (J Alzheimers Dis, 2017)
Reductions in bioenergetic fluxes, mitochondrial enzyme activities, and mitochondrial number are observed in Alzheimer's disease (AD). Preclinical work indicates estrogen pathway signaling by either estrogen or selective β estrogen receptor (ERβ) agonists benefits these parameters. To assess whether an ERβ agonist could improve mitochondrial function in actual AD subjects, we administered S-equol (10 mg twice daily) to 15 women with AD and determined the platelet mitochondria cytochrome oxidase (COX) activity before initiating S-equol (lead-in), after two weeks of S-equol (active treatment), and two weeks after stopping S-equol (wash-out). Because the intra-individual variation of this enzyme across samples taken at different times was unknown we used a nonparametric, single-arm, dichotomous endpoint that classified subjects whose active treatment COX activity exceeded the average of their lead-in and wash-out measures as positive responders. Eleven positive responses were observed (p < 0.06). The implications of this finding on our null hypothesis (that S-equol does not influence platelet mitochondria COX activity) are discussed. To our knowledge, this is the first time a direct mitochondrial target engagement biomarker has been utilized in an AD clinical study.

Moderate Physical Activity is Associated with Cerebral Glucose Metabolism in Adults at Risk for Alzheimer's Disease. - Dougherty, Ryan J; Schultz, Stephanie A; Kirby, Taylor K; Boots, Elizabeth A; Oh, Jennifer M; Edwards, Dorothy; Gallagher, Catherine L; Carlsson, Cynthia M; Bendlin, Barbara B; Asthana, Sanjay; Sager, Mark A; Hermann, Bruce P; et al. (J Alzheimers Dis, 2017)
The objective of this study was to investigate the relationship between accelerometer-measured physical activity (PA) and glucose metabolism in asymptomatic late-middle-aged adults. Ninety-three cognitively healthy late-middle-aged adults from the Wisconsin Registry for Alzheimer's Prevention participated in this cross-sectional study. They underwent 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) imaging and wore an accelerometer (ActiGraph GT3X+) to measure free-living PA. Accelerometer data yielded measures of light (LPA), moderate (MPA), and vigorous (VPA) intensity PA. FDG-PET images were scaled to the cerebellum and pons, and cerebral glucose metabolic rate was extracted from specific regions of interest (ROIs) known to be hypometabolic in AD, i.e., hippocampus, posterior cingulate, inferior temporal cortex, and angular gyrus. Regression analyses were utilized to examine the association between PA and glucose metabolism, while adjusting for potential confounds. There were associations between MPA and glucose metabolism in all ROIs examined. In contrast, LPA was not associated with glucose uptake in any ROI and VPA was only associated with hippocampal FDG uptake. Secondary analyses did not reveal associations between sedentary time and glucose metabolism in any of the ROIs. Exploratory voxel-wise analysis identified additional regions where MPA was significantly associated with glucose metabolism including the precuneus, supramarginal gyrus, amygdala, and middle frontal gyrus. These findings suggest that the intensity of PA is an important contributor to neuronal function in a late-middle-aged cohort, with MPA being the most salient. Prospective studies are necessary for fully elucidating the link between midlife engagement in PA and later life development of AD.

The Modified Frontal Behavioral Inventory (FBI-mod) for Patients with Frontotemporal Lobar Degeneration, Alzheimer's Disease, and Mild Cognitive Impairment. - Suhonen, Noora-Maria; Hallikainen, Ilona; Hänninen, Tuomo; Jokelainen, Jari; Krüger, Johanna; Hall, Anette; Pikkarainen, Maria; Soininen, Hilkka; Remes, Anne M (J Alzheimers Dis, 2017)
While behavioral symptoms are both early and prevalent features of behavioral variant frontotemporal dementia (bvFTD), they can be present in other types of dementia as well, including Alzheimer's disease (AD) and even mild cognitive impairment (MCI). The Frontal Behavioral Inventory (FBI) was specifically developed to capture the behavioral and personality changes in bvFTD; it has also been modified into a self-administered caregiver questionnaire (FBI-mod). We examined the utility of the FBI-mod in differentiating bvFTD (n = 26), primary progressive aphasia (PPA) (n = 7), AD (n = 53), and MCI (n = 50) patients, and investigated how the FBI-mod may be associated with neuropsychological measures. The bvFTD patients scored significantly higher as compared to all other patient groups on the FBI-mod Total (p < 0.005), Negative (p < 0.005), and Positive (p < 0.01) scores. The cut-off point for the FBI-mod Total score that best discriminated the bvFTD and AD patients in our sample was 16, thus substantially lower than reported for the original FBI. For the bvFTD group, only mild correlations emerged between the FBI-mod and the cognitive measures. However, significant correlations between the FBI-mod and depressive symptoms as measured by the BDI-II were found for bvFTD. This suggests that while behavioral symptoms appear independent from cognitive deficits in bvFTD, they may nevertheless be interrelated with depressive symptoms. We conclude that the FBI-mod is an easily administered behavioral scale that can aid in differential diagnosis of bvFTD and should be used in clinical practice. The FBI-mod may further be considered as an outcome measure in clinical trials.

Neuronal Expression of Truncated Tau Efficiently Promotes Neurodegeneration in Animal Models: Pitfalls of Toxic Oligomer Analysis. - Skrabana, Rostislav; Kovacech, Branislav; Filipcik, Peter; Zilka, Norbert; Jadhav, Santosh; Smolek, Tomas; Kontsekova, Eva; Novak, Michal (J Alzheimers Dis, 2017)
Animal models of neurodegeneration induced by neuronal expression of truncated tau protein emerge as an important tool for understanding the pathogenesis of human tauopathies and for therapy development. Here we highlight common features of truncated tau models and make a critical assessment of possible pitfalls in their analysis. Particularly, the amount of soluble tau oligomers, which are suspected to be neurotoxic agents participating on the spreading of pathology inside the brain, may be overestimated due to a post-lysis oxidative tau oligomerization. Using a mouse brain lysate spiked with recombinant truncated and full length tau forms, we show that tau oligomers might inadvertently be produced during the isolation procedure. This finding is further corroborated by the analysis of brain lysates originated from a mouse model expressing truncated tau variant. Our results underline the necessity of thiol-protecting conditions during the analysis of tau oligomers involved in the etiopathogenesis of various tauopathies including Alzheimer's disease.

Neuropsychological Profile in the C9ORF72 Associated Behavioral Variant Frontotemporal Dementia. - Suhonen, Noora-Maria; Haanpää, Ramona M; Korhonen, Ville; Jokelainen, Jari; Pitkäniemi, Anni; Heikkinen, Anna-Leena; Krüger, Johanna; Hartikainen, Päivi; Helisalmi, Seppo; Hiltunen, Mikko; Hänninen, Tuomo; Remes, Anne M (J Alzheimers Dis, 2017)
While the C9ORF72 expansion is a major cause of behavioral variant frontotemporal dementia (bvFTD), little is known of the resultant cognitive profile. Our aim was to characterize the neuropsychological profile of the C9ORF72 associated bvFTD. We contrasted structured neuropsychological assessments of the C9ORF72 expansion carrier bvFTD patients (n = 26) with non-carrier bvFTD patients (n = 47) and those with Alzheimer's disease (AD) (n = 47). As compared to the non-carrier bvFTD patients, the C9ORF72 expansion carriers performed at a higher level in an immediate verbal memory test while showing poorer phonemic verbal fluency. Additionally, the expansion carriers committed more errors in the Stroop test and the Alternating S task relative to the non-carriers. Finally, while the AD patients outperformed both bvFTD patient groups in working memory, their performance was more impaired in episodic memory tasks relative to the bvFTD groups. We conclude that bvFTD patients carrying the C9ORF72 expansion may display more pronounced executive deficits together with less severe verbal memory impairment as compared to their non-carrier bvFTD counterparts. Knowledge of the specific neuropsychological features associated with the C9ORF72 related bvFTD may aid in the early diagnosis of the disease as well as in targeting genetic testing.

A Novel PSEN1 K311R Mutation Discovered in Chinese Families with Late-Onset Alzheimer's Disease Affects Amyloid-β Production and Tau Phosphorylation. - Dong, Jing; Qin, Wei; Wei, Cuibai; Tang, Yi; Wang, Qi; Jia, Jianping (J Alzheimers Dis, 2017)
BACKGROUND: Presenilin-1 (PSEN1) is the most frequently mutated gene in familial Alzheimer's disease (AD), whereas only several novel mutations have been reported in China and functional studies were seldom conducted. OBJECTIVE: We describe a novel PSEN1 K311R mutation in two Chinese families with late-onset AD and its functional impact on amyloid-β protein precursor (AβPP) processing and tau phosphorylation. METHODS: The mutation was detected by direct sequencing of PSEN1 exon 9. HEK293 cells stably expressing wild-type APP695 (HEK293-APP695wt) were transfected with plasmids containing human wild-type PSEN1, PSEN1 K311R mutation, and PSEN1 E280A mutation to compare the K311R mutation's effects on AβPP processing with other groups. In addition, each group of cells were co-transfected with plasmids harboring PSEN1 and human wild-type MAPT complementary DNA to study the mutation's impacts on tau phosphorylation. RESULTS: The K311R mutation was detected in probands of two late-onset AD families. Expression of the K311R or E280A mutation increased amyloid-β (Aβ)42 levels but decreased Aβ40 levels, resulting in an overall increase in the Aβ42/Aβ40 ratio compared to those in wild-type PSEN1 transfected cells (p < 0.05). The K311R or E280A mutation also increased the levels of phosphorylated tau compared to wild-type PSEN1 (p < 0.05). CONCLUSION: The K311R mutation might contribute to AD pathogenesis by overproducing toxic Aβ species and enhancing tau phosphorylation. Further in-depth studies are needed to decipher the pathogenic mechanisms of the K311R mutation in terms of AβPP cleavage, tau phosphorylation, and other presenilin-1 mediated functional pathways.

N-Terminal Pro-B Type Natriuretic Peptide is Associated with Mild Cognitive Impairment in the General Population. - Kara, Kaffer; Mahabadi, Amir Abbas; Weimar, Christian; Winkler, Angela; Neumann, Till; Kälsch, Hagen; Dragano, Nico; Moebus, Susanne; Erbel, Raimund; Jöckel, Karl-Heinz; Jokisch, Martha (J Alzheimers Dis, 2017)
BACKGROUND: N-terminal pro-B type natriuretic peptide (NT-proBNP) is a marker of cardiac stress and is linked with silent cardiac diseases. While associations of cognitive impairment with manifest cardiovascular diseases are established, data on whether subclinical elevation of NT-proBNP levels below clinically established threshold of heart failure is related with cognitive functioning, especially mild cognitive impairment (MCI), is rare. OBJECTIVE: Aim of the present study was to investigate the cross-sectional association of NT-proBNP levels and MCI in a population-based study sample without heart failure. METHODS: We used data from the second examination of the population based Heinz-Nixdorf-Recall-Study. Subjects with overt coronary heart disease and subjects with NT-proBNP levels indicating potential heart failure (NT-proBNP≥300 pg/ml) were excluded from this analysis. Participants performed a validated brief cognitive assessment and were classified either as MCI [subtypes: amnestic-MCI (aMCI), non-amnestic-MCI (naMCI)], or cognitively-normal. RESULTS: We included 419 participants with MCI (63.1±7.4 y; 47% men; aMCI n = 209; naMCI n = 210) and 1,206 cognitively normal participants (62.42±7.1 y; 48% men). NT-proBNP-levels≥125 pg/ml compared to <125 pg/ml were associated with MCI in fully adjusted models (OR 1.65 (1.23;2.23) in the total sample, 1.73 (1.09;2.74) in men and 1.63(1.10;2.41) in women). For aMCI, the fully adjusted OR was 1.53 (1.04;2.25) and for naMCI, the fully adjusted OR was 1.34 (1.09; 166) in the total sample. CONCLUSION: Within normal ranges and without manifest heart failure, higher NT-proBNPlevels are associated with MCI and both MCI subtypes independent of traditional cardiovascular risk factors and sociodemographic parameters.

One-Year Evolution of Behavioral and Psychological Symptoms of Dementia in Patients Initially Hospitalized in Cognitive Behavioral Units: The EVITAL Prospective Cohort. - Rouch, Isabelle; Pongan, Elodie; Trombert, Béatrice; Fabre, Florence; Auguste, Nicolas; Sellier, Claire; Freulon, Magalie; Jacqueline, Sophie; Federico, Denis; Mouchoux, Christelle; Martin-Gaujard, Géraldine; Krolak-Salmon, Pierre; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The 2008-2012 French Alzheimer's Plan has provided hospital Cognitive and Behavioral Units (CBU) to improve the management of patients with productive behavioral and psychological symptoms of dementia (BPSD). Little is known concerning the behavioral outcome of these patients after discharge. OBJECTIVE: The present study investigated the long-term evolution of BPSD over one year after CBU discharge. METHODS: The EVITAL cohort included 221 participants admitted to the CBUs of 3 French hospitals. BPSD were collected using the Neuropsychiatric Inventory (NPI) at admission and 3, 6, and 12 months after hospitalization. The global NPI score evolution was assessed using a linear mixed-effect model. A four-factor model of the NPI including behavioral dyscontrol, psychosis, mood, and agitation subscores was also analyzed. RESULTS: Our analysis focused on 148 patients followed up during 12 months and evaluated at each visit. The global NPI score was 48.5 (SD 21.7) at baseline, 28.8 (SD 18.7) at 3-month, 23.2 (SD 16.4) at 6-month and 20.9 (SD 15.9) at 12-month follow-up. The score significantly decreased from baseline to follow-up (F = 109.3 p < 0.0001). Moreover, the decrease was observed for each NPI subscores. The Clinical Dementia Rating (CDR) scale score was significantly linked to the baseline NPI score (t = 2.76, p = 0.009). Conversely, the NPI decline was observed whatever the CDR level. CONCLUSION: The present study showed a decrease in the global NPI score and all its subscores during the year following the CBU hospitalization, regardless of the initial CDR score.

Pathway-Specific Polygenic Risk Scores as Predictors of Amyloid-β Deposition and Cognitive Function in a Sample at Increased Risk for Alzheimer's Disease. - Darst, Burcu F; Koscik, Rebecca L; Racine, Annie M; Oh, Jennifer M; Krause, Rachel A; Carlsson, Cynthia M; Zetterberg, Henrik; Blennow, Kaj; Christian, Bradley T; Bendlin, Barbara B; Okonkwo, Ozioma C; Hogan, Kirk J; et al. (J Alzheimers Dis, 2017)
Polygenic risk scores (PRSs) have been used to combine the effects of variants with small effects identified by genome-wide association studies. We explore the potential for using pathway-specific PRSs as predictors of early changes in Alzheimer's disease (AD)-related biomarkers and cognitive function. Participants were from the Wisconsin Registry for Alzheimer's Prevention, a longitudinal study of adults who were cognitively asymptomatic at enrollment and enriched for a parental history of AD. Using genes associated with AD in the International Genomics of Alzheimer's Project's meta-analysis, we identified clusters of genes that grouped into pathways involved in amyloid-β (Aβ) deposition and neurodegeneration: Aβ clearance, cholesterol metabolism, and immune response. Weighted pathway-specific and overall PRSs were developed and compared to APOE alone. Mixed models were used to assess whether each PRS was associated with cognition in 1,200 individuals, cerebral Aβ deposition measured using amyloid ligand (Pittsburgh compound B) positron emission imaging in 168 individuals, and cerebrospinal fluid Aβ deposition, neurodegeneration, and tau pathology in 111 individuals, with replication performed in an independent sample. We found that PRSs including APOE appeared to be driven by the inclusion of APOE, suggesting that the pathway-specific PRSs used here were not more predictive than an overall PRS or APOE alone. However, pathway-specific PRSs could prove to be useful as more knowledge is gained on the genetic variants involved in specific biological pathways of AD.

Pazopanib Reduces Phosphorylated Tau Levels and Alters Astrocytes in a Mouse Model of Tauopathy. - Javidnia, Monica; Hebron, Michaeline L; Xin, Yue; Kinney, Nikolas G; Moussa, Charbel E-H (J Alzheimers Dis, 2017)
Hyperphosphorylation and aggregation of tau protein is a critical factor in many neurodegenerative diseases. These diseases are increasing in prevalence, and there are currently no cures. Previous work from our group and others has shown that tyrosine kinase inhibitors (TKIs) can stimulate autophagy, decrease pathological proteins, and improve symptoms in models of neurodegeneration. Here we examined the role of pazopanib in mouse models that express either human mutant P301L tau (TauP301L) or triple mutant amyloid precursor protein (3x-AβPP). The TauP301L mouse expresses P301L tau under the control of a prion promoter in both neurons and astrocytes, reminiscent of some human tauopathies. Pazopanib crosses the blood-brain barrier with no detectable peripheral off-side effects, and decreases p-tau in TauP301L mice. Pazopanib reaches a brain concentration sufficient for inhibition of several tyrosine kinases, including vascular endothelial growth factor receptors (VEGFRs). Further, pazopanib does not affect microglia but reduces astrocyte levels toward nontransgenic controls in TauP301L mice. Pazopanib does not alter amyloid beta levels or astrocytes in 3x-AβPP mice but modulates a number of inflammatory markers (IP-10, MIP-1α, MIP-1β, and RANTES). These data suggest that pazopanib may be involved in p-tau clearance and modulation of astrocytic activity in models of tauopathies.

People with Dementia Can Learn Compensatory Movement Maneuvers for the Sit-to-Stand Task: A Randomized Controlled Trial. - Werner, Christian; Wiloth, Stefanie; Lemke, Nele Christin; Kronbach, Florian; Jansen, Carl-Philipp; Oster, Peter; Bauer, Jürgen M; Hauer, Klaus (J Alzheimers Dis, 2017)
BACKGROUND: A complex motor skill highly relevant to mobility in everyday life (e.g., sit-to-stand [STS] transfer) has not yet been addressed in studies on motor learning in people with dementia (PwD). OBJECTIVE: To determine whether a dementia-specific motor learning exercise program enables PwD to learn compensatory STS maneuvers commonly taught in geriatric rehabilitation therapy to enhance patients' STS ability. METHODS: Ninety-seven patients with mild-to-moderate dementia (Mini-Mental State Examination: 21.9±2.9 points) participated in a double-blinded, randomized, placebo-controlled trial with 10-week intervention and 3-month follow-up period. The intervention group (IG, n = 51) underwent a motor learning exercise program on compensatory STS maneuvers specifically designed for PwD. The control group (CG, n = 46) performed a low-intensity motor placebo activity. Primary outcomes were scores of the Assessment of Compensatory Sit-to-stand Maneuvers in People with Dementia (ACSID), which covers the number of recalled and initiated, and of effectively performed compensatory STS maneuvers. Secondary outcomes included temporal and kinematic STS characteristics measured by a body-fixed motion sensor (BFS, DynaPort® Hybrid). RESULTS: The IG significantly improved in all ACSID scores compared to the CG (p < 0.001). Secondary analysis confirmed learning effects for all BFS-based outcomes (p < 0.001-0.006). Learning gains were sustained during follow-up for most outcomes. CONCLUSION: People with mild-to-moderate dementia can learn and retain compensatory STS maneuvers in response to a dementia-specific motor learning exercise program. This is the first study that demonstrated preserved motor learning abilities in PwD by using a motor skill highly relevant to everyday life.

Persistence with Antihypertensive Drugs in Patients with Hypertension and Dementia in Germany. - Jacob, Louis; Adam-Schnepf, Leonie; Kostev, Karel (J Alzheimers Dis, 2017)
BACKGROUND: Hypertension, a chronic disease resulting from aging and its related physiopathological dysregulations, is often associated with dementia. OBJECTIVE: The goal was to analyze the persistence with antihypertensive drugs in patients affected by both hypertension and dementia in Germany. METHODS: This study included hypertension patients who were initially treated with antihypertensive drugs in 1,262 general practices in Germany between January 2013 and December 2015 (index date). Patients with hypertension and comorbid dementia were matched (1 : 1) to patients without dementia by age, gender, type of residence (nursing home versus home-care setting), physician, and initial antihypertensive therapy, using a propensity score method. The primary outcome was the rate of patients without treatment discontinuation with antihypertensive drugs in cases and controls in the 12 months following the index date. Cox regressions were used to determine the impact of dementia on persistence with antihypertensive treatment. RESULTS: This study included 2,191 patients with hypertension and comorbid dementia and 2,191 patients with hypertension but without dementia. The mean age was 79.3 years (SD = 10.3 years) in both groups. Twelve months after initiation of antihypertensive therapy, 73.5% of cases and 69.5% of controls were persistent (p < 0.001). Dementia was associated with a significant decrease in the risk of non-persistence with antihypertensive drugs in the entire population (HR = 0.86, 95% CI: 0.79-0.93). This finding was corroborated in five different subgroups (age ≤60 years, age 61-70 years, men, women, and patients living in home-care settings). CONCLUSIONS: Dementia was found to be a protective factor for persistence with antihypertensive drugs in Germany.

Pleiotropic Effect of Human ApoE4 on Cerebral Ceramide and Saturated Fatty Acid Levels. - den Hoedt, Sandra; Janssen, Carola I F; Astarita, Giuseppe; Piomelli, Daniele; Leijten, Frank P J; Crivelli, Simone M; Verhoeven, Adrie J M; De Vries, Helga E; Walter, Jochen; Martinez-Martinez, Pilar; Sijbrands, Eric J G; Kiliaan, Amanda J; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Apolipoprotein E (ApoE) is known for its role in lipid trafficking and the ɛ4 allele is a risk factor for late onset Alzheimer's disease (AD). Recently, aberrant ceramide and fatty acid (FA) levels have been implicated in AD. OBJECTIVE: To determine the specific effects of human ApoE4 (hE4) on cerebral ceramide and FA content during chow or a high fat/high cholesterol (HFHC) diet. METHODS: Cerebral ceramide and FA profiles were determined by LC-MSMS in 15-month-old female wild-type (WT), ApoE-knockout (E0), and hE4-knockin mice fed chow or a HFHC diet for 3 months. mRNA levels of genes involved in ceramide and FA metabolism were determined by qPCR. RESULTS: Similar to E0, hE4 mice displayed lower cerebral total ceramide, Cer16 : 0, and Cer24 : 1 levels than WT mice on both diets. Akin to WT mice, hE4 mice had lower total and saturated FA levels on chow than E0 mice. The HFHC diet significantly increased total and saturated FA levels in hE4 mice. Chow-fed hE4 mice showed lower mRNA levels of ceramide synthase (CerS) 6, acid sphingomyelinase, and of most ceramide and FA transporters than WT and E0 mice. The HFHC diet downregulated the expression of CerSs in hE4 and WT mice, and of ceramide and FA transporters in WT mice, but not in E0 mice. CONCLUSION: hE4 reduced cerebral ceramide levels to levels observed in E0 mice independent of diet. The HFHC diet increased cerebral FA levels in hE4 mice. This was associated with alterations in the expression of ceramide and FA transporters specifically in hE4 mice.

Predicting Development of Amyotrophic Lateral Sclerosis in Frontotemporal Dementia. - Van Langenhove, Tim; Piguet, Olivier; Burrell, James R; Leyton, Cristian; Foxe, David; Abela, Melissa; Bartley, Lauren; Kim, Woojin S; Jary, Eve; Huang, Yue; Dobson-Stone, Carol; Kwok, John B; et al. (J Alzheimers Dis, 2017)
BACKGROUND: A proportion of patients with frontotemporal dementia (FTD) also develop amyotrophic lateral sclerosis (ALS). OBJECTIVE: We aimed to establish the risk of developing ALS in patients presenting with FTD and to identify the relevant clinical variables associated with progression from FTD to FTD-ALS. METHODS: Of 218 consecutive patients with FTD, 10.1% had a dual FTD-ALS diagnosis at presentation. The remaining 152 FTD patients with follow-up of at least 12 months were included in the present study. We calculated the rate of progression to FTD-ALS and compared the baseline characteristics of FTD patients who developed ALS to those who did not develop ALS. RESULTS: Five percent of FTD patients developed ALS. The incidence rate of ALS was 6.7/100 patient-years in patients with FTD symptoms since 1 year, which declined with duration of FTD symptoms. No FTD patients developed ALS after 5 years. Five out of 8 FTD patients who developed ALS had presented with a mixed behavioral variant FTD and progressive non-fluent aphasia (bvFTD+PNFA) phenotype, 2 with bvFTD, and 1 with PNFA. Progression to FTD-ALS was significantly more frequent in patients with bvFTD+PNFA compared to those without this phenotype (p < 0.0001, OR 38.3, 95% CI: 7.3 to 199.2), and in FTD patients who carried the C9orf72 repeat expansion compared to those without the repeat expansion (p = 0.02, OR 8.0, 95% CI: 1.7 to 38.6). CONCLUSIONS: FTD patients with a mixed bvFTD+PNFA phenotype and with a C9orf72 repeat expansion should be closely monitored for the possible development of ALS. The risk of developing ALS in FTD appears to decline with the duration of FTD symptoms.

Prediction Model of Conversion to Dementia Risk in Subjects with Amnestic Mild Cognitive Impairment: A Longitudinal, Multi-Center Clinic-Based Study. - Jang, Hyemin; Ye, Byoung Seok; Woo, Sookyoung; Kim, Sun Woo; Chin, Juhee; Choi, Seong Hye; Jeong, Jee Hyang; Yoon, Soo Jin; Yoon, Bora; Park, Kyung Won; Hong, Yun Jeong; Kim, Hee Jin; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Patients with amnestic mild cognitive impairment (aMCI) have an increased risk of dementia. However, conversion rate varies. Therefore, predicting the dementia conversion in these patients is important. OBJECTIVE: We aimed to develop a nomogram to predict dementia conversion in aMCI subjects using neuropsychological profiles. METHODS: A total of 338 aMCI patients from two hospital-based cohorts were used in analysis. All patients were classified into 1) verbal, visual, or both, 2) early or late, and 3) single or multiple-domain aMCI according to the modality, severity of memory dysfunction, and multiplicity of involved cognitive domains, respectively. Patients were followed up, and conversion to dementia within 3 years was defined as the primary outcome. Our patients were divided into a training data set and a validation data set. The associations of potential covariates with outcome were tested, and nomogram was constructed by logistic regression model. We also developed another model with APOE data, which included 242 patients. RESULTS: In logistic regression models, both modalities compared with visual only (OR 4.44, 95% CI 1.83-10.75, p = 0.001), late compared to early (OR 2.59, 95% CI 1.17-5.72, p = 0.019), and multiple compared to single domain (OR 3.51, 95% CI 1.62-7.60, p = 0.002) aMCI were significantly associated with dementia conversion within 3 years. A nomogram incorporating these clinical variables was constructed on the training data set and validated on the validation data set. Both nomograms with and without APOE data showed good prediction performance (c-statistics ≥ 0.75). CONCLUSIONS: This study showed that several neuropsychological profiles of aMCI are significantly associated with imminent dementia conversion, and a nomogram incorporating these clinical subtypes is simple and useful to help to predict disease progression.

Prevalence of Use of Cardiovascular Drugs in Dementia Patients Treated in General Practices in Germany. - Jacob, Louis; Bohlken, Jens; Kostev, Karel (J Alzheimers Dis, 2017)
BACKGROUND: Dementia is a chronic disease associated with numerous cardiovascular disorders. OBJECTIVE: To analyze the prevalence of cardiovascular drug use in dementia patients treated in general practices in Germany. METHODS: The present study included patients who were diagnosed with dementia (Alzheimer's disease, vascular dementia, or unspecified dementia) in 2015. The main outcome measure was the proportion of patients using cardiovascular drugs. Demographical and clinical variables included age, sex, dementia type, and cardiovascular co-diagnoses. A multivariate logistic regression model was used to analyze the association between cardiovascular drug use and these variables. RESULTS: We identified 7,987 and 1,268 dementia patients with and without prescriptions for cardiovascular drugs, respectively. The share of individuals who received cardiovascular treatments was 86.3%. Diuretics (20.9%), beta blocking agents (20.0%), and ACE inhibitors (17.4%) were the three most commonly prescribed types of medications. Patients between the ages of 71-80 (OR = 1.59), 81-90 (OR = 1.61), and over 90 years (OR = 1.48) were more likely to receive cardiovascular drugs than patients under the age of 70 years. Moreover, compared to those with unspecified dementia, individuals with Alzheimer's disease had a lower chance while those with vascular dementia had a higher chance of being prescribed these drugs (ORs equal to 0.81 and 1.22, respectively). Finally, we found a positive association between the use of cardiovascular drugs and all co-diagnoses (ORs ranging from 1.23 to 7.12). CONCLUSION: The prevalence of cardiovascular drug use in dementia patients was around 86%. This use was significantly associated with such factors as age, type of dementia, and co-diagnoses.

Prevalence, Risk Factors, and Complaints Screening Tool Exploration of Subjective Cognitive Decline in a Large Cohort of the Chinese Population. - Hao, Lixiao; Wang, Xiaoni; Zhang, Ling; Xing, Yue; Guo, Qihao; Hu, Xiaochen; Mu, Bin; Chen, Yili; Chen, Guanqun; Cao, Jing; Zhi, Xiaodong; Liu, Jiaojiao; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Substantial studies have reported the prevalence and the affecting factors of subjective cognitive decline (SCD). The complaints screening scale has also been used for probing. However, little is known in China. OBJECTIVE: To investigate the prevalence and risk factors of SCD, and explore an SCD complaints screening scale in China. METHODS: Stratified cluster random sampling was conducted. 2,689 residents aged 60-80 years completed questionnaire 1. 814 residents were included for clinical and neuropsychological evaluations. Two standards were used to make the diagnosis of mild cognitive impairment (MCI) and SCD, and a preliminary screening rate comparison was carried out. Finally, we assessed the risk factors of SCD and the correlation between the SCD-questionnaire 9 (SCD-Q9) and the Auditory Verbal Learning Test-Long Delay Free Recall (AVLT-LR). RESULTS: 1) Standard 1 (ADNI2): the prevalence of SCD was 18.8% (95% CI = 14.7-22.9%) and zero conformed to six criteria (SCD plus). 2) Standard 2 (Jak/Bondi): the prevalence of SCD was 14.4% (95% CI = 10.7-18.1%). 3) Standard 1 had a relatively higher "false" positive rate, whereas Standard 2 had higher "false" negative rate. 4) Age, low education, fewer close friends, and daily drinking were independent risk factors for SCD progressing to MCI. 5) Total points of SCD-Q9 were negatively correlated to the value of AVLT-LR. CONCLUSIONS: The prevalence of SCD is high in the ShunYi District in Beijing, China. Age, low education, less social support, and daily drinking are independent risk factors. The brief SCD-Q9 can be used as a reference.

proBDNF Accelerates Brain Amyloid-β Deposition and Learning and Memory Impairment in APPswePS1dE9 Transgenic Mice. - Chen, Jia; Zhang, Tao; Jiao, Shusheng; Zhou, Xinfu; Zhong, Jinhua; Wang, Yanjiang; Liu, Juan; Deng, Juan; Wang, Shuiping; Xu, Zhiqiang (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is pathologically known for the amyloid-β (Aβ) deposition, neurofibrillary tangles, and neuronal loss in the brain. The precursor of brain-derived neurotrophic factor (proBDNF) before proteolysis has opposing functions to its mature form in neuronal survival and neurite growth. However, the role of proBDNF in the pathogenesis of AD remains unclear. OBJECTIVE: To investigate the effects of proBDNF on neurons in vitro, and on learning and memory impairment and brain Aβ production in a transgenic AD mouse model (APPswePS1dE9). METHODS: We here examined the effects of proBDNF on the viability (MTT assay) and neurite growth (morphologic measurement) of the primary neurons in vitro. After the intracerebroventricular injection of adeno-associated virus-proBDNF (AAV-proBDNF), we then investigated the learning and memory impairment (Morris water maze) and Aβ deposition in the brains of the AD mice. RESULTS: The results showed that proBDNF could inhibit neuronal viability and neurite growth in vitro, enhance Aβ levels, and accelerate its deposition in the brain, which was consistent with the learning and memory impairment of AD mice, likely dependent on the membrane receptor of p75NTR. CONCLUSIONS: Our findings suggest that proBDNF may exert a crucially negative effect during AD pathogenesis andprogression.

Protein Expression of BACE1 is Downregulated by Donepezil in Alzheimer's Disease Platelets. - Sarno, Tamires Alves; Talib, Leda Leme; Joaquim, Helena Passarelli Giroud; Bram, Jessyka Maria de França; Gattaz, Wagner Farid; Forlenza, Orestes Vicente (J Alzheimers Dis, 2017)
BACKGROUND: Abnormal amyloid-β protein precursor (AβPP) metabolism is a key feature of Alzheimer's disease (AD). Platelets contain most of the enzymatic machinery required for AβPP processing, and correlates of intracerebral abnormalities have been demonstrated in platelets of patients with AD. Thus, AβPP-related molecules in platelets may be regarded as peripheral markers of AD. OBJECTIVE: We sought to determine the protein expression of the AβPP secretases (ADAM10, BACE1, and PSEN1) and AβPP ratio in platelets of patients with mild or moderate AD compared to healthy controls. We further determined whether the protein expression of these markers might be modified by chronic treatment with donepezil. METHODS: Platelet samples were obtained from patients and controls at baseline and after 3 and 6 months of continuous treatment with therapeutic doses of donepezil. The protein expression of platelet markers was determined by western blotting. RESULTS: AD patients had a significant decrease in AβPP ratio, ADAM10, and PSEN1 compared to controls at baseline, but these differences were not modified by the treatment. Nonetheless, a significant reduction in the protein expression of BACE1 was observed in patients treated with donepezil for 6 months. CONCLUSION: Our results corroborate previous findings from our group and others of decreased AβPP ratio and protein expression of ADAM10 in AD. We further show that PSEN1 is decreased in AD platelets, and that the protein expression of BACE1 is downregulated by chronic treatment with donepezil. This effect may be interpreted as evidence of disease modification.

Psychotropic Polypharmacy in Patients with Dementia: Prevalence and Predictors. - Nørgaard, Ane; Jensen-Dahm, Christina; Gasse, Christiane; Hansen, Elsebet Steno; Waldemar, Gunhild (J Alzheimers Dis, 2017)
BACKGROUND: Antipsychotics and other psychotropics are frequently used to treat neuropsychiatric symptoms in patients with dementia, even though the evidence for effect is limited. Concerns have been raised about the safety of antipsychotics, but concomitant use of multiple psychotropic drug classes (psychotropic polypharmacy) may also pose a risk for patients. OBJECTIVE: To investigate the prevalence and predictors associated with use of psychotropic polypharmacy in patients with dementia. METHODS: A population-based study using nationwide registers. Patients with dementia were identified among all Danish residents ≥65 years on January 1, 2012. Data on prescriptions and comorbidity was included in the analysis. Overlapping prescriptions for different psychotropic drug classes were used to determine psychotropic polypharmacy. A multivariable logistic regression analysis was conducted to evaluate factors independently associated with the prescription of other psychotropic drug classes among patients already using antipsychotics. RESULTS: Among all patients registered with dementia (34,553), 25.3% (8,728) used ≥2 psychotropic drugs. Among patients treated with antipsychotics 75.8% (5,403) used at least one other psychotropic drug during the antipsychotic treatment period. Nursing home residency, number of non-psychotropic medications used in 2011, and prior psychiatric diagnosis were associated with psychotropic polypharmacy among antipsychotic drug users. The most frequent combination of psychotropic drugs was antipsychotics and antidepressants. CONCLUSION: Concomitant use of psychotropic drugs was frequent in dementia patients. Patients living in nursing homes had the highest risk of receiving a combination of antipsychotics and other psychotropic drugs. Concomitant use of psychotropics may cause adverse events, and potential consequences for patients' safety call for further investigation.

Pupillary Responses as a Biomarker of Early Risk for Alzheimer's Disease. - Granholm, Eric L; Panizzon, Matthew S; Elman, Jeremy A; Jak, Amy J; Hauger, Richard L; Bondi, Mark W; Lyons, Michael J; Franz, Carol E; Kremen, William S (J Alzheimers Dis, 2017)
Task-evoked pupillary responses may be a psychophysiological biomarker of early risk for mild cognitive impairment (MCI) and Alzheimer's disease (AD). Pupil dilation during cognitive tasks reflects cognitive effort until compensatory capacity is surpassed and performance declines are manifest, and reflects activation in the locus coeruleus, where degenerative changes have been found in the earliest stages of AD. We recorded pupillary responses during digit span recall in 918 participants ages 56-66. Despite normal performance, amnestic single-domain MCI (S-MCI) participants showed greater pupil dilation than non-amnestic S-MCI and cognitively normal (CN) participants at lower cognitive loads. Multi-domain MCI (M-MCI) participants failed to modulate effort across cognitive loads and showed poorer performance. Pupillary responses differentiated MCI and CN groups. Amnestic S-MCI participants required compensatory effort to maintain performance, consistent with increased risk for decline. Greater effort in CN individuals might indicate risk for MCI. Results are consistent with dysfunction in locus coeruleus-linked brain systems. This brief task shows promise as a biomarker for early MCI and AD risk prediction.

Reduced Cardiovascular Functions in Patients with Alzheimer's Disease. - Jin, Wang-Sheng; Bu, Xian-Le; Wang, Ye-Ran; Li, Ling; Li, Wei-Wei; Liu, Yu-Hui; Zhu, Chi; Yao, Xiu-Qing; Chen, Yang; Gao, Chang-Yue; Zhang, Tao; Gao, Chang-Yue; et al. (J Alzheimers Dis, 2017)
Previous studies have suggested that cardiovascular functions might play a critical role in Alzheimer's disease (AD) pathogenesis. However, the relationship among heart function, blood flow of cerebral vessels, and AD remains unclear. In the present study, AD patients (n = 34) and age- and gender-matched cognitively normal controls (n = 34) were recruited. Comorbidity information was collected. The ejection fraction was measured using echocardiography, and the mean velocity, pulsatility index (PI), and resistance index (RI) of the basilar artery (BA), left terminal internal carotid artery (LTICA), and right terminal internal carotid artery (RTICA) were measured using transcranial Doppler. The lacunae, white matter changes, and plaque in the aortic arch and carotid arteries were collected from brain magnetic resonance imaging and computed tomography angiography images. Compared with normal controls, AD patients had lower ejection fractions and cerebral blood flow velocities and a higher RI and PI in the BA, LTICA, and RTICA, as well as more plaques in the aortic and carotid arteries. In the multivariate logistic regression analysis, the ejection fraction and the mean velocity of the BA and LTICA were independently associated with AD after adjusting for age, gender, education, vascular risk factors, arterial plaques, and brain ischemic lesions detected in the brain images. These findings suggest that heart function and vascular condition may play important roles in AD pathogenesis. Improving cardiovascular functions could be a promising approach for the prevention and treatment of AD.

Reduced Cerebrospinal Fluid Concentration of Apolipoprotein A-I in Patients with Alzheimer's Disease. - Johansson, Per; Almqvist, Erik G; Bjerke, Maria; Wallin, Anders; Johansson, Jan-Ove; Andreasson, Ulf; Blennow, Kaj; Zetterberg, Henrik; Svensson, Johan (J Alzheimers Dis, 2017)
BACKGROUND: Apolipoprotein E (ApoE) has been extensively studied in Alzheimer's disease (AD), but little is known of apolipoprotein A-I (ApoA-I) in cerebrospinal fluid (CSF). OBJECTIVE: Plasma lipids as well as ApoA-I and ApoE in plasma and CSF were determined and related to Mini-Mental State Examination (MMSE) score, APOE genotype, and CSF AD biomarkers. METHODS: Consecutive patients with AD (n = 29), stable mild cognitive impairment (n = 13), other dementias (n = 14), and healthy controls (n = 18) were included at a single center. RESULTS: AD patients had higher plasma triglycerides and lower CSF ApoA-I concentration than controls (both p < 0.05). CSF ApoE concentration was reduced in other dementias (p < 0.01). In AD as well as other dementias, the ratios between CSF and plasma concentrations of both ApoA-I and ApoE were lower than those in the controls. ApoA-I and ApoE in plasma and CSF were not influenced by APOEɛ4 allele distribution. In the total study population (n = 74), CSF ApoA-I correlated positively with MMSE score (r = 0.26, p < 0.05) and negatively with CSF P-tau (r = -0.25, p < 0.05). CSF ApoE correlated positively with CSF concentrations of T-tau and P-tau in the total study population and in AD patients. CONCLUSION: CSF ApoA-I was reduced in AD patients and associated with measures of cognitive function and AD disease status. The mechanisms underlying the decreased CSF:plasma ratios of ApoA-I and ApoE in AD and other dementias need to be explored in further studies.

Relation of Odor Identification with Alzheimer's Disease Markers in Cerebrospinal Fluid and Cognition. - Reijs, Babette L R; Ramakers, Inez H G B; Elias-Sonnenschein, Lyzel; Teunissen, Charlotte E; Koel-Simmelink, Marleen; Tsolaki, Magda; Wahlund, Lars-Olof; Waldemar, Gunhild; Hausner, Lucrezia; Johannsen, Peter; Vanderstichele, Hugo; Verhey, Frans; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Impaired olfactory function is an early characteristic of Alzheimer's disease (AD), but it remains unclear if odor identification also relates to early markers of AD in cerebrospinal fluid (CSF). OBJECTIVE: To investigate the association between odor identification and amyloid-β 1-42 (Aβ42) and total tau (t-tau) concentrations in CSF. In addition, to examine the relation between odor identification and cognitive function at baseline and at follow-up, and whether these associations are moderated by CSF Aβ42 and t-tau and apolipoprotein E (APOE) genotype. METHODS: We included 160 individuals (40 with normal cognition, 45 with mild cognitive impairment (MCI), 42 with AD-type dementia, and 26 individuals with non-AD dementia) from the EDAR study. Individuals were recruited from six memory clinics across Europe. Odor identification was tested with the brief University of Pennsylvania Smell Identification Test. CSF Aβ42 and t-tau were assessed with INNO-BIA AlzBio3 Luminex assay. Neuropsychological assessment included tests for verbal memory, verbal fluency, attention, executive function, and visuoconstruction. Follow-up was performed within 3 years after baseline. RESULTS: Lower odor identification scores correlated with increased CSF t-tau concentrations and with lower scores on all cognitive measures at baseline independent of diagnostic group. Lower odor identification scores predicted decline on the MMSE in the total group, and decline on wordlist learning and delayed recall in APOE ɛ4 carriers and in individuals with abnormal Aβ42. CONCLUSION: Odor identification impairment may be an indicator of neuronal injury rather than amyloid pathology.

Risk Factors for Mild Cognitive Impairment in German Primary Care Practices. - Jacob, Louis; Bohlken, Jens; Kostev, Karel (J Alzheimers Dis, 2017)
BACKGROUND: Mild cognitive impairment (MCI) is a common mental disorder affecting around 16% of elderly people without dementia. MCI is considered an intermediate state between normal cognition and dementia. OBJECTIVE: To analyze risk factors for the development of MCI in German primary care practices. METHODS: In total, 3,604 MCI patients and 3,604 controls without MCI were included between January 2010 and December 2015. Several disorders potentially associated with MCI were determined. Multivariate logistic regression models were fitted with MCI as a dependent variable and other disorders as potential predictors. RESULTS: The mean age was 75.2 years and 45.3% of patients were men. MCI development was found to be associated with 12 disorders: intracranial injury, anxiety disorder, depression, mental and behavioral disorders due to alcohol use, stroke, hyperlipidemia, obesity, hypertension, Parkinson's disease, sleep disorder, coronary heart disease, and diabetes with odds ratios ranging from 1.13 (diabetes) to 2.27 (intracranial injury). CONCLUSION: Intracranial injury, anxiety, and depression showed the strongest association with MCI. Further analyses are needed to gain a better understanding of the MCI risk factors.

Sample Size Estimation for Alzheimer's Disease Trials from Japanese ADNI Serial Magnetic Resonance Imaging. - Fujishima, Motonobu; Kawaguchi, Atsushi; Maikusa, Norihide; Kuwano, Ryozo; Iwatsubo, Takeshi; Matsuda, Hiroshi (J Alzheimers Dis, 2017)
BACKGROUND: Little is known about the sample sizes required for clinical trials of Alzheimer's disease (AD)-modifying treatments using atrophy measures from serial brain magnetic resonance imaging (MRI) in the Japanese population. OBJECTIVE: The primary objective of the present study was to estimate how large a sample size would be needed for future clinical trials for AD-modifying treatments in Japan using atrophy measures of the brain as a surrogate biomarker. METHODS: Sample sizes were estimated from the rates of change of the whole brain and hippocampus by the k-means normalized boundary shift integral (KN-BSI) and cognitive measures using the data of 537 Japanese Alzheimer's Neuroimaging Initiative (J-ADNI) participants with a linear mixed-effects model. We also examined the potential use of ApoE status as a trial enrichment strategy. RESULTS: The hippocampal atrophy rate required smaller sample sizes than cognitive measures of AD and mild cognitive impairment (MCI). Inclusion of ApoE status reduced sample sizes for AD and MCI patients in the atrophy measures. CONCLUSION: These results show the potential use of longitudinal hippocampal atrophy measurement using automated image analysis as a progression biomarker and ApoE status as a trial enrichment strategy in a clinical trial of AD-modifying treatment in Japanese people.

Screening for Alzheimer's Disease: Cognitive Impairment in Self-Referred and Memory Clinic-Referred Patients. - Kirsebom, Bjørn-Eivind; Espenes, Ragna; Waterloo, Knut; Hessen, Erik; Johnsen, Stein Harald; Bråthen, Geir; Aarsland, Dag; Fladby, Tormod (J Alzheimers Dis, 2017)
BACKGROUND: Cognitive assessment is essential in tracking disease progression in AD. Presently, cohorts including preclinical at-risk participants are recruited by different means, which may bias cognitive and clinical features. We compared recruitment strategies to levels of cognitive functioning. OBJECTIVE: We investigate recruitment source biases in self-referred and memory clinic-referred patient cohorts to reveal potential differences in cognitive performance and demographics among at-risk participants. METHODS: We included 431 participants 40-80 years old. Participants were classified as controls (n = 132) or symptom group (n = 299). The symptom group comprised of subjective cognitive decline (SCD, n = 163) and mild cognitive impairment (MCI, n = 136). We compared cognitive performance and demographics in memory clinic-referrals (n = 86) to self-referred participants responding to advertisements and news bulletins (n = 179). Participants recruited by other means were excluded from analysis (n = 34). RESULTS: At symptom group level, we found significant reductions in cognitive performance in memory clinic-referrals compared to self-referrals. However, here reductions were only found within the MCI group. We found no differences in cognitive performance due to recruitment within the SCD group. The MCI group was significantly impaired compared to controls on all measures. Significant reductions in learning, and executive functions were also found for the SCD group. CONCLUSION: Regardless of recruitment method, both the SCD and MCI groups showed reductions in cognitive performance compared to controls. We found differences in cognitive impairment for memory clinic-referrals compared to self-referrals only within the MCI group, SCD-cases being equally affected irrespective of referral type.

Sex Difference in Aerobic Exercise Efficacy to Improve Cognition in Older Adults with Vascular Cognitive Impairment: Secondary Analysis of a Randomized Controlled Trial. - Barha, Cindy K; Hsiung, Ging-Yuek R; Best, John R; Davis, Jennifer C; Eng, Janice J; Jacova, Claudia; Lee, Philip E; Munkacsy, Michelle; Cheung, Winnie; Liu-Ambrose, Teresa (J Alzheimers Dis, 2017)
Aerobic training (AT) is a promising, non-pharmacological intervention to mitigate the deleterious effects of aging and disease on brain health. However, a large amount of variation exists in its efficacy. This is a secondary analysis of a randomized controlled trial of AT in 71 older adults with subcortical ischemic vascular cognitive impairment (NCT01027858). Specifically, we investigated: 1) whether sex moderates the relationship between AT and executive functions, and 2) the role of brain derived neurotrophic factor (BDNF) and gains in functional fitness capacity. Older adults were randomly assigned to either 6-month, thrice-weekly AT or to usual care plus education (CON). At baseline, trial completion, and 6-month follow-up, executive functions were assessed with the Trail Making Test (A & B), verbal digits forward and backward test, and the Stroop Test. Functional fitness capacity was assessed with the 6-Minute Walk Test. Compared with CON, AT significantly improved Trail Making Test performance in females but not males, an effect that was retained at follow-up. AT significantly increased BDNF levels in females but decreased levels in males. On the other hand, AT led to significant gains in functional fitness capacity in males only. This study provides evidence that sex differences exist in AT efficacy on brain health as well as in the biological mechanisms subserving AT.

Sleep Deprivation Induced Plasma Amyloid-β Transport Disturbance in Healthy Young Adults. - Wei, Meng; Zhao, Beiyu; Huo, Kang; Deng, Yongning; Shang, Suhang; Liu, Jie; Li, Yanbo; Ma, Louyan; Jiang, Yu; Dang, Liangjun; Chen, Chen; Wei, Shan; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Sleep is an important physiological process and beneficial in the removal of brain metabolites and functional recovery. Prior studies have shown that sleep disorders are significant risk factors for Alzheimer's disease (AD). OBJECTIVE: The present study was designed to characterize the effect of short-term total sleep deprivation (TSD) on plasma amyloid-β (Aβ) concentrations. METHODS: A clinical trial was conducted between March 1, 2016, and April 1, 2016. Twenty volunteers (age 27.3±3.4 years) with normal cognitive function and sleeping habits were recruited from the local population. Participants underwent 24 h of TSD. Periprocedural blood samples were collected to compare the changes of plasma Aβ42, Aβ40, low-density lipoprotein receptor-related protein (sLRP-1), soluble receptors for advanced glycation end products (sRAGE), and serum superoxide dismutase (SOD) and malonaldehyde (MDA). RESULTS: TSD increased morning plasma Aβ40 levels by 32.6% (p < 0.001) and decreased the Aβ42/Aβ40 ratio by 19.3% (p < 0.001). A positive relationship was found between TSD duration and plasma Aβ40 level (r = 0.51, p < 0.001) and Aβ40/Aβ42 ratio (r = 0.25, p = 0.003). Plasma concentrations of sLRP1 (p = 0.018) and sRAGE (p = 0.001) decreased significantly after TSD. Aβ40 and Aβ42 plasma concentrations correlated with plasma levels of sLRP1 and sRAGE. Serum SOD decreased after TSD (p = 0.005), whereas serum MDA was increased (p = 0.001). CONCLUSION: Sleep deprivation can lead to an elevation of plasma Aβ40 and decrease of the Aβ42/Aβ40 ratio. The underlying mechanisms may be related to increased oxidative stress and impaired peripheral Aβ clearance as pathomechanisms of AD.
Keywords: Adult; Amyloid beta-Peptides; Female; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Malondialdehyde; Peptide Fragments; Receptor for Advanced Glycation End Products; Sleep Deprivation; Superoxide Dismutase; Time Factors; Young Adult

Sporadic Cases with Novel Mutations and Pedigree in Hereditary Leukoencephalopathy with Axonal Spheroids. - Wu, Liyong; Liu, Jia; Sha, Longze; Wang, Xianling; Li, Jieying; Dong, Jing; Jia, Jianping (J Alzheimers Dis, 2017)
Hereditary diffuse leukoencephalopathy with spheroids (HDLS) is an autosomal dominant hereditary disease, featured by cerebral white matter degeneration with demyelination and axonal spheroids. We collected three gene-confirmed HDLS cases in our neurodegenerative clinic. Two HDLS cases were sporadic with novel mutations, while another case had a family history with previously described mutations. All three cases suffered memory problems with white matter lesions and pyramid signs. No obvious clinical differences were observed between sporadic and familial HDLS cases. Distinct features, such as subcortical calcification in brain computed tomography and asymmetric abnormal MRI signal along the pyramid tracts throughout brainstem and spinal cord (cervical, thoracic, and lumbar segments), were observed in one sporadic case with novel mutation. Therefore, the interactions of genotype-phenotype still need to be further investigated.

Stress-Induced Synaptic Dysfunction and Neurotransmitter Release in Alzheimer's Disease: Can Neurotransmitters and Neuromodulators be Potential Therapeutic Targets? - Jha, Saurabh Kumar; Jha, Niraj Kumar; Kumar, Dhiraj; Sharma, Renu; Shrivastava, Abhishek; Ambasta, Rashmi K; Kumar, Pravir (J Alzheimers Dis, 2017)
The communication between neurons at synaptic junctions is an intriguing process that monitors the transmission of various electro-chemical signals in the central nervous system. Albeit any aberration in the mechanisms associated with transmission of these signals leads to loss of synaptic contacts in both the neocortex and hippocampus thereby causing insidious cognitive decline and memory dysfunction. Compelling evidence suggests that soluble amyloid-β (Aβ) and hyperphosphorylated tau serve as toxins in the dysfunction of synaptic plasticity and aberrant neurotransmitter (NT) release at synapses consequently causing a cognitive decline in Alzheimer's disease (AD). Further, an imbalance between excitatory and inhibitory neurotransmission systems induced by impaired redox signaling and altered mitochondrial integrity is also amenable for such abnormalities. Defective NT release at the synaptic junction causes several detrimental effects associated with altered activity of synaptic proteins, transcription factors, Ca2+ homeostasis, and other molecules critical for neuronal plasticity. These detrimental effects further disrupt the normal homeostasis of neuronal cells and thereby causing synaptic loss. Moreover, the precise mechanistic role played by impaired NTs and neuromodulators (NMs) and altered redox signaling in synaptic dysfunction remains mysterious, and their possible interlink still needs to be investigated. Therefore, this review elucidates the intricate role played by both defective NTs/NMs and altered redox signaling in synaptopathy. Further, the involvement of numerous pharmacological approaches to compensate neurotransmission imbalance has also been discussed, which may be considered as a potential therapeutic approach in synaptopathy associated with AD.

Tai Chi Chuan and Baduanjin Increase Grey Matter Volume in Older Adults: A Brain Imaging Study. - Tao, Jing; Liu, Jiao; Liu, Weilin; Huang, Jia; Xue, Xiehua; Chen, Xiangli; Wu, Jinsong; Zheng, Guohua; Chen, Bai; Li, Ming; Sun, Sharon; Jorgenson, Kristen; et al. (J Alzheimers Dis, 2017)
The aim of this study is to investigate and compare how 12-weeks of Tai Chi Chuan and Baduanjin exercise can modulate brain structure and memory function in older adults. Magnetic resonance imaging and memory function measurements (Wechsler Memory Scale-Chinese revised, WMS-CR) were applied at both the beginning and end of the study. Results showed that both Tai Chi Chuan and Baduanjin could significantly increase grey matter volume (GMV) in the insula, medial temporal lobe, and putamen after 12-weeks of exercise. No significant differences were observed in GMV between the Tai Chi Chuan and Baduanjin groups. We also found that compared to healthy controls, Tai Chi Chuan and Baduanjin significantly improved visual reproduction subscores on the WMS-CR. Baduanjin also improved mental control, recognition, touch, and comprehension memory subscores of the WMS-CR compared to the control group. Memory quotient and visual reproduction subscores were both associated with GMV increases in the putamen and hippocampus. Our results demonstrate the potential of Tai Chi Chuan and Baduanjin exercise for the prevention of memory deficits in older adults.

Tau Pathology Promotes the Reorganization of the Extracellular Matrix and Inhibits the Formation of Perineuronal Nets by Regulating the Expression and the Distribution of Hyaluronic Acid Synthases. - Li, Yin; Li, Ze-Xu; Jin, Tan; Wang, Zhan-You; Zhao, Pu (J Alzheimers Dis, 2017)
Hyaluronic acid (HA) is the backbone of the extracellular matrix (ECM) and provides biochemical and physical support to aggrecan-based perineuronal nets (PNNs), which are associated with the selective vulnerability of neurons in Alzheimer's disease (AD). Here, we showed that HA synthases (HASs), including Has1, Has2, and Has3, were widely expressed in murine central nervous system. All types of HASs were localized to cell bodies of neurons; only Has1 existed in the membranes of neural axons. By using TauP301S transgenic (Tg) mouse model, we found that the axonal-localization of Has1 was abolished in TauP301S overexpressed mouse brain, and the redistribution of Has1 was also observed in human AD brains, suggesting that the localization of Has1 is dependent on intact microtubules which are regulated partially by the phosphorylation and dephosphorylation cycles of tau proteins. Furthermore, Has1 was reduced and Has3 was increased in TauP301S Tg mouse brain, resulting in the upregulation of shorter-chain HA in the ECM. These findings suggest that by abolishing the axonal-localization of Has1 and promoting the expression of Has3 and the synthesis of shorter-chain HA, the tau pathology breaks the balance of ECM components, promotes the reorganization of the ECM, and inhibits the formation of PNNs in the hippocampus, and then regulates neuronal plasticity during the progression of AD.

Temporal Order of Alzheimer's Disease-Related Cognitive Marker Changes in BLSA and WRAP Longitudinal Studies. - Bilgel, Murat; Koscik, Rebecca L; An, Yang; Prince, Jerry L; Resnick, Susan M; Johnson, Sterling C; Jedynak, Bruno M (J Alzheimers Dis, 2017)
Investigation of the temporal trajectories of currently used neuropsychological tests is critical to identifying earliest changing measures on the path to dementia due to Alzheimer's disease (AD). We used the Progression Score (PS) method to characterize the temporal trajectories of measures of verbal memory, executive function, attention, processing speed, language, and mental status using data spanning normal cognition, mild cognitive impairment, and AD from 1,661 participants with a total of 7,839 visits (age at last visit 77.6 SD 9.2) in the Baltimore Longitudinal Study of Aging (BLSA) and 1510 participants with a total of 3,473 visits (age at last visit 59.5 SD 7.4) in the Wisconsin Registry for Alzheimer's Prevention (WRAP). This method aligns individuals in time based on the similarity of their longitudinal measurements to reveal temporal trajectories. As a validation of our methodology, we explored the associations between the individualized cognitive progression scores (Cog-PS) computed by our method and clinical diagnosis. Digit span tests were the first to show declines in both data sets, and were detected mainly among cognitively normal individuals. These were followed by tests of verbal memory, which were in turn followed by Trail Making Tests, Boston Naming Test, and Mini-Mental State Examination. Differences in Cog-PS across the clinical diagnosis and APOEɛ4 groups were statistically significant, highlighting the potential use of Cog-PS as individualized indicators of disease progression. Identifying cognitive measures that are changing in preclinical AD can lead to the development of novel cognitive tests that are finely tuned to detecting earliest changes.

TMEM230 Accumulation in Granulovacuolar Degeneration Bodies and Dystrophic Neurites of Alzheimer's Disease. - Siedlak, Sandra L; Jiang, Yinfei; Huntley, Mikayla L; Wang, Luwen; Gao, Ju; Xie, Fei; Liu, Jingyi; Su, Bo; Perry, George; Wang, Xinglong (J Alzheimers Dis, 2017)
Transmembrane Protein 230 (TMEM230) is a newly identified protein associated with Parkinson's disease (PD) found in Lewy bodies and Lewy neurites of patients with PD or dementia with Lewy body disease. However, TMEM230 has not yet been investigated in the most common neurodegenerative disorder, Alzheimer's disease (AD). Here, we demonstrate that the expression of TMEM230 is specifically increased in neurons in AD patients. Importantly, both granulovacuolar degeneration (GVD) and dystrophic neurites (DNs), two prominent characteristic pathological structures associated with AD, contain TMEM230 aggregates. TMEM230 immunoreactivity can be detected in neurofibrillary tangles-containing neurons and hyperphosphorylated tau positive DNs. TMEM230 accumulation is also noted around senile plaques. These findings identifying TMEM230 as a component of GVD and DNs suggest TMEM230 dysregulation as a likely mechanism playing an important role in the pathogenesis of AD.

Trajectories of Multidimensional Caregiver Burden in Chinese Informal Caregivers for Dementia: Evidence from Exploratory and Confirmatory Factor Analysis of the Zarit Burden Interview. - Li, Dan; Hu, Nan; Yu, Yueyi; Zhou, Aihong; Li, Fangyu; Jia, Jianping (J Alzheimers Dis, 2017)
BACKGROUND: Despite its popularity, the latent structure of 22-item Zarit Burden Interview (ZBI) remains unclear. There has been no study exploring how caregiver multidimensional burden changed. OBJECTIVE: The aim of the work was to validate the latent structure of ZBI and to investigate how multidimensional burden evolves with increasing global burden. METHODS: We studied 1,132 dyads of dementia patients and their informal caregivers. The caregivers completed the ZBI and a questionnaire regarding caregiving. The total sample was randomly split into two equal subsamples. Exploratory factor analysis (EFA) was performed in the first subsample. In the second subsample, confirmatory factor analysis (CFA) was conducted to validate models generated from EFA. The mean of weighted factor score was calculated to assess the change of dimension burden against the increasing ZBI total score. RESULTS: The result of EFA and CFA supported that a five-factor structure, including role strain, personal strain, incompetency, dependency, and guilt, had the best goodness-of-fit. The trajectories of multidimensional burden suggested that three different dimensions (guilt, role strain and personal strain) became the main subtype of burden in sequence as the ZBI total score increased from mild to moderate. Factor dependency contributed prominently to the total burden in severe stage. CONCLUSION: The five-factor ZBI is a psychometrically robust measure for assessing multidimensional burden in Chinese caregivers. The changes of multidimensional burden have deepened our understanding of the psychological characteristics of caregiving beyond a single total score and may be useful for developing interventions to reduce caregiver burden.

Two Novel Mutations in the First Transmembrane Domain of Presenilin1 Cause Young-Onset Alzheimer's Disease. - Liu, Collin Y; Ohki, Yu; Tomita, Taisuke; Osawa, Satoko; Reed, Bruce R; Jagust, William; Van Berlo, Victoria; Jin, Lee-Way; Chui, Helena C; Coppola, Giovanni; Ringman, John M (J Alzheimers Dis, 2017)
BACKGROUND: The presenilin-1 protein (PS1) is the catalytic unit of γ-secretase implicated in the production of abnormally long forms of amyloid-β (Aβ), including Aβ42, proteins thought critical in the pathogenesis of Alzheimer's disease (AD). In AD of autosomal dominant inheritance, the majority of pathogenic mutations have been found in the PSEN1 gene within which the location of the mutation can provide clues as to the mechanism of pathogenesis. OBJECTIVE: To describe clinical features of two novel mutations in the transmembrane portion 1 (TMD-1) of PSEN1 as well as biochemical features in one and neuropathological findings in the other. METHODS: Two index patients with young onset AD with an autosomal dominant pattern of inheritance underwent clinical and imaging assessments, as well as PSEN1 sequencing. Postmortem examination was completed in one patient. An artificial construct in which the P88L mutation was introduced was created to examine its effects on γ-secretase cleavage. RESULTS: Two novel variants in TMD-1 (P88L and V89L) were identified in affected probands. The neuropathological findings of AD were confirmed in the V89L mutation. Both patients presented around age 40 with early short-term memory deficits followed by seizures and corticospinal tract signs. The P88L mutation additionally featured early myoclonus followed by Parkinsonism. The causal role of the P88L mutation is supported by demonstration that this mutation dramatically increased Aβ42 and decreased APP and Notch intracellular domain production in vitro. CONCLUSION: Changes in a single amino acid in codons 88 and 89 of TMD-1 can result in young-onset AD. The TMD-1 of PS1 is a region important for the γ-secretase cleavage of Aβ.

Urine Formaldehyde Predicts Cognitive Impairment in Post-Stroke Dementia and Alzheimer's Disease. - Tong, Zhiqian; Wang, Weishan; Luo, Wenhong; Lv, Jihui; Li, Hui; Luo, Hongjun; Jia, Jianping; He, Rongqiao (J Alzheimers Dis, 2017)
Although Alzheimer's disease (AD) was first described over 100 years ago, there is still no suitable biomarker for diagnosing AD in easily collectable samples (e.g., blood plasma, saliva, and urine). Here, we investigated the relationship between morning urine formaldehyde concentration and cognitive impairment in patients with post-stroke dementia (PSD) or AD in this cross-sectional survey for 7 years. Cognitive abilities of the study participants (n = 577, four groups: 231 controls, 61 stroke, 65 PSD, and 220 AD) were assessed by Mini-Mental State Examination (MMSE). Morning urine formaldehyde concentrations were measured by high performance liquid chromatography (HPLC). Gender- and age-matched participants were selected from the four groups (n = 42 in each group). Both semicarbazide-sensitive amine oxidase (SSAO, a formaldehyde-generating enzyme) and formaldehyde levels in the blood and urine were analyzed by using an enzyme-linked immunosorbent assay (ELISA) and HPLC, respectively. We found that morning urine formaldehyde levels were inversely correlated with MMSE scores. The threshold value (the best Cut-Off value) of formaldehyde concentration for predicting cognitive impairment was 0.0418 mM in patients with PSD (Sensitivity: 92.3%; Specificity: 77.1%), and 0.0449 mM in patients with AD (Sensitivity: 94.1%; Specificity: 81.8%), respectively. The results of biochemical analysis revealed that the observed increase in urine formaldehyde resulted from an overexpression of SSAO in the blood. The findings suggest that measuring the concentration of formaldehyde in overnight fasting urine could be used as a potentially noninvasive method for evaluating the likelihood of ensuing cognitive impairment or dementia.

Varying Degrees of Temporoparietal Hypometabolism on FDG-PET Reveal Amyloid-Positive Logopenic Primary Progressive Aphasia is not a Homogeneous Clinical Entity. - Krishnan, Kamini; Machulda, Mary M; Whitwell, Jennifer L; Butts, Alissa M; Duffy, Joseph R; Strand, Edythe A; Senjem, Matthew L; Spychalla, Anthony J; Jack, Clifford R; Lowe, Val J; Josephs, Keith A (J Alzheimers Dis, 2017)
BACKGROUND: The logopenic variant of primary progressive aphasia (lvPPA) manifests due to a breakdown of the language network with prominent hypometabolism of the left temporoparietal region. LvPPA is strongly associated with amyloid deposition, yet there is question as to whether it is a homogeneous clinical entity. OBJECTIVE: This study investigated whether differences in temporoparietal metabolic patterns on 18F fludeoxyglucose positron emission tomography (FDG-PET) could elucidate brain regions preferentially affected in lvPPA. METHOD: We used differences in FDG-PET metabolic z-scores relative to controls for means of left lateral temporal, left inferior parietal, and left superior parietal regions to classify 53 amyloid-positive lvPPA patients into temporal, parietal, or temporoparietal predominate groups. Clinical features and FDG-PET regions of hypometabolism outside of the temporoparietal region were then compared across the three groups; the latter using statistical parametric mapping. RESULTS: Of the 53 lvPPA patients, 15 were classified as temporal, 14 as temporoparietal, and 22 as parietal predominate. There were no significant differences between the groups on demographic measures, language evaluation, or apolipoprotein E genotype. Compared to the other two groups, individuals with the parietal predominate pattern had extensive hypometabolism in left frontal lobe and the precuneus. Furthermore, this group had greater behavioral dyscontrol and deficits in executive function, visuospatial skills, visual memory retention, working memory, and cognitive flexibility (Bonferronip < 0.05). CONCLUSIONS: This study demonstrates that there is clinical heterogeneity within amyloid-positive lvPPA. Patients with lvPPA with predominant parietal hypometabolism, unlike those with temporal or temporoparietal predominant hypometabolism, demonstrated widespread cognitive and behavioral changes.

Visual Rating of Posterior Atrophy as a Marker of Progression to Dementia in Mild Cognitive Impairment Patients. - Kim, Hang-Rai; Park, Young Ho; Jang, Jae-Won; Park, So Young; Wang, Min Jeong; Baek, Min Jae; Kim, Beom Joon; Ahn, Soyeon; Kim, SangYun (J Alzheimers Dis, 2017)
BACKGROUND: Although medial temporal atrophy (MTA) is a useful imaging marker of the progression to dementia in mild cognitive impairment (MCI), substantial numbers of MCI patients without MTA still progress to dementia. OBJECTIVE: We investigated whether visual ratings of posterior atrophy (PA) on magnetic resonance imaging show independent predictive value for the progression to dementia in MCI patients. METHODS: This was a retrospective cohort study of elderly patients who visited Seoul National University Bundang Hospital between 2004 and 2012. A total of 148 patients who were initially diagnosed with MCI were followed for up to 3 years (median 22 months) to determine whether they progressed to dementia. We used 4-point and 5-point visual rating scales to assess PA and MTA, respectively. PA and MTA scores were dichotomized into normal (no atrophy) or abnormal (atrophy) in each patient. We performed a Cox regression analysis to examine the hazard ratios (HRs) of PA and MTA for the progression to dementia with adjustment for age, APOEɛ4 allele status, and baseline Mini-Mental State Examination score. RESULTS: Among the study population, 47 patients progressed to dementia. Visual assessment of the MRI scans revealed that 67 patients (45.3%) showed PA, whereas 85 patients (57.3%) showed MTA. The HRs with 95% confidence intervals for PA and MTA were 2.516 (1.244-5.091) and 4.238 (1.680-10.687), respectively. The predictive values of visually assessed PA and MTA remained significant, independent of the covariates. CONCLUSION: Visual assessment of PA has independent predictive value for progression to dementia in MCI patients.

Vitamin D Insufficiency and Cognitive Function Trajectories in Older Adults: The Rancho Bernardo Study. - Laughlin, Gail A; Kritz-Silverstein, Donna; Bergstrom, Jaclyn; Reas, Emilie T; Jassal, Simerjot K; Barrett-Connor, Elizabeth; McEvoy, Linda K (J Alzheimers Dis, 2017)
BACKGROUND: Evidence of a role for vitamin D (VitD) in cognitive aging is mixed and based primarily on extreme VitD deficiency. We evaluated the association of VitD insufficiency with cognitive function in older, community-dwelling adults living in a temperate climate with year-round sunshine. METHODS: A population-based longitudinal study of 1,058 adults (median age 75; 62% women) who had cognitive function assessed and serum levels of 25-hydroxyvitaminD (25OHD) measured in 1997-99 and were followed for up to three additional cognitive function assessments over a 12-year period. RESULTS: Overall, 14% (n = 145) of participants had VitD insufficiency defined as 25OHD <30 ng/ml. Adjusting for age, sex, education, and season, VitD insufficiency was associated with poorer baseline performance on the Mini-Mental Status Exam (MMSE) (p = 0.013), Trails Making Test B (Trails B) (p = 0.015), Category Fluency (p = 0.006), and Long Term Retrieval (p = 0.019); differences were equivalent to 5 years of age. For those with VitD insufficiency, the odds of mildly impaired performance at baseline were 38% higher for MMSE (p = 0.08), 78% higher for Trails B (p = 0.017), and 2-fold higher for Category Fluency and Long Term Retrieval (both p = 0.001). VitD insufficiency was not related to the rate of cognitive decline on any test or the risk of developing impaired performance during follow-up. CONCLUSION: In this population with little VitD deficiency, even moderately low VitD was associated with poorer performance on multiple domains of cognitive function. Low VitD did not predict 12-year cognitive decline. Clinical trials are essential to establish a causal link between VitD and cognitive well-being.

What Drives Country Differences in Cost of Alzheimer's Disease? An Explanation from Resource Use in the GERAS Study. - Reed, Catherine; Happich, Michael; Argimon, Josep Maria; Haro, Josep Maria; Wimo, Anders; Bruno, Giuseppe; Dodel, Richard; Jones, Roy W; Vellas, Bruno; Belger, Mark (J Alzheimers Dis, 2017)
BACKGROUND: Country differences in resource use and costs of Alzheimer's disease (AD) may be driven by differences in health care systems and resource availability. OBJECTIVE: To compare country resource utilization drivers of societal costs for AD dementia over 18 months. METHODS: GERAS is an observational study in France (n = 419), Germany (n = 550), and the UK (n = 526). Resource use of AD patients and caregivers contributing to >1% of total societal costs (year 2010) was assessed for country differences, adjusting for participant characteristics. RESULTS: Mean 18-month societal costs per patient were France €33,339, Germany €38,197, and UK €37,899 (£32,501). Caregiver time spent on basic and instrumental activities of daily living (ADL) contributed the most to societal costs (54% France, 64% Germany, 65% UK). Caregivers in France spent less time on ADL than UK caregivers and missed fewer work days than in other countries. Compared with other countries, patients in France used more community care services overall and were more likely to use home aid. Patients in Germany were least likely to use temporary accommodation or to be institutionalized at 18 months. UK caregivers spent the most time on instrumental ADL, UK patients used fewest outpatient resources, and UK patients/caregivers were most likely to receive financial support. CONCLUSION: Caregiver time on ADL contributed the most to societal costs and differed across countries, possibly due to use of community care services and institutionalization. Other resources had different patterns of use across countries, reflecting country-specific health and social care systems.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Caregivers; Cohort Studies; Cost of Illness; Europe; Female; Health Resources; Humans; International Cooperation; Male; Surveys and Questionnaires

White Matter Hyperintensities Potentiate Hippocampal Volume Reduction in Non-Demented Older Individuals with Abnormal Amyloid-β. - Freeze, Whitney M; Jacobs, Heidi I L; Gronenschild, Ed H; Jansen, Jacobus F A; Burgmans, Saartje; Aalten, Pauline; Clerx, Lies; Vos, Stephanie J; van Buchem, Mark A; Barkhof, Frederik; van der Flier, Wiesje M; Verbeek, Marcel M; et al. (J Alzheimers Dis, 2017)
Cerebral small vessel disease (cSVD) and amyloid-β (Aβ) deposition often co-exist in (prodromal) dementia, and both types of pathology have been associated with neurodegeneration. We examined whether cSVD and Aβ have independent or interactive effects on hippocampal volume (HV) in a memory clinic population. We included 87 individuals with clinical diagnoses of Alzheimer's disease (AD) (n = 24), mild cognitive impairment (MCI) (n = 26), and subjective cognitive complaints (SCC) (n = 37). cSVD magnetic resonance imaging markers included white matter hyperintensity (WMH) volume, lacunar infarct presence, and microbleed presence. Aβ pathology was assessed as cerebrospinal fluid-derived Aβ1 - 42 levels and dichotomized into normal or abnormal, and HV was determined by manual volumetric measurements. A linear hierarchical regression approach was applied for the detection of additive or interaction effects between cSVD and Aβ on HV in the total participant group (n = 87) and in the non-demented group (including SCC and MCI individuals only, n = 63). The results revealed that abnormal Aβ and lacunar infarct presence were independently associated with lower HV in the non-demented individuals. Interestingly, Aβ and WMH pathology interacted in the non-demented individuals, such that WMH had a negative effect on HV in individuals with abnormal CSF Aβ42 levels, but not in individuals with normal CSF Aβ42 levels. These associations were not present when individuals with AD were included in the analyses. Our observations suggest that relatively early on in the disease process older individuals with abnormal Aβ levels are at an increased risk of accelerated disease progression when concomitant cSVD is present.

Young to Middle-Aged Dogs with High Amyloid-β Levels in Cerebrospinal Fluid are Impaired on Learning in Standard Cognition tests. - Borghys, Herman; Van Broeck, Bianca; Dhuyvetter, Deborah; Jacobs, Tom; de Waepenaert, Katja; Erkens, Tim; Brooks, Melissa; Thevarkunnel, Sandy; Araujo, Joseph A (J Alzheimers Dis, 2017)
Understanding differences in Alzheimer's disease biomarkers before the pathology becomes evident can contribute to an improved understanding of disease pathogenesis and treatment. A decrease in amyloid-β (Aβ)42 in cerebrospinal fluid (CSF) is suggested to be a biomarker for Aβ deposition in brain. However, the relevance of CSF Aβ levels prior to deposition is not entirely known. Dogs are similar to man with respect to amyloid-β protein precursor (AβPP)-processing, age-related amyloid plaque deposition, and cognitive dysfunction. In the current study, we evaluated the relation between CSF Aβ42 levels and cognitive performance in young to middle-aged dogs (1.5-7 years old). Additionally, CSF sAβPPα and sAβPPβ were measured to evaluate AβPP processing, and CSF cytokines were measured to determine the immune status of the brain. We identified two groups of dogs showing consistently low or high CSF Aβ42 levels. Based on prior studies, it was assumed that at this age no cerebral amyloid plaques were likely to be present. The cognitive performance was evaluated in standard cognition tests. Low or high Aβ concentrations coincided with low or high sAβPPα, sAβPPβ, and CXCL-1 levels, respectively. Dogs with high Aβ concentrations showed significant learning impairments on delayed non-match to position (DNMP), object discrimination, and reversal learning compared to dogs with low Aβ concentrations. Our data support the hypothesis that high levels of CSF Aβ in dogs coincide with lower cognitive performance prior to amyloid deposition. Further experiments are needed to investigate this link, as well as the relevance with respect to Alzheimer's disease pathology progression.

ABCA1 Agonist Reverses the ApoE4-Driven Cognitive and Brain Pathologies. - Boehm-Cagan, Anat; Bar, Roni; Liraz, Ori; Bielicki, John K; Johansson, Jan O; Michaelson, Daniel M (J Alzheimers Dis, 2016)
The allele ɛ4 of apolipoprotein E (apoE4) is the most prevalent genetic risk factor for Alzheimer's disease (AD) and is therefore a promising therapeutic target. Human and animal model studies suggest that apoE4 is hypolipidated; accordingly, we have previously shown that the retinoid X receptor (RXR) agonist bexarotene upregulates ABCA1, the main apoE-lipidating protein, resulting in increased lipidation of apoE4, and the subsequent reversal of the pathological effects of apoE4, namely: accumulation of Aβ42 and hyperphosphorylated tau, as well as reduction in the levels of synaptic markers and cognitive deficits. Since the RXR system has numerous other targets, it is important to devise the means of activating ABCA1 selectively. We presently utilized CS-6253, a peptide shown to directly activate ABCA1 in vitro, and examined the extent to which it can affect the degree of lipidation of apoE4 in vivo and counteract the associated brain and behavioral pathologies. This revealed that treatment of young apoE4-targeted replacement mice with CS-6253 increases the lipidation of apoE4. This was associated with a reversal of the apoE4-driven Aβ42 accumulation and tau hyperphosphorylation in hippocampal neurons, as well as of the synaptic impairments and cognitive deficits. These findings suggest that the pathological effects of apoE4 in vivo are associated with decreased activation of ABCA1 and impaired lipidation of apoE4 and that the downstream brain-related pathology and cognitive deficits can be counteracted by treatment with the ABCA1 agonist CS-6253. These findings have important clinical ramifications and put forward ABCA1 as a promising target for apoE4-related treatment of AD.

Added Prognostic Value of Cerebrospinal Fluid Biomarkers in Predicting Decline in Memory Clinic Patients in a Prospective Cohort. - Handels, Ron L H; Joore, Manuela A; Vos, Stephanie J B; Aalten, Pauline; Ramakers, Inez H G B; Rikkert, Marcel Olde; Scheltens, Philip; Jansen, Willemijn J; Visser, Pieter-Jelle; van Berckel, Bart M N; van Domburg, Peter; Smid, Machiel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Limited information is available on short-term prognosis of Alzheimer's disease (AD) biomarkers in cerebrospinal fluid (CSF) in addition to routine diagnostic workup. OBJECTIVE: This study aims to investigate the added prognostic value of AD CSF biomarkers. METHODS: In a prospective cohort study, clinical experts predicted cognitive and functional symptoms in 114 memory clinic patients by assessing comprehensive routine diagnostic test information (patient history, and physical, neurological, psychiatric, neuropsychological, and MRI examinations), without and with CSF biomarkers. The reference standard was the 'observed clinically relevant decline' using baseline and 1- and 2-year follow-up information. RESULTS: Decline over a 2-year period was observed in 51% of all participants (3% in SMC, 48% in MCI, 90% in mild dementia). In the total sample, the accuracy of predicted decline did not differ significantly between routine assessment without (79% correctly predicted) and with (74% correctly predicted) CSF biomarkers. Subgroup analyses revealed 25 (83%) correct predictions in SMC, 30 (68%) in MCI, and 35 (88%) in dementia without the use of CSF; and 21 (70%), 27 (61%), and 36 (90%), respectively, with the use of CSF in addition to the routine assessment. CONCLUSION: AD CSF biomarkers did not increase accuracy of 2-year prognosis of cognitive and functional decline when added to routine diagnostic workup. This suggests that the standard diagnostic workup without CSF biomarkers allows fairly accurate predictions for the short-term course of symptoms. Routine AD biomarkers in CSF have limited prognostic value over 2 years in persons with a suspected cognitive disorder.

Administering Cognitive Tests Through Touch Screen Tablet Devices: Potential Issues. - Jenkins, Amy; Lindsay, Stephen; Eslambolchilar, Parisa; Thornton, Ian M; Tales, Andrea (J Alzheimers Dis, 2016)
Mobile technologies, such as tablet devices, open up new possibilities for health-related diagnosis, monitoring, and intervention for older adults and healthcare practitioners. Current evaluations of cognitive integrity typically occur within clinical settings, such as memory clinics, using pen and paper or computer-based tests. In the present study, we investigate the challenges associated with transferring such tests to touch-based, mobile technology platforms from an older adult perspective. Problems may include individual variability in technical familiarity and acceptance; various factors influencing usability; acceptability; response characteristics and thus validity per se of a given test. For the results of mobile technology-based tests of reaction time to be valid and related to disease status rather than extraneous variables, it is imperative the whole test process is investigated in order to determine potential effects before the test is fully developed. Researchers have emphasized the importance of including the 'user' in the evaluation of such devices; thus we performed a focus group-based qualitative assessment of the processes involved in the administration and performance of a tablet-based version of a typical test of attention and information processing speed (a multi-item localization task), to younger and older adults. We report that although the test was regarded positively, indicating that using a tablet for the delivery of such tests is feasible, it is important for developers to consider factors surrounding user expectations, performance feedback, and physical response requirements and to use this information to inform further research into such applications.

Altered Affective Evaluations of Smells in Alzheimer's Disease. - Joussain, Pauline; Bessy, Marion; Fournel, Arnaud; Ferdenzi, Camille; Rouby, Catherine; Delphin-Combe, Floriane; Krolak-Salmon, Pierre; Bensafi, Moustafa (J Alzheimers Dis, 2016)
BACKGROUND: Studies of olfaction in Alzheimer's disease (AD) mainly focused on deficits in odor detection and identification, with very few investigations of olfactory emotional changes and their consequences for hedonics. OBJECTIVE: The aim of the present study was to characterize affective evaluations of odors in AD patients. METHODS: To this end, 20 AD patients and 20 matched controls were tested. Participants were screened for odor detection and identification ability and then asked to rate the intensity, pleasantness, and edibility of 20 odorants. RESULTS: Results showed that, overall, AD patients had lower detection ability and perceived all odors as weaker than controls. As expected, they had lower identification ability on both cued and non-cued tasks. In addition, when smelling pleasant odors, patients had significantly lower hedonic ratings than controls (p <  0.02), whereas no group difference was found for neutral or unpleasant odors (p >  0.05 in both cases). Moreover, an analysis combining both intensity and pleasantness ratings showed that whereas intensity increased as a function of pleasantness and unpleasantness in controls, this quadratic relationship was not observed in AD patients. CONCLUSIONS: The study suggests that the simplest categorization criteria of odors (intensity and hedonic valence) are impaired in AD patients (especially for pleasant odors).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Case-Control Studies; Emotions; Female; Humans; Male; Mood Disorders; Odorants; Olfaction Disorders; Psychiatric Status Rating Scales; Smell; Surveys and Questionnaires

Altered Brain Activities Associated with Neural Repetition Effects in Mild Cognitive Impairment Patients. - Yu, Jing; Li, Rui; Jiang, Yang; Broster, Lucas S; Li, Juan (J Alzheimers Dis, 2016)
Older adults with mild cognitive impairment (MCI) manifest impaired explicit memory. However, studies on implicit memory such as repetition effects in persons with MCI have been limited. In the present study, 17 MCI patients and 16 healthy normal controls (NC) completed a modified delayed-match-to-sample task while undergoing functional magnetic resonance imaging. We aim to examine the neural basis of repetition; specifically, to elucidate whether and how repetition-related brain responses are altered in participants with MCI. When repeatedly rejecting distracters, both NC and MCI showed similar behavioral repetition effects; however, in both whole-brain and region-of-interest analyses of functional data, persons with MCI showed reduced repetition-driven suppression in the middle occipital and middle frontal gyrus. Further, individual difference analysis found that activation in the left middle occipital gyrus was positively correlated with rejecting reaction time and negatively correlated with accuracy rate, suggesting a predictor of repetition behavioral performance. These findings provide new evidence to support the view that neural mechanisms of repetition effect are altered in MCI who manifests compensatory repetition-related brain activities along with their neuropathology.

Altered Energy Metabolism Pathways in the Posterior Cingulate in Young Adult Apolipoprotein E ɛ4 Carriers. - Perkins, Michelle; Wolf, Andrew B; Chavira, Bernardo; Shonebarger, Daniel; Meckel, J P; Leung, Lana; Ballina, Lauren; Ly, Sarah; Saini, Aman; Jones, T Bucky; Vallejo, Johana; Jentarra, Garilyn; et al. (J Alzheimers Dis, 2016)
The APOE gene, encoding apolipoprotein E, is the primary genetic risk factor for late-onset Alzheimer's disease (AD). Apolipoprotein E ɛ4 allele (APOE4) carriers have alterations in brain structure and function (as measured by brain imaging) even as young adults. Examination of this population is valuable in further identifying details of these functional changes and their association with vulnerability to AD decades later. Previous work demonstrates functional declines in mitochondrial activity in the posterior cingulate cortex, a key region in the default mode network, which appears to be strongly associated with functional changes relevant to AD risk. Here, we demonstrate alterations in the pathways underlying glucose, ketone, and mitochondrial energy metabolism. Young adult APOE4 carriers displayed upregulation of specific glucose (GLUT1 & GLUT3) and monocarboxylate (MCT2) transporters, the glucose metabolism enzyme hexokinase, the SCOT & AACS enzymes involved in ketone metabolism, and complexes I, II, and IV of the mitochondrial electron transport chain. The monocarboxylate transporter (MCT4) was found to be downregulated in APOE4 carriers. These data suggest that widespread dysregulation of energy metabolism in this at-risk population, even decades before possible disease onset. Therefore, these findings support the idea that alterations in brain energy metabolism may contribute significantly to the risk that APOE4 confers for AD.

Alzheimer's Disease Risk Genes and Lipid Regulators. - El Gaamouch, Farida; Jing, Ping; Xia, Jiahong; Cai, Dongming (J Alzheimers Dis, 2016)
Brain lipid homeostasis plays an important role in Alzheimer's disease (AD) and other neurodegenerative disorders. Aggregation of amyloid-β peptide is one of the major events in AD. The complex interplay between lipids and amyloid-β accumulation has been intensively investigated. The proportions of lipid components including phospholipids, sphingolipids, and cholesterol are roughly similar across different brain regions under physiological conditions. However, disruption of brain lipid homeostasis has been described in AD and implicated in disease pathogenesis. Moreover, studies suggest that analysis of lipid composition in plasma and cerebrospinal fluid could improve our understanding of the disease development and progression, which could potentially serve as disease biomarkers and prognostic indicators for AD therapies. Here, we summarize the functional roles of AD risk genes and lipid regulators that modulate brain lipid homeostasis including different lipid species, lipid complexes, and lipid transporters, particularly their effects on amyloid processing, clearance, and aggregation, as well as neuro-toxicities that contribute to AD pathogenesis.

Analysis of Cerebrospinal Fluid and [11C]PIB PET Biomarkers for Alzheimer's Disease with Updated Protocols. - Wang, Min Jeong; Yi, SangHak; Han, Jee-Young; Park, So Young; Jang, Jae-Won; Chun, In Kook; Giau, Vo Van; Bagyinszky, Eva; Lim, Kun Taek; Kang, Sung Min; An, Seong Soo A; Park, Young Ho; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recently, a Korean research group suggested a consensus protocol, based on the Alzheimer's Disease Neuroimaging Initiative study protocol but with modifications for minimizing the confounding factors, for the evaluation of cerebrospinal fluid (CSF) biomarkers. OBJECTIVE: Here, we analyzed fluid and imaging biomarkers of Alzheimer's disease (AD) in Korean population. We used the updated protocol to propose a more accurate CSF biomarker value for the diagnosis of AD. METHODS: Twenty-seven patients with AD and 30 cognitively normal controls (NC) were enrolled. CSF was collected from 55 subjects (patients with AD = 26, NC = 29) following the Korea consensus protocol. CSF biomarkers were measured using the INNO-BIA AlzBio3 immunoassay, and Pittsburgh compound B (PIB) positron emission tomography (PET) scans were also performed. RESULTS: The cutoff values of CSF amyloid beta 1-42 (Aβ42), total tau (t-Tau), and phosphorylated tau (p-Tau) proteins were 357.1 pg/ml, 83.35 pg/ml, and 38.00 pg/ml, respectively. The cutoff values of CSF t-Tau/Aβ42 and p-Tau/Aβ42 ratio- were 0.210 (sensitivity 100%, specificity 86.21%) and 0.1350 (sensitivity 88.46%, specificity of 92.86%). The concordance rate with PIB-PET was higher using the CSF t-Tau/Aβ42 ratio (κ= 0.849, CI 0.71-0.99) than CSF Aβ42 alone (κ= 0.703, CI 0.51-0.89). CONCLUSIONS: Here, we improved controversial factors associated with the previous CSF study protocol and suggested a new cutoff value for the diagnosis of AD. Our results showed good diagnostic performance for differentiation of AD. Thus, we expect our findings could be a cornerstone in the establishment and clinical application of biomarkers for AD diagnosis.

Anemia and Mild Cognitive Impairment in the German General Population. - Dlugaj, Martha; Winkler, Angela; Weimar, Christian; Dürig, Jan; Broecker-Preuss, Martina; Dragano, Nico; Moebus, Susanne; Jöckel, Karl-Heinz; Erbel, Raimund; Eisele, Lewin (J Alzheimers Dis, 2016)
There is increasing evidence that anemia is associated with cognitive impairment. Therefore, the aim of the study was to examine the cross-sectional association of anemia as well as the persistence of anemia over the last five years with mild cognitive impairment (MCI) and MCI subtypes (amnestic/non-amnestic MCI (aMCI/naMCI)). Out of 4,157 participants (50% men, 50-80 years) of the second examination (t1) of a cohort study (baseline (t0) 2000-2003), we included 4,033 participants with available hemoglobin information and complete cognitive assessment. Anemia was defined as hemoglobin <13 g/dl in men (n = 84) and <12 g/dl in women (n = 79). Group comparisons were used to compare the cognitive subtests. To determine the association of MCI with anemia at t1, with anemia five years prior to the cognitive assessment (t0) and anemia at both time points, we used logistic regression models and included 579 participants with MCI and 1,438 cognitively normal participants out of the total cohort. Anemic participants showed lower performances in verbal memory and executive functions. The fully adjusted odds ratios (OR) for MCI, aMCI, and naMCI in anemic versus non-anemic participants were 1.92 (95% -CI, 1.09-3.39), 1.96 (1.00-3.87), and 1.88 (0.91-3.87). Anemia at both times points showed a non-significant association with naMCI (OR 3.74, 0.94-14.81, fully adjusted). Our results suggest that anemia is associated with an increased risk of MCI independent of traditional cardiovascular risk factors. The association of anemia and MCI has important clinical relevance, because many causes of anemia can be treated effectively.
Keywords: Aged; Aged, 80 and over; Anemia; Cognitive Dysfunction; Cohort Studies; Executive Function; Female; Follow-Up Studies; Germany; Humans; Male; Memory; Middle Aged; Neuropsychological Tests; Prevalence; Speech Perception

Antioxidative and Neuroprotective Effects of Curcumin in an Alzheimer's Disease Rat Model Co-Treated with Intracerebroventricular Streptozotocin and Subcutaneous D-Galactose. - Huang, Han-Chang; Zheng, Bo-Wen; Guo, Yu; Zhao, Jian; Zhao, Jiang-Yan; Ma, Xiao-Wei; Jiang, Zhao-Feng (J Alzheimers Dis, 2016)
Epidemiological data imply links between the increasing incidences of Alzheimer's disease (AD) and type 2 diabetes mellitus. In this study, an AD rat model was established by combining treatments with intracerebroventricular streptozotocin (icv-STZ) and subcutaneous D-galactose, and the effects of curcumin on depressing AD-like symptoms were investigated. In the AD model group, rats were treated with icv-STZ in each hippocampus with 3.0 mg/kg of bodyweight once and then were subcutaneously injected with D-galactose daily (125 mg/kg of bodyweight) for 7 weeks. In the curcumin-protective group, after icv-STZ treatment, rats were treated with D-galactose (the same as in the AD model group) and intraperitoneally injected with curcumin daily (10 mg/kg of bodyweight) for 7 weeks. Vehicle-treated rats were treated as control. Compared with the vehicle control, the amount of protein carbonylation and glutathione in liver, as well as malondialdehyde in serum, were upregulated but glutathione peroxidase activity in blood was downregulated in the AD model group. The shuttle index and locomotor activity of rats in the AD model group were decreased compared with the vehicle control group. Furthermore, AD model rats showed neuronal damage and neuron loss with formation of amyloid-like substances and neurofibrillary tangles, and the levels of both β-cleavage of AβPP and phosphorylation of tau (Ser396) were significantly increased compared with the vehicle control group. Notably, compared with the AD model group, oxidative stress was decreased and the abilities of active avoidance and locomotor activity were improved, as well as attenuated neurodegeneration, in the curcumin-protective group. These results imply the applications of this animal model for AD research and of curcumin in the treatment of AD.

The Anti-Prion Antibody 15B3 Detects Toxic Amyloid-β Oligomers. - Stravalaci, Matteo; Tapella, Laura; Beeg, Marten; Rossi, Alessandro; Joshi, Pooja; Pizzi, Erika; Mazzanti, Michele; Balducci, Claudia; Forloni, Gianluigi; Biasini, Emiliano; Salmona, Mario; Diomede, Luisa; et al. (J Alzheimers Dis, 2016)
15B3 is a monoclonal IgM antibody that selectively detects pathological aggregates of the prion protein (PrP). We report the unexpected finding that 15B3 also recognizes oligomeric but not monomeric forms of amyloid-β (Aβ)42, an aggregating peptide implicated in the pathogenesis of Alzheimer's disease (AD). The 15B3 antibody: i) inhibits the binding of synthetic Aβ42 oligomers to recombinant PrP and neuronal membranes; ii) prevents oligomer-induced membrane depolarization; iii) antagonizes the inhibitory effects of oligomers on the physiological pharyngeal contractions of the nematode Caenorhabditis elegans; and iv) counteracts the memory deficits induced by intracerebroventricular injection of Aβ42 oligomers in mice. Thus this antibody binds to pathologically relevant forms of Aβ, and offers a potential research, diagnostic, and therapeutic tool for AD.

Application of the IWG-2 Diagnostic Criteria for Alzheimer's Disease to the ADNI. - Wang, Hui-Fu; Tan, Lan; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Liu, Ying; Wang, Chong; Tsai, Richard M; Jia, Jian-Ping; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: The International Working Group (IWG) recently proposed the revised diagnostic criteria for Alzheimer's disease (AD) to define and refine several types of AD, and to reclassify AD-related biomarkers into diagnostic and progression markers, but its performance is not known. OBJECTIVE: This study was designed to describe the application of the revised IWG criteria in the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset, and to ascertain whether diagnostic and progression markers show significant differences in their relationships to AD severity and progression. METHODS: Based on the requirements of the refined criteria, 857 ADNI subjects with memory evaluation and at least one pathophysiological marker (CSF or amyloid imaging biomarkers) were eligible and reclassified in this study, and we calculated the associations of diagnostic (CSF and amyloid PET) and progression markers (MRI and fluorodeoxyglucose-PET) with AD severity and progression respectively. RESULTS: The majority (84.2% ) of ADNI AD group (n = 117) and 173 MCI (37.4% ) subjects in ADNI met the definition of typical AD; and 105 cognitively normal (41.0% ) individuals were diagnosed as asymptomatic AD. Furthermore, diagnostic and progression markers showed significant differences when correlated to AD severity and progression. CONCLUSION: A large proportion of AD dementia subjects were categorized as typical AD, and the revised criteria could identify typical AD from MCI status as well as asymptomatic AD at the asymptomatic stage. Moreover, the significant differences between diagnostic and progression markers further supported the new biomarkers categorization in the refined criteria.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Cognitive Dysfunction; Databases, Factual; Disease Progression; Female; Humans; Longitudinal Studies; Male; Multicenter Studies as Topic; Neuroimaging; Psychiatric Status Rating Scales; tau Proteins

Aquaporin-4 and Alzheimer's Disease. - Yang, Canhong; Huang, Xiaomin; Huang, Xiaoyu; Mai, Hantao; Li, Jie; Jiang, Tao; Wang, Xiaofeng; Lü, Tianming (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most common form of dementia. Although the pathogenesis of AD remains unclear, AD is thought to result from an imbalance in the production and clearance of amyloid-β protein (Aβ). Aquaporin-4 (AQP4) is the major aquaporin in the mammalian brain, is mostly expressed on astrocytic endfeet, and functions as a water transporter. However, the distribution and expression of AQP4 are altered in both AD clinical populations and animal models. Recent studies have revealed that AQP4 is important to the clearance of Aβ in brain via lymphatic clearance, transcytotic delivery, and glial degradation, as well as to the synaptic function. Thus, AQP4 likely plays an important role in the pathogenesis of AD. Further studies would provide new targets for prevention, ultimately leading to improved treatment options for AD.

Assessment and Reporting of Driving Fitness in Patients with Dementia in Clinical Practice: Data from SveDem, the Swedish Dementia Registry. - Lovas, Joel; Fereshtehnejad, Seyed-Mohammad; Cermakova, Pavla; Lundberg, Catarina; Johansson, Björn; Johansson, Kurt; Winblad, Bengt; Eriksdotter, Maria; Religa, Dorota (J Alzheimers Dis, 2016)
BACKGROUND: Driving constitutes a very important aspect of daily life and is dependent on cognitive functions such as attention, visuo-spatial skills and memory, which are often compromised in dementia. Therefore, the driving fitness of patients with dementia needs to be addressed by physicians and those that are deemed unfit should not be allowed to continue driving. OBJECTIVE: We aimed at investigating to what extent physicians assess driving fitness in dementia patients and determinant factors for revoking of their licenses. METHODS: This study includes 15113 patients with newly diagnosed dementia and driver's license registered in the Swedish Dementia Registry (SveDem). The main outcomes were reporting to the licensing authority and making an agreement about driving eligibility with the patients. RESULTS: Physicians had not taken any action in 16% of dementia patients, whereas 9% were reported to the authority to have their licenses revoked. Males (OR = 3.04), those with an MMSE score between 20-24 (OR = 1.35) and 10-19 (OR = 1.50), patients with frontotemporal (OR = 3.09) and vascular dementia (OR = 1.26) were more likely to be reported to the authority. CONCLUSION: For the majority of patients with dementia, driving fitness was assessed. Nevertheless, physicians did not address the issue in a sizeable proportion of dementia patients. Type of dementia, cognitive status, age, sex and burden of comorbidities are independent factors associated with the assessment of driving fitness in patients with dementia. Increased knowledge on how these factors relate to road safety may pave the way for more specific guidelines addressing the issue of driving in patients with dementia.

Association of Platelet Serotonin Levels in Alzheimer's Disease with Clinical and Cerebrospinal Fluid Markers. - Tajeddinn, Walid; Fereshtehnejad, Seyed-Mohammad; Seed Ahmed, Mohammed; Yoshitake, Takashi; Kehr, Jan; Shahnaz, Tasmin; Milovanovic, Micha; Behbahani, Homira; Höglund, Kina; Winblad, Bengt; Cedazo-Minguez, Angel; Jelic, Vesna; et al. (J Alzheimers Dis, 2016)
INTRODUCTION: Serotonin (5-HT) is involved in the pathology of Alzheimer's disease (AD). OBJECTIVE: We aimed to measure 5-HT level in platelets in AD and explore its association with cerebrospinal fluid (CSF), AD biomarkers (amyloid-β 1-42 (Aβ42), total tau (t-tau), and phosphorylated tau (p-tau)), and clinical symptoms. METHODS: 15 patients with AD and 20 patients with subjective cognitive impairment (SCI) were included. 5-HT metabolites were measured, in a specific fraction, using high performance liquid chromatography with electrochemical detection (HPLC-ECD). RESULTS: Significantly lower 5-HT concentrations were observed in AD patients compared to SCI patients both after normalization against total protein (p = 0.008) or platelet count (p = 0.019). SCI patients with lower 5-HT level have higher AD CSF biomarkers, total tau (p = 0.026) and tau/Aβ42 ratio (p = 0.001), compared to those with high 5-HT levels. CONCLUSION: AD patients have reduced platelet 5-HT levels. In SCI, lower 5-HT content was associated with a higher AD-CSF biomarker burden.

Association of Serum Vitamin D with the Risk of Incident Dementia and Subclinical Indices of Brain Aging: The Framingham Heart Study. - Karakis, Ioannis; Pase, Matthew P; Beiser, Alexa; Booth, Sarah L; Jacques, Paul F; Rogers, Gail; DeCarli, Charles; Vasan, Ramachandran S; Wang, Thomas J; Himali, Jayandra J; Annweiler, Cedric; Seshadri, Sudha (J Alzheimers Dis, 2016)
BACKGROUND: Identifying nutrition- and lifestyle-based risk factors for cognitive impairment and dementia may aid future primary prevention efforts. OBJECTIVE: We aimed to examine the association of serum vitamin D levels with incident all-cause dementia, clinically characterized Alzheimer's disease (AD), MRI markers of brain aging, and neuropsychological function. METHODS: Framingham Heart Study participants had baseline serum 25-hydroxyvitamin D (25(OH)D) concentrations measured between 1986 and 2001. Vitamin D status was considered both as a continuous variable and dichotomized as deficient (<10 ng/mL), or at the cohort-specific 20th and 80th percentiles. Vitamin D was related to the 9-year risk of incident dementia (n = 1663), multiple neuropsychological tests (n = 1291) and MRI markers of brain volume, white matter hyperintensities and silent cerebral infarcts (n = 1139). RESULTS: In adjusted models, participants with vitamin D deficiency (n = 104, 8% of the cognitive sample) displayed poorer performance on Trail Making B-A (β= -0.03 to -0.05±0.02) and the Hooper Visual Organization Test (β= -0.09 to -0.12±0.05), indicating poorer executive function, processing speed, and visuo-perceptual skills. These associations remained when vitamin D was examined as a continuous variable or dichotomized at the cohort specific 20th percentile. Vitamin D deficiency was also associated with lower hippocampal volumes (β= -0.01±0.01) but not total brain volume, white matter hyperintensities, or silent brain infarcts. No association was found between vitamin D deficiency and incident all-cause dementia or clinically characterized AD. CONCLUSIONS: In this large community-based sample, low 25(OH)D concentrations were associated with smaller hippocampal volume and poorer neuropsychological function.
Keywords: Adult; Aging; Brain; Cohort Studies; Dementia; Female; Humans; Incidence; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Regression Analysis; Risk; Sensitivity and Specificity; Vitamin D

Associations between Performance on an Abbreviated CogState Battery, Other Measures of Cognitive Function, and Biomarkers in People at Risk for Alzheimer's Disease. - Racine, Annie M; Clark, Lindsay R; Berman, Sara E; Koscik, Rebecca L; Mueller, Kimberly D; Norton, Derek; Nicholas, Christopher R; Blennow, Kaj; Zetterberg, Henrik; Jedynak, Bruno; Bilgel, Murat; Carlsson, Cynthia M; et al. (J Alzheimers Dis, 2016)
It is not known whether computerized cognitive assessments, like the CogState battery, are sensitive to preclinical cognitive changes or pathology in people at risk for Alzheimer's disease(AD). In 469 late middle-aged participants from the Wisconsin Registry for Alzheimer's Prevention(mean age 63.8±7 years at testing; 67% female; 39% APOE4+), we examined relationships between a CogState abbreviated battery(CAB) of seven tests and demographic characteristics, traditional paper-based neuropsychological tests as well as a composite cognitive impairment index, cognitive impairment status(determined by consensus review), and biomarkers for amyloid and tau(CSF phosphorylated-tau/Aβ42 and global PET-PiB burden) and neural injury(CSF neurofilament light protein). CSF and PET-PiB were collected in n = 71 and n = 91 participants, respectively, approximately four years prior to CAB testing. For comparison, we examined three traditional tests of delayed memory in parallel. Similar to studies in older samples, the CAB was less influenced by demographic factors than traditional tests. CAB tests were generally correlated with most paper-based cognitive tests examined and mapped onto the same cognitive domains. Greater composite cognitive impairment index was associated with worse performance on all CAB tests. Cognitively impaired participants performed significantly worse compared to normal controls on all but one CAB test. Poorer One Card Learning test performance was associated with higher levels of CSF phosphorylated-tau/Aβ42. These results support the use of the CogState battery as measures of early cognitive impairment in studies of people at risk for AD.

AZD3293: A Novel, Orally Active BACE1 Inhibitor with High Potency and Permeability and Markedly Slow Off-Rate Kinetics. - Eketjäll, Susanna; Janson, Juliette; Kaspersson, Karin; Bogstedt, Anna; Jeppsson, Fredrik; Fälting, Johanna; Haeberlein, Samantha Budd; Kugler, Alan R; Alexander, Robert C; Cebers, Gvido (J Alzheimers Dis, 2016)
A growing body of pathological, biomarker, genetic, and mechanistic data suggests that amyloid accumulation, as a result of changes in production, processing, and/or clearance of brain amyloid-β peptide (Aβ) concentrations, plays a key role in the pathogenesis of Alzheimer's disease (AD). Beta-secretase 1 (BACE1) mediates the first step in the processing of amyloid-β protein precursor (AβPP) to Aβ peptides, with the soluble N terminal fragment of AβPP (sAβPPβ) as a direct product, and BACE1 inhibition is an attractive target for therapeutic intervention to reduce the production of Aβ. Here, we report the in vitro and in vivo pharmacological profile of AZD3293, a potent, highly permeable, orally active, blood-brain barrier (BBB) penetrating, BACE1 inhibitor with unique slow off-rate kinetics. The in vitro potency of AZD3293 was demonstrated in several cellular models, including primary cortical neurons. In vivo in mice, guinea pigs, and dogs, AZD3293 displayed significant dose- and time-dependent reductions in plasma, cerebrospinal fluid, and brain concentrations of Aβ40, Aβ42, and sAβPPβ. The in vitro potency of AZD3293 in mouse and guinea pig primary cortical neuronal cells was correlated to the in vivo potency expressed as free AZD3293 concentrations in mouse and guinea pig brains. In mice and dogs, the slow off-rate from BACE1 may have translated into a prolongation of the observed effect beyond the turnover rate of Aβ. The preclinical data strongly support the clinical development of AZD3293, and patients with AD are currently being recruited into a combined Phase 2/3 study to test the disease-modifying properties of AZD3293.
Keywords: Administration, Oral; Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Animals; Blood Chemical Analysis; Blood-Brain Barrier; Brain; Dogs; Dose-Response Relationship, Drug; Drug Evaluation, Preclinical; Enzyme Inhibitors; Female; Guinea Pigs; Humans; Imidazoles; Kinetics; Male; Mice, Inbred C57BL; Peptide Fragments; Spiro Compounds

Brain Amyloid-β Plays an Initiating Role in the Pathophysiological Process of the PS1V97L-Tg Mouse Model of Alzheimer's Disease. - Wang, Wei; Lu, Lu; Wu, Qiao-Qi; Jia, Jian-Ping (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) aggregation, tau hyperphosphorylation, oxidative stress, and neuroinflammation are major pathophysiological events in Alzheimer's disease (AD). However, the relationships among these processes and which first exerts an effect are unknown. In the present study, we investigated age-dependent behavioral changes and the sequential pathological progression from the brain to the periphery in AD transgenic (PS1V97L-Tg) mice and their wild-type littermates. We discovered that the brain Aβ significantly increased at 6 months old, the increased brain Aβ caused memory dysfunction, and the ability of Aβ to induce tau hyperphosphorylation might be due to oxidative stress and neuroinflammatory reactions. The levels of Aβ42, total tau (t-tau), oxidative stress parameters, and proinflammatory cytokines in plasma can be used to differentiate between PS1V97L-Tg mice and their wild-type littermates at different time points. Collectively, our findings support the hypothesis that Aβ is a trigger among these pathophysiological processions and show that plasma biomarkers can reflect the condition of the AD brain.

Brain Serotonergic and Noradrenergic Deficiencies in Behavioral Variant Frontotemporal Dementia Compared to Early-Onset Alzheimer's Disease. - Vermeiren, Yannick; Janssens, Jana; Aerts, Tony; Martin, Jean-Jacques; Sieben, Anne; Van Dam, Debby; De Deyn, Peter P (J Alzheimers Dis, 2016)
Routinely prescribed psychoactive drugs in behavioral variant frontotemporal dementia (FTD) for improvement of (non)cognitive symptoms are primarily based on monoamine replacement or augmentation strategies. These were, however, initially intended to symptomatically treat other degenerative, behavioral, or personality disorders, and thus lack disease specificity. Moreover, current knowledge on brain monoaminergic neurotransmitter deficiencies in this presenile disorder is scarce, particularly with reference to changes in Alzheimer's disease (AD). The latter hence favors neurochemical comparison studies in order to elucidate the monoaminergic underpinnings of FTD compared to early-onset AD, which may contribute to better pharmacotherapy. Therefore, frozen brain samples, i.e., Brodmann area (BA) 6/8/9/10/11/12/22/24/46, amygdala, and hippocampus, of 10 neuropathologically confirmed FTD, AD, and control subjects were analyzed by means of reversed-phase high-performance liquid chromatography. Levels of serotonergic, dopaminergic, and noradrenergic compounds were measured. In nine brain areas, serotonin (5-HT) concentrations were significantly increased in FTD compared to AD patients, while 5-hydroxyindoleacetic acid/5-HT ratios were decreased in eight regions, also compared to controls. Furthermore, in all regions, noradrenaline (NA) levels were significantly higher, and 3-methoxy-4-hydroxyphenylglycol/NA ratios were significantly lower in FTD than in AD and controls. Contrarily, significantly higher dopamine (DA) levels and reduced homovanillic acid/DA ratios were only found in BA12 and BA46. Results indicate that FTD is defined by distinct serotonergic and noradrenergic deficiencies. Additional research regarding the interactions between both monoaminergic networks is required. Similarly, clinical trials investigating the effects of 5-HT1A receptor antagonists or NA-modulating agents, such as α1/2/β1-blockers, seem to have a rationale and should be considered.

Bridging Integrator 1 (BIN1) Genotypes Mediate Alzheimer's Disease Risk by Altering Neuronal Degeneration. - Wang, Hui-Fu; Wan, Yu; Hao, Xiao-Ke; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Tan, Lin; Zhang, Dao-Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: Bridging integrator 1 (BIN1) has been identified as one of the most associated loci for Alzheimer's disease (AD), and recently was reported to modulate tau pathology to mediate AD in vitro. However, the effects of BIN1 on the AD related biomarkers in AD continuum were not specifically assessed. OBJECTIVE: We explored the effects of BIN1 loci on AD specific biomarkers (CSF proteins, brain structures, glucose and amyloid-β (Aβ) metabolisms) to investigate the role BIN1 in AD pathogenesis. METHODS: We calculated the associations of BIN1 loci with these markers at baseline and follow-up in multiple linear models in 812 ADNI subjects. RESULTS: BIN1 loci were significantly associated with the levels of T-tau (rs744373: pc = 0.047, rs13031703: pc = 0.042) and P-tau (rs744373: pc = 0.044, rs13031703: pc = 0.019), but not with Aβ in CSF test. BIN1 genotypes were strongly related to atrophy of hippocampus (rs7561528: pc = 0.011), CA1 (rs1469980: pc = 0.029) and parahippocampus (rs72838284, pc = 0.017) on MRI, and to glucose metabolism on FDG-PET, but not to Aβ deposition on AV45-PET imaging. Furthermore, haplotype and subgroup analysis confirmed these significant findings. In addition, the loci associated with these markers were also identified to influence the risk for AD in the meta-analysis of 74 046 European individuals. CONCLUSION: This study supported that BIN1 contributes to the risk of AD by altering neural degeneration (abnormal tau, brain atrophy and glucose metabolism) but not Aβ pathology.
Keywords: Adaptor Proteins, Signal Transducing; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Databases, Factual; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Predisposition to Disease; Glucose; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Degeneration; Nuclear Proteins; Polymorphism, Single Nucleotide; Positron-Emission Tomography; Risk; tau Proteins; Tumor Suppressor Proteins

Cerebrospinal Fluid Markers of Alzheimer's Disease Pathology and Microglial Activation are Associated with Altered White Matter Microstructure in Asymptomatic Adults at Risk for Alzheimer's Disease. - Melah, Kelsey E; Lu, Sharon Yuan-Fu; Hoscheidt, Siobhan M; Alexander, Andrew L; Adluru, Nagesh; Destiche, Daniel J; Carlsson, Cynthia M; Zetterberg, Henrik; Blennow, Kaj; Okonkwo, Ozioma C; Gleason, Carey E; Dowling, N Maritza; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The immune response in Alzheimer's disease (AD) involves activation of microglia which may remove amyloid-β (Aβ). However, overproduction of inflammatory compounds may exacerbate neural damage in AD. AD pathology accumulates years before diagnosis, yet the extent to which neuroinflammation is involved in the earliest disease stages is unknown. OBJECTIVE: To determine whether neuroinflammation exacerbates neural damage in preclinical AD. METHODS: We utilized cerebrospinal fluid (CSF) and magnetic resonance imaging collected in 192 asymptomatic late-middle-aged adults (mean age = 60.98 years). Neuroinflammatory markers chitinase-3-like protein 1 (YKL-40) and monocyte chemoattractant protein-1 (MCP-1) in CSF were utilized as markers of neuroinflammation. Neural cell damage was assessed using CSF neurofilament light chain protein (NFL), CSF total tau (T-Tau), and neural microstructure assessed with diffusion tensor imaging (DTI). With regard to AD pathology, CSF Aβ42 and tau phosphorylated at threonine 181 (P-Tau181) were used as markers of amyloid and tau pathology, respectively. We hypothesized that higher YKL-40 and MCP-1 in the presence of AD pathology would be associated with higher NFL, T-Tau, and altered microstructure on DTI. RESULTS: Neuroinflammation was associated with markers of neural damage. Higher CSF YKL-40 was associated with both higher CSF NFL and T-Tau. Inflammation interacted with AD pathology, such that greater MCP-1 and lower Aβ42 was associated with altered microstructure in bilateral frontal and right temporal lobe and that greater MCP-1 and greater P-Tau181 was associated with altered microstructure in precuneus. CONCLUSION: Inflammation may play a role in neural damage in preclinical AD.
Keywords: Adipokines; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Chemokine CCL2; Chitinase-3-Like Protein 1; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Lectins; Male; Microglia; Middle Aged; Peptide Fragments; tau Proteins; White Matter

The Cerebrospinal Fluid Neurogranin/BACE1 Ratio is a Potential Correlate of Cognitive Decline in Alzheimer's Disease. - De Vos, Ann; Struyfs, Hanne; Jacobs, Dirk; Fransen, Erik; Klewansky, Tom; De Roeck, Ellen; Robberecht, Caroline; Van Broeckhoven, Christine; Duyckaerts, Charles; Engelborghs, Sebastiaan; Vanmechelen, Eugeen (J Alzheimers Dis, 2016)
BACKGROUND: In diagnosing Alzheimer's disease (AD), ratios of cerebrospinal fluid (CSF) biomarkers, such as CSF Aβ1-42/tau, have an improved diagnostic performance compared to the single analytes, yet, still a limited value to predict cognitive decline. Since synaptic dysfunction/loss is closely linked to cognitive impairment, synaptic proteins are investigated as candidate CSF AD progression markers. OBJECTIVE: We studied CSF levels of the postsynaptic protein neurogranin and protein BACE1, predominantly localized presynaptically, and their relation to CSF total-tau, Aβ1-42, Aβ1-40, and Aβ1-38. All six analytes were considered as single parameters as well as ratios. METHODS: Every ELISA involved was based on monoclonal antibodies, including the BACE1 and neurogranin immunoassay. The latter specifically targets neurogranin C-terminally truncated at P75, a more abundant species of the protein in CSF. We studied patients with MCI due to AD (n = 38) and 50 dementia due to AD patients, as well as age-matched cognitively healthy elderly (n = 20). A significant subset of the patients was followed up by clinical and neuropsychological (MMSE) examinations for at least one year. RESULTS: The single analytes showed statistically significant differences between the clinical groups, but the ratios of analytes indeed had a higher diagnostic performance. Furthermore, only the ratio of CSF neurogranin trunc P75/BACE1 was significantly correlated with the yearly decline in MMSE scores in patients with MCI and dementia due to AD, pointing toward the prognostic value of the ratio. CONCLUSION: This is the first study demonstrating that the CSF neurogranin trunc P75/BACE1 ratio, reflecting postsynaptic/presynaptic integrity, is related to cognitive decline.

Characterizing White Matter Tract Degeneration in Syndromic Variants of Alzheimer's Disease: A Diffusion Tensor Imaging Study. - Madhavan, Ajay; Schwarz, Christopher G; Duffy, Joseph R; Strand, Edythe A; Machulda, Mary M; Drubach, Daniel A; Kantarci, Kejal; Przybelski, Scott A; Reid, Robert I; Senjem, Matthew L; Gunter, Jeffrey L; Apostolova, Liana G; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Different clinical syndromes can arise from Alzheimer's disease (AD) neuropathology, including dementia of the Alzheimer's type (DAT), logopenic primary progressive aphasia (lvPPA), and posterior cortical atrophy (PCA). OBJECTIVE: To assess similarities and differences in patterns of white matter tract degeneration across these syndromic variants of AD. METHODS: Sixty-four subjects (22 DAT, 24 lvPPA, and 18 PCA) that had diffusion tensor imaging and showed amyloid-β deposition on PET were assessed in this case-control study. A whole-brain voxel-based analysis was performed to assess differences in fractional anisotropy, mean diffusivity, axial diffusivity, and radial diffusivity across groups. RESULTS: All three groups showed overlapping diffusion abnormalities in a network of tracts, including fornix, corpus callosum, posterior thalamic radiations, superior longitudinal fasciculus, inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, and uncinate fasciculus. Subtle regional differences were also observed across groups, with DAT particularly associated with degeneration of fornix and cingulum, lvPPA with left inferior fronto-occipital fasciculus and uncinate fasciculus, and PCA with posterior thalamic radiations, superior longitudinal fasciculus, posterior cingulate, and splenium of the corpus callosum. CONCLUSION: These findings show that while each AD phenotype is associated with degeneration of a specific structural network of white matter tracts, striking spatial overlap exists among the three network patterns that may be related to AD pathology.
Keywords: Aged; Alzheimer Disease; Aniline Compounds; Anisotropy; Aphasia, Primary Progressive; Case-Control Studies; Diffusion Tensor Imaging; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Nerve Fibers, Myelinated; Neurodegenerative Diseases; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; Retrospective Studies; Thiazoles; White Matter

Clinical and Demographic Factors Associated with the Cognitive and Emotional Efficacy of Regular Musical Activities in Dementia. - Särkämö, Teppo; Laitinen, Sari; Numminen, Ava; Kurki, Merja; Johnson, Julene K; Rantanen, Pekka (J Alzheimers Dis, 2016)
Recent evidence suggests that music-based interventions can be beneficial in maintaining cognitive, emotional, and social functioning in persons with dementia (PWDs). Our aim was to determine how clinical, demographic, and musical background factors influence the cognitive and emotional efficacy of caregiver-implemented musical activities in PWDs. In a randomized controlled trial, 89 PWD-caregiver dyads received a 10-week music coaching intervention involving either singing or music listening or standard care. Extensive neuropsychological testing and mood and quality of life (QoL) measures were performed before and after the intervention (n = 84) and six months later (n = 74). The potential effects of six key background variables (dementia etiology and severity, age, care situation, singing/instrument playing background) on the outcome of the intervention were assessed. Singing was beneficial especially in improving working memory in PWDs with mild dementia and in maintaining executive function and orientation in younger PWDs. Music listening was beneficial in supporting general cognition, working memory, and QoL especially in PWDs with moderate dementia not caused by Alzheimer's disease (AD) who were in institutional care. Both music interventions alleviated depression especially in PWDs with mild dementia and AD. The musical background of the PWD did not influence the efficacy of the music interventions. Our findings suggest that clinical and demographic factors can influence the cognitive and emotional efficacy of caregiver-implemented musical activities and are, therefore, recommended to take into account when applying and developing the intervention to achieve the greatest benefit.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Caregivers; Case-Control Studies; Cognition Disorders; Dementia; Executive Function; Female; Follow-Up Studies; Humans; Male; Memory, Short-Term; Middle Aged; Mood Disorders; Music Therapy; Neuropsychological Tests; Orientation; Outcome Assessment (Health Care); Psychiatric Status Rating Scales; Quality of Life

Connected Language in Late Middle-Aged Adults at Risk for Alzheimer's Disease. - Mueller, Kimberly Diggle; Koscik, Rebecca L; Turkstra, Lyn S; Riedeman, Sarah K; LaRue, Asenath; Clark, Lindsay R; Hermann, Bruce; Sager, Mark A; Johnson, Sterling C (J Alzheimers Dis, 2016)
Connected language is often impaired among people with Alzheimer's disease (AD), yet little is known about when language difficulties first emerge on the path to a clinical diagnosis. The objective of this study was to determine whether individuals with psychometric (preclinical) evidence of amnestic mild cognitive impairment (pMCI) showed deficits in connected language measures. Participants were 39 pMCI and 39 cognitively healthy (CH) adults drawn from the Wisconsin Registry for Alzheimer's Prevention, who were matched for age, literacy, and sex. Participants completed a connected language task in which they described the Cookie Theft picture from the Boston Diagnostic Aphasia Examination. Language samples were analyzed across three language domains: content, syntactic complexity, and speech fluency. Paired t-tests were used to compare CH and pMCI groups on all variables, and Cohen's d effect sizes were calculated for each comparison. The CH and pMCI groups differed significantly on measures of content (e.g., CH group produced more semantic units, more unique words and had larger idea density, on average, than the pMCI group). The picture description findings are consistent with previous retrospective studies showing semantic language differences in adults with autopsy-confirmed AD. Given that these comparisons are between cognitively healthy and pMCI individuals (before a clinical MCI diagnosis), these findings may represent subtle language difficulty in spontaneous speech, and may be predictive of larger language changes over time.

Decreased Inter-Hemispheric Functional Connectivity in Cognitively Intact Elderly APOE ɛ4 Carriers: A Preliminary Study. - Luo, Xiao; Qiu, Tiantian; Xu, Xiaojun; Huang, Peiyu; Gu, Quanquan; Shen, Zhujing; Yu, Xinfeng; Jia, YunLu; Guan, Xiaojun; Song, Ruirui; Zhang, Minming (J Alzheimers Dis, 2016)
The apolipoprotein E (APOE) ɛ4 allele is the best-known genetic risk factor for developing sporadic Alzheimer's disease (AD). According to neuroimaging studies, the APOE ɛ4 allele is associated with localized altered brain function. However, in long-range circuitry, APOE ɛ4 allele-related alterations in functional communication between hemispheres have rarely been directly investigated. We examined the alteration of resting-state functional connectivity (RSFC) between inter-hemispheric homotopic regions in cognitively intact, elderly APOE ɛ4 carriers. The voxel-mirrored homotopic connectivity method was used to assess the inter-hemispheric RSFC. The current study included 13 cognitively intact, elderly APOE ɛ4 carriers (with at least one copy of APOE ɛ4 allele) and 22 well-matched ɛ3 homozygotes. Comparisons between the two groups were conducted, and subsequently, the correlation between the differential inter-hemispheric RSFC and cognitive ability was analyzed. Compared with ɛ3 homozygotes, APOE ɛ4 carriers showed decreased inter-hemispheric RSFC in the bilateral medial temporal lobe (MTL) and orbital frontal cortex (OFC). Moreover, in APOE ɛ4 carriers, the inter-hemispheric RSFC of the MTL correlated with the Wechsler Memory Scale-Logical Memory (WMS-LM) (immediate and delayed performance, r = 0.64, p <  0.05; r = 0.65, p <  0.05, respectively), and the inter-hemispheric RSFC of the OFC correlated with the WMS-LM delayed performance (r = 0.71, p <  0.05). In our study, the presence of the APOE ɛ4 allele was linked with decreased inter-hemispheric RSFC, which was attributed to memory performance in carriers.
Keywords: Aged; Aging; Apolipoprotein E4; Brain; Brain Mapping; Female; Functional Laterality; Genotyping Techniques; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Memory; Neuropsychological Tests; Rest

Decreased Levels of VAMP2 and Monomeric Alpha-Synuclein Correlate with Duration of Dementia. - Vallortigara, Julie; Whitfield, David; Quelch, William; Alghamdi, Amani; Howlett, David; Hortobágyi, Tibor; Johnson, Mary; Attems, Johannes; O'Brien, John T; Thomas, Alan; Ballard, Clive G; Aarsland, Dag; et al. (J Alzheimers Dis, 2016)
Alpha-synuclein (α-syn) aggregations are the key pathological hallmark of dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD), but are also frequently present in Alzheimer's disease (AD). Much remains unknown about the role of α-syn in the synapse and the wider role of synaptic dysfunction in these dementias. Changes in concentrations of key 'SNAP (Soluble N-ethylmaleimide Sensitive Factor Attachment Protein) Receptor' (SNARE) proteins as a consequence of alterations in the aggregation state of α-syn may contribute to synaptic dysfunction in patients with DLB, PDD, and AD and result in impaired cognition. We have studied a large cohort (n = 130) of autopsy confirmed DLB, PDD, AD, and control brains. Using semi-quantitative western blotting, we have demonstrated significant changes across the diagnostic groups of DLB, PDD, and AD in the SNARE and vesicle proteins syntaxin, Munc18, VAMP2, and monomeric α-syn in the prefrontal cortex, with a significant reduction of Munc18 in AD patients (p <  0.001). This correlated to the final MMSE score before death (p = 0.016). We also identified a significant negative correlation between the duration of dementia and the levels of the binding partners VAMP2 (p = 0.0004) and monomeric α-syn (p = 0.0002). Our findings may indicate that an upregulation of SNARE complex related proteins occurs in the early stages of disease as an attempt at compensating for failing synapses, prior to widespread deposition of pathological α-syn.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Amyloid beta-Peptides; Analysis of Variance; Cognition Disorders; Dementia; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Regression Analysis; Synaptophysin; tau Proteins; Vesicle-Associated Membrane Protein 2

Dementia Apraxia Test (DATE): A Brief Tool to Differentiate Behavioral Variant Frontotemporal Dementia from Alzheimer's Dementia Based on Apraxia Profiles. - Johnen, Andreas; Frommeyer, Jana; Modes, Fenja; Wiendl, Heinz; Duning, Thomas; Lohmann, Hubertus (J Alzheimers Dis, 2016)
BACKGROUND: Standardized praxis assessments with modern, empirically validated screening tests have substantially improved clinical evaluation of apraxia in patients with stroke. Although apraxia may contribute to early differential diagnosis of Alzheimer's dementia (AD) and behavioral variant frontotemporal dementia (bvFTD), no comparable test is readily available to clinicians for this purpose to date. OBJECTIVE: To design a clinically useful apraxia test for the differentiation of AD and bvFTD. METHODS: 84 test items pertaining to twelve praxis subdomains were evaluated for their efficacy to discriminate between patients with bvFTD (n = 24), AD (n = 28), and elderly healthy controls (HC; n = 35). Items were then selected based on discriminative value and psychometric properties. RESULTS: Items indicative of mild AD comprised spatially complex imitation of hand and finger postures and to a lesser degree, pantomime of common object-use. Buccofacial apraxia including imitation of face postures, emblematic face postures, and repetition of multisyllabic pseudowords differentiated bvFTD from HC and AD. The final test version consisting of 20 items proved highly efficient for the discrimination of biologically confirmed dementia patients from HC (sensitivity 91% , specificity 71%) but also for differential diagnosis of bvFTD and AD (sensitivity 74% , specificity 93%). CONCLUSIONS: Assessment of praxis profiles effectively contributes to diagnosis and differential diagnosis of AD and bvFTD. The Dementia Apraxia Test (DATE) is a brief and easy to administer cognitive tool for dementia assessment, has a high inter-rater reliability (Cohen's κ= 0.885) and demonstrates content validity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Apraxias; Diagnosis, Differential; Female; Frontotemporal Dementia; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reference Values

A Depressive Endophenotype for Predicting Cognitive Decline among Mexican American Adults and Elders. - Johnson, Leigh A; Gamboa, Adriana; Vintimilla, Raul; Edwards, Melissa; Hall, James; Weiser, Brent; Yadav, Menaka; Dickensheets, Tony; O'Bryant, Sid E (J Alzheimers Dis, 2016)
BACKGROUND: Late life depression is a prodromal feature and a risk factor for Alzheimer's disease (AD) and mild cognitive impairment (MCI). We identified five items in the Geriatric Depression scale (DepE) that are important as a risk for MCI and AD: memory problems, feeling blue, crying, feeling worthless, and trouble concentrating. OBJECTIVE: Our goal was to examine the relationship between DepE and cognition in a cohort of Mexican Americans. METHODS: Data from 317 Mexican Americans from the HABLE study were analyzed. DepE scores were dichotomized into two groups: endorsement of 1 item or less, and endorsement of 2 or more items. Cognition was assessed via neuropsychological tests, and diagnosis was based on consensus review. We utilized linear regression to examine the association between DepE and cognitive performance, and logistic regression to examine the utility of DepE in predicting MCI. To examine the impact of DepE on memory over 12 months, we performed ANOVA analysis. RESULTS: Elevated DepE scores were associated with poorer performance on various measures of memory and cognition, but not executive or visual spatial skills. Over 12 months, we found a decline in immediate memory among women but not men. Those with high scores were 4 times more likely to have MCI. ANOVA of total scores revealed differences between groups on immediate memory (p < 0.05) in women, with no significant differences on delay recall in either gender. CONCLUSION: DepE can be utilized in Mexican Americans to identify those at risk of memory related cognitive decline.

Development and Validation of the RxDx-Dementia Risk Index to Predict Dementia in Patients with Type 2 Diabetes and Hypertension. - Mehta, Hemalkumar B; Mehta, Vinay; Tsai, Chu-Lin; Chen, Hua; Aparasu, Rajender R; Johnson, Michael L (J Alzheimers Dis, 2016)
BACKGROUND: Elderly patients with type 2 diabetes mellitus and hypertension are at high risk for developing dementia. In addition to comorbid disease conditions (Dx), prescription drugs (Rx) are important risk factors for dementia. OBJECTIVE: Develop and validate the RxDx-Dementia risk index by combining diagnosis and prescription information in a single risk index to predict incident dementia, and compare its performance with diagnosis-based Charlson comorbidity score (CCS) and prescription-based chronic disease score (CDS). METHODS: Elderly patients diagnosed with type 2 diabetes mellitus and hypertension, and without prior dementia were identified from the Clinical Practice Research Datalink (2003-2012). A Cox proportional hazard model was constructed to model the time to dementia by incorporating age, gender, and 31 RxDx disease conditions as independent variables. Points were assigned to risk factors to obtain summary risk score. Discrimination and calibration of the risk index were evaluated. Different risk indices were compared against RxDx-Dementia risk index using c-statistic, net reclassification improvement (NRI) and integrated discrimination improvement (IDI). RESULTS: Of 133,176 patients with type 2 diabetes mellitus and hypertension, 3.42% patients developed dementia.The c-statistics value for RxDx-Dementia risk index was 0.806 (95% CI, 0.799-0.812). Based on the c-statistics, NRI and IDI values, the RxDx-Dementia risk index performed better compared to CCS, CDS, and their combinations. CONCLUSION: The RxDx-Dementia risk index can be a useful tool to identify hypertensive and diabetic patients who are at high risk of developing dementia. This has implications for clinical management of patients with multiple comorbid conditions as well as risk adjustment for database studies.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Dementia; Diabetes Mellitus, Type 2; Female; Humans; Hypertension; Male; Middle Aged; Predictive Value of Tests; Prescription Drugs; Proportional Hazards Models; Reproducibility of Results; Risk Assessment; Risk Factors

Development of a Proxy-Free Objective Assessment Tool of Instrumental Activities of Daily Living in Mild Cognitive Impairment Using Smart Home Technologies. - Jekel, Katrin; Damian, Marinella; Storf, Holger; Hausner, Lucrezia; Frölich, Lutz (J Alzheimers Dis, 2016)
BACKGROUND: The assessment of activities of daily living (ADL) is essential for dementia diagnostics. Even in mild cognitive impairment (MCI), subtle deficits in instrumental ADL (IADL) may occur and signal a higher risk of conversion to dementia. Thus, sensitive and reliable ADL assessment tools are important. Smart homes equipped with sensor technology and video cameras may provide a proxy-free assessment tool for the detection of IADL deficits. OBJECTIVE: The aim of this paper is to investigate the potential of a smart home environment for the assessment of IADL in MCI. METHOD: The smart home consisted of a two-room flat equipped with activity sensors and video cameras. Participants with either MCI or healthy controls (HC) had to solve a standardized set of six tasks, e.g., meal preparation, telephone use, and finding objects in the flat. RESULTS: MCI participants needed more time (1384 versus 938 seconds, p <  0.001) and scored less total points (48 versus 57 points, p <  0.001) while solving the tasks than HC. Analyzing the subtasks, intergroup differences were observed for making a phone call, operating the television, and retrieving objects. MCI participants showed more searching and task-irrelevant behavior than HC. Task performance was correlated with cognitive status and IADL questionnaires but not with participants' age. CONCLUSION: This pilot study showed that smart home technologies offer the chance for an objective and ecologically valid assessment of IADL. It can be analyzed not only whether a task is successfully completed but also how it is completed. Future studies should concentrate on the development of automated detection of IADL deficits.

Diagnostic Value of Cerebrospinal Fluid Biomarkers (Phospho-Tau181, total-Tau, Aβ42, and Aβ40) in Prodromal Stage of Alzheimer's Disease and Dementia with Lewy Bodies. - Bousiges, Olivier; Cretin, Benjamin; Lavaux, Thomas; Philippi, Nathalie; Jung, Barbara; Hezard, Sylvie; Heitz, Camille; Demuynck, Catherine; Gabel, Aurelia; Martin-Hunyadi, Catherine; Blanc, Frédéric (J Alzheimers Dis, 2016)
BACKGROUND: Dementia with Lewy bodies (DLB) symptoms are close to those of Alzheimer's disease (AD), and the differential diagnosis is difficult especially early in the disease. Unfortunately, AD biomarkers in cerebrospinal fluid (CSF), and more particularly Aβ1 - 42, appear to be altered in dementia with Lewy bodies (DLB). However, the level of these biomarkers has never been studied in the prodromal stage of the disease. OBJECTIVE: To compare these biomarkers between DLB and AD, with a particular focus on the prodromal stage. METHODS: A total of 166 CSF samples were collected at the memory clinic of Strasbourg. They were obtained from prodromal DLB (pro-DLB), DLB dementia, prodromal AD (pro-AD), and AD dementia patients, and elderly controls. Phospho-Tau181, total-Tau, Aβ42, and Aβ40 were measured in the CSF. RESULTS: At the prodromal stage, contrary to AD patients, DLB patients' biomarker levels in the CSF were not altered. At the demented stage of DLB, Aβ42 levels were reduced as well as Aβ40 levels. Thus, the Aβ42/Aβ40 ratio remained unchanged between the prodromal and demented stages, contrary to what was observed in AD. Tau and Phospho-Tau181 levels were unaltered in DLB patients. CONCLUSIONS: We have shown that at the prodromal stage the DLB patients had no pathological profile. Consequently, CSF AD biomarkers are extremely useful for differentiating AD from DLB patients particularly at this stage when the clinical diagnosis is difficult. Thus, these results open up new perspectives on the interpretation of AD biomarkers in DLB.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lewy Body Disease; Male; Middle Aged; Peptide Fragments; Prodromal Symptoms; Psychiatric Status Rating Scales; Retrospective Studies; Statistics, Nonparametric; tau Proteins

Differential Diagnosis of Dementia with High Levels of Cerebrospinal Fluid Tau Protein. - Grangeon, Lou; Paquet, Claire; Bombois, Stephanie; Quillard-Muraine, Muriel; Martinaud, Olivier; Bourre, Bertrand; Lefaucheur, Romain; Nicolas, Gaël; Dumurgier, Julien; Gerardin, Emmanuel; Jan, Mary; Laplanche, Jean-Louis; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Total Tau concentration in cerebrospinal fluid (CSF) is widely used as a biomarker in the diagnosis of neurodegenerative process primarily in Alzheimer's disease (AD). A particularly high Tau level may indicate AD but may also be associated with Creutzfeldt-Jakob disease (CJD). In such situations little is known about the distribution of differential diagnoses. OBJECTIVE: Our study aimed to describe the different diagnoses encountered in clinical practice for patients with dementia and CSF Tau levels over 1000 pg/ml. We studied the p-Tau/Tau ratio to specify its ability to distinguish AD from CJD. METHODS: Patients (n = 202) with CSF Tau levels over 1000 pg/ml were recruited in three memory clinics in France. All diagnoses were made using the same diagnostic procedure and criteria. RESULTS: Patients were diagnosed with AD (n = 148, 73.2%), mixed dementia (n = 38, 18.8%), CJD, vascular dementia (n = 4, 2.0% for each), Lewy body dementia, and frontotemporal dementia (n = 3, 1.5% for each). Dispersion of CSF Tau levels clearly showed an overlap between all diagnoses. Using the p-Tau/Tau ratio suggestive of CJD (<0.075), all CJD patients were correctly categorized and only two AD patients were miscategorized. This ratio was highly associated with CJD compared to AD (p < 0.0001). CONCLUSION: Our study showed that in clinical practice, extremely high CSF Tau levels are mainly related to diagnosis of AD. CJD patients represent a minority. Our results support a sequential interpretation algorithm for CSF biomarkers in dementia. High CSF Tau levels should alert clinicians to check the p-Tau/Tau ratio to consider a probable diagnosis of CJD.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Creutzfeldt-Jakob Syndrome; Dementia, Vascular; Diagnosis, Differential; Female; France; Frontotemporal Dementia; Humans; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged; Phosphorylation; Retrospective Studies; Sex Factors; tau Proteins

Differential Mass Spectrometry Profiles of Tau Protein in the Cerebrospinal Fluid of Patients with Alzheimer's Disease, Progressive Supranuclear Palsy, and Dementia with Lewy Bodies. - Barthélemy, Nicolas R; Gabelle, Audrey; Hirtz, Christophe; Fenaille, François; Sergeant, Nicolas; Schraen-Maschke, Susanna; Vialaret, Jérôme; Buée, Luc; Junot, Christophe; Becher, François; Lehmann, Sylvain (J Alzheimers Dis, 2016)
Microtubule-associated Tau proteins are major actors in neurological disorders, the so-called tauopathies. In some of them, and specifically in Alzheimer's disease (AD), hyperphosphorylated forms of Tau aggregate into neurofibrillary tangles. Following and understanding the complexity of Tau's molecular profile with its multiple isoforms and post-translational modifications represent an important issue, and a major analytical challenge. Immunodetection methods are, in fact, limited by the number, specificity, sensitivity, and capturing property of the available antibodies. Mass spectrometry (MS) has recently allowed protein quantification in complex biological fluids using isotope-labeled recombinant standard for absolute quantification (PSAQ). To study Tau proteins, which are found at very low concentrations within the cerebrospinal fluid (CSF), we relied on an innovative two-step pre-fractionation strategy, which was not dependent on immuno-enrichment. We then developed a sensitive multiplex peptide detection capability using targeted high-resolution MS to quantify Tau-specific peptides covering its entire sequence. This approach was used on a clinical cohort of patients with AD, progressive supranuclear palsy (PSP), and dementia with Lewy body (DLB) and with control non-neurodegenerative disorders. We uncovered a common CSF Tau molecular profile characterized by a predominance of central core expression and 1N/3R isoform detection. While PSP and DLB tau profiles showed minimal changes, AD was characterized by a unique pattern with specific modifications of peptide distribution. Taken together these results provide important information on Tau biology for future therapeutic interventions, and improved molecular diagnosis of tauopathies.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analysis of Variance; Chromatography, Liquid; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged; Neuroimaging; Neuropsychological Tests; Peptide Fragments; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Statistics as Topic; Supranuclear Palsy, Progressive; tau Proteins

Differential Risk of Incident Alzheimer's Disease Dementia in Stable Versus Unstable Patterns of Subjective Cognitive Decline. - Wolfsgruber, Steffen; Kleineidam, Luca; Wagner, Michael; Mösch, Edelgard; Bickel, Horst; Lϋhmann, Dagmar; Ernst, Annette; Wiese, Birgitt; Steinmann, Susanne; König, Hans-Helmut; Brettschneider, Christian; Luck, Tobias; et al. (J Alzheimers Dis, 2016)
BACKGROUND: It is unknown whether longitudinal stability versus instability in subjective cognitive decline (SCD) is a modifying factor of the association between SCD and risk of incident Alzheimer's disease (AD) dementia. OBJECTIVE: We tested the modifying role of temporal stability of the SCD report on AD dementia risk in cognitively normal elderly individuals. METHODS: We analyzed data of 1,990 cognitively normal participants from the longitudinal AgeCoDe Study. We assessed SCD with/without associated worries both at baseline and first follow-up 18 months later. Participants were then classified either as (a) Controls (CO, with no SCD at both baseline and follow-up 1, n = 613), (b) inconsistent SCD (with SCD reported only at baseline or at follow-up 1, n = 637), (c) consistent SCD but without/or with inconsistent worries (n = 610) or (d) consistent SCD with worries (n = 130). We estimated incident AD dementia risk over up to 6 years for each group with Cox-Proportional Hazard Regression analyses adjusted for age, gender, education, ApoE4 status, and depression. RESULTS: Compared to CO, inconsistent SCD was not associated with increased risk of incident AD dementia. In contrast, risk was doubled in the group of consistent SCD without/ with inconsistent worries, and almost 4-fold in the group of consistent SCD with worries. These results could be replicated when using follow-up 1 to follow-up 2 response patterns for group definition. CONCLUSION: These findings suggest that longitudinal stability versus instability is an important modifying factor of the association between SCD and AD dementia risk. Worrisome SCD that is also consistently reported over time is associated with greatly increased risk of AD dementia.

Direct Evidence of Internalization of Tau by Microglia In Vitro and In Vivo. - Bolós, Marta; Llorens-Martín, María; Jurado-Arjona, Jerónimo; Hernández, Félix; Rábano, Alberto; Avila, Jesús (J Alzheimers Dis, 2016)
The microtubule-associated protein (MAP) tau plays a critical role in the pathogenesis of tauopathies. Excess tau can be released into the extracellular medium in a physiological or pathological manner to be internalized by surrounding neurons-a process that contributes to the spread of this protein throughout the brain. Such spreading may correlate with the progression of the abovementioned diseases. In addition to neurons, tau can be internalized into other cells. Here we demonstrate that microglia take up tau in vitro and in vivo. In this regard, microglia from primary cultures internalized soluble (human recombinant tau42) and insoluble (homogenates derived from human AD brain) tau in vitro. Furthermore, using stereotaxic injection of tau in mice in vivo, we show that murine microglia internalize human tau. In addition, we demonstrate, for the first time, that microglia colocalize with various forms of tau in postmortem brain tissue of patients with Alzheimer's disease and non-demented control subjects. Our data reveal a potential role of microglia in the internalization of tau that might be relevant for the design of strategies to enhance the clearance of extracellular tau in neurodegenerative diseases characterized by the accumulation of this protein.
Keywords: Alzheimer Disease; Analysis of Variance; Animals; Animals, Newborn; Calcium-Binding Proteins; Cells, Cultured; Cerebral Cortex; Glial Fibrillary Acidic Protein; Hippocampus; Humans; Mice; Mice, Inbred C57BL; Microfilament Proteins; Microglia; Phosphorylation; Protein Transport; Rats; tau Proteins; Time Factors

Discovery and Subsequent Confirmation of Novel Serum Biomarkers Diagnosing Alzheimer's Disease. - Shah, Dipti Jigar; Rohlfing, Frederick; Anand, Swati; Johnson, W Evan; Alvarez, MeiHwa Tanielle Bench; Cobell, Jesse; King, Jackson; Young, Sydney A; Kauwe, John S K; Graves, Steven W (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) remains challenging to diagnose, especially early disease. Having serum AD biomarkers would be of significant interest both in the clinical setting and in drug development efforts. OBJECTIVE: We applied a novel serum proteomic approach to interrogate the low-molecular weight proteome for serum AD biomarkers. METHODS: A discovery study used sera from 58 any-stage AD cases and 55 matched controls analyzed by capillary liquid chromatography-electrospray ionization-tandem mass spectrometry. Candidate biomarkers were statistically modeled and promising biomarkers were retested in a second, blinded confirmatory study (AD cases = 68, controls = 57). Biomarkers that replicated in the second study were modeled for the diagnosis of any-stage and very early stage AD. Further, they were chemically identified by tandem MS. RESULTS: The initial discovery study found 59 novel potential AD biomarkers. Thirteen recurred in more than one multi-marker panel. In a second, blinded, confirmatory study, these same biomarkers were retested in separate specimens. In that study, four markers validated comparing controls to patients with any-stage AD and also with very early AD. The four biomarkers with replicable ability to diagnose AD were then chemically identified. CONCLUSION: These results suggest novel serum AD diagnostic biomarkers can be found using this approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Chromatography, Liquid; Female; Humans; Male; Psychiatric Status Rating Scales; Reproducibility of Results; ROC Curve; Tandem Mass Spectrometry

Discrepancy in Expression of β-Secretase and Amyloid-β Protein Precursor in Alzheimer-Related Genes in the Rat Medial Temporal Lobe Cortex Following Transient Global Brain Ischemia. - Pluta, Ryszard; Kocki, Janusz; Ułamek-Kozioł, Marzena; Petniak, Alicja; Gil-Kulik, Paulina; Januszewski, Sławomir; Bogucki, Jacek; Jabłoński, Mirosław; Brzozowska, Judyta; Furmaga-Jabłońska, Wanda; Bogucka-Kocka, Anna; Czuczwar, Stanisław J (J Alzheimers Dis, 2016)
Brain ischemia may be causally related with Alzheimer's disease. Presumably, β-secretase and amyloid-β protein precursor gene expression changes may be associated with Alzheimer's disease neuropathology. Consequently, we have examined quantitative changes in both β-secretase and amyloid-β protein precursor genes in the medial temporal lobe cortex with the use of quantitative rtPCR analysis following 10-min global brain ischemia in rats with survival of 2, 7, and 30 days. The greatest significant overexpression of β-secretase gene was noted on the 2nd day, while on days 7-30 the expression of this gene was only modestly downregulated. Amyloid-β protein precursor gene was downregulated on the 2nd day, but on days 7-30 postischemia, there was a significant reverse tendency. Thus, the demonstrated alterations indicate that the considerable changes of expression of β-secretase and amyloid-β protein precursor genes may be connected with a response of neurons in medial temporal lobe cortex to transient global brain ischemia. Finally, the ischemia-induced gene changes may play a key role in a late and slow onset of Alzheimer-type pathology.
Keywords: Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Brain Ischemia; Disease Models, Animal; Down-Regulation; Female; Rats; Rats, Wistar; Temporal Lobe; Time Factors

Distinctive Resting State Network Disruptions Among Alzheimer's Disease, Subcortical Vascular Dementia, and Mixed Dementia Patients. - Kim, Hee Jin; Cha, Jungho; Lee, Jong-Min; Shin, Ji Soo; Jung, Na-Yeon; Kim, Yeo Jin; Choe, Yearn Seong; Lee, Kyung Han; Kim, Sung Tae; Kim, Jae Seung; Lee, Jae Hong; Na, Duk L; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent advances in resting-state functional MRI have revealed altered functional networks in Alzheimer's disease (AD), especially those of the default mode network (DMN) and central executive network (CEN). However, few studies have evaluated whether small vessel disease (SVD) or combined amyloid and SVD burdens affect the DMN or CEN. OBJECTIVE: The aim of this study was to evaluate whether SVD or combined amyloid and SVD burdens affect the DMN or CEN. METHODS: In this cross-sectional study, we investigated the resting-state functional connectivity within DMN and CEN in 37 Pittsburgh compound-B (PiB)(+) AD, 37 PiB(-) subcortical vascular dementia (SVaD), 13 mixed dementia patients, and 65 normal controls. RESULTS: When the resting-state DMN of PiB(+) AD and PiB(-) SVaD patients were compared, the PiB(+) AD patients displayed lower functional connectivity in the inferior parietal lobule while the PiB(-) SVaD patients displayed lower functional connectivity in the medial frontal and superior frontal gyri. Compared to the PiB(-) SVaD or PiB(+) AD, the mixed dementia patients displayed lower functional connectivity within the DMN in the posterior cingulate gyrus. When the resting-state CEN connectivity of PiB(+) AD and PiB(-) SVaD patients were compared, the PiB(-) SVaD patients displayed lower functional connectivity in the anterior insular region. Compared to the PiB(-) SVaD or PiB(+) AD, the mixed dementia patients displayed lower functional connectivity within the CEN in the inferior frontal gyrus. CONCLUSIONS: Our findings suggest that in PiB(+) AD and PiB(-) SVaD, there is divergent disruptions in resting-state DMN and CEN. Furthermore, patients with combined amyloid and SVD burdens exhibited more disrupted resting-state DMN and CEN than patients with only amyloid or SVD burden.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Cerebral Cortex; Cross-Sectional Studies; Dementia; Dementia, Vascular; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Models, Neurological; Neural Pathways; Neuropsychological Tests; Oxygen; Psychiatric Status Rating Scales; Radionuclide Imaging; Rest; Thiazoles

Dose-Dependent Neuroprotection and Neurotoxicity of Simvastatin through Reduction of Farnesyl Pyrophosphate in Mice Treated with Intracerebroventricular Injection of Aβ 1-42. - Jin, Huafeng; Chen, Tingting; Li, Guoxi; Wang, Conghui; Zhang, Baofeng; Cao, Xinyuan; Sha, Sha; Wan, Qi; Chen, Ling (J Alzheimers Dis, 2016)
BACKGROUND: Simvastatin (SV) has been reported to improve dementia and slow progression of Alzheimer's disease (AD), however there are conflicting reports. OBJECTIVE & METHODS: Intracerebroventricular injection of aggregated Aβ1-42 in mice (Aβ1-42-mice) caused spatial cognitive deficits, long-term potentiation (LTP) impairment, and death of hippocampal pyramidal cells. The present study focused on exploring the dose-dependent effects of SV (10-80 mg/kg) on Aβ1-42-impaired spatial memory and the underlying mechanisms. RESULTS: The treatment of Aβ1-42-mice with SV for continuous 15 days could attenuate the spatial cognitive deficits and recover the LTP induction in a "U" type dose-dependent manner. The death of pyramidal cells in Aβ1-42-mice was significantly reduced by the SV-treatment at 20 mg/kg, but not at a dose of 10 or 40 mg/kg, even was aggravated at a dose of 80 mg/kg. Hippocampal NMDA receptor (NMDAr) NR2B phosphorylation (phospho-NR2B) was elevated in Aβ1-42-mice, which was further dose-dependently increased by SV-treatment. Replenishment of isoprenoid farnesyl pyrophosphate (FPP) by applying farnesol (FOH) could abolish the SV-increased phospho-NR2B in Aβ1-42-mice, but had no effect on the Aβ1-42-enhanced phospho-NR2B. NMDAr antagonist blocked the neurotoxicity of Aβ1-42 and SV (80 mg/kg) in Aβ1-42-mice, whereas FOH only inhibited SV (80 mg/kg)-neurotoxicity. The SV-treatment in Aβ1-42-mice corrected the decrease in hippocampal Akt phosphorylation. The PI3K inhibitor abolished the SV (20 mg/kg)-neuroprotection in Aβ1-42-mice. CONCLUSION: SV-treatment in Aβ1-42-mice exerts dose-dependent neuroprotection and neurotoxicity by reducing FPP to enhance the phosphorylation of NR2B and Akt.
Keywords: Amyloid beta-Peptides; Animals; Dose-Response Relationship, Drug; Hippocampus; Injections, Intraventricular; Male; Maze Learning; Mice; Neuroprotective Agents; Peptide Fragments; Phosphorylation; Polyisoprenyl Phosphates; Receptors, N-Methyl-D-Aspartate; Sesquiterpenes; Simvastatin; Spatial Memory

Dysregulation of Autophagy, Mitophagy, and Apoptotic Genes in the Medial Temporal Lobe Cortex in an Ischemic Model of Alzheimer's Disease. - Ułamek-Kozioł, Marzena; Kocki, Janusz; Bogucka-Kocka, Anna; Petniak, Alicja; Gil-Kulik, Paulina; Januszewski, Sławomir; Bogucki, Jacek; Jabłoński, Mirosław; Furmaga-Jabłońska, Wanda; Brzozowska, Judyta; Czuczwar, Stanisław J; Pluta, Ryszard (J Alzheimers Dis, 2016)
Ischemic brain damage is a pathological incident that is often linked with medial temporal lobe cortex injury and finally its atrophy. Post-ischemic brain injury associates with poor prognosis since neurons of selectively vulnerable ischemic brain areas are disappearing by apoptotic program of neuronal death. Autophagy has been considered, after brain ischemia, as a guardian against neurodegeneration. Consequently, we have examined changes in autophagy (BECN 1), mitophagy (BNIP 3), and apoptotic (caspase 3) genes in the medial temporal lobe cortex with the use of quantitative reverse-transcriptase PCR following transient 10-min global brain ischemia in rats with survival 2, 7, and 30 days. The intense significant overexpression of BECN 1 gene was noted on the 2nd day, while on days 7-30 the expression of this gene was still upregulated. BNIP 3 gene was downregulated on the 2nd day, but on days 7-30 post-ischemia, there was a significant reverse tendency. Caspase 3 gene, associated with apoptotic neuronal death, was induced in the same way as BNIP 3 gene after brain ischemia. Thus, the demonstrated changes indicate that the considerable dysregulation of expression of BECN 1, BNIP 3, and caspase 3 genes may be connected with a response of neuronal cells in medial temporal lobe cortex to transient complete brain ischemia.

Early Postmenopausal Transdermal 17β-Estradiol Therapy and Amyloid-β Deposition. - Kantarci, Kejal; Lowe, Val J; Lesnick, Timothy G; Tosakulwong, Nirubol; Bailey, Kent R; Fields, Julie A; Shuster, Lynne T; Zuk, Samantha M; Senjem, Matthew L; Mielke, Michelle M; Gleason, Carey; Jack, Clifford R; et al. (J Alzheimers Dis, 2016)
BACKGROUND: It remains controversial whether hormone therapy in recently postmenopausal women modifies the risk of Alzheimer's disease (AD). OBJECTIVE: To investigate the effects of hormone therapy on amyloid-β deposition in recently postmenopausal women. METHODS: Participants within 5-36 months past menopause in the Kronos Early Estrogen Prevention Study, a randomized, double blinded placebo-controlled clinical trial, were randomized to: 1) 0.45 mg/day oral conjugated equine estrogens (CEE); 2) 50μg/day transdermal 17β-estradiol; or 3) placebo pills and patch for four years. Oral progesterone (200 mg/day) was given to active treatment groups for 12 days each month. 11C Pittsburgh compound B (PiB) PET imaging was performed in 68 of the 118 participants at Mayo Clinic approximately seven years post randomization and three years after stopping randomized treatment. PiB Standard unit value ratio (SUVR) was calculated. RESULTS: Women (age = 52-65) randomized to transdermal 17β-estradiol (n = 21) had lower PiB SUVR compared to placebo (n = 30) after adjusting for age [odds ratio (95% CI) = 0.31(0.11-0.83)]. In the APOEɛ4 carriers, transdermal 17β-estradiol treated women (n = 10) had lower PiB SUVR compared to either placebo (n = 5) [odds ratio (95% CI) = 0.04(0.004-0.44)], or the oral CEE treated group (n = 3) [odds ratio (95% CI) = 0.01(0.0006-0.23)] after adjusting for age. Hormone therapy was not associated with PiB SUVR in the APOEɛ4 non-carriers. CONCLUSION: In this pilot study, transdermal 17β-estradiol therapy in recently postmenopausal women was associated with a reduced amyloid-β deposition, particularly in APOEɛ4 carriers. This finding may have important implications for the prevention of AD in postmenopausal women, and needs to be confirmed in a larger sample.

The Effect of Propofol Versus Isoflurane Anesthesia on Human Cerebrospinal Fluid Markers of Alzheimer's Disease: Results of a Randomized Trial. - Berger, Miles; Nadler, Jacob W; Friedman, Allan; McDonagh, David L; Bennett, Ellen R; Cooter, Mary; Qi, Wenjing; Laskowitz, Daniel T; Ponnusamy, Vikram; Newman, Mark F; Shaw, Leslie M; Warner, David S; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Preclinical studies have found differential effects of isoflurane and propofol on the Alzheimer's disease (AD)-associated markers tau, phosphorylated tau (p-tau) and amyloid-β (Aβ). OBJECTIVE: We asked whether isoflurane and propofol have differential effects on the tau/Aβ ratio (the primary outcome), and individual AD biomarkers. We also examined whether genetic/intraoperative factors influenced perioperative changes in AD biomarkers. METHODS: Patients undergoing neurosurgical/otolaryngology procedures requiring lumbar cerebrospinal fluid (CSF) drain placement were prospectively randomized to receive isoflurane (n = 21) or propofol (n = 18) for anesthetic maintenance. We measured perioperative CSF sample AD markers, performed genotyping assays, and examined intraoperative data from the electronic anesthesia record. A repeated measures ANOVA was used to examine changes in AD markers by anesthetic type over time. RESULTS: The CSF tau/Aβ ratio did not differ between isoflurane- versus propofol-treated patients (p = 1.000). CSF tau/Aβ ratio and tau levels increased 10 and 24 h after drain placement (p = 2.002×10-6 and p = 1.985×10-6, respectively), mean CSF p-tau levels decreased (p = 0.005), and Aβ levels did not change (p = 0.152). There was no interaction between anesthetic treatment and time for any of these biomarkers. None of the examined genetic polymorphisms, including ApoE4, were associated with tau increase (n = 9 polymorphisms, p > 0.05 for all associations). CONCLUSION: Neurosurgery/otolaryngology procedures are associated with an increase in the CSF tau/Aβ ratio, and this increase was not influenced by anesthetic type. The increased CSF tau/Aβ ratio was largely driven by increases in tau levels. Future work should determine the functional/prognostic significance of these perioperative CSF tau elevations.

Evaluation of a Genetic Risk Score to Improve Risk Prediction for Alzheimer's Disease. - Chouraki, Vincent; Reitz, Christiane; Maury, Fleur; Bis, Joshua C; Bellenguez, Celine; Yu, Lei; Jakobsdottir, Johanna; Mukherjee, Shubhabrata; Adams, Hieab H; Choi, Seung Hoan; Larson, Eric B; Fitzpatrick, Annette; et al. (J Alzheimers Dis, 2016)
Effective prevention of Alzheimer's disease (AD) requires the development of risk prediction tools permitting preclinical intervention. We constructed a genetic risk score (GRS) comprising common genetic variants associated with AD, evaluated its association with incident AD and assessed its capacity to improve risk prediction over traditional models based on age, sex, education, and APOEɛ4. In eight prospective cohorts included in the International Genomics of Alzheimer's Project (IGAP), we derived weighted sum of risk alleles from the 19 top SNPs reported by the IGAP GWAS in participants aged 65 and older without prevalent dementia. Hazard ratios (HR) of incident AD were estimated in Cox models. Improvement in risk prediction was measured by the difference in C-index (Δ-C), the integrated discrimination improvement (IDI) and continuous net reclassification improvement (NRI>0). Overall, 19,687 participants at risk were included, of whom 2,782 developed AD. The GRS was associated with a 17% increase in AD risk (pooled HR = 1.17; 95% CI =   [1.13-1.21] per standard deviation increase in GRS; p-value =  2.86×10-16). This association was stronger among persons with at least one APOEɛ4 allele (HRGRS = 1.24; 95% CI =   [1.15-1.34]) than in others (HRGRS = 1.13; 95% CI =   [1.08-1.18]; pinteraction = 3.45×10-2). Risk prediction after seven years of follow-up showed a small improvement when adding the GRS to age, sex, APOEɛ4, and education (Δ-Cindex =  0.0043 [0.0019-0.0067]). Similar patterns were observed for IDI and NRI>0. In conclusion, a risk score incorporating common genetic variation outside the APOEɛ4 locus improved AD risk prediction and may facilitate risk stratification for prevention trials.

Evidence For and Against a Pathogenic Role of Reduced γ-Secretase Activity in Familial Alzheimer's Disease. - Jayne, Tanya; Newman, Morgan; Verdile, Giuseppe; Sutherland, Greg; Münch, Gerald; Musgrave, Ian; Moussavi Nik, Seyyed Hani; Lardelli, Michael (J Alzheimers Dis, 2016)
The majority of mutations causing familial Alzheimer's disease (fAD) have been found in the gene PRESENILIN1 (PSEN1) with additional mutations in the related gene PRESENILIN2 (PSEN2). The best characterized function of PRESENILIN (PSEN) proteins is in γ-secretase enzyme activity. One substrate of γ-secretase is encoded by the gene AMYLOID BETA A4 PRECURSOR PROTEIN (AβPP/APP) that is a fAD mutation locus. AβPP is the source of the amyloid-β (Aβ) peptide enriched in the brains of people with fAD or the more common, late onset, sporadic form of AD, sAD. These observations have resulted in a focus on γ-secretase activity and Aβ as we attempt to understand the molecular basis of AD pathology. In this paper we briefly review some of the history of research on γ-secretase in AD. We then discuss the main ideas regarding the role of γ-secretase and the PSEN genes in this disease. We examine the significance of the "fAD mutation reading frame preservation rule" that applies to PSEN1 and PSEN2 (and AβPP) and look at alternative roles for AβPP and Aβ in fAD. We present a case for an alternative interpretation of published data on the role of γ-secretase activity and fAD-associated mutations in AD pathology. Evidence supports a "PSEN holoprotein multimer hypothesis" where PSEN fAD mutations generate mutant PSEN holoproteins that multimerize with wild type holoprotein and dominantly interfere with an AD-critical function(s) such as autophagy or secretion of Aβ. Holoprotein multimerization may be required for the endoproteolysis that activates PSENs' γ-secretase activity.

Expression of the Alzheimer's Disease Mutations AβPP695sw and PSEN1M146I in Double-Transgenic Göttingen Minipigs. - Jakobsen, Jannik E; Johansen, Marianne G; Schmidt, Mette; Liu, Ying; Li, Rong; Callesen, Henrik; Melnikova, Margarita; Habekost, Mette; Matrone, Carmela; Bouter, Yvonne; Bayer, Thomas A; Nielsen, Anders Lade; et al. (J Alzheimers Dis, 2016)
Mutations in the amyloid-β protein precursor gene (AβPP), the presenilin 1 gene (PSEN1) or the presenilin 2 gene (PSEN2) that increase production of the AβPP-derived peptide Aβ42 cause early-onset Alzheimer's disease. Rodent models of the disease show that further increase in Aβ42 production and earlier brain pathology can be obtained by coexpressing AβPP and PSEN1 mutations. To generate such elevated Aβ42 level in a large animal model, we produced Göttingen minipigs carrying in their genome one copy of a human PSEN1 cDNA with the Met146Ile (PSEN1M146I) mutation and three copies of a human AβPP695 cDNA with the Lys670Asn/Met671Leu (AβPPsw) double-mutation. Both transgenes were expressed in fibroblasts and in the brain, and their respective proteins were processed normally. Immunohistochemical staining with Aβ42-specific antibodies detected intraneuronal accumulation of Aβ42 in brains from a 10- and an 18-month-old pig. Such accumulation may represent an early event in the pathogenesis of Alzheimer's disease.

FDG-PET and Neuropsychiatric Symptoms among Cognitively Normal Elderly Persons: The Mayo Clinic Study of Aging. - Krell-Roesch, Janina; Ruider, Hanna; Lowe, Val J; Stokin, Gorazd B; Pink, Anna; Roberts, Rosebud O; Mielke, Michelle M; Knopman, David S; Christianson, Teresa J; Machulda, Mary M; Jack, Clifford R; Petersen, Ronald C; et al. (J Alzheimers Dis, 2016)
One of the key research agenda of the field of aging is investigation of presymptomatic Alzheimer's disease (AD). Furthermore, abnormalities in brain glucose metabolism (as measured by FDG-PET) have been reported among cognitively normal elderly persons. However, little is known about the association of FDG-PET abnormalities with neuropsychiatric symptoms (NPS) in a population-based setting. Thus, we conducted a cross-sectional study derived from the ongoing population-based Mayo Clinic Study of Aging in order to examine the association between brain glucose metabolism and NPS among cognitively normal (CN) persons aged > 70 years. Participants underwent FDG-PET and completed the Neuropsychiatric Inventory Questionnaire (NPI-Q), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI). Cognitive classification was made by an expert consensus panel. We conducted multivariable logistic regression analyses to compute odds ratios (OR) and 95% confidence intervals after adjusting for age, sex, and education. For continuous variables, we used linear regression and Spearman rank-order correlations. Of 668 CN participants (median 78.1 years, 55.4% males), 205 had an abnormal FDG-PET (i.e., standardized uptake value ratio < 1.32 in AD-related regions). Abnormal FDG-PET was associated with depression as measured by NPI-Q (OR = 2.12; 1.23-3.64); the point estimate was further elevated for APOE ɛ4 carriers (OR = 2.59; 1.00-6.69), though marginally significant. Additionally, we observed a significant association between abnormal FDG-PET and depressive and anxiety symptoms when treated as continuous measures. These findings indicate that NPS, even in community-based samples, can be an important additional tool to the biomarker-based investigation of presymptomatic AD.

Gene Expression of Quaking in Sporadic Alzheimer's Disease Patients is Both Upregulated and Related to Expression Levels of Genes Involved in Amyloid Plaque and Neurofibrillary Tangle Formation. - Farnsworth, Bryn; Peuckert, Christiane; Zimmermann, Bettina; Jazin, Elena; Kettunen, Petronella; Emilsson, Lina Sors (J Alzheimers Dis, 2016)
Quaking (QKI) is a gene exclusively expressed within glial cells. QKI has previously been implicated in various neurological disorders and diseases, including Alzheimer's disease (AD), a condition for which increasing evidence suggests a central role of glia cells. The objective of the present study was to investigate the expression levels of QKI and three QKI isoforms (QKI5, QKI6, and QKI7) in AD. Genes that have previously been related to the ontogeny and progression of AD, specifically APP, PSEN1, PSEN2, and MAPT, were also investigated. A real-time PCR assay of 123 samples from human postmortem sporadic AD patients and control brains was performed. The expression values were analyzed with an analysis of covariance model and subsequent multiple regressions to explore the possibility of related expression values between QKI, QKI isoforms, and AD-related genes. Further, the sequences of AD-related genes were analyzed for the presence of QKI binding domains. QKI and all measured QKI isoforms were found to be significantly upregulated in AD samples, relative to control samples. However, APP, PSEN1, PSEN2, and MAPT were not found to be significantly different. QKI and QKI isoforms were found to be predictive for the variance of APP, PSEN1, PSEN2, and MAPT, and putative QKI binding sites suggests an interaction with QKI. Overall, these results implicate a possible role of QKI in AD, although the exact mechanism by which this occurs remains to be uncovered.

Geographical Variation in Antipsychotic Drug Use in Elderly Patients with Dementia: A Nationwide Study. - Zakarias, Johanne Købstrup; Jensen-Dahm, Christina; Nørgaard, Ane; Stevnsborg, Lea; Gasse, Christiane; Andersen, Bodil Gramkow; Søren, Jakobsen; Waldorff, Frans Boch; Moos, Torben; Waldemar, Gunhild (J Alzheimers Dis, 2016)
BACKGROUND: Use of antipsychotics in elderly patients with dementia has decreased in the past decade due to safety regulations; however use is still high. Geographical variation may indicate discrepancies in clinical practice and lack of adherence to evidence-based guidelines for the management of behavioral symptoms. OBJECTIVE: To investigate potential geographical variances in use of antipsychotic drugs in dementia care. METHODS: A registry-based cross-sectional study in the entire elderly population of Denmark (≥65 years) conducted in 2012. Data included place of residence, prescriptions filled, and hospital discharge diagnoses. Antipsychotic drug use among elderly with (n = 34,536) and without (n = 931,203) a dementia diagnosis was compared across the five regions and 98 municipalities in Denmark, adjusted for age and sex. RESULTS: In 2012, the national prevalence of antipsychotic drug use was 20.7% for elderly patients with dementia, with a national incidence of 3.9%. The prevalence ranged from 17.0% to 23.3% in the five regions and from 7.5% to 33.1% in the 98 municipalities, demonstrating an over four-fold difference. CONCLUSION: The observed geographical variation was more pronounced at municipal level as compared to regional level, suggesting that the variation may be related to variances in clinical practice in primary care. This study highlights an urgent need for further educating professional carers and physicians to guide non-pharmacological as well as pharmacological management of neuropsychiatric symptoms in elderly patients with dementia.

The Gesture Imitation in Alzheimer's Disease Dementia and Amnestic Mild Cognitive Impairment. - Li, Xudong; Jia, Shuhong; Zhou, Zhi; Hou, Chunlei; Zheng, Wenjing; Rong, Pei; Jiao, Jinsong (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease dementia (ADD) has become an important health problem in the world. Visuospatial deficits are considered to be an early symptom besides memory disorder. OBJECTIVES: The gesture imitation test was devised to detect ADD and amnestic mild cognitive impairment (aMCI). METHODS: A total of 117 patients with ADD, 118 with aMCI, and 95 normal controls were included in this study. All participants were administered our gesture imitation test, the Mini-Mental State Examination (MMSE), the Montreal Cognitive Assessment (MoCA), the Clock Drawing Test (CDT), and the Clinical Dementia Rating Scale (CDR). RESULTS: Patients with ADD performed worse than normal controls on global scores and had a lower success rate on every item (p < 0.001). The area under the curve (AUC) for the global scores when comparing the ADD and control groups was 0.869 (p < 0.001). Item 4 was a better discriminator with a sensitivity of 84.62% and a specificity of 67.37%. The AUC for the global scores decreased to 0.621 when applied to the aMCI and control groups (p = 0.002). After controlling for age and education, the gesture imitation test scores were positively correlated with the MMSE (r = 0.637, p < 0.001), the MoCA (r = 0.572, p < 0.001), and the CDT (r = 0.514, p < 0.001) and were negatively correlated with the CDR scores (r = -0.558, p < 0.001). CONCLUSIONS: The gesture imitation test is an easy, rapid tool for detecting ADD, and is suitable for the patients suspected of mild ADD and aMCI in outpatient clinics.

Glutamine and Glutamate Complex, as Measured by Functional Magnetic Resonance Spectroscopy, Alters During Face-Name Association Task in Patients with Mild Cognitive Impairment and Alzheimer's Disease. - Jahng, Geon-Ho; Oh, Janghoon; Lee, Do-Wan; Kim, Hyug-Gi; Rhee, Hak Young; Shin, Wonchul; Paik, Jong-Woo; Lee, Kyung Mi; Park, Soonchan; Choe, Bo-Young; Ryu, Chang-Woo (J Alzheimers Dis, 2016)
BACKGROUND: The metabolite response during a memory task in Alzheimer's disease (AD) patients is unknown. OBJECTIVE: To investigate the metabolite changes in subjects with AD, amnestic mild cognitive impairment (aMCI), and cognitively normal (CN) elderly during a memory task using functional magnetic resonance spectroscopy (fMRS). METHODS: This study involved 23 young normal controls (YC), 24 CN elderly, 24 aMCI, and 24 mild and probable AD individuals. fMRS data were acquired at the precuneus and posterior cingulate brain regions during a face-name association task. Statistical analyses of quantified metabolites were performed to evaluate differences of the metabolite values between the stimulation conditions and among the four subject groups. Receiver operating curve analysis was performed to evaluate whether the metabolic changes after functional activations can differentiate the subject groups. RESULT: Glutamine and glutamate complex (Glx) was statistically significantly different between the fixation and repeat conditions in aMCI (p = 0.0492) as well as between the fixation and the novel conditions in the AD (p = 0.0412) group. The total N-acetylaspartate (tNAA) was statistically significantly different among the four subject groups in the fixation condition (DF = 3, F = 7.673, p <  0.001), the novel condition (DF = 3, F = 6.945, p <  0.001), and the repeat condition (DF = 3, F = 7.127, p <  0.001). tNAA, tCr, and mIns could be used to differentiate CN from aMCI. Furthermore, tNAA, tCr, Glx, and Glu could also differentiate CN from AD, and aMCI from AD. CONCLUSION: Glx was altered during a stimulation that may be used to evaluate neuronal dysfunction in a demented patient. tNAA and tCr were reduced in patients with AD.

GSK-3β is Dephosphorylated by PP2A in a Leu309 Methylation-Independent Manner. - Chu, Dandan; Tan, Jianxin; Xie, Shutao; Jin, Nana; Yin, Xiaomin; Gong, Cheng-Xin; Iqbal, Khalid; Liu, Fei (J Alzheimers Dis, 2016)
Hyperphosphorylation of tau is pivotally involved in the pathogenesis of Alzheimer's disease (AD) and related tauopathies. Glycogen synthase kinase-3β (GSK-3β) and protein phosphate 2A (PP2A) are crucial enzymes to regulate tau phosphorylation. GSK-3β activity is regulated by its inhibitory phosphorylation at Ser9. We previously reported the cross-talk between GSK-3β and PP2A signaling and showed that PP2A could dephosphorylate GSK-3β at Ser9. Here, we investigated the dephosphorylation of GSK-3β in brain extracts in the presence of phosphatase inhibitors and found that a PP2A-like phosphatase activity was required for dephosphorylation of GSK-3β at Ser9. PP2A interacted with GSK-3β and suppressed its Ser9 phosphorylation in vitro and in HEK-293FT cells. Activity of PP2A negatively correlated to the level of phosphorylated GSK-3β in kainic acid-induced excitotoxic mouse brain. Alteration of methylation of the catalytic subunit of PP2A (PP2Ac) at Leu309 did not affect GSK-3β phosphorylation. These findings suggest that Leu309 methylation is not required for PP2A to dephosphorylate GSK-3β at Ser9.
Keywords: Animals; Brain; Carboxylic Ester Hydrolases; Cell Line, Transformed; Dose-Response Relationship, Drug; Enzyme Inhibitors; Excitatory Amino Acid Agonists; Glycogen Synthase Kinase 3; Glycogen Synthase Kinase 3 beta; Humans; Kainic Acid; Leucine; Luminescent Proteins; Male; Methylation; Mice; Phosphorylation; Protein O-Methyltransferase; Protein Phosphatase 2; RNA, Small Interfering; Serine; tau Proteins

Halting of Caspase Activity Protects Tau from MC1-Conformational Change and Aggregation. - Mead, Emma; Kestoras, Dimitra; Gibson, Yolanda; Hamilton, Lucy; Goodson, Ross; Jones, Sophie; Eversden, Sarah; Davies, Peter; O'Neill, Michael; Hutton, Michael; Szekeres, Philip; Wolak, Joanna (J Alzheimers Dis, 2016)
Intracellular neurofibrillary tangles (NFTs) are the hallmark of Alzheimer's disease and other tauopathies in which tau, a microtubule-associated protein, loses its ability to stabilize microtubules. Several post-translational modifications including phosphorylation and truncation increase tau's propensity to aggregate thus forming NFTs; however, the mechanisms underlying tau conformational change and aggregation still remain to be defined. Caspase activation and subsequent proteolytic cleavage of tau is thought to be a potential trigger of this disease-related pathological conformation. The aim of this work was to investigate the link between caspase activation and a disease-related conformational change of tau in a neuroblastoma cell-based model of spontaneous tau aggregation. We demonstrated that caspase induction initiates proteolytic cleavage of tau and generation of conformationally altered and aggregated tau recognized by the MC1 conformational antibody. Most importantly, these events were shown to be attenuated with caspase inhibitors. This implies that therapeutics aimed at inhibiting caspase-mediated tau cleavage may prove beneficial in slowing cleavage and aggregation, thus potentially halting tau pathology and disease progression.

Heterogeneous Language Profiles in Patients with Primary Progressive Aphasia due to Alzheimer's Disease. - Louwersheimer, Eva; Keulen, M Antoinette; Steenwijk, Martijn D; Wattjes, Mike P; Jiskoot, Lize C; Vrenken, Hugo; Teunissen, Charlotte E; van Berckel, Bart N M; van der Flier, Wiesje M; Scheltens, Philip; van Swieten, John C; Pijnenburg, Yolande A L (J Alzheimers Dis, 2016)
BACKGROUND: The logopenic variant of Primary Progressive Aphasia (lvPPA) is associated with underlying Alzheimer's disease (AD) pathology and characterized by impaired single word retrieval and repetition of phrases and sentences. OBJECTIVE: We set out to study whether logopenic aphasia is indeed the prototypic language profile in PPA patients with biomarker evidence of underlying AD pathology and to correlate language profiles with cortical atrophy patterns on MRI. METHODS: Inclusion criteria: (I) clinical diagnosis of PPA; (II) CSF profile and/or PiB-PET scan indicative for amyloid pathology; (III) availability of expert language evaluation. Based on language evaluation, patients were classified as lvPPA (fulfilling lvPPA core criteria), lvPPA extended (fulfilling core criteria plus other language disturbances), or PPA unclassifiable (not fulfilling lvPPA core criteria). Cortical atrophy patterns on MRI were visually rated and quantitative measurements of cortical thickness were performed using FreeSurfer. RESULTS: We included 22 patients (age 67±7 years, 50% female, MMSE 21±6). 41% were classified as lvPPA, 36% as lvPPA extended with additional deficits in language comprehension and/or confrontation naming, and 23% as PPA unclassifiable. By both qualitative and quantitative measurements, patients with lvPPA showed mild global cortical atrophy on MRI, whereas patients with lvPPA extended showed more focal cortical atrophy, predominantly at the left tempo-parietal side. For PPA unclassifiable, qualitative measurements revealed a heterogeneous atrophy pattern. CONCLUSION: Although most patients fulfilled the lvPPA criteria, we found that their language profiles were heterogeneous. The clinical and radiological spectrum of PPA due to underlying AD pathology is broader than pure lvPPA.
Keywords: Aged; Alzheimer Disease; Aphasia, Primary Progressive; Atrophy; Biomarkers; Brain; Female; Humans; Language; Language Tests; Magnetic Resonance Imaging; Male; Mental Status Schedule; Organ Size; Positron-Emission Tomography; Retrospective Studies

High Risk of Dementia in Ventricular Enlargement with Normal Pressure Hydrocephalus Related Symptoms1. - Koivisto, Anne M; Kurki, Mitja I; Alafuzoff, Irina; Sutela, Anna; Rummukainen, Jaana; Savolainen, Sakari; Vanninen, Ritva; Jääskeläinen, Juha E; Soininen, Hilkka; Leinonen, Ville (J Alzheimers Dis, 2016)
BACKGROUND: Differential diagnosis of ventricular enlargement with normal pressure hydrocephalus (NPH) related symptoms is challenging. Patients with enlarged ventricles often manifest cognitive deterioration but their long-term outcome is not well known. OBJECTIVES: We aim to evaluate long-term cognitive outcome in patients with enlarged ventricles and clinically suspected NPH. METHODS: A neurologist and a neurosurgeon clinically evaluated 468 patients with enlarged ventricles and suspected NPH using radiological methods, intraventricular pressure monitoring, and frontal cortical brain biopsy. The neurologist confirmed final diagnoses after a median follow-up interval of 4.8 years. RESULTS: Altogether, 232 patients (50%) with enlarged ventricles did not fulfill the criteria for shunt surgery. The incidence of dementia among patients with enlarged ventricles, and at least one NPH-related symptom with adequate follow-up data (n = 446) was high, varying from 77 (iNPH, shunt responders) to 141/1000 person-years (non-shunted patients with enlarged ventricles). At the end of the follow-up, 59% of all these patients were demented. The demented population comprised 73% of non-shunted patients with enlarged ventricles, 63% of shunted iNPH patients that did not respond to treatment, and 46% of iNPH patients that were initially responsive to shunting. The most common cause of dementia was Alzheimer's disease (n = 94, 36%), followed by vascular dementia (n = 68, 26%). CONCLUSIONS: One-half of patients with enlarged ventricles and clinically suspected NPH were not shunted after intraventricular pressure monitoring. Dementia caused by various neurodegenerative diseases was frequently seen in patients with ventricular enlargement. Thus, careful diagnostic evaluation in collaboration with neurologists and neurosurgeons is emphasized.

Human Truncated Tau Induces Mature Neurofibrillary Pathology in a Mouse Model of Human Tauopathy. - Zimova, Ivana; Brezovakova, Veronika; Hromadka, Tomas; Weisova, Petronela; Cubinkova, Veronika; Valachova, Bernadeta; Filipcik, Peter; Jadhav, Santosh; Smolek, Tomas; Novak, Michal; Zilka, Norbert (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) represents the most common neurodegenerative disorder. Several animal models have been developed in order to test pathophysiological mechanisms of the disease and to predict effects of pharmacological interventions. Here we examine the molecular and behavioral features of R3m/4 transgenic mice expressing human non-mutated truncated tau protein (3R tau, aa151-391) that were previously used for efficacy testing of passive tau vaccine. The mouse model reliably recapitulated crucial histopathological features of human AD, such as pre-tangles, neurofibrillary tangles, and neuropil threads. The pathology was predominantly located in the brain stem. Transgenic mice developed mature sarkosyl insoluble tau complexes consisting of mouse endogenous and human truncated and hyperphosphorylated forms of tau protein. The histopathological and biochemical features were accompanied by significant sensorimotor impairment and reduced lifespan. The sensorimotor impairment was monitored by a highly sensitive, fully-automated tool that allowed us to assess early deficit in gait and locomotion. We suggest that the novel transgenic mouse model can serve as a valuable tool for analysis of the therapeutic efficacy of tau vaccines for AD therapy.

Hyperactivity with Agitative-Like Behavior in a Mouse Tauopathy Model. - Jul, Pia; Volbracht, Christiane; de Jong, Inge E M; Helboe, Lone; Elvang, Anders Brandt; Pedersen, Jan Torleif (J Alzheimers Dis, 2016)
Tauopathies, such as Alzheimer's disease (AD) and frontotemporal dementia (FTD), are characterized by formation of neurofibrillary tangles consisting of hyperphosphorylated tau. In addition to memory loss, patients experience behavioral symptoms such as agitation, aggression, depression, and insomnia. We explored the behavioral phenotype of a mouse model (rTg4510) carrying the human tau P301L mutation found in a familial form of FTD. We tested these mice in locomotor activity assays as well as in the Morris water maze to access spatial memory. In addition to cognitive impairments, rTg4510 mice exhibited a hyperactivity phenotype which correlated with progression of tau pathology and was dependent on P301L tau transgene expression. The hyperactive phenotype was characterized by significantly increased locomotor activity in a novel and in a simulated home cage environment together with a disturbed day/night cycle. The P301L-tau-dependent hyperactivity and agitative-like phenotype suggests that these mice may form a correlate to some of the behavioral disturbances observed in advanced AD and FTD.
Keywords: Age Factors; Analysis of Variance; Animals; Brain; Cognition Disorders; Disease Models, Animal; Doxycycline; Exploratory Behavior; Humans; Hyperkinesis; Male; Maze Learning; Mice; Mice, Transgenic; Motor Activity; Mutation; Psychomotor Agitation; tau Proteins; Tauopathies; Time Factors

"I Don't Think Of It As An Illness": Illness Representations in Mild to Moderate Dementia. - Clare, Linda; Quinn, Catherine; Jones, Ian Rees; Woods, Robert T (J Alzheimers Dis, 2016)
The self-regulatory model proposes that illness representations influence adjustment and coping in chronic conditions. Better understanding of the illness representations held by people with dementia could help with targeting information and support so as to optimize adjustment and coping. In this mixed-methods study of illness representations among people with mild to moderate Alzheimer's, vascular, or mixed dementia we aimed to clarify the nature of the representations held, to determine whether specific profiles can be identified based on perceptions of the identity and cause of the condition, and to examine associations between these profiles and other participant characteristics. Data were collected in the second wave of the Memory Impairment and Dementia Awareness Study (MIDAS). Sixty-four people with dementia, who had been told their diagnosis at a memory clinic, completed interviews and responded to questionnaires. In each case a carer was also interviewed. Cluster analysis based on responses about identity and cause identified three profiles. 'Illness' cluster participants saw themselves as living with an illness and used diagnostic labels, 'ageing' cluster participants did not use diagnostic labels and viewed their difficulties as related to ageing, and 'no problem' cluster participants considered that they did not have any difficulties. 'Illness' cluster participants had better cognition and better awareness, but lower mood, and perceived more practical consequences, than 'ageing' cluster participants. Holding an 'illness' model may not be advantageous. Rather than encouraging adoption of such a model, it may be preferable to target information and select interventions in line with the person's representation profile.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Aging; Awareness; Caregivers; Dementia; Female; Follow-Up Studies; Humans; Male; Middle Aged; Psychiatric Status Rating Scales; Residence Characteristics; Self Concept; Statistics, Nonparametric; Surveys and Questionnaires

Identification of Physician-Diagnosed Alzheimer's Disease and Related Dementias in Population-Based Administrative Data: A Validation Study Using Family Physicians' Electronic Medical Records. - Jaakkimainen, R Liisa; Bronskill, Susan E; Tierney, Mary C; Herrmann, Nathan; Green, Diane; Young, Jacqueline; Ivers, Noah; Butt, Debra; Widdifield, Jessica; Tu, Karen (J Alzheimers Dis, 2016)
BACKGROUND: Population-based surveillance of Alzheimer's and related dementias (AD-RD) incidence and prevalence is important for chronic disease management and health system capacity planning. Algorithms based on health administrative data have been successfully developed for many chronic conditions. The increasing use of electronic medical records (EMRs) by family physicians (FPs) provides a novel reference standard by which to evaluate these algorithms as FPs are the first point of contact and providers of ongoing medical care for persons with AD-RD. OBJECTIVE: We used FP EMR data as the reference standard to evaluate the accuracy of population-based health administrative data in identifying older adults with AD-RD over time. METHODS: This retrospective chart abstraction study used a random sample of EMRs for 3,404 adults over 65 years of age from 83 community-based FPs in Ontario, Canada. AD-RD patients identified in the EMR were used as the reference standard against which algorithms identifying cases of AD-RD in administrative databases were compared. RESULTS: The highest performing algorithm was "one hospitalization code OR (three physician claims codes at least 30 days apart in a two year period) OR a prescription filled for an AD-RD specific medication" with sensitivity 79.3% (confidence interval (CI) 72.9-85.8%), specificity 99.1% (CI 98.8-99.4%), positive predictive value 80.4% (CI 74.0-86.8%), and negative predictive value 99.0% (CI 98.7-99.4%). This resulted in an age- and sex-adjusted incidence of 18.1 per 1,000 persons and adjusted prevalence of 72.0 per 1,000 persons in 2010/11. CONCLUSION: Algorithms developed from health administrative data are sensitive and specific for identifying older adults with AD-RD.

Impacts of Illiteracy on the Risk of Dementia: A Global Health Perspective. - Suh, Seung Wan; Han, Ji Won; Park, Jae Young; Hong, Jong Woo; Kim, Kayoung; Kim, Taehyun; Lee, Kyoung Hwan; Han, Guehee; Jeong, Hyeon; Seo, Jiyeong; Kim, Tae Hui; Lee, Dong Young; et al. (J Alzheimers Dis, 2016)
Despite its significance as a contributing factor for late-life dementia risk, illiteracy is frequently underappreciated in the management of dementia. In this study, we estimated the proportion of dementia cases attributable to illiteracy using the population attributable fraction (PAF), and calculated to what extent the monetary cost of dementia could be saved in the future by reducing illiteracy from the South Korean, Latin American, South Asian/Middle Eastern, and African populations. We collected necessary data from the 2011 United Nations Human Development Report and prevalence studies conducted in these regions. Additional variables not included in the above sources were estimated using a logit model under a "trend scenario"-based assumption. Around 16% of the total number of dementia cases in South Korea in 2015 can be attributed to illiteracy, with this figure predicted to decline to around 2% by 2050. This translates to a saving in dementia care costs of approximately 52 billion USD, providing we are successful in theoretically eradicating illiteracy as of 2015, in the population aged 65 years or under. Likewise, reducing illiteracy to 50% in Latin America, South Asia/The Middle East, and Africa by 2050 could generate further cost savings of between 71 and 244 billion, 13 and 94 billion, and 17 and 78 billion USD, respectively. Even public policies aimed solely at reducing illiteracy in the childhood, adolescent, or middle-aged population could potentially have a role in the primary prevention of dementia. Moving forward, governments will need to address this issue in a purposeful and systematic manner.

Impaired Parahippocampus Connectivity in Mild Cognitive Impairment and Alzheimer's Disease. - Liu, Jieqiong; Zhang, Xinqing; Yu, Chunshui; Duan, Yunyun; Zhuo, Junjie; Cui, Yue; Liu, Bing; Li, Kuncheng; Jiang, Tianzi; Liu, Yong (J Alzheimers Dis, 2016)
BACKGROUND: The parahippocampal gyrus (PHG) is an important region of the limbic system that plays an important role in episodic memory. Elucidation of the PHG connectivity pattern will aid in the understanding of memory deficits in neurodegenerative diseases. OBJECTIVE: To investigate if disease severity associated altered PHG connectivity in Alzheimer's disease (AD) exists. METHODS: We evaluated resting-state functional magnetic resonance imaging data from 18 patients with amnestic mild cognitive impairment (MCI), 35 patients with AD, and 21 controls. The PHG connectivity pattern was examined by calculating Pearson's correlation coefficients between the bilateral PHG and whole brain. Group comparisons were performed after controlling for the effects of age and gender. The functional connectivity strength in each identified region was correlated with the MMSE score to evaluate the relationship between connectivity and cognitive ability. RESULTS: Several brain regions of the default mode network showed reduced PHG connectivity in the AD patients, and PHG connectivity was associated with disease severity in the MCI and AD subjects. More importantly, correlation analyses showed that there were positive correlations between the connectivity strengths of the left PHG-PCC/Pcu and left PHG-left MTG and the Mini-Mental State Examination, indicating that with disease progression from MCI to severe AD, damage to the functional connectivity of the PHG becomes increasingly severe. CONCLUSIONS: These results indicate that disease severity is associated with altered PHG connectivity, contributing to knowledge about the reduction in cognitive ability and impaired brain activity that occur in AD/MCI. These early changes in the functional connectivity of the PHG might provide some potential clues for identification of imaging markers for the early detection of MCI and AD.
Keywords: Aged; Alzheimer Disease; Apolipoproteins E; Brain Mapping; Cognitive Dysfunction; Female; Hippocampus; Humans; Limbic System; Magnetic Resonance Imaging; Male; Mental Status Schedule; Neural Pathways; Rest; Severity of Illness Index

Inequalities in Access to Treatment and Care for Patients with Dementia and Immigrant Background: A Danish Nationwide Study. - Stevnsborg, Lea; Jensen-Dahm, Christina; Nielsen, Thomas R; Gasse, Christiane; Waldemar, Gunhild (J Alzheimers Dis, 2016)
BACKGROUND: Previous studies demonstrated lower quality diagnostic assessment of dementia in immigrant populations, but knowledge about the quality of treatment and care for dementia is still lacking. OBJECTIVE: To conduct a nationwide registry-based study to determine whether inequality exists regarding access to anti-dementia treatment and care between immigrant and Danish-born patients with dementia. METHODS: A cross-sectional register-based study was conducted in the entire elderly (60≥years) population with dementia in Denmark in 2012 (n = 34,877). The use of anti-dementia drugs and residency in a nursing home were compared among Danish-born and Western and non-Western immigrants with dementia. Logistic regression analysis was done with adjustment for age, sex, comorbidity, marital status, basis of inclusion, and time since dementia diagnosis. RESULTS: Immigrant background was associated with a significantly lower likelihood of receiving anti-dementia drug therapy (odds ratio (OR) [95% confidence interval (CI)]): non-Western = 0.70 [0.56-0.87]; Western = 0.74 [0.63-0.87]). No significant differences were found in type or amount of anti-dementia medication dispensed between the population groups (proxy measure for adherence). Non-Western immigrants were significantly less likely to live in a nursing home (0.52 [0.41-0.65]). CONCLUSION: This nationwide registry-based study indicated a worrisome difference in access to anti-dementia treatment and care for dementia patients with an immigrant background, but similar levels of adherence compared with the Danish-born population. Further research is necessary to pinpoint barriers to access to suitable healthcare among elderly immigrants with dementia but also to identify and develop culturally sensitive methods for their treatment and care.

Inhibition of Cholesterol Biosynthesis Reduces γ-Secretase Activity and Amyloid-β Generation. - Kim, Yoonhee; Kim, Chaeyoung; Jang, Hye Young; Mook-Jung, Inhee (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) is one of major molecules contributing to the pathogenesis of Alzheimer's disease (AD). Aβ is derived from amyloid-β protein precursor (AβPP) through sequential cleavages by β- and γ-secretases. Regulation of these components is thought to be an important factor in Aβ generation during the pathogenesis of AD. AβPP, β-secretase, and γ-secretase reside in lipid rafts, where cholesterol regulates the integrity and flexibility of membrane proteins and Aβ is generated. However, the relationship between cholesterol and Aβ generation is controversial. In this study, we aimed to elucidate the direct effects of cholesterol depletion on AβPP processing using AY9944, which blocks the last step of cholesterol biosynthesis and thus minimizes the unknown side effects of upstream inhibitors, such as HMG-CoA reductase inhibitors. Treatment with AY9944 decreased γ-secretase activity and Aβ generation. These results suggested that changes in membrane composition by lowering cholesterol with AY9944 affected γ-secretase activity and Aβ generation, which is associated with AD pathogenesis.
Keywords: Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Analysis of Variance; Animals; Anticholesteremic Agents; Cell Line; Cholesterol; Cricetinae; Down-Regulation; Humans; In Situ Nick-End Labeling; Luminescent Proteins; Membrane Glycoproteins; Membrane Microdomains; Mutation; Presenilin-1; Protein Transport; trans-1,4-Bis(2-chlorobenzaminomethyl)cyclohexane Dihydrochloride; Transfection

Insulin Resistance is Associated with Increased Levels of Cerebrospinal Fluid Biomarkers of Alzheimer's Disease and Reduced Memory Function in At-Risk Healthy Middle-Aged Adults. - Hoscheidt, Siobhan M; Starks, Erika J; Oh, Jennifer M; Zetterberg, Henrik; Blennow, Kaj; Krause, Rachel A; Gleason, Carey E; Puglielli, Luigi; Atwood, Craig S; Carlsson, Cynthia M; Asthana, Sanjay; Johnson, Sterling C; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Type 2 diabetes is associated with an increased risk for Alzheimer's disease (AD). Regulation of normal insulin function may be important in reducing the prevalence of dementia due to AD, particularly in individuals who harbor genetic risk for or have a parental family history of AD. The relationship between insulin resistance (IR) and AD pathology remains poorly understood, particularly in midlife prior to the onset of clinical metabolic disease or cognitive decline. OBJECTIVE: We examined associations between IR as indexed by HOMA-IR, cerebrospinal fluid (CSF) biomarkers of AD pathology, and memory in middle-aged adults enriched for AD. We postulated that higher HOMA-IR and APOEɛ4 carriage would be associated with greater CSF AD pathology and poor memory performance. METHODS: Cognitively asymptomatic middle-aged adults (N = 70, mean age = 57.7 years) from the Wisconsin Alzheimer's Disease Research Center with a parental family history of dementia due to AD underwent lumbar puncture, blood draw, and neuropsychological testing. CSF AD biomarkers including soluble amyloid-β protein precursor β (sAβPPβ), amyloid-β42 (Aβ42), and phosphorylated tau (P-tau181) were examined with respect to HOMA-IR and APOEɛ4 status. Delayed memory performance was examined with respect to HOMA-IR, CSF AD biomarkers, and APOEɛ4 status. RESULTS: Higher HOMA-IR was associated with higher sAβPPβ and Aβ42 . APOEɛ4 carriers had significantly higher levels of sAβPPα, sAβPPβ, and P-tau181/Aβ42 compared to noncarriers. The concurrent presence of higher HOMA-IR and CSF AD pathology predicted worse delayed memory performance. CONCLUSION: Overall, the findings suggest that IR and APOEɛ4 are contributing factors to the development of AD pathology in midlife, and provide support for targeting insulin function as a potentially modifiable risk factor for AD.

The Latent Dementia Phenotype δ is Associated with Cerebrospinal Fluid Biomarkers of Alzheimer's Disease and Predicts Conversion to Dementia in Subjects with Mild Cognitive Impairment. - Koppara, Alexander; Wolfsgruber, Steffen; Kleineidam, Luca; Schmidtke, Klaus; Frölich, Lutz; Kurz, Alexander; Schulz, Stefanie; Hampel, Harald; Heuser, Isabella; Peters, Oliver; Reischies, Friedel M; Jahn, Holger; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The recently proposed latent variable δ is a new tool for dementia case finding. It is built in a structural equation modeling framework of cognitive and functional data and constitutes a novel endophenotype for Alzheimer's disease (AD) research and clinical trials. OBJECTIVE: To investigate the association of δ with AD biomarkers and to compare the prediction of δ with established scales for conversion to dementia in patients with mild cognitive impairment (MCI). METHODS: Using data from a multicenter memory clinic study, we examined the external associations of the latent variable δ and compared δ with well-established cognitive and functional scales and cognitive-functional composite scores. For that purpose, logistic regressions with cerebrospinal fluid (CSF) biomarkers and conversion to dementia as dependent variables were performed with the investigated scores. The models were tested for significant differences. RESULTS: In patients with MCI, δ based on a broad range of cognitive scales (including the ADAS-cog, the MMSE, and the CERAD neuropsychological battery) predicted an abnormal CSF Aβ42/tau ratio indicative of AD (n = 340, AUC = 0.78, p <  0.001), and predicted incident dementia within 1-3 years of follow-up (n = 525, AUC = 0.84, p <  0.001). These associations were generally stronger than for any other scale or cognitive-functional composite examined. Homologs of δ based on reduced test batteries yielded somewhat lower effects. CONCLUSION: These findings support the interpretation of δ as a construct capturing the disease-related "essence" of cognitive and functional impairments in patients with MCI and dementia, and suggest that δ might become an analytical tool for dementia research.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Phenotype; Predictive Value of Tests; Retrospective Studies; tau Proteins

Longitudinal Study of Impaired Intra- and Inter-Network Brain Connectivity in Subjects at High Risk for Alzheimer's Disease. - Zhan, Yafeng; Ma, Jianhua; Alexander-Bloch, Aaron F; Xu, Kaibin; Cui, Yue; Feng, Qianjin; Jiang, Tianzi; Liu, Yong (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is associated with abnormal resting-state network (RSN) architecture of the default mode network (DMN), the dorsal attention network (DAN), the executive control network (CON), the salience network (SAL), and the sensory-motor network (SMN). However, little is known about the disrupted intra- and inter-network architecture in mild cognitive impairment (MCI). Here, we employed a priori defined regions of interest to investigate the intra- and inter-network functional connectivity profiles of these RSNs in longitudinal participants, including normal controls (n = 23), participants with early MCI (n = 26), and participants with late MCI (n = 19). We found longitudinal alterations of functional connectivity within the DMN, where they were correlated with variation in cognitive ability. The SAL as well as the interaction between the DMN and the SAL were disrupted in MCI. Furthermore, our results demonstrate that longitudinal alterations of functional connectivity are more profound in earlier stages as opposed to later stages of the disease. The increased severity of cognitive impairment is associated with increasingly altered RSN connectivity patterns, suggesting that disruptions in functional connectivity may contribute to cognitive dysfunction and may represent a potential biomarker of impaired cognitive ability in MCI. Earlier prevention and treatment may help to delay disease progression to AD.

Lower Late-Life Body-Mass Index is Associated with Higher Cortical Amyloid Burden in Clinically Normal Elderly. - Hsu, David C; Mormino, Elizabeth C; Schultz, Aaron P; Amariglio, Rebecca E; Donovan, Nancy J; Rentz, Dorene M; Johnson, Keith A; Sperling, Reisa A; Marshall, Gad A (J Alzheimers Dis, 2016)
BACKGROUND: Lower body-mass index (BMI) in late life has been associated with an increased risk of dementia, and weight loss has been associated with more rapid decline in Alzheimer's disease (AD) dementia. OBJECTIVE: To explore the association between BMI and cortical amyloid burden in clinically normal (CN) elderly at risk for AD dementia. METHODS: Cross-sectional analyses were completed using baseline data from the Harvard Aging Brain Study, consisting of 280 community-dwelling CN older adults aged 62-90. Assessments included medical histories and physical exam, Pittsburgh compound B (PiB) positron emission tomography (PET) amyloid imaging, and apolipoprotein E ɛ4 (APOE4) genotyping. For the primary analysis, a general linear regression model was used to evaluate the association of BMI with PiB retention. Covariates included age, sex, years of education, and APOE4 carrier status. Secondary analyses were performed for BMI subdivisions (normal, overweight, obese), APOE4 carriers, and BMI×APOE4 interaction. RESULTS: In the primary analysis, greater PiB retention was associated with lower BMI (β  =  -0.14, p = 0.02). In the secondary analyses, APOE4 carrier status (β= -0.27, p = 0.02) and normal BMI (β= -0.25, p = 0.01), as opposed to overweight or obese BMI, were associated with greater PiB retention. The BMI×APOE4 interaction was also significant (β= -0.14, p = 0.04). CONCLUSIONS: This finding offers new insight into the role of BMI at the preclinical stage of AD, wherein lower BMI late in life is associated with greater cortical amyloid burden. Future studies are needed to elucidate the mechanism behind this association, especially in those with lower BMI who are APOE4 carriers.

LRP/LR Antibody Mediated Rescuing of Amyloid-β-Induced Cytotoxicity is Dependent on PrPc in Alzheimer's Disease. - Pinnock, Emma C; Jovanovic, Katarina; Pinto, Maxine G; Ferreira, Eloise; Dias, Bianca Da Costa; Penny, Clement; Knackmuss, Stefan; Reusch, Uwe; Little, Melvyn; Schatzl, Hermann M; Weiss, Stefan F T (J Alzheimers Dis, 2016)
The neuronal perturbations in Alzheimer's disease are attributed to the formation of extracellular amyloid-β (Aβ) neuritic plaques, composed predominantly of the neurotoxic Aβ42 isoform. Although the plaques have demonstrated a role in synaptic dysfunction, neuronal cytotoxicity has been attributed to soluble Aβ42 oligomers. The 37kDa/67kDa laminin receptor has been implicated in Aβ42 shedding and Aβ42-induced neuronal cytotoxicity, as well as internalization of this neurotoxic peptide. As the cellular prion protein binds to both LRP/LR and Aβ42, the mechanism underlying this cytotoxicity may be indirectly due to the PrPc-Aβ42 interaction with LRP/LR. The effects of this interaction were investigated by 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assays. PrPc overexpression significantly enhanced Aβ42 cytotoxicity in vitro, while PrP-/-  cells were more resistant to the cytotoxic effects of Aβ42 and exhibited significantly less cell death than PrPc expressing N2a cells. Although anti-LRP/LR specific antibody IgG1-iS18 significantly enhanced cell viability in both pSFV1-huPrP1-253 transfected and non-transfected cells treated with exogenous Aβ42, it failed to have any cell rescuing effect in PrP-/-  HpL3-4 cells. These results suggest that LRP/LR plays a significant role in Aβ42-PrPc mediated cytotoxicity and that anti-LRP/LR specific antibodies may serve as potential therapeutic tools for Alzheimer's disease.
Keywords: Amyloid beta-Peptides; Animals; Antibodies; Cell Line, Transformed; Cell Survival; Flow Cytometry; Gene Expression Regulation; Humans; Mice; Peptide Fragments; Prions; Receptors, Laminin; Transfection

M2 Macrophage Transplantation Ameliorates Cognitive Dysfunction in Amyloid-β-Treated Rats Through Regulation of Microglial Polarization. - Zhu, Dan; Yang, Nan; Liu, Yan-Yong; Zheng, Ji; Ji, Chao; Zuo, Ping-Ping (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most common neurodegenerative disorder in the elderly population. Neuroinflammation induced by amyloid-β (Aβ) aggregation is considered to be the critical factor underlying AD pathological mechanisms. Alternatively activated (M2) macrophages/microglia have been reported to have neuroprotective effects in neurodegenerative disease. In this study, we characterized the neuroprotective effects of M2 macrophage transplantation in AD model rats and investigated the underlying mechanisms. Intracerebroventricular injection of Aβ1 - 42 to rats was used to model AD and resulted in cognitive impairment, neuronal damage, and inflammatory changes in the brain microenvironment. We observed an increased interferon regulatory factor (IRF) 5/IRF4 ratio, resulting in greater production of classically activated (M1) versus M2 microglia. M2 macrophage transplantation attenuated inflammation in the brain, reversed Aβ1 - 42-induced changes in the IRF4-IRF5 ratio, drove endogenous microglial polarization toward the M2 phenotype, and ameliorated cognitive impairment. Nerve growth factor (NGF) treatment reduced the IRF5/IRF4 ratio and induced primary microglial polarization to the M2 phenotype in vitro; these effects were prevented by tyrosine Kinase Receptor A (TrkA) inhibition. M2 macrophage transplantation restored the balance of IRF4-IRF5 by affecting the expression of NGF and inflammatory cytokines in the brains of AD model rats. This drove microglial polarization to the M2 phenotype, promoted termination of neuroinflammation, and resulted in improved cognitive abilities.

Memory for Public Events in Mild Cognitive Impairment and Alzheimer's Disease: The Importance of Rehearsal. - Langlois, Roxane; Joubert, Sven; Benoit, Sophie; Dostie, Valérie; Rouleau, Isabelle (J Alzheimers Dis, 2016)
Ribot's law refers to the better preservation of remote memories compared with recent ones that presumably characterizes retrograde amnesia. Even if Ribot-type temporal gradient has been extensively studied in retrograde amnesia, particularly in Alzheimer's disease (AD), this pattern has not been consistently found. One explanation for these results may be that rehearsal frequency rather than remoteness accounts for the better preservation of these memories. Thus, the aim of present study was to address this question by studying retrograde semantic memory in subjects with amnestic mild cognitive impairment (aMCI) (n = 20), mild AD (n = 20) and in healthy older controls (HC; n = 19). In order to evaluate the impact of repetition as well as the impact of remoteness, we used a test assessing memory for enduring and transient public events that occurred in the recent and remote past. Results show no clear temporal gradient across time periods (1960-1975; 1976-1990; 1991-2005; 2006-2011), but a better performance was observed in all three groups for enduring compared with transient events. Moreover, although deficits were globally found in both patients groups compared with HC, more specific analyses revealed that aMCI patients were only impaired on transient events while AD patients were impaired on both transient and enduring events. Exploratory analyses also revealed a tendency suggesting preservation of remote transient events in aMCI. These findings are discussed with regards to memory consolidation models.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Learning; Male; Memory; Psychological Tests; Semantics

A Mercaptoacetamide-Based Class II Histone Deacetylase Inhibitor Increases Dendritic Spine Density via RasGRF1/ERK Pathway. - Song, Jung Min; Sung, You Me; Nam, Jin Han; Yoon, Hyejin; Chung, Andrew; Moffat, Emily; Jung, Mira; Pak, Daniel T S; Kim, Jungsu; Hoe, Hyang-Sook (J Alzheimers Dis, 2016)
BACKGROUND: The accumulation of amyloid-β (Aβ) leads to the loss of dendritic spines and synapses, which is hypothesized to cause cognitive impairments in Alzheimer's disease (AD) patients. In our previous study, we demonstrated that a novel mercaptoacetamide-based class II histone deacetylase inhibitor (HDACI), known as W2, decreased Aβ levels and improved learning and memory in mice. However, the underlying mechanism of this effect is unknown. OBJECTIVE: Because dendritic spine formation is associated with cognitive performance, here we investigated whether HDACI W2 regulates dendritic spine density and its molecular mechanism of action. METHODS: To examine the effect of HDACI W2 on dendritic spine density, we conducted morphological analysis of dendritic spines using GFP transfection and Golgi staining. In addition, to determine the molecular mechanism of W2 effects on spines, we measured the levels of mRNAs and proteins involved in the Ras signaling pathway using quantitative real-time PCR, immunocytochemistry, and western analysis. RESULTS: We found that HDACI W2 altered dendritic spine density and morphology in vitro and in vivo. Additionally, W2 increased the mRNA or protein levels of Ras GRF1 and phospho-ERK. Moreover, knockdown of RasGRF1 and inhibition of ERK activity prevented the W2-mediated spinogenesis in primary hippocampal neurons. CONCLUSION: Our Class II-selective HDACI W2 promotes the formation and growth of dendritic spines in a RasGRF1 and ERK dependent manner in primary hippocampal neurons.
Keywords: Acetamides; Animals; Blotting, Western; Cells, Cultured; Cerebral Cortex; Dendritic Spines; Gene Knockdown Techniques; Green Fluorescent Proteins; Hippocampus; Histone Deacetylase Inhibitors; Immunohistochemistry; MAP Kinase Signaling System; Mice, Inbred C57BL; ras-GRF1; Rats, Sprague-Dawley; Real-Time Polymerase Chain Reaction; Receptors, AMPA; Receptors, N-Methyl-D-Aspartate; RNA, Messenger; Thioglycolates; Transfection

Metabolic Syndrome and Mild Cognitive Impairment: A Case-Control Study among Elderly in a Shanghai Suburb. - Yao, Qian; Jiang, Guo-Xin; Zhou, Zhi-Ming; Chen, Jin-Mei; Cheng, Qi (J Alzheimers Dis, 2016)
BACKGROUND: Metabolic syndrome (MetS) maybe associated with mild cognitive impairment (MCI). OBJECTIVE: To investigate the relationship between MetS, with its individual or combined components, and MCI among elderly. METHODS: A case-control study was conducted among the elderly aged 65 years and over in a community located in the southwestern suburb of Shanghai, China. The Chinese version of the Mini-Mental Status Examination (C-MMSE) was used to screen subjects with MCI. Associations of MetS with its individual or combined components and MCI were analyzed using conditional regression analyses with or without adjustment for gender, education, current smoking, current drinking, and physical activities. RESULTS: There were 379 subjects with MCI and 379 gender- and age-matched healthy controls in the study. Compared with healthy controls in univariate analyses, subjects with MCI were more likely to have less time spent on physical activity, lower C-MMSE score, heavier weight, larger waistline and hipline, higher diastolic blood pressure, higher body mass index, higher abdominal obesity index, higher serum glycated hemoglobin, higher serum triglycerides, higher serum cholesterol, higher serum uric acid, and higher serum alanine aminotransferase. After multivariable adjustment, MetS was significantly associated with an increased risk of MCI (OR = 2.277; 95% CI: 1.086-4.773). Among MetS components, abdominal obesity (OR = 2.101; 95% CI: 1.224-3.608) and hypertension (OR = 2.075; 95% CI: 1.170-3.678) showed a significant association with MCI, respectively; while these two components were combined, the association was stronger (OR = 2.459; 95% CI: 1.360-4.447). CONCLUSION: MetS and its components, particularly abdominal obesity and hypertension, were found to be significantly associated with the risk of MCI.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Case-Control Studies; Chi-Square Distribution; China; Cities; Cognition Disorders; Community Health Planning; Female; Humans; Male; Mental Status Schedule; Metabolic Diseases; Risk Factors

Mild Cognitive Impairment and Susceptibility to Scams in Old Age. - Han, S Duke; Boyle, Patricia A; James, Bryan D; Yu, Lei; Bennett, David A (J Alzheimers Dis, 2016)
BACKGROUND: Falling victim to financial scams can have a significant impact upon social and financial wellbeing and independence. A large proportion of scam victims are older adults, but whether older victims with mild cognitive impairment (MCI) are at higher risk remains unknown. OBJECTIVE: We tested the hypothesis that older persons with MCI exhibit greater susceptibility to scams compared to those without cognitive impairment. METHODS: Seven hundred and thirty older adults without dementia were recruited from the Rush Memory and Aging Project, a community-based epidemiologic study of aging. Participants completed a five-item self-report measure of susceptibility to scams, a battery of cognitive measures, and clinical diagnostic evaluations. RESULTS: In models adjusted for age, education, and gender, the presence of MCI was associated with greater susceptibility to scams (B = 0.125, SE = 0.063, p-value = 0.047). Further, in analyses of the role of specific cognitive systems in susceptibility to scams among persons with MCI (n = 144), the level of performance in two systems, episodic memory and perceptual speed abilities, were associated with susceptibility. CONCLUSIONS: Adults with MCI may be more susceptible to scams in old age than older persons with normal cognition. Lower abilities in specific cognitive systems, particularly perceptual speed and episodic memory, may contribute to greater susceptibility to scams in those with MCI.
Keywords: Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; Crime Victims; Disease Susceptibility; Female; Humans; Male; Memory, Episodic; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Residence Characteristics; Self Report

Mini-Mental State Examination in Elderly Chinese: A Population-Based Normative Study. - Li, Hanzhi; Jia, Jianping; Yang, Zhiqiang (J Alzheimers Dis, 2016)
BACKGROUND: Chinese nationwide norms of the Mini-Mental State Examination (MMSE) have not been established despite its wide use. OBJECTIVE: To obtain norms for the MMSE based on age, gender, education, and rural or urban residences and to determine the optimal cut-off points of the MMSE in elderly Chinese. METHODS: A cross-sectional study was conducted in Chinese community residents aged 65 years or over selected by cluster random sampling. The MMSE was administered to 9,629 subjects (7,110 cognitively normal, 2,024 with mild cognitive impairment, and 495 with dementia). The demographic influences on MMSE scores were investigated and the norms were established considering those factors. Receiver operating characteristic (ROC) analysis was used to determine the optimal cut-off points. RESULTS: Years of education (standardized β= 0.399), rural residence (standardized β= -0.261), age (standardized β= -0.198), and being female (standardized β= -0.101) had significant effects on MMSE scores (p < 0.001). Accordingly, we presented the demographic-stratified normative data for the MMSE. The optimal cut-off points for dementia screening were 16/17 for illiterate (sensitivity 87.6% and specificity 80.8%), 19/20 for individuals with 1-6 years of education (sensitivity 93.6% and specificity 92.7%), and 23/24 for individuals with 7 or more years of education (sensitivity 94.3% and specificity 94.3%). CONCLUSION: We provide the age-, gender-, education-, and residence-specific reference norms for the MMSE derived from an investigation of a large-scale, multicenter, nationwide representative Chinese elderly population. It could be of great improvement for the use of the MMSE in dementia screening in Chinese elderly population.

"Missed" Mild Cognitive Impairment: High False-Negative Error Rate Based on Conventional Diagnostic Criteria. - Edmonds, Emily C; Delano-Wood, Lisa; Jak, Amy J; Galasko, Douglas R; Salmon, David P; Bondi, Mark W (J Alzheimers Dis, 2016)
Mild cognitive impairment (MCI) is typically diagnosed using subjective complaints, screening measures, clinical judgment, and a single memory score. Our prior work has shown that this method is highly susceptible to false-positive diagnostic errors. We examined whether the criteria also lead to "false-negative" errors by diagnostically reclassifying 520 participants using novel actuarial neuropsychological criteria. Results revealed a false-negative error rate of 7.1%. Participants' neuropsychological performance, cerebrospinal fluid biomarkers, and rate of decline provided evidence that an MCI diagnosis is warranted. The impact of "missed" cases of MCI has direct relevance to clinical practice, research studies, and clinical trials of prodromal Alzheimer's disease.

Moderate-to-High Intensity Physical Exercise in Patients with Alzheimer's Disease: A Randomized Controlled Trial. - Hoffmann, Kristine; Sobol, Nanna A; Frederiksen, Kristian S; Beyer, Nina; Vogel, Asmus; Vestergaard, Karsten; Brændgaard, Hans; Gottrup, Hanne; Lolk, Annette; Wermuth, Lene; Jacobsen, Søren; Laugesen, Lars P; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Studies of physical exercise in patients with Alzheimer's disease (AD) are few and results have been inconsistent. OBJECTIVE: To assess the effects of a moderate-to-high intensity aerobic exercise program in patients with mild AD. METHODS: In a randomized controlled trial, we recruited 200 patients with mild AD to a supervised exercise group (60-min sessions three times a week for 16 weeks) or to a control group. Primary outcome was changed from baseline in cognitive performance estimated by Symbol Digit Modalities Test (SDMT) in the intention-to-treat (ITT) group. Secondary outcomes included changes in quality of life, ability to perform activities of daily living, and in neuropsychiatric and depressive symptoms. RESULTS: The ITT analysis showed no significant differences between intervention and control groups in change from baseline of SDMT, other cognitive tests, quality of life, or activities of daily living. The change from baseline in Neuropsychiatric Inventory differed significantly in favor of the intervention group (mean: -3.5, 95% confidence interval (CI) -5.8 to -1.3, p = 0.002). In subjects who adhered to the protocol, we found a significant effect on change from baseline in SDMT as compared with the control group (mean: 4.2, 95% CI 0.5 to 7.9, p = 0.028), suggesting a dose-response relationship between exercise and cognition. CONCLUSIONS: This is the first randomized controlled trial with supervised moderate-to-high intensity exercise in patients with mild AD. Exercise reduced neuropsychiatric symptoms in patients with mild AD, with possible additional benefits of preserved cognition in a subgroup of patients exercising with high attendance and intensity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Depression; Exercise; Exercise Therapy; Female; Humans; Male; Middle Aged; Quality of Life; Treatment Outcome

Modulation of miR-19 in Aluminum-Induced Neural Cell Apoptosis. - Zhu, Mingming; Huang, Cong; Ma, Xiao; Wu, Rui; Zhu, Weiwei; Li, Xiaoting; Liang, Zhaofeng; Deng, Feifei; Zhu, Jianyun; Xie, Wei; Yang, Xue; Jiang, Ye; et al. (J Alzheimers Dis, 2016)
Neuronal cell death is an important feature of neurodegeneration. Aluminum is associated with neurodegenerative disorders, particularly Alzheimer's disease. However, the underlying mechanisms by which aluminum induces neuronal apoptosis remain to be elucidated. miR-19 is a key miRNA implicated in regulating cell survival process, while the role of miR-19 in Alzheimer's disease has not been investigated. In the present study, we showed that Aluminum maltolate (Al-malt), a lipophilic Al complex which is a common component of human diet with the ability to facilitate the entry of Al into the brain, induced apoptosis in human neuroblastoma SH-SY5Y cells, along with downregulation of miR-19a/miR-19b, upregulation of miR-19-targeted PTEN, and alterations of its downstream apoptosis related proteins including AKT, p53, Bax, and Bcl-2. miR-19 overexpression attenuated Al-malt-induced apoptosis as well as changes in the expression of apoptosis related proteins in SH-SY5Y cells. We further revealed that exposure of rats to Al-malt for 12 weeks at doses relevant to human exposure significantly elevated Al concentrations in serum and brain tissues. Al-malt dose-dependently induced apoptosis in rat brain, as evidenced by increased caspase activation and increased TUNEL staining. Consistent with in vitro results, Al-malt reduced miR-19 expression and altered the expression of apoptotic related proteins in rat brain. Taken together, our data suggest for the first time that miR-19 modulation is critically involved in Al-induced neural cell apoptosis. Findings from this study could provide new insight into the molecular mechanisms of Al-associated neurodegenerative pathogenesis.
Keywords: Aluminum; Animals; Apoptosis; Brain; Cell Line, Tumor; Dose-Response Relationship, Drug; Humans; Male; MicroRNAs; Neurons; Proto-Oncogene Proteins c-akt; PTEN Phosphohydrolase; Rats, Sprague-Dawley; Tumor Suppressor Protein p53

Molecular markers of amnestic mild cognitive impairment among Mexican Americans. - Edwards, Melissa; Hall, James; Williams, Benjamin; Johnson, Leigh; O'Bryant, Sid (J Alzheimers Dis, 2016)
BACKGROUND: Mexican Americans face a significant health disparity when it comes to Alzheimer's disease (AD) as they present with higher rates of the disease and develop AD at an earlier age compared to other ethnic groups. Recent work identified a proteomic profile of AD among this population; however, no work to date has sought to examine the biological profile of pre-AD among Mexican Americans. OBJECTIVE: This study aims to identify an amnestic mild cognitive impairment (aMCI) proteomic profile among Mexican Americans. METHODS: Data were analyzed from 284 Mexican American participants (aMCI, n = 73; normal controls, n = 211) from the Health & Aging Brain among Latino Elders study. Fasting serum samples were analyzed using a multi-plex biomarker assay platform. A biomarker profile was generated using random forest analyses. RESULTS: Among aMCI cases, the biomarker profile was found to be largely inflammatory with the top three markers shown to include TNFα, IL10, and TARC. The overall diagnostic accuracy of the biomarkers in detecting aMCI was 96% (sensitivity = 0.82; specificity = 0.97). Inclusion of clinical variables with the selected biomarkers did not impact the overall detection accuracy (area under the curve = 0.96) but led to a slight improvement in specificity (specificity = 0.99) and decrease in sensitivity (sensitivity = 0.74). CONCLUSION: The biomarker profile of aMCI was shown to be different from our previously generated AD profile among Mexican Americans, which was largely metabolic in nature. The findings implicate a possible interplay between inflammatory and metabolic processes and additional work is needed to further examine this.
Keywords: Aged; Alzheimer Disease; Area Under Curve; Biomarkers; Cognitive Dysfunction; Female; Humans; Male; Mexican Americans; Middle Aged; Neuropsychological Tests; Proteome; Sensitivity and Specificity; United States

Netrin-1 Interrupts Amyloid-β Amplification, Increases sAβPPα in vitro and in vivo, and Improves Cognition in a Mouse Model of Alzheimer's Disease. - Spilman, Patricia R; Corset, Veronique; Gorostiza, Olivia; Poksay, Karen S; Galvan, Veronica; Zhang, Junli; Rao, Rammohan; Peters-Libeu, Clare; Vincelette, Jon; McGeehan, Andrew; Dvorak-Ewell, Melita; Beyer, Janine; et al. (J Alzheimers Dis, 2016)
Recent studies have shown that inoculation of susceptible mice with amyloid-β (Aβ) peptides accelerates Aβ deposition in the brain, supporting the idea that Aβ may be self-amplifying; however, the exact mechanism is not understood. Here we provide evidence that Aβ may self-amplify, in part, by inhibiting α-secretase ADAM10 (a disintegrin and metalloprotease) cleavage of full-length Aβ precursor protein (FL AβPP) and therefore allow greater β-secretase processing, and that Aβ itself is a substrate for ADAM10. Exposure of primary neuronal cultures from PDAβPP mice to exogenous rat Aβ1- 40 resulted in increased de novo human Aβ1-42 production and exposure of cells to Aβ decreased production of ADAM10 cleavage product soluble AβPPα (sAβPPα). In a cell-free assay, Aβ decreased ADAM10 cleavage of the chimeric substrate MBP-AβPPC125 and Aβ itself was apparently cleaved by the enzyme. The axonal guidance and trophic factor netrin-1, however, reduced the Aβ1- 40-induced Aβ1-42 increase, increased sAβPPα, and reversed the Aβ-induced sAβPPα decrease in vitro. In vivo, induction of netrin-1 expression in PDAβPPSwe/Ind transgenic mice resulted in reductions in both Aβ1-42 and Aβ1- 40, and ICV delivery of netrin-1 to PDAβPPSwe/Ind mice increased sAβPPα, decreased Aβ, and improved working memory. Finally, to support further study of netrin-1's potential as a therapeutic for Alzheimer's disease, pilot gene therapy studies were performed and a netrin mimetic peptide synthesized and tested that, like netrin, can increase sAβPPα and decrease Aβ1-42in vitro. Taken together, these data provide mechanistic insights into Aβ self-amplification and the ability of netrin-1 to disrupt it.

Neurodegeneration-Like Pathological and Behavioral Changes in an AAV9-Mediated p25 Overexpression Mouse Model. - Zhou, Xiao; Huang, Jianou; Pan, Suyue; Xu, Miaojing; He, Rongni; Ji, Zhong; Hu, Yafang (J Alzheimers Dis, 2016)
BACKGROUND: The transgenic mice models overexpressing human p25 contribute greatly to the in vivo neurotoxic mechanism of p25 in neurodegenerative diseases. However, it is time-consuming to manipulate existing transgenic mice models. OBJECTIVE: Here we aim to establish a novel mouse model of neurodegeneration by overexpressing p25 mediated by recombinant adeno-associated virus serotype 9 (rAAV9). METHODS: AAV9-GFP-p25 encoding GFP-fused p25 driven by synapsin promoter, and the control, AAV9-GFP, were delivered in mice by tail-vein injection. Assessments of p25 expression, neurodegenerative pathology, and behavioral changes were performed. RESULTS: GFP expression was detected by in vivo imaging as early as one week after virus injection. Notably, widespread expression of p25 was obviously found in cortex, hippocampus, and cerebellum in AAV9-GFP-p25 mice. Moreover, decreased hippocampus volumes in AAV9-GFP-p25 mice were detected by 7T MRI examination about one month after injection. Further, these AAV9-GFP-p25 mice exhibited progressive memory impairment from three-month to six-month after virus injection. At last, hyperphosphorylated tau, neurofibrillary tangles, activated astrocytes and microglia cells were elevated in these p25 mice at about six months after virus delivery. However, amyloid-β plaques, overt neuronal loss, and apoptosis in the hippocampus and cortex were not significantly induced by AAV9-mediated p25 overexpression. CONCLUSION: The AAV9-mediated p25 overexpression mouse model, which is a practical model exhibiting neurodegeneration-like pathological and behavioral changes, provides an easier and time-saving method to explore the functions of p25 in vivo, as well as an alternative tool for development of drugs against neurotoxic of p25.

Omega-3 Fatty Acid Status Enhances the Prevention of Cognitive Decline by B Vitamins in Mild Cognitive Impairment. - Oulhaj, Abderrahim; Jernerén, Fredrik; Refsum, Helga; Smith, A David; de Jager, Celeste A (J Alzheimers Dis, 2016)
A randomized trial (VITACOG) in people with mild cognitive impairment (MCI) found that B vitamin treatment to lower homocysteine slowed the rate of cognitive and clinical decline. We have used data from this trial to see whether baseline omega-3 fatty acid status interacts with the effects of B vitamin treatment. 266 participants with MCI aged ≥70 years were randomized to B vitamins (folic acid, vitamins B6 and B12) or placebo for 2 years. Baseline cognitive test performance, clinical dementia rating (CDR) scale, and plasma concentrations of total homocysteine, total docosahexaenoic and eicosapentaenoic acids (omega-3 fatty acids) were measured. Final scores for verbal delayed recall, global cognition, and CDR sum-of-boxes were better in the B vitamin-treated group according to increasing baseline concentrations of omega-3 fatty acids, whereas scores in the placebo group were similar across these concentrations. Among those with good omega-3 status, 33% of those on B vitamin treatment had global CDR scores >0 compared with 59% among those on placebo. For all three outcome measures, higher concentrations of docosahexaenoic acid alone significantly enhanced the cognitive effects of B vitamins, while eicosapentaenoic acid appeared less effective. When omega-3 fatty acid concentrations are low, B vitamin treatment has no effect on cognitive decline in MCI, but when omega-3 levels are in the upper normal range, B vitamins interact to slow cognitive decline. A clinical trial of B vitamins combined with omega-3 fatty acids is needed to see whether it is possible to slow the conversion from MCI to AD.
Keywords: Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Disease Progression; Fatty Acids, Omega-3; Female; Humans; Male; Neuropsychological Tests; Treatment Outcome; Vitamin B Complex

Optimized Standard Operating Procedures for the Analysis of Cerebrospinal Fluid Aβ42 and the Ratios of Aβ Isoforms Using Low Protein Binding Tubes. - Vanderstichele, Hugo Marcel Johan; Janelidze, Shorena; Demeyer, Leentje; Coart, Els; Stoops, Erik; Herbst, Victor; Mauroo, Kimberley; Brix, Britta; Hansson, Oskar (J Alzheimers Dis, 2016)
BACKGROUND: Reduced cerebrospinal fluid (CSF) concentration of amyloid-β1-42 (Aβ1-42) reflects the presence of amyloidopathy in brains of subjects with Alzheimer's disease (AD). OBJECTIVE: To qualify the use of Aβ1-42/Aβ1-40 for improvement of standard operating procedures (SOP) for measurement of CSF Aβ with a focus on CSF collection, storage, and analysis. METHODS: Euroimmun ELISAs for CSF Aβ isoforms were used to set up a SOP with respect to recipient properties (low binding, polypropylene), volume of tubes, freeze/thaw cycles, addition of detergents (Triton X-100, Tween-20) in collection or storage tubes or during CSF analysis. Data were analyzed with linear repeated measures and mixed effects models. RESULTS: Optimization of CSF analysis included a pre-wash of recipients (e.g., tubes, 96-well plates) before sample analysis. Using the Aβ1-42/Aβ1-40 ratio, in contrast to Aβ1-42, eliminated effects of tube type, additional freeze/thaw cycles, or effect of CSF volumes for polypropylene storage tubes. 'Low binding' tubes reduced the loss of Aβ when aliquoting CSF or in function of additional freeze/thaw cycles. Addition of detergent in CSF collection tubes resulted in an almost complete absence of variation in function of collection procedures, but affected the concentration of Aβ isoforms in the immunoassay. CONCLUSION: The ratio of Aβ1-42/Aβ1-40 is a more robust biomarker than Aβ1-42 toward (pre-) analytical interfering factors. Further, 'low binding' recipients and addition of detergent in collection tubes are able to remove effects of SOP-related confounding factors. Integration of the Aβ1-42/Aβ1-40 ratio and 'low-binding tubes' into guidance criteria may speed up worldwide standardization of CSF biomarker analysis.

An Oral Aβ Vaccine Using a Recombinant Adeno-Associated Virus Vector in Aged Monkeys: Reduction in Plaque Amyloid and Increase in Aβ Oligomers. - Hara, Hideo; Ono, Fumiko; Nakamura, Shinichiro; Matsumoto, Shin-Ei; Jin, Haifeng; Hattori, Nobutaka; Tabira, Takeshi (J Alzheimers Dis, 2016)
With the objective to improve the amyloid-β (Aβ) targeting immunotherapy, we investigated the safety and efficacy of an oral vaccine with recombinant adeno-associated virus vector carrying a signal sequence and Aβ1-43 cDNA (rAAV/Aβ) in old non-human primates, 12 African green and 10 cynomolgus monkeys. The enteric-dissolving coated capsules containing rAAV/Aβ were orally administered once or twice, then monkeys' conditions were carefully observed with complete blood count and laboratory examinations of the sera. General conditions, food intake, water intake, stool conditions, body weight changes, and menstruation cycles were not significantly altered, and laboratory tests and pathological examinations of the systemic organs were unremarkable. Pathological examinations of the brain showed significant reduction of the amyloid plaque burden and intracellular Aβ without inflammatory or hemorrhagic changes in the brain. However, soluble Aβ and some Aβ oligomers were increased in rAAV-treated monkey brains without changes of the neuronal density and vascular amyloidosis. Thus, this vaccine seems to be safe in general, but we must be cautious about the increase of Aβ oligomers after vaccination. This vaccine may be recommended at a very early stage of Alzheimer's disease when little amyloid is deposited.

Oral Infections and Cytokine Levels in Patients with Alzheimer's Disease and Mild Cognitive Impairment Compared with Controls. - Cestari, José Augusto Ferrari; Fabri, Gisele Maria Campos; Kalil, Jorge; Nitrini, Ricardo; Jacob-Filho, Wilson; de Siqueira, José Tadeu Tesseroli; Siqueira, Silvia Regina D T (J Alzheimers Dis, 2016)
BACKGROUND: Oral infections are prevalent in the adult population. Their impact includes the implication as a risk factor for Alzheimer's disease (AD), altering its progression. One of the potential mechanisms involves immune mediators such as circulating cytokines. OBJECTIVE: The goal of the present study was to investigate the prevalence of oral infections and blood levels of IL-1β, TNF-α, and IL-6 in patients with AD, mild cognitive impairment (MCI), and controls. METHODS: Sixty-five elderly were evaluated (25 AD, 19 MCI, and 21 controls) by the following methods: Mini Mental State Exam, Questionnaire of Functional Activities, periodontal and oral evaluation, and blood concentrations of IL-1β, TNF-α and IL-6. RESULTS: Patients with AD had high serum IL-6 levels (p = 0.029), and patients with periodontitis had high serum TNF-α levels (p = 0.005). There was an association between IL-6 and TNF-α in patients with AD/MCI and periodontitis (p = 0.023). CONCLUSION: The increased levels of TNF-α and IL-6 in this study suggests their implication in the overlapping mechanisms between oral infections and AD. Longitudinal studies are necessary for further investigation.

A Pathway Based Classification Method for Analyzing Gene Expression for Alzheimer's Disease Diagnosis. - Voyle, Nicola; Keohane, Aoife; Newhouse, Stephen; Lunnon, Katie; Johnston, Caroline; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Hodges, Angela; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies indicate that gene expression levels in blood may be able to differentiate subjects with Alzheimer's disease (AD) from normal elderly controls and mild cognitively impaired (MCI) subjects. However, there is limited replicability at the single marker level. A pathway-based interpretation of gene expression may prove more robust. OBJECTIVES: This study aimed to investigate whether a case/control classification model built on pathway level data was more robust than a gene level model and may consequently perform better in test data. The study used two batches of gene expression data from the AddNeuroMed (ANM) and Dementia Case Registry (DCR) cohorts. METHODS: Our study used Illumina Human HT-12 Expression BeadChips to collect gene expression from blood samples. Random forest modeling with recursive feature elimination was used to predict case/control status. Age and APOE ɛ4 status were used as covariates for all analysis. RESULTS: Gene and pathway level models performed similarly to each other and to a model based on demographic information only. CONCLUSIONS: Any potential increase in concordance from the novel pathway level approach used here has not lead to a greater predictive ability in these datasets. However, we have only tested one method for creating pathway level scores. Further, we have been able to benchmark pathways against genes in datasets that had been extensively harmonized. Further work should focus on the use of alternative methods for creating pathway level scores, in particular those that incorporate pathway topology, and the use of an endophenotype based approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Cohort Studies; Datasets as Topic; Female; Gene Expression; Gene Expression Profiling; Humans; Male; Models, Genetic; Oligonucleotide Array Sequence Analysis; Signal Transduction

Pauses During Autobiographical Discourse Reflect Episodic Memory Processes in Early Alzheimer's Disease. - Pistono, Aurélie; Jucla, Mélanie; Barbeau, Emmanuel J; Saint-Aubert, Laure; Lemesle, Béatrice; Calvet, Benjamin; Köpke, Barbara; Puel, Michèle; Pariente, Jérémie (J Alzheimers Dis, 2016)
There is a large body of research on discourse production in Alzheimer's disease (AD). Some studies have focused on pause production, revealing that patients make extensive use of pauses during speech. This has been attributed to lexical retrieval difficulties, but pausing may also reflect other forms of cognitive impairment as it increases with cognitive load. The aim of the present study was to analyze autobiographical discourse impairment in AD from a broad perspective, looking at pausing behavior (frequency, duration, and location). Our first objective was to characterize discourse changes in mild cognitive impairment (MCI) due to AD. Our second objective was to determine the cognitive and neuroanatomical correlates of these changes. Fifteen patients with MCI due to AD and 15 matched cognitively normal controls underwent an ecological episodic memory task, a full neuropsychological assessment, and a 3D T1-weighted MRI scans. Autobiographical discourse collected from the ecological episodic memory task was recorded, transcribed, and analyzed, focusing on pausing. Intergroup comparisons showed that although patients did not produce more pauses than controls overall, they did make more between-utterance pauses. The number of these specific pauses was positively correlated with patients' episodic memory performance. Furthermore, neuroimaging analysis showed that, in the patient group, their use was negatively correlated with frontopolar area (BA 10) grey matter density. This region may therefore play an important role in the planning of autobiographical discourse production. These findings demonstrate that pauses in early AD may reflect a compensatory mechanism for improving mental time travel and memory retrieval.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Brain; Female; Humans; Male; Memory Disorders; Memory, Episodic; Mental Status Schedule; Neuropsychological Tests; Positron-Emission Tomography; Statistics as Topic

PiB-PET Imaging-Based Serum Proteome Profiles Predict Mild Cognitive Impairment and Alzheimer's Disease. - Kang, Seokjo; Jeong, Hyobin; Baek, Je-Hyun; Lee, Seung-Jin; Han, Sun-Ho; Cho, Hyun Jin; Kim, Hee; Hong, Hyun Seok; Kim, Young Ho; Yi, Eugene C; Seo, Sang Won; Na, Duk L; et al. (J Alzheimers Dis, 2016)
Development of a simple, non-invasive early diagnosis platform of Alzheimer's disease (AD) using blood is urgently required. Recently, PiB-PET imaging has been shown to be powerful to quantify amyloid-β plaque loads leading to pathophysiological alterations in AD brains. Thus, there has been a need for serum biomarkers reflecting PiB-PET imaging data as an early diagnosis platform of AD. Here, using LC-MS/MS analysis coupled with isobaric tagging, we performed comprehensive proteome profiling of serum samples from cognitively normal controls, mild cognitive impairment (MCI), and AD patients, who were selected using PiB-PET imaging. Comparative analysis of the proteomes revealed 79 and 72 differentially expressed proteins in MCI and AD, respectively, compared to controls. Integrated analysis of these proteins with genomic and proteomic data of AD brain tissues, together with network analysis, identified three biomarker candidates representing the altered proteolysis-related process in MCI or AD: proprotein convertase subtilisin/kexin type 9 (PCSK9), coagulation factor XIII, A1 polypeptide (F13A1), and dermcidin (DCD). In independent serum samples of MCI and AD, we confirmed the elevation of the candidates using western blotting and ELISA. Our results suggest that these biomarker candidates can serve as a potential non-invasive early diagnosis platform reflecting PiB-PET imaging for MCI and AD.

Plasma Ceramides and Neuropsychiatric Symptoms of Alzheimer's Disease. - Xing, Yi; Tang, Yi; Zhao, Lina; Wang, Qi; Qin, Wei; Zhang, Jin-Lan; Jia, Jianping (J Alzheimers Dis, 2016)
BACKGROUND: Various evidence demonstrates the influences of ceramides on Alzheimer's disease (AD) pathogenesis. Furthermore, increased ceramides were also suggested to be related to cognitive decline. However, the association between ceramides and neuropsychiatric symptoms of AD remains unclear. OBJECTIVE: This study sought to investigate the association between plasma ceramide levels and multiple neuropsychiatric symptoms in AD. METHODS: A total of 98 patients and 92 cognitively normal controls participated in this study, including 56 with mild AD and 42 with moderate to severe AD. The Neuropsychiatric Inventory (NPI) was used to assess neuropsychiatric symptoms. Considering the influences of dementia severity on ceramide levels and neuropsychiatric symptoms, a subgroup analysis was conducted by dementia severity. RESULTS: Except for C24 : 0, all ceramide species were significantly higher in AD patients than in controls. After controlling for confounding factors, the C16 : 0 and C20 : 0 levels were positively associated with delusions, and the quartiles of C22 : 0 and C24 : 0 were positively associated with depression. In the subgroup analysis, association between ceramide species and delusions were only observed in mild AD, and the association between ceramides and depression were prominent in moderate to severe AD. In mild AD, after controlling for age, gender, anti-dementia medications, diabetes status, and ApoE ɛ4 status, the C16 : 0, C20 : 0, and quartiles of C24 : 1 were associated with delusions. In moderate to severe AD, depression was associated with C22 : 0 and C24 : 0. CONCLUSION: There were stage-specific associations between ceramides and neuropsychiatric symptoms of AD. The potential mechanisms deserve further investigation.

Plasma Phospholipid and Sphingolipid Alterations in Presenilin1 Mutation Carriers: A Pilot Study. - Chatterjee, Pratishtha; Lim, Wei L F; Shui, Guanghou; Gupta, Veer B; James, Ian; Fagan, Anne M; Xiong, Chengjie; Sohrabi, Hamid R; Taddei, Kevin; Brown, Belinda M; Benzinger, Tammie; Masters, Colin; et al. (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: Aberrant lipid metabolism has been implicated in sporadic Alzheimer's disease (AD). The current study investigated plasma phospholipid and sphingolipid profiles in individuals carrying PSEN1 mutations responsible for autosomal dominant AD (ADAD). METHODS: Study participants evaluated were from the Perth and Melbourne sites of the Dominantly Inherited Alzheimer Network (DIAN) study. Plasma phospholipid and sphingolipid profiles were measured using liquid chromatography coupled with mass spectrometry in 20 PSEN1 mutation carriers (MC; eight of whom were symptomatic and twelve asymptomatic, based on Clinical Dementia Rating scores) and compared with six non carriers (NC) using linear mixed models. Further, AD gold standard biomarker data obtained from the DIAN database were correlated with lipid species significantly altered between MC and NC, using Spearman's correlation coefficient. RESULTS: One-hundred and thirty-nine plasma phospholipid and sphingolipid species were measured. Significantly altered species in MC compared to NC primarily belonged to choline and ethanolamine containing phospholipid classes and ceramides. Further phosphatidylcholine species (34:6, 36:5, 40:6) correlated with cerebrospinal fluid tau (p <  0.05), and plasmalogen ethanolamine species (34:2, 36:,4) correlated with both cerebrospinal fluid tau and brain amyloid load within the MC group (p <  0.05). CONCLUSION: These findings indicate altered phospholipid and sphingolipid metabolism in ADAD and provide insight into the pathomolecular changes occurring with ADAD pathogenesis. Further, findings reported in this study allow comparison of lipid alterations in ADAD with those reported previously in sporadic AD. The findings observed in the current pilot study warrant validation in the larger DIAN cohort.
Keywords: Adult; Alzheimer Disease; Apolipoproteins E; Female; Humans; Linear Models; Male; Middle Aged; Mutation; Phospholipids; Pilot Projects; Presenilin-1; Sphingolipids

Platelet Membrane β-Secretase Activity in Mild Cognitive Impairment and Conversion to Dementia: a Longitudinal Study. - McGuinness, Bernadette; Fuchs, Marc; Barrett, Suzanne L; Passmore, A Peter; Johnston, Janet A (J Alzheimers Dis, 2016)
A blood-based biomarker to complement the clinical and neuropsychological assessments used to evaluate the risk of individuals with mild cognitive impairment (MCI) developing Alzheimer's disease (AD) would be invaluable. Previous pilot studies by our group identified elevated platelet membrane β-secretase activity in patients with AD and MCI, as compared to controls, and this activity was influenced by membrane cholesterol levels. The present study investigated baseline platelet membrane β-secretase activity and cholesterol levels in 97 MCI participants and 85 controls and explored whether these parameters differed in individuals with stable MCI, as compared to those who subsequently developed AD. To evaluate signal specificity, β-secretase activity assays were conducted in the presence and absence of beta-site amyloid-β protein precursor-cleaving enzyme (BACE) inhibitors. Baseline platelet membrane β-secretase activity did not differ significantly in MCI participants, as compared to controls, and platelet membrane cholesterol levels were significantly lower in the MCI group. The longitudinal study indicated that the activities inhibited by two different BACE inhibitors did not predict conversion to AD; however, the activity that was not affected by BACE inhibitors was significantly (40%) higher in individuals with stable MCI, as compared with those who subsequently developed AD. These findings indicated that further research into the source of this activity could contribute to a measure facilitating prediction of the risk of conversion from MCI to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid Precursor Protein Secretases; Biomarkers; Blood Platelets; Cholesterol; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged; Neuropsychological Tests; Sensitivity and Specificity

Posterior Accumulation of Tau and Concordant Hypometabolism in an Early-Onset Alzheimer's Disease Patient with Presenilin-1 Mutation. - Smith, Ruben; Wibom, Moa; Olsson, Tomas; Hägerström, Douglas; Jögi, Jonas; Rabinovici, Gil D; Hansson, Oskar (J Alzheimers Dis, 2016)
It is unclear whether the distribution of tau pathology differs between cases with early-onset familial Alzheimer's disease (AD) and sporadic AD. We present positron emission tomography (PET) data from a young patient with a presenilin-1 mutation (Thr116Asn). 18F-flutemetamol PET showed a distribution of amyloid-β fibrils similar to sporadic AD. However, the pattern of tau pathology, revealed using 18F-AV1451 PET, showed higher uptake in posterior cingulate, precuneus, parietal and occipital cortices compared to late-onset sporadic AD. Further, the tau pathology, but not amyloid pathology, exhibited a very clear inverse relationship with 18F-fluorodeoxyglucose-metabolism, indicating neuronal hypometabolism in regions affected by tau aggregates.
Keywords: Adult; Age of Onset; Alzheimer Disease; Amyloid beta-Peptides; Aniline Compounds; Benzothiazoles; Brain; Brain Mapping; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Positron-Emission Tomography; Presenilin-1; Radiopharmaceuticals; tau Proteins

Preliminary Study of Plasma Exosomal Tau as a Potential Biomarker for Chronic Traumatic Encephalopathy. - Stern, Robert A; Tripodis, Yorghos; Baugh, Christine M; Fritts, Nathan G; Martin, Brett M; Chaisson, Christine; Cantu, Robert C; Joyce, James A; Shah, Sahil; Ikezu, Tsuneya; Zhang, Jing; Gercel-Taylor, Cicek; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Chronic traumatic encephalopathy (CTE) is a tauopathy associated with prior exposure to repetitive head impacts, such as those incurred through American football and other collision sports. Diagnosis is made through neuropathological examination. Many of the clinical features of CTE are common in the general population, with and without a history of head impact exposure, making clinical diagnosis difficult. As is now common in the diagnosis of other neurodegenerative disorders, such as Alzheimer's disease, there is a need for methods to diagnose CTE during life through objective biomarkers. OBJECTIVE: The aim of this study was to examine tau-positive exosomes in plasma as a potential CTE biomarker. METHODS: Subjects were 78 former National Football League (NFL) players and 16 controls. Extracellular vesicles were isolated from plasma. Fluorescent nanoparticle tracking analysis was used to determine the number of vesicles staining positive for tau. RESULTS: The NFL group had higher exosomal tau than the control group (p <  0.0001). Exosomal tau discriminated between the groups, with 82% sensitivity, 100% specificity, 100% positive predictive value, and 53% negative predictive value. Within the NFL group, higher exosomal tau was associated with worse performance on tests of memory (p = 0.0126) and psychomotor speed (p = 0.0093). CONCLUSION: These preliminary findings suggest that exosomal tau in plasma may be an accurate, noninvasive CTE biomarker.
Keywords: Adult; Aged; Analysis of Variance; Case-Control Studies; Chronic Traumatic Encephalopathy; Extracellular Vesicles; Humans; Male; Middle Aged; Plasma; tau Proteins

Primary Progressive Aphasia in the Network of French Alzheimer Plan Memory Centers. - Magnin, Eloi; Démonet, Jean-François; Wallon, David; Dumurgier, Julien; Troussière, Anne-Cécile; Jager, Alain; Duron, Emmanuelle; Gabelle, Audrey; de la Sayette, Vincent; Volpe-Gillot, Lisette; Tio, Gregory; Evain, Sarah; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Few demographical data about primary progressive aphasia (PPA) are available, and most knowledge regarding PPA is based on tertiary centers' results. OBJECTIVE: Our aims were to describe demographical characteristics of the PPA population in a large sample of PPA patients from the network of French Alzheimer plan memory centers (Sample 1), and to describe the stratification of cerebrospinal fluid (CSF) biomarkers in two different samples of PPA patients (Samples 2 and 3). METHODS: All registered PPA patients in the French Alzheimer's disease (AD) databank (Sample 1: n = 2,035) and a subsample (Sample 2: n = 65) derived from a multicentric prospective cohort with CSF biomarker analysis were analyzed. A multicentric retrospective cohort from language expert tertiary centers (Sample 3: n = 97) with CSF biomarker analysis was added. Sample 3 was added to replicate the CSF results of the Sample 2 and to evaluate repartition of AD pathology in the three variant of PPA according to the latest classification. RESULTS: Non-Fluent/Agrammatic, Logopenic, and Unclassifiable PPA patients (NF/A-Logo-Unclass PPA) were older and more frequent than Semantic PPA patients (2.2 versus 0.8/100,000 inhabitants; p < 0.00001). Male predominance occurred after the age of 80 (p < 0.00001). A higher level of education was observed in the PPA population compared to a typical amnesic AD group. No demographical significant difference between PPA due to AD and not due to AD was observed. The Logopenic variant was most frequent with 85% of AD CSF biomarker profiles (35% in NF/A PPA; 20% in Semantic PPA). CONCLUSION: PPA occurs also in an elderly population, especially in male patients over 80. CSF biomarkers are useful to stratify PPA. The epidemiology of PPA should be further investigated to confirm gender and cognitive reserve role in PPA to better understand the factors and mechanisms leading to this language-predominant deficit during neurodegenerative diseases.

Primary Progressive Orofacial Apraxia: A Ten-Year Long Follow-Up Case Report. - Trebbastoni, Alessandro; D'Antonio, Fabrizia; de Lena, Carlo; Onesti, Emanuela; John, Bev; Inghilleri, Maurizio (J Alzheimers Dis, 2016)
Orofacial apraxia (OA) as the main symptom in neurodegenerative disorders has not been yet reported. We present the case of a woman with a 22-month long history of isolated OA, studied with cerebrospinal fluid biomarkers and repeated clinical, neuropsychological, and morpho-functional evaluations. Baseline morpho-functional neuroimages revealed a left frontal operculum hypoperfusion with a widespread fronto-temporal involvement at follow-up. Cerebrospinal fluid concentrations of tau and amyloid-β were normal. The ten-year long clinical observation disclosed progressive OA worsening and the late onset of frontal functions impairment and extrapyramidal signs. The early and late stages of a neurodegenerative syndrome with OA as the main clinical feature were characterized.

Prolonged Visual Facial Grasp in Frontotemporal Dementia. - Paholpak, Pongsatorn; Li-Jung, Liang; Carr, Drew R; Jimenez, Elvira; Barrows, Robin J; Sabodash, Valeiry; Mendez, Mario F (J Alzheimers Dis, 2016)
BACKGROUND: Gaze and eye contact is a critical aspect of social interaction. Patients with behavioral variant frontotemporal dementia (bvFTD) may exhibit abnormally prolonged stare toward human faces. OBJECTIVE: To study characteristics of social gaze in patients with bvFTD compared to age and education matched-patients with early-onset Alzheimer's disease (eAD) and healthy controls (HC). METHOD: Fifty picture stimuli were presented to each participant (bvFTD = 12, eAD = 18, HC = 13). Each stimuli contained two properties: face (facial versus non-facial) and valence (positive, negative, and neutral). The "facial" stimuli contained human faces. The participants Visual Fixation Time (VFT) was measured for each picture stimuli of interest (per facial expressions on the Facial Action Coding System). A linear mixed-effects regression model with participant-level of random effects was used to compare VFTs between groups. RESULTS: The patients with bvFTD showed significantly prolonged VFTs to faces than the patients with eAD and the HC, regardless of valence (all p < 0.01). There were no differences in VFTs for non-facial stimuli between patients with bvFTD and eAD. However, patients with bvFTD and eAD had significantly prolonged VFTs to negative non-facial stimuli than the HC (p = 0.006 and 0.019, respectively). CONCLUSION: Patients with bvFTD exhibited a prolonged stare toward human faces. This prolonged visual facial grasp may contribute to the disturbed social interactions of patients with bvFTD and can help distinguish them from those with Alzheimer's disease and other conditions. Additionally, both dementia groups tended to stare at negative stimuli whether faces or non-faces.

Psychotropic Drug Prescription in Patients with Dementia: Nursing Home Residents Versus Patients Living at Home. - Jacquin-Piques, Agnès; Sacco, Guillaume; Tavassoli, Neda; Rouaud, Olivier; Bejot, Yannick; Giroud, Maurice; Robert, Philippe; Vellas, Bruno; Bonin-Guillaume, Sylvie (J Alzheimers Dis, 2016)
BACKGROUND: Psychotropic drugs are frequently prescribed in nursing homes (NH). Nonetheless, we hoped that institutionalization decreases the number of psychotropic drug classes prescribed, because NH residents may have more psychosocial interventions than patients living at home. OBJECTIVE: The aim was to compare the type and number of psychotropic drugs prescribed in elderly NH residents with dementia with those in community-living patients. METHODS: This cross-sectional study included elderly patients (at least 75 years old) with dementia recorded in the National Alzheimer's data Bank ("Banque Nationale Alzheimer") during the year 2012 and who were taking at least one psychotropic drug. Psychotropic drugs were classified as follows: antidepressant, anxiolytic, hypnotic, and antipsychotic drugs. Patients were classified into three categories of dementia severity according to the MMSE score. RESULTS: Among the 50,932 patients with dementia recorded in the BNA, 40.1% had at least one psychotropic drug prescribed. Most of the patients who were treated by at least one psychotropic drug class had antidepressant therapy (69.0%), whatever their residence type, and 16.1% were treated with antipsychotics. Among the study population, 51.9% of the NH residents and 67.4% of the patients living at home had only one psychotropic drug class prescribed. Living in a NH was significantly associated with the more frequent prescription of anxiolytic, hypnotic, and antipsychotic drugs, and with a greater number of psychotropic drug classes prescribed, whatever the severity of the dementia. CONCLUSION: We underlined the more frequent prescription of psychotropic drugs in NH residents regardless of MMSE scores.
Keywords: Aged; Aged, 80 and over; Chi-Square Distribution; Cross-Sectional Studies; Databases, Factual; Dementia; Drug Prescriptions; Female; Humans; Male; Nursing Homes; Psychotropic Drugs; Residence Characteristics

A Qualitative Impairment in Face Perception in Alzheimer's Disease: Evidence from a Reduced Face Inversion Effect. - Lavallée, Marie Maxime; Gandini, Delphine; Rouleau, Isabelle; Vallet, Guillaume T; Joannette, Maude; Kergoat, Marie-Jeanne; Busigny, Thomas; Rossion, Bruno; Joubert, Sven (J Alzheimers Dis, 2016)
Prevalent face recognition difficulties in Alzheimer's disease (AD) have typically been attributed to the underlying episodic and semantic memory impairment. The aim of the current study was to determine if AD patients are also impaired at the perceptual level for faces, more specifically at extracting a visual representation of an individual face. To address this question, we investigated the matching of simultaneously presented individual faces and of other nonface familiar shapes (cars), at both upright and inverted orientation, in a group of mild AD patients and in a group of healthy older controls matched for age and education. AD patients showed a reduced inversion effect (i.e., larger performance for upright than inverted stimuli) for faces, but not for cars, both in terms of error rates and response times. While healthy participants showed a much larger decrease in performance for faces than for cars with inversion, the inversion effect did not differ significantly for faces and cars in AD. This abnormal inversion effect for faces was observed in a large subset of individual patients with AD. These results suggest that AD patients have deficits in higher-level visual processes, more specifically at perceiving individual faces, a function that relies on holistic representations specific to upright face stimuli. These deficits, combined with their memory impairment, may contribute to the difficulties in recognizing familiar people that are often reported in patients suffering from the disease and by their caregivers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Face; Facial Recognition; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Orientation; Pattern Recognition, Visual; Perceptual Disorders; Photic Stimulation; Psychiatric Status Rating Scales; Reaction Time; Statistics as Topic

Reliability and Validity of a Novel Internet-Based Battery to Assess Mood and Cognitive Function in the Elderly. - Myers, Candice A; Keller, Jeffrey N; Allen, H Raymond; Brouillette, Robert M; Foil, Heather; Davis, Allison B; Greenway, Frank L; Johnson, William D; Martin, Corby K (J Alzheimers Dis, 2016)
Dementia is a chronic condition in the elderly and depression is often a concurrent symptom. As populations continue to age, accessible and useful tools to screen for cognitive function and its associated symptoms in elderly populations are needed. The aim of this study was to test the reliability and validity of a new internet-based assessment battery for screening mood and cognitive function in an elderly population. Specifically, the Helping Hand Technology (HHT) assessments for depression (HHT-D) and global cognitive function (HHT-G) were evaluated in a sample of 57 elderly participants (22 male, 35 female) aged 59-85 years. The study sample was categorized into three groups: 1) dementia (n = 8; Mini-Mental State Exam (MMSE) score 10-24), 2) mild cognitive impairment (n = 24; MMSE score 25-28), and 3) control (n = 25; MMSE score 29-30). Test-retest reliability (Pearson correlation coefficient, r) and internal consistency reliability (Cronbach's alpha, α) of the HHT-D and HHT-G were assessed. Validity of the HHT-D and HHT-G was tested via comparison (Pearson r) to commonly used pencil-and-paper based assessments: HHT-D versus the Geriatric Depression Scale (GDS) and HHT-G versus the MMSE. Good test-retest (r = 0.80; p < 0.0001) and acceptable internal consistency reliability (α= 0.73) of the HHT-D were established. Moderate support for the validity of the HHT-D was obtained (r = 0.60 between the HHT-D and GDS; p < 0.0001). Results indicated good test-retest (r = 0.87; p < 0.0001) and acceptable internal consistency reliability (α= 0.70) of the HHT-G. Validity of the HHT-G was supported (r = 0.71 between the HHT-G and MMSE; p < 0.0001). In summary, the HHT-D and HHT-G were found to be reliable and valid computerized assessments to screen for depression and cognitive status, respectively, in an elderly sample.

The Role of Alzheimer's and Cerebrovascular Pathology in Mediating the Effects of Age, Race, and Apolipoprotein E Genotype on Dementia Severity in Pathologically-Confirmed Alzheimer's Disease. - Gavett, Brandon E; John, Samantha E; Gurnani, Ashita S; Bussell, Cara A; Saurman, Jessica L (J Alzheimers Dis, 2016)
BACKGROUND: Dementia severity can be modeled as the construct δ, representing the "cognitive correlates of functional status." OBJECTIVE: We recently validated a model for estimating δ in the National Alzheimer's Coordinating Center's Uniform Data Set; however, the association of δ with neuropathology remains untested. METHODS: We used data from 727 decedents evaluated at Alzheimer's Disease (AD) Centers nationwide. Participants spoke English, had no genetic abnormalities, and were pathologically diagnosed with AD as a primary or contributing etiology. Clinical data from participants' last visit prior to death were used to estimate dementia severity (δ). RESULTS: A structural equation model using age, education, race, and apolipoprotein E (APOE) genotype (number of ɛ2 and ɛ4 alleles) as predictors and latent AD pathology and cerebrovascular disease (CVD) pathology as mediators fit the data well (RMSEA = 0.031; CFI = 0.957). AD pathology mediated the effects of age and APOE genotype on dementia severity. An older age at death and more ɛ2 alleles were associated with less AD pathology and, in turn, with less severe dementia. In contrast, more ɛ4 alleles were associated with more pathology and more severe dementia. Although age and race contributed to differences in CVD pathology, CVD pathology was not related to dementia severity in this sample of decedents with pathologically-confirmed AD. CONCLUSIONS: Using δ as an estimate of dementia severity fits well within a structural model in which AD pathology directly affects dementia severity and mediates the relationship between age and APOE genotype on dementia severity.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Apolipoproteins E; Cerebrovascular Disorders; Continental Population Groups; Dementia; Educational Status; Female; Genotype; Humans; Male; Mental Status Schedule; Middle Aged; Models, Theoretical

The Role of Cerebrovascular Disease in Amyloid Deposition. - Noh, Young; Seo, Sang Won; Jeon, Seun; Lee, Jong Min; Kim, Jae Seung; Lee, Jae-Hong; Kim, Jung-Hyun; Kim, Geon Ha; Ye, Byoung Seok; Cho, Hanna; Kim, Hee Jin; Yoon, Cindy W; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Some patients clinically diagnosed with subcortical vascular cognitive impairment (SVCI) have co-morbidity with AD pathology. OBJECTIVE: We investigated topographical differences in amyloid burden between SVCI and Alzheimer's disease type cognitive impairment (ADCI) using [11C] Pittsburgh compound B (PiB) positron emission tomography (PET). The purpose of this study was to investigate the role of cerebrovascular disease (CVD) in amyloid deposition. METHODS: We recruited 44 patients with SVCI and 44 patients with ADCI (amnestic mild cognitive impairment or Alzheimer's disease) with absent or minimal white matter hyperintensities, all with PiB-positive PET scans [PiB+]. As controls, we included 13 participants with normal cognition and PiB-negative scans. We divided the SVCI and ADCI patients into three groups according to global PiB retention ratio of SVCI, and then compared the tertiles in terms of the distribution of PiB retention using statistical parametric mapping analyses. Lobar to global PiB retention ratio and asymmetry indices were also compared between SVCI and ADCI groupsResults: Compared to PiB+ ADCI patients, PiB+ SVCI patients exhibited: 1) increased left-right asymmetry, and increased anterior-posterior difference; and 2) increased PiB retention in the parietal cortex, the occipital cortex and the precuneus-posterior cingulate cortex. In contrast, ADCI patients showed increased PiB retention in the striatum. When stratified by level of PiB retention, each group showed different characteristics. CONCLUSION: Our results showed that the distribution of amyloid deposition differed between patients with PiB+ SVCI and ADCI. These suggest that CVD contribute to and alter the known progression pattern in amyloid deposition in Alzheimer's disease.

Serum Adiponectin Levels, Neuroimaging, and Cognition in the Mayo Clinic Study of Aging. - Wennberg, Alexandra M V; Gustafson, Deborah; Hagen, Clinton E; Roberts, Rosebud O; Knopman, David; Jack, Clifford; Petersen, Ronald C; Mielke, Michelle M (J Alzheimers Dis, 2016)
BACKGROUND: Adiponectin, a protein involved in inflammatory pathways, may impact the development and progression of Alzheimer's disease (AD). Adiponectin levels have been associated with mild cognitive impairment (MCI) and AD; however, its association with Alzheimer-associated neuroimaging and cognitive outcomes is unknown. OBJECTIVE: Determine the cross-sectional association between plasma adiponectin and neuroimaging and cognitive outcomes in an older population-based sample. METHODS: Multivariable adjusted regression models were used to investigate the association between plasma adiponectin and hippocampal volume (HVa), PiB-PET, FDG PET, cortical thickness, MCI diagnosis, and neuropsychological test performance. Analyses included 535 non-demented participants aged 70 and older enrolled in the Mayo Clinic Study of Aging. RESULTS: Women had higher adiponectin than men (12,631 ng/mL versus 8,908 ng/mL, p < 0.001). Among women, higher adiponectin was associated with smaller HVa (B = -0.595; 95% CI -1.19, -0.005), poorer performance in language (B = -0.676; 95% CI -1.23, -0.121), and global cognition (B = -0.459; 95% CI -0.915, -0.002), and greater odds of a MCI diagnosis (OR = 6.23; 95% CI 1.20, 32.43). In analyses stratified by sex and elevated amyloid (PiB-PET SUVR >1.4), among women with elevated amyloid, higher adiponectin was associated with smaller HVa (B = -0.723; 95% CI -1.43, -0.014), poorer performance in memory (B = -1.02; 95% CI -1.73, -0.312), language (B = -0.896; 95% CI -1.58, -0.212), global cognition (B = -0.650; 95% CI -1.18, -0.116), and greater odds of MCI (OR = 19.34; 95% CI 2.72, 137.34). CONCLUSION: Higher plasma adiponectin was associated with neuroimaging and cognitive outcomes among women. Longitudinal analyses are necessary to determine whether higher adiponectin predicts neurodegeneration and cognitive decline.

Shared Genetic Etiology between Type 2 Diabetes and Alzheimer's Disease Identified by Bioinformatics Analysis. - Gao, Lei; Cui, Zhen; Shen, Liang; Ji, Hong-Fang (J Alzheimers Dis, 2016)
Type 2 diabetes (T2D) and Alzheimer's disease (AD) are two major health issues, and increasing evidence in recent years supports the close connection between these two diseases. The present study aimed to explore the shared genetic etiology underlying T2D and AD based on the available genome wide association studies (GWAS) data collected through August 2014. We performed bioinformatics analyses based on GWAS data of T2D and AD on single nucleotide polymorphisms (SNPs), gene, and pathway levels, respectively. Six SNPs (rs111789331, rs12721046, rs12721051, rs4420638, rs56131196, and rs66626994) were identified for the first time to be shared genetic factors between T2D and AD. Further functional enrichment analysis found lipid metabolism related pathways to be common between these two disorders. The findings may have important implications for future mechanistic and interventional studies for T2D and AD.
Keywords: Alzheimer Disease; Apolipoprotein C-I; Computational Biology; Databases, Factual; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lipid Metabolism; Male; Polymorphism, Single Nucleotide

Specific Binding of Cu(II) Ions to Amyloid-Beta Peptides Bound to Aggregation-Inhibiting Molecules or SDS Micelles Creates Complexes that Generate Radical Oxygen Species. - Tiiman, Ann; Luo, Jinghui; Wallin, Cecilia; Olsson, Lisa; Lindgren, Joel; Jarvet, Jϋri; Per, Roos; Sholts, Sabrina B; Rahimipour, Shai; Abrahams, Jan Pieter; Karlström, Amelie Eriksson; Gräslund, Astrid; et al. (J Alzheimers Dis, 2016)
Aggregation of the amyloid-beta (Aβ) peptide into insoluble plaques is a major factor in Alzheimer's disease (AD) pathology. Another major factor in AD is arguably metal ions, as metal dyshomeostasis is observed in AD patients, metal ions modulate Aβ aggregation, and AD plaques contain numerous metals including redox-active Cu and Fe ions. In vivo, Aβ is found in various cellular locations including membranes. So far, Cu(II)/Aβ interactions and ROS generation have not been investigated in a membrane environment. Here, we study Cu(II) and Zn(II) interactions with Aβ bound to SDS micelles or to engineered aggregation-inhibiting molecules (the cyclic peptide CP-2 and the ZAβ3(12-58)Y18L Affibody molecule). In all studied systems the Aβ N-terminal segment was found to be unbound, unstructured, and free to bind metal ions. In SDS micelles, Aβ was found to bind Cu(II) and Zn(II) with the same ligands and the same KD as in aqueous solution. ROS was generated in all Cu(II)/Aβ complexes. These results indicate that binding of Aβ to membranes, drugs, and other entities that do not interact with the Aβ N-terminal part, appears not to compromise the N-terminal segment's ability to bind metal ions, nor impede the capacity of N-terminally bound Cu(II) to generate ROS.

Thyroid-Stimulating Hormone and Mild Cognitive Impairment: Results of the Heinz Nixdorf Recall Study. - Winkler, Angela; Weimar, Christian; Jöckel, Karl-Heinz; Erbel, Raimund; Dragano, Nico; Broecker-Preuss, Martina; Moebus, Susanne; Führer-Sakel, Dagmar; Dlugaj, Martha (J Alzheimers Dis, 2016)
BACKGROUND: Although some studies reported on the association of serum thyroid-stimulating hormone (TSH) concentration and cognition, only one population-based study investigated the association of TSH concentration and mild cognitive impairment (MCI). OBJECTIVE: To investigate the gender-specific association of low- and high-normal TSH concentrations with MCI in euthyroid participants. METHODS: Analysis sample 1 included 2,563 euthyroid participants (aged 50-80 years) from the second examination of the population-based Heinz Nixdorf Recall study. Gender-specific TSH quintiles (Q1 low, Q2-Q4 middle, Q5 high TSH concentration) were determined and group comparisons of age- and education-adjusted mean scores were performed for all cognitive subtests. Analysis sample 2 included 378 participants with MCI and 931 cognitively normal participants. MCI was diagnosed according to previously published MCI criteria. Multivariate logistic regression models were performed using TSH quintiles (Q2-Q4 as reference) to assess the association of low- and high-normal TSH concentration with MCI. Models were performed unadjusted and adjusted for sociodemographic and cardiovascular risk factors. RESULTS: Group comparisons showed significant differences only in the immediate recall of the verbal memory task in women. Only women showed a strong association of high-normal TSH concentration with MCI (unadjusted: odds ratio 2.09, 95% confidence interval 1.29-3.37, full adjusted: 1.86, 1.06-3.27). There was no association with low-normal TSH concentration in women and no association of either low- or high-normal TSH concentration with MCI in men. CONCLUSIONS: These results suggest that women with high-normal TSH concentration might be at higher risk of cognitive decline. This needs to be confirmed in the longitudinal analysis.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Case-Control Studies; Cognitive Dysfunction; Female; Follow-Up Studies; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Risk Factors; Sex Characteristics; Statistics, Nonparametric; Thyrotropin

Time trends in antipsychotic drug use in patients with dementia: a nationwide study. - Nørgaard, Ane; Jensen-Dahm, Christina; Gasse, Christiane; Hansen, Hanne Vibe; Waldemar, Gunhild (J Alzheimers Dis, 2016)
BACKGROUND: Antipsychotics are often used to treat neuropsychiatric symptoms in dementia, but the evidence for effect is limited. Antipsychotics have been associated with increased risk of adverse events and mortality in patients with dementia, leading to safety regulations worldwide. OBJECTIVE: To investigate time trends in use of antipsychotics and other psychotropic drugs in dementia care. METHODS: The study included longitudinal data on all Danish residents ≥65 years. The study population was defined on January 1 of each year from 2000-2012. Data included prescriptions, discharge diagnoses, and somatic and psychiatric comorbidities. Multivariate time trend analyses of psychotropic drug use in patients with dementia within 4-year age bands were performed. RESULTS: Overall, among patients with dementia the prevalence of antipsychotic drug use decreased from 31.3% in 2000 to 20.4% in 2012. The decreasing use of antipsychotics was accompanied by decreasing use of anxiolytics and hypnotics/sedatives, but an increase in the use of antidepressants from 43.3% in 2000 to 53.8% in 2012. These changes were significant across almost all age groups. Treatment intensity among patients using antipsychotics increased as the annual median number of defined daily doses (DDD) increased from 33.3 to 42.0 DDD. CONCLUSIONS: The changing patterns of psychotropic drug use may be caused by warnings against use of antipsychotics. Further research is needed to explore the implications for patient safety.
Keywords: Aged; Aged, 80 and over; Anti-Anxiety Agents; Antidepressive Agents; Antipsychotic Agents; Dementia; Denmark; Drug Prescriptions; Female; Homes for the Aged; Humans; Hypnotics and Sedatives; Longitudinal Studies; Male; Multivariate Analysis; Nursing Homes; Registries

Towards a Pathway Inventory of the Human Brain for Modeling Disease Mechanisms Underlying Neurodegeneration. - Iyappan, Anandhi; Gündel, Michaela; Shahid, Mohammad; Wang, Jiali; Li, Hui; Mevissen, Heinz-Theodor; Müller, Bernd; Fluck, Juliane; Jirsa, Viktor; Domide, Lia; Younesi, Erfan; Hofmann-Apitius, Martin (J Alzheimers Dis, 2016)
Molecular signaling pathways have been long used to demonstrate interactions among upstream causal molecules and downstream biological effects. They show the signal flow between cell compartments, the majority of which are represented as cartoons. These are often drawn manually by scanning through the literature, which is time-consuming, static, and non-interoperable. Moreover, these pathways are often devoid of context (condition and tissue) and biased toward certain disease conditions. Mining the scientific literature creates new possibilities to retrieve pathway information at higher contextual resolution and specificity. To address this challenge, we have created a pathway terminology system by combining signaling pathways and biological events to ensure a broad coverage of the entire pathway knowledge domain. This terminology was applied to mining biomedical papers and patents about neurodegenerative diseases with focus on Alzheimer's disease. We demonstrate the power of our approach by mapping literature-derived signaling pathways onto their corresponding anatomical regions in the human brain under healthy and Alzheimer's disease states. We demonstrate how this knowledge resource can be used to identify a putative mechanism explaining the mode-of-action of the approved drug Rasagiline, and show how this resource can be used for fingerprinting patents to support the discovery of pathway knowledge for Alzheimer's disease. Finally, we propose that based on next-generation cause-and-effect pathway models, a dedicated inventory of computer-processable pathway models specific to neurodegenerative diseases can be established, which hopefully accelerates context-specific enrichment analysis of experimental data with higher resolution and richer annotations.

Tract-Specific Correlates of Neuropsychological Deficits in Patients with Subcortical Vascular Cognitive Impairment. - Jung, Na-Yeon; Han, Cheol E; Kim, Hee Jin; Yoo, Sang Wook; Kim, Hee-Jong; Kim, Eun-Joo; Na, Duk L; Lockhart, Samuel N; Jagust, William J; Seong, Joon-Kyung; Seo, Sang Won (J Alzheimers Dis, 2016)
The white matter tract-specific correlates of neuropsychological deficits are not fully established in patients with subcortical vascular cognitive impairment (SVCI), where white matter tract damage may be a critical factor in cognitive impairment. The purpose of this study is to investigate the tract-specific correlates of neuropsychological deficits in SVCI patients using tract-specific statistical analysis (TSSA). We prospectively recruited 114 SVCI patients, and 55 age-, gender-, and education-matched individuals with normal cognition (NC). All participants underwent diffusion weighted imaging and neuropsychological testing. We classified tractography results into fourteen major fiber tracts and analyzed group comparison and correlation with cognitive impairments. Relative to NC subjects, SVCI patients showed decreased fractional anisotropy values in bilateral anterior-thalamic radiation, cingulum, superior-longitudinal fasciculus, uncinate fasciculus, corticospinal tract, and left inferior-longitudinal fasciculus. Focal disruptions in specific tracts were associated with specific cognitive impairments. Our findings suggest that disconnection of specific white matter tracts, especially those neighboring and providing connections between gray matter regions important to certain cognitive functions, may contribute to specific cognitive impairments in SVCI.
Keywords: Aged; Brain; Cerebrovascular Disorders; Cognitive Dysfunction; Diffusion Magnetic Resonance Imaging; Diffusion Tensor Imaging; Female; Gray Matter; Humans; Male; Neural Pathways; Neuropsychological Tests; White Matter

Two Phase 2 Multiple Ascending-Dose Studies of Vanutide Cridificar (ACC-001) and QS-21 Adjuvant in Mild-to-Moderate Alzheimer's Disease. - Pasquier, Florence; Sadowsky, Carl; Holstein, Ann; Leterme, Ghislaine Le Prince; Peng, Yahong; Jackson, Nicholas; Fox, Nick C; Ketter, Nzeera; Liu, Enchi; Ryan, J Michael (J Alzheimers Dis, 2016)
Vanutide cridificar (ACC-001), an immunotherapeutic vaccine, is a potentially disease-modifying therapy that aims to reduce brain amyloid-β (Aβ) plaques in patients with Alzheimer's disease (AD). ACC-001 was evaluated in two phase 2a, multicenter, randomized, third party-unblinded, placebo-controlled, multiple ascending-dose studies of ACC-001 (3μg, 10μg, 30μg) with and without QS-21 adjuvant that enrolled patients with mild-to-moderate AD (n = 245). Patients were treated with up to five doses of study vaccine or placebo and followed for safety and tolerability (primary objective) and anti-Aβ IgG immunogenicity (secondary objective) up to 12 months after the last vaccination. Exploratory assessments included cognitive/functional measures, brain magnetic resonance imaging (MRI) volumetry, and pharmacodynamic markers in plasma and cerebrospinal fluid (CSF). The most frequent treatment-emergent adverse events (≥10%) were local injection reactions and headache. Amyloid-related imaging abnormalities with vasogenic edema occurred in two (0.8%) patients (ACC-001 30μg + QS-21; ACC-001 10μg). ACC-001 + QS-21 elicited consistently higher peak and sustained anti-Aβ IgG titers compared with ACC-001 alone. Plasma Aβx-40 was significantly higher in all ACC-001 + QS-21 groups versus placebo (weeks 16-56), with no evidence of dose response. Exploratory cognitive evaluations, volumetric brain MRI, and CSF biomarkers did not show differences or trends between treatment groups and placebo. ACC-001 with or without QS-21 adjuvant has an acceptable safety profile in patients with mild-to-moderate AD.
Keywords: Adjuvants, Immunologic; Aged; Alzheimer Disease; Amyloid beta-Peptides; Antipsychotic Agents; Dose-Response Relationship, Drug; Female; Follow-Up Studies; Humans; Interferon-gamma; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Recombinant Fusion Proteins; Saponins; Single-Blind Method; Treatment Outcome

Unstable Body Mass Index and Progression to Probable Alzheimer's Disease Dementia in Patients with Amnestic Mild Cognitive Impairment. - Ye, Byoung Seok; Jang, Eun Young; Kim, Seong Yoon; Kim, Eun-Joo; Park, Sun Ah; Lee, Yunhwan; Hong, Chang Hyung; Choi, Seong Hye; Yoon, Bora; Yoon, Soo Jin; Na, Hae Ri; Lee, Jae-Hong; et al. (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: We investigated the influence of body mass index (BMI) status at baseline and changes in BMI over a follow-up period on the development of dementia in amnestic mild cognitive impairment (aMCI) patients. METHODS: The longitudinal data of 747 aMCI patients were used to investigate the relationships among baseline BMI status, subsequent changes in BMI (median follow-up duration: 1.6 years, interquartile range: 1.0-2.3 years), and risk of progression to probable Alzheimer's disease dementia (pADD). The aMCI patients were classified into underweight, normal weight, overweight, and obese subgroups, and further categorized into increased BMI, stable BMI, and decreased BMI subgroups during follow-up using a 4% mean annual change in BMI cut-off value. RESULTS: Compared to the normal weight group, the underweight group had a higher risk of pADD (hazard ratio [HR]: 1.89, 95% confidence interval [CI]: 1.07-3.37) while the obese group had a lower risk (HR: 0.70, 95% CI: 0.49-0.999). After controllingfor baseline BMI status, the decreased BMI (HR: 2.29, 95% CI: 1.41-3.72) and increased BMI (HR: 3.96, 95% CI: 2.62-6.00) groups were at increased risk of progression to pADD. CONCLUSIONS: Our findings suggested that underweight at baseline was associated with a higher risk of progression to pADD, while obesity at baseline predicted a lower risk. Furthermore, significant changes in BMI during the follow-up period reflected an increased risk of progression to pADD, regardless of BMI status at baseline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Body Mass Index; Body Weight; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Kaplan-Meier Estimate; Longitudinal Studies; Male; Neuropsychological Tests; Registries

Upregulation of Connexin 43 Expression Via C-Jun N-Terminal Kinase Signaling in Prion Disease. - Lee, Geon-Hwi; Jang, Byungki; Choi, Hong-Seok; Kim, Hee-Jun; Park, Jeong-Ho; Jeon, Yong-Chul; Carp, Richard I; Kim, Yong-Sun; Choi, Eun-Kyoung (J Alzheimers Dis, 2016)
Prion infection leads to neuronal cell death, glial cell activation, and the accumulation of misfolded prion proteins. However, the altered cellular environments in animals with prion diseases are poorly understood. In the central nervous system, cells connect the cytoplasm of adjacent cells via connexin (Cx)-assembled gap junction channels to allow the direct exchange of small molecules, including ions, neurotransmitters, and signaling molecules, which regulate the activities of the connected cells. Here, we investigate the role of Cx43 in the pathogenesis of prion diseases. Upregulated Cx43 expression, which was dependent on c-Jun N-Terminal Kinase (JNK)/c-Jun signaling cascades, was found in prion-affected brain tissues and hippocampal neuronal cells. Scrapie infection-induced Cx43 formed aggregated plaques within the cytoplasmic compartments at the cell-cell interfaces. The ethidium bromide (EtBr) uptake assay and scrape-loading dye transfer assay demonstrated that increased Cx43 has functional consequences for the activity of Cx43 hemichannels. Interestingly, blockade of PrPSc accumulation reduced Cx43 expression through the inhibition of JNK signaling, indicating that PrPSc accumulation may be directly involved in JNK activation-mediated Cx43 upregulation. Overall, our findings describe a scrapie infection-mediated novel regulatory signaling pathway of Cx43 expression and may suggest a role for Cx43 in the pathogenesis of prion diseases.
Keywords: Animals; Brain; Cell Membrane; Cells, Cultured; Connexin 43; Disease Models, Animal; JNK Mitogen-Activated Protein Kinases; MAP Kinase Signaling System; Mesocricetus; Mice, Inbred C57BL; Mice, Knockout; PrPSc Proteins; RNA, Messenger; Scrapie; Up-Regulation

The Vanderbilt Memory & Aging Project: Study Design and Baseline Cohort Overview. - Jefferson, Angela L; Gifford, Katherine A; Acosta, Lealani Mae Y; Bell, Susan P; Donahue, Manus J; Davis, L Taylor; Gottlieb, JoAnn; Gupta, Deepak K; Hohman, Timothy J; Lane, Elizabeth M; Libon, David J; Mendes, Lisa A; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Vascular health factors frequently co-occur with Alzheimer's disease (AD). A better understanding of how systemic vascular and cerebrovascular health intersects with clinical and pathological AD may inform prevention and treatment opportunities. OBJECTIVE: To establish the Vanderbilt Memory & Aging Project, a case-control longitudinal study investigating vascular health and brain aging, and describe baseline methodology and participant characteristics. METHODS: From September 2012 to November 2014, 335 participants age 60- 92 were enrolled, including 168 individuals with mild cognitive impairment (MCI, 73±8 years, 41% female) and 167 age-, sex-, and race-matched cognitively normal controls (NC, 72±7 years, 41% female). At baseline, participants completed a physical and frailty examination, fasting blood draw, neuropsychological assessment, echocardiogram, cardiac MRI, and brain MRI. A subset underwent 24-hour ambulatory blood pressure monitoring and lumbar puncture for cerebrospinal fluid (CSF) collection. RESULTS: As designed, participant groups were comparable for age (p = 0.31), sex (p = 0.95), and race (p = 0.65). MCI participants had greater Framingham Stroke Risk Profile scores (p = 0.008), systolic blood pressure values (p = 0.008), and history of left ventricular hypertrophy (p = 0.04) than NC participants. As expected, MCI participants performed worse on all neuropsychological measures (p-values < 0.001), were more likely to be APOEɛ4 carriers (p = 0.02), and had enhanced CSF biomarkers, including lower Aβ42 (p = 0.02), higher total tau (p = 0.004), and higher p-tau (p = 0.02) compared to NC participants. CONCLUSION: Diverse sources of baseline and longitudinal data will provide rich opportunities to investigate pathways linking vascular and cerebrovascular health, clinical and pathological AD, and neurodegeneration contributing to novel strategies to delay or prevent cognitive decline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Blood Pressure Monitoring, Ambulatory; Brain; Case-Control Studies; Cerebral Angiography; Cognitive Dysfunction; Echocardiography; Epidemiologic Research Design; Female; Follow-Up Studies; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Research Design

Vitamin D Supplementation Appears to Increase Plasma Aβ40 in Vitamin D Insufficient Older Adults: A Pilot Randomized Controlled Trial. - Miller, Brendan J; Whisner, Corrie M; Johnston, Carol S (J Alzheimers Dis, 2016)
Low plasma amyloid-β (Aβ) is linked to Alzheimer's disease. Since vitamin D cleared brain Aβ in vitro, this 8-week trial examined whether vitamin D increased plasma Aβ40. Vitamin D insufficient adults (6/18 M/F; 64.3 ± 10.9 y) were randomized to placebo or vitamin (50,000 IU/week) treatments. The vitamin group experienced greater plasma Aβ40 change than controls, +14.9 ± 12.0 and +12.8 ± 12.8 pg/mL (p = 0.045; effect size, 0.228). Change in Aβ40 for older participants (≥60 y) was +18.3 ± 33.6 and -3.2 ± 44.5 pg/mL for vitamin (n = 4) and placebo (n = 4) groups (effect size, 0.295). Thus, vitamin D may increase plasma Aβ, particularly in older adults, suggesting decreased brain Aβ.

Amyloid-β and Tau Dynamics in Human Brain Interstitial Fluid in Patients with Suspected Normal Pressure Hydrocephalus. - Herukka, Sanna-Kaisa; Rummukainen, Jaana; Ihalainen, Jouni; von Und Zu Fraunberg, Mikael; Koivisto, Anne M; Nerg, Ossi; Puli, Lakshman K; Seppälä, Toni T; Zetterberg, Henrik; Pyykkö, Okko T; Helisalmi, Seppo; Tanila, Heikki; et al. (J Alzheimers Dis, 2015)
Background: Amyloid-β (Aβ1-42), total tau (T-tau), and phosphorylated tau (P-tau181) in the cerebrospinal fluid (CSF) are the most promising biomarkers of Alzheimer's disease (AD). Still, little is known about the dynamics of these molecules in the living brain. In a transgenic mouse brain, soluble Aβ decreases with increasing age and advanced Aβ pathology as seen similarly in CSF. Objective: To assess the relationship between AD-related pathological changes in human brain tissue, ventricular and lumbar CSF, and brain interstitial fluid (ISF). Methods: Altogether 11 patients with suspected idiopathic normal pressure hydrocephalus underwent frontal cortical brain biopsy, 24-h intraventricular pressure monitoring, and a microdialysis procedure. AD-related biomarkers were analyzed from brain tissue, CSF, and ISF. Results: ISF T-tau levels decreased strongly within the first 12 h, then plateauing until the end of the experiment. Aβ1-42 and P-tau181 remained stable during the experiment (n = 3). T-tau and P-tau were higher in the ISF than in ventricular or lumbar CSF, while Aβ1-42 levels were within similar range in both CSF and ISF samples. ISF P-tau correlated with the ventricular CSF T-tau (r = 0.70, p = 0.017) and P-tau181 (r = 0.64, p = 0.034). Five patients with amyloid pathology in the brain biopsy tended to reveal lower ISF Aβ1-42 levels than those six without amyloid pathology. Conclusions: This is the first study to report ISF Aβ and tau levels in the human brain without significant brain injury. The set-up used enables sampling from the brain ISF for at least 24 h without causing adverse effects due to the microdialysis procedure to follow the dynamics of the key molecules in AD pathogenesis in the living brain at various stages of the disease.

Ankle-Brachial Index but Neither Intima Media Thickness Nor Coronary Artery Calcification is Associated With Mild Cognitive Impairment. - Weimar, Christian; Winkler, Angela; Dlugaj, Martha; Lehmann, Nils; Hennig, Frauke; Bauer, Marcus; Kröger, Knut; Kälsch, Hagen; Mahabadi, Amir-Abass; Dragano, Nico; Moebus, Susanne; Hoffmann, Barbara; et al. (J Alzheimers Dis, 2015)
BACKGROUND: Several studies have reported an association of atherosclerosis with mild cognitive impairment (MCI) and dementia independent of cardiovascular risk factors. OBJECTIVE: To compare the cross-sectional association of the ankle-brachial index (ABI), intima media thickness (IMT), and coronary artery calcification (CAC) with MCI and its subtypes, amnestic MCI (aMCI) and non-amnestic MCI (naMCI) in the population-based Heinz Nixdorf Recall cohort study. METHODS: 4,086 participants performed a validated brief cognitive assessment at the first follow-up examination (2006-2008). MCI was diagnosed according to previously published criteria. Prevalence ratio (PR) regression models adjusted for age, gender, education, cardiovascular risk factors, and APOE genotype were used to compare the association of the ABI, the CAC-Agatston score and the IMT with MCI and its subtypes. RESULTS: We identified 490 participants with MCI (mean age 66.1 ± 7.8, 46.9 % male, aMCI n = 249, naMCI n = 241) and 1,242 cognitively normal participants. A decreasing ABI (per 0.1) was significantly associated with a higher MCI prevalence in fully adjusted models (PR 1.06; 95% confidence interval (CI) 1.01-1.11), whereas an increasing CAC (log(CAC+1)) or IMT (per 0.1 mm) were not associated after adjustment. A decreasing ABI was also significantly associated with naMCI in fully adjusted models (PR 1.12; CI 1.03-1.21) but not with aMCI. CONCLUSIONS: Our data show that the degree of generalized atherosclerosis as measured by the ABI is associated with MCI and with naMCI in a population-based cohort.

AβPP-Transgenic 2576 Mice Mimic Cell Type-Specific Aspects of Acetyl-CoA-Linked Metabolic Deficits in Alzheimer's Disease. - Bielarczyk, Hanna; Jankowska-Kulawy, Agnieszka; Hofling, Corinna; Ronowska, Anna; Gul-Hinc, Sylwia; Rossner, Steffen; Schliebs, Reinhard; Pawelczyk, Tadeusz; Szutowicz, Andrzej (J Alzheimers Dis, 2015)
The pyruvate-derived acetyl-CoA is a principal direct precursor substrate for bulk energy synthesis in the brain. Deficits of pyruvate dehydrogenase in the neocortex are common features of Alzheimer's disease and other age-related encephalopathies in humans. Therefore, amyloid-β overload in brains of diverse transgenic Alzheimer's disease model animals was investigated as one of neurotoxic compounds responsible for pyruvate dehydrogenase inhibition yielding deficits of cholinergic neurotransmission and cognitive functions. Brains of aged, 14-16-month-old Tg2576 mice contained 0.6 μmol/kg levels of amyloid-β 1-42. Activities of pyruvate dehydrogenase complex, choline acetyltransferase, and several enzymes of acetyl-CoA and energy metabolism were found to be unchanged in both forebrain mitochondria and synaptosomes of Tg2576 mice, indicating preservation of structural integrity at least cholinergic neuronal cells. However, in transgenic brain synaptosomes, pyruvate utilization, mitochondrial levels, and cytoplasmic acetyl-CoA levels, as well as acetylcholine content and its quantal release, were all found to be decreased by 25-40% . On the contrary, activation of pyruvate utilization was detected and no alterations in acetyl-CoA content and citrate or α-ketoglutarate accumulation were observed in transgenic whole brain mitochondria. These data indicate that amyloid-β evoked deficits in acetyl-CoA are confined to mitochondrial and cytoplasmic compartments of Tg2576 nerve terminals, becoming early primary signals paving path for further stages of neurodegeneration. On the other hand, acetyl-CoA synthesis in mitochondrial compartments of glial cells seems to be activated despite amyloid-β accumulated in transgenic brains.

A Blood-Based, 7-Metabolite Signature for the Early Diagnosis of Alzheimer's Disease. - Olazarán, Javier; Gil-de-Gómez, Luis; Rodríguez-Martín, Andrés; Valentí-Soler, Meritxell; Frades-Payo, Belén; Marín-Muñoz, Juan; Antúnez, Carmen; Frank-García, Ana; Jiménez, Carmen Acedo; Gracia, Lorenzo Morlén; Torregrossa, Roberto Petidier; Guisasola, María Concepción; et al. (J Alzheimers Dis, 2015)
Accurate blood-based biomarkers of Alzheimer's disease (AD) could constitute simple, inexpensive, and non-invasive tools for the early diagnosis and treatment of this devastating neurodegenerative disease. We sought to develop a robust AD biomarker panel by identifying alterations in plasma metabolites that persist throughout the continuum of AD pathophysiology. Using a multicenter, cross-sectional study design, we based our analysis on metabolites whose levels were altered both in AD patients and in patients with amnestic mild cognitive impairment (aMCI), the earliest identifiable stage of AD. UPLC coupled to mass spectrometry was used to independently compare the levels of 495 plasma metabolites in aMCI (n = 58) and AD (n = 100) patients with those of normal cognition controls (NC, n = 93). Metabolite alterations common to both aMCI and AD patients were used to generate a logistic regression model that accurately distinguished AD from NC patients. The final panel consisted of seven metabolites: three amino acids (glutamic acid, alanine, and aspartic acid), one non-esterified fatty acid (22:6n-3, DHA), one bile acid (deoxycholic acid), one phosphatidylethanolamine [PE(36:4)], and one sphingomyelin [SM(39:1)]. Detailed analysis ruled out the influence of potential confounding variables, including comorbidities and treatments, on each of the seven biomarkers. The final model accurately distinguished AD from NC patients (AUC, 0.918). Importantly, the model also distinguished aMCI from NC patients (AUC, 0.826), indicating its potential diagnostic utility in early disease stages. These findings describe a sensitive biomarker panel that may facilitate the specific detection of early-stage AD through the analysis of plasma samples.

Body Mass Index and Mortality Rate in Korean Patients with Alzheimer's Disease. - Jang, Hyemin; Kim, Jong Hun; Choi, Seong Hye; Lee, Yunhwan; Hong, Chang Hyung; Jeong, Jee Hyang; Han, Hyun Jeong; Moon, So Young; Park, Kyung Won; Han, Seol-Hee; Park, Kee Hyung; Kim, Hee Jin; et al. (J Alzheimers Dis, 2015)
Background: A relationship between body weight, cognitive impairment, and the onset of Alzheimer's disease (AD) was recently reported. However, to our knowledge, no studies have investigated the relationship between body weight and mortality in Asian AD patients. Objective: We evaluated the relationship between body mass index (BMI) and mortality rate in Korean AD cohorts. Methods: Participants were consecutively included from two Korean representative registries: 579 AD patients from Samsung Medical Center and 1911 AD patients from the Clinical Research Center for Dementia of South Korea study. We combined these two AD cohorts to evaluate the association between BMI and mortality. BMI was used to categorize the participants into underweight, normal-weight, overweight, and obesity subgroups. All deaths were confirmed through the nationwide mortality database of Statistics Korea. Results: 53 of 181 (29.3%), 208 of 1,127 (18.5%), 88 of 626 (14.1%), and 115 of 556 (20.7%) patients died in the underweight, normal-weight, overweight, and obese subgroups during 43.7 months of follow-up. The time-dependent cox proportional hazards model showed that, relative to the normal-weight subgroup, the underweight group had higher mortality (HR 1.82 (95% CI, 1.07-3.09)) while overweight group had lower mortality rate (HR 0.60 (95% CI, 0.38-0.95)) The effects of underweight and overweight were prominent in younger and older elderly group, respectively. However, there were no interactive effects of dementia severity or gender and BMI on survival rate. Conclusion: Relative to AD patients of normal weight, those who were underweight had an increased mortality rate, and overweight predicted decreased mortality in AD patients. Furthermore, our findings may help facilitate mortality stratification in AD patients by using baseline BMI.

Comorbid Depression and Diabetes as a Risk for Mild Cognitive Impairment and Alzheimer's Disease in Elderly Mexican Americans. - Johnson, Leigh A; Gamboa, Adriana; Vintimilla, Raul; Cheatwood, Austin J; Grant, Alyann; Trivedi, Ashesh; Edwards, Melissa; Hall, James R; O'Bryant, Sid E (J Alzheimers Dis, 2015)
BACKGROUND: The links between diabetes, depression, and Alzheimer's disease (AD) has been established, but they are still poorly understood. However, little research has examined the effect that comorbidity of depression and diabetes has on cognitive impairment in an ethnically diverse sample. OBJECTIVE: The purpose of this study was to investigate the relationship between comorbid diabetes and depression on cognitive dysfunction; and examine the relationship in an ethnically diverse population. METHODS AND RESULTS: Analyses of data from 2,436 participants (914 men and 1,522 women) of three separate cohorts: HABLE, FRONTIER, and TARCC. In the HABLE cohort, comorbidity (odds ratio [OR] = 3.008; 95% CI = 1.358-6.667), age (OR = 1.138; 95% CI = 1.093-1.185), and education (OR = 0.915; 95% CI = 0.852-0.982) increased the risk of mild cognitive impairment (MCI) diagnosis among elderly Mexican American. In the TARCC cohort, results showed an increase risk of MCI in both non-Hispanic whites (OR = 18.795; 95% CI = 2.229-158.485) and Mexican Americans (OR = 8.417; 95% CI = 2.967-23.878). Finally, results in the FRONTIER cohort showed that in elderly Mexican Americans, comorbidity (OR = 2.754; 95% CI = 1.084-6.995) and age (OR = 1.069; 95% CI = 1.023-1.118) significantly increased risk of MCI. In non-Hispanic whites, comorbidity did not significantly increase risk of MCI. CONCLUSIONS: Among elderly Mexican Americans, comorbid depression and diabetes significantly increased risk for MCI and AD across cohorts. Effects of comorbid diabetes and depression on MCI were inconclusive. Our results support the link between comorbid diabetes and depression and risk for cognitive decline among Mexican Americans. This finding is of critical importance as the Hispanic population is at higher risk of developing AD.

A Critical Proton MR Spectroscopy Marker of Alzheimer's Disease Early Neurodegenerative Change: Low Hippocampal NAA/Cr Ratio Impacts APOE ɛ4 Mexico City Children and Their Parents. - Calderón-Garcidueñas, Lilian; Mora-Tiscareño, Antonieta; Sánchez, Gastón Melo; Rodríguez-Díaz, Joel; Torres-Jardón, Ricardo; Styner, Martin; Mukherjee, Partha S; Lin, Weili; Jewells, Valerie (J Alzheimers Dis, 2015)
Severe air pollution exposures produce systemic, respiratory, myocardial, and brain inflammation and Alzheimer's disease (AD) hallmarks in clinically healthy children. We tested whether hippocampal metabolite ratios are associated with contrasting levels of air pollution, APOE, and body mass index (BMI) in paired healthy children and one parent sharing the same APOE alleles. We used 1H-MRS to interrogate bilateral hippocampal single-voxel in 57 children (12.45 ± 3.4 years) and their 48 parents (37.5 ± 6.78 years) from a low pollution city versus Mexico City (MC). NAA/Cr, Cho/Cr, and mI/Cr metabolite ratios were analyzed. The right hippocampus NAA/Cr ratio was significantly different between cohorts (p = 0.007). The NAA/Cr ratio in right hippocampus in controls versus APOE ɛ4 MC children and in left hippocampus in MC APOE ɛ4 parents versus their children was significantly different after adjusting for age, gender, and BMI (p = 0.027 and 0.01, respectively). The NAA/Cr ratio is considered reflective of neuronal density/functional integrity/loss of synapses/higher pTau burden, thus a significant decrease in hippocampal NAA/Cr ratios may constitute a spectral marker of early neurodegeneration in young urbanites. Decreases in NAA/Cr correlate well with cognitive function, behavioral symptoms, and dementia severity; thus, since the progression of AD starts decades before clinical diagnosis, our findings support the hypothesis that under chronic exposures to fine particulate matter and ozone above the standards, neurodegenerative processes start in childhood and APOE ɛ4 carriers are at higher risk. Gene and environmental factors are critical in the development of AD and the identification and neuroprotection of young urbanites at high risk must become a public health priority.

Depressive Symptoms and Biomarkers of Alzheimer's Disease in Cognitively Normal Older Adults. - Donovan, Nancy J; Hsu, David C; Dagley, Alexander S; Schultz, Aaron P; Amariglio, Rebecca E; Mormino, Elizabeth C; Okereke, Olivia I; Rentz, Dorene M; Johnson, Keith A; Sperling, Reisa A; Marshall, Gad A (J Alzheimers Dis, 2015)
Even low levels of depressive symptoms are associated with an increased risk of cognitive decline in older adults without overt cognitive impairment (CN). Our objective was to examine whether very low, "subthreshold symptoms of depression" are associated with Alzheimer's disease (AD) biomarkers of neurodegeneration in CN adults and whether these associations are specific to particular depressive symptoms. We analyzed data from 248 community-dwelling CN older adults, including measurements of cortical amyloid burden, neurodegeneration markers of hippocampal volume (HV) and cerebral 18F-fluorodeoxyglucose (FDG) metabolism in a composite of AD-related regions and the 30-item Geriatric Depression Scale (GDS). Participants with GDS >10 were excluded. General linear regression models evaluated the cross-sectional relations of GDS to HV or FDG in separate backward elimination models. Predictors included GDS total score, age, gender, premorbid intelligence, a binary amyloid variable and its interaction with GDS. Principal component analyses of GDS item scores revealed three factors (the Dysphoria, Apathy-Anhedonia, and Anxiety-Concentration Factors). In secondary analyses, GDS total score was replaced with the three factor scores in repeated models. Higher GDS score (p = 0.03) was significantly associated with lower HV and was marginally related (p = 0.06) to FDG hypometabolism. In secondary models, higher Dysphoria (p = 0.02) and Apathy-Anhedonia (p = 0.05) were related to lower HV while higher Apathy-Anhedonia (p = 0.003) was the sole factor related to FDG hypometabolism. Amyloid was not a significant predictor in any model. In conclusion, very low-level dysphoria, apathy and anhedonia may point to neurodegeneration in AD-related regions but this association appears to be independent of amyloid burden.

The GLP-1 Receptor Agonist Liraglutide Improves Memory Function and Increases Hippocampal CA1 Neuronal Numbers in a Senescence-Accelerated Mouse Model of Alzheimer's Disease. - Hansen, Henrik H; Fabricius, Katrine; Barkholt, Pernille; Niehoff, Michael L; Morley, John E; Jelsing, Jacob; Pyke, Charles; Bjerre Knudsen, Lotte; Farr, Susan A; Vrang, Niels (J Alzheimers Dis, 2015)
Recent studies indicate that glucagon-like peptide 1 (GLP-1) receptor agonists, currently used in the management of type 2 diabetes, exhibit neurotrophic and neuroprotective effects in amyloid-β (Aβ) toxicity models of Alzheimer's disease (AD). We investigated the potential pro-cognitive and neuroprotective effects of the once-daily GLP-1 receptor agonist liraglutide in senescence-accelerated mouse prone 8 (SAMP8) mice, a model of age-related sporadic AD not dominated by Aβ plaques. Six-month-old SAMP8 mice received liraglutide (100 or 500 μg/kg/day, s.c.) or vehicle once daily for 4 months. Vehicle-dosed age-matched 50% back-crossed as well as untreated young (4-month-old) SAMP8 mice were used as control groups for normal memory function. Vehicle-dosed 10-month-old SAMP8 mice showed significant learning and memory retention deficits in an active-avoidance T-maze, as compared to both control groups. Also, 10-month-old SAMP8 mice displayed no immunohistological signatures of Aβ plaques or hyperphosphorylated tau, indicating the onset of cognitive deficits prior to deposition of amyloid plaques and neurofibrillary tangles in this AD model. Liraglutide significantly increased memory retention and total hippocampal CA1 pyramidal neuron numbers in SAMP8 mice, as compared to age-matched vehicle-dosed SAMP8 mice. In conclusion, liraglutide delayed or partially halted the progressive decline in memory function associated with hippocampal neuronal loss in a mouse model of pathological aging with characteristics of neurobehavioral and neuropathological impairments observed in early-stage sporadic AD.

Long-Term Interrelationship between Brain Metabolism and Amyloid Deposition in Mild Cognitive Impairment. - Kemppainen, Nina; Joutsa, Juho; Johansson, Jarkko; Scheinin, Noora M; Någren, Kjell; Rokka, Johanna; Parkkola, Riitta; Rinne, Juha O (J Alzheimers Dis, 2015)
The aim of this longitudinal positron emission tomography (PET) study was to evaluate the interrelationship between brain metabolism and amyloid accumulation during the disease process from mild cognitive impairment (MCI) to Alzheimer's disease (AD). Nine MCI patients, who converted to AD between two and five years, and nine healthy subjects underwent [11C]PIB and [18F]FDG PET scans at baseline and at 5 years. [11C]PIB uptake was clearly higher in MCI patients at baseline compared to controls and spread extensively to the cerebral cortex during the conversion to AD. [18F]FDG uptake was reduced especially in the temporal-parietal regions in MCI compared to controls at baseline, and widely over the cortex at the 5-year follow-up. The reduction in metabolism during the follow-up was significant in the posterior brain regions. In addition, brain amyloid load was positively associated with metabolism in posterior brain regions in MCI, but not after conversion to AD. The results suggest that there are interactions between brain amyloid accumulation and metabolism during the AD process, including a possible compensatory upregulation of posterior brain metabolism in the early phase.

sAβPPα is a Potent Endogenous Inhibitor of BACE1. - Peters-Libeu, Clare; Campagna, Jesus; Mitsumori, Michael; Poksay, Karen S; Spilman, Patricia; Sabogal, Alex; Bredesen, Dale E; John, Varghese (J Alzheimers Dis, 2015)
Proteolytic cleavage of the amyloid-β protein precursor (AβPP) by the enzyme BACE1 (BACE) is the initial step in production of amyloid-β peptide (Aβ), and as such has been a major target of Alzheimer's disease (AD) drug discovery efforts. Overproduction of Aβ results in neuronal cell death and accumulation of amyloid plaques in AD and in traumatic brain injury, and is also associated with stroke due to cerebral amyloid angiopathy. Herein we report for the first time that sAβPPα, the product of the cleavage of AβPP by α-secretase, is a potent endogenous direct inhibitor of the BACE enzyme, and that its inhibition is likely by an allosteric mechanism. Furthermore, using small-angle X-ray scattering, we show that sAβPPβ, which is identical to sAβPPα except for a 16-amino acid truncation at the carboxy terminus, adopts a completely different structure than sAβPPα and does not inhibit BACE. Our data thus reveal a novel mechanistic role played by sAβPPα in regulating overproduction of Aβ and restoring neuronal homeostasis and neuroprotection. Identification of sAβPPα as a direct BACE inhibitor may lead to design of new therapeutics targeting pathologies associated with overproduction of Aβ.

Advancing research diagnostic criteria for Alzheimer's disease: the IWG-2 criteria. - Dubois, Bruno; Feldman, Howard H; Jacova, Claudia; Hampel, Harald; Molinuevo, José Luis; Blennow, Kaj; DeKosky, Steven T; Gauthier, Serge; Selkoe, Dennis; Bateman, Randall; Cappa, Stefano; Crutch, Sebastian; et al. (Lancet Neurol, 2014)
In the past 8 years, both the International Working Group (IWG) and the US National Institute on Aging-Alzheimer's Association have contributed criteria for the diagnosis of Alzheimer's disease (AD) that better define clinical phenotypes and integrate biomarkers into the diagnostic process, covering the full staging of the disease. This Position Paper considers the strengths and limitations of the IWG research diagnostic criteria and proposes advances to improve the diagnostic framework. On the basis of these refinements, the diagnosis of AD can be simplified, requiring the presence of an appropriate clinical AD phenotype (typical or atypical) and a pathophysiological biomarker consistent with the presence of Alzheimer's pathology. We propose that downstream topographical biomarkers of the disease, such as volumetric MRI and fluorodeoxyglucose PET, might better serve in the measurement and monitoring of the course of disease. This paper also elaborates on the specific diagnostic criteria for atypical forms of AD, for mixed AD, and for the preclinical states of AD.
Keywords: Alzheimer Disease; Biomarkers; Humans; International Cooperation; Phenotype; Practice Guidelines as Topic; Societies, Medical

Phase 3 trials of solanezumab for mild-to-moderate Alzheimer's disease. - Doody, Rachelle S; Thomas, Ronald G; Farlow, Martin; Iwatsubo, Takeshi; Vellas, Bruno; Joffe, Steven; Kieburtz, Karl; Raman, Rema; Sun, Xiaoying; Aisen, Paul S; Siemers, Eric; Liu-Seifert, Hong; et al. (N Engl J Med, 2014)
BACKGROUND: Alzheimer's disease is characterized by amyloid-beta plaques, neurofibrillary tangles, gliosis, and neuronal loss. Solanezumab, a humanized monoclonal antibody, preferentially binds soluble forms of amyloid and in preclinical studies promoted its clearance from the brain. METHODS: In two phase 3, double-blind trials (EXPEDITION 1 and EXPEDITION 2), we randomly assigned 1012 and 1040 patients, respectively, with mild-to-moderate Alzheimer's disease to receive placebo or solanezumab (administered intravenously at a dose of 400 mg) every 4 weeks for 18 months. The primary outcomes were the changes from baseline to week 80 in scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11; range, 0 to 70, with higher scores indicating greater cognitive impairment) and the Alzheimer's Disease Cooperative Study-Activities of Daily Living scale (ADCS-ADL; range, 0 to 78, with lower scores indicating worse functioning). After analysis of data from EXPEDITION 1, the primary outcome for EXPEDITION 2 was revised to the change in scores on the 14-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog14; range, 0 to 90, with higher scores indicating greater impairment), in patients with mild Alzheimer's disease. RESULTS: Neither study showed significant improvement in the primary outcomes. The modeled difference between groups (solanezumab group minus placebo group) in the change from baseline was -0.8 points for the ADAS-cog11 score (95% confidence interval [CI], -2.1 to 0.5; P=0.24) and -0.4 points for the ADCS-ADL score (95% CI, -2.3 to 1.4; P=0.64) in EXPEDITION 1 and -1.3 points (95% CI, -2.5 to 0.3; P=0.06) and 1.6 points (95% CI, -0.2 to 3.3; P=0.08), respectively, in EXPEDITION 2. Between-group differences in the changes in the ADAS-cog14 score were -1.7 points in patients with mild Alzheimer's disease (95% CI, -3.5 to 0.1; P=0.06) and -1.5 in patients with moderate Alzheimer's disease (95% CI, -4.1 to 1.1; P=0.26). In the combined safety data set, the incidence of amyloid-related imaging abnormalities with edema or hemorrhage was 0.9% with solanezumab and 0.4% with placebo for edema (P=0.27) and 4.9% and 5.6%, respectively, for hemorrhage (P=0.49). CONCLUSIONS: Solanezumab, a humanized monoclonal antibody that binds amyloid, failed to improve cognition or functional ability. (Funded by Eli Lilly; EXPEDITION 1 and 2 ClinicalTrials.gov numbers, NCT00905372 and NCT00904683.).
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Cognition; Double-Blind Method; Female; Humans; Intention to Treat Analysis; Male; Neuropsychological Tests; Severity of Illness Index; tau Proteins; Treatment Failure

Ten-year effects of the advanced cognitive training for independent and vital elderly cognitive training trial on cognition and everyday functioning in older adults. - Rebok, George W; Ball, Karlene; Guey, Lin T; Jones, Richard N; Kim, Hae-Young; King, Jonathan W; Marsiske, Michael; Morris, John N; Tennstedt, Sharon L; Unverzagt, Frederick W; Willis, Sherry L (J Am Geriatr Soc, 2014)
OBJECTIVES: To determine the effects of cognitive training on cognitive abilities and everyday function over 10 years. DESIGN: Ten-year follow-up of a randomized, controlled single-blind trial (Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE)) with three intervention groups and a no-contact control group. SETTING: Six U.S. cities. PARTICIPANTS: A volunteer sample of 2,832 persons (mean baseline age 73.6; 26% African American) living independently. INTERVENTION: Ten training sessions for memory, reasoning, or speed of processing; four sessions of booster training 11 and 35 months after initial training. MEASUREMENTS: Objectively measured cognitive abilities and self-reported and performance-based measures of everyday function. RESULTS: Participants in each intervention group reported less difficulty with instrumental activities of daily living (IADLs) (memory: effect size = 0.48, 99% confidence interval (CI) = 0.12-0.84; reasoning: effect size = 0.38, 99% CI = 0.02-0.74; speed of processing: effect size = 0.36, 99% CI = 0.01-0.72). At a mean age of 82, approximately 60% of trained participants, versus 50% of controls (P < .05), were at or above their baseline level of self-reported IADL function at 10 years. The reasoning and speed-of-processing interventions maintained their effects on their targeted cognitive abilities at 10 years (reasoning: effect size = 0.23, 99% CI = 0.09-0.38; speed of processing: effect size = 0.66, 99% CI = 0.43-0.88). Memory training effects were no longer maintained for memory performance. Booster training produced additional and durable improvement for the reasoning intervention for reasoning performance (effect size = 0.21, 99% CI = 0.01-0.41) and the speed-of-processing intervention for speed-of-processing performance (effect size = 0.62, 99% CI = 0.31-0.93). CONCLUSION: Each Advanced Cognitive Training for Independent and Vital Elderly cognitive intervention resulted in less decline in self-reported IADL compared with the control group. Reasoning and speed, but not memory, training resulted in improved targeted cognitive abilities for 10 years.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cognition Disorders; Cognitive Therapy; Female; Follow-Up Studies; Humans; Independent Living; Male; Memory Disorders; Mental Processes; Single-Blind Method; United States

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Tracking pathophysiological processes in Alzheimer's disease: an updated hypothetical model of dynamic biomarkers. - Jack, Clifford R; Knopman, David S; Jagust, William J; Petersen, Ronald C; Weiner, Michael W; Aisen, Paul S; Shaw, Leslie M; Vemuri, Prashanthi; Wiste, Heather J; Weigand, Stephen D; Lesnick, Timothy G; Pankratz, Vernon S; et al. (Lancet Neurol, 2013)
In 2010, we put forward a hypothetical model of the major biomarkers of Alzheimer's disease (AD). The model was received with interest because we described the temporal evolution of AD biomarkers in relation to each other and to the onset and progression of clinical symptoms. Since then, evidence has accumulated that supports the major assumptions of this model. Evidence has also appeared that challenges some of our assumptions, which has allowed us to modify our original model. Refinements to our model include indexing of individuals by time rather than clinical symptom severity; incorporation of interindividual variability in cognitive impairment associated with progression of AD pathophysiology; modifications of the specific temporal ordering of some biomarkers; and recognition that the two major proteinopathies underlying AD biomarker changes, amyloid β (Aβ) and tau, might be initiated independently in sporadic AD, in which we hypothesise that an incident Aβ pathophysiology can accelerate antecedent limbic and brainstem tauopathy.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Humans; Models, Biological; Nonlinear Dynamics; tau Proteins

An epigenetic blockade of cognitive functions in the neurodegenerating brain. - Gräff, Johannes; Rei, Damien; Guan, Ji-Song; Wang, Wen-Yuan; Seo, Jinsoo; Hennig, Krista M; Nieland, Thomas J F; Fass, Daniel M; Kao, Patricia F; Kahn, Martin; Su, Susan C; Samiei, Alireza; et al. (Nature, 2012)
Cognitive decline is a debilitating feature of most neurodegenerative diseases of the central nervous system, including Alzheimer's disease. The causes leading to such impairment are only poorly understood and effective treatments are slow to emerge. Here we show that cognitive capacities in the neurodegenerating brain are constrained by an epigenetic blockade of gene transcription that is potentially reversible. This blockade is mediated by histone deacetylase 2, which is increased by Alzheimer's-disease-related neurotoxic insults in vitro, in two mouse models of neurodegeneration and in patients with Alzheimer's disease. Histone deacetylase 2 associates with and reduces the histone acetylation of genes important for learning and memory, which show a concomitant decrease in expression. Importantly, reversing the build-up of histone deacetylase 2 by short-hairpin-RNA-mediated knockdown unlocks the repression of these genes, reinstates structural and synaptic plasticity, and abolishes neurodegeneration-associated memory impairments. These findings advocate for the development of selective inhibitors of histone deacetylase 2 and suggest that cognitive capacities following neurodegeneration are not entirely lost, but merely impaired by this epigenetic blockade.
Keywords: Acetylation; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Epigenesis, Genetic; Gene Expression Regulation; Gene Knockdown Techniques; Hippocampus; Histone Deacetylase 2; Histones; Humans; Hydrogen Peroxide; Memory Disorders; Mice; Neurodegenerative Diseases; Neuronal Plasticity; Peptide Fragments; Phosphorylation; Promoter Regions, Genetic; Receptors, Glucocorticoid; RNA Polymerase II

A mutation in APP protects against Alzheimer's disease and age-related cognitive decline. - Jonsson, Thorlakur; Atwal, Jasvinder K; Steinberg, Stacy; Snaedal, Jon; Jonsson, Palmi V; Bjornsson, Sigurbjorn; Stefansson, Hreinn; Sulem, Patrick; Gudbjartsson, Daniel; Maloney, Janice; Hoyte, Kwame; Gustafson, Amy; et al. (Nature, 2012)
The prevalence of dementia in the Western world in people over the age of 60 has been estimated to be greater than 5%, about two-thirds of which are due to Alzheimer's disease. The age-specific prevalence of Alzheimer's disease nearly doubles every 5 years after age 65, leading to a prevalence of greater than 25% in those over the age of 90 (ref. 3). Here, to search for low-frequency variants in the amyloid-β precursor protein (APP) gene with a significant effect on the risk of Alzheimer's disease, we studied coding variants in APP in a set of whole-genome sequence data from 1,795 Icelanders. We found a coding mutation (A673T) in the APP gene that protects against Alzheimer's disease and cognitive decline in the elderly without Alzheimer's disease. This substitution is adjacent to the aspartyl protease β-site in APP, and results in an approximately 40% reduction in the formation of amyloidogenic peptides in vitro. The strong protective effect of the A673T substitution against Alzheimer's disease provides proof of principle for the hypothesis that reducing the β-cleavage of APP may protect against the disease. Furthermore, as the A673T allele also protects against cognitive decline in the elderly without Alzheimer's disease, the two may be mediated through the same or similar mechanisms.
Keywords: Aging; Alleles; Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Cognition; Cognition Disorders; Genetic Predisposition to Disease; HEK293 Cells; Humans; Mutation; Plaque, Amyloid

An operational approach to National Institute on Aging-Alzheimer's Association criteria for preclinical Alzheimer disease. - Jack, Clifford R; Knopman, David S; Weigand, Stephen D; Wiste, Heather J; Vemuri, Prashanthi; Lowe, Val; Kantarci, Kejal; Gunter, Jeffrey L; Senjem, Matthew L; Ivnik, Robert J; Roberts, Rosebud O; Rocca, Walter A; et al. (Ann Neurol, 2012)
OBJECTIVE: A workgroup commissioned by the Alzheimer's Association (AA) and the National Institute on Aging (NIA) recently published research criteria for preclinical Alzheimer disease (AD). We performed a preliminary assessment of these guidelines. METHODS: We employed Pittsburgh compound B positron emission tomography (PET) imaging as our biomarker of cerebral amyloidosis, and (18) fluorodeoxyglucose PET imaging and hippocampal volume as biomarkers of neurodegeneration. A group of 42 clinically diagnosed AD subjects was used to create imaging biomarker cutpoints. A group of 450 cognitively normal (CN) subjects from a population-based sample was used to develop cognitive cutpoints and to assess population frequencies of the different preclinical AD stages using different cutpoint criteria. RESULTS: The new criteria subdivide the preclinical phase of AD into stages 1 to 3. To classify our CN subjects, 2 additional categories were needed. Stage 0 denotes subjects with normal AD biomarkers and no evidence of subtle cognitive impairment. Suspected non-AD pathophysiology (SNAP) denotes subjects with normal amyloid PET imaging, but abnormal neurodegeneration biomarker studies. At fixed cutpoints corresponding to 90% sensitivity for diagnosing AD and the 10th percentile of CN cognitive scores, 43% of our sample was classified as stage 0, 16% stage 1, 12 % stage 2, 3% stage 3, and 23% SNAP. INTERPRETATION: This cross-sectional evaluation of the NIA-AA criteria for preclinical AD indicates that the 1-3 staging criteria coupled with stage 0 and SNAP categories classify 97% of CN subjects from a population-based sample, leaving only 3% unclassified. Future longitudinal validation of the criteria will be important.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognition Disorders; Disease Progression; Female; Fluorodeoxyglucose F18; Humans; Longitudinal Studies; Male; Mental Status Schedule; National Institute on Aging (U.S.); Neuropsychological Tests; Positron-Emission Tomography; Thiazoles; United States

Reduction of hippocampal hyperactivity improves cognition in amnestic mild cognitive impairment. - Bakker, Arnold; Krauss, Gregory L; Albert, Marilyn S; Speck, Caroline L; Jones, Lauren R; Stark, Craig E; Yassa, Michael A; Bassett, Susan S; Shelton, Amy L; Gallagher, Michela (Neuron, 2012)
Elevated hippocampal activation is observed in conditions that confer risk for Alzheimer's disease, including amnestic mild cognitive impairment (aMCI). Studies in relevant animal models have indicated that overactivity in selective hippocampal circuits contributes to cognitive impairment. Here, we tested the effect of reducing hippocampal activation in aMCI. Under placebo treatment, hippocampal activation in the dentate gyrus/CA3 was elevated in aMCI patients compared to a healthy control group. By using a low dose of the antiepileptic levetiracetam hippocampal activation in aMCI was reduced to a level that did not differ from the control group. Compared to aMCI memory performance under placebo, performance in the scanning task was significantly improved under drug treatment. Contrary to the view that greater hippocampal activation might serve a beneficial function, these results support the view that increased hippocampal activation in aMCI is a dysfunctional condition and that targeting excess hippocampal activity has therapeutic potential.
Keywords: Aged; Aged, 80 and over; Amnesia; Brain Mapping; Case-Control Studies; Choice Behavior; Double-Blind Method; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Mild Cognitive Impairment; Neuropsychological Tests; Nootropic Agents; Oxygen; Photic Stimulation; Piracetam; Statistics as Topic

Caspase signalling controls microglia activation and neurotoxicity. - Burguillos, Miguel A; Deierborg, Tomas; Kavanagh, Edel; Persson, Annette; Hajji, Nabil; Garcia-Quintanilla, Albert; Cano, Josefina; Brundin, Patrik; Englund, Elisabet; Venero, Jose L; Joseph, Bertrand (Nature, 2011)
Activation of microglia and inflammation-mediated neurotoxicity are suggested to play a decisive role in the pathogenesis of several neurodegenerative disorders. Activated microglia release pro-inflammatory factors that may be neurotoxic. Here we show that the orderly activation of caspase-8 and caspase-3/7, known executioners of apoptotic cell death, regulate microglia activation through a protein kinase C (PKC)-δ-dependent pathway. We find that stimulation of microglia with various inflammogens activates caspase-8 and caspase-3/7 in microglia without triggering cell death in vitro and in vivo. Knockdown or chemical inhibition of each of these caspases hindered microglia activation and consequently reduced neurotoxicity. We observe that these caspases are activated in microglia in the ventral mesencephalon of Parkinson's disease (PD) and the frontal cortex of individuals with Alzheimer's disease (AD). Taken together, we show that caspase-8 and caspase-3/7 are involved in regulating microglia activation. We conclude that inhibition of these caspases could be neuroprotective by targeting the microglia rather than the neurons themselves.
Keywords: Alzheimer Disease; Animals; Caspase 3; Caspase 7; Caspase 8; Caspase Inhibitors; Caspases; Cell Death; Cells, Cultured; Dopamine; Enzyme Activation; Frontal Lobe; Gene Knockdown Techniques; Humans; Lipopolysaccharides; Mice; Microglia; Neostriatum; Neurotoxicity Syndromes; Parkinson Disease; Protein Kinase C-delta; Rats; Signal Transduction; Substantia Nigra; Toll-Like Receptor 4

The diagnosis of dementia due to Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - McKhann, Guy M; Knopman, David S; Chertkow, Howard; Hyman, Bradley T; Jack, Clifford R; Kawas, Claudia H; Klunk, William E; Koroshetz, Walter J; Manly, Jennifer J; Mayeux, Richard; Mohs, Richard C; Morris, John C; et al. (Alzheimers Dement, 2011)
The National Institute on Aging and the Alzheimer's Association charged a workgroup with the task of revising the 1984 criteria for Alzheimer's disease (AD) dementia. The workgroup sought to ensure that the revised criteria would be flexible enough to be used by both general healthcare providers without access to neuropsychological testing, advanced imaging, and cerebrospinal fluid measures, and specialized investigators involved in research or in clinical trial studies who would have these tools available. We present criteria for all-cause dementia and for AD dementia. We retained the general framework of probable AD dementia from the 1984 criteria. On the basis of the past 27 years of experience, we made several changes in the clinical criteria for the diagnosis. We also retained the term possible AD dementia, but redefined it in a manner more focused than before. Biomarker evidence was also integrated into the diagnostic formulations for probable and possible AD dementia for use in research settings. The core clinical criteria for AD dementia will continue to be the cornerstone of the diagnosis in clinical practice, but biomarker evidence is expected to enhance the pathophysiological specificity of the diagnosis of AD dementia. Much work lies ahead for validating the biomarker diagnosis of AD dementia.
Keywords: Alzheimer Disease; Biomarkers; Diagnosis, Differential; Diagnostic Imaging; Disease Progression; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

The diagnosis of mild cognitive impairment due to Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Albert, Marilyn S; DeKosky, Steven T; Dickson, Dennis; Dubois, Bruno; Feldman, Howard H; Fox, Nick C; Gamst, Anthony; Holtzman, David M; Jagust, William J; Petersen, Ronald C; Snyder, Peter J; Carrillo, Maria C; et al. (Alzheimers Dement, 2011)
The National Institute on Aging and the Alzheimer's Association charged a workgroup with the task of developing criteria for the symptomatic predementia phase of Alzheimer's disease (AD), referred to in this article as mild cognitive impairment due to AD. The workgroup developed the following two sets of criteria: (1) core clinical criteria that could be used by healthcare providers without access to advanced imaging techniques or cerebrospinal fluid analysis, and (2) research criteria that could be used in clinical research settings, including clinical trials. The second set of criteria incorporate the use of biomarkers based on imaging and cerebrospinal fluid measures. The final set of criteria for mild cognitive impairment due to AD has four levels of certainty, depending on the presence and nature of the biomarker findings. Considerable work is needed to validate the criteria that use biomarkers and to standardize biomarker analysis for use in community settings.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Diagnosis, Differential; Diagnostic Imaging; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Evidence for ordering of Alzheimer disease biomarkers. - Jack, Clifford R; Vemuri, Prashanthi; Wiste, Heather J; Weigand, Stephen D; Aisen, Paul S; Trojanowski, John Q; Shaw, Leslie M; Bernstein, Matthew A; Petersen, Ronald C; Weiner, Michael W; Knopman, David S (Arch Neurol, 2011)
OBJECTIVE: To empirically assess the concept that Alzheimer disease (AD) biomarkers significantly depart from normality in a temporally ordered manner. DESIGN: Validation sample. SETTING: Multisite, referral centers. PARTICIPANTS: A total of 401 elderly participants in the Alzheimer's Disease Neuroimaging Initiative who were cognitively normal, who had mild cognitive impairment, or who had AD dementia. We compared the proportions of 3 AD biomarker values (the Aβ42 level in cerebrospinal fluid [CSF], the total tau level in CSF, and the hippocampal volume adjusted for intracranial volume [hereafter referred to as the adjusted hippocampal volume]) that were abnormal as cognitive impairment worsened. Cut points demarcating normal vs abnormal for each biomarker were established by maximizing diagnostic accuracy in independent autopsy samples. MAIN OUTCOME MEASURES: Three AD biomarkers (ie, the CSF Aβ42 level, the CSF total tau level, and the adjusted hippocampal volume). RESULTS: Within each clinical group of the entire sample (n = 401), the CSF Aβ42 level was abnormal more often than was the CSF total tau level or the adjusted hippocampal volume. Among the 298 participants with both baseline and 12-month data, the proportion of participants with an abnormal Aβ42 level did not change from baseline to 12 months in any group. The proportion of participants with an abnormal total tau level increased from baseline to 12 months in cognitively normal participants (P = .05) but not in participants with mild cognitive impairment or AD dementia. For 209 participants with an abnormal CSF Aβ42 level at baseline, the percentage with an abnormal adjusted hippocampal volume but normal CSF total tau level increased from baseline to 12 months in participants with mild cognitive impairment. No change in the percentage of MCI participants with an abnormal total tau level was seen between baseline and 12 months. CONCLUSIONS: A reduction in the CSF Aβ42 level denotes a pathophysiological process that significantly departs from normality (ie, becomes dynamic) early, whereas the CSF total tau level and the adjusted hippocampal volume are biomarkers of downstream pathophysiological processes. The CSF total tau level becomes dynamic before the adjusted hippocampal volume, but the hippocampal volume is more dynamic in the clinically symptomatic mild cognitive impairment and AD dementia phases of the disease than is the CSF total tau level.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Hippocampus; Humans; Longitudinal Studies; Male; Mild Cognitive Impairment; tau Proteins

Human apoE isoforms differentially regulate brain amyloid-β peptide clearance. - Castellano, Joseph M; Kim, Jungsu; Stewart, Floy R; Jiang, Hong; DeMattos, Ronald B; Patterson, Bruce W; Fagan, Anne M; Morris, John C; Mawuenyega, Kwasi G; Cruchaga, Carlos; Goate, Alison M; Bales, Kelly R; et al. (Sci Transl Med, 2011)
The apolipoprotein E (APOE) ε4 allele is the strongest genetic risk factor for late-onset, sporadic Alzheimer's disease (AD). The APOE ε4 allele markedly increases AD risk and decreases age of onset, likely through its strong effect on the accumulation of amyloid-β (Aβ) peptide. In contrast, the APOE ε2 allele appears to decrease AD risk. Most rare, early-onset forms of familial AD are caused by autosomal dominant mutations that often lead to overproduction of Aβ(42) peptide. However, the mechanism by which APOE alleles differentially modulate Aβ accumulation in sporadic, late-onset AD is less clear. In a cohort of cognitively normal individuals, we report that reliable molecular and neuroimaging biomarkers of cerebral Aβ deposition vary in an apoE isoform-dependent manner. We hypothesized that human apoE isoforms differentially affect Aβ clearance or synthesis in vivo, resulting in an apoE isoform-dependent pattern of Aβ accumulation later in life. Performing in vivo microdialysis in a mouse model of Aβ-amyloidosis expressing human apoE isoforms (PDAPP/TRE), we find that the concentration and clearance of soluble Aβ in the brain interstitial fluid depends on the isoform of apoE expressed. This pattern parallels the extent of Aβ deposition observed in aged PDAPP/TRE mice. ApoE isoform-dependent differences in soluble Aβ metabolism are observed not only in aged but also in young PDAPP/TRE mice well before the onset of Aβ deposition in amyloid plaques in the brain. Additionally, amyloidogenic processing of amyloid precursor protein and Aβ synthesis, as assessed by in vivo stable isotopic labeling kinetics, do not vary according to apoE isoform in young PDAPP/TRE mice. Our results suggest that APOE alleles contribute to AD risk by differentially regulating clearance of Aβ from the brain, suggesting that Aβ clearance pathways may be useful therapeutic targets for AD prevention.
Keywords: Adult; Aged; Alleles; Alzheimer Disease; Amyloid beta-Peptides; Animals; Apolipoprotein E4; Biomarkers; Brain; Female; Genotype; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microdialysis; Middle Aged; Protein Isoforms

Neuronal basis of age-related working memory decline. - Wang, Min; Gamo, Nao J; Yang, Yang; Jin, Lu E; Wang, Xiao-Jing; Laubach, Mark; Mazer, James A; Lee, Daeyeol; Arnsten, Amy F T (Nature, 2011)
Many of the cognitive deficits of normal ageing (forgetfulness, distractibility, inflexibility and impaired executive functions) involve prefrontal cortex (PFC) dysfunction. The PFC guides behaviour and thought using working memory, which are essential functions in the information age. Many PFC neurons hold information in working memory through excitatory networks that can maintain persistent neuronal firing in the absence of external stimulation. This fragile process is highly dependent on the neurochemical environment. For example, elevated cyclic-AMP signalling reduces persistent firing by opening HCN and KCNQ potassium channels. It is not known if molecular changes associated with normal ageing alter the physiological properties of PFC neurons during working memory, as there have been no in vivo recordings, to our knowledge, from PFC neurons of aged monkeys. Here we characterize the first recordings of this kind, revealing a marked loss of PFC persistent firing with advancing age that can be rescued by restoring an optimal neurochemical environment. Recordings showed an age-related decline in the firing rate of DELAY neurons, whereas the firing of CUE neurons remained unchanged with age. The memory-related firing of aged DELAY neurons was partially restored to more youthful levels by inhibiting cAMP signalling, or by blocking HCN or KCNQ channels. These findings reveal the cellular basis of age-related cognitive decline in dorsolateral PFC, and demonstrate that physiological integrity can be rescued by addressing the molecular needs of PFC circuits.
Keywords: Action Potentials; Adrenergic alpha-2 Receptor Agonists; Aging; Animals; Biomedical Enhancement; Cues; Cyclic AMP; Cyclic Nucleotide-Gated Cation Channels; Guanfacine; Humans; Hyperpolarization-Activated Cyclic Nucleotide-Gated Channels; KCNQ Potassium Channels; Macaca mulatta; Male; Memory, Short-Term; Models, Neurological; Neural Pathways; Potassium Channel Blockers; Potassium Channels; Prefrontal Cortex; Receptors, Adrenergic, alpha-2; Signal Transduction; Time Factors

Pathogenic protein seeding in Alzheimer disease and other neurodegenerative disorders. - Jucker, Mathias; Walker, Lary C (Ann Neurol, 2011)
The misfolding and aggregation of specific proteins is a seminal occurrence in a remarkable variety of neurodegenerative disorders. In Alzheimer disease (the most prevalent cerebral proteopathy), the two principal aggregating proteins are β-amyloid (Aβ) and tau. The abnormal assemblies formed by conformational variants of these proteins range in size from small oligomers to the characteristic lesions that are visible by optical microscopy, such as senile plaques and neurofibrillary tangles. Pathologic similarities with prion disease suggest that the formation and spread of these proteinaceous lesions might involve a common molecular mechanism-corruptive protein templating. Experimentally, cerebral β-amyloidosis can be exogenously induced by exposure to dilute brain extracts containing aggregated Aβ seeds. The amyloid-inducing agent probably is Aβ itself, in a conformation generated most effectively in the living brain. Once initiated, Aβ lesions proliferate within and among brain regions. The induction process is governed by the structural and biochemical nature of the Aβ seed, as well as the attributes of the host, reminiscent of pathogenically variant prion strains. The concept of prionlike induction and spreading of pathogenic proteins recently has been expanded to include aggregates of tau, α-synuclein, huntingtin, superoxide dismutase-1, and TDP-43, which characterize such human neurodegenerative disorders as frontotemporal lobar degeneration, Parkinson/Lewy body disease, Huntington disease, and amyotrophic lateral sclerosis. Our recent finding that the most effective Aβ seeds are small and soluble intensifies the search in bodily fluids for misfolded protein seeds that are upstream in the proteopathic cascade, and thus could serve as predictive diagnostics and the targets of early, mechanism-based interventions. Establishing the clinical implications of corruptive protein templating will require further mechanistic and epidemiologic investigations. However, the theory that many chronic neurodegenerative diseases can originate and progress via the seeded corruption of misfolded proteins has the potential to unify experimental and translational approaches to these increasingly prevalent disorders.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; DNA-Binding Proteins; Humans; Neurodegenerative Diseases; Prions; Proteins; tau Proteins

Soluble amyloid beta-protein dimers isolated from Alzheimer cortex directly induce Tau hyperphosphorylation and neuritic degeneration. - Jin, Ming; Shepardson, Nina; Yang, Ting; Chen, Gang; Walsh, Dominic; Selkoe, Dennis J (Proc Natl Acad Sci U S A, 2011)
Alzheimer disease is a major cause of cognitive failure, and a pathogenically related but more subtle process accounts for many cases of mild memory symptoms in older humans. Insoluble fibrillar plaques of amyloid β-proteins (Aβ) and neurofibrillary deposits of hyperphosphorylated tau proteins are the diagnostic lesions of AD, but their temporal mechanistic relationship has long been debated. The recent recognition that small, diffusible oligomers may be the principal bioactive form of Aβ raises the key question of whether these are sufficient to initiate cytoskeletal change and neurite degeneration. A few studies have examined the effects of oligomers of synthetic Aβ peptides of one defined length at supraphysiological concentrations, but the existence of such assemblies in the AD brain is not established. Here, we isolated Aβ dimers, the most abundant form of soluble oligomer detectable in the human brain, from the cortices of typical AD subjects and found that at subnanomolar concentrations, they first induced hyperphosphorylation of tau at AD-relevant epitopes in hippocampal neurons and then disrupted the microtubule cytoskeleton and caused neuritic degeneration, all in the absence of amyloid fibrils. Application of pure, synthetic dimers confirmed the effects of the natural AD dimers, although the former were far less potent. Knocking down endogenous tau fully prevented the neuritic changes, whereas overexpressing human tau accelerated them. Coadministering Aβ N-terminal antibodies neutralized the cytoskeletal disruption. We conclude that natural dimers isolated from the AD brain are sufficient to potently induce AD-type tau phosphorylation and then neuritic dystrophy, but passive immunotherapy mitigates this.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Blotting, Western; Chromatography, Gel; Dimerization; Genetic Vectors; Hippocampus; Humans; Immunohistochemistry; Immunoprecipitation; In Situ Nick-End Labeling; Lentivirus; Microscopy, Confocal; Microtubules; Neurites; Phosphorylation; Rats; Rats, Sprague-Dawley; tau Proteins

Toward defining the preclinical stages of Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Sperling, Reisa A; Aisen, Paul S; Beckett, Laurel A; Bennett, David A; Craft, Suzanne; Fagan, Anne M; Iwatsubo, Takeshi; Jack, Clifford R; Kaye, Jeffrey; Montine, Thomas J; Park, Denise C; Reiman, Eric M; et al. (Alzheimers Dement, 2011)
The pathophysiological process of Alzheimer's disease (AD) is thought to begin many years before the diagnosis of AD dementia. This long "preclinical" phase of AD would provide a critical opportunity for therapeutic intervention; however, we need to further elucidate the link between the pathological cascade of AD and the emergence of clinical symptoms. The National Institute on Aging and the Alzheimer's Association convened an international workgroup to review the biomarker, epidemiological, and neuropsychological evidence, and to develop recommendations to determine the factors which best predict the risk of progression from "normal" cognition to mild cognitive impairment and AD dementia. We propose a conceptual framework and operational research criteria, based on the prevailing scientific evidence to date, to test and refine these models with longitudinal clinical research studies. These recommendations are solely intended for research purposes and do not have any clinical implications at this time. It is hoped that these recommendations will provide a common rubric to advance the study of preclinical AD, and ultimately, aid the field in moving toward earlier intervention at a stage of AD when some disease-modifying therapies may be most efficacious.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; United States

Alzheimer's Disease Neuroimaging Initiative (ADNI): clinical characterization. - Petersen, R C; Aisen, P S; Beckett, L A; Donohue, M C; Gamst, A C; Harvey, D J; Jack, C R; Jagust, W J; Shaw, L M; Toga, A W; Trojanowski, J Q; Weiner, M W (Neurology, 2010)
BACKGROUND: Neuroimaging measures and chemical biomarkers may be important indices of clinical progression in normal aging and mild cognitive impairment (MCI) and need to be evaluated longitudinally. OBJECTIVE: To characterize cross-sectionally and longitudinally clinical measures in normal controls, subjects with MCI, and subjects with mild Alzheimer disease (AD) to enable the assessment of the utility of neuroimaging and chemical biomarker measures. METHODS: A total of 819 subjects (229 cognitively normal, 398 with MCI, and 192 with AD) were enrolled at baseline and followed for 12 months using standard cognitive and functional measures typical of clinical trials. RESULTS: The subjects with MCI were more memory impaired than the cognitively normal subjects but not as impaired as the subjects with AD. Nonmemory cognitive measures were only minimally impaired in the subjects with MCI. The subjects with MCI progressed to dementia in 12 months at a rate of 16.5% per year. Approximately 50% of the subjects with MCI were on antidementia therapies. There was minimal movement on the Alzheimer's Disease Assessment Scale-Cognitive Subscale for the normal control subjects, slight movement for the subjects with MCI of 1.1, and a modest change for the subjects with AD of 4.3. Baseline CSF measures of Abeta-42 separated the 3 groups as expected and successfully predicted the 12-month change in cognitive measures. CONCLUSION: The Alzheimer's Disease Neuroimaging Initiative has successfully recruited cohorts of cognitively normal subjects, subjects with mild cognitive impairment (MCI), and subjects with Alzheimer disease with anticipated baseline characteristics. The 12-month progression rate of MCI was as predicted, and the CSF measures heralded progression of clinical measures over 12 months.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cross-Sectional Studies; Diagnostic Imaging; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged

Genetic evidence implicates the immune system and cholesterol metabolism in the aetiology of Alzheimer's disease. - Jones, Lesley; Holmans, Peter A; Hamshere, Marian L; Harold, Denise; Moskvina, Valentina; Ivanov, Dobril; Pocklington, Andrew; Abraham, Richard; Hollingworth, Paul; Sims, Rebecca; Gerrish, Amy; Pahwa, Jaspreet Singh; et al. (PLoS One, 2010)
BACKGROUND: Late Onset Alzheimer's disease (LOAD) is the leading cause of dementia. Recent large genome-wide association studies (GWAS) identified the first strongly supported LOAD susceptibility genes since the discovery of the involvement of APOE in the early 1990s. We have now exploited these GWAS datasets to uncover key LOAD pathophysiological processes. METHODOLOGY: We applied a recently developed tool for mining GWAS data for biologically meaningful information to a LOAD GWAS dataset. The principal findings were then tested in an independent GWAS dataset. PRINCIPAL FINDINGS: We found a significant overrepresentation of association signals in pathways related to cholesterol metabolism and the immune response in both of the two largest genome-wide association studies for LOAD. SIGNIFICANCE: Processes related to cholesterol metabolism and the innate immune response have previously been implicated by pathological and epidemiological studies of Alzheimer's disease, but it has been unclear whether those findings reflected primary aetiological events or consequences of the disease process. Our independent evidence from two large studies now demonstrates that these processes are aetiologically relevant, and suggests that they may be suitable targets for novel and existing therapeutic approaches.
Keywords: Alzheimer Disease; Apolipoproteins E; Cholesterol; Chromosome Mapping; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Immune System; Polymorphism, Single Nucleotide